(E)-1-(2-Hydroxy-3,4-dimethoxyphenyl)-3-(4-hydroxyphenyl)-prop-2-en-1-on e - Krishna, J. R.; Kumar, N. J.; Krishnaiah, M.; Rao, C. V.; Rao, Y. K.; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2005)
The title compound, C17H16O5, crystallizes with two independent molecules in the asymmetric unit. These are oriented approximately orthogonal to one another. The keto group adopts an s-cis conformation; the six-membered ring formed by the O-H&BULL;&BULL;&BULL; O hydrogen bond and the adjacent benzene ring are approximately coplanar. In addition to an intramolecular O-H&BULL;&BULL;&BULL; O hydrogen bond, intermolecular O-H&BULL;&BULL;&BULL; O interactions link adjacent molecules into chains.

Effect of 2-(2-pyridyl)azole-based ancillary ligands (L1-4) on the electrophilicity of the nitrosyl function in [Ru-II(trpy)(L1-4)(NO)](3+) [trpy=2,2 `: 6 `,2 `'-terpyridine]. synthesis, structures, and spectroscopic, electrochemical, and kinetic aspects - Chanda, N.; Paul, D.; Kar, S.; Mobin, Shaikh M.; Datta, Anindya; Puranik, Vedavati G.; Rao, K. K.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2005)
Ruthenium nitrosyl complexes [Ru(trpy)(L1-4)(NO)](3+) (13-16) [trpy = 2,2':6',2"-terpyridine, L-1 = 2-(2-pyridyl)-benzoxazole, L-2 = 2-(2-pyridyl)benzthiazole, L-3 = 2-(2-pyridyl)benzimidazole, L-4 = 1-methyl-2-(2-pyridyl)-1H-benzimidazole] were obtained in a stepwise manner starting from [Ru-II(trpy)(L1-4) (Cl)]ClO4 (1-4) &RARR; [Ru-II(trpy)(L1-4) (H2O)](ClO4)(2) (5-8) &RARR; [Ru-II(trpy)(L1-4) (NO2)ClO4 (9-12) &RARR; [Ru-II(trpy)(L-1,L-2,L-4) (NO)](ClO4)(3) (13, 14, 16)/[Ru-II(trpy)(L-3) (NO)](Cl)(4))(2)(NO3) (15). Crystal structures of 1, 2, 4, 9, 12, 13, 15, and 16 established the stereoretentive nature of the transformation processes. Though the complexes of L1, L3, and L 4 were isolated in the isomeric form A (π-acceptor trpy and azole ring in the equatorial plane and the pyridine and chloride donors in the axial positions), complexes of L 2 preferentially stabilized in form B (trpy and pyridine in the equatorial plane and the azole ring and chloride donors in the axial positions). The v(NO) stretching frequency varied in the range of 1957-1932 cm(-1), 13 &MGT; 14 &MGT; 15 > 16, primarily depending on the electronic aspects of L as well as the isomeric structural forms. The coordinated nitrosyl function underwent successive reductions of [Ru-II-NO+](3+) &RARR; [Ru-II-NO&BULL;](2+) and [Ru-II-NO&BULL;](2+) - [Ru-II-NO-](+), and the first reduction potential follows the order 14 > 13 &MGT; 15 &AP; 16. The nearly axial EPR spectra having nitrogen hyperfine splittings (A &AP; 26 G) at 77 K of 13(-)-16(-) with (g) &AP; 2.0 established that the reduction process is largely centered around the nitrosyl function. Despite an appreciably high v(NO), the complexes were found to be unusually stable even in the aqueous medium. They transformed slowly and only partially into the corresponding nitro derivatives in H2O (k &AP; 10(-4) s(-1) and K = 0.4-3.8). The chloro (1-4), aqua (5-8), and nitro (9-12) derivatives displayed reasonably strong emissions near 700 nm at 77 K (φ = 10(-1)-10(-2)). The aqua derivative 7 was found to interact with the calf thymus and the circular form of p-Bluescript SK DNA.

Effect of connectivity and terminal functionality on mesophase behaviour of thermotropic liquid crystals containing biphenyl units - Ranganathan, T.; Ramesh, C.; Kumar, Anil (Liquid Crystals, 2005)
A series of 4,4'-disubstituted biphenyls, designated as series HBC, in which, one substituent is an ester group linked directly to the ring and the other is the hydroxy-containing group O(CH2)(n)OH, have been prepared and analysed by differential scanning Calorimetry, polarizing optical microscopy and X-ray diffraction. The introduction of a trimethylene unit between the ester functional group and the biphenyl moiety of the HBC series gives rise to the HBB series, which did not exhibit liquid crystalline behaviour. Interestingly, mesophase behaviour could be restored by replacing the methylene group ( of the trimethylene unit) that was directly attached to the biphenyl ring by a keto group (HBOB series). When the terminal hydroxy group of these three series was substituted by a group such as acetoxy or hydrogen, the transition temperatures were reduced, and the disappearance of mesophase behaviour was observed in some cases. However, this could be recovered by the replacement of the ester group by a carboxylic acid group.

Effect of disorder on the magnetic properties of LaMn0.5Fe0.5O3 - Bhame, Shekhar D.; Joly, V. L. Joseph; Joy, Pattayil Alias (Physical Review B, 2005)
Polycrystalline LaMn0.5Fe0.5O3 is synthesized by a low-temperature method and the magnetic properties of the resulting powder have been studied after annealing the sample in air at different temperatures in the range 200 degrees C-1350 degrees C. Room temperature Mossbauer spectroscopic studies show that the Fe ions are present in the +3 oxidation state in the material. However, the magnetic properties vary widely in an unexpected manner when samples are annealed at different temperatures. Zero field cooled magnetization studies show a cusp below 100 K, for the sample annealed at 200 degrees C, indicating a spin-glass-like or superparamagnetic behavior. However, this cusp disappears completely when the sample is annealed at 700 degrees C but still showing a magnetic hysteresis loop with reduced magnetization at low temperatures. The cusp again appears when the sample is annealed at higher temperatures with increasing low-temperature magnetization. EPR and IR spectroscopic studies indicate changes in the distribution of Mn3+ and Fe3+ ions in the lattice. The overall results can be explained in terms of random distribution of Mn3+ and Fe3+ ions in the lattice and formation of some magnetic clusters, with the degree of distribution of the ions varying for samples annealed at different temperatures.

Effect of NaBr, KCl, KBr, and MgCl2 on viscosities of aqueous glycine and L-alanine solutions at 298.15 K - Badarayani, Rohini; Satpute, D. B.; Kumar, Anil (Journal of Chemical and Engineering Data, 2005)
Viscosities, η, of glycine and L-alanine are measured in aqueous solutions of NaBr, KCl, KBr, and MgCl2 up to high concentrations at 298.15 K. This study suggests that 1:1 electrolytes enhance the structure making ability of the amino acids whereas MgCl2 does not. The viscosities of the above solutions are correlated using a simple model with two interaction parameters.

Effect of RuO2 in the shape selectivity of submicron-sized SnO2 structures - Ramgir, N. S.; Mulla, Imtiaz S.; Vijayamohanan, K. P. (Journal of Physical Chemistry B, 2005)
Several dissimilar types of tin oxide microstructures including bipyramids, cubes, and wires synthesized effectively by means of a simple approach were investigated using X-ray diffraction (XRD), thermogravimetry/ differential thermometric analysis (TG-DTA), and X-ray photoelectron spectroscopy (XPS). A possible growth mechanism is proposed using the results of these studies. The texture coefficient values of all the structures, indexed to a tetragonal lattice, exhibit amazing variation in the preferred orientation with respect to their shapes. Although XPS data indicate that wires and cubes have a strong SnO2 type signal, bipyramids interestingly exhibit both SnO and SnO2 signals and a correlation of the binding energy helps in understanding the growth kinetics of such submicron structures. The. results suggest that the bipyramids are formed because of the vapor-solid process (VS) while wires and cubes are formed by the vapor-liquid-solid (VLS) progression.

Effects of conjugation length and donor-acceptor functionalization on the non-linear optical properties of organic push-pull molecules using density functional theory - Datta, Anindya; Pal, S. (Journal of Molecular Structure-Theochem, 2005)
We consider a series of dipolar organic molecules where the donor groups and the acceptor groups are separated by pi-conjugation like phenyl ring or alkene chains. We have performed extensive quantum chemical calculations based on density functional theory (DFT) to calculate their linear and non-linear optical coefficients. We show that though DFT is known to overestimate the polarizabilities of quasilinear systems,the results with proper inclusion of exchange correlation compare well with the experimental studies. On increasing the pi-conjugation length, the coefficients increase non-linearly. We also vary the donor and the acceptor groups and study the role of chemical modifications on the response properties. Herein we suggest experimental methods by which the molecules may be arranged in non-centrosymmetric fashion in the bulk for device integration. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: DFr; donor-acceptor functionalization; non-linear properties; push-pull molecules

Efficient and improved method for the Biginelli reaction using solid superacid (sulphated SnO2) - Bhosale, R. S.; Hashmi, A. M.; Zubaidha, P. K.; Dongare, Mohan K. (Heterocyclic Communications, 2005)
One-pot synthesis of 3,4-dihydropyrimidin-2(1H)-one (DHPM) has been effected efficiently by coupling of the three components, aldehyde, ethyl acetoacetate and urea/thiourea in the presence of solid Superacid (sulphated SnO2). The method presented herein is attractive with respect to yield, reaction time, workup procedure and reusable catalyst.
Keywords: Biginelli; DHPM; sulphated SnO2

Efficient and selective cleavage of the tert-butoxycarbonyl (Boc) group under basic condition - Mohapatra, Debendra K.; Durugkar, Kulbhushan A. (Arkivoc, 2005)
A simple, efficient and mild method for the selective cleavage of tert-butoxycarbonyl (Boc) from dicarbamates and a carbonyl or aromatic ring in conjugation with the nitrogen atom bearing the Boc-group is described under basic condition.
Keywords: alpha-amino acids; celogenitins; di-t-butylimidodicarbonate; racemization; Selective deprotection

Efficient method for the synthesis of methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate - Salunke, D. B.; Hazra, Braja G.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Pore, V. S. (Tetrahedron, 2005)
The synthesis of methyl 11 alpha-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate, methyl 11 beta-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate and methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate have been achieved. Mechanistic aspects for the decomposition of steroidal azidoketones to its enamines are discussed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 11-aminosteroid; 11-azidosteroid; base catalyzed epimerization; HIV-1 protease inhibitors; steroidal enamines

Efficient stereoselective synthesis of (2S,4S,5R)-(-)- and (2R,4R,5S)-(+)-bulgecinine - Chavan, Subhash P.; Praveen, C.; Sharma, P.; Kalkote, Uttam R. (Tetrahedron Letters, 2005)
A short synthetic route to (-)-and (+)-bulgecinine, the amino acid moiety of the bulgecins was achieved from the readily available nonchiral pool starting material cis-2-butene-1,4-diol in which a Claisen orthoester rearrangement and a Sharpless asymmetric dihydroxylation were used as the key steps. (C) 2004 Elsevier Ltd. All rights reserved.

Efficient synthesis of 2,3-aziridino-gamma-lactones from azetidin-2-ones - Kale, Ajaykumar S.; Deshmukh, A. R. A. S. (Synlett, 2005)
An efficient synthesis of enantiopure 2,3-aziridino-gamma-lactones from azetidin-2-ones is described. Acid-catalyzed tandem intramolecular azetidinone ring opening followed by aziridine ring formation via elimination of a mesylate group is the key step in this synthesis. 2,3-Aziridino-gamma-lactones are important precursors for biologically important glutamic acid derivatives.
Keywords: azetidin-2-ones; aziridines; glutamic acid; lactones

Efficient total synthesis of iso-cladospolide B and cladospolide B - Pandey, SK; Kumar, P (Tetrahedron Letters, 2005)
An efficient synthesis of iso-cladospolide B and cladospolide B has been achieved using Jacobsen's hydrolytic kinetic resolution (HKR), Sharpless asymmetric dihydroxylation and Yamaguchi macrolactonization as the key steps. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cladospolide B; Hydrolytic kinetic resolution; iso-cladospolide B; sharpless asymmetric dihydroxylation; Yamaguchi macrolactonization

Efficient total synthesis of sapinofuranone B - Kumar, P; Naidu, SV; Gupta, P (Journal of Organic Chemistry, 2005)
An efficient enantioselective synthesis of sapinofuranone B (1) using Sharpless asymmetric dihydroxylation, Sonogashira coupling, and Wittig olefination as the key steps is described.

Electrochemical studies of poly (3,4-ethylenedioxythiophene) PEDOT/VS2 nanocomposite as a cathode material for rechargeable lithium batteries - Murugan, A. Vadivel; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Electrochemistry Communications, 2005)
Here, we demonstrate the electrochemical characterization of a new type of layered poly (3,4-ethylenedioxythiophene) PEDOT/ VS2 nanocomposite. It has been prepared via flocculation of delaminated VS2 with subsequent in situ oxidative polymerization of 3,4-ethylenedioxythiophene (EDOT) with VS2 as a host material in the presence of an external oxidizing agent. The interlayer spacing Of VS2 expands from 5.71 to 14.01 A and this interlayer separation is consistent with the existence of a monolayer of PEDOT in the VS2 framework. X-ray diffraction, XPS and TEM studies have been;shown the change in interlayer separation is consistent with the existence of two phases of organic and inorganic species in the nanocomposites corresponding to the intercalation of PEDOT in the VS2 framework. The application potential of the nanocomposite as a cathode material for rechargeable lithium batteries is also demonstrated by the electrochemical intercalation of lithium into the PEDOT/VS2 nanocomposite, where a significant enhancement in the discharge capacity is observed (similar to130 mAh/g) compared to that (80 mAh/g) for pristine VS2. (C) 2004 Published by Elsevier B.V.
Keywords: layered nanocomposite; lithium batteries; polythiophene; vanadium disulfide

Electrochemical synthesis and corrosion protection properties of poly(o-toluidine) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2005)
Uniform and strongly adherent poly(o-toluidine) (POT) coatings have been synthesized on low carbon steel (LCS) substrates by electrochemical polymerization (ECP) of o-toluidine under cyclic voltammetric conditions from an aqueous sodium tartrate solution. Cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) measurements, and scanning electron microscopy (SEM) were used to characterize these coatings, which indicates that the sodium tartrate is a suitable medium for the ECP of o-toluidine and it occurs without noticeable dissolution of LCS. Corrosion protection properties of the POT coatings were evaluated in aqueous 3% NaCl by the potentiodynamic polarization measurements and CV. The result of the potentiodynamic polarization demonstrates that the POT coating has ability to protect the LCS against corrosion. The corrosion potential was about 334 mV more positive in aqueous 3% NaCl for the POT-coated LCS than that of bare LCS and reduces the corrosion rate of LCS almost by a factor of 50. (c) 2005 Wiley Periodicals, Inc.
Keywords: conducting polymers; Corrosion resistant coatings; cyclic voltarnmetry; Electrochemical polymerization; FT-IR; Poly(o-toluidine); UV-vis spectroscopy

Electronic spectra and ionization potentials of halogen oxides using the fock space coupled-cluster method - Vaval, N; Manohar, Prashant Uday; Pal, S (Collection of Czechoslovac Chemical Communications, 2005)
The ionization potentials and excitation energies of halogen monoxides and dihalogen oxides are studied using fully size-extensive Fock space version of multi-reference coupled-cluster theory. The low-lying excited states of ClO-, FO-, Cl2O and F2O are obtained along with the ionization spectra of Cl2O and F2O. The adiabatic electron affinity of ClO, FO and the vertical detachment energy of ClO- and FO- are also presented.

Electronic structure and ferromagnetism of polycrystalline Zn1-xCoxO (0 <= x <= 0.15) - Deka, Sasanka; Joy, Pattayil Alias (Solid State Communications, 2005)
The electronic structure of polycrystalline ferromagnetic Zn1-x,CoxO (0.05 <= x <= 0.15) and the oxidation state of Co in it, have been investigated. The Co-doped polycrystalline samples are synthesized by a combustion method and are ferromagnetic at room temperature. XPS and optical absorption studies show evidence for Co2+ ions in the tetrahedral symmetry, indicating, substitution of Co2+ in the ZnO lattice. However, powder XRD and electron diffraction data shock the presence of Co metal in the samples. This give evidence to the fact that some Co2+ ion are incorporated in the ZnO lattice which gives changes in the electronic structure whereas ferromagnetism comes from the Co metal impurities present in the samples. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Magnetically ordered materials; Optical properties; Semiconductors

Enantioselective synthesis of 1-azaspiro[5.5]undecane ring system of histrionicotoxin alkaloids from D(+)-glucose - Bera, Smritilekha (Heterocycles, 2005)
Histrionicotoxins, the archetype of a group of spiropiperidine containing alkaloids from the brightly colored poison arrow frog Dendrobates histronicus native to the Amazon rain forests of Southern Columbia, was first isolated by Daly, Witkop and co-workers in 1971.1 They all share a common Iazaspiro[5.5]undecan-8-ol ring system with unsaturated C4 or C5 side chains at both the 2 and 7 positions. The nature and length of the side chains distinguish the different members of the histrionicotoxin family.
Keywords: chiron approach; domino reaction; Ring closing metathesis

Enantioselective synthesis of (S)-alpha-arylpropionic acids via pd-catalyzed kinetic resolution of benzylic alcohols - Thakur, V. V.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
A convenient synthetic route for the synthesis of three (S)-alpha-propionic acids, (S)-naproxen (90% ee), (S)-ibuprofen (82% ee) and (S)-phenylpropioilic acid (92% ee) is described. Pd-catalyzed oxidative kinetic resolution of the corresponding benzylic alcohols is used as a key step to introduce stereogenicity into the molecule.

Enantioselective synthesis of tarchonanthuslactone via iterative hydrolytic kinetic resolution - Gupta, P; Naidu, SV; Kumar, P (Tetrahedron Letters, 2005)
A short and practical enantioselective synthesis of tarchonanthuslactone has been achieved in high diastereomeric excess using iterative Jacobsen's hydrolytic kinetic resolution and ring closing metathesis as the key steps. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Jacobsen's hydrolytic kinetic resolution; Ring closing metathesis; tarchonanthuslactone

Encoding and decoding graphical chemical structures as two-dimensional (PDF417) barcodes - Karthikeyan, Muthukumarasamy; Bender, Andreas (Journal of Chemical Information and Modeling, 2005)
A wide range of molecular representations exist today, ranging from human-readable structural diagrams over line notations such as Wiswesser Line Notation (WLN) and SMILES to several dozen computer-readable file formats. Still, to encode molecular structures in a computer-readable way for inputting structures in computer systems those formats are not the method of choice since they are not easily and faultlessly readable via optical recognition. In the present study a two-dimensional (PDF417) barcode representation of molecular structures in SMILES format is explored that enables the user to read and input molecular structures into computer systems in a fully automated fashion. A Lempel-Ziv-Welch (LZW) based compressed version of SMILES is suggested for cases where the size of the structure exceeds the storage capacity of PDF417 barcodes. Alternatively, the compact ACS format may be employed as a structural representation. The input via barcodes is fast, practically error free due to the 2D barcodes used which employ error correction and fully automatic. A Web application interface is developed which is able to interpret these barcodes and export them as optimized 3D chemical structures. Applications of this representation range from keeping automated storage systems to Web-based tracking systems of molecular samples. The National Chemical Laboratory, Pune, employs 2D barcode encoded structures for in-house repository management, where barcodes can also be used for querying the database for similar or substructures of the query structure.

Enhanced selectivity to decalin in naphthalene hydrogenation under supercritical carbon dioxide - Hiyoshi, Norihito; Miura, R.; Rode, C. V.; Sato, O.; Shirai, M. (Chemistry Letters, 2005)
A charcoal-supported rhodium catalyst was highly active and selective to decalin for the hydrogenation of naphthalene at very low temperature (333 K) under supercritical carbon dioxide.

Enhancement of double-layer capacitance behavior and its electrical conductivity in layered poly (3, 4-ethylenedioxythiophene)-based nanocomposites - Murugan, A. Vadivel; Viswanath, A. K.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Applied Physics Letters, 2005)
In this letter, we report on the enhanced double-layer capacitance of a layered poly (3, 4-ethylene dioxythiophene) PEDOT-MoO3 nanocomposite, which has been synthesized by a novel microwave irradiation method. The x-ray photoelectron spectroscopy analysis shows the changes in electron density and the shift in binding energy suggesting charge transfer from sulfur atoms upon PEDOT intercalation between MoO3 layers. The room-temperature conductivity for the PEDOT-MoO3 composite is found to be 1.82x10(-1) S cm(-1), which is four orders of magnitude higher than that of the pristine oxide (3.78x10(-5) S cm(-1)). The enhanced double-layer capacitance of the PEDOT-MoO3 nanocomposite (similar to 300 F g(-1)) compared to that (similar to 40 mF g(-1)) of pristine MoO3 is attributed to higher electronic conductivity, enhanced bidimensionality, and increase in surface area of the nanocomposite.

Entrapment of poly(3,4-ethylenedioxythiophene) between VS2 layers to form a new organic-inorganic intercalative nanocomposite - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Vijayamohanan, K. (Journal of Materials Chemistry, 2005)
Here we report the synthesis and characterization of a new class of nanocomposite by direct in situ oxidative polymerization of 3,4-ethylenedioxythiophene (EDOT) with VS2 as a host material in the presence of an external oxidizing agent. Upon intercalation, the interlayer spacing of VS2 expands from 5.71 Angstrom to 14.01 Angstrom, followed by exfoliation and a restacking process facilitating expansion of the lattice in a direction perpendicular to the dichalcogenide layers. This change in interlayer separation is consistent with the existence of two phases of organic and inorganic species in the nanocomposites corresponding to the intercalation of PEDOT in the VS2 framework. The resulting nanocomposite is characterized by thermal analysis (TGA), X-ray diffraction, FTIR, SEM, TEM, and four-probe electrical conductivity measurements. The application potential of the nanocomposite as a cathode material for rechargeable lithium batteries is also demonstrated by the electrochemical intercalation of lithium into the PEDOT-VS2 nanocomposite, where a significant enhancement in the discharge capacity is observed (similar to130 mA h g(-1)) compared to that (80 mA h g(-1)) for pristine VS2.

Enzymatic hydrolysis of delignified bagasse polysaccharides - Adsul, Mukund G.; Ghule, J. E.; Shaikh, H.; Singh, R.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Sugarcane bagasse, consisting of cellulose, xylan, and lignin, was chemically treated to generate bagasse samples with continuously decreasing content of lignin. These bagasse samples were hydrolyzed by cellulase and xylanase enzymes, produced earlier by Penicillium janthinellum NCIM 1171 in the same bagasse polysaccharides production medium. The hydrolysis was carried out by using different concentrations of the enzymes at two different temperatures, 30 and 50 degrees C, taking hydrolysis of Avicel as control. It was found that while the maximum hydrolysis for Avicel was 70% that of some of the bagasse polysaccharides was as high as 95%. The products of hydrolysis were glucose, xylose, and arabinose, as confirmed by high pressure ion chromatography (HPIC). It is interesting to note that arabinose, which constitutes about 10% of the weight of bagasse xylan, could also be released easily by the enzymes. Also, the initial rates of hydrolysis was found to be much higher for the bagasse polysaccharides, and in some cases about 90% of the hydrolysis occurred within 20 h. Amongst all bagasse samples, the sample with (Kappa no. 1.2, lignin content 0.18%) gave the highest degree of hydrolysis at 50 degrees C. Even the bagasse polysaccharide with Kappa no. 16.8 (lignin content 2.5%) underwent greater extent of hydrolysis than Avicel. Apparently, the delignified bagasse medium appears to be a facile medium for the combined hydrolytic action of the cellulase and xylanase enzymes. Considering that sugarcane bagasse is a waste biomass material available in abundance annually, this methodology can be used to value-add to this biomass to produce sugars, which can be fermented to produce biofuels like ethanol. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: bagasse polysaccharides; Cellulase; chemical treatment; Enzymatic hydrolysis; Penicillium janthinellum; Sugarcane bagasse; Xylanase

Epoxidation of styrene by anhydrous hydrogen peroxide over boehmite and alumina catalysts with continuous removal of the reaction water - Choudhary, Vasant R.; Patil, N. S.; Chaudhari, Nitin K.; Bhargava, Suresh Kumar (Journal of Molecular Catalysis A-Chemical, 2005)
Boehmite and alumina (obtained from the boehmite by its calcination at different temperatures 300-900degreesC) are active and stable catalysts for the selective epoxidation of styrene by anhydrous H2O2 to styrene oxide with continuous removal of the reaction water. Influence of the catalyst (boehemite) calcination temperature, H2O2/styrene ratio and catalyst loading on the styrene conversion and selectivity for styrene oxide. phenyl acetaldehyde. benzaldehyde and benzoic acid in the epoxidation has been investigated. In the presence of water. the catalyst shows very poor activity and selectivity in the epoxidation. The catalyst also catalyses H2O2 decomposition and hence has optimum loading for obtaining high-styrene conversion in the epoxidation. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Alumina; anhydrous hydrogen peroxide; boehmite; Epoxidation of styrene; Styrene oxide

Expedient synthesis of 1,2,3-triazole-fused tetracyclic compounds by intramolecular Huisgen ('click') reactions on carbohydrate-derived azido-alkynes - Hotha, Srinivas; Anegundi, Ramakrishna I.; Natu, A. A. (Tetrahedron Letters, 2005)
An efficient, practical and convenient synthesis of 1,2,3-triazole-fused tetracyclic compounds was achieved by intramolecular 1,3-dipolar cycloaddition of carbohydrate-derived azido-alkynes. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Click chemistry; Cycloaddition; diversity oriented synthesis; Huisgen reaction

Expeditious convergent synthesis of a dibromotyrosine alkaloid inhibitor of mycothiol-S-conjugate amidase - Chanda, B. M.; Sulake, R. S. (Tetrahedron Letters, 2005)
A quick, economic synthesis of the alkaloid 1, an inhibitor of mycothiol-S-conjugate amidase (MCA) is reported. Starting from low-cost, commercially available 4-hydroxybenzaldehyde, the nine-step synthesis involved dibromination and coupling with N-acetylglycine to give a stable methyloxazole intermediate 5 which was hydrolyzed, oximated and coupled to agmatine to yield the oxime in -30% overall yield. It was not necessary to protect the oxime in the synthetic sequence thereby circumventing a deprotection step. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 4-hydroxybenzaldehyde; marine alkaloid; mycothiol-S-conjugate amidase

Extracellular biosynthesis of bimetallic Au-Ag alloy nanoparticles - Senapati, S.; Ahmad, Absar; Khan, Mohammad Islam; Sastry, M.; Kumar, R. (Small, 2005)
Keywords: alloys; Biosynthesis; composites; enzymes; Nanoparticles

Extracellular nuclease from a thermophile, streptomyces thermonitrificans: production, purification and partial characterization of - double strand preferential - deoxyribonuclease activity - Patil, N. S.; Deshmukh, Satej S.; Shankar, V. (Process Biochemistry, 2005)
A thermophilic strain of Streptomyces themionitrificans produced high levels of extracellular nuclease (designated as nuclease Stn beta) when grown on nutrient broth glucose medium. Maximal nuclease activity (51 U ml(-1)) was obtained, in 40 h, when the culture was grown on modified NBG medium at 45 degreesC. The enzyme was purified to homogeneity with an overall recovery of 5.6% and a specific activity of 10,833. The relative molecular mass of the purified enzyme, determined by gel filtration, was 22.4 kDa and it showed an obligate requirement for Mn2+ for activity. The optimum pH and temperature of nuclease Stn beta were 8.0 and 45 degreesC, respectively. The enzyme was inhibited by Mg2+ CO2+, Cu2+, Zn2+ and Hg2+, inorganic phosphate, pyrophosphate, dithiothreitol, beta-mereaptoethanol, EDTA and NaCl. Nuclease Stn beta was stable to high concentrations of urea and organic solvents but susceptible to low concentrations of SDS and guanidine hydrochloride. Nuclease Stn beta is a multifunctional enzyme with substrate specificity in the order of dsDNA > ssDNA much greater than RNA. The end products of dsDNA hydrolysis were predominantly oligonucleotides (85-90%) and small amounts of 5' mononucleotides (10-15%) suggesting an endo mode of action. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Characterization; Endonuclease; extracellular nuclease; production; Purification; Streptomyces thermonitrificans

Extra-/intracellular biosynthesis of gold nanoparticles by an alkalotolerant fungus, trichothecium sp. - Ahmad, Absar; Senapati, Satyajyoti; Khan, Mohammad Islam; Kumar, Rajiv; Sastry, Murali (Journal of Biomedical Nanotechnology, 2005)
The development of reliable, eco-friendly processes for the synthesis of nanoscale materials is an important aspect of nanotechnology. As part of our ongoing investigation into the use of fungi for nanoparticle synthesis, we report herein that depending on the reaction conditions of the fungus Trichothecium sp. with aqueous gold ions, gold nanoparticle synthesis can be controlled to occur either within the biomass or extracellularly. Moreover, we have found that reaction of gold ions with the Trichothecium sp. fungal biomass under stationary conditions results in the rapid extracellular formation of gold nanoparticles of spherical, rod-like and triangular morphology whereas reaction of the biomass under shaking conditions resulted in intracellular growth of the nanoparticles. It is believed that on changing the reaction conditions of the fungus with gold ions, the enzymes and proteins which are being released into the medium under stationary conditions do not get released under shaking conditions resulting in the formation of extracellular or intracellular gold nanoparticles respectively. The gold nanoparticles are not toxic to the cells and the cells continued to grow after the biosynthesis of the gold nanoparticles in both the cases.
Keywords: Biosynthesis; enzymes; Fungus; Gold; Morphology Control; Nanoparticles

Effect of a focusing electric field on the formation of arc generated carbon nanotubes - Karmakar, Soumen; Nagar, Harshada; Pasricha, R.; Seth, T.; Sathe, V. G.; Bhoraskar, S. V.; Das, A. K. (Nanotechnology, 2006)
The effect of a focusing electric field on the formation of carbon nanotubes in a direct current arc-plasma is investigated. The hard deposits on the surface of the cathode are the main products, rich in multi-walled carbon nanotubes. It is seen that the focusing electric field has a distinct influence on the yield, purity and morphology of the nanotubes. The yield of the carbon nanotubes under the `focused field condition' has been found to be higher than that derived from the normal electrode configuration. It has been observed that the deposition of carbonaceous soot on the reactor wall is considerably reduced on application of the focusing electric field. Transmission electron microscopy has been used to determine the morphology of the nanotubes. In addition, Raman spectroscopy has helped in distinguishing the graphene-like structures from the disordered carbon networks and helped in analysing the morphology of the tubes. Thermal analysis gave a qualitative estimation of the relative yield of carbon nanotubes within the cathode deposits and their thermal stabilities. The crystalline nature of the samples has been confirmed by x-ray diffraction analysis. The results clearly indicate that the focusing electric field confines the positively charged carbon precursors within the cathode-anode space causing high relative yield and purity and has a distinct effect on controlling the inner diameter of the as-synthesized carbon nanotubes.

Effect of annealing on properties of ZrSe2 thin films - Hankare, P. P.; Asabe, M. R.; Kokate, A. V.; Delekar, S. D.; Sathe, D. J.; Mulla, Imtiaz S.; Chougule, B. K. (Journal of Crystal Growth, 2006)
Thin films of ZrSe2 have been prepared on stainless steel and fluorine-doped tin oxide-coated glass substrates using electrodeposition technique at potentiostatic mode. Double-distilled water containing precursors Zr and Se with ethylene diamine tetra-acetic acid disodium salt as a complexing agent was used to obtain good quality deposits by controlling the rate of reaction. The preparative parameters such as concentration of bath, deposition time, bath temperature, pH of the bath and annealing temperature have been optimized using photoelectrochernical (PEC) technique. The films deposited at optimum preparative parameters are annealed at different temperatures. The film annealed at 200 degrees C shows more photosensitivity. The as-deposited and annealed films at 200 degrees C have been characterized by X-ray diffraction (XRD), energy dispersive analysis by X-ray (EDAX), optical absorption and scanning electron microscopy (SEM). The XRD analysis of the as-deposited and annealed films showed the presence of polycrystalline nature with hexagonal crystal structure. EDAX study reveals that deposited films are almost stoichiometric. Optical absorption study shows the presence of direct transition and band gap energies are found to be 1.5 and 1.38 eV, respectively, for the as-deposited and annealed films. SEM study revels that the grains are uniformly distributed over the surface of substrate for the as-deposited as well as annealed film, which indicates formation of good and compact type of crystal structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: band gap; EDAX; Electrodeposition; PEC; SEM; XRD; ZrSe2 thin films

Effect of calcination cycles on the preparation of tin oxide based traditional drug: studies on its formation and characterization - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Gaikwad, A. B.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2006)
The preparation method of metal based Indian traditional drugs involves conversion of a pure metal into its oxide by repeated high temperature calcination cycles. In this work, the effect of number of calcination cycles followed in the preparation of tin oxide based Ayurvedic drug, `vanga bhasma' was studied by a systematic characterization of the drug samples after various calcination stages. It was found that tin was in the form of Sn4+ state and that the formation of SnO2 proceeded step-wise through Sn(OH)(4). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: calcination cycles; Oxidation; oxidation state of tin; Particle size; tin oxide; vanga bhasma

Effect of calcination temperature on the catalytic activity of zirconia-supported heteropoly acids - Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Zirconia-supported silicotungstic acid (15% STA) catalyst with different calcination temperatures (600-850 degrees C) was prepared by suspending zirconium oxyhydroxide in methanol solution of STA followed by drying and calcination. These catalysts were characterized by XRD, FTIR pyridine adsorption and DRUV-vis spectroscopy. The catalysts showed both Bronsted as well as Lewis acidity and 15% STA on zirconia calcined at 750 degrees C (15 SZ-750) had the highest Bronsted acidity. Characterization of 15 SZ-750 catalyst by Raman spectroscopy showed the presence of zirconia-anchored mono-oxotungstate as the major tungsten species present in this catalyst. These catalysts were used in benzoylation of veratrole with benzoic anhydride and 15 SZ-750 catalyst showed the highest activity. For catalyst with support calcined at different temperatures before HPA impregnation, catalytic activity decreases as the support calcination temperature increases due to the decrease in Bronsted acidity. Comparison of the catalytic activity of 15 SZ-750 with that of zirconia-supported phosphotungstic acid (15%, calcined at 750 degrees C, 15 PZ-750) in benzoylation of veratrole with benzoic anhydride, acylation of anisole with acetic anhydride and in alkylation of diphenylether with 1-dodecene showed that 15 SZ-750 catalyst has higher activity and deactivation resistance due to its higher Bronsted acidity. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Alkylation; Anisole; diphenylether; Phosphotungstic acid; Silicotungstic acid; veratrole; Zirconia

Effect of organic additives on the mitigation of volatility of 1-nitro-3,3 `-dinitroazetidine (TNAZ): next generation powerful melt cast able high energy material - Talawar, M. B.; Singh, Alok; Naik, N. H.; Polke, B. G.; Gore, G. M.; Asthana, S. N.; Gandhe, B. R. (Journal of Hazardous Materials, 2006)
1-Nitro-3,3'-dinitroazetidine(TNAZ) was synthesized based on the lines of reported method. Thermolysis studies on synthesized and characterized TNAZ using differential scanning calorimetry (DSC) and hyphenated TG-FT-IR techniques were undertaken to generate data on decomposition pattern. FF-IR of decomposition products of TNAZ revealed the evolution of oxides of nitrogen and HCN containing species suggesting the cleavage of C/N-NO(2) bond accompanied with the collapse of ring structure. The effect of incorporation of 15% additives namely, 3-amino-1,2,4-triazole(AT), 3,5-diamino-1,2,4-triazole (DAT), carbohydrazide (CHZ), 5,7-dinitrobenzofuroxan (DNBF), bis (2,2-dinitropropyl) succinate (BNPS), triaminoguanidinium nitrate (TAGN), 2,4,6-trinitrobenzoic acid (TNBA) and nitroguanidine (NQ) on the volatility of TNAZ was investigated by undertaking thermogravimetric analysis. The TG pattern brings out the potential of BNPS and TAGN as additives to mitigate the volatility of TNAZ. The influence of additives on thermal decomposition of pattern of TNAZ was also investigated by DSC. The DSC results indicated that the additives did not have appreciable effect on the melting point of TNAZ. Scanning electron microscopic (SEM) studies were carried out to investigate the effect of additives on morphology of TNAZ. This paper also discusses the possible mechanism involved in between the TNAZ and TAGN and BNPS. It appears that the formation of charge transfer complex formation between the TNAZ and TAGN/BNPS. The effect of addition of high explosives such as CL-20, HMX and RDX on thermo-physical characteristics of TNAZ is also reported in this paper. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: melt castable explosive; morphological structure; synthesis; Thermolysis; trinitroazetidine (TNAZ); volatility behavior

Effect of spacer groups on the performance of MCM-41-supported platinum cluster-derived hydrogenation catalysts - Maity, Niladri; Basu, Susmit; Mapa, Maitri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
MCM-41 was functionalized with (EtO)(3)SiCH2Cl, (MeO)(3)SiCH2CH2CH2Cl, and (CH3)Cl2SiCH2Cl. The functionalized materials were characterized by solid-state NMR (CPMAS, Si-29 and C-13) and XPS. The NMR data indicate that three new silicon environments were created by(EtO)(3)SiCH2Cl and (MeO)(3)SiCH2CH2CH2Cl, whereas with (CH3)Cl2SiCH2Cl, two new silicon environments were obtained. XPS results from Si 2p core level and the valence band from the material functionalized by (MeO)(3)Si(CH2)(3)Cl was found to be the same as that of the corresponding fresh catalyst (1a), in contrast to that of the materials functionalized by the other two silane reagents. After further functionalization with triethylamine, these materials were used as inorganic anion exchangers to support the cluster anion [Pt-12(CO)(24)](2-). Solid-state NMR (29Si, C-13, N-15) was used to establish the presence of the quaternary ammonium group in the cluster-supported species. Analogous materials were also created using fumed silica as the support, and all of the cluster-supported materials were tested as catalysts for the hydrogenation of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, ethylacetoacetate, 4-nitrotoluene, cyclohexanone, allyl alcohol, and styrene. The best activity was obtained for the catalyst that had MCM-41 as the support and chloropropyl as the spacer group. TEM showed that the supports and the spacer groups had observable effects on the platinum crystallite size of the catalysts. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: functionalized inorganic oxides; hydrogenation catalysts; MCM-41; platinum carbonyl cluster; Solid-state NMR; spacer groups; XPS

Effect of thermal annealing on Fe40Ni38B18Mo4 thin films: modified Herzer model for magnetic evolution - Hysen, T.; Deepa, S.; Saravanan, S.; Ramanujan, R. V.; Avasthi, D. K.; Joy, Pattayil Alias; D Kulkarni, S.; Anantharaman, Maliemadom R. (Journal of Physics D-Applied Physics, 2006)
Magnetic properties of nano-crystalline soft magnetic alloys have usually been correlated to structural evolution with heat treatment. However, literature reports pertaining to the study of nano-crystalline thin films are less abundant. Thin films of Fe40Ni38B18Mo4 were deposited on glass substrates under a high vacuum of approximate to 10(-6) Torr by employing resistive heating. They were annealed at various temperatures ranging from 373 to 773K based on differential scanning calorimetric studies carried out on the ribbons. The magnetic characteristics were investigated using vibrating sample magnetometry. Morphological characterizations were carried out using atomic force microscopy (AFM), and magnetic force microscopy (MFM) imaging is used to study the domain characteristics. The variation of magnetic properties with thermal annealing is also investigated. From AFM and MFM images it can be inferred that the crystallization temperature of the as-prepared films are lower than their bulk counterparts. Also there is a progressive evolution of coercivity up to 573 K, which is an indication of the lowering of nano-crystallization temperature in thin films. The variation of coercivity with the structural evolution of the thin films with annealing is discussed and a plausible explanation is provided using the modified random anisotropy model.

Efficient amano PS-catalyzed chemo-, regio- and enantioselective hydrolysis of (+/-)-2,3-di-O-acetyl-2-C-methyl-D-erythrono-1,4-lactone: a facile preparation of bioactive natural products (-)-saccharinic acid lactone and potassium (2R,3R)-2,3,4-trihydr - Gogoi, Sanjib; N. P. Argade (Tetrahedron-Asymmetry, 2006)

Efficient deprotection of dithioacetals to carbonyls using Oxone-KBr in aqueous acetonitrile - Desai, Uday V.; Pore, D. M.; Tamhankar, B. V.; Jadhav, Sushilkumar A.; Wadgaonkar, P. P. (Tetrahedron Letters, 2006)
A simple and efficient method has been developed for the chemoselective dethioacetalization of dithioacetals to aldehydes and ketones using Oxone-KBr in aqueous acetonitrile at room temperature. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: deprotection; dethioacetalization; Oxone

Efficient protocol for genetic transformation and shoot regeneration of turmeric (Curcuma longa L.) via particle bombardment - Shirgurkar, M. V.; Naik, V. B.; von Arnold, S.; Nadgauda, R. S.; Clapham, D. H. (Plant Cell Reports, 2006)

Efficient, solvent-free method for the chemoselective synthesis of acylals from aldehydes and their deprotection catalyzed by silica sulfuric acid as a reusable solid acid catalyst - Desai, Uday V.; Thopate, T. S.; Pore, D. M.; Wadgaonkar, P. P. (Catalysis Communications, 2006)
An efficient method has been developed for the chemoselective synthesis of acylals from aldehydes and acetic anhydride in the presence of silica sulfuric acid as a reusable solid acid catalyst under solvent-free conditions. Ketones are found to remain unaffected under the reaction conditions. The deprotection of acylals has also been achieved using SSA in methanol medium. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylals; aldehydes; Chemoselective; protection and deprotection silica sulfuric acid

Electrical bistability in a xanthene class molecule: conduction mechanisms - Rath, Arup Kumar; Sahu, Satyajit; Pal, Amlan J. (Applied Physics Letters, 2006)
The author study conduction mechanism in two conducting states of a bistable device at range. They find that in the electrical bistable devices, electrical switching is associated with a change in the conduction mechanism. Device current in the low-conducting state follows an injection-limited mechanism. The current in the high-conducting state conforms a bulk-dominated mechanism, namely, space-charge limited conduction with an exponential distribution of traps. The bistability has an associated memory phenomenon. The devices exhibit read-only and random-access memory applications for several hours.

Electrochemical organization of monolayer protected gold nanoclusters on single-walled carbon nanotubes: significantly enhanced double layer capacitance - Mahima, Subhramanyam; Chaki, N. K.; Sharma, J.; Kakade, Bhalchandra A.; Pasricha, R.; Rao, A. M.; Vijayamohanan, K. (Journal of Nanoscience and Nanotechnology, 2006)
This paper reports a novel electrochemical route for anchoring monolayer protected gold nanoclusters (size 8 +/- 0.2 nm) on single-walled carbon nanotube bundles, resulting in the formation of hybrid materials. Monolayer protected gold nanoclusters prepared by modified Brust synthesis route were organized on SWNT bundles by cycling-the potential in dichloromethane between -1 to +1 V at a scan rate of 50 mV/s. Monolayer protected nanoclusters in electrolyte solutions possess ionic space charge around them (double layer charging), making them suitable for organization on nanotube bundles, by tuning the electrostatic interactions. More significantly, analysis of the double layer capacitance of these hybrid materials shows almost ten times increase in capacitance compared to that of bare SWNT bundles. We believe that these hybrid materials are potentially useful in nanoelectronics.
Keywords: double layer capacitance; double layer charging; hybrid materials; monolayer protected gold nanoclusters; single-walled carbon nanotubes

Electrochemical polymerization of o-anisidine on low carbon steel from aqueous salicylate solution: corrosion protection study - Wankhede, M. G.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
The electrochemical polymerization of o-anisidine was carried out on low carbon steel from an aqueous salicylate medium using cyclic voltammetry. The resulting poly(o-anisidine) coatings were uniform and adherent to the steel substrates. These coatings were characterized by cyclic voltammetry, LTV-visible absorption spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction measurements and scanning electron microscopy. The ability of the poly(o-anisidine) coatings to protect low carbon steel in an aqueous 3% NaCl was evaluated by the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(o-anisidine) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 15. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; low carbon steel; poly(o-anisidine) coatings

Electrochemical synthesis of corrosion protective polyaniline coatings on mild steel from aqueous salicylate medium - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Science and Technology of Advanced Materials, 2006)
Strongly adherent polyaniline coatings were electrochemically synthesized on mild steel from an aqueous salicylate medium. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy. The extent of the corrosion protection offered by polyaniline coatings to mild steel was investigated in aqueous 3% NaCl solution, 0.01 M Na2SO4 Solution and in aqueous solutions of NaCl + Na2SO4 with different concentrations by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies reveal that the corrosion resistance of the polyaniline-coated mild steel is significantly higher and the corrosion rate is considerably lower than that of uncoated steel. (c) 2006 Published by NIMS and Elsevier Ltd.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; polyaniline coatings mild steel

Electron beam induced surface cross-linking of functional monomers coated on silicon substrate - Mahapatra, S. K.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A.; Bhoraskar, Vasant N. (Materials Letters, 2006)
A 3: 1 composition of functional monomer: multifunctional acrylate was spin coated and later cross-linked under the influence of keV electron irradiation on the surface of silicon to generate a surface-anchored cross-linked network bearing functional moieties. Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) as well as wetting angle measurements were used for the analysis of functional monomer cross-linked surfaces. Results of the surface reconstruction of surfaces and electron irradiated on coated silicon wafers reveal that long-term hydrophilic surfaces can be achieved. Thus, the surface architecture can be favorably manipulated by using this remarkable technique with a Suitable combination of functional monomers and cross-linkers. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: electron beam irradiation; FTIR; Polymers; surface modification; XPS

Electron transfer behavior of monolayer protected nanoclusters and nanowires of silver and gold - Sharma, Jadab; Vivek, J. P.; Vijayamohanan, Kunjukrishna P. (Journal of Nanoscience and Nanotechnology, 2006)
Understanding the electron transfer behavior of nanometer sized, both metallic and semiconducting particles and wires is important due to the fundamental interest in size and shape dependent electronic properties and also because of its applications in nano-electronic devices like single electron transistors and molecular switches. Monolayer protected nanoclusters enable one simple and elegant method of synthesis of these types of metallic and semiconducting materials using interfacial chemistry as has been successfully used in several applications ranging from catalysis to molecular electronics. The success of this type of nanostructured materials is due in part to the well known protecting/stabilizing action of the ligands (also known as surface passivating/capping agents), which facilitate the synthesis and processing of these hydrophobic colloids in solution form. The present article discusses the electron transfer behavior of silver nanowires and nanoparticles with varied sizes. In particular, we have investigated the electrochemical properties of silver nanowires (diameter 70 nm, length several micrometers) and compared with the behavior of similar relatively larger sized nanoparticles (size 40 nm). A critical analysis of the redox behavior of silver nanowires and nanoparticles is presented in aqueous medium under various electrolytic conditions along with a comparison of analogous properties of smaller sized (2-7 nm) silver and gold nanoclusters.
Keywords: cyclic voltammetry; nanoclusters/nanoparticles; Nanowires

Enantio- and diastereocontrolled total synthesis of (+)-boronolide - Kumar, P.; Naidu, S. V. (Journal of Organic Chemistry, 2006)
An efficient stereoselective total synthesis of (+)-boronolide from valeraldehyde is described. The key steps include a Sharpless asymmetric hydroxylation, a chelation-controlled vinyl Grignard reaction followed by a Sharpless asymmetric epoxidation, hydrolytic kinetic resolution, and a ring-closing metathesis.

Enantioselective synthesis of (2R,3R)- and (2S,3S)-beta-hydroxyornithine - Pandey, Satyendra Kumar; Kumar, Pradeep (Tetrahedron Letters, 2006)
An efficient and short synthesis of (2R,3R)- and (2S,3S)-beta-hydroxyornithine 1a-b is described using Sharpless asymmetric dihydroxylation and regioselective nucleophilic opening of a cyclic sulfite as the key steps. (c) 2006 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone, novel cytokine modulators via sharpless asymmetric epoxidation and L-proline catalyzed mannich reaction - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron, 2006)
A short and efficient enantioselective synthesis of (-)-cytoxazone and its stereoisomer (+)-epi-cytoxazone, novel cytokine modulators, has been described with good yield and enantioselectivity. Ti-catalyzed Sharpless asymmetric epoxidation of allyl alcohol and L-proline catalyzed three-component Mannich reaction constitute the key steps in introducing stereogenicity into the molecule. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Asymmetric synthesis; epoxidation; Mannich reaction; Oxidation; Ozonolysis

Enantioselective synthesis of (S,S)-ethambutol using proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination - Kotkar, Shriram P.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2006)
An efficient enantioselective synthesis of (S,S)-ethambutol, a tuberculostatic antibiotic, has been achieved in 99% ee via both proline-catalyzed alpha-aminooxylation and alpha-amination of n-butyraldehyde as the key step. (c) 2006 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (+)-(S,S)-reboxetine - Siddiqui, Shafi A.; Narkhede, Umesh C.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synlett, 2006)
An efficient enantioselective synthesis leading directly to (+)-(S,S)-reboxetine has been described from commercially available trans-cinnammyl bromide using Sharpless asymmetric dihydroxylation as the key step.
Keywords: coupling; Dihydroxylation; Hydrogenation; reboxetine; trans-cinnamyl bromide

Engaging zwitterions in carbon-carbon and carbon-nitrogen bond- forming reactions: a promising synthetic strategy - Nair, Vijay; Menon, Rajeev S.; Sreekanth, A. R.; Abhilash, N.; Biju, Akkattu T. (Accounts of Chemical Research, 2006)
An Account of carbon−carbon and carbon−nitrogen bond-forming reactions mediated by zwitterions generated by the addition of organic nucleophiles to activated unsaturated systems highlighting their synthetic potential is presented.

Enhanced magnetostrictive properties of Mn substituted cobalt ferrite Co1.2Fe1.8O4 - Bhame, Shekhar D.; Joy, Pattayil Alias (Journal of Applied Physics, 2006)
The effect of substitution of Fe and Co by Mn on the magnetostrictive properties of the cobalt ferrite Co1.2Fe1.8O4 has been studied and compared. The studies on Co1.2-xMnxFe1.8O4 and Co1.2Fe1.8-xMnxO4 (0 <= x <= 0.4) showed a marked dependence of magnetostriction on the substitution of both Fe and Co by Mn. Higher magnetostriction is obtained for the substitution of Co by Mn whereas the magnetostriction is reduced substantially on the substitution of Fe by Mn. Higher magnetostriction at low magnetic fields and enhancement of the strain ratio have been observed for the substitution of Co by Mn. (c) 2006 American Institute of Physics.

Enhancement of gas permeation properties of polybenzimidazoles by systematic structure architecture - Kumbharkar, Santosh C.; Karadkar, Prasad B.; Kharul, Ulhas K. (Journal of Membrane Science, 2006)
Systematic structural variations in thermally stable polybenzimidazole (PBI) are explored that led to a substantial improvement in gas permeation properties. Physical property determinations revealed that incorporation of hexafluoroisopropylidene and tert-butyl groups led to amorphous polymers with slightly lowered thermal stability and decreased chain packing. PBI based on 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) and 5-tert-butyl isophthalic acid exhibited 10-40 times higher permeability, while changes in selectivities for industrially important pairs ranged from modest decrease of 75% or less than that of PBI based on isophthalic acid. The O-2/N-2 selectivity was almost doubled in case of PBI based on 5-tert-butyl isophthalic acid. Gas diffusion coefficients were estimated from solubility and permeability coefficient determinations. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior. The permeability predictions for heavier gases in isophthalic acid based PBI correlated well with physical properties. The occurrence of permeation characteristics (especially P-H2 and P-H2/P-N2) near Robeson's upper bound, high thermal stability and good solvent solubility achieved by these structural modifications depicted the potential of this family of polymers as gas separation membrane materials. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; Polybenzimidazole; Sorption; thermal stability

Enhancing cross-peak intensity in 2D-SLF spectroscopy - the role of equilibrium carbon magnetization in cross-polarization experiment - Das, Bibhuti B.; Ajithkumar, Thalasseril G.; Ramanathan, K. V. (Chemical Physics Letters, 2006)
A modification to the standard Hartmann-Hahn cross-polarization experiment has been proposed in which the initial 90 degrees pulses are applied both on the I and S spins. The inclusion of the available equilibrium polarization in the static magnetic field for the S spins is shown to have a beneficial effect for the 2D-SLF experiment, contributing to an increase in the cross-peak intensity and hence to a better resolution of the dipolar cross-peaks. (c) 2006 Elsevier B.V. All rights reserved.

Epoxidation of indene and cyclooctene on nanocrystalline anatase titania catalyst - Ramaswamy, Veda; Awati, Preeti; Ramaswamy, A. V. (Topics in Catalysis, 2006)
Nanocrystalline anatase titania samples of different crystallite sizes were prepared by sol gel method using ultrasonication and calcination at different temperatures. The calcined samples were treated with H2O2 in order to study the role of surface hydroxyl groups present on titania in generating reactive oxygen species responsible for the epoxidation reaction. The crystallite size of the calcined samples increased from 4 to 18 nm as the calcination temperature increased from 473 to 773 K, respectively. More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline TiO2 by using ultrasonication. EPR spectral data on the H2O2-treated samples confirmed the presence of superoxide radical species. The two distinct UV bands observed at 400 and 450 nm are assigned to charge transfer of peroxide (O-2 2-) to Ti. FT-IR spectral data show that the surface hydroxyl groups are the active sites in the generation of reactive oxygen species. The catalytic activity was evaluated in a series of epoxidation reactions using indene and cyclooctene as substrates and aqueous H2O2 as oxidant. The activity was found to decrease with increase in the calcination temperature of the samples, obviously due to an increase in crystallite size and a decrease in surface hydroxyl groups. The nanoparticle titania samples show better conversion and selectivity than the standard titania (Degussa P-25). The kinetic studies revealed that the reaction followed a pseudo first order kinetics in excess of H2O2.
Keywords: cyclooctene epoxidation; epoxidation of indene; nanocrystalline anatase titania; superoxide radical on titania

Eu3+ doped lanthanum oxide nanowhiskers: microwave hydrothermal synthesis, characterization and photoluminescence properties - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Kakade, Bhalchandra A.; Ravi, V.; Saaminathan, V. (Journal of Physics D-Applied Physics, 2006)
We report here a straightforward and rapid microwave - hydrothermal route providing an easy synthesis of Eu3+ doped La2O3 nanowhiskers. The nanostructured Eu3+ doped La2O3 is characterized by x-ray diffraction studies, scanning electron microscopy and photoluminescence (PL). The emission spectrum shows transitions from the excited 5D(0) state to F-7(J) (J = 0, 1, 2, 3, 4) levels of the Eu3+ ion. The most intense peak around 611 nm is due to the D-5(0) -> F-7(2) transition, expected from the Judd-Ofelt selection rules. PL spectra measurements demonstrate that the lanthanum oxide nanowhisker shows higher PL intensity.

Eulerian-lagrangian simulations of unsteady gas-liquid flows in bubble columns - Buwa, Vivek V.; Deo, Dhanannjay S.; Ranade, Vivek V. (International Journal of Multiphase Flow, 2006)
We studied the dynamics of gas-liquid flows in a rectangular bubble column using Eulerian-Lagrangian simulations. Three-dimensional, unsteady simulations were performed to simulate the dynamic characteristics of the oscillating bubble plume. The effect of superficial gas velocity and aerated liquid height-to-column width (HI K) ratio on the dynamic and time-averaged flow properties was studied and the simulated results were validated using wall pressure and voidage fluctuation measurements. The effect of lift force and numerical diffusion on the dynamic and time-averaged properties is discussed in detail. Further, the results obtained using the Eulerian-Lagrangian simulations were compared with the Eulerian-Eulerian simulations. The bubble scale information, which is otherwise lost in the Eulerian-Eulerian simulations, was validated using the voidage fluctuation measurements. Such experimentally validated Eulerian-Lagrangian models will be useful for the simulation of mass transfer and reactions in bubble columns. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Bubble column; CFD; Dynamics; Eulerian-Eulerian simulations; Eulerian-Lagrangian simulations; gas-liquid flow

Evidence for intergranular tunnelling in polyaniline passivated alpha-Fe nanoparticles - Sunny, Vijutha; Narayanan, T. N.; Sajeev, U. S.; Joy, Pattayil Alias; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanotechnology, 2006)
Nanoparticles are of immense importance both from the fundamental and application points of view. They exhibit quantum size effects which are manifested in their improved magnetic and electric properties. Mechanical attrition by high energy ball milling (HEBM) is a top down process for producing fine particles. However, fineness is associated with high surface area and hence is prone to oxidation which has a detrimental effect on the useful properties of these materials. Passivation of nanoparticles is known to inhibit surface oxidation. At the same time, coating polymer film on inorganic materials modifies the surface properties drastically. In this work a modified set-up consisting of an RF plasma polymerization technique is employed to coat a thin layer of a polymer film on Fe nanoparticles produced by HEBM. Ball-milled particles having different particle size ranges are coated with polyaniline. Their electrical properties are investigated by measuring the dc conductivity in the temperature range 10-300 K. The low temperature dc conductivity (I-V) exhibited nonlinearity. This nonlinearity observed is explained on the basis of the critical path model. There is clear-cut evidence for the occurrence of intergranular tunnelling. The results are presented here in this paper.

Evolution of the stereoselective pinacol coupling reaction - Chatterjee, A.; Joshi, Navalkishore N. (Tetrahedron, 2006)
Keywords: diastereoselective; enantioselective.; pinacol coupling; reductive dimerization

Exfoliation-induced nanoribbon formation of poly(3,4-ethylene dioxythiophene) PEDOT between MoS2 layers as cathode material for lithium batteries - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Power Sources, 2006)
A new type of layered nanocomposite synthesized by delaminated MoS2 nanosheets and poly(3,4-ethylenedioxythiophene) (PEDOT) are restacked to produce alternate polymer nanoribbons between layers Of MoS2 with an interlayer distance of similar to 1.38 nm. The unique properties of resulting nanocomposite are investigated by powder XRD, XPS, SEM, TEM, and four-probe conductivity measurements. The obtained nanocomposite can be used as a cathode material for a small power rechargeable lithium battery as demonstrated by the electrochemical insertion of lithium into the PEDOT/MoS2 nanocomposite. A significant enhancement in the discharge capacity (100 mAh g(-1)) is observed compared with that (40 mAh g(-1)) for MoS2. (c) 2005 Elsevier B.V All rights reserved.
Keywords: cathode material; lithium batteries; MoS2; organic-inorganic nanocomposite; PEDOT-nanoribbons

Experimental comparison of the structural, magnetic, electronic, and optical properties of ferromagnetic and paramagnetic polycrystalline Zn1-xCoxO (x=0,0.05,0.1) - Deka, Sasanka; Pasricha, Renu; Joy, Pattayil Alias (Physical Review B, 2006)
Ferromagnetism at room temperature is observed in one case whereas paramagnetism down to 12 K is observed in the second case when polycrystalline Zn1-xCoxO is synthesized under almost identical conditions. Identical x-ray diffraction, optical absorption, and x-ray photoelectron spectroscopy results indicate the incorporation of Co2+ ions in the ZnO lattice in both cases. However, electron diffraction studies show the presence of Co metal impurities in the ferromagnetic samples, indicating that pure Co doped ZnO is not likely to be ferromagnetic.

Eco-friendly, selective hydroxylation of C-7 aromatic compounds catalyzed by TS-1/H2O2 system under solvent-free solid-liquid-liquid-type triphase conditions - Mukherjee, P.; Bhaumik, Asim; Kumar, Rajiv (Industrial & Engineering Chemistry Research, 2007)
Direct ring hydroxylation of aromatics, namely, anisole, toluene, and benzylchloride, using TS-1 catalyst, a MFI-type titanium silicate molecular sieve, dilute H2O2 as oxidizing agent, and water as reaction medium, was investigated under solid-liquid-liquid (SLL)-type triphase conditions. The aim was to study the relative influence of commonly used organic solvents, under solid-liquid (SL)-type biphase reaction conditions, as compared to that of water, on the conversion and product selectivity. Under solvent-free triphase conditions, the ring hydroxylation of anisole, toluene, and benzylchloride leads to significant enhancement in the conversion, turn-over frequency, and para-selectivity. However, in the case of benzyl chloride, no ring hydroxylation took place under biphase conditions (using acetone as solvent) contrary to significant ring hydroxylation (ca. 60% H2O2 efficiency) under triphase aqueous medium conditions. The simple product recovery (phase separation of organic and aqueous layers) and use of water as reaction medium are other advantages. Since TS-1 is relatively hydrophobic, the reaction is hindered in the presence of organic solvents as they compete favorably with the substrate for diffusion inside the TS-1 channels. However, in the presence of water, the organic substrate competes favorably with water, leading to increased conversion and para-selectivity.

Eco-friendly synthesis of epichlorohydrin catalyzed by titanium silicate (TS-1) molecular sieve and hydrogen peroxide - Pandey, Rajesh Kumar; Kumar, Rajiv (Catalysis Communications, 2007)
In a mixed solvent system of acetonitrile and methanol, titanium silicate molecular sieve, TS-1, having MFI topology, efficiently catalyses the epoxidation of allyl chloride to the corresponding epichlorohydrin in excellent yields using dilute hydrogen peroxide (45%) as an oxidizing agent. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: allyl chloride; epichlorohydrin; epoxidation; heterogeneous catalysis; selectivity; titanium silicalite-1

Effect of auxin types on in vitro and ex vitro rooting and acclimatization of grapevine as influenced by substrates - Barreto, M. S.; Nookaraju, A. (Indian Journal of Horticulture, 2007)
Transferring micropropagated plantlets from in vitro to in vivo conditions is a critical step because plantlets have under-developed cuticle and stomata which result in wilting due to low humidity, fungal attack and bleaching in high light intensities. The resumption of terminal growth indicates successful establishment which is a change from mixotrophy to autotrophy. The survival of Vitis vinifera cvs. 2A-Clone and Red Globe plantlets rooted in vitro was 86.66 and 83.33%, respectively and the established plants showed a well-defined root system. Plantlets rooted in vivo by auxin pulse were easier to transfer and acclimatize with a survival percentage of 96.66 and 79.92 for 2A-Clone and Red Globe, respectively but the rooting was of fibrous type with few main roots and less number of root hairs. Coco-peat in combination with sand and soil was better for quick acclimatization and establishment (97.5 and 95% survival for 2A-Clone and Red Globe respectively) of the micropropagated plantlets.
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival

Effect of halogen addition to monolayer protected gold nanoparticles - Singh, Sanjay; Pasricha, Renu; Bhatta, Umananda M.; Satyam, P. V.; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2007)
The effects of N-halosuccinimide and halogen addition to monolayer protected gold nanoparticles (Au NPs) dispersed in organic media are described. Contrary to the expectation that nanoparticles dispersed in organic media are stable against aggregation, N-iodosuccinimide addition induced aggregation of octadecylamine capped gold nanoparticles in chloroform or toluene. It was observed that even KI and CuI addition could bring about the aggregation though they are very sparingly soluble in organic solvents. It was also found that even molecular iodine could bring about the above mentioned aggregation. Interestingly, when CuI is used the aggregated structures readily convert to very thin flat nanostructures upon exposure to an electron beam or UV irradiation. In fact when the aggregation is induced by the addition of KI or N-iodosuccinamide we do not see the flattening of the aggregated structures exemplifying the important role of Cu ions in making these flat structures.

Effect of pretreatment conditions on the catalytic activity of nano-sized TPA/ZrO2 dispersed in SBA-15 channels in acetylation reactions - Sawant, Dhanashri P.; Hartmann, Martin; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2007)
Acetylation of an aromatic compounds such as veratrole (1,2-dimethoxybenzene), anisole, thioanisole, isobutyl benzene and 2-methoxynaphthalene with acetic anhydride has been investigated over a nano-sized 12-tungstophosphoric acid (TPA)/22.4 wt.%ZrO2/SBA- 15 catalysts in the liquid phase conditions. Catalysts with different (%) TPA and zirconia loadings calcined at different temperatures were prepared by wet-impregnation and characterized by XRD, N-2 adsorption-desorption, FT-Rarnan, X-ray photoelectron spectroscopy (XPS). The acidic behavior of the catalyst was studied by TPD of ammonia and FT-IR pyridine adsorption. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/SBA- 15 calcined at 1123 K had the highest acidity and was the most active catalyst in veratrole acetylation with acetic anhydride. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: acetylation; SBA-15; TPA/ZrO2; veratrole; wet-impregnation

Effect of sparger design on the flow in a bubble column: symbolic analysis of LDA data - Kulkarni, A. A.; Deshpande, Suvarna S.; Joshi, J. B.; Kumar, V. Ravi; Kulkarni, B. D. (Industrial & Engineering Chemistry Research, 2007)
This paper aims at developing a methodology that helps in the characterization of the effects of a single point and multipoint sparger on the flow patterns in a bubble column reactor. The methodology uses the simultaneously measured instantaneous velocity-time data (two orthogonal velocity components) using LDA at different measurement locations. The data sets are transformed into their equivalent description in terms of polar coordinates, viz., resultant velocity vector and angle. This information is further transformed in terms of symbolic representation in a binary number format. The covariance matrices obtained from the binary data are analyzed for their eigenvalues, and the spectrum is used for the identification of the dominant, energy containing modes in the data. In the vicinity of the sparger, the nature of covariance matrix and the eigenvalue spectrum for the single point sparger (SPS) data was significantly different from that of the multipoint sparger (MPS). In the bulk region, for both types of spargers, the nature of the eigenvalues and the number of dominant modes is seen to be different from the near sparger region. In general, more numbers of eigenvalues are required to capture the total energy in the data for a multipoint sparger when compared to a single point sparger. This suggests a higher level of complexities existing due to the intricate hydrodynamics for the multipoint sparger. The possible use of this methodology for practical purposes, e.g., identification of malfunctioning of gas-liquid sparger reactors is discussed.

Effect of substituent polarity, bulk, and substitution site toward enhancing gas permeation in dibromohexafluorobisphenol-A based polyarylates - Ishole, Yogesh S.; Karadkar, Prasad R.; Kharul, Ulhas K. (Journal of Polymer Science Part B-Polymer Physics, 2007)
The gas permeation properties of polyarylates were tuned by varying nature and site of substituents present on both of its monomers, viz., bisphenol and dicarboxylic acid. The phenyl rings of hexafluorobisphenol-A were substituted in asymmetric manner by polar bromine to obtain dibromohexafluorobisphenol-A. This bisphenol was polymerized with equimolar mixture of iso- and terephthalic acid (base case), bromo- and nitroterephthalic acid (polar group substituted acids), 4,4'-hexafluoroisopropylidene bis(benzoic acid), and t-butyl isophthalic acid (bulky group containing acids). Physical properties and gas permeation properties of these polyarylates were investigated to assess combined effects of asymmetric nature of bisphenol substitution, polar nature of substituent bromine, hexafluoroisopropylidene group present at the bridge position of bisphenol, and substituent present on the acid moiety. The combination of these substituent types led these polyarylates to lie near Robeson upper bound. The gas sorption analysis and estimation of diffusivity in these polyarylates shed a light on observed variations in gas permeation properties by attempted structural variations. (c) 2007 Wiley Periodicals, Inc.
Keywords: asymmetric substitution; Diffusion; Gas permeation; gas sorption; polyarylates; selectivity; structure-property relations

Effect of surface chemistry of Fe-Ni nanoparticles on mechanistic pathways of azo dye degradation - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Environmental Science & Technology, 2007)
The degradation of Orange G a monoazo dye, in aqueous solutions was investigated using as-synthesized and stored Fe-Ni bimetallic nanoparticles. Batch experiments with a nanocatalyst loading of 3 g/L showed complete. dye degradation (150 mg/L) after 10 min of reactiontime. HPLC-MS analysis of the degradation products showed that assynthesized nanoparticles reductively cleaved the azo linkage to produce aniline as the major degradation product. However, 1-year-stored nanoparticles showed an oxidative degradation of Orange G through a hydroxyl-radical induced coupling of parent and/or product molecules. XPS analysis in corroboration with HPLC-MS data showed that the surface chemistry between Fe and Ni in assynthesized and stored nanoparticles play a crucial role. in directing the mode of degradation. Reductive dye degradation using as-synthesized nanoparticles proceeded through hydride transfer from nickel, whereas formation of a Fe (2+) -Ni(0) galvanic cell in stored nanoparticles generated hydroxyl radicals from water in a nonFenton type reaction. The latter were responsible for the generation of radical centers on the dye molecule, which led to a coupling-mediated oxidative degradation of Orange G. The generation of hydroxyl radicals is further substantiated with radical quenching experiments using ascorbic acid indicating that stored nanoparticles degrade Orange G through a predominantly oxidative mechanism. HPLC-MS and XPS analysis of dye degradation using as-synthesized nanoparticles exposed to air and water confirmed that the reductive or oxidative degradation capability of Fe-Ni nanoparticles is decided by the time and type of catalyst aging process.

Efficient and practical total synthesis of (+/-)-alpha-cuparenone - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthesis-Stuttgart, 2007)
A one-pot cyclopentannulation approach as the key step for the total synthesis of (+/-)-alpha-cuparenone is described.
Keywords: Alkylation; annulation; hydroboration-oxidation; reduction

Efficient, eco-friendly process for aldol and Michael reactions of trimethylsilyl enolate over organic base-functionalized SBA-15 catalysts (vol 264, pg 146, 2007) - Srivastava, Rajendra (Journal of Molecular Catalysis A-Chemical, 2007)

Efficient higher-order cycloaddition reactions of 8,8-dicyanoheptafulvenes with dienes - Nair, Vijay; Gopalakrishnan Abhilash, K.; Biju, Akkattu T.; Eringathodi, Suresh (Synthesis-Stuttgart, 2007)
The cycloaddition reactions of 8,8-dicyanoheptafulvene with electron-rich dienes afforded the higher order cycloaddition products in excellent yields. With cyclic dienes as well as dimethoxybutadiene the [8+2] adducts were obtained exclusively. With methyl- and dimethylbutadienes the [6+4] adducts were the only products isolated.
Keywords: cycloadditions - bicyclic compounds - polycycles - dicyanoheptafulvene - tetrahydroazulenes

Efficient N-arylation of amines catalyzed by Cu-Fe-hydrotalcite - Jadhav, Vinod H.; Dumbre, Deepa K.; Phapale, Vilas B.; Borate, Hanumant B.; Wakharkar, Radhika D. (Catalysis Communications, 2007)
An efficient N-arylation of amines with aryl halides in presence of heterogeneous recyclable Cu-Fe-hydrotalcite catalyst has been developed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: amines; Aryl halides; Cu-Fe-hydrotalcite; heterogeneous catalyst; N-arylation

Efficient one-pot synthesis of alpha-amino phosphonates catalyzed by bismuth nitrate pentahydrate - Bhattacharya, Asish K.; Kaur, Tanpreet (Synlett, 2007)
A simple, efficient, and environmentally benign method has been developed for the synthesis of alpha-amino phosphonates through a one-pot reaction of aldehydes with amines and diethyl phosphite in the presence of bismuth nitrate pentahydrate as a catalyst. Some of the major advantages of this protocol are: good yields, the involvement of a less-expensive and non-toxic catalyst, mild and solvent-free reaction conditions and also tolerance towards other functional groups present in the substrates. Eighteen examples are described, highlighting the substrate scope of the reaction.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; bismuth nitrate pentahydrate; synthetic methods

Efficient organocatalytic route to the atorvastatin side-chain - George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An organocatalytic route to the synthesis of the atorvastatin side-chain, a building block present in the statin family, is described using L-proline-catalyzed alpha-aminooxylation of an aldehyde. The method also employs an iodine-induced intramolecular electrophilic cyclization of a carbonate to produce the iodocarbonate in a highly diastereoselective manner. (C) 2007 Elsevier Ltd. All rights reserved.

Efficient synthesis of 2,4-disubstituted thiazoles using ionic liquid under ambient conditions: a practical approach towards the synthesis of Fanetizole - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Tetrahedron, 2007)
A highly efficient and rapid synthesis of 2-amino-4-arylthiazoles and 2-methyl-4-arylthiazole from alpha-bromoketone and thiourea/thioamide is described using room temperature ionic liquid at ambient conditions. The method is simple, rapid and practical, generating thiazole derivatives in excellent isolated yields. This protocol is utilized for a commercially feasible synthesis of an anti-inflammatory agent, Fanetizole. (c) 2007 Published by Elsevier Ltd.
Keywords: alpha-bromo ketone; ionic liquids; thiazoles; thiourea/thioamide

Efficient synthesis of azetidine-2,3-diones from L-(+)-diethyl tartrate - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synlett, 2007)
A convenient route to enantiopure azetidine-2,3-diones is described. The chiral ketene generated from commercially available L-(+)-diethyl tartrate on Staudinger cycloaddition with different imines gave spiro-beta-lactams in good yields. These spiro-beta-lactams were transformed into azetidine-2,3-diones in excellent yields in a two-step process.
Keywords: Cycloaddition; imines; lactams; spiro compounds; stereoselective synthesis

Efficient synthesis of fused 1,2,3-triazolo-delta-lactams using huisgen [3+2] dipolar cycloaddition ``click-chemistry'' in water - Kumar, Indresh; Rode, Chandrashekhar V. (Chemistry Letters, 2007)
A general approach for the quick synthesis of various 1,2,3-triazolo-delta-lactams has been described, which involves the Huisgen [3 + 2] dipolar cycloaddition of azides derived from different amino acids with dimethyl acetylenedicarboxylate in water followed by cyclization.

Efficient total synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid - Pandey, Satyendra Kumar; Kumar, Pradeep (European Journal of Organic Chemistry, 2007)
An efficient enantioselective synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid (1) from epichlorohydrin is described. The key steps include Jacobsen's HKR, Sharpless asymmetric dihydroxylation, regioselective opening of epoxide and cyclic sulfate. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007).
Keywords: cyclic sulfate; Dihydroxylation; Grignard reaction; hydroboration-oxidation; Jacobsen's hydrolytic kinetic resolution (HKR); regio selectivity

Electrochromic device (ECD) cell characterization on electron beam evaporated MoO3 films by intercalating/deintercalating the H+ ions - Sivakumar, R.; Gopinath, Chinnakonda S.; Jayachandran, M.; Sanjeeviraja, C. (Current Applied Physics, 2007)
Thin films of molybdenum oxide (MoO3) is one of the most interesting layered intercalation materials because of its excellent application in solid state batteries, large-area window and display systems. In recent years there has been considerable interest in variable transmittance electrochromic devices (ECD) based on Li+, H+ and K+ intercalation in transition metal oxide (MoO3) thin films. In the present investigation, thin films of MoO3 were prepared by electron beam evaporation technique on microscopic glass and fluorine doped tin oxide (FTO) coated glass substrates for the application in electrochromic device cells. The compositional stoichiometry of the films was studied by X-ray photoelectron spectroscopy (XPS). The electrochromic nature of the films has been analyzed by inserting H+ ions from the H2SO4 electrolyte solution using the cyclic-voltammetry (CV) technique. We studied the electrochromic device cells (ECD) incorporating an evaporated MoO3 thin films as electrochromic layers. The devices exhibit good optical properties with low transmittance values in the colored state, which make them suitable for large-area window applications. The maximum coloration efficiency of the cell was observed at about 70 cm(2)/c. (c) 2005 Published by Elsevier B.V.
Keywords: coloration efficiency; electrochromic device cells; molybdenum oxide thin films; optical density; stoichiometry

Electronic structure of spherical quantum dots using coupled cluster method - Heidari, Ideh; Pal, Sourav; Pujari, B. S.; Kanhere, Dilip G. (Journal of Chemical Physics, 2007)
2, 6, 12, and 20 electron quantum dots have been studied using coupled cluster at singles and doubles level and extensive multireference coupled cluster (MRCC) method. A Fock-space version of MRCC (FSMRCC) containing single hole-particle excited determinants has been used to calculate low-lying excited states of the above system. The ionization potential and electron affinity are also calculated. The effect of correlation energy on excitation energy and charge density is shown by calculating them at the high density region (low value of density parameter r(s)) and at the low density region (high value of density parameter r(s)). (c) 2007 American Institute of Physics.

Enantiomeric separation of novel anticancer agent 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one - Shinde, Popat D.; Jadhav, Vinod H.; Borate, Hanumant B.; Bhide, Sunil R.; Sonawane, Kiran B.; Wakharkar, Radhika D. (Journal of Chromatography A, 2007)
The enantiomers of 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one, a novel anticancer agent, were separated by derivatisation with caronaldehyde, separation of the resulting diastereoisomers of the corresponding esters by silica gel column chromatography and regeneration of alcohols (S)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-one and (R)5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2- en- 1-one under aqueous conditions. The absolute configuration of the enantiomers was determined by H-1 NMR studies of the corresponding Mosher esters. Alternatively, the enantiomers were separated by preparative HPLC to collect the (S)- and (R)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-ones with high purity which was comparable with that obtained by the chemical method. The details of these methods have been presented herein. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Anticancer; column chromatography; diaryl cyclopentenone; diastereoisomers; enantioseparation; HPLC; Resolution

Enantioselective syntheses of (-)-pinellic acid, alpha- and beta-dimorphecolic acid - Baruah, Pranjal K.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Tetrahedron, 2007)
An efficient enantioselective convergent approach for the synthesis of (-)-pinellic acid 1, alpha- and beta- dimorphecolic acid (2 and 3) from 1,9-nonane diol is described. The synthetic strategy features Sharpless asymmetric hydroxylation, Sonogashira coupling and Birch reduction. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric dihydroxylation; influenza; Sonogashira coupling

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone via Rh-catalyzed diastereoselective oxidative C-H aminations - Narina, Srinivasarao V.; Kumar, Talluri Siva; George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An efficient enantioselective synthesis of (-)-cytoxazone (1) and (+)-epi-eytoxazone (2) using proline-catalyzed asymmetric alpha-amino-oxylation of aldehydes followed by Rh-catalyzed diastereoselective oxidative C-H amination as the key steps is described. syn or anti 1,2-aminoalcohols were obtained by Rh-catalyzed intramolecular amidation of the C-H bonds of carbamates or sulfamate esters with good to excellent diastereoselectivity. (c) 2006 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (-)-pinellic acid - Naidu, S. Vasudeva; Kumar, Pradeep (Tetrahedron Letter, 2007)
An enantioselective convergent approach toward the total synthesis of pinellic acid 1 from 1,9-nonanediol is described. The synthetic strategy features iterative Sharpless asymmetric dihydroxylation, Sonogashira coupling and Birch reduction. (c) 2007 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (S)-dapoxetine - Siddiqui, Shafi A.; Srinivasan, Kumar V. (Tetrahedron-Asymmetry, 2007)
An efficient enantioselective synthesis leading directly to (+)-(S)-dapoxetine has been described for the first time using Sharpless asymmetric dihydroxylation, Barton-McCombie deoxygention, and Mitsunobu reaction as the key steps. (C) 2007 Published by Elsevier Ltd.

Enantioselective synthesis of (S)-timolol via kinetic resolution of terminal epoxides and dihydroxylation of allylamines - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron, 2007)
An efficient enantioselective synthesis of (S)-timolol has been described using chiral Co-salen-catalyzed kinetic resolution of less expensive (+/-)-epichlorohydrin with 3-hydroxy-4-(N-morpholino)-1,2,5-thiadiazole in good overall yield (55%) and excellent enantioselectivity (98%). Synthesis of (S)-timolol has also been achieved using hydrolytic kinetic resolution as well as asymmetric dihydroxylation routes in 90% ee and 56% ee, respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric reactions; diols; epoxides; Kinetic resolution; oxazolidinone

Enantioselective synthesis of tarchonanthuslactone using proline-catalyzed asymmetric alpha-aminooxylation - George, Shyla; Sudalai, Arurnugam (Tetrahedron-Asymmetry, 2007)
A practical enantio selective synthesis of tarchonanthuslactone 1, an important natural product with a polyol unit, is described. The sequence of synthetic reactions involves proline-catalyzed alpha-aminooxylation and iodine-induced electrophilic cyclization as the chiral inducing steps. (c) 2007 Elsevier Ltd. All rights reserved.

Encapsulation of endoglucanase using a biopolymer Gum arabic for its controlled release - Ramakrishnan, Anish; Pandit, Nilesh; Badgujar, Mahesh; Bhaskar, C.; Rao, Mala (Bioresource Technology, 2007)
{Gum Arabic, a biodegradable natural polymer was used as a matrix to encapsulate endoglucanase from Thermomonospora sp. The modified enzyme retained complete biocatalytic activity and exhibited a shift in the optimum temperature [
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase

Energy analysis of field emitted electrons from a ZnO tetrapod - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Ramgir, Niranjan S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Applied Physics Letters, 2007)
The experimental total energy distribution (TED) of the field emitted electrons from a single pod of a ZnO tetrapod has been obtained, exhibiting a two-peak feature. The energy difference between the two peaks in the TED is found to be nearly equal to the band gap of the bulk ZnO. The results show that field emitted electrons originate from both the conduction and valence bands. The peak position dependence on the applied voltage has also been observed. In the present case, the size of the ZnO tetrapod is not small enough to reflect the quantum confinement effects.

Enforcing periodic secondary structures in hybrid peptides: a novel hybrid foldamer containing periodic gamma-turn motifs - Baruah, Pranjal K.; Sreedevi, N. K.; Gonnade, Rajesh G.; Ravindranathan, Sapna; Damodaran, Krishnan; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2007)
{This note describes the design, synthesis, and conformational studies of a novel hybrid foldamer that adopts a definite compact, three-dimensional structure determined by a combined effect of the special conformational properties of the foldamer constituents. The striking feature of this de novo designed foldamer is its ability to display periodic gamma-turn conformations stabilized by intramolecular hydrogen bonds. Conformational investigations by single-crystal X-ray studies, solution-state NMR, and ab initio MO theory at the HF/6-31G*
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

Enhanced permeability and dielectric constant of NiZn ferrite synthesized in nanocrystalline form by a combustion method - Deka, Sasanka; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2007)
The performance parameters of Ni0.5Zn0.5Fe2O4, synthesized in the nanocrystalline form by an autocombustion method, have been investigated. The sample sintered at 1200 degrees C, with Bi2O3 as additive shows a very high value of initial permeability mu'(i) of > 400 at 1 MHz, with low loss. Similarly, a very high dielectric constant is obtained at lower frequencies. The results show that optimum magnetic and electrical properties can be achieved for the NiZn ferrite nanocrystalline powders synthesized by the present autocombustion method and sintered at a relatively lower temperature of 1200 degrees C when compared with a temperature of 1400 degrees C required for the materials synthesized by the conventional ceramic method.

Enhancement of the phase transformation temperature of gamma-Fe2O3 by Zn2+ doping - Deka, Sasanka; Joy, Pattayil Alias (Journal of Materials Chemistry, 2007)
The phase transformation temperature of gamma-Fe2O3 to alpha-Fe2O3 is increased with Zn2+ doping and enhancement of the transition temperature by similar to 100 degrees C is obtained for doping of >= 15 mol% Zn in nanocrystalline gamma-Fe2O3 synthesized by an autocombustion method.

Environmentally benign catalytic hydroformylation-oxidation route for naproxen synthesis - Rajurkar, Kalpendra B.; Tonde, Sunil S.; Didgikar, Mahesh R.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Hydroformylation of 6-methoxy-2-vinylnaphthalene (MVN), using homogeneous Rh(CO)acac) as a catalyst and a chelating bidentate ligand (1,2-bis-(diphenylphosphino) ethane, dppe), followed by oxidation of the product (2-(6-methoxynaphthyl) propanal, 2-MNP) has been studied as an alternative route for the synthesis Of D,L-naproxen. The feasibility of the MVN hydroformylation route has been demonstrated, and a detailed study has been reported on the key hydroformylation step. The roles of the catalyst, ligands, and solvents, as well as the effect of reaction conditions on the reaction rate and regioselectivity of the product 2-MNP, have been investigated. With Rh(CO)2(acac) as a catalyst and dppe as a ligand, > 98% selectivity to 2-MNP (an important precursor to D,L-naproxen) has been achieved. A possible mechanism to explain the variation in regioselectivity with Rh(CO)(2)(acac) as a catalyst and dppe as a ligand has been discussed. The kinetics of the hydroformylation step has been investigated and a rate equation has been proposed. The second step in the proposed route for naproxen-the oxidation of 2-MNP to 2-(6-methoxynaphthyl) propanoic acid (2-MNPA, or naproxen) - has been studied using Na2WO4 as a catalyst and tetrabutyl ammonium hydrogen sulfate (TBAHS) as the phase-transfer catalyst with H2O2 as the oxidant for the first time. Screening of the catalysts that consisted of the early transition metals, such as salts of tungsten, vanadium, and molybdenum showed that Na2WO4 gives the best performance for the oxidation step with > 80% selectivity to 2-(6-methoxynaphthyl)propanoic acid (2-MNPA/naproxen). This study would be valuable in developing a new environmentally benign route for naproxen synthesis.

Estimation of gross calorific value of coals using artificial neural networks - Patel, Shagufta U.; Kumar, B. Jeevan; Badhe, Yogesh P.; Sharma, B. K.; Saha, Sujan; Biswas, Subhasish; Chaudhury, Asim; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Fuel, 2007)
The gross calorific value (GCV) is an important property defining the energy content and thereby efficiency of fuels, such as coals. There exist a number of correlations for estimating the GCV of a coal sample based upon its proximate and/or ultimate analyses. These correlations are mainly linear in character although there are indications that the relationship between the GCV and a few constituents of the proximate and ultimate analyses could be nonlinear. Accordingly, in this paper a total of seven nonlinear models have been developed using the artificial neural networks (ANN) methodology for the estimation of GCV with a special focus on Indian coals. The comprehensive ANN model developed here uses all the major constituents of the proximate and ultimate analyses as inputs while the remaining six sub-models use different combinations of the constituents of the stated analyses. It has been found that the GCV prediction accuracy of all the models is excellent with the comprehensive model being the most accurate GCV predictor. Also, the performance of the ANN models has been found to be consistently better than that of their linear counterparts. Additionally, a sensitivity analysis of the comprehensive ANN model has been performed to identify the important model inputs, which significantly affect the GCV. The ANN-based modeling approach illustrated in this paper is sufficiently general and thus can be gainfully extended for estimating the GCV of a wide spectrum of solid, liquid and gaseous fuels. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Artificial neural network; gross calorific value (GCV); proximate and ultimate analyses

Ethane bridged hybrid mesoporous silsesquioxanes with sulfonic acid functionalities: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Parischa, Renu; Singh, A. P. (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
Periodic mesoporous organosilicas having -CH(2)-CH(2)- groups in the framewall positions and sulfonic acid groups in the pore channels were prepared using 1,2-bis(triethoxysilyl) ethane, 3-mercaptopropyltriethoxysilane and cetyltrimethylammonium surfactant, under basic conditions, by a one-pot synthesis method. XRD, N(2) sorption isotherm and TEM analysis revealed that the mesoporous structural ordering is retained after the functionalization of organic groups while solid-state NMR techniques like (13)C CP MAS NMR and (29)Si MAS NMR show the presence of sulfonic acid groups and the stability of the mesoporous framework with integrated ethane moieties as bridging groups. The hybrid material was more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts in the Claisen-Schmidt condensation of acetophenone with benzaldehyde to form chalcone.

Excellent exo/endo-selectivity in the 1,3-dipolar cycloaddition of cyclic azomethine ylide: exploring the facile investigation of cocaine antagonists - Laha, Joydev K. (Letters in Organic Chemistry, 2007)
High exo-selectivity was achieved in the 1,3-dipolar cycloaddition of a cyclic azomethine ylide and phenyl vinyl sulfone or Opplozer's camphorsultam chiral dipolarophile leading to the synthesis of two novel tropane compounds.
Keywords: 1; 3-dipolar cycloaddition; cocaine antagonists; cyclic azomethine ylide; exo/endo-selectivity.; tropane

Exhaustive analysis of frontal copolymerization of functionalized monovinyl and divinyl monomers - Pujari, Narahari S.; Inamdar, Satish R.; Ambekar, Jalindar D.; Kulkarni, B. D.; Ponrathnam, Surendra (Chemistry-A European Journal, 2007)
A series of copolymers of 2-hydroxyethyl methacrylate (HEMA)/ glycidyl methacrylate (GMA) and ethylene dimethacrylate (EGDM) were synthesized by frontal polymerization (FP). This study was conducted to investigate the effect of crosslink density, type and concentration of initiator, the use of a complex initiator system, porogen, and diluent on the most relevant parameters of FP, such as sustainability of the front, temperature profile, front velocity, and yield. The products were also characterized for intruded pore volume, pore-size distribution, epoxy-functionality number, and surface morphology. Higher crosslink densities (CLDs) and initiator concentration produced higher front velocities, whereas no trend in front temperature was noted. A complex initiation system was effective in stabilizing and increasing the polymerization yield. Relative to suspension polymerization (SP), FP products synthesized without a solvent were microporous, whereas micro-to-macroporous products were obtained in the presence of a solvent (for HEMA-EGDM polymers). We also present, explain, and discuss the exotic patterns observed under a microscope. We observed two basic types of spatial patterns, namely, planar and nonplanar patterns. The type of planar pattern observed under scanning electron microscopy (SEM) has a spatial impulse that appears as a loop followed by regular periodic motion in the radial and axial directions. This behavior gives rise to a repeating pattern that is a few microns thick. Also, nonplanar patterns, namely, layered concentric rings and winding staircase patterns, were observed under SEM.
Keywords: copolymerization; patterns; Polymers; porosity

Expeditious assembly of 3,4-benzannulated 8-oxabicyclo[3.2.1]octane systems by [2+2+2] alkyne cyclotrimerisation: Total synthesis of (-)-bruguierol A - Ramana, Chepuri V.; Salian, Sumanth R.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2007)
Facile construction of benzene-fused 8-oxabicyclo[3.2.1]octane systems by employing a cross alkyne cyclotrimerisation reaction was explored. With this procedure, (-)-bruguierol A was synthesised, and its absolute configuration was established.
Keywords: cyclotrimerisation; epoxidation; Total synthesis; Wilkinson's catalyst

Effect of fuel and its concentration on the nature of Mn in Mn/CeO2 solid solutions prepared by solution combustion synthesis - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, Veda (Acta Materialia, 2008)
Nano and microcrystalline, Mn/CeO2 solid solutions (5 mol.% Mn) have been prepared by solution combustion synthesis using urea, glycine or polyethylene glycol (PEG) as fuel. The nature of the fuel and its concentration (fuel to metal mole ratio, F/M have a strong influence on the physical and chemical characteristics of the resulting Mn/CeO2 solid solutions. The variations in the physicochemical properties are attributed to differences in (i) the adiabatic/real flame temperature realized with these fuels at different F/M ratios; (ii) the sustenance of the temperature or the quenching effect of the fuel at higher F/M ratios; (iii) combustion or decomposition of the precursors as the main course of the reaction; and (iv) the generation of gaseous products during combustion. Since the addition of the fuel to the initial precursor solution does not change the pH of the medium, the differences in the type of Mn species formed are mainly attributed to the combustion process. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; Mn-ceria; Nanocomposites; X-ray diffraction (XRD); X-ray photoelectron spectroscopy (XPS)

Effect of gold dispersion on the photocatalytic activity of mesoporous titania for the vapor-phase oxidation of acetone - Awate, S. V.; Belhekar, Anagha A.; Bhagwat, S. V.; Kumar, R.; Gupta, N. M. (International Journal of Photoenergy, 2008)
Mesostructured titanium dioxide photocatalyst, having uniform crystallite size (6-12 nm) and average pore diameter of similar to 4.2 nm, was synthesized by using a low-temperature nonsurfactant hydrothermal route, employing tartaric acid as a templating agent. Gold additions from 0.5 to 2wt% were incorporated, either during the hydrothermal process or by postsynthesis wet impregnation. Compared to the impregnation-prepared samples, the samples synthesized hydrothermally contained smaller-size (<= 1 nm) gold clusters occluded in the pores of the host matrix. Whereas CO(2) and H(2)O were the main reaction products in UV-assisted vapor-phase oxidation of acetone using these catalysts, C(2)H(6) and HCO(2)CH(3) were also produced for higher acetone concentrations in air. The conversion of acetone was found to increase with decrease in the size of both TiO(2) and gold particles. In situ IR spectroscopy revealed that titania and gold particles serve as independent adsorption and reaction sites for acetone and oxygen molecules. Acetone molecules adsorb exclusively at TiO(2) surface, giving rise to a strongly adsorbed (condensed) state as well as to the formation of formate- and methyl formate- type surface species. Hydroxyl groups at titania surface participate directly in these adsorption steps. Nanosize gold particles, on the other hand, were primarily responsible for the adsorption and activation of oxygen molecules. Mechanistic aspects of the photochemical processes are discussed on the basis of these observations. Copyright (C) 2008.

Effect of hydrodynamic cavitation on zooplankton: a tool for disinfection - Sawant, Subhash Shivram; Anil, Arga Chandrashekar; Krishnamurthy, Venkat; Gaonkar, Chetan; Kolwalkar, Janhavi; Khandeparker, Lidita; Desai, Dattesh; Mahulkar, Amit Vinod; Ranade, Vivek Vinayak; Pandit, Aniruddha Balchandra (Biochemical Engineering Journal, 2008)
Application of hydrodynamic cavitation for disinfection of water is gaining momentum, as it provides environmentally and economically sound options. In this effort, the effect of cavitating conditions created by differential pump valve opening and that created by flowing through a cavitating element (orifice plates) on the microbes (zooplankton in sea water) is described. The experimental results are compared with modelling of cavitating conditions that includes cavity dynamics, turbulence generated by individual oscillating cavity, cell wall strength and geometrical and operating parameters of cavitation device. Theoretical model for quantifying the cavitationally generated turbulent shear and extent of microbial disinfection has been developed. Experimental results indicated that cavitation and/or turbulent fluid shear dominantly originating from cavitation are effective tools for sea water disinfection as more than 80% of the zooplankton present in the sea water were killed. It was also observed that shock waves generated due to cavitation is not the sole cause for zooplankton disruption. A correct physical mechanism accounting fluid turbulence and shear, generated from stable oscillation of cavity, significantly contribute towards the disruption. Further refinement of the model presented will serve as a basis for higher degree of disinfection and provide a practical tool for sea water disinfection. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Cell disruption; heat transfer; Hydrodynamic cavitation; Modelling; Wastewater treatment; Zooplankton

Effect of organic modifiers and silicate type on filler dispersion, thermal, and mechanical properties of ABS-Clay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Applied Polymer Science, 2008)
Acrylonitrile-butadiene-styrene (ABS)-clay composite and intercalated nanocomposites were prepared by melt processing, using Na-montmorillonite (MMT), several chemically different organically modified MMT (OMMT) and Na-laponite clays. The polymer-clay hybrids were characterized by WAXD, TEM, DSC, TGA, tensile, and impact tests. Intercalated nanocomposites are formed with organoclays, a composite is obtained with unmodified MMT, and the nanocomposite based on synthetic laponite is almost exfoliated. An unintercalated nanocomposite is formed by one of the organically modified clays, with similar overall stack dispersion as compared to the intercalated nanocomposites. T, of ABS is unaffected by incorporation of the silicate filler in its matrix upto 4 wt % loading for different aspect ratios and organic modifications. A significant improvement in the onset of thermal decomposition (40-44 degrees C at 4 wt % organoclay) is seen. The Young's modulus shows improvement, the elongation-at-break shows reduction, and the tensile strength shows improvement. Notched and unnotched impact strength of the intercalated MMT nanocomposites is lower as compared to that of ABS matrix. However, laponite and overexchanged organomontmorillonite clay lead to improvement in ductility. For the MMT clays, the Young's modulus (E) correlates with the intercalation change in organoclay interlayer separation (Delta d(001)) as influenced by the chemistry of the modifier. Although ABS-laponite composites are exfoliated, the intercalated OMMT-based nanocomposites show greater improvement in modulus. (C) 2008 Wiley Periodicals, Inc. J Appl Polym Sci 110:2374-2383, 2008
Keywords: clay; filler; mechanical; structure characterization; styrene-butadiene

Effect of repeated in vitro sub-culturing on the virulence of metarhizium anisopliae against helicoverpa armigera (Lepidoptera : Noctuidae) - Nahar, Pallavi B.; Kulkarni, Shuklangi A.; Kulye, Mahesh S.; Chavan, Santosh B.; Kulkarni, Girish; Rajendran, Armugham; Yadav, Priya D.; Shouche, Yogesh; Deshpande, Mukund V. (Biocontrol Science and Technology, 2008)
The effect of repeated conidial sub-culturing of Metarhizium anisopliae on its virulence against Helicoverpa armigera (Hbner) was studied. The LT(50) observed against third instar larvae of H. armigera for the first sub-culture was 3.4 days; it increased to 4.5 and 5.6 days for the 20th and the 40th sub-cultures, respectively. The LT50 values after passage of the 40th sub-culture on H. armigera decreased to 4.4 and 3.7 days for the 40th (first in vivo) and the 40th (fifth in vivo) passages, respectively. Similarly, the LC(50) of M. anisopliae towards third instar larvae of H. armigera increased from the first sub-culture (0.17x10(4)) to (3.0x10(4)) for the 40th conidial transfers on potato dextrose agar and again decreased to 0.74x10(4) and 0.23x10(4) in the 40th (first in vivo) and the 40th (fifth in vivo) passage, respectively. Similar trends for LC(50) and LT(50) values were seen when sugarcane woolly aphid, Ceratovacuna lanigera Zehntner was used as a host. Significant variation in appressorium formation and cuticle-degrading enzyme production such as chitinase, chitin deacetylase, chitosanase and protease during subsequent sub-culturing and passage through H. armigera was observed. Though there was no effect on internal transcribed spacer (ITS) sequence pattern, interestingly, in randomly amplified polymorphic DNA (RAPD), significant differences in the band intensities and in the banding pattern for different sub-cultures of M. anisopliae were observed. As stable virulence towards the insect pest is desirable for commercialisation of a mycoinsecticide, such changes in virulence due to repeated in vitro transfer need to be monitored and minimised.
Keywords: appressorium formation; chitin deacetylase; chitinase; Helicoverpa armigera; in vitro sub-culturing; Lipase; Metarhizium anisopliae; Protease

Effect of sintering conditions and microstructure on the magnetostrictive properties of cobalt ferrite - Bhame, Shekhar D.; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2008)
The effects of sintering temperature and dwell time on the magnetostrictive properties of polycrystalline cobalt ferrite synthesized by the conventional ceramic method have been investigated. The present study showed that the magnitude of magnetostriction strongly depends on the microstructure of the final sintered product. The presence of small and uniform grains with less porous structure in the sintered material leads to enhancement of the magnetostrictive strain. Higher magnetostriction is obtained for samples sintered at a relatively lower temperature of 1100 degrees C. These results are further corroborated by analyzing the effect of some additives during sintering on the microstructural and magnetostrictive properties.

Effect of synthesis procedure on the structure and properties of palladium/polycarbonate nanocomposites - Valmikanathan, O. P.; Ostroverkhova, O.; Mulla, Imtiaz S.; Vijayamohanan, K.; Atre, S. V. (Polymer, 2008)
In this paper, we compare two procedures for the synthesis of palladium (Pd)/polycarbonate (PC) nanocomposites as well as their morphological, optical, thermal and electrical properties. Pd nanoclusters were produced by the reduction of palladium chloride using a variation of Brust's method. Discrete I'd nanoclusters of similar to 15 nm size were formed in the absence of PC in the reaction mixture (ex situ method) while agglomeration of Pd nanoclusters was noticed in the presence of PC in the reaction mixture (in situ method). Fourier transform infrared spectroscopy (FTIR) suggests nanoparticle-polymer interactions and polymer conformational changes in the in situ nanocomposite films. Even after having the same Pd content, the ex situ nanocomposites films were found to transmit more light than the in situ nanocomposites. The glass transition temperature (T-g), decreased by similar to 16 degrees C for both the ex situ and in situ samples. Thermogravimetric analysis (TGA) indicated that the presence of Pd nanoclusters significantly improved the thermal stability of the nanocomposites, as evidenced by the enhanced onset of degradation by similar to 20 degrees C and similar to 40 degrees C for the in situ and ex situ nanocomposites, respectively. The electrical conductivity measurement shows a dramatic difference between these nanocomposites with a significantly higher value for the in situ nanocomposite (resistivity = 2.1 X 10(5) Omega m) compared to the ex situ nanocomposite (resistivity = 7.2 x 10(13) Omega m). (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: in situ and ex situ syntheses; Morphology; Nanocomposites

Effect of TDZ and 2, 4-D on peanut somatic embryogenesis and in vitro bud development - Joshi, Madhumita; Sujatha, K.; Hazra, Sulekha (Plant Cell Tissue and Organ Culture, 2008)
Failure of peanut somatic embryos to convert into plantlets is attributed to the abnormal development of the plumule. Thidiazuron (TDZ) was effective in the conversion of peanut somatic embryos to plantlets by triggering morphogenetic activity in the abnormal plumules of the rooted somatic embryos. The present study aimed to induce normal embryo differentiation by culturing the embryogenic masses in embryo development medium containing 2,4-D and various concentrations of TDZ. Although this was not achieved due to restricted somatic embryo development in the presence of TDZ, bud-like projections appeared in the embryogenic masses when these were cultured in media containing combinations of 2,4-D and TDZ. These projections developed into buds, which subsequently formed shoots and plantlets. The response varied with the concentration and exposure of TDZ. At lower concentrations, the buds appeared in a defined row in the equatorial region of the explant, and with extended incubation, more and more buds appeared in rows alongside the initial row. Induction of multiple buds in a defined row in this specific site (equatorial region) suggested the presence of potent cells around this region. At higher concentrations, these projections appeared in large numbers spread over the whole upper part of the embryogenic mass starting from the equatorial region. The ability of embryogenic mass to convert into organogenic mass and to produce large number of organogenic buds provides an excellent system for basic studies and for the genetic transformation of peanut.
Keywords: Arachis hypogaea; embyogenic mass; somatic embryogenesis; thidiazuron

Effective arsenic removal using polyacrylonitrile-based ultrafiltration (UF) membrane - Lohokare, Harshada R.; Muthu, M. R.; Agarwal, Gopal P.; Kharul, Ulhas K. (Journal of Membrane Science, 2008)
Applicability of polyacrylonitrile (PAN)-based negatively charged ultrafiltration (UF) membrane for effective arsenic removal has been demonstrated, to our knowledge, for the first time. The hydrolysis of PAN-based UF membrane surface by NaOH leading to the formation of carboxylate (-COO-) groups and reduction in initial pore size rendered As-V rejection capability by Donnan exclusion principle. A lowering in pore size was indicated by the reduction in water flux and elevation in rejection of protein and polyethylene glycol (PEG). NaOH treatment leading to formation of carboxylate group on the membrane surface was indicated by FTIR-ATR, while contact angle measurement indicated increased hydrophilicity. This treatment rendered membrane surface smoothening as confirmed by SEM and AFM analyses. The molecular weight cut off after the NaOH treatment was found to be similar to 6 kDa. The rejection of pentavalent arsenic (As-V) by these surface modified membranes was studied with different feed concentration, cross-flow velocity, pressure, temperature and pH. Experiments with 50 ppb As-V in feed showed that arsenic rejection was close to 100% and remained constant up to 6 h. Feed sample concentration of 1000 ppb and 50 ppm of As-V showed >95% rejection at pH 7 and room temperature, but for 1000 ppm feed concentration, the rejection was 40-65%. For concentrations <= 50 ppm of arsenic in the feed, the rejection coefficient was not dependent on cross-flow velocity or transmembrame pressure. The rejection for 1000 ppm. concentration of As-V varied from 40 to 65% with variation in the cross-flow velocity and transmembrane pressure as the concentration polarization was important. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; concentration polarization; cross-flow velocity; Polyacrylonitrile; surface modification; Ultrafiltration

Efficacy of 4-methyl-7-hydroxy coumarin derivatives against vectors aedes aegypti and culex quinquefasciatus - Deshmukh, Madhavi; Pawar, Pushpa; Joseph, Mary P.; Phalgune, Usha; Kashalkar, Rajashree; Deshpande, Nirmala R. (Indian Journal of Experimental Biology, 2008)
4-Methyl-7-hydroxy coumarin is considered as a lead molecule as a biopesticide. Its mono bromo and tribromo derivatives were synthesized. Two more derivatives were synthesized by acylation. Compound 1 (3.6,8-tribromo-7-hydroxy-4-methyl-chromen-2-one) was found to be the most potent against IV(th) instar larvae of C. quinquefasciatus and A. aegypti the LC(50) being 1.49 and 2.23 ppm respectively. It showed 100% larval mortality at 25 ppm against A. aegypti and at 10 ppm against C. quinquefasciatus. Compounds 1 and 2 (3,6,8-tribromo-7-hydroxy-4-methyl-chromen-2'-oxo-2H-chromen-7-yl acetate) showed remarkable ovicidal activity. Significant reduction of 80-85%, hatching of eggs of both mosquito species was observed at the highest dose of 100 ppm. The hatched larvae showed 100% mortality in the successive instars. Compounds 3 and 4 (3-bromo-7-hydroxy-4-methyl-chromen-2-one and 3-bromo-4-methyl-2'-oxo-2H-chromen-7-yl acetate) showed moderate activity against both mosquito species.
Keywords: 4-Methyl-7-hydroxy coumarin; Aedes aegypti; Culex quinquefasciatus; Larval mortality; Ovicidal activity

Efficient and eco-friendly synthesis of 2-amino-1,3-selenazoles in an ionic liquid/water system under ambient conditions - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Arkivoc, 2008)
An efficient and eco-friendly synthesis of 2-amino-1,3-selenazoles in ionic liquid/water solvent system is described. The paper describes synthesis of 2-amino-1,3-selenazoles by condensation of various phenacyl bromide with selenourea under ambient conditions in short reaction times. This protocol has notable advantages such as the absence of any added catalyst, simple operation and excellent yields of products and recyclability of the ionic liquid.
Keywords: 2-Amino-1; 3-selenazoles; ambient conditions; heterocycles; ionic liquid/water system; selenoureas; substituted phenacyl bromide

Efficient method for the synthesis of acylals from aldehydes under solvent-free conditions catalyzed by antimony trichloride - Bhattacharya, Asish K.; Mujahid, Mohammad; Natu, Arvind A. (Synthetic Communications, 2008)
A mild and efficient method has been developed for the preparation of acylals from aldehydes catalyzed by antimony trichloride under solvent-free conditions in very good to excellent yields. The easy availability, low cost, and ease of handling of the catalyst make this procedure especially attractive for large-scale synthesis.
Keywords: acetic anhydride; Acylals; aldehydes; antimony trichloride; solvent-free conditions

Efficient route towards the covalent functionalization of single walled carbon nanotubes - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Applied Surface Science, 2008)
A simple and efficient method of chemical functionalization of both single and multiwalled carbon nanotubes has been discussed to give enhanced water solubility by rapidly and efficiently generating an appreciable amount of hydrophilic functional groups using microwave radiation. Surface functionalization containing more than 30 wt% of oxygen has been achieved, resulting into solubility of 2-5 mg/mL. Further covalent functionalization of such soluble SWNTs provides a remarkable degree of aniline functionalization through amidation, where the formation of polyaniline has been avoided. Functionalization of SWNTs is confirmed by techniques like electron microscopy, Fourier transform infrared spectroscopy, thermogravimetry, Raman spectroscopy, cyclic voltammetry and impedance spectroscopy. Electrochemical analysis suggests an enhanced double layer capacitance (similar to 110 F/g) of nanotubes after microwave treatment. Aniline functionalization of SWNTs shows possible variations on the nanotube topography with concomitant formation of a dynamic polymer layer on the nanotube surface. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Carbon nanotubes; Functionalization; Microwave; solubility

Efficient synthesis of 1,8-dioxo-octahydro-xanthene derivatives promoted by a room temperature ionic liquid at ambient conditions under ultrasound irradiation - Venkatesan, K.; Pujari, Suresh S.; Lahoti, Rajgopal J.; Srinivasan, K. V. (Ultrasonics Sonochemistry, 2008)
The condensation reaction involving an aldehyde and diketone was efficiently promoted by the Ionic liquid, [Hbim]BF(4) (IL) as a reaction medium with methanol as co-solvent at ambient temperature under ultrasonic irradiation to afford the corresponding 1,8-dioxo-octahydroxantliene (xanthene) derivatives in excellent yields. The advantages of this method include among others the use of a recyclable, non-volatile ionic liquid, which promotes this protocol under ambient temperature without the requirement of ally added catalyst. The reaction times and yields are compared with p-TSA catalyzed synthesis of xanthenes under thermal conditions, which is also reported for the first time under our reaction conditions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: aldehydes; ambient conditions; Bronsted acidity; dimedone; Ionic liquid; Ultrasound; Xanthenes

Efficient synthesis of antifungal pyrimidines via palladium catalyzed Suzuki/Sonogashira cross-coupling reaction from Biginelli 3,4-dihydropyrimidin-2(1H)-ones - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Deshpande, Mukund V.; Srinivasan, Kumar V. (Tetrahedron, 2008)
An efficient regioselective approach to the synthesis of tetrasubstituted pyrimidines was developed by sequential functionalization of easily available Biginelli 3,4-dihydropyrimidine-2(1H)-ones via dehydrogenation, chlorination followed by palladium catalyzed C-C Suzuki/Sonogashira coupling reaction. All the synthesized compounds were evaluated in vitro for their antifungal activities against Candida albicans, Cryptococcus neoformans, Benjaminiella poitrasii, Yarrowia lipolytica, and Fusarium oxysporum, and antibacterial activities against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activities; Biginelli compounds; chlorination; Oxidation; Pyrimidines; Suzuki coupling

Efficient synthesis of quinoxalines in the ionic liquid 1-n-butylimidazolium tetrafluoroborate ([Hbim]BF4) at ambient temperature - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Quinoxaline derivatives have been synthesized in excellent yields using an ionic liquid (IL) (viz., 1-n-butylimidazolium tetrafluoroborate) as a reaction medium as well as promoter from various 1,2-diketones and aryl-1,2-diamines. The process is general for the synthesis of quinoxaline derivatives from aromatic as well as aliphatic-1,2-diketones. The advantages of the present method are ambient reaction temperature, simplicity of operation, high yields of products, the recyclability of the IL, and ecofriendly nature of the reaction medium.
Keywords: 1; 2-diamines; 2-Diketones; Aryl-1; ionicliquid(IL); quinoxalines

Efficient total synthesis of decarestrictine D - Guptali, Priti; Kumar, Pradeep (European Journal of Organic Chemistry, 2008)
An efficient total synthesis of decarestrictine D has been achieved using cross-metathesis or ring-closing metathesis and Yamaguchi macrolactonization as key steps. The stereogenic centres were generated by means of hydrolytic kinetic resolution (HKR) and Sharpless asymmetric dihydroxylation (AD).
Keywords: Cross metathesis; Hydrolytic kinetic resolution; Macrolides; Ring-closing metathesis; sharpless asymmetric dihydroxylation

Electric field induced, superhydrophobic to superhydrophilic switching in multiwalled carbon nanotube papers - Kakade, Bhalchandra A.; Mehta, Rutvik; Durge, Apurva; Kulkarni, Sneha; Pillai, Vijayamohanan (Nano Letters, 2008)
Superhydrophobic multiwalled carbon nanotube bucky paper, fabricated after ozonolysis, shows fascinating electrowetting behavior, which could be remarkably tuned by changing key solution variables like the ionic strength, the nature of the electrolyte, and the pH of the water droplet. More significantly, the droplet behavior can be reversibly switched between superhydrophobic, Cassie-Baxter state to hydrophilic, Wenzel state by the application of an electric field, especially below a threshold value.

Electric field response of molecular reactivity descriptors: a case study - Kar, Rahul; Pal, Sourav (Theoretical Chemistry Accounts, 2008)
In the present article, we study the influence of external electric field on the density-based global and local reactivity descriptors using examples of some planar nonlinear polyatomic molecules with C-2V point group symmetry. The study mainly involves the application of weak electric field in a direction along the principal axis and along its perpendicular direction. We also discuss the strength of the electric field studied in this work in terms of the strength of the molecular interaction. The work is expected to throw light on the effect of interactions within the above range on reactivity descriptors. Results are presented for a few prototype molecules.
Keywords: electric field; molecular interaction; planar nonlinear polyatomic molecules; Reactivity descriptors

Electrochemical sensing of sulphur dioxide: a comparison using dodecanethiol and citrate capped gold nanoclusters - Sathe, Bhaskar R.; Risbud, Mandar S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Nanoscience and Nanotechnology, 2008)
A comparison of cyclic voltammograms of dodecanethiol (DDT) capped Au nanoclusters (5.0 +/- 0.5 nm) and trisodium citrate (Cit) capped Au nanoclusters (similar to 10-15 nm) modified glassy carbon electrode shows a dramatic variation in the current when exposed to a small amount of sulphur dioxide. This is explained using the electrocatalytic properties of Au nanoclusters towards the oxidation of SO2, thus facilitating the fabrication of electrochemical sensors for the detection of SO2. The intrinsic redox changes observed for gold nanocluster-modified glassy carbon electrodes disappear on passing SO2, despite a dramatic current increase, which indeed scales up with the amount of dissolved SO2. Interestingly, a complete rejuvenation of the redox behavior of gold is also observed on subsequent removal of SO2 from the solution by passing pure nitrogen for 15 minutes. Further, these nanoclusters when characterized with X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) after SO2 passage reveal a variety of SO2 adsorption modes on gold surface. XP spectra also show a shift of 1.03 eV towards higher binding energy indicating a strong adsorption of SO2 gas, while FTIR gives conclusive evidence for the interaction of SO2 with gold nanoparticles.
Keywords: cyclic voltammetry; Fourier transform infrared spectroscopy; monolayer protected gold nanoclusters (Au-MPCs); SO2 sensor; X-ray photoelectron spectra

Enantioselective hydrogenation of olefins by chiral iridium phosphorothioite complex covalently anchored on mesoporous silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
Chiral monodentate phosphorous-based ligands have proven effective for the enantioselective hydrogenation of olefins. Binol-derived monodentate phosphorothioite (PS) ligand was synthesized from binol and thiopropyltriethoxysilane, and its iridium complex was covalently anchored to mesoporous silica supports like SBA-15, MCM-41, and MCM-48. These catalysts were characterized by different physicochemical techniques and assessed for their catalytic performances in the heterogeneous asymmetric hydrogenation of itaconic acid and its derivatives. It was found that the catalytic activities and enantioselectivities of the heterogenized iridium complex (IrPSSBA-15) in the hydrogenation reactions were comparable to its homogeneous analogue. Binol-derived monodentate phosphorothioite ligand in heterogeneously anchored form (iridium complex) is a more effective catalyst than the reported monodentate phosphorous ligand systems in the hydrogenation reactions, possibly due to the changes in electronic properties around the iridium metal center. The effects of substrate-to-catalyst molar ratio, solvents, and temperature on substrate conversions and enantioselectivities, of the products were investigated in hydrogenation reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: binol; Enantioselective hydrogenation; Immobilization; iridium complex; itaconic acid; Mesoporous silica SBA-15; monodentate ligand; phosphorothioite ligand

Energy-efficient syngas production through, catalytic oxy-methane reforming reactions - Choudhary, Tushar V.; Choudhary, Vasant R. (Angewandte Chemie-International Edition, 2008)
Keywords: fuels; heterogeneous catalysis; methane activation; Partial oxidation; Syngas

Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds

Enhanced field emission from hexagonal rhodium nanostructures - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Late, Dattatray J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2008)
Shape selective synthesis of nanostructured Rh hexagons has been demonstrated with the help of a modified chemical vapor deposition using rhodium acetate. An ultralow threshold field of 0.72 V/mu m is observed to generate a field emission current density of 4 x 10(-3) mu A/cm(2). The high enhancement factor (9325) indicates that the origin of electron emission is from nanostructured features. The smaller size of emitting area, excellent current density, and stability over a period of more than 3 h are promising characteristics for the development of electron sources. (C) 2008 American Institute of Physics.

Enhanced shape anisotropy and magneto-optical birefringence by high energy ball milling in NixFe1-xFe2O4 ferrofluids - Nair, Swapna S.; Xavier, Francis; Joy, Pattayil Alias; Kulkarni, S. D.; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2008)
Ferrofluids belonging to the series NixFe1-xFe2O4 were synthesised by two different procedures-one by standard co-precipitation techniques, the other by co-precipitation for synthesis of particles and dispersion aided by high-energy ball milling with a view to understand the effect of strain and size anisotropy on the magneto-optical properties of ferrofluids. The birefringence measurements were carried out using a standard ellipsometer. The birefringence signal obtained for chemically synthesised samples was satisfactorily fitted to the standard second Langevin function. The ball-milled ferrofluids showed a deviation and their birefringence was enhanced by an order. This large enhancement in the birefringence value cannot be attributed to the increase in grain size of the samples, considering that the grain sizes of sample synthesised by both modes are comparable; instead, it can be attributed to the lattice strain-induced shape anisotropy(oblation) arising from the high-energy ball-milling process. Thus magnetic-optical (MO) signals can be tuned by ball-milling process, which can find potential applications. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: birefringence; Co-precipitation; ferrofluid; HEBM

Enhancement of glycerol conversion to acetol in high-temperature liquid water by high-pressure carbon dioxide - Yamaguchi, Aritomo; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2008)
Dehydration of glycerol to acetol proceeded in high-temperature liquid water at 573 K in a batch reactor. The acetol formation rate increased with an addition of high-pressure carbon dioxide.

Environment friendly crosslinked chitosan as a matrix for selective adsorption and purification of lipase of aspergillus niger - Trimukhe, K. D.; Mahadik, N. D.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2008)
Chitosan and its derivatives have been used as affinity matrices for purification of lipase from Aspergillus niger NCIM 1207. Trimellitic anhydride (TMA)-crosslinked deacetylated chitin adsorbed lipase selectively, yielding approximately 5-fold purification of the crude lipase with 70% yield. Further 9-fold purification occurred on eluting through Sephacryl-100. These results suggest that chitosan derivatives can be used as inexpensive biopolymer matrices for the purification of lipases for industrial applications. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Chitosan; Lipase; Matrix; Purification

EPR and DRS evidence for NO2 sensing in Al-doped ZnO - Navale, Shalaka C.; Ravi, V.; Srinivas, D.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2008)
Zinc oxide (ZnO) is a well-known semiconducting multifunctional material wherein properties right from the morphology to gas sensitivity can be tailor-made by doping or surface modification. Aluminum (Al)-incorporated porous zinc oxide (AI:ZnO) exhibits good response towards NO2 at low-operating temperature. The NO2 gas concentration as low as 20 ppm exhibits S = 17% for 5 wt. % Al-incorporated ZnO. The NO2 response increases with operating temperature and concentration and reaches to its maximum at 300 degrees C without any interference from other gases such as SO3, HCl, LPG and alcohol. Physico-chemical characterization likes differential thermogravimetric analysis (TG-DTA) electron paramagnetic resonance (EPR) and diffused reflectance spectroscopy (DRS) have been used to understand the sensing behavior for pure and A]-incorporated ZnO. The TG-DTA depicts formation of ZnO phase at 287 degrees C. The EPR study reveals distinct variation for O- (g=2.003) and Zn interstitial (g = 1.98) defect sites in pure and Al:ZnO. The DRS studies elucidate signature of adsorbed NO, species in aluminium-incorporated zinc oxide indicating its tendency to adsorb these species even at low temperatures. This paper is an attempt to correlate the gas sensing behavior with the physico-chemical studies such as EPR and DRS. (c) 2007 Published by Elsevier B.V.
Keywords: aluminum doping; DRS; EPR; NO2 sensor; ZnO

Erosion of a granular bed driven by laminar fluid flow - Lobkovsky Alexander E.; Orpe, Ashish V.; Molloy, Ryan; Kudrolli, Arshad; Rothman, D. H. (Journal of Fluid Mechanics, 2008)
Motivated by examples of erosive incision of channels in sand, we investigate the motion of individual grains in a granular bed driven by a laminar fluid to give us new insights into the relationship between hydrodynamic stress and surface granular flow. A closed cell of rectangular cross-section is partially filled with glass beads and a constant fluid flux Q flows through the cell. The refractive indices of the fluid and the glass beads are matched and the cell is illuminated with a laser sheet, allowing us to image individual beads. The bed erodes to a rest height hr which depends on Q. The Shields threshold criterion assumes that the non-dimensional ratio θ of the viscous stress on the bed to the hydrostatic pressure difference across a grain is sufficient to predict the granular flux. Furthermore, the Shields criterion states that the granular flux is non-zero only for θ > θc. We find that the Shields criterion describes the observed relationship hr ∝ Q1/2 when the bed height is offset by approximately half a grain diameter. Introducing this offset in the estimation of θ yields a collapse of the measured Einstein number q* to a power-law function of θ − θc with exponent 1.75 ± 0.25. The dynamics of the bed height relaxation are described well by the power-law relationship between the granular flux and the bed stress.

Ethyl cyanoacetate - a versatile reagent - Mrunali, Kale S. (Research Journal of Chemistry and Environment, 2008)
Ethyl cyanoacetate is widely used as an active methylene reagent in variety of condensation reactions. It also plays a very important role in organic synthesis as well as in medicinal chemistry due to ease formation of C-C bond formations reactions.

Expeditious one-step entry to the tetracyclic core of integrastatins - Ramana, C. V.; Reddy, Challa Nageswara; Gonnade, Rajesh G. (Chemical Communications, 2008)
Herein we describe a one-step assembly of structurally complex small molecules representing the central skeleton of integrastatins by employing a simple pinacol transform.

Experimental analysis of the lift force on bubbles in a swarm - Kulkarni, Amol A. (Chemical Engineering Science, 2008)
The lift force acting on bubbles in a swarm has been estimated by analyzing the instantaneous velocity-time data obtained using LDA in a cylindrical bubble column. Phase distinction was achieved through the multiresolution analysis of the velocity-time data. Several important issues related to the transverse motion of bubbles subjected to a shear field have been discussed quantitatively. The actually measured bubble sizes, the respective slip velocity values in transverse and axial directions and the local shear rates (gamma) enabled the verification of known formulations for the lift coefficient (C-L) for bubbles. At many locations in the column the radial flux of the gas phase by turbulent dispersion and the radial slip were estimated. The radially inward movement of bubbles from low to high axial velocity (from column wall to center, i.e., C-L < 0) was observed at most of the measurement locations. The local lift coefficient was estimated using the transverse drag force and the values support the results from the material balance approach. The estimated C-L values showed a wide variation over the column cross-section. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bubble; Bubble column; bubble size; hydrodynamics; LDA; lift force

Extracellular bacterial synthesis of protein-functionalized ferromagnetic Co3O4 nanocrystals and imaging of self-organization of bacterial cells under stress after exposure to metal ions - Kumar, Umesh; Shete, Ashvini; Harle, Arti S.; Kasyutich, Oksana; Schwarzacher, W.; Pundle, Archana; Poddar, Pankaj (Chemistry of Materials, 2008)
Co3O4, which crystallizes in the spinet phase at temperatures much higher than ambient temperatures, orders antiferromagnetically below its Neel temperature (similar to 40 K). However, in nanosize, it shows ferromagnetic ordering due to surface canting, disorder, imperfect oxygen atom coordination, etc. Here, for the first time, we report the synthesis of single-crystalline, ferromagnetic Co3O4 nanoparticles functionalized with proteins (size 5-7 nm) using cobalt acetate as precursor at room temperature in aqueous medium by a metal-tolerant marine bacterium isolated from the coast of the Arabian Sea. Energetically unfavorable change in the oxidation state of Co atoms from (+2 to +3) during synthesis by the bacterial strain was evidenced by X-ray photoelectron spectroscopy. The effect on the morphology of bacterial cells after exposure to the cobalt acetate was imaged by scanning electron microscopy showing cooperative, self-organized. structured colony formation, possibly due to the interbacterial communication under external stress.

Extracellular synthesis of crystalline silver nanoparticles and molecular evidence of silver resistance from morganella sp.: towards understanding biochemical synthesis mechanism - Parikh, Rasesh Y.; Singh, Sanjay; Bhagavatula L. V. Prasad; Patole, Milind S.; Sastry, Murali; Shouche, Yogesh S. (ChemBioChem, 2008)
There has been significant progress in the biological synthesis of nanomaterials. However, the molecular mechanism of synthesis of such bio-nanomaterials remains largely unknown. Here, we report the extracellular synthesis of crystalline silver nanoparticles (AgNPs) by using Morganella sp., and show molecular evidence I of silver resistance by elucidating the synthesis mechanism. The AgNPs were 20 +/- 5 nm in diameter and were highly stable at 1 room temperature. The kinetics of AgNPs formation was investigated. Detectable particles were formed after on hour of reaction, and their production remained exponential up to 18 h, and saturated at 24 h. Morganella sp. was found to be highly resistant to silver cations and was able to grow in the presence of more than 0.5 mm AgNO3. Three gene homologues viz. silE, silP and silS were identified in silver-resistant Morganella sp. The homologue of silE from Morganella sp. showed 99% nucleotide sequence similarity with the previously reported gene, silE, which encodes a periplasmic silver-binding protein. The homologues of silP and silS were also highly similar to previously reported sequences. Similar activity was totally absent in closely related Escherichia coli; this suggests that a unique mechanism of extracellular AgNPs synthesis is associated with silver-resistant Morganella sp. The molecular mechanism of silver resistance and its gene products might have a key role to play in the overall synthesis process of AgNPs by Morganella sp. An understanding of such biochemical mechanisms at the molecular level might help in developing an ecologically friendly and cost-effective protocol for microbial AgNPs synthesis.
Keywords: Biosynthesis; Morganella sp.; Nanoparticles; sil gene homologues; Silver

Effect of chirality of L/D-proline and prochiral glycine as the linker amino acid in five-atom linked thymidinyl-(alpha-aminoacid)-thymidine dimers - Seema Bagmare; D'Costa, Moneesha; Kumar, Vaijayanti A. (Chemical Communications, 2009)
The chirality of the amide linker in dimer blocks was found to have a profound effect on the orientation of base stacking interactions as studied by CD and NMR spectroscopy.

Effect of cultural conditions and media constituents on production of penicillin V acylase and CTAB treatment to enhance whole-cell enzyme activity of rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Singh, Sanjay; Poddar, Pankaj; Prabhune, Asmita; Pundle, Archana (Applied Biochemistry and Biotechnology, 2009)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme as it plays a vital role in the manufacture of semi-synthetic beta-lactam antibiotics. Rhodotorula aurantiaca (NCIM 3425) produced high levels of intracellular penicillin V acylase after 18 h at pH 8.0 and temperature 27 degrees C. Fructose was the best carbon source for PVA production, whereas tryptone was the best nitrogen source to produce the enzyme up to 170 and 1,088 IU/l of culture, respectively. Additionally, the cell-bound PVA activity was enhanced on treatment with cationic detergent. Whole-cell activity was found to be doubled (204%) on treatment of 0.01 g dry weight of cells with 50 mu g/ml solution of N-cetyl-N,N,N-trimethylammoniumbromide at pH 8.0 for 1 h at room temperature. Atomic force microscopy images of permeabilized cells show perturbation in the cell wall and offer first-ever visual illustration of surface structure modifications that occur during permeabilization of R. aurantiaca cells leading to enhancement in activity of intracellular enzyme.
Keywords: Atomic force microscopy; Intracellular enzyme; Penicillin Vacylase; Permeabilization; Rhodotorula aurantiaca

Effect of different operational conditions on the decolorization of molasses spent wash using once developed soil inoculum - Adikane, H. V.; Dixit, J. N. (Biodegradation, 2009)
A stirred vessel coupled with membrane unit containing cellulose acetate (0.45 mu m) membrane was used to study the decolorization of anaerobically digested molasses spent wash (MSW). The soil collected from the MSW disposal site was used as inoculum to study the decolorization without addition of any additives. The same inoculum was used over a period of 163 days at room temperature to study the decolorization of 12.5-50% (v/v) MSW using different operational conditions. The reactor was entered in to the inhibition mode after the feeding of 50% MSW, which was restored 100% without changing any operational condition. The maximum decolorization obtained for 12.5% (v/v) MSW was 77.22 +/- A 0.13%. The decolorization achieved for 25, 37.5, and 50% (v/v) MSW was 70.41 +/- A 0.12, 56.47 +/- A 0.17, and 48.78 +/- A 0.09%, respectively. Increase in the utilization of protein and reducing sugar was observed up to 25% MSW whereas, higher concentration showed decrease in the utilization. Results indicate 63% removal of chemical oxygen demand for 12.5% (v/v) MSW. Membrane flux which was significantly reduced after the feeding of 50% MSW was regenerated without changing the washing procedure, however, 35% decrease in sample flux was observed over the continuous use of membrane for the period of 198 days.
Keywords: Decolorization; Membrane flux; Molasses spent wash; Soil as inoculum; stirred vessel

Effect of flow structures on heat transfer in single and multiphase jet reactors - Deshpande, Sagar S.; Mathpati, Channamallikarjun S.; Gulawani, Sagar S.; Joshi, Jyeshtharaj B.; Kumar, V. Ravi (Industrial & Engineering Chemistry Research, 2009)
High frequency experimental measurements by hot film anemometry (HFA) of liquid velocities and temperature in the region of vapor-liquid (VL) and solid-liquid (SL) interfaces for two important reactor types, namely, condensation jet and jet loop reactors, have been studied for their heat transfer characteristics. An algorithm for flow structure identification has been devised from velocity data based oil (i) zero crossings and (ii) continuous wavelet transform. The wavelet transform algorithm is especially found to be useful in accurately estimating both the age and size distributions of eddies near interfaces in a multiscale framework Using these distributions, it is shown that the calculated values of heat transfer coefficients (HTC) at the SL and VL interfaces show remarkable correspondence with the HTC values obtained experimentally from instantaneous temperature measurements. For this purpose, a modified capacitance model has been proposed that takes into account the information about both the age and size distributions. The results obtained by the present methodology show the improvement possible for calculating the HTC at interfaces when compared with the earlier surface renewal models. It may therefore be used to study the interaction between flow dynamics and heat transfer behavior in chemical process equipment

Effect of gamma-dose rate on crystallinity and morphological changes of gamma-sterilized biomedical polypropylene - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2009)
The present work is aimed to study the changes in crystallinity and morphology of biomedical polyolefins after gamma-sterilization. The isotactic polypropylene (iPP) films were sterilized by gamma-radiation and the changes were characterized by differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and atomic force microscopy (AFM) techniques. The effect of dose rate on crystallinity changes also was focused. It was found that crystallinity and morphology significantly changed with gamma-irradiation. There was an increase in crystallinity Lip to 10 kGy accompanied with decrease in viscosity and mechanical properties. The changes in crystallinity mainly depend on gamma-irradiation dose and dose rate. The rise in crystallinity was attributed to chain scission and forming new perfect lamellae. However, the reduction was accompanied by occurrence of gamma- and beta-phases and crosslinking. Possible explanations for transitions in phases are also discussed based on our results. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Crystallinity; Dose rate; Gamma radiation; mechanical properties; Morphology; polypropylene

Effect of nickel nanofillers on the dielectric and magnetic properties of composites based on rubber in the X-band - Jamal, E. Muhammad Abdul; Mohanan, P.; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Applied Physics A-Materials Science & Processing, 2009)
Nickel-rubber nanocomposites were synthesized by incorporating ferromagnetic nickel nanoparticles in a natural rubber as well as neoprene rubber matrix. Complex dielectric permittivity and magnetic permeability of these composites were evaluated in the X-band microwave frequencies at room temperature using cavity perturbation technique. The dielectric loss in natural rubber is smaller compared to neoprene rubber. A steady increase in the dielectric permittivity is observed with increase in the content of nickel in both the composites. The magnetic permeability exhibits a steady decrease with increase in frequency and magnetic loss shows a relaxation at 8 GHz. The suitability of these composites as microwave absorbers is modeled based on the reflection loss which is dependant on the real and imaginary components of the complex dielectric permittivity and magnetic permeability.

Effect of organic solvents on cell-bound penicillin V acylase activity of erwinia aroideae (DSMZ 30186): a permeabilization effect - Kumar, Atul; Pundle, Archana (Journal of Molecular Catalysis B-Enzymatic, 2009)
Erwinia aroideae (DSMZ 30186) is a potential microbial culture to produce intracellular penicillin V acylase (PVA). The whole cell PVA activity was improved by permeabilization with various organic solvents. The cell-bound PVA activity showed an eightfold increase upon treatment with chloroform (5 mu L/mg(dry) (biomass)) for 10 min and diethyl ether (10 mu L/mg(dry) (biomass)) for 45 min. Hexane, toluene, ethyl acetate and dichloromethane enhanced the enzyme activity up to two-, six-, four- and two-fold, respectively; whereas, PVA activity declined drastically on permeabilization with acetone, pyridine and alcohols. The physicochemical properties of the organic solvents used for permeabilization were correlated with the change in activity. It was found that solvents with high hydrophobicity (log P > 0.68) and lower dielectric constant (< 9) were relatively effective in increasing PVA activity. These results allow systematic selection of suitable solvent for best performance. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: dielectric constant; Erwinia aroideae; Hydrophobicity; Organic solvents; Penicillin V acylase; Permeabilization

Effect of relative humidity and sea level pressure on electrical conductivity of air over Indian ocean - Pawar, S. D.; Murugavel, P.; Lal, D. M. (Journal of Geophysical Research-Atmospheres, 2009)
The electrical conductivity measured over the Indian Ocean (15 degrees N, 77 degrees E to 20 degrees S, 58 degrees E) during the Indian Ocean Experiment (INDOEX-1999) from 20 January to 12 March 1999 has been analyzed. The conductivity values over two oceanic regions, one with very low aerosol concentration and another with very high aerosol concentration, are studied in relation with meteorological parameters such as relative humidity and sea level pressure. The average conductivity is as low as 0.295 x 10(-14) Sm-1 in the region of high aerosol concentration and it is 0.783 x 10(-14) Sm-1 in the region of very low aerosol concentration. In both the regions, conductivity shows an inverse relation with relative humidity and this effect is more in the presence of high aerosol concentration. The hydrate growth of aerosol particles in high-humidity condition may be responsible for the inverse relation between conductivity and relative humidity. Size distributions of aerosol particles measured in the same cruise during high-humid conditions are also analyzed to show that sizes, rather than numbers, of aerosol particles increase with an increase in humidity. The relationship between conductivity and sea level pressure in these two regions is also studied and it shows good correlation in the region where the background aerosol concentration is low and no correlation in the region where aerosol concentration is high. The inverse relation between sea level pressure and electrical conductivity is attributed to the possible transportation of ultrafine particles from free troposphere, with subsiding motions associated with high pressure. The positive correlation between ultrafine particles and sea level pressure supports this idea.

Effect of sintering temperature and thermoelectric power studies of the system MgFe2-xCrxO4 - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Gavali, L. V.; Sasikala, R.; Mulla, Imtiaz S. (Solid State Sciences, 2009)
Mixed metal oxides showing the spinel structure exhibit interesting structural and electrical properties. Substances with specific compositions in the system MgFe2-xCrxO4 were synthesized by the simple co-precipitation method and have been investigated by X-ray diffraction (XRD) and scanning electron microscope (SEM) to study the effect of temperature on the size of particles and grains. The infrared spectrum shows, two strong bands around 600 and 500 cm(-1). An elemental composition of one of the samples, MgFeCrO4 was found by energy dispersive X-ray spectroscopy (EDS). The thermoelectric power measurements carried out from room temperature to 500 degrees C, show both n-type and p-type behavior. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: synthesis; Temperature effect; Thermoelectric studies

Effects for the incorporation of five-atom thioacetamido nucleic acid (TANA) backbone on hybridization thermodynamics and kinetics of DNA duplexes - Kaur, Harleen; Arora, Amit; Gogoi, K.; Solanke, P.; Gunjal, Anita D.; Kumar, Vaijayanti A.; Maiti, Souvik (Journal of Physical Chemistry B, 2009)
Thermodynamic studies of nucleic acids serve not only to widen our understanding on the nature and strength of forces that stabilize nucleic acids in a myriad of structural states they assume but also to facilitate the development of databases that could be used to predict the stability and selectivity of probe/primer-sets required in a broad range of nucleic acid-based diagnostic and therapeutic protocols. In the current study, we investigated the effect of a novel, backbone-modified ``thioacetamido linkage'' (TANA) on thermodynamics of hybridization, binding kinetics, and conformation of a DNA duplex. The modification comprises of an extended five-atom amide (N3'-CO-CH(2)-S-CH(2)) linker, as opposed to four-atom phosphodiester linker backbone present in DNA. One to three TANA-substitutions have been introduced in the linker backbone of two thymidine residues of one of the strand of the DNA duplex. Using spectroscopic and calorimetric techniques, we observed that TANA destabilizes the DNA helix by lowering the favorable enthalpy parameter of duplex formation. TANA center dot DNA duplexes were found to adopt a conformation toward an A-type duplex as shown by circular dichroism spectroscopy studies. Analysis of differential scanning calorimetry data indicated a nonzero heat capacity change, Delta C(p), accompanying the duplex formation. The average Delta C(p) change per duplex was found to be 832.5 cal mol(-1) K(-1), giving an average base-pair change of 59.5 cal (mol of base pairs)(-1) K(-1). Hybridization kinetic measurements using surface plasmon resonance indicated a decrease in binding affinity parameter (K(A)) that originates from higher dissociation rate constants (k(d)). Furthermore, optical melting studies showed that increasing the number of modifications results in a modest change in the number of counterions taken up during duplex formation.

Efficient formal synthesis of (S)-dapoxetine from enantiopure 3-hydroxy azetidin-2-one - Chincholkar, Pinak M.; Kale, Ajaykumar S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2009)
An efficient formal synthesis of S-(+) dapoxetine starting from 3-hydroxy azetidin-2-one is described. The intermediate (S)-3-(dimethyl amino)-3-phenylpropan-1-ol was synthesized in enantiopure form starting with 3-hydroxy azetidin-2-one in seven steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Azetidin 2 ones; beta-Lactams; Enantioselective synthesis; reduction; Staudinger reaction

Efficient gamma-Fe2O3 catalyst for liquid phase air oxidation of p-hydroxybenzyl alcohol under mild conditions - Garade, Ajit C.; Bharadwaj, M.; Bhagwat, S. V.; Athawale, A. A.; Rode, C. V. (Catalysis Communications, 2009)
gamma-Fe2O3 (maghemite) particles were synthesized at 5 degrees C (LT, low temperature) and 95 degrees C (HT, high temperature) using a simple chemical protocol. The major reflection in XRD was observed to be of the gamma-Fe2O3 phase which was further supported by the XPS analysis. Fe3+ species were responsible for initiation of the oxidation of p-hydroxybenzyl alcohol. SEM revealed that the morphologies of the catalysts were different for samples prepared at two different temperatures. gamma-Fe2O3 (LT) showed the highest catalyst activity (84% conversion) for liquid phase air oxidation of p-hydroxybenzyl alcohol with 94% selectivity to the oxidation products at 370 K and ambient pressure conditions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Air oxidation; gamma-Fe2O3; p-Hydroxybenzaldehyde; p-Hydroxybenzyl alcohol; scanning electron microscopy

Efficient, rapid, and regioselective bromination of anilines and phenols with 1-butyl-3-methylpyridinium tribromide as a new reagent/solvent under mild conditions - Borikar, Sanjay P.; Daniel, Thomas; Paul, Vincent (Tetrahedron Letters, 2009)
1-Butyl-3-methylpyridinium tribromide, [BMPy]Br(3) proves to be a highly efficient, regioselective reagent/solvent for nuclear bromination of various anilines and phenols. The synthesis and characterization of the room temperature ionic liquid [BMPy]Br(3) (2) is described. The bromination was carried out in the absence of organic solvents and in most cases the only extraction solvent needed was water. The spent 1-butyl-3-methylpyridinium bromide (1) was easily recycled. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bromination; Ionic liquid; Regioselective; [BMPy]Br(3)

Electronic decoupling of surface layers from bulk and its influence in oxidation catalysis: a molecular beam study - Thirunavukkarasu, Kandasamy; Nagarajan, Sankaranarayanan; Gopinath, Chinnakonda S. (Applied Surface Science, 2009)
Interactions between oxygen and Pd-surfaces have important implications, especially towards oxidation reactions, and influence of subsurface oxygen to oxidation reactions is the focus of the present study. In our efforts to understand the above aspects, CO oxidation reactions have been carried out with mixed molecular beam (MB), consisting CO and O(2), on Pd(1 1 1) surfaces under a wide variety of conditions (T = 400-900 K, CO: O(2) = 7: 1 to 1: 10). A new aspect of the above reaction observed in the transient kinetics regime is the evidence for oxygen diffusion into Pd subsurface layers, and its significant influence towards CO oxidation at high temperatures (>= 600 K). Interesting information derived from the above studies is the necessity to fill up the subsurface layers with oxygen atoms to a threshold coverage (theta(O-sub)), above which the reactive CO adsorption occurs on the surface and simultaneous CO(2) production begins. There is also a significant time delay (G) observed between the onset of oxygen adsorption and CO adsorption (and CO(2) production). Above studies suggest an electronic decoupling of oxygen covered surface and subsurface layers, which is slightly oxidized, from the metallic bulk, which induces CO adsorption at high temperatures and simultaneous oxidation to CO(2). (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic decoupling; heterogeneous catalysis; molecular beam; Oxidation; Pd(111); Subsurface diffusion

Electronic manifestation of cation-vacancy-induced magnetic moments in a transparent oxide semiconductor: anatase Nb:TiO2 - Zhang, Shixiong; Ogale, Satishchandra B.; Yu, Weiqiang; Gao, Xingyu; Liu, Tao; Ghosh, Saurabh; Das, Gour P.; Wee, Andrew T. S.; Greene, Richard L.; Venkatesan, Thirumalai (Advanced Materials, 2009)
Nb-doped anatase TiO2 thin films grown by pulsed-laser deposition show Kondo scattering in elctronic-transport measurements, providing evidence for the formation of magnetic moments. The origin of magnetism is attributed to cation (Ti) vacancies, confirmed by X-ray absorption spectroscopy and first-principle calculations. The Ti vacancies are controlled by oxygen partial pressure during growth.

Electronic structure and catalytic study of solid solution of GaN in ZnO - Mapa, Maitri; Thushara, K. S.; Saha, Biswajit; Chakraborty, Purushottam; Janet, C. M.; Viswanath, R. P.; Nair, C. Madhavan; Murty, K. V. G. K.; Gopinath, Chinnakonda S. (Chemistry of Materials, 2009)
Solid solutions of GaN in ZnO (Zn1-zGaz)(O1-xNx) (x and z <= 0.15) have been prepared by simple solution combustion method, Except for minor changes in the lattice contraction, no significant change in the Wurtzite structure was observed. Raman and secondary ion mass spectrometry results show the direct Zn-N and Ga-N bonds in (Zn1-zGaz)(O1-xNx). Visible light absorption and XPS results demonstrate that N 2p states of nitride occupy the states above the O 2p valence band, and hence a change in optical band gap reduction occurs to similar to 2.5 eV from 3.37 eV for ZnO. Significant nitrogen fixation catalytic activity through NH3 formation has been observed at ambient pressure oil virgin (Zn1-zGaz)(O1-xNx) material, indicating its potential as a catalyst.

Enantioselective synthesis of decarestrictine J - Chowdhury, Partha Sarathi; Gupta, Priti; Kumar, Pradeep (Tetrahedron Letters, 2009)
An efficient total synthesis of decarestrictine J has been achieved using ring-closing metathesis and Yamaguchi esterification as key steps. The stereogenic centres were generated by means of iterative hydrolytic kinetic resolution (HKR) of racemic epoxides. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decanolides; epoxides; Hydrolytic kinetic resolution; Ring-closing metathesis; Yamaguchi esterification

Enantioselective total synthesis of (2S,3R,4R)-D-xylo-phytosphingosine from substituted azetidin-2-one - Pandey, Ganesh; Tiwari, Dharmendra Kumar (Tetrahedron Letters, 2009)
Enantiomerically pure (2S,3R,4R)-D-xylo phytosphingosine is synthesized in 36% overall yield in seven steps from known beta-lactam (8) derived from D-mannitol triacetonide. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: beta-lactam; Enantioselective synthesis; Sphingosine; Wittig reaction

Enhanced conversion efficiency in dye-sensitized solar cells based on hydrothermally synthesized TiO2-MWCNT nanocomposites - Muduli, Subas; Lee, Wonjoo; Dhas, Vivek V.; Mujawar, Sarfraj; Dubey, Megha; Vijayamohanan, K.; Han, Sung-Hwan; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2009)
A 50 % enhancement in the conversion efficiency (4.9-7.37 %) is realized in dye-sensitized solar cells Using hydrothermally synthesized TiO2-multiwalled carbon nanotube (MWCNT) nanocomposites as compared to hydrothermally synthesized TiO2 without MWCNT and Degussa P25. Several characterizations have been employed to reveal the nature of the modification imparted to the MWCNTs under hydrothermal processing conditions and the resulting TiO2-MWCNT conjugation through -COOH groups. Efficient charge transfer In the nanocomposite and efficient electron transport by MWCNT (significantly higher Incident-photon-to-current conversion efficiency) are suggested to be the possible reasons for the enhancement.
Keywords: Carbon nanotubes; charge transfer; Dye-sensitized solar cells; Hybrid composite; hydrothermal

Enhanced nonvolatile resistive switching in dilutely cobalt doped TiO2 - Bogle, Kashinath A.; Bachhav, Mukesh N.; Deo, Meenal S.; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2009)
Incorporation of dilute concentration of dopant having a valence state different than that of the host cation enables controlled incorporation proximity vacancy defects for local charge balance. Since nonvolatile resistive switching is a phenomenon tied to such defects, it can be expected to be influenced by dilute doping. In this work, we demonstrate that enhanced nonvolatile resistive switching is realized in dilutely cobalt doped TiO2 films grown at room temperature. We provide essential characterizations and analyses. We suggest that the oxygen vacancies in the proximity of immobile dopants provide well distributed anchors for the development of systematic filamentary tracks.
Keywords: cobalt; Doping; magnetic switching; random-access storage; titanium compounds; vacancies (crystal); valency

Enhanced production of amidase from Rhodococcus erythropolis MTCC 1526 by medium optimisation using a statistical experimental design - Vaidya, Bhalchandra K.; Mutalik, Snehal R.; Joshi, Renuka M.; Nene, Sanjay N.; Kulkarni, Bhaskar D. (Journal of Industrial Microbiology & Biotechnology, 2009)
In the present work, statistical experimental methodology was used to enhance the production of amidase from Rhodococcus erythropolis MTCC 1526. R. erythropolis MTCC 1526 was selected through screening of seven strains of Rhodococcus species. The Placket-Burman screening experiments suggested that sorbitol as carbon source, yeast extract and meat peptone as nitrogen sources, and acetamide as amidase inducer are the most influential media components. The concentrations of these four media components were optimised using a face-centred design of response surface methodology (RSM). The optimum medium composition for amidase production was found to contain sorbitol (5 g/L), yeast extract (4 g/L), meat peptone (2.5 g/L), and acetamide (12.25 mM). Amidase activities before and after optimisation were 157.85 units/g dry cells and 1,086.57 units/g dry cells, respectively. Thus, use of RSM increased production of amidase from R. erythropolis MTCC 1526 by 6.88-fold.
Keywords: Amidase; Medium optimisation; Plackett-Burman screening; Response surface methodology; Rhodococcus erythropolis

Enhanced solar-radiation induced photocatalytic activity of surface-modified nanocrystalline anatase-titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K. R.; Warrier, K. G. K. (Catalysis Letters, 2009)
Sol-gel derived pure nanocrystalline (similar to 20-30 nm) anatase-titania has been surface-modified by depositing silver(I) oxide and silver (predominantly the former) via UV-reduction process. The pure and surface-modified nanocrystalline anatase-titania have been characterized using different analytical techniques for determining the average nanocrystallite size, phase-contents, surface-chemistry, as well as the absorption and photoluminescence characteristics. It is demonstrated that, the latter exhibits an enhanced solar-radiation induced photocatalytic activity as compared to that of the former as a result of the absorption in the visible-region and enhanced photo-induced e(-)/h(+) life-time, both caused by the surface-deposition of silver(I) oxide and silver.
Keywords: Nanocrystalline; Photocatalysis; Silver; sol-gel; titania; UV-reduction

Enhancing intermolecular benzoyl-transfer reactivity in crystals by growing a ``reactive'' metastable polymorph by using a chiral additive - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2009)
Racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate, which normally crystallizes in a monoclinic form (form I, space group P2(1)/n) could be persuaded to crystallize out as a metastable polymorph (form II, space group C2/c) by using a small amount of either D- or L- 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoformate as an additive in the crystallization medium. The structurally similar enantiomeric additive was chosen by the scrutiny of previous experimental results on the crystallization of racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate. Form II crystals call be thermally transformed to form I crystals at about 145 degrees C. The relative organization of the molecules in these dimorphs vary slightly in terms of the helical assembly of molecules, that is, electrophile (El)center dot center dot center dot nucleophile (Nu) and C-H center dot center dot center dot pi interactions, but these minor variations have a profound effect on the facility and specificity of benzoyl-group-transfer reactivity in the two crystal forms. While form II crystals undergo a clean intermolecular benzoyl-group-transfer reaction, form I crystals are less reactive and undergo non-specific benzoyl-group transfer leading to a Mixture of products. The role played by the additive in fine-tuning small changes that are required in the molecular packing opens up the possibility of creating new polymorphs that show varied physical and chemical properties. Crystals of D-2.6-di-O-benzoyl-myo-inositol-1,3,5-orthoformate (additive) did not show facile benzoyl-group-transfer reactivity (in contrast to the corresponding racemic compound) due to the lack of proper juxtaposition and assembly of molecules.
Keywords: Acylation; carbohydrates; Crystal growth; cyclitols; solid-state reactions

Entrainer for batch distillation of acetic acid -water system - Gadekar, S. V.; Naik, R. V.; Kaul, S. N. (Journal of Scientific & Industrial Research, 2009)
Acetic acid-water system (AW) poses a challenge in reactive distillation, acetic acid purity and loss of acetic acid in aqueous solutions. Feasible separation of AW has been studied using entrainers but acetic acid loss in lean phase cannot be avoided. This study presents feasible region to operate column with toluene and benzene as entrainer for AW. Liquid-liquid equilibrium data and nature of tie line for ethyl acetate are given priority.
Keywords: Acetic acid; Batch distillation; Benzene; Entrainer; Toluene

Epitaxially grown zinc-blende structured Mn doped ZnO nanoshell on ZnS nanoparticles - Limaye, Mukta V.; Singh, Shashi B.; Date, Sadgopal K.; Gholap, Ramkrishna S.; Kulkarni, Sulabha K. (Materials Research Bulletin, 2009)
Zinc oxide in the bulk as well as in the nanocrystalline form is thermodynamically stable in the wurtzite structure. However, zinc oxide in the zinc-blende structure is more useful than that in the wurtzite structure due to its superior electronic properties as well as possibility of efficient doping. Therefore, zinc oxide shell is grown epitaxially on zinc sulphide core nanoparticles having zinc-blende structure. It is shown that doping of manganese could be achieved in zinc oxide nanoshell with zinc-blende structure. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Luminescence; Nanostructures; Semiconductors; X-ray diffraction

Epoxy powder coatings containing polyaniline for enhanced corrosion protection - Radhakrishnan, S.; Sonawane, Narendra; Siju, C. R. (Progress in Organic Coatings, 2009)
Incorporation of polyaniline (PANI) in epoxy type powder coating formulations has not been attempted earlier. Using specific grade of PANI with low doping, it can be incorporated in epoxy powder coating formulations by twin screw extrusion process. The powder formulations were deposited on steel substrates by electrostatic spray coating at -60 W and baked at 140 degrees C for 20 min. These were extensively tested for corrosion resistance by exposure to hot saline conditions followed by electrochemical impedance spectroscopy and also salt spray testing. PANI incorporated coatings showed no deterioration even after 1400 h of hot (65 degrees C) saline treatment. The coatings intentionally scratched also exhibited self healing property and there was no rust formation even after prolonged exposure to hot saline conditions. These results could be explained on the basis of additional crosslinking due to PANI, as confirmed by DSC results, which gave rise to improved barrier property and self healing was associated with the scavenging of ions by PANI which prevented corrosion of the underlying substrate. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Corrosion resistance; Epoxy; polyaniline; Powder coating

Estimation of free fatty acid content in oils, fats, and biodiesel by (1)H NMR spectroscopy - Satyarthi, Jitendra K.; Srinivas, D.; Ratnasamy, Paul (Energy & Fuels, 2009)
A novel (1)H NMR method for the quantification of free fatty acid (FFA) content in vegetable oils, animal fats, and biodiesel is reported. Nonedible oils and animal fats, which are increasingly being explored as cheaper, renewable feed stocks for biodiesel production by transesterification with methanol, contain a significant amount of FFA along with other acidic impurities. The (1)H NMR spectroscopic method is found to be more accurate than the conventional titrimetric analysis for the estimation of FFA content especially in those cases where acidic entities other than the FFA are also present in the feedstock. The titrimetric methods provide a gross acid value which corresponds to that of FFA and other acidic impurities. Our NMR method provides the FFA content exclusively. In the case of refined edible oils (wherein the other acidic impurities are negligible), the results obtained from the (1)H NMR method are comparable with those from the titrimetic analysis.

Eudragit (R) EPO based nanoparticle suspension of andrographolide: in vitro and in vivo - Bothiraja, C.; Pawar, Atmaram P.; Shaikh, Karimunnisa S.; Sher, Praveen (Nanoscience and Nanotechnology Letters, 2009)
Characteristic formulation of an isolated active phytoconstituent is of great therapeutic significance. The purpose of this work was to develop Eudragit (R) EPO based nanoparticle suspension of isolated andrographolide in order to increase its solubility and efficacy. Andrographolide was isolated from Andrographis paniculata and Its Nanoparticle suspension was prepared by precipitation technique. The 3(2) factorial design was used to study the effect of Eudragit (R) EPO and Pluronic (R) F-68 on characteristics of nanoparticle suspension. The optimized formulation was subjected to lyophilization. The nanoparticle suspension, lyophilized suspension and the redispersed lyophilized nanoparticle suspension were characterized by drug content, encapsulation efficiency, particle size, electrokinetic properties, DSC, PXRD, FTIR, TEM and in vitro drug release. Optimized batch showed particle size 255 +/- 9 nm with encapsulation efficiency 93.8 +/- 0.67% and zeta potential 29.3 +/- 3.4 mV. There was marked increase in drug dissolution with complete drug release within 10 minutes in nanoparticle suspension and redispersed naoparticle suspension as compared to pure drug. However, lyophilization retarded the drug release. The nanoparticle suspension and redispersed nanoparticle suspension also showed improved hepatoprotectivity as compared to andrographolide against CCl(4)-induced hepatotoxicity in rats. The results were confirmed by histopathological studies on hepatic lesions. Thus particle engineering can be used to improve pharmaceutical properties of phytoconstituents.
Keywords: Andrographolide; Eudragit (R) EPO; Hepatoprotective Activity; Nanoparticle Suspension; Pluronic (R) F-68

Evaluation of high performance liquid chromatography purified leptospiral antigen for the diagnosis of leptospirosis - Pol, Sae; Bharadwaj, Renu (Japanese Journal of Infectious Diseases, 2009)
Leptospirosis is a re-emerging infection, and often occurs in outbreaks. Early diagnosis is important for appropriate control measures and treatment. The sensitivity and specificity of the diagnostic test depends on the antigen, which is used for the detection of antibodies. In the present study, an effort was made to purify and characterize leptospiral antigens, and their performance in the laboratory was assessed. Leptospira biflexa semaranga, Patoc was subjected to processing by the heat extraction method, and the crude antigenic preparation was subjected to high-performance liquid chromatography for purification. The purified antigen fractions were subjected to enzyme-linked immunosorbent assay (ELISA) to determine their reactivity. Only the reactive fractions were tested for specificity by ELISA by allowing the fractions to react with positive sera of patients with non-leptospiral illness. H1, the purified antigen fraction of the heat-extracted preparation, was found to be the most reactive and specific of all fractions tested. The protein was found to have a molecular weight of 50 kDa. The performance of H1 in the laboratory was assessed by formulating an in-house ELISA using the H1 antigen. The results were compared with those of microscopic agglutination testing and commercial ELISA. The specificity and sensitivity of in-house ELISA using the H1 antigen were found to be 93.3 and 85.0%, respectively.

Evaluation of repulsive particle swarm method for phase equilibrium and phase stability problems - Rahman, Imran; Das, Anwesh Kr.; Mankar, Raju B.; Kulkarni, B. D. (Fluid Phase Equilibria, 2009)
Phase equilibrium and stability problems are of crucial importance in simulation, design and optimization of several separation processes. Recently, these problems have been solved using minimization of Gibbs free energy, using global optimization techniques. In this paper, repulsive particle swarm (RPS), a recent global optimization technique is explored for the Solution of phase stability and phase equilibrium. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid equilibria; Phase equilibrium; Phase stability analysis; Repulsive particle swarm method

Exploration of click reaction for the synthesis of modified nucleosides as chitin synthase inhibitors - Chaudhary, Preeti M.; Chavan, Sayalee R.; Shirazi, Fazal; Razdan, Meenakshi; Nimkar, Prachi; Maybhate, Shailaja P.; Likhite, Anjali P.; Gonnade, Rajesh G.; Hazra, Braja G.; Deshpande, Mukund V.; Deshpande, Sunita R. (Bioorganic & Medicinal Chemistry, 2009)
Click reaction approach toward the synthesis of two sets of novel 1,2,3-triazolyl linked uridine derivatives 19a-19g and 21a-21g was achieved by Cu(I)-catalyzed 1,3-dipolar cycloaddition of 5'-azido-5'-deoxy-2',3'-O-(1-methylethylidene) uridine (17) with propargylated ether of phenols 18a-18g and propargylated esters 20a-20g. Structure of one of the representative compound 19d was unambiguously confirmed by X-ray crystallography. Chitin synthase inhibition study of all these compounds 19a-19g and 21a-21g was carried out to develop antifungal strategy. Compounds 19d, 19e, 19f, and 21f were identified as potent chitin synthase inhibitors by comparing with nikkomycin. Compounds 19a, 19b, 19c, 19d, 21a, and 21b showed good antifungal activity against human and plant pathogens. Compounds 19a, 19b, 19f, 21c, 21f, and 21g were identified as lead chitin synthase inhibitors for further modi. cations by comparing results of inhibition of growth, % germ tube formation and chitin synthase activity. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; 4-Disubstituted-1; 5 `-Azidouridine; Antifungal compounds; Chitin synthase activity; Click reaction; Uridine nucleosides

Ecofriendly synthesis and solar photocatalytic activity of S-doped ZnO - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Hazardous Materials, 2010)
The S-doped ZnO was prepared by new ecofriendly method, which involves simple mechanochemical synthesis followed by thermal decomposition of bisthiourea zinc oxalate (BTZO) powders. The BTZO was characterized by FTIR and TG-DTA analysis while S-doped ZnO crystallite was characterized by XRD, XPS, SEM, EDXS, and photoluminescence (PL) spectra. X-ray diffraction data suggest the single phase wurtzite structure for S-doped ZnO and the incorporation of sulfur expand the lattice constants of ZnO. Room temperature PL spectra show more number of oxygen vacancies in S-doped ZnO as compare to that of pure ZnO. Photocatalytic activity of S-doped ZnO was checked by means of solar photocatalytic degradation (PCD) of resorcinol, using a batch photoreactor. The PCD efficiency of S-doped ZnO was found to be 2 times greater than that of pure ZnO. The inherent relationship between PL intensity and photocatalytic activity of S-doped ZnO was discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Photocatalysis; photoluminescence; Resorcinol; S-doped ZnO; Sunlight; XPS

Effect of additives on the co-electrodeposition of Sn-Ag-Cu lead-free solder composition - Joseph, Shany; Phatak, Girish J. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
We have developed a methane sulfonic acid (MSA) based ternary electrodeposition bath for the deposition of near eutectic Sn-Ag-Cu films aimed at solder bumping applications in electronics. The bath contains thiourea as chelating agent and iso-octyl phenoxy ethanol (OPPE) as surfactant. We added gelatin to this bath and studied its effect on bath stability, microstructure of the deposited films and the film composition. It is found that the bath containing both the additives, viz. OPPE and gelatin, show improved stability up to 8-10 days. Striking improvement in the film microstructure, in terms of the compactness, uniformity and refinement of grains was found when the bath contained these additives. Detailed electrochemical studies with the help of cyclic voltametry and impedance analysis helped in understanding the role played by these additives during deposition. It is confirmed that there is a formation of loosely connected, highly non-uniform passivating film on the cathode surface, which is removed competitively by the depositing metal ions during the deposition. It is also clear that the additives play a role in the formation of such a passivating film. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Additives; Lead-free solders; Sn-Ag-Cu; Solder bumping; Ternary bath

Effect of Fe3O4 on morphology of Fe-SnO2 hyperbranched heterostructures - Sathe, Bhaskar R.; Walke, Pravin S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Chemical Physics Letters, 2010)
A simple modified thermal evaporation technique is employed for the synthesis of microstructured Fe:SnO2 system and their plausible growth mechanism has been proposed based on the results from various characterization techniques. Such structures grow in two steps; initially, growth of Fe core takes place from Fe3O4 source which acts as nucleating site for SnO2 growth on its surface as per the vapor-liquid- solid progression. Moreover, the composition of Fe/Sn source and temperature are found to have key roles in governing their morphology. XPS studies clearly demonstrate the presence of Fe species, which acts as a catalyst along with source for hetero-structure growth with SnO2. (C) 2010 Published by Elsevier B.V.

Effect of gamma-dose rate on biodegradation of gamma-sterilized biomedical polyolefins - Alariqi, Sameh A. S.; Singh, R. P. (Journal of Polymers and the Environment, 2010)
The aim of the present study is to study the effect of gamma-dose rate on the biodegradation of gamma-sterilized polyolefins. Films of isotactic polypropylene, high density polyethylene and ethylene-propylene (EP) copolymer were sterilized under gamma-radiation with doses of 10 and 25 kGy. Two different (60)Co sources were used with dose rate 600 and 780 Gy h(-1). Neat and sterilized samples were incubated in compost and fungal culture environments. The changes in functional groups, surface morphology and intrinsic viscosity in polymer chains were characterized by FT-IR spectroscopy, SEM and viscometric measurements, respectively. It was observed that both gamma-degradation and biodegradation processes depend on the dose rate of gamma-source. It was found that the biodegradation of gamma-sterilized polyolefins in composting and microbial culture environments increased with decreasing the gamma-dose rate.
Keywords: Biodegradation; Composting and fungal culture; gamma-Dose rate; Polyolefins; Sterilization

Effect of leakage current and dielectric constant on single and double layer oxides in MOS structure - Laha, Pinaki; Panda, A. B.; Dahiwale, S.; Date, Kalyani S.; Patil, K. R.; Barhai, P. K.; Das, A. K.; Banerjee, Indrani; Mahapatra, S. K. (Thin Solid Films, 2010)
MOS structure of Al/Al2O3/n-Si, Al/TiO2/n-Si and Al/Al2O3/TiO2/n-Si was obtained by deposition of Al2O3 and TiO2 on silicon substrate by RF Magnetron Sputtering system. The total thickness of the oxide layer similar to 40 +/- 5 nm in the MOS structure was kept constant. Samples were characterized by X-Ray diffraction (XRD). X-Ray photoelectron spectroscopy (XPS), Impedance analyzer and Current-voltage (J-V) characteristics. The variations in the dielectric constant and tan 8 of the MOS capacitor in the frequency range of 1000Hz-1MHz were measured by impedance analyzer. The variation in dielectric constant of the Al/Al2O3/TiO2/n-Si multilayer compared to single layer of Al/Al2O3/n-Si and Al/TiO2/n-Si is due to high probability of defects, lattice mismatch and interface interactions. The steep rise of Tan 6 values in the Al/Al2O3/TiO2/n-Si structure is due to the resonance effect of both Al2O3 and TiO2 layers. The leakage current mechanisms of MOS structures were extracted from Schottky coefficient and Poole-Frenkel coefficient. Theoretical values of Schottky coefficients (beta(SC)) and Poole-Frenkel coefficients (beta(PF)) for each sample were estimated using the real part of the dielectric constant. The experimental values were calculated from J-V characteristics and compared with theoretical values. The appropriate model has been proposed. It was found that Schottky and Poole-Frenkel mechanisms are applicable at low and high field respectively for all MOS structures. The combination of Al/Al2O3/TiO2/n-Si is found to be a promising structure with high dielectric constant and low leakage current suitable for MOS devices. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Al2O3; dielectric constant; Leakage current; MOS device; Poole-Frenkel emission; Schottky emission; TiO2

Effect of nanoparticle conjugation on gene silencing by RNA interference - Singh, Neetu; Agrawal, Amit C.; Leung, Anthony K. L.; Sharp, Phillip A.; Bhatia, Sangeeta N. (Journal of American Chemical Society, 2010)

Effect of reduced particle size on the magnetic properties of chemically synthesized BiFeO3 nanocrystals - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
Here, we report the effect of reduction in particle size on the temperature dependent magnetization of chemically synthesized BiFeO3 nanocrystals with average grain size of 55 nm. The X-ray photoelectron spectroscopy results show a significant broadening of binding energy peaks associated to Fe3+ 2p(3/2) core levels due to the reduced size. Additionally, due to the nanosize effect, the M-H loops show a significant coercivity starting from 390 K with an anomaly located in the vicinity of 150 K in our H-c vs T as well as M-r/M-s(50 kOe) vs T curves. At this temperature, both H-c and M-r/M-s(50 kOe) undergo minima. Additionally, our results for the first time show the evidence of existence of a low temperature anomaly due to spin-glass transition in the range from 40-44 K in the field cooled magnetization curves. In bulk single crystals, this transition is reported to be situated at around 50 K, however, this transition remained so far undiscovered in the recent studies on BiFeO3 nanoparticles due to the insufficient temperature resolution. The significant shift in this transition toward lower temperature can be attributed to size dependent effects. Our results clearly present new information on the size dependent properties of BiFeO3 nanoparticles.

Effect of solvents having different dielectric constants on reactivity: a conceptual DFT approach - Kar, Rahul; Pal, Sourav (International Journal of Quantum Chemistry, 2010)
Conceptual density functional theory is exploited to understand the reactivity in a medium of solvents with increasing dielectric constants. Aprotic as well as protic solvents are used for this study. It is found that the global parameters, such as chemical potential and hardness, decrease from gas phase to solvent phase with increasing dielectric constant. However, it is observed that the Fukui functions of the reactive atoms increase significantly with the dielectric constants of the aprotic solvents while for the protic solvents the variation of the reactivity indices is insignificant. (C) 2009 Wiley Periodicals, Inc. Int J Quantum Chem 110: 1642-1647, 2010
Keywords: COSMO; DFT; dielectric constant; Reactivity descriptors; solvent effect

Effect of sub-lethal concentrations of insect growth regulator, lufenuron on larval growth and development of Aedes aegypti - Salokhe, S. G.; Mukherjee, Samindra N.; Deshpande, S. G.; Ghule, V. P.; Mathad, J. R. (Current Science, 2010)
The effect of sub-lethal concentrations (LC20 = 0.0002 and 0.001 ppm, and LC40 = 0.002 and 0.02 ppm for II and IV instar larvae respectively) of a dispersible concentrate formulation of the insect growth regulator, lufenuron on larval growth and development of Aedes aegypti was studied. When II and IV instar larvae were subjected to the above-mentioned sub-lethal concentrations of lufenuron through the culture medium, there was a significant increase in the time taken for pupation (17.2 +/- 0.74 and 11.4 +/- 0.8 days for II and IV instar LC20-treated larvae respectively, and 19 +/- 0.89 and 14.6 +/- 1.0 days for II and IV instar LC40-treated larvae respectively). Also, there was increase in the time taken for adult emergence 3.8 +/- 0.83 and 5.4 +/- 0.83 days from pupation of LC40-treated II and IV instar larvae respectively). There was 28.1 +/- 2.06% and 43.59 +/- 0.87% reduction in pupation in LC20 of lufenuron-treated II and IV instar A. aegypti larvae respectively. Also, with LC20 of lufenuron-treated II and IV instar larvae there was 43.54 +/- 5.12% and 43.59 +/- 0.87% reduction in adult emergence respectively. Further, it was observed that II instar larvae treated with LC20 of lufenuron developed into 25.8 +/- 2.08% deformed adults. In LC40-treated II instar larvae there was 33.72 +/- 2.38% reduction in pupation and 63.44 +/- 4.76% reduction in adult emergence. Also, it was observed that there was 54.84 +/- 3.9% and 61.3 +/- 5.2% reduction in pupation and adult emergence respectively, in IV instar larvae treated with LC40 of lufenuron. The reduction in pupation of the IV instar larvae treated with LC40 of lufenuron was due to failure of the larvae to undergo pupation. These studies are fundamental to the use of lufenuron in A. aegypti management.
Keywords: Aedes aegypti; larval growth and development; lufenuron; sub-lethal concentration

Effect of the allylic substituents on ring closing metathesis: the total synthesis of stagonolide B and 4-epi-stagonolide B - Giri, Awadut G.; Mondal, Mohabul A.; Puranik, Vedavati G.; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2010)
The total syntheses of stagonolide B and its 4-epimer were carried out to probe into how the relative stereochemistry of allylic hydroxy groups and their protecting groups influence the efficiency of the ring closing metathesis.

Efficient heterogeneous catalytic system for chemoselective hydrogenation of unsaturated ketones in aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Polyhedron, 2010)
A highly chemoselective and green heterogeneous catalytic system of immobilized Ru(II)-phenanthroline complexes on amino functionalised MCM-41 material for the chemoselective hydrogenation of unsaturated ketones to unsaturated alcohols is demonstrated using water as a solvent The XRD and FTIR spectra show the highly ordered hexagonal nature of the MCM-41 even after encapsulation of the ruthenium complex The complex retains its configuration after anchoring as was confirmed by FTIR and UV-Vis analysis The detailed reaction parametric effect was studied for the hydrogenation of 3 methylpent-3-en-2-one to achieve complete conversion up to >99% chemoselectivity of 3-methylpent-3-en-2 ol The anchored heterogeneous catalysts were recycled effectively and reused five times with marginal changes in activity and selectivity The use of water as a solvent not only afforded high activity for the hydroge nation reaction compared to organic solvents but also afforded a green process Crown Copyright (C) 2010 Published by Elsevier Ltd All rights reserved
Keywords: 1 10 Phenanthroline; alpha beta Unsaturated ketone; Chemoselective hydrogenation; mesoporous materials; ruthenium

Efficient industrial dye decolorization by Bacillus sp. VUS with its enzyme system - Dawkar, Vishal V.; Jadhav, Umesh U.; Tamboli, Dhawal P.; Govindwar, Sanjay P. (Ecotoxicology and Environmental Safety, 2010)
This work presents role of different enzymes in decolorization of industrial dye Orange T4LL by Bacillus sp. VUS. Bacillus sp. strain VUS decolorized dye Orange T4LL, under static anoxic condition in 24 h. During decolorization of Orange T4LL a significant induction in the activities of lignin peroxidase, tyrosinase, and reductases (NADH-DCIP, azo, and riboflavin) was observed. The biodegradation was monitored by Ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, and high performance liquid chromatography. The final products 4-methyl-2-o-tolylazo-benzene-1,3-diamine and [3-(phenyl-hydrazono)-cyclohexa-1,4-dienyl]-methanol were characterized by gas chromatography-mass spectroscopy. Phytotoxicity, COD, and BUD revealed non-toxicity of degraded products. Phytotoxicity study demonstrated non-toxicity of the biodegraded products for crop plants with respect to Triticum aestivum and Sorghum bicolor. Bacillus sp. VUS with its enzyme system could be a useful tool for textile effluent treatment. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Decolorization; GC-MS; Lignin peroxidase; Orange T4LL; Phytotoxicity; Reductases

Efficient synthesis of varenicline - Pasikanti, Srinivas; Reddy, D. Srinivasa; Venkatesham, B.; Dubey, P. K.; Iqbal, Javed; Das, Parthasarathi (Tetrahedron Letters, 2010)
Synthesis of varenicline the antismoking drug has been achieved in six steps with 10% overall yield. A Diels-Alder reaction, oxidative cleavage of an olefin and reductive amination remain as key steps in the synthesis (C) 2009 Elsevier Ltd. All rights reserved.

Elucidation of the role of hexamine and other precursors in the formation of magnetite nanorods and their stoichiometry - Singh, Hema; Bhagwat, Shrikant; Jouen, Samuel; Lefez, Benoit; Athawale, Anjali A.; Hannoyer, Beatrice; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2010)
Hexamine is known to assist anisotropic growth of metal oxides and the same is also found to be true for magnetite nanosynthesis. In this work we elucidate the role of hexamine and other precursors in the formation of magnetite nanorods by the hydrothermal route and their stoichiometry. Various others hydrolyzing agents such as sodium hydroxide (NaOH), sodium hydroxide + hexamine, ammonia (NH(3)), ammonia + formaldehyde are also studied. The synthesized nanoparticles are characterized with the help of various techniques such as X-ray diffraction (XRD), FT-IR spectroscopy, UV-VIS-NIR spectroscopy, transmission electron microscopy (TEM), Mossbauer spectroscopy and SQUID magnetization measurements. It is found that only when ferric chloride, ferrous ammonium sulfate (FAS) and hexamine are used, well defined nanorods are formed. When sodium hydroxide and hexamine are used as a hydrolyzing system nearly spherical nanoparticles with small size (similar to 13 nm) are formed, as compared to the case of sodium hydroxide alone which leads to bigger cube like nanoparticles. Interestingly the decomposition products of hexamine do not lead to nanorod formation. Thus, slow decomposition of hexamine at elevated temperature and the consequent slow rise in pH is the key to the anisotropic growth of the iron oxide system.

Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Enantioselective synthesis of (+)-alpha-conhydrine and (-)-sedamine by L-proline-catalysed alpha-aminooxylation - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2010)
An efficient organocatalytic approach to the enantioslective synthesis of two important piperidine alkaloids, namely (+)-alpha-conhydrine (98% ee) and (-)-sedamine (95% ee), by L-proline-catalysed alpha-aminooxylation of aldehydes has been developed. The strategy involves an intramolecular cyclization to construct the piperidine core.
Keywords: alkaloids; Amino acids; Aminooxylation; Enantioselectivity; organocatalysis

Enantioselective synthesis of (R)-(+)-alpha-lipoic acid via proline-catalyzed sequential alpha-aminoxylation and HWE olefination of aldehyde - Panchgalle, Sharad P.; Jogdand, Ganesh F.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron Letters, 2010)
An efficient enantioselective synthesis of (R)-(+)-alpha-lipoic acid is described, in high optical purity (>97% ee), using L-proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde as the key step. (C) 2010 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of syn/anti-1,3-amino alcohols via proline-catalyzed sequential alpha-aminoxylation/alpha-amination and horner-wadsworth-emmons olefination of aldehydes - Jha, Vishwajeet; Kondekar, Nagendra B.; Kumar, Pradeep (Organic Letters, 2010)
A novel and general method for asymmetric synthesis of both syn/anti-1,3-amino alcohols is described. The method uses proline-catalyzed sequential alpha-aminoxylation/alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes as the key step. By using this method, a short synthesis of a bioactive molecule, (R)-1-((S)-1-methylpyrrolidin-2-yl)-5-phenylpentan-2-ol, is also accomplished.

Enantiospecific synthesis of sex pheromone of the obscure mealybug from pantolactone via tandem conjugate addition/cyclization - Hajare, Atul K.; Datrange, Laxmikant S.; Vyas, Samir; Bhuniya, Debnath; Reddy, D. Srinivasa (Tetrahedron Letters, 2010)
An efficient synthesis of an enantiomer of insect's natural pheromone is reported starting from chiral pool D-(-)-pantolactone. Highly stereoselective tandem conjugate addition/cyclization sequence and hydrogenation of exocyclic double bond are the key steps in the present synthesis. (C) 2010 Elsevier Ltd. All rights reserved.

Enhanced negative thermal expansion in MFI molecular sieves by varying framework composition - Bhange, Deu S.; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2010)
In the present investigations we have carried out the high temperature X-ray diffraction (HTXRD) studies on the metallosilicate molecular sieves iron silicalite-1 (FeS-1) samples of different Si/M ratios (Si/Fe = 50, 75, 100 and infinity) for their negative thermal expansion (NTE) behavior. All the samples exhibit NTE behavior in the temperature range 373-773 K. Systematic increase in negative thermal expansion coefficient is observed as a function of increasing Fe content in the MFI framework. Strength of the negative thermal expansion increases in the order Si/Fe = infinity < 100 < 75 < 50. It is concluded that by changing the composition of the framework of MFI, enhanced negative thermal expansion can be obtained. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: HTXRD; Negative thermal expansion; Silicalite-1

Enhanced production of gibberellin A(4) (GA(4)) by a mutant of Gibberella fujikuroi in wheat gluten medium - Lale, Geetanjali; Gadre, Ramchandra V. (Journal of Industrial Microbiology & Biotechnology, 2010)
Mutants of Gibberella fujikuroi with different colony characteristics, morphology and pigmentation were generated by exposure to UV radiation. A mutant, Mor-189, was selected based on its short filament length, relatively high gibberellin A(4) (GA(4)) and gibberellin A(3) (GA(3)) production, as well as its lack of pigmentation. Production of GA(4) by Mor-189 was studied using different inorganic and organic nitrogen sources, carbon sources and by maintaining the pH of the fermentation medium using calcium carbonate. Analysis of GA(4) and GA(3) was done by reversed-phase high-performance liquid chromatography and LC-MS. The mutants of G. fujikuroi produced more GA(4) when the pH of the medium was maintained above 5. During shake flask studies, the mutant Mor-189 produced 210 mg l(-1) GA(4) in media containing wheat gluten as the nitrogen source and glucose as the carbon source. Fed-batch fermentation in a 14 l agitated fermenter was performed to evaluate the applicability of the mutant Mor-189 for the production of GA(4). In 7-day fed-batch fermentation, 600 mg l(-1) GA(4) were obtained in the culture filtrate. The concentration of GA(4) and GA(3) combined was 713 mg l(-1), of which GA(4) accounted for 84% of the total gibberellin. These values are substantially higher than those published previously. The present study indicated that, along with maintenance of pH and controlled glucose feeding, the use of wheat gluten as the sole nitrogen source considerably enhances GA(4) production by the mutant Mor-189.
Keywords: Fermentation; GA(4); Gibberella fujikuroi; Mutant; Wheat gluten

Enhancement of anisotropic conductivity, elastic, and dielectric constants in a liquid crystal-gold nanorod system - Sridevi, S.; Prasad, S. Krishna; Nair, Geetha G.; D'Britto, Virginia; Bhagavatula L. V. Prasad (Applied Physics Letters, 2010)
We report electrical conductivity (sigma), dielectric constant (epsilon) and the elastic constant measurements in a nematic liquid crystal (LC) doped with small concentrations of gold nanorods. This LC-nanoparticle complex, shows not only orders of magnitude higher sigma, but also stabilizes its anisotropy. The epsilon data suggests an increased ordering in the nematic phase, and an improved antiparallel correlation of the molecules in the isotropic phase. Surprisingly, an anisotropic enhancement of the Frank elasticity is also seen. We suggest a possible electro/magnetomechanical conductivity switch and also provide explanations based on the aspect ratio of the nanoparticles vis-a-vis the LC molecules. (c) 2010 American Institute of Physics. [doi:10.1063/1.3499744]

Enhancement of thermal stability and phase relaxation behavior of chitosan dissolved in aqueous l-lactic acid: using `silver nanoparticles' as nano filler - Rana, V. K.; Pandey, Asutosh K.; Singh, Raj Pal; Kumar, B.; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Chitosan films with various compositions of silver nanoparticles were prepared by solution casting with an aqueous solution of chitosan and l-lactic acid. The chitosan/Ag nanocomposites were characterized by wide angle Xray diffraction (WAXD) and UV-vis spectroscopy. An analysis of the surface topography and size of the Ag nanoparticles (<= 100 nm) were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Thermogravimetric analysis (TGA/DTA) confirmed the increase in thermal stability with increasing Ag nanoparticle content in the nanocomposites. Dynamic thermal analysis (DMA) was used to examine the phase relaxation behavior of chitosan and its nanocomposites. The conductivity of chitosan/Ag nanocomposites was considered with respect to the frequency. Contact angle measurements were used to characterize the surface twistability, surface cleanliness, and hydrophilic/hydrophobic nature of the surface.
Keywords: Chitosan; conductivity; contact angle; relaxation; silver nanoparticles

Enzymatic hydrolysis and ethanol production using xyloglucanase and debaromyces hansenii from tamarind kernel powder: galactoxyloglucan predominant hemicellulose - Menon, Vishnu; Prakash, Gyan; Rao, Mala (Journal of Biotechnology, 2010)
The hydrolysis and ethanol production from tamarind kernel powder (TKP), a rich source of galactoxyloglucan (GXG) was investigated for the first time using xyloglucanase and thermotolerant Debaromyces hansenii. The acid hydrolysis of TKP with 2N H(2)SO(4) at 120 degrees C for 30 min yielded an overall saccharification of 94% based on the total available carbohydrate content and further fermentation at 40 degrees C with thermotolerant D hansenii produced an ethanol yield of 0.35 g/g. A maximum hydrolysis of 55 and 78% for GXG was obtained in 48 h at 50 degrees C using Thermomonospora xyloglucanase (TXy) and accellerase (TM) 1000, respectively. The synergistic effect of beta-galactosidase and xyloglucanase was demonstrated by the exogenous addition of beta-galactosidase to TXy which improved the overall hydrolysis of GXG by 30%. The rate of hydrolysis of GXG with TXy and accellerase was increased by 15-20% in the presence of chemical surfactants (tween 80 and toluene) or protein additive (BSA). The fermentation of enzymatic hydrolysates of GXG by TXy and accellerase with free cells at 40 degrees C produced an ethanol yield of 0.39 and 0.41 g/g whereas with immobilized cells produced 0.45 and 0.43 g/g, respectively, with a theoretical conversion efficiencies of 78-88%. The immobilized yeast cells were reused six times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Galactoxyloglucan; Hydrolysis; Tamarind kernel powder; Thermotolerant yeast; Xyloglucanase

Evidence for the co-existence of distorted tetrahedral and trigonal bipyramidal aluminium sites in SrAl12O19 from Al-27 NMR studies - Harindranath, K.; Viswanath, K. Anusree; Chandran, C. Vinod; Braeuniger, Thomas; Madhu, Perunthiruthy K.; Ajithkumar, Thalasseril G.; Joy, Pattayil Alias (Solid State Communications, 2010)
Strontium aluminate, SrAl12O19, is a ceramic material having the hexagonal magnetoplumbite-type structure, with multiple Al coordination environments. An earlier low-field Al-27 solid-state NMR study reported five different Al sites in this system: one AlO4, one AlO5, and three AlO6 sites; whereas a later high-field study showed that the AlO5 site is a distorted AlO4 site with a very large quadrupolar coupling constant (similar to 20 MHz). Our magic angle spinning (MAS) and 3-quantum magic angle spinning (3QMAS) NMR studies at 7.05 T unambiguously show evidence for an AlO5 site. However, evidence for the presence of a distorted AlO4 site is obtained from studies at high fields (16.4 and 17.6 T), in addition to the AlO5 site. Thus the present solid-state NMR studies give evidence for the simultaneous presence of both the five-coordinated and distorted four-coordinated sites in this system. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Local structure; MQMAS; Nuclear magnetic resonance; Strontium aluminate

Exfoliation of clay layers in polypropylene matrix using potassium succinate-g-polypropylene as compatibilizer - Rama, Mallikarjuna Shroff; Neppalli, Ramesh; Chellaswamy, Ramesh; Swaminathan, Sivaram (Composites Science and Technology, 2010)
The efficiency of potassium succinate-g-polypropylene (KPPSA) as compatibilizer for the dispersion of clay in a high molecular weight polypropylene during melt mixing for the preparation of nanocomposites was evaluated and compared with maleic anhydride-g-polypropylene (PPMA). Nanocomposites were prepared by direct melt mixing and by masterbatch methods and the structure obtained was characterized by WAXD and TEM. The exfoliation and better dispersion of the organoclay was observed with KPPSA than PPMA. The dispersion of clay was found to be dependent on the method of preparation, type and the amount of compatibilizer used. The dispersion was better when the nanocomposites were prepared by two step masterbatch route than the single step direct mixing method. Flexural moduli and crystallization behavior were studied and correlated with the dispersion of organoclay in the PP matrix. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: differential scanning calorimetry; Mechanical property; Nano composites; Nanoclays; polypropylene

Experimental and theoretical study on the remarkable influence of protecting groups on the selectivity of addition of amines to vinyl sulfone-modified hex-2-enopyranosides - Bhattacharya, Rahul; Kesharwani, Manoj K.; Manna, Chinmoy; Ganguly, Bishwajit; Suresh, Cheravakattu G.; Pathak, Tanmaya (Journal of Organic Chemistry, 2010)
Although phenylmethylene-protected vinyl sulfone-modified carbohydrate 2 alpha reacts with both primary and secondary amines in Michael fashion to afford aminated products, only primary amines react with the dibenzyl-protected 3 alpha, 6-O-trityl-protected 4 alpha, and unprotected 5 alpha, highlighting for the first time the remarkable influence of protecting, groups on the reaction patterns of vinyl sulfone-modified carbohydrates. The quantum chemical calculations suggest that the Michael addition of amines and proton transfer to vinyl sulfone-modified carbohydrates 2 alpha and 5 alpha are possible via relay process in a concerted mechanism. These calculations reveal that the addition of primary amines to vinyl sulfone-modified carbohydrate is preferential due to the low activation energy barriers, whereas the addition of secondary amines has relatively higher activation energy barriers. The theoretical conclusions are in line with the experimental observations.

Expression profiling of various genes during the fruit development and ripening of mango - Pandit, Sagar S.; Kulkarni, Ram S.; Giri, Ashok P.; Koellner, Tobias G.; Degenhardt, Joerg; Gershenzon, Jonathan; Gupta, Vidya S. (Plant Physiology and Biochemistry, 2010)
Mango (Mangifera indica L. cv. Alphonso) development and ripening are the programmed processes; conventional indices and volatile markers help to determine agronomically important stages of fruit life (fruit-setting, harvesting maturity and ripening climacteric). However, more and precise markers are required to understand this programming; apparently, fruit's transcriptome can be a good source of such markers. Therefore, we isolated 18 genes related to the physiology and biochemistry of the fruit and profiled their expression in developing and ripening fruits, flowers and leaves of mango using relative quantitation PCR. In most of the tissues, genes related to primary metabolism, abiotic stress, ethylene response and protein turnover showed high expression as compared to that of the genes related to flavor production. Metallothionin and/or ethylene-response transcription factor showed highest level of transcript abundance in all the tissues. Expressions of mono- and sesquiterpene synthases and 14-3-3 lowered during ripening; whereas, that of lipoxygenase, ethylene-response factor and ubiquitin-protein ligase increased during ripening. Based on these expression profiles, flower showed better positive correlation with developing and ripening fruits than leaf. Most of the genes showed their least expression on the second day of harvest, suggesting that harvesting signals significantly affect the fruit metabolism. Important stages in the fruit life were clearly indicated by the significant changes in the expression levels of various genes. These indications complemented those from the previous analyses of fruit development, ripening and volatile emission, revealing the harmony between physiological, biochemical and molecular activities of the fruit. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Mangifera indica; Stress response; Terpene metabolism; Transcriptome analysis

Early stages of unwinding of zwitterionic alpha-helical homopolymeric peptides - Pandey, Prithvi Raj; Roy, Sudip (Chemical Physics Letters, 2011)
Unwinding mechanisms of helices of the zwitterionic polyalanine, polyleucine, and polylysine were studied using classical molecular dynamics simulation at 300 K temperature. Interestingly the helices of polyalanine and polyleucine start to unwind from the terminals, which is further relayed to the middle of the chain with time. Polylysine helix also starts to unwind from the terminals of the alpha-helical chain but the unwinding is not relayed to the middle. The reason behind this observation is investigated whether the presence of -NH(2) groups in the side chain of polylysine is influencing the unwinding. Two competitive mechanisms, fluctuation of the terminal residues and exchange of H-bonds between residues and water trigger the process of unwinding. (C) 2011 Elsevier B. V. All rights reserved.

Ecofriendly hydrogen production from abundant hydrogen sulfide using solar light-driven hierarchical nanostructured ZnIn2S4 photocatalyst - Chaudhari, Nilima S.; Bhirud, Ashwini P.; Sonawane, Ravindra S.; Nikam, Latesh K.; Warule, Sambhaji S.; Rane, Vilas H.; Kale, Bharat B. (Green Chemistry, 2011)
It is quite well-known that refineries are producing huge amount of H2S which has been used to produce sulphur and water using the well-known Claus process. This process is not an economically viable process, due to the high-cost chemical process and creates further acute environmental problems. Therefore, we have demonstrated the conversion of poisonous H2S into H-2 using an ecofriendly phocatalysis process which is a green unconventional energy source. We have investigated ecofriendly nanostructured ZnIn2S4 photocatalyst to produce hydrogen from H2S using solar light. We also demonstrate the controlled synthesis of hierarchical nanostructured ZnIn2S4 using a facile hydrothermal method. The morphologies obtained have been greatly influenced by the presence of triethylamine (TEA) with various concentrations during the reaction. Surprisingly, a highly crystalline hexagonal layer structured ZnIn2S4 was obtained instead of cubic spinel. The hierarchical nanostructure, i.e. marigold flower-like morphology, was obtained without any surfactant. The thin and transparent petals self-assembled to form the unique nanostructured marigold flower. The highly crystalline puffy marigold flowers and nanoplates/nanostrips were obtained using TEA-assisted hydrothermal synthesis. Optical study shows the band gap in the range of 2.34-2.48 eV. Considering the band gap in the visible region, ZnIn2S4 is used as photocatalyst for hydrogen production from hydrogen sulphide under solar light which is hitherto unattempted. The constant photocatalytic activity of hydrogen evolution, i.e. 5287 mu mol h(-1), was obtained using such hierarchical nanostructured ZnIn2S4 under visible light irradiation. It is noteworthy that the H-2 evolution rate obtained is much higher compared to earlier reported photocatalysts. Considering the significance of morphologies for photocatalytic application, the formation mechanism has also been furnished. The unique hierarchical nanostructured ZnIn2S4 ternary semiconductor having hexagonal layer will have potential applications in solar cells, LEDs, charge storage, electrochemical recording, thermoelectricity and other prospective electronic and optical devices.

Effect of aluminium doping on structural and gas sensing properties of zinc oxide thin films deposited by spray pyrolysis - Badadhe, Satish S.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2011)
A facile spray pyrolysis route is used to deposit aluminium doped ZnO (AZO) thin films on to the glass substrates. It is observed that on aluminium doping the particle size of ZnO reduces significantly; moreover, uniformity of particle also gets enhanced. Their XRD study reveals that intensity ratio of crystal planes depend on the aluminium doping concentration. The gas response studies of; similar to 800 nm thick Al-doped ZnO films at different operating temperatures show that 5 at% Al-doped ZnO thin film exhibits highest response towards H(2)S gas at 200 degrees C. The results suggest that the gas response strongly depends on the particle size and aluminium doping in the ZnO. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Aluminium; H(2)S sensor; Spray pyrolysis; thin film; Zinc oxide

Effect of blend composition and organoclay loading on the nanocomposite structure and properties of miscible poly(methyl methacrylate)/poly(styrene-co-acrylonitrile) blends - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2011)
Organically-modified montmorillonite clay nanocomposites of poly(styrene-co-acrylonitrile) (SAN), poly(methyl methacrylate) (PMMA) and SAN/PMMA miscible blend are investigated. Structure characteristics at the nanoscale and microscale and thermal and tensile properties are studied as a function of polymer blend composition and filler loading fraction. Blend miscibility and T(g) are unaffected by up to 10% by wt. organoclay. Thermal degradation stability increases with SAN content and exhibits an optimum value of clay loading. Stiffness shows significant improvement. Tensile strength and elongation-at-break suffer as a result of nanocomposite formation. Modulus shows a maximum enhancement of 57% (5 +/- 0.06 GPa at 10 wt% filler, 20/80 SAN/PMMA) and varies linearly with clay fraction for all compositions of matrix phase. Predictions of Halpin-Tsai composite model are in excellent agreement with the experimental behavior over full range of polymer blend composition. Fundamental aspects of a polymer blend-clay nanocomposite are clarified, such as lack of additional synergy between clay platelets and matrix, and tensile ductility reduction, compared with polymer-clay system. POLYM. ENG. SCI., 51:979-991, 2011. (C) 2011 Society of Plastics Engineers

Effect of chemical substituents on the structure of glassy diphenyl polycarbonates - Sulatha, M. S.; Natarajan, Upendra (Journal of Physical Chemistry B, 2011)
Polycarbonates offer a wide variety of physical property behavior that is difficult to predict due to complexities at the molecular scale. Here, the physical structure of amorphous glassy polycarbonates having aliphatic and cycloaliphatic chemical groups is explored through atomistic simulations. The influence of chemical structure on solubility parameter, torsion distributions, radial distribution function, scattering structure factor; orientation distributions of phenylene rings and carbonate groups, and free volume distributions, leading to interchain packing effects, are shown. The effect of the cyclohexyl ring at the isopropylidene carbon as compared to the effect of the methyl groups positioned on the phenylene rings results in a larger reduction in the solubility parameter (delta). The interchain distance estimated for polycarbonates in this work is in the range of 5-5.8 angstrom. The o-methyl groups on the phenylene, rings, as compared to a cyclohexyl ring, lead to higher interchain distances. The highest interchain distance is observed with a trimethylcyclohexylidene group at the isopropylidene carbon. Atomistic simulations reveal two different types of packing arrangement of nearest neighbor chains in the glassy state, one type of which agrees with the NMR experimental data The fundamental insights provided here can be utilized for design of chemical structures for tailored macroscopic properties.

Effect of composition on chain dimensions of styrene-methylmethacrylate random copolymers under theta condition - Karyappa, Rahul B.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2011)
Rotational-isomeric-state (RIS)-Metropolis Monte Carlo simulations are performed on poly(styrene-ran-methylmethacrylate) random copolymers to study the intrinsic unperturbed (theta-condition) dimensions. Mean-squared end-to-end distance (< r(2)>(o)), mean-squared radius of gyration (< s(2)>(o)), and characteristic ratio (C(n)) have been calculated for these copolymers constituted by different overall chemical compositions (styrene fractions 0.29, 0.56, and 0.70). Calculations were carried out with chains of 500 repeating units. With an increase in the styrene content there is an increase in (< r(2)>(o)), `, and C(n), in agreement with experimental observations. An increase in the fraction of trans conformational states in the backbone torsion angles is found to be responsible for the exhibited chain expansion behavior. The dimensions calculated by the Monte Carlo simulations agree well with experimental values reported in the literature.
Keywords: chain dimensions; Monte Carlo; poly(methyl methacrylate); Polystyrene; random copolymer; theta conditions

Effect of inter-particle interactions on the magnetic properties of magnetite nanoparticles after coating with dextran - Sreeja, V.; Joy, Pattayil Alias (International Journal of Nanotechnology, 2011)
Nanoparticles of magnetite (Fe3O4) are synthesised by a coprecipitation method and coated with the biocompatible polymer, dextran. The uncoated and dextran coated magnetite nanoparticles are characterised by powder X-ray diffraction, infrared spectroscopy, transmission electron microscopy, and magnetic measurements. The magnetic properties of the uncoated and coated magnetite nanoparticles are compared to study the effect of inter-particle magnetic interactions on the magnetic characteristics. Absence of magnetic hysteresis at room temperature indicates the superparamagnetic nature of the two samples. Evidence for the effect of reduced inter-particle magnetic interactions is directly obtained from the field dependence of magnetisation at room temperature. The decreased superparamagnetic blocking temperature and the nature and shape of the field cooled magnetisation curve of the dextran coated sample further confirmed that the inter-particle magnetic interactions are completely suppressed after coating.
Keywords: dextran coating; magnetic interactions; magnetic properties; magnetite; Nanoparticles

Effect of particle size and annealing on spin and phonon behavior in TbMnO3 - Das, Raja; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2011)
Interest has grown to study TbMnO3 as it was recently reported to show a gigantic magnetoelectric effect. Here, we report the synthesis and detailed magnetic and Raman spectroscopy study on TbMnO3 particles of size similar to 25 nm and 2-3 mu m, respectively. The incommensurate-commensurate (lock-in) transition, usually observed at 27 K for bulk phase of TbMnO3 was not observed in susceptibility versus T curve but was seen at 30 K in the coercivity versus T curve in similar to 25 nm particles. This transition, which is due to the spin modulation length scale, gets weakened in nanosize due to the increased intrinsic lattice strain observed in 2-3 mu m particles, due to the effect of increased particle size. The increased value of magnetization in the 2-3 mu m sample was attributed to double exchange interactions between Mn+3 and Mn+4 spins. The role of annealing related effects on the fate of the Neel temperature for TbMnO3 was investigated. Raman spectroscopy indicated a decrease in the lattice distortion for similar to 25 nm particles. (c) 2011 American Institute of Physics. [doi:10.1063/1.3563571]

Effect of solvation on the vertical ionization energy of thymine: from microhydration to bulk - Ghosh, Debashree; Isayev, Olexandr; Slipchenko, Lyudmila V.; Krylov, Anna I. (Journal of Physical Chemistry A, 2011)
The effect of hydration on the vertical ionization energy (VIE) of thymine was characterized using equation-of-motion ionization potential coupled-cluster (EOM-IP-CCSD) and effective fragment potential (EFP) methods. We considered several microsolvated clusters as well as thymine solvated in bulk water. The VIE in bulk water was computed by averaging over solvent-solute configurations obtained from equilibrium molecular dynamics trajectories at 300 K. The effect of microsolvation was analyzed and contrasted against the combined effect of the first solvation shell in bulk water. Microsolvation reduces the ionization energy (IE) by about 0.1 eV per water molecule, while the first solvation shell increases the IE by 0.1 eV. The subsequent solvation lowers the IE, and the bulk value of the solvent-induced shift of thymine's VIE is approximately -0.9 eV. The combined effect of the first solvation shell was explained in terms of specific solute-solvent interactions, which were investigated using model structures. The convergence of LE to the bulk value requires the hydration sphere of approximately 13.5 angstrom radius. The performance of the EOM-IP-CCSD/EFP scheme was benchmarked against full EOM-IP-CCSD using microhydrated structures. The errors were found to be less than 0.01-0.02 eV. The relative importance of the polarization and higher multipole moments in EFP model was also investigated.

Effect of tethering on the structure-property relationship of TPU-dual modified laponite clay nanocomposites prepared by ex-situ and in-situ techniques - Mishra, Ananta K.; Chattopadhyay, Santanu; Rajamohanan, P. R.; Nando, Golok B. (Polymer, 2011)
Novel Thermoplastic Polyurethane (TPU)-dual modified Laponite clay nanocomposites were prepared by ex-situ and in-situ techniques. Two types of modified clays used in this work differ from each other by the number of active functional groups (tethering). Modified nanoclays are characterized by FTIR, Solid State NMR, XRD and TGA. Structural differences in the modified clays lead to novel tubular, elliptical and spherically aggregated morphologies of clays together with the hard segments of TPU. Changes in such morphology result in the difference in segmental relaxation, mechanical and rheological properties of the nanocomposites. In-situ prepared nanocomposites register inferior properties as compared to their ex-situ counterparts. The percent improvement in tensile strength and elongation at break of the ex-situ prepared nanocomposites with the modified clay having lesser tethering are found to be 67% and 208%, respectively. Thermal stability is enhanced by 35 degrees C as compared to that of the neat TPU. (C) 2010 Published by Elsevier Ltd.
Keywords: Dual modification; Nanocomposites; Thermoplastic polyurethane

Effect of triples to dipole moments in fock-space multireference coupled cluster method - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2011)
In this paper, we present the new implementation of partial triples for the dipole moment of doublet radicals in Lagrangian formulation of Fock-space multireference coupled cluster (A-FSMRCC) response method. We have implemented a specific scheme of noniterative triples, in addition to singles and doubles schemes, which accounts for the effects appearing at least at the third order in dipole moments. The method is applied to the ground states of OH, OOH, HCOO, CN, CH, and PO radicals.

Efficiency and recycling capability of montmorillonite supported Fe-Ni bimetallic nanocomposites towards hexavalent chromium remediation - Kadu, Brijesh S.; Sathe, Yogesh D.; Ingle, Abhijit B.; Chikate, Rajeev C.; Patil, Kashinath R.; Rode, Chandrashekhar V. (Applied Catalysis B-Environmental, 2011)
The remediation of Cr(VI) from simulated water streams is investigated using Fe-Ni bimetallic nanoparticles (Fe-Ni NPs) and their nanocomposites prepared with montmorillonite (MMT) clay. These nanocomposites are characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) surface area analyses. XRD analysis revealed proper dispersion as well as intercalation of Fe-Ni NPs in the clay matrix. TEM of nanocomposites showed the presence of spherical particles having a size of 20-40 nm. Batch experiments with a 25 mg L(-1) Cr(VI) solution and 2 g L-1 Fe-Ni NPs exhibited complete reduction of Cr(VI) within 10 min that follows first order reaction kinetics. Amongst 25%, 50%, 75% in situ and loaded nanocomposites, 75% compositions possess better activity with enhanced reduction capacity below pH 4 due to generation of reactive H center dot species. XPS analysis of nanocomposites after Cr(VI) treatment suggested that reduction process occurs through Cr(111) formation followed by its subsequent reduction to Cr(0). Their potentiality towards reusage is established from the recycling experiments that revealed the order of efficiency as 75% in situ > Fe-Ni NPs > 75% loaded nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cr(VI) remediation; Iron-nickel bimetallics; Montmorillonite; Nanocomposites; Recycling

Efficient convergent access to spiroketal segment of (+)-spiroxaline methyl ether - Singh, Mandeep; N. P. Argade (Synthesis-Stuttgart, 2011)
Starting from trimethylsilylacetylene, a facile synthesis of optically pure spiroketal unit of (+)-spiroxaline methyl ether has been described. The synthesis entails stepwise alkylation and acylation of an alkyne with two different readily available chiral building blocks followed by the reductive in situ regio- and stereoselective spiroketalization pathway.
Keywords: (+)-spiroketal segment synthesis; (R)-gamma-valerolactone; (R)-oxirane; alkyne; nucleophilic reactions

Efficient hydrogenation of organic carbonates, carbamates, and formates indicates alternative routes to methanol based on CO2 and CO - Balaraman, Ekambaram; Gunanathan, Chidambaram; Zhang, Jing; Shimon, Linda J. W.; Milstein, David (Nature Chemistry, 2011)
Catalytic hydrogenation of organic carbonates, carbamates and formates is of significant interest both conceptually and practically, because these compounds can be produced from CO2 and CO, and their mild hydrogenation can provide alternative, mild approaches to the indirect hydrogenation of CO2 and CO to methanol, an important fuel and synthetic building block. Here, we report for the first time catalytic hydrogenation of organic carbonates to alcohols, and carbamates to alcohols and amines. Unprecedented homogeneously catalysed hydrogenation of organic formates to methanol has also been accomplished. The reactions are efficiently catalysed by dearomatized PNN Ru(II) pincer complexes derived from pyridine- and bipyridine-based tridentate ligands. These atom-economical reactions proceed under neutral, homogeneous conditions, at mild temperatures and under mild hydrogen pressures, and can operate in the absence of solvent with no generation of waste, representing the ultimate ‘green’ reactions. A possible mechanism involves metal–ligand cooperation by aromatization–dearomatization of the heteroaromatic pincer core.

Efficient synthesis of benzodiazepinyl phosphonates as clostripain inhibitors via FeCl3 catalyzed four-component reaction - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Raut, Dnyaneshwar S.; Mhaindarkar, Vaibhav P.; Khan, Mohammad Islam (Organic & Biomolecular Chemistry, 2011)
A novel one-pot route for the synthesis of benzodiazepinyl phosphonates (BDPs) has been achieved. FeCl3 efficiently catalyzed four-component condensation of diamines, acetone and phosphites in the presence of molecular sieves to furnish BDPs as novel chemical entities with good yield. The synthesized BDPs have shown significant protease inhibition activity against clostripain, a disease model for gas gangrene, suggesting that these novel chemical entities could be further explored as cysteine protease inhibitors.

Efficient synthesis of benzofuranones: N-heterocyclic carbene (NHC)/base-catalyzed hydroacylation-stetter-rearrangement cascade - Padmanaban, Mohan; Biju, Akkattu T.; Glorius, Frank (Organic Letters, 2011)
A N-heterocyclic carbene/base-catalyzed cascade reaction leading to the formation of functionalized benzofuranones is reported. The reaction proceeds via an intramolecular hydroacylation of unactivated alkynes followed by an intermolecular Stetter reaction and a base-catalyzed chromanone to benzofuranone rearrangement.

Electrical behavior of silver particulate films deposited on 8 MeV electron beam irradiated softened polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Journal of Materials Science-Materials in Electronics, 2011)
Results of the investigations carried out on the electrical behavior of silver particulate films deposited on electron beam irradiated polystyrene (PS) coated substrates held at a temperature of 455 K in a vacuum of 8 x 10(-6) torr at a constant deposition rate of 0.4 nm/s are reported. It is known that when metals are evaporated on to softened polymer substrates, subsurface particulate structures are formed whose morphology is dependent on deposition parameters. Further, it was shown that the morphology is dependent on polymer-metal interaction. The present work demonstrates that the polymer-metal interaction can be brought about in inert polymers like PS by electron irradiation. The results indicate that the films deposited on PS irradiated to a dose of 20 and 25 kGy gives rise to smaller clusters with smaller inter-cluster separation, better suited for sensor applications. The induced polymer-metal interaction is attributed to the creation of free radicals due to the 8 MeV electron irradiation.

Electrochemical fluorescence switching from a patternable poly(1,3,4-oxadiazole) thin film - Seo, Seogjae; Kim, Yuna; You, Jungmok; Sarwade, Bhimrao D.; Wadgaonkar, Prakash P.; Menon, Shamal K.; More, Arvind S.; Kim, Eunkyoung (Macromolecular Rapid Communications, 2011)
A highly soluble poly(1,3,4-oxadiazole) (POD) substituted with long alkyl chains was examined for electrochemical fluorescence switching. The high solubility of the polymers enabled a simple fabrication of an electrochemical cell, which showed reversible fluorescence switching between dark (n-doping) and bright (neutral) states with a maximum on/off ratio of 2.5 and a cyclability longer than 1000 cycles. Photochemical cleavage of the oxadiazole in POD allowed photo-patterning of the POD film upon exposure to UV source. The patterned POD films displayed patterned image reversibly under a step potential of +1.8/-1.8V.
Keywords: fluorescence; lithography; Luminescence; photochemistry; switching device

Electrochemical unzipping of multi-walled carbon nanotubes for facile synthesis of high-quality graphene nanoribbons - Shinde, Dhanraj B.; Debgupta, Joyashish; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of the American Chemical Society, 2011)
Here we report a remarkable transformation of carbon nanotubes (CNTs) to nanoribbons composed of a few layers of graphene by a two-step electrochemical approach. This consists of the oxidation of CNTs at controlled potential, followed by reduction to form graphene nanoribbons (GNRs) having smooth edges and fewer defects, as evidenced by multiple characterization techniques, including Raman spectroscopy, atomic force microscopy, and transmission electron microscopy. This type of ``unzipping'' of CNTs (single-walled, multi-walled) in the presence of an interfacial electric field provides unique advantages with respect to the orientation of CNTs, which might make possible the production of GNRs with controlled widths and fewer defects.

Electronic decoupling of surface layers and its influence in oxidation catalysis: More wine in old bottle - Chinnakonda, Gopinath S. (241st National Meeting and Exposition of the American-Chemical-Society (ACS), 2011)

Electron-rich PNP- and PNN-type Ru(II) hydrido-borohydride complexes. synthesis, structure and catalytic activity towards dehydrogenation of alcohols and hydrogenation of esters - Zhang, Jing; Balaraman, Ekambaram; Leitus, Gregory; Milstein, David (Organometallics, 2011)
Electron-rich PNP- and PNN-type ruthenium(II) hydrido borohydride pincer complexes, [RuH(BH4)(tBu-PNP)] (tBu-PNP = (2,6-bis(di-tert-butylphosphinomethyl)pyridine) (5) and [RuH(BH4)(tBu-PNN)] (tBu-PNN = 2-di-tert-butylphosphinomethyl-6-diethylaminomethylpyridine) (6), were prepared from their corresponding N2-bridged dinuclear Ru(II) complexes [(tBu-PNP)RuCl2]2(μ-N2) (3) and [(tBu-PNN)RuCl2]2(μ-N2) (4), respectively. The X-ray structure of 5 reveals a BH4– anion η2 coordinated to ruthenium through two bridging hydrides. A variable-temperature 1H NMR study of 6 exhibits interesting fluxional behavior of the BH4– ligand. Similarly, the Ru(II) hydrido borohydride complex 9, in which the BH4– moiety is coordinated in a η1 bonding mode, was obtained by reaction of [RuCl2(PPh3)(iPr-PNP)] (iPr-PNP = 2,6-bis(diisopropylphosphinomethyl)pyridine) (8) with two equivalents of NaBH4 at room temperature. The hydrido borohydride pincer complexes 5, 6, and 9 catalyze the acceptorless dehydrogenative coupling of primary alcohols to esters and the dehydrogenation of secondary alcohols to the corresponding ketones, accompanied by evolution of hydrogen gas. The reactivity follows the order 6 > 9 > 5. With the hydrido borohydride complex 6 as catalyst, high yields (up to 98%) and high turnover numbers (TON ∼1000) were obtained in the dehydrogenation of primary alcohols under mild and neutral conditions. In addition, 6 effectively catalyzes the hydrogenation of nonactivated aromatic and aliphatic esters to the corresponding alcohols with TON ∼200 under a relatively mild pressure of dihydrogen and neutral and homogeneous conditions. Thus, an efficient homogeneous catalytic system for the dehydrogenation–hydrogenation reactions of alcohols is developed, which is relevant to the current interest in hydrogen storage.

Employing homoenolates generated by NHC catalysis in carbon-carbon bond-forming reactions: state of the art - Nair, Vijay; Menon, Rajeev S.; Biju, Akkattu T.; Sinu, C. R.; Paul, Rony Rajan; Jose, Anu; Sreekumar, Vellalath (Chemical Society Reviews, 2011)
Homoenolate is a reactive intermediate that possesses an anionic or nucleophilic carbon beta to a carbonyl group or its synthetic equivalent. The recent discovery that homoenolates can be generated from alpha,beta-unsaturated aldehydes via N-Heterocyclic Carbene (NHC) catalysis has led to the development of a number of new reactions. A majority of such reactions include the use of carbon-based electrophiles, such as aldehydes, imines, enones, dienones etc. resulting in the formation of a variety of annulated as well as acyclic products. The easy availability of chiral NHCs has allowed the development of very efficient enantioselective variants of these reactions also. The tolerance showed by NHCs towards magnesium and titanium based Lewis acids has been exploited in the invention of cooperative catalytic processes. This tutorial review focuses on these and other types of homoenolate reactions reported recently, and in the process, updates the previous account published in 2008 in this journal.

Enantioselective total syntheses of (-)-isonitramine, (-)-sibirine, and (+)-nitramine by ring-closing metathesis - Pandey, Ganesh; Kumara, Prasanna C.; Burugu, Shiva Kumar; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
Concise enantioselective total syntheses of naturally occurring 2-azaspiro[5,5]undecan-7-ol (Nitraria) alkaloids viz. ()-isonitramine, ()-sibirine, and (+)-nitramine are accomplished in 42, 38, and 25?% overall yield, respectively, in six steps starting from enantiomerically pure (S)-methyl 3-allyl-2-oxo-1,2,3,6-tetrahydropyridine-3-carboxylate (>99?%?ee). The key feature of the syntheses involves diastereoselective HosomiSakurai allylation followed by ring-closing metathesis.
Keywords: Alk-aloids; Allylation; Amino alcohols; Metathesis; Total synthesis

Enantiospecific route to (+)-(1R, 3S)-cis-chrysanthemic acid from (-)-D-pantolactone(1) - Hajare, Atul K.; Datrange, Laxmikant S.; Murthy, Y. L. N.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2011)
In this paper, a novel route for the synthesis of (+)-(1R,3S)-cis-chrysanthemic acid is described. The use of readily available (-)-D-pantolactone as a starting point, application of ring-closing metathesis to form the cyclopentene intermediate, and Haller-Bauer/Grob-type fragmentation to form the target compound are the highlights of the present synthesis.
Keywords: alkenes; Metathesis; ring closure; stereoselective synthesis; Wittig reaction

Energy optimization in integrated pulp and paper mills with recourse to environmental benefits - Pharande, V. A.; Asthana, S. R.; Saini, D. R.; Kaul, S. N. (Journal of Scientific & Industrial Research, 2011)
This study focuses on energy optimization in evaporator and digester of integrated pulp and paper mills in India, and recommends application of 7 effects/plates evaporator in place of 5 effects/plates normally used. Steam economy resulting from this modification is definitely more than 7. Pinch technology is found suitable for optimization of controlled parameters in the digester. Using recommendations, total energy savings was observed in West Coast Paper Mill (11.74%) and Star Paper Mill (12.97%). Environmental benefits that will accrue in terms of reductions in emissions are: SPM, 46464-48664 TPA; SO(2), 1045 kg/annum; H(2)S, 55,020 kg/annum; and CO(2), 13612 TPA.
Keywords: Air emissions; Digester; Evaporator; Pinch technology; Steam economy

Enhanced dielectric permittivity in poly (vinylidene) fluoride/multiwalled carbon nanotubes nanocomposite thin films fabricated by pulsed laser deposition - Chanmal, Chetan; Deo, Meenal S.; Jog, Jyoti Prakash (Applied Surface Science, 2011)
The fabrication of high quality thin films of poly (vinylidene fluoride) embedded with multiwalled carbon nanotubes using pulsed laser deposition technique is reported. The prepared films were characterized for structural, morphology and dielectric properties. The morphology analysis revealed uniform dispersion of multiwalled carbon nanotubes throughout the polymer matrix. X-ray diffraction results suggested that the poly (vinylidene fluoride) film is in amorphous phase while addition of multiwalled carbon nanotubes showed presence of crystalline peaks in the nanocomposites films. It was interesting to note that the nanocomposite films exhibits significant enhancement of the ferroelectric beta-phase as evidenced by the X-ray diffraction and Fourier transform infrared spectroscopy results. The dielectric analysis shows a remarkable enhancement in the dielectric permittivity of nanocomposites with lower loss and conductivity level. The results can be attributed to the formation of minicapacitor network and relatively higher percolation threshold in the nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dielectric permittivity; Ferroelectric polymer; Percolation threshold; pulsed laser deposition; Thin films

Enhanced DNA binding of 9-omega-amino alkyl ether analogs from the plant alkaloid berberine - Islam, Md Maidul; Basu, Anirban; Hossain, Maidul; Sureshkumar, Gopalsamy; Hotha, Srinivas; Kumar, Gopinatha Suresh (DNA and Cell Biology, 2011)
To understand the structure-activity relationship of isoquinoline alkaloids, absorption, fluorescence, circular dichroism, and thermodynamics were employed to study the interaction of five C-9-omega-amino alkyl ether analogs from the plant alkaloid berberine with double-stranded calf thymus DNA. The C-9 derivatization resulted in dramatic enhancements in the fluorescence emission of these compounds. The most remarkable changes in the spectral and binding properties were in the BC4 and BC5 derivatives. Interactions of these analogs, which have an additional recognition motif with DNA, were evaluated through different spectroscopic and calorimetric titration experiments. The analogs remarkably enhanced the DNA binding affinity and the same was directly dependent on the alkyl chain length. The analog with six alkyl chains enhanced the DNA binding affinity by about 33 times compared with berberine. The binding became more entropically driven with increasing chain length. These results may be of potential use in the design of berberine derivatives and understanding of the structure-activity relationship for improved therapeutic applications.

Enhanced DSSC performance with high surface area thin anatase TiO2 nanoleaves - Dhas, Vivek V.; Muduli, Subas; Agarkar, Shruti A.; Rana, Abhimanyu; Hannoyer, Beatrice; Banerjee, Rahul; Ogale, Satishchandra B. (Solar Energy, 2011)
Thin anatase TiO2 nanoleaves (NLs) with high surface area (similar to 93 m(2)/g) are synthesized by hydrothermal route and dye-sensitized solar cells (DSSC) made using such NLs are compared with those made with hydro-thermally synthesized TiO2 nanoparticles and the Degussa P25 powder. The NLs-based DSSCs show increment of 16% and 24% in the total conversion efficiency over the cells made with NPs and P25 respectively. Interestingly, the highest increment in the conversion efficiency (similar to 35%) is achieved for cells made using a 50:50 (wt/wt) mixture of NLs and NPs. In this case the dye loading is found to be >50% higher than the case of NP films. Moreover the DC resistance of diffusion of I-3(-) in electrolyte (as revealed by the electrochemical impedance spectroscopy) is substantially lower than the NP film case, other cell parameters being nominally comparable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cells; Electrochemical impedance spectroscopy; hydrothermal

Enhanced electrocatalytic performance of functionalized carbon nanotube electrodes for oxygen reduction in proton exchange membrane fuel cells - Kannan, Ramaiyan; Bipinlal, Unni; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Although nitrogen doped CNTs (N-CNTs) are considered as a promising alternative to platinized carbon for the oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells (PEMFCs), the origin of the enhanced ORR activity with N-CNTs is not clear at present. Among several plausible reasons, the exposure of edge plane and creation of impurity band/surface states near the Fermi level are considered as major causes behind the catalytic activity. However, CNTs without nitrogen doping are not known to catalyze the ORR. In this work, we study the ORR activity of functionalized carbon nanotubes with different functional groups, such as sulfonic acid and phosphonic acid, in order to understand the role of surface functionalities in catalyzing the reaction. Functionalized CNTs show significantly enhanced activity towards the ORR, while CNTs without such surface functional groups do not reveal any such special ORR activity. Linear sweep voltammetry experiments with different rotation rates show diffusion controlled limiting current values for functionalized CNTs, and the `n' values derived from Koutecky-Levich plots are 3.3 and 1.7 for S-MWCNTs and P-MWCNTs, respectively. This work demonstrates the ORR activity of functionalized MWCNTs, which opens up new strategies for electrocatalyst design in PEMFCs.

Enhanced electrocatalytic performance of interconnected Rh nano-chains towards formic acid oxidation - Sathe, Bhaskar R.; Balan, Beena K.; Pillai, Vijayamohanan K. (Energy & Environmental Science, 2011)
A chain-like assembly of rhodium nanoparticles (5-7 nm mean diameter) has been synthesized from rhodium chloride with the help of polydentate molecules like tartaric and ascorbic acids (1 : 3 in mM scale) as capping agents at room temperature. Subsequent characterization using transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy reveals a unique inter-connected network like features, while their electrochemical behavior using cyclic voltammetry and current-time transient suggests potential applications as electrocatalysts in fuel cells. A significant negative shift in the onset potential as well as higher anodic peak current density for formic acid oxidation on Rh-tartaric acid (Rh-TA) as compared to that of bulk Rh metal confirms their higher electrocatalytic activity. Interestingly, the enhancement factor (R) with respect to that of bulk metallic Rh towards formic acid oxidation ranges up to 2000% for Rh-TA and 1200% for Rh-AA (Rh-ascorbic acid) respectively. The composition of Rh nano-chains has been further analyzed with thermogravimetry and Fourier transform infra-red spectroscopy to demonstrate the importance of controlling the chain topology using polyfunctional organic molecules. These findings open up new possibilities for tailoring nanostructured electrodes with potential benefits since the development of a better electrocatalysts for many fuel cell reactions continues to be an important challenge.

Enhanced electron transport through template-derived pore channels in dye-sensitized solar cells - Phadke, Sarika; Du Pasquier, Aurelien; Birnie, Dunbar P. (Journal of Physical Chemistry C, 2011)
Dye-sensitized solar cells use porous nanoparticle TiO(2) coating as their photoanode. To obtain effective dye adsorption and better electrolyte permeation in the TiO(2) coating, the porosity structure must be fully, three-dimensionally interconnected. Templated processing offers the advantage of preparing TiO(2) photoanodes in controlled shape and interconnection to the porosity structures that result, including the creation of dual size scale porosity in some cases. In the present work, an emulsion templating method was employed to obtain the dual porosity in the titania coating. We have studied the effect of the enhanced permeation of the electrolyte provided by these interconnected pore channels using electrochemical impedance spectroscopy. The change in internal resistances of the dye-sensitized solar cell during operation is correlated with the microstructural features using scanning electron microscopy, mercury porosimetry and I-V characterization.

Enhanced enzymatic hydrolysis of cellulose by partial modification of its chemical structure - Shaikh, H. M.; Adsul, Mukund G.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2011)
A series of 2,3-dialdehyde celluloses with different degrees of oxidation were used for deriving corresponding dicarboxylate, dicarboxy, and Schiff's base cellulose derivatives. The dialdehyde cellulose was hydrolyzed by cellulase to a lower extent than the starting cellulose, except at high levels of aldehyde content (above 50%). For dicarboxylate and dicarboxy celluloses, the highest level of oxidized NaDCC and DCC hydrolysed up to 70 and 60% respectively which was 3-4 times more than cellulose. The 2,3-dioxime cellulose derivative hydrolyzes only up to 16.3% for the highest level of oxidized dioxime. In the case of 2,3-diethylimine cellulose, all derivatives hydrolyse faster than the native cellulose. Up to 75% hydrolysis was observed for 2,3-diethyimine cellulose-50, 2,3-dipropylimine and 2,3-dibutylimine cellulose. The 2,3-dibenzylimine cellulose hydrolyses a little slower than the alkylimine derivatives. The 2,3-dihydrazone cellulose derivatives with all level of oxidation showed resistance towards enzymatic hydrolysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 2; 3-Dialdehyde celluloses; 3-Dibenzylimine cellulose; 3-Dibutylimine cellulose; 3-Dicarboxy celluloses; 3-Diethyimine cellulose; 3-Dihydrazone cellulose; 3-Dipropylimine cellulose; Cellulase; Enzymatic hydrolysis

Enhanced stability of G-quadruplexes from conformationally constrained aep-PNA backbone - Sharma, Nagendra K.; Ganesh, Krishna N. (Organic & Biomolecular Chemistry, 2011)
Nucleic (DNA) acids having contiguous stretch of G sequence form quadruplex structure, which is very critical to control cell division. Recently the existence of G-quadruplex in RNA is also reported in presence of monovalent metal ion. PNA is a promising DNA analogue which binds strongly to DNA to form PNA: DNA duplex or PNA(2) : DNA triplex. PNA also forms quadruplexes such G-quadruplex and i-motif in G and C-rich sequences respectively. aep-PNA containing a prolyl ring is one of several PNA analogues that provide rigidity and chirality in backbone and has binding affinity to natural DNA which is higher than that of PNA. Here we examine the ability of aep-PNA-G to form a quadruplex by UV, CD and mass spectroscopic techniques.

Enhancement of oxygen vacancies and solar photocatalytic activity of zinc oxide by incorporation of nonmetal - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Solid State Chemistry, 2011)
B-doped ZnO and N-doped ZnO powders have been synthesized by mechanochemical method and characterized by TG-DTA, XRD, SEM-EDX, XPS, UV-visible and photoluminescence (PL) spectra. X-ray diffraction data suggests the hexagonal wurtzite structure for modified ZnO crystallites and the incorporation of nonmetal expands the lattice constants of ZnO. The room temperature PL spectra suggest more number of oxygen vacancies exist in nonmetal-doped ZnO than that of undoped zinc oxide. XPS analysis shows the substitution of some of the O atoms of ZnO by nonmetal atoms. Solar photocatalytic activity of B-doped ZnO, N-doped ZnO and undoped ZnO was compared by means of oxidative photocatalytic degradation (PCD) of Bisphenol A (BPA). B-doped ZnO showed better solar PCD efficiency as compare to N-doped ZnO and undoped ZnO. The PCD of BPA follows first order reaction kinetics. The detail mechanism of PCD of Bisphenol A was proposed with the identification of intermediates such as hydroquinone, benzene-1,2,4-triol and 4-(2-hydroxypropan-2-yl) phenol. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Bisphenol A; Enhanced oxygen vacancies; Nonmetal doping; Photocatalysis; Sunlight

Enthalpic approach to delineate the interactions of cations of imidazolium-based ionic liquids with molecular solvents - Rai, Gitanjali; Kumar, Anil (Physical Chemistry Chemical Physics, 2011)
We present a systematic investigation on the enthalpic assessment of the interactions operating between the cation and anion of four imidazolium ionic liquids with aqueous and various nonaqueous solvents. Accurate experimental information gathered with the help of an isothermal titration calorimeter at 298.15 K has been analyzed for excess partial molar enthalpy of the ionic liquid, H(IL)(E), in terms of hydrophobic and solvation effects. The variations in the limiting excess partial molar enthalpy of the ionic liquid, H(IL)(E infinity), have been correlated with solvent properties. We have quantified the enthalpic effects due to dissociation of ionic liquids in very dilute solutions and to clathrate formation with the increasing concentration of ionic liquid. A change in enthalpic behavior from endothermic to exothermic is observed on increasing the carbon chain length attached to the imidazolium ring. The solvent reorganization around the cationic species has been unraveled by employing the ionic liquid interaction parameters called as H(IL-IL)(E) deduced from the H(IL)(E) data. The apparent relative molar enthalpy, phi(L), derived from H(IL)(E) data has been examined in the light of the specific ion interaction theory as advanced by Pitzer with accurate results.

Environmental potential applications of alkali metal exchanged zeolite x in carbon dioxide adsorption - Joshi, U. D.; Joshi, P. N.; Roh, H. S.; Yoon, W. L.; Shiralkar, V. P. (Research Journal of Chemistry and Environment, 2011)
The increasing atmospheric CO2 concentration, mainly caused by the Thermal Power Stations, Industrial sector and fossil fuel combustion, has led to consequences of global warming. Zeolitic adsorption processes is more promising, energy saving and viable method for CO2 removal in Comparison to other technologies. In order to examine the behavior and to establish the trends in carbon dioxide sorption, NaX zeolite (Si/Al = 1.15) and it's the modified forms with identical degree (55.5 +/- 2.5) of exchange by K+, Rb+ and Cs+ cations have been selected., The samples were characterized by powder XRD, Low temperature nitrogen adsorption/desorption measurements, chemical analysis and also for the intermediate electronegativity and the partial charges on the atoms using Sanderson's electronegativity equalization principle. The isotherms of carbon dioxide using these NaX, NaKX, NaRbX and NaCsX samples were measured at an interval of 30 K in the temperature range of 273 to 363 K up to 600 Torr. The uptake of CO2 was found to depend on both, the size of the nonframework cation and the temperature at which the isotherms were measured. The cations with lower charge density will have lower extent of electrostatic interaction with the sorbate molecules. Since CO2 has more linear quadrupole moment, it interacts mainly with the extra-framework cations and framework oxygen. The carbon dioxide sorption data satisfactorily represented by Langmuir and also analyzed for the chemical affinity. The Isosteric heat (q(st)) of NaX for the coverage of 20 molecules per unit cell is nearly equal to 26 kJ, mol(-1). The NaX and NaKX comparatively show a flat heat profile with the increasing amount sorbed than those of NaRbX and NaCsX indicating a balance between the strength of energetic heterogeneity of sorbate-sorbent interactions and sorbate-sorbate interactions.
Keywords: CO2 sorption; Ionic exchange; Isosteric heat; NaX zeolite; Theoretical models

Esterification of fatty acids with glycerol over Fe-Zn double-metal cyanide catalyst - Kotwal, Mehejabeen; Deshpande, Suvarna S.; Srinivas, D. (Catalysis Communications, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complex exhibits high catalytic activity for esterification of fatty acids (FA) with glycerol. DMC catalysts with varying acidities were prepared by synthesizing the material at four different temperatures (10, 25, 50 and 80 degrees C). The catalyst prepared at 50 degrees C exhibited highest catalytic activity. Catalytic activity of DMC was influenced by both acidity and surface area. Complete conversion of FA was achieved at 140-200 degrees C under atmospheric pressure. Chain length of FA was found to influence the rate of reaction and product selectivity. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid-catalyzed reaction; Double-metal cyanide (DMC); Esterification of fatty acid; Fatty acid glycerides; solid acid catalyst

Esterification of levulinic acid to n-butyl levulinate over heteropolyacid supported on acid-treated clay - Dharne, S.; Bokade, Vijay V. (Journal of Natural Gas Chemistry, 2011)
Levulinic acid has been identified as a promising green, biomass-derived platform chemical. n-Butyl levulinate is used as an important intermediate having diverse applications. The present work focuses on the synthesis of n-butyl levulinate by esterification of levulinic acid with n-butanol using heteropolyacid (HPA) supported on acid-treated clay montmorillonite (K10). 20% (w/w) dodecatungestophosphoric acid (DTPA) supported on K10 was found to be the most efficient catalyst with 97% levulinic acid conversion and 100% selectivity towards n-butyl levulinate. Effects of various process parameters were studied to examine the efficacy of 20% (w/w) DTPA/K10 for optimization of the activity.
Keywords: dodectungestophosphoric acid; K10; levulinic acid; n-butanol; n-Butyl levulinate

Eutectic mixture-directed kinetics of Diels-Alder reaction - Nagare, Amit S.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
In the search for environmentally benign solvent media, a new class of solvents composed of mixtures of carbohydrates with urea or methylated urea has been noted to be effective in enhancing the reaction rates of a bimolecular organic reaction like the Diels-Alder reaction of cyclopentadiene with methyl acrylate. The viscosity of these media appears to be an important parameter in controlling the second order kinetics.
Keywords: carbohydrates; Cycloaddition; Diels-Alder reaction; Dimethylurea; kinetics; Reaction rates; solvent effects; Urea; viscosity

Evidence of lateral heat transfer during laser assisted atom probe tomography analysis of large band gap materials - Bachhav, Mukesh N.; Danoix, R.; Vurpillot, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Danoix, F. (Applied Physics Letters, 2011)
Investigation of wustite (FeO), iron (Fe), and silicon (Si) specimens by infrared laser assisted three dimensional atom probe tomography shows evidence of confined surface absorption of the laser energy as the mechanism of laser assisted field evaporation for high band gap materials. The absorption region is shown to be located on the laser illumination side, close to the specimen apex. A simple model based on thermal diffusivity and spatial extent of the absorption region is derived and applied to the experimental results. The values of thermal diffusivity thus obtained are in good agreement with the published data. (C) 2011 American Institute of Physics. [doi:10.1063/1.3622647]

Exciton-coupled charge-transfer dynamics in a porphyrin J-aggregate/TiO 2 complex - Verma, Sandeep; Ghosh, Amrita; Das, Amitava; Ghosh, Hirendra Nath (Chemistry a European Journal, 2011)
Exciton-coupled charge-transfer (CT) dynamics in TiO2 nanoparticles (NP) sensitized with porphyrin J-aggregates has been studied by femtosecond time-resolved transient absorption spectroscopy. J-aggregates of 5,10,15-triphenyl-20-(3,4-dihydroxyphenyl) porphyrin (TPPcat) form CT complexes on TiO2 NP surfaces. Catechol-mediated strong CT coupling between J-aggregate and TiO2 NP facilitates interfacial exciton dissociation for electron injection into the conduction band of the TiO2 nanoparticle in pulse width limited time (<80 fs). Here, the electron-transfer (<80 fs) process dominates over the intrinsic exciton-relaxation process (J-aggregates: ca. 200 fs) on account of exciton-coupled CT interaction. The parent hole on J-aggregates is delocalized through J-aggregate excitonic coherence. As a result, holes immobilized on J-aggregates are spatially less accessible to electrons injected into TiO2, and thus the back electron transfer (BET) process is slower than that of the monomer/TiO2 system. The J-aggregate/porphyrin system shows exciton spectral and temporal properties for better charge separation in strongly coupled composite systems.

Experimental and computational approach of understanding the gas adsorption in amino functionalized interpenetrated metal organic frameworks (MOFs) - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Journal of Materials Chemistry, 2011)
Two isostructural, three dimensional, interpenetrated, amino (-NH2) functionalized Metal Organic Frameworks [Cd(ANIC)(2)] (Cd-ANIC-1) and [Co(ANIC)(2)] (Co-ANIC-1) with amine-lined pores have been reported. The framework adopts dia topology with interpenetration. Cd-ANIC-1 and Co-ANIC-1 show high CO2 (273 K) and H-2 (77 K) uptake due to the presence of free -NH2 groups and framework interpenetration. The effect of interpenetration and amino functionalization on gas uptake properties of MOFs has been analysed experimentally and computationally, in the isostructural MOFs Cd-ANIC-1 and Co-ANIC-1.

Exploration of L-proline-catalyzed -aminoxylation of aldehyde to (S)-guaifenesin-related drug molecules - Panchgalle, Sharad P.; Kunte, Sunita S.; Chavan, Subhash P.; Kalkote, Uttam R. (Synthetic Communications, 2011)
[image omitted] An efficient enantioselective synthesis of (S)-guaifenesin with 99% ee using L-proline-catalyzed -aminoxylation of aldehyde as key step is described and explored for asymmetric syntheses of (S)-moprolol and (R)-methocarbamol.
Keywords: -Aminoxylation; guaifenesin; methocarbamol; moprolol; Proline

Expression analysis of cinnamoyl-CoA reductase (CCR) gene in developing seedlings of Leucaena leucocephala: A pulp yielding tree species - Srivastava, Sameer; Gupta, Ranadheer K.; Arha, Manish; Vishwakarma, Rishi K.; Rawal, Shuban K.; Kishor, P. B. Kavi; Khan, Bashir Mohammad (Plant Physiology and Biochemistry, 2011)
Removal of lignin is a major hurdle for obtaining good quality pulp. Leucaena leucocephala (subabul) is extensively used in paper industry in India; therefore, as a first step to generate transgenic plants with low lignin content, cDNA and genomic clones of CCR gene were isolated and characterized. The cDNA encoding CCR (EC 1.2.1.44) was designated as LI-CCR; the sequence analysis revealed an Open Reading Frame (ORF) of 1005 bp. Phylogenetic analysis showed that LI-CCR sequence is highly homologous to CCRs from other dicot plants. The 2992 bp genomic clone of Leucaena CCR consists of 5 exons and 4 introns. The haploid genome of L leucocephala contains two copies as revealed by DNA blot hybridization. LI-CCR gene was over-expressed in Escherichia coli, which showed a molecular mass of approximately 38 kDa. Protein blot analysis revealed that LI-CCR protein is expressed at higher levels in root and in stem, but undetectable in leaf tissues. Expression of CCR gene in Leucaena increased up to 15 d in case of roots and stem as revealed by QRT-PcR studies in 0-15 d old seedlings. ELISA based studies of extractable CCR protein corroborated with QRT-PCR data. CCR protein was immuno-cytolocalized around xylem tissue. Lignin estimation and expression studies of 5,10 and 15 d old stem and root suggest that CCR expression correlates with quantity of lignin produced, which makes it a good target for antisense down regulation for producing designer species for paper industry. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Cinnamoyl-CoA reductase; Developing seedling; Leucaena leucocephala; Lignin biosynthesis

Ex-situ dispersion of core-shell nanoparticles of Cu-Pt on an in situ modified carbon surface and their enhanced electrocatalytic activities - Dhavale, Vishal M.; Unni, SreeKuttan M.; Kagalwala, Husain N.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2011)
Direct dispersion of core-shell nanoparticles on a carbon support (Cu@ Pt/C) has been achieved while retaining the essential core-shell features of the nanoparticles by adopting an in situ surface modification-cum-anchoring strategy.

Extending nhc-catalysis: reaction of aldehydes with unconventional reaction partners - Biju, Akkattu T.; Kuhl, Nadine; Glorius, Frank (Accounts of Chemical Research, 2011)
Transition metal catalysis is a powerful means of effecting organic reactions, but it has some inherent drawbacks, such as the cost of the catalyst and the toxicity of the metals. Organocatalysis represents an attractive alternative and, in some cases, offers transformations unparalleled in metal catalysis. Unique transformations are a particular hallmark of N-heterocyclic carbene (NHC) organocatalysis, a versatile method for which a number of modes of action are known. The NHC-catalyzed umpolung (that is, the inversion of polarity) of electrophilic aldehydes, through formation of the nucleophilic Breslow intermediate, is probably the most important mode of action. In this Account, we discuss the reaction of Breslow intermediates with unconventional reaction partners.

Extrudate swell of linear and branched polyethylenes: ALE simulations and comparison with experiments - Ganvir, Vivek; Gautham, Basavarsu P.; Pol, Harshawardhan; Bhamla, M. Saad; Sclesi, Lino; Thaokar, Rochish; Lele, Ashish K.; Mackley, Malcolm (Journal of Non-Newtonian Fluid Mechanics, 2011)
Extrudate swell is a common phenomenon observed in the polymer extrusion industry. Accurate prediction of the dimensions of an extrudate is important for appropriate design of dies for profile extrusion applications. Prediction of extrudate swell has been challenging due to (i) difficulties associated with accurate representation of the constitutive behavior of polymer melts, and (ii) difficulties associated with the simulation of free surfaces, which requires special techniques in the traditionally used Eulerian framework. In a previous work we had argued that an Arbitrary Lagrangian Eulerian (ALE) based finite element formulation may have advantages in simulating free surface deformations such as in extrudate swell. In the present work we reinforce this argument by comparing our ALE simulations with experimental data on the extrudate swell of commercial grades of linear polyethylene (LLDPE) and branched polyethylene (LOPE). Rheological behavior of the polymers was characterized in shear and uniaxial extensional deformations, and the data was modeled using either the Phan-Thien Tanner (PTT) model or the eXtended Pom-Pom (XPP) model. Additionally, flow birefringence and pressure drop measurements were done using a 10:1 contraction-expansion (CE) slit geometry in a MultiPass Rheometer. Simulated pressure drop and contours of the principal stress difference were compared with experimental data and were found to match well. This provided an independent test for the accuracy of the ALE code and the constitutive equations for simulating a processing-like flow. The polymers were extruded from long (L/D=30) and short (L/D=10) capillaries dies at 190 degrees C. ALE simulations were performed for the same extrusion conditions and the simulated extrudate swell showed good agreement with the experimental data. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: ALE-FEM; extrudate swell; Flow birefringence; MultiPass Rheometer; PSD; PTT; XPP

Eco-friendly, highly stable and efficient nanostructured p-type N-doped ZnO photocatalyst for environmentally benign solar hydrogen production - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Nikam, Latesh K.; Kale, Bharat B. (Green Chemistry, 2012)
We have investigated an economical green route for the synthesis of a p-type N-doped ZnO photocatalyst by a wet chemical method. Significantly, hazardous H2S waste was converted into eco-friendly hydrogen energy using the p-type N-doped ZnO photocatalyst under solar light, which has previously been unattempted. The as-synthesized p-type N-doped ZnO shows a hexagonal wurtzite structure. The optical study shows a drastic shift in the band gap of the doped ZnO in the visible region (3.19-2.3 eV). The doping of nitrogen into the ZnO lattice is conclusively proved from X-ray photoelectron spectroscopy analysis and Raman scattering. The morphological features of the N-doped ZnO are studied from FESEM, TEM and reveal particle sizes to be in the range of similar to 4-5 nm. The N-doped ZnO exhibits enhanced photocatalytic hydrogen generation (similar to 3957 mu mol h(-1)) by photodecomposition of hydrogen sulfide under visible light irradiation, which is much higher as compared to semiconductor metal oxides reported so far. It is noteworthy that a green catalyst is investigated to curtail H2S pollution along with production of hydrogen (green fuel) using solar light, i.e., a renewable energy source. The green process investigated will have the potential to synthesize other N-doped metal oxides.

Effect of addition of `carrier' DNA during transient protein expression in suspension CHO culture - Pradhan, Ketaki; Gadgil, Mugdha (Cytotechnology, 2012)
Transient protein expression using polyethyleneimine as a transfection agent is useful for the rapid production of small amounts of recombinant proteins. It is known that an increase in extracellular DNA concentration during transfection can lead to a nonlinear increase in intracellular DNA concentration. We present an approach that hypothesizes that this nonlinearity can be used to decrease the amount of plasmid required for productive transfections. Through addition of non coding `carrier' DNA to increase total DNA concentration during transfection, we report a statistically significant increase in protein (IgG) expression per unit plasmid used for transfection. This approach could be useful to increase protein yields for large scale transfections under conditions where plasmid availability is limited.
Keywords: Carrier DNA; Cell age; DNA: polyethyleneimine particle size; Medium equilibration with CO2; pH excursion; Salmon sperm DNA; Transient protein expression

Effect of alkali pretreatment on the structural properties and enzymatic hydrolysis of corn cob - Sahare, Padmavati; Singh, Rajkumar; Laxman, Ryali Seeta; Rao, Mala (Applied Biochemistry and Biotechnology, 2012)
An effective alkali pretreatment which affects the structural properties of cellulose (corn cob) has been studied. The pretreatment of corn cob was carried out with different combinations of alkali at varying temperatures. The most effective pretreatment of corn cob was achieved with 1 % alkali at 50 A degrees C in 4 h. The crystallinity index (CrI) and specific surface area (SSA) of untreated corn cob was 39 % and 0.52 m(2)/g wherein after alkali pretreatment CrI decreased to 15 % and SSA increased to 3.32 m(2)/g. The fungal organism was identified as Penicillium pinophilum on the basis of ITS sequence. At 5 % substrate concentration using a complete cellulase from Penicillium pinophilum the hydrolysis of untreated corn cob with 5, 10 and 20 FPU/g enzyme loadings were 11 %, 13 % and 16 %, whereas after alkali treatment the hydrolysis increased to 78 %, 90 % and 100 %, respectively. Further hydrolytic potential of commercial cellulases viz. Accellerase (TM) 1,000, Palkofeel-30 and Palkocel-40 were investigated under similar conditions.
Keywords: Corn cob; Crystallinity index; Enzymatic hydrolysis; Penicillium pinophilum; Specific surface area

Effect of digestive ripening agent on nanoparticle size in the digestive ripening process - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2012)
Digestive ripening is an efficient method that leads to monodispersed nanoparticles from polydispersed ones. A systematic investigation of digestive ripening with different agents viz. dodecanethiol and dodecylamine on different metallic systems is presented. It is shown that both the metallic system involved and the digestive ripening agent have influences on the final size distribution. Further, it is demonstrated that the interaction strength between the different metals and the digestive ripening agents based on Hard Soft Acid Base principles could be invoked to explain the variation in nanoparticle size. (C) 2012 Elsevier B.V. All rights reserved.

Effect of particle size on selective hydrogenation of cinnamaldehyde by Pt encapsulated in mesoporous silica - Prashar, Atul K.; Mayadevi, S.; Devi, R. Nandini (Catalysis Communications, 2012)
Pt nanoparticles of various sizes, viz. 8. 4.9, 3.6 and 1.8 nm were encapsulated in 2D hexagonal mesoporous silica by in-situ synthesis as well as post synthetic modifications so that the final catalyst composition was <= 1 wt.% Pt/SiO2. A kinetic analysis of the effect of particle size on selective hydrogenation of cinnamaldehyde was carried out on these catalysts. It was found that the materials, even at such low loading of Pt, were very active for the hydrogenation and selective for the desired product, cinnamyl alcohol. Among the different particle sizes, selectivity was found to be the highest on 8 nm particles. Kinetic analysis shows that the reaction follows a consecutive reaction pathway. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: alpha; beta-Unsaturated aldehydes; Cinnamaldehyde hydrogenation; Kinetic analysis; Mesoporous silica; Pt nanoparticles; Selective hydrogenation

Effect of preparation parameters of Cu catalysts on their physico-chemical properties and activities for glycerol hydrogenolysis - Mane, R. B.; Kondawar, S. E.; Niphadkar, P. S.; Joshi, P. N.; Patil, K. R.; Rode, C. V. (Catalysis Today, 2012)
Cu based catalysts were prepared by co-precipitation, alkali fusion followed by precipitation and direct solid state fusion methods. The changes in the phase formation, morphology, crystallite size, extent of aggregation, strength and nature of acid sites were observed due to variations in precipitating agents and also their order of addition. The catalyst prepared by co-precipitation using Na2CO3 showed the predominant presence of metallic Cu phase with a crystallite size of 5 nm, well segregated spherical morphology and highest acidity in the activated sample. These intrinsic properties contributed to achieve the highest glycerol conversion of 62% and 1,2-PDO selectivity of 88% in glycerol hydrogenolysis. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Co-precipitation; Cu catalysts; Glycerol hydrogenolysis; Physico-chemical properties; Solid state fusion

Effect of the A30P mutation on the structural dynamics of micelle-bound alpha synuclein released in water: a molecular dynamics study - Chatterjee, Prathit; Sengupta, Neelanjana (European Biophysics Journal With Biophysics Letters, 2012)
Atomistic molecular dynamics simulation has been used to probe the effect of the A30P mutation on the structural dynamics of micelle-bound, helical alpha Synuclein when released in an aqueous environment. On the timescales simulated, the effect of the mutation on the secondary structure is restricted to local changes close to the mutation site in the N-terminal helical domain. The changes are transient, and all residues except Lys23 recover their initial structure. The local behavior due to the mutation gives rise to a global difference in the A30P mutant in the form of a permanent kink in the N-terminal helical domain.
Keywords: A30P mutation; Alpha synuclein; Kink formation; molecular dynamics simulation; Structural persistence

Effect of the surface roughness of conducting polypyrrole thin-film electrodes on the electrocatalytic reduction of nitrobenzene - Adhikari, Arindam; Radhakrishnan, S.; Vijayan, M. (Journal of Applied Polymer Science, 2012)
Conducting polypyrrole (PPy) thin-film electrodes were prepared by the electropolymerization of pyrrole on gold-coated glass plates. Films of various roughnesses were obtained by the variation of the scan rates during electropolymerization. These thin films were modified by doping with 6mM of the dopant NiCl2. The surface morphology of the films was studied by scanning electron microscopy and atomic force microscopy (AFM), which suggested films prepared with a high scan rate were rougher in nature than the films produced with a low scan rate. The electrocatalytic reduction of nitrobenzene was carried out with these electrodes with the cyclic voltammetry technique in acetonitrile containing 0.1M HClO4 as a supporting electrolyte. The various results obtained show that the conducting PPy thin-film electrodes were catalytically active toward the electroreduction process. The modified PPy film electrodes doped with NiCl2 were more active toward nitrobenzene electroreduction than the PPy film alone. The results indicate that the roughness of the films played a very important role in determining their catalytic activity. The PPy films that were more rough in nature were catalytically more active than the smooth films; this may have been due to the availability of more reactive sites in the case of rough films. The apparent diffusion coefficients of the PPy film electrodes were also calculated. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: atomic force microscopy (AFM); conducting polymers; Diffusion; surface modification; Thin films

Effects of arsenite stress on growth and proteome of Klebsiella pneumoniae - Daware, Vandana; Kesavan, Suresh K.; Patil, Rajendra; Natu, Arvind; Kumar, Ameeta; Kulkarni, Mahesh J.; Gade, Wasudeo N. (Journal of Biotechnology, 2012)
In the present study an arsenite, As(III), tolerating bacterium, MR4, was isolated from Mulla River Pune, India, capable of reducing arsenate to arsenite and identified as Klebsiella pneumoniae (HQ857583). Comparative proteomic analysis using two-dimensional gel electrophoresis (2-DGE) and matrix assisted laser desorption ionization-time of flight-time of flight (MALDI-TOF/ TOF) was used to monitor the proteins undergoing changes in expression levels under 2.5 mM As(III) stress. The 2-DGE proteome map has shown that 60 proteins were differentially expressed under As(III) stress, of which 39 proteins were successfully identified with a MASCOT score greater than 70 (p < 0.05). Among the identified proteins, membrane transport/ binding proteins, porins, and amino acid metabolism enzymes were down-regulated while stress responsive proteins and antioxidant enzymes were up-regulated. Proteins involved in carbohydrate metabolism, particularly those in pentose phosphate pathway were also up-regulated while those involved in pyruvate metabolism were down-regulated. However, proteins involved in glycolysis and tricarboxylic acid cycle showed a mixed regulation response. These findings provide new insights into the probable mechanisms by which K. pneumoniae (HQ857583) could be adapting to As(III) stress. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: (2-DGE); Arsenite stress; Klebsiella pneumoniae; MALDI-TOF-TOF; Two dimensional gel electrophoresis

Effects of grain morphology, microstructure and dispersed metal cocatalyst on the photoreduction of water over impurity-doped LaInO3 - Dhanasekaran, P.; Gupta, N. M. (Materials Research Bulletin, 2012)
The single phase lanthanum indates doped with Ga (for La) and N (for O), i.e. La1-xGaxInO3 (0 <= x <= 0.2) and LaInO1-yNy (y similar to 0.6), exhibit significant activity for photoreduction of water; the yield of H-2 produced depending on dopant, excitation source, and addition of a sacrificial reagent. The two-step H-2 evolution observed for this reaction corresponds with the two distinct absorbance regimes displayed by these materials, one in UV-region due to bandgap excitation and the other in visible region arising from the transitions involving sub-bandgap donor or acceptor energy states. The photocatalytic activity of these d(10) metal oxides increases on coating with a metal/metal oxide co-catalyst, gold exhibiting superior activity to Pt and NiO, irrespective of excitation source and sample composition. The preparation-controlled particle morphology, doping-induced lattice imperfections, and metal/semiconductor hetero-junctions are envisaged to play a key role in the absorption characteristics and photocatalytic water reduction activity of metal/LaInO3 nanocomposites. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Chemical synthesis; Electron microscopy; Interfaces; Semiconductors

Efficient diels-alder reaction of 1,2-benzoquinones with arynes and its utility in one-pot reactions - Kaicharla, Trinadh; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
A new protocol for the efficient Diels–Alder reaction of 1,2-benzoquinones with arynes is reported. The aryne generated by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes a facile Diels–Alder reaction with 1,2-benzoquinones, affording the dioxobenzobicyclooctadienes in moderate to excellent yields. In addition, this methodology has been applied to the one-pot synthesis of benzoquinoxalinobarrelene and naphthalene derivatives.

Efficient hydrogenation of biomass derived cyclic di-esters to 1,2-diols - Balaraman, Ekambaram; Fogler, Eran; Milstein, David (Chemical Communications, 2012)
The unprecedented homogeneous hydrogenation of cyclic di-esters, in particular biomass-derived glycolide and lactide, to the corresponding 1,2-diols is catalyzed by Ru(II) PNN (1) and Ru(II) CNN (2) pincer complexes under mild hydrogen pressure and (in the case of 1) neutral conditions. No racemization was observed when a chiral di-ester was used.

Efficient lipase purification using reverse micellar extraction - Gaikaiwari, Raghavendra P.; Wagh, Shilpa A.; Kulkarni, Bhaskar D. (Bioresource Technology, 2012)
Reverse micellar extraction (RME) of enzyme provides an attractive option for conventional method with the potential to achieve purification and concentration in a single step with high yield. This study presents a methodology for optimization of RME with Pseudomonas lipase as model system. Fold-purification, percent recovery and extraction time were the objective functions while the type and concentration of surfactant, contact time, pH, ionic strength, and the ratio of organic to aqueous phase were the decision variables. Under optimized conditions, the AOT (Aerosol OT (bis 2-ethylhexyl) sodium sulfosuccinate)-isooctane system gave a 15-fold purification, 80% recovery and 2.5-fold concentration of the Pseudomonas lipase with process time of 45 min. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: (Hexadicetyltrimethylammoniumbromide); AOT; CTAB; Lipase; RME

Efficient oxygen reduction electrocatalyst from graphene by simultaneously generating pores and nitrogen doped active sites - Palaniselvam, Thangavelu; Aiyappa, Harshitha Barike; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
A simple way to simultaneously create pores and nitrogen doped active sites on graphene for the electrochemical oxygen reduction reaction (ORR) is developed. The key aspect of the process is the in-situ generation of Fe2O3 nanoparticles and their concomitant dispersion on graphene by pyrolyzing graphene oxide (GO) with the iron phenanthroline complex. Thus the deposited Fe2O3 nanoparticles act as the seeds for pore generation by etching the carbon layer along the graphene-Fe2O3 interface. Detection of the presence of Fe3C along with Fe2O3 confirms carbon spill-over from graphene as a plausible step involved in the pore engraving process. Since the process offers a good control on the size and dispersion of the Fe2O3 nanoparticles, the pore size and distribution also could be managed very effectively in this process. As the phenanthroline complex decomposes and gives Fe2O3 nanoparticles and subsequently the pores on graphene, the unsaturated carbons along the pore openings simultaneously capture nitrogen of the phenanthroline complex and provide very efficient active sites for ORR under alkaline conditions. The degree of nitrogen doping and hence the ORR activity could be further improved by subjecting the porous material for a second round of nitrogen doping using iron-free phenanthroline. This porous graphene enriched with the N-doped active sites effectively reduces oxygen molecule through a 3e(-) pathway, suggesting a preferential shift towards the more favourable 4e(-) route compared to the 2e(-) reaction as reported for many N-doped carbon nano-morphologies. The 90 mV onset potential difference for oxygen reduction as compared to the state-of-the art 20 wt% Pt/C catalyst is significantly low compared to the overpotentials in the range of 120-200 mV reported in the literature for few N-doped graphenes.

Efficient, rapid synthesis of bis(indolyl)methane using ethyl ammonium nitrate as an ionic liquid - Mulla, Shafeek Abdul Rashid; Sudalai, A.; Pathan, Mohsinkhan Y.; Siddique, Shafi A.; Inamdar, Suleman M.; Chavan, Santosh S.; Reddy, R. Santosh (RSC Advances, 2012)
A simple and rapid protocol has been developed for an efficient synthesis of bis( indolyl)methane in excellent yields using ethyl ammonium nitrate (EAN) as reusable ionic liquid at room temperature. The protocol involves an electrophilic substitution reaction of indoles with several aldehydes.

Efficient synthesis of a hydroxyethylamine (HEA) isostere and its alpha-aminophosphonate and phosphoramidate derivatives as potential anti-HIV agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Pannecouque, Christophe; De Clercq, Eric (Chemmedchem, 2012)
HIV protease is a promising drug target for AIDS therapy, and several potent HIV-1 protease inhibitors have been reported to date. Although existing inhibitors exhibit high selectivity, they have also been associated with severe side effects and the possible emergence of therapeutic resistance. As HIV protease cleaves the peptide bond via a tetrahedral intermediate, various transition-state models such as hydroxyethylamine (HEA) have been designed. We therefore pursued an efficient synthesis of an HEA isostere; this was performed with a novel one-pot reductiontransiminationreduction reaction sequence as a key step. a-Aminophosphonate and phosphoramidate derivatives of the HEA isostere were designed and synthesized, and all of the synthesized derivatives were assayed for their anti-HIV activities against wild-type and mutant HIV strains. Phosphoramidate derivative 15?a was found to be the most active of all synthesized compounds against the IIIB and RES056 strains. As phosphonates are known to exhibit physiological stability, good cell permeability, and other promising pharmacokinetic characteristics, our newly synthesized compounds have the potential as alternatives to existing therapeutics and diagnostics.
Keywords: a-aminophosphonates; antiviral agents; hydroxyethylamine isosteres; phosphoramidates; synthesis

Efficient synthesis of gamma-keto sulfones by NHC-catalyzed intermolecular stetter reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
The N-heterocyclic carbene-catalyzed intermolecular Stetter reaction of aldehydes with α,β-unsaturated sulfones allows the atom-economic and selective formation of γ-keto sulfones in good yields. Key to the success of this unique transition-metal-free carbon–carbon bond-forming reaction is the right choice of the NHC precursor and base. The reaction tolerates a broad range of different aldehydes.

Efficient total synthesis of calothrixin B - Bhosale, Shrikar M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2012)
An efficient synthesis of calothrixin B (2) is demonstrated starting from 9H-carbazol-4-ol, having two one-pot reaction sequences as key steps. As a novel observation, DMF-methanol was shown to be a hydride donor for reduction of aldehyde to alcohol. Unexpectedly, nucleophilic substitution of benzyloxy by methoxy group was observed. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Calothrixin B; CAN; DMF-methanol; Hydride donor

Elaboration of the ether cleaving ability and selectivity of the classical pearlman's catalyst [Pd(OH)(2)/C]: concise synthesis of a precursor for a myo-inositol pyrophosphate - Mart, Alson; Shashidhar, Mysore S. (Tetrahedron, 2012)
The cleavage of propargyl, allyl, benzyl, and PMB ethers by Pd(OH)(2)/C can be tuned in that order, by varying the reaction conditions. Other moieties such as C-C double bonds, esters, trityl ether, p-bromo and p-nitrobenzyl ethers are stable to these reaction conditions. Cleavage of allyl ethers can be made catalytic by using 1:1 mixture of Pd(OH)(2)/C and Pd/C. The synthetic potential of the selective ether cleaving ability of Pd(OH)(2)/C, essentially under neutral conditions, has been demonstrated by an efficient synthesis of a precursor for the preparation of an inositol pyrophosphate derivative. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Ether cleavage; Inositol; Palladium; Protecting group

Electrochemical preparation of luminescent graphene quantum dots from multiwalled carbon nanotubes - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemistry-A European Journal, 2012)
Green luminescent, graphene quantum dots (GQDs) with a uniform size of 3, 5, and 8.2(+/- 0.3) nm in diameter were prepared electrochemically from MWCNTs in propylene carbonate by using LiClO4 at 90?degrees C, whereas similar particles of 23(+/- 2) nm were obtained at 30?degrees C under identical conditions. Both these sets of GQDs displayed a remarkable quantum efficiency of 6.3 and 5.1?%, respectively. This method offers a novel strategy to synthesise size-tunable GQDs as evidenced by multiple characterisation techniques like transmission and scanning electron microscopy, atomic force microscopy, Raman spectroscopy and X-ray diffraction (XRD). Photoluminescence of these GQDs can be tailored by size variation through a systematic change in key process parameters, like diameter of carbon nanotube, electric field, concentration of supporting electrolyte and temperature. GQDs are promising candidates for a variety of applications, such as biomarkers, nanoelectronic devices and chemosensors due to their unique features, like high photostability, biocompatibility, nontoxicity and tunable solubility in water.
Keywords: electrochemical synthesis; graphene; Nanostructures; photoluminescence; quantum dots

Electrospinning of PHBV/ZnO membranes: structure and properties - Naphade, Rounak; Jog, Jyoti Prakash (Fibers and Polymers, 2012)
Polyhydroxy butyrate-co-valerate (PHBV) - Zinc oxide (ZnO) nano composite fibers were prepared using electrospinning. The structural and optical properties were studied using Fourier transform infrared spectroscopy (FT-ER), X-ray diffraction (XRD) and photoluminescence study (PL). The morphology observed with scanning electron microscope (SEM) revealed no significant changes in the nano composite fibers as compared to bare polymer. The low concentration of ZnO nanoparticles resulted in an increase in overall crystallinity of the polymer matrix which was confirmed from FT-IR and XRD results. The photoluminescence (PL) study indicated the quenching of visible emission in the composite fibers. The ratio of UV to visible emission (I-uv/I-vis) intensity was found to be 12.8 times enhanced in the composite fibers compared to bare ZnO nanoparticles. The nanofibrous mats are self supported and hence offer potential applications in optoelectronic devices and the biomedical imaging.
Keywords: Biomarkers; Biopolymers; electrospinning; ZnO nanoparticles

Electrostatic grafting of a triphenylphosphine sulfonate on SBA-15: application in palladium catalyzed hydrogenation - Wang, Lei; Dehe, Daniel; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Zhou, Zhou; Hartmann, Martin; Taylor, Robin N. Klupp; Singh, Anand Pal; Jia, Mingjun; Thiel, Werner R. (Catalysis Science & Technology, 2012)
A novel strategy for the immobilization of a sulfonate functionalized triphenylphosphine ligand by ion-ion interactions on an imidazolium modified SBA-15 is presented. A support containing electrostatically grafted triphenylphosphine as the ligand was reacted with PdCl2( CNPh)(2) and the resulting hybrid material catalyzed olefin hydrogenation under mild conditions. The catalyst exhibits excellent activity, selectivity and stability and it can be reused for at least ten times without any loss of activity. An analogous but covalently grafted palladium system does not show any hydrogenation activity under the same conditions. TEM images of the used catalyst clearly prove the absence of palladium nanoparticles. Additionally, XPS investigations prove that palladium( 0) is formed and the phosphine is oxidized. By AAS no palladium contamination down to 0.5 X 10(-4) mmol could be detected in the products and further leaching tests verified the reaction to be truly heterogeneous. This concept of non-covalent immobilization guarantees a tight bonding of the catalytically active species to the surface in combination with a high mobility, which should be favorable for other catalyses, too.

Enantio- and diastereocontrolled conversion of chiral epoxides to trans-cyclopropane carboxylates: application to the synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II - Kumar, Pradeep; Dubey, Abhishek; Harbindu, Anand (Organic & Biomolecular Chemistry, 2012)
An efficient high yielding improved method for the enantio- and diastereoselective cyclopropanation of chiral epoxides using triethylphosphonoacetate and base (Wadsworth-Emmons cyclopropanation) is reported. The utility of this protocol is illustrated by concise and practical synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II, a cyclopropane containing natural products.

Enantioselective synthesis of HIV protease inhibitor amprenavir via Co-catalyzed HKR of 2-(1-azido-2-phenylethyl)oxirane - Gadakh, Sunita K.; Reddy, R. Santhosh; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A short and efficient enantioselective synthesis of the HIV protease inhibitor amprenavir 1 (99% ee) as well as a formal synthesis of saquinavir 3 have been achieved in high enantiomeric purity starting from commercially available materials. Our strategy mainly comprises a Co-catalyzed two-stereocentred hydrolytic kinetic resolution (HKR) of racemic 2-(1-azido-2-phenylethyl)oxirane as the chirality inducing step. Also presented is a concise synthesis of (S)-3-hydroxytetrahydrofuran 4, the key structural feature, in high enantiomeric purity (98% ee). (c) 2012 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of the essential oil and pheromonal component ar-himachalene by a chiral pool and chirality induction approach - Chavan, Subhash P.; Khatod, Harshali S. (Tetrahedron-Asymmetry, 2012)
The enantioselective synthesis of both isomers of ar-himachalene has been achieved starting from enantiomerically pure citronellal and p-methyl alpha-methyl styrene as an application of a chiral pool and chirality induction approach, respectively. The key reactions involved in the synthesis include the Sharpless asymmetric dihydroxylation for the induction of chirality at benzylic carbon bearing the methyl group and the use of a hypervalent iodine reagent or trimethylsilyldiazomethane (TMSCHN2) for the six to seven membered ring expansion. (C) 2012 Elsevier Ltd. All rights reserved.

Encapsulation of enzyme in large mesoporous material with small mesoporous windows - Malvi, Bharmana; Sen Gupta, Sayam (Chemical Communications, 2012)
Trypsin has been encapsulated in the mesopores of a hierarchical mesoporous silica material synthesized via Cu(I) catalyzed azide-alkyne click reaction between azide functionalized large spherical SBA-15 particles and alkyne functionalized mesoporous silica nanoparticles (MSNs). Encapsulated trypsin functions as an efficient biocatalyst and can be recycled several times.

Engineered glucose to generate a spectroscopic probe for studying carbohydrate biology - Tripathi, Ashish; Singh, Vibha; Aishwarya, K. G.; Aradhyam, Gopala Krishna; Hotha, Srinivas (Advances in Experimental Medicine and Biology, 2012)

Enhanced magnetic parameters in the morphotropic phase boundary region of nanocrystalline multiferroic Bi1-xLaxFeO3 - Thakuria, P.; Joy, Pattayil Alias (Solid State Communications, 2012)
Antiferromagnetic multiferroic BiFeO3 shows ferromagnetic characteristics by simultaneous substitution of Bi by La and decrease in the particle size to nanometer dimensions. Large changes in saturation and remnant magnetization, magnetic susceptibility at low and high fields, along with some anomalous changes in the magnetic transition temperature are observed in nanocrystalline Bi1-xLaxFeO3 system for 0.1 <= x <= 0.2. This compositional region corresponds to the morphotropic phase boundary (MPB) region separating the rhombohedral and orthorhombic phases, and the effect is similar to that observed in many ferroelectric systems. The present observation of enhanced ferromagnetic parameters in the MPB region of the nanocrystalline multiferroic La substituted BiFeO3 system, combined with the known ferroelectric characteristics, is suitable for future device applications. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Bismuth ferrite; magnetic properties; Multiferroics; Nanocrystalline materials

Enhanced permeation, leaf retention, and plant protease inhibitor activity with bicontinuous microemulsions - Tamhane, Vaijayanti A.; Dhaware, Deepika G.; Khandelwal, Neha; Giri, Ashok P.; Panchagnula, Venkateswarlu (Journal of Colloid and Interface Science, 2012)
Bicontinuous microemulsions (BCMEs) have excellent solubulizing properties along with low interfacial tension and aqueous content that can be controlled. In this work, water soluble plant protease inhibitor (PI), well characterized for its activity against insect pests, was incorporated into a BCME system and explored for permeation on hydrophobic leaf surfaces and protease inhibition activity. The bicontinuous nature of the microemulsion containing water:2-propanol:1-butanol (55:35:10 w/w) was characterized using conductivity and self-diffusion coefficient measurements. The PI was soluble in the water-rich bicontinuous domains, stable in the microemulsions, and protease inhibition activity was retained for a prolonged duration. The microemulsions ensured greater wettability and a wider spread of the PI on hydrophobic leaf surfaces as revealed by contact angle measurements. Significantly, trypsin inhibition activity assays of the PI recovered from the leaves after delivery from the microemulsion indicated a significant increase in the PI retention on the leaf. This BCME enabled greater leaf permeation and retention of the PI can be attributed to a temporary disruption of the waxy leaf surface followed by self-repair without causing any long term damage to the plant. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Bicontinuous microemulsion; Biopesticide; Microemulsion pesticide; protease inhibitor; Protein encapsulation; Protein permeation

Enhanced photocatalytic activity of multi-doped TiO2 for the degradation of methyl orange - Charanpahari, A.; Umare, S. S.; Gokhale, S. P.; Sudarsan, V.; Sreedhar, B.; Sasikala, R. (Applied Catalysis A-General, 2012)
We report the synergistic effect of dopants like Gd, N and Sin enhancing the photocatalytic activity of TiO2. Nanosized TiO2 doped at both cationic and anionic sites by Gd, N and S exhibited increased photocatalytic activity compared to TiO2 doped with either Gd or N and S. All the doped TiO2 existed as anatase phase and no separate phase due to Gd2O3 was seen up to a Gd concentration of 2%. The particle size as seen from the transmission electron micrograph was similar to 25 nm. The optical absorption property of TiO2 was improved by doping and redshift of the absorption edge is seen for all doped samples compared to pristine TiO2. The red shift of the absorption edge was the highest for the multiple ion-doped sample. Presence of bonded N and S in TiO2 was detected by X-ray photoelectron spectroscopy. Fluorescence lifetime studies indicated an enhanced lifetime for the charge carriers in the doped system compared to pristine TiO2. Photocatalytic activity study showed that the multi-doped sample has the highest activity for the degradation of methyl orange compared to Gd-TiO2, NS-TiO2 and pristine TiO2. The enhanced photocatalytic activity of the multi-doped TiO2 is attributed to factors such as improved optical absorption property and improved lifetime of the charge carriers. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Fluorescence lifetime; Gd N S doped TiO2; Methyl orange; Photocatalyst; Photodegradation

Enhanced piezoresponse of electrospun PVDF mats with a touch of nickel chloride hexahydrate salt - Dhakras, Dipti; Borkar, Vivek; Ogale, Satishchandra; Jog, Jyoti Prakash (Nanoscale, 2012)
PVDF nanofibers are prepared using electrospinning. The effect of addition of a hydrated salt, nickel chloride hexahydrate (NiCl2 center dot 6H(2)O), on the phase formation is examined. Addition of the hydrated salt (NC) is found to enhance the polar beta phase by about 30%. The peak to peak piezo-voltage generated for PVDF NC is almost 0.762 V, a factor of 3 higher than that for PVDF. The fiber mats exhibit a significantly enhanced dynamic strain sensor response. The voltage generated per unit micro-strain developed during the free vibration test for PVDF was 0.119 mV whereas it was 0.548 mV for PVDF NC, exhibiting a non-linearly enhanced performance vis a vis the increase in the beta phase component.

Enhanced tolerance of transgenic grapevines expressing chitinase and beta-1,3-glucanase genes to downy mildew - Nookaraju, Akula; Agrawal, Dinesh C. (Plant Cell Tissue and Organ Culture, 2012)
An Agrobacterium-mediated transformation protocol for grapevine cv. Crimson Seedless using sonication and anti-necrotic agents has been optimized, and transgenic lines carrying wheat chitinase and beta-1,3-glucanase genes have exhibited enhanced tolerance to downy mildew incited by Plasmopara viticola. cDNA clones encoding chitinase and beta-1,3-glucanase have been isolated from a cDNA library, constructed from scab-infected Sumai-3 wheat, and introduced into a plant cloning vector to generate the plasmids pCAMBAR.chi.11 and pCAMBAR.638. Embryogenic cultures, established from in vitro-derived leaves, of Crimson Seedless were used as explants for Agrobacterium tumefaciens-mediated transformation studies. Sonication of somatic embryos in a bacterial suspension of A. tumefaciens and incorporation of anti-necrotic agents in the co-cultivation medium significantly enhanced transformation efficiency. Transformation efficiency of embryos with either chitinase or beta-1,3-glucanase gene was highest when embryos were suspended in a bacterial cell suspension at 0.5 OD600 and sonicated for 2 or 3 s at 60 kHz. Transformation efficiency with chitinase was highest on incorporation of 2 or 3 mg l(-1) phenylalanine, 1 or 2 mg l(-1) silver nitrate or 400 mg l(-1) l-cysteine in co-cultivation medium while incorporation of 20 mg l(-1) sodium thiosulphate produced highest transformation efficiency with beta-1,3-glucanase. Confirmed transgenic grapevine lines harboring anti-fungal genes exhibited higher levels of chitinase and beta-1,3-glucanase transcripts as well as enzymatic activities. Moreover, transgenic lines showed enhanced tolerance to P. viticola infection following detached leaf assays.
Keywords: Agrobacterium tumefaciens; Anti-oxidants; Downy mildew tolerance; Grapevine; Sonication

Enhancement in the magnetostriction of sintered cobalt ferrite by making self-composites from nanocrystalline and bulk powders - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (ACS Applied Materials & Interfaces, 2012)
Sintered polycrystalline cobalt ferrite is a potential magnetostrictive smart material for applications as sensors and actuators. A novel concept of enhancing the magnetostrictive strain of sintered cobalt ferrite by making self-composites from nanosized and bulk powders with different particle sizes of the same material as components is reported. The self-composites give higher magnetostriction coefficient and strain derivative when compared to the sintered products obtained from the individual powders. The individual components give a maximum magnetostriction up to similar to 310 ppm, whereas up to similar to 370 ppm is obtained for a two-component system consisting of powders of two different sizes. On the other hand, a three-component self-composite made from starting powders of 3 nm, 40 nm and >1 mu m give very high magnetostriction of similar to 400 ppm at 800 kA/m, suitable for making devices.
Keywords: Cobalt ferrite; Magnetostriction; Nanocrystalline; self-composite; Sintering

Enhancing the hydrogen storage capacity of Pd-functionalized multi-walled carbon nanotubes - Singh, Priyanka; Kulkarni, Mukta V.; Gokhale, Suresh P.; Chikkali, Samir H.; Kulkarni, Chandrashekhar V. (Applied Surface Science, 2012)
We demonstrate that the hydrogen storage capacity of multi-walled carbon nanotubes can be enhanced by polyvinylpyrrolidone functionalization. The polyvinylpyrrolidone acts as a stabilizing agent for Pd-nanoparticles, reduces their size and facilitates their uniform and enhanced loading onto multi-walled carbon nanotubes. According to sorption studies, the polyvinylpyrrolidone capping and consequent nanostructural modification enables 2.3 times more hydrogen adsorption than mere Pd-functionalization of multi-walled carbon nanotubes. Corresponding morphological changes before and after polyvinylpyrrolidone capping, characterized using Raman Spectroscopy, X-ray diffraction, TEM and thermal analysis techniques, are also presented. The results contribute towards increasing the efficiency of hydrogen based sustainable energy sources. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Hydrogen based energy sources; Hydrogen storage capacity; Multiwalled carbon nanotubes; Pd functionalization; PVP capping

Environmental pollution reduction in cement industry for cocombustion of waste tyre and coal as a fuel - Patil, R. K.; Garnaik, Baijayantimala; Khond, M. P.; Nawale, L. G. (International Journal of Modern Engineering Research, 2012)
In recent years, there are several problems encountered in waste management system particularly waste tyre as well as coals. The energy generation on incineration provides large amount of polycyclic aromatic hydrocarbon (PAH) emissions which is the cause of major environmental threat. Therefore, the combustion of coal and tyre were carried out in cement industry in order to generate heat energy at 1300oC and the only remaining residue (steel powder) to enhance the strength of the cement. At the outset, the particle size of coal and tyre was cut into 63-75 and 180-212 µm respectively. Combustion experiments were conducted using Nelson reactor under controlled conditions in presence of air and also in presence of nitrogen gas (INOX) atmosphere. The temperature range was varied from 300-13000C and several fuel mass loading in the furnace, expressed in terms of bulk equivalence ratios in the range of 0.7-2.4. At fixed bulk equivalence ratios, as the furnace gas (Air) temperature increased the polycyclic aromatic hydrocarbon yields from both fuels decreased drastically, while the CO2 yields increased. At the highest temperature around 13000C, the effluent of combustion of both (coal and tyre) fuels was practically devoid of polycyclic aromatic hydrocarbon (PAH) (at a detection limit of 0.3 µg of a PAH component/g of fuel burnt). In order to understand the rate of thermal effect and morphology of co combustion material (coal and tyre), the preliminary results are very essential to explore. Therefore, the thermo gravimetric analysis (TGA) and environmental scanning electron microscopy (ESEM) were carried out and results of coal and tyre mixture at various temperature conditions will be highlighted.

Environmentally benign synthesis of beta-hydroxy sulfides using cyclic carbonates catalyzed by large-pore zeolites - Upare, Pravin P.; Kinage, Anil K.; Shingote, Savita K.; Gupte, Sunil P. (Green Chemistry Letters and Reviews, 2012)
An efficient one-pot synthesis of beta-hydroxy sulfides from thiophenol and cyclic carbonates catalyzed by large-pore zeolites has been reported. Reaction of thiophenol with ethylene carbonate in the presence of the Na-X zeolite catalyst gave the highest yield of 2-(phenylthio)ethanol (100%), while reaction with propylene carbonate a highest yield of regioselective product 1-(phenylthio)propan-2-ol was obtained (97%). Enantiomerically pure 1,2-propylene carbonate gave highly regioselective and stereospecific phenylthiopropanol, demonstrating that original chirality of propylene carbonate is retained. A plausible mechanism has been proposed for zeolite-catalyzed transformation involving a chemoselective nucleophilic attack of thiophenoloxide ion onto the less-substituted carbon of cyclic carbonate. The Na-X zeolite catalyst is recyclable and provides advantages of green chemistry approach to the synthesis of beta-hydroxy sulfides without the use of any solvent.
Keywords: beta-hydroxy sulfide; ethylene carbonate; propylene carbonate; thiophenol; zeolite

Enzyme immobilization on epoxy supports in reverse micellar media: prevention of enzyme denaturation - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Yalangi; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Journal of Molecular Catalysis B-Enzymatic, 2012)
Immobilization of enzymes such as alpha-chymotrypsin (EC 3.4.21.1), yeast alcohol dehydrogenase (YADH) from Saccharomyces cerevisiae (EC 1.1.1.1) and glucose dehydrogenase (GDH) from Gluconobacter cerinus (EC 1.1.1.119) has been carried out. Copolymers of allyl glycidyl ether (AGE) crosslinked with 25% ethylene glycol dimethacrylate (EGDM) (25 mg, dry wt) were contacted with the enzymes solubilized in reverse micellar media (0.5-5 mg/mL)(overall) of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) salt in isooctane, and cetyl trimethylammonium bromide (CTAB) in chloroform-isooctane (50:50, v/v). Although the enzymes are readily denatured (>90%) after adsorption on the copolymer in aqueous buffers, no such adsorption-induced denaturation takes place in reverse micelles. alpha-Chymotrypsin is remarkably stable in AOT reverse micelles when 0.025 M citrate buffer of pH 9.0 containing 2 mM CaCl2 is used in the water pools instead of Tris-HCl buffer of pH 8.5. It was possible to achieve enzyme concentration of 5 mg/mL in 0.3 M AOT at molar ratio of water to surfactant, (W-0), 30 and to obtain alpha-chymotrypsin loading of 20 mg/g of copolymer. The recovered enzyme solution can be reused with a fresh batch of polymer after supplementing the depleted solution. The immobilized enzyme exhibits excellent stability in aqueous buffers at room temperature and can be recycled several times. YADH is stable in both AOT and CTAB reverse micelles while GDH is stable only in CTAB reverse micelles containing 0.05 M Tris-HCI buffer of pH 8.5. Interestingly, the combination of YADH (2.5 mg/g) and GDH (0.5 mg/g) co-immobilized on the copolymer using CTAB-chloroform-isooctane system can be used for regeneration and recycle of NADPH at least 50 times as exemplified by complete reduction of a prochiral ketoester, ethyl 4-phenyl-2,4-dioxobutyrate (10 mM) to ethyl (R)-2-hydroxy-4-phenylbutyrate (HPB ester) using NADPH (0.2 mM). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: allyl glycidyl ether; alpha-Chymotrypsin; ethylene glycol dimethacrylate; Glucose dehydrogenase; Reverse micelles; Yeast alcohol dehydrogenase

Epitaxial magnetic oxide nanocrystals via phase decomposition of bismuth perovskite precursors - Bogle, Kashinath A.; Cheung, Jeffrey; Chen, Yong-Lun; Liao, Sheng-Chieh; Lai, Chih-Hung; Chu, Ying-Hao; Gregg, John M.; Ogale, Satishchandra B.; Valanoor, Nagarajan (Advanced Functional Materials, 2012)
The phase instability of bismuth perovskite (BiMO3), where M is a ferromagnetic cation, is exploited to create self-assembled magnetic oxide nanocrystal arrays on oxide supports. Conditions during pulsed laser deposition are tuned so as to induce complete breakdown of the perovskite precursor into bismuth oxide (Bi2O3) and metal oxide (M-Ox) pockets. Subsequent cooling in vacuum volatizes the Bi2O3 leaving behind an array of monodisperse nanocrystals. In situ reflective high energy electron diffraction beam is exploited to monitor the synthesis in real-time. Analysis of the patterns confirms the phase separation and volatization process. Successful synthesis of M-Ox, where M = Mn, Fe, Co, and Cr, is shown using this template-free facile approach. Detailed magnetic characterization of nanocrystals is carried out to reveal the functionalities such as magnetic anisotropy as well as larger than bulk moments, as expected in these oxide nanostructures.
Keywords: Bi2O3 evaporation; bismuth perovskites; epitaxial nanostructures; magnetic oxides; phase separation

Equation-of-motion coupled-cluster method for the study of shape resonance - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2012)
The equation-of-motion coupled-cluster method (EOM-CC) is applied for the first time to calculate the energy and width of a shape resonance in an electron-molecule scattering. The procedure is based on inclusion of complex absorbing potential with EOM-CC theory. We have applied this method to investigate the shape resonance in e(-)N(2), e(-)CO, and e(-)C(2)H(2). (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4729464]

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Evaluation of the insect growth regulator lufenuron (MatchA (R)) for control of aedes aegypti by simulated field trials - Salokhe, S. G.; Deshpande, S. G.; Mukherjee, Samindra N. (Parasitology Research, 2012)
The insect growth regulator, Lufenuron, at concentrations of even multiples of LC90 (determined under laboratory conditions) was tested against the III instar larvae of Aedes aegypti under simulated field conditions. For all concentrations tested, 100 % mortality of the larvae was observed within 24 h of exposure to Lufenuron-treated water. In experiments with LC90 x 4 Lufenuron concentration and where 15 % of water volume was replaced daily, percent mortality of the larvae was reduced to 40 % after the 54th day of treatment. Percentage mortality of the III instar larvae on the 54th day was higher in water with LC90 x 6 concentration than that observed for water with LC90 x 4 of Lufenuron. In the experiments with LC90 x 4 and LC90 x 6 concentrations of Lufenuron where 15 % of water volume was replaced weekly, larval mortality obtained after the eighth week was 68.75 and 88.33 %, respectively. In LC90 x 4 and LC90 x 6 of Lufenuron-treated stagnant water (without replacement of water), the percent mortality of the larvae on the 55th day was 65 and 90 %, respectively. Introducing a fresh batch of III instar A. aegypti larvae in the Lufenuron-treated waters revealed that residual activity of Lufenuron was sustained for 45 days after the treatment. All these experiments revealed that Lufenuron not only affects the prevalence of the A. aegypti larvae but also induces the development of abnormal adults.

Evidence of cationic Pt active for water-gas shift reaction: Pt-doped BaCeO3 perovskite - Rajesh, Thattarathody; Rajarajan, Anakot K.; Gopinath, Chinnakonda S.; Devi, R. Nandini (Journal of Physical Chemistry C, 2012)
Precious metal incorporated into stable lattices like perovskites can be envisaged as an alternative catalysts to address deactivation problems. Here we report the barium cerate perovskite doped with varying amounts of Pt as catalysts for the water-gas shift reaction whereby ionic Pt is evidenced to be active. It is found that maximum CO conversion occurs above 325 degrees C and increases more than 2-fold after the first cycle. XPS analysis shows that after the first cycle, more ionic Pt species are present on the surface of the catalyst. X-ray and neutron diffraction studies also indicate the presence of oxygen vacancies that increases with increasing Pt substitution.

Expanding the structural repertoire of beta/alpha Ant-Pro (anthranilic acid-proline) oligomers into gamma/alpha 2-Amb-Pro (2-aminomethyl benzoic acid-proline) oligomers - Ramesh, Veera V. E.; Priya, Gowri; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Tetrahedron, 2012)
In this article, we report a novel class of heterogeneous synthetic oligomers featuring the conformationally constrained amino acid residues - 2-aminomethyl benzoic acid (2-Amb) and proline (Pro) in repeating sequences. Oligomers as large as hexadecamers featuring the conformationally restricted gamma/alpha 2-Amb-Pro motif have been assembled using solution-phase Boc strategy, following multi-step synthetic sequences starting from the commercially available O-toluic acid. EDC-mediated peptide coupling has been found to be optimum for the assembly of the relatively non-polar oligomers, which could be readily purified by the standard column chromatographic purification procedures. This study offers considerable prospects of expanding the structural repertoire of beta/alpha Ant-Pro motif, which has been described earlier to assume right-handed helical architecture displaying robust nine-membered-ring closed network of hydrogen-bonding interactions, into gamma/alpha 2-Amb-Pro motif. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Foldamer; Peptides; Proline; Synthetic oligomers

Exploring the potential of doped zero-dimensional cages for proton transfer in fuel cells: a computational study - Mane, Manoj V.; Venkatnathan, Arun; Ghatak, Kamalika; Vanka, Kumar (Journal of Physical Chemistry B, 2012)
Calculations with density functional theory (DFT) and MP2 have been done to investigate the potential of recently synthesized durable zero-dimensional (OD) nitrogen-based cage structures to perform as efficient proton-exchange membranes (PEMs) in fuel cells. Our calculations suggest that the hydrogenated 0-D cages, in combination with hydrogen-bonding 1,2,3- and 1,2,4-triazole molecules, would perform as highly efficient PEMs. The results are important in the context of the need for efficient PEMs for fuel cells, especially at higher temperatures (greater than 120 degrees C) where conventional water-based PEMs such as Nafion have been found to be ineffective.

Extended coupled cluster for Raman and infrared spectra of small molecules - Joshi, Sayali P.; Dutta, Achintya Kumar; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
In this paper we study the harmonic vibrational frequencies, infrared (IR) intensities, Raman intensities and depolarization ratio using extended coupled cluster method. Raman and IR intensities are mixed derivatives of energy with respect to the electric field and geometric perturbation whereas vibrational frequencies are derivatives of energy with respect to geometry. We use semi-numerical approach to obtain these derivatives. We have studied the effect of electron correlation and basis set for the above properties. We compare our results with non-variational coupled cluster and experimental values, wherever available. We have studied HF, BH, CH+, CO and H2CO molecules in different basis sets. For HF molecule, benchmarking is done with full CI values and basis set convergence is studied for this molecule. Effect of triples is studied for all the molecules. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Extended coupled cluster; IR and Raman spectroscopy; Mixed derivatives

Extracellular biosynthesis of platinum nanoparticles using the fungus fusarium oxysporum - Syed, Asad; Ahmad, Absar (Colloids and Surfaces B-Biointerfaces, 2012)
Nanoscience is a blooming field and promises a better future. In order to fabricate nanoparticles in an eco-friendly and inexpensive manner, significant efforts are being made to replace the chemical and physical methods currently being used with the biological methods. Chemical methods are toxic while the physical ones are very expensive. Biological methods, apart from being cost-effective, also provide protein capped nanoparticles which are thus very stable, have good dispersity and do not flocculate, and may find use in various applications. The present work emphasizes on platinum nanoparticles synthesis protocol which occurs at ambient conditions. The fungus Fusarium oxysporum when incubated with hexachloroplatinic acid (H2PtCl6) in ambient conditions reduces the precursor and leads to the formation of stable extracellular platinum nanoparticles. The biosynthesis of platinum nanoparticles was monitored by UV-visible spectroscopy and these nanoparticles were completely characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The nanoparticles are in the size range of 5-30 nm and are stabilized by proteins present in the solution. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, fungal-based method for the synthesis of nanoparticles over a wide range of chemical compositions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biosynthesis; Fungus; Nanoparticles; platinum

Extraction and purification of tannase by reverse micelle system - Gaikaiwari, Raghavendra P.; Wagh, Shilpa A.; Kulkarni, Bhaskar D. (Separation and Purification Technology, 2012)
Tannin acyl hydrolase commonly called as tannase (EC 3.1.1.20) is a commercially important enzyme. Partially purified and concentrated tannase is required for commercial applications. Typical objectives of purification process comprise high fold-purification, recovery and concentration. These objectives may be potentially conflicting. Conventional methods of purification require multiple steps which are time consuming and may cause higher loss. Reverse micellar extraction (RME) using ionic surfactants provides an attractive option for concentration and purification of tannase which is a highly hydrophilic glycoprotein. This study presents an optimized methodology for RME and purification of Aspergillus allahabadi intracellular tannase. Fold-purification, percent recovery and extraction time were the objective while the type and concentration of surfactant, contact time, pH, ionic strength, and the ratio of organic to aqueous phase were the decision variables. Some of these parameters were also studied for their effect on back-extraction. Among the surfactants tested, CTAB-isooctane system was found to be suitable. Under optimized conditions, 12.7-fold purification, 81.2% recovery and 3-fold concentration of tannase with a process time of 45 min was obtained. Conventional purification methods provided a higher fold-purification albeit at a much lower enzyme recovery. Further, the conventional method requires a process time of several hours. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: CTAB; Reverse micellar extraction; Tannase

Easy and multigram-scale synthesis of pillar[5]quinone by the hypervalent iodine oxidation of 1,4-dimethoxypillar[5]arene - Shivakumar, Kilingaru I.; Sanjayan, Gangadhar J. (Synthesis-Stuttgart, 2013)
Pillar[5]quinone (P[5]Q), a potential molecule for anion recognition and supramolecular host-guest chemistry, has not as yet been used for practical purposes, presumably due to the synthetic difficulties in obtaining it in large amounts. Herein, we reveal an easy-to-operate and chromatography-free synthetic strategy that can furnish P[5]Q on a multigram scale; its success relies on the utility of hypervalent iodine, generated in situ from Oxone/ iodobenzene, as an efficient oxidant. Pillar[5]quinone was obtained in multigram quantities by oxidation of 1,4-dimethoxypillar[5]arene with Oxone/iodobenzene and simple purification by crystallization from 1,1,2,2-tetrachloroethane, thus opening up the opportunity to explore the properties of this interesting macrocyclic quinone.
Keywords: hypervalent iodine oxidation; macromolecules; pillar-arenes; supramolecular chemistry

Effect of carbon dioxide pressure on 4-t-butylphenol hydrogenation activity of supported rhodium catalyst - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of the Japan Petroleum Institute, 2013)
Hydrogenation of 4-t-butylphenol over an activated carbon-supported rhodium catalyst in carbon dioxide solvent was analyzed based on phase observation with a view cell and calculations of the solubility of 4-t-butylphenol using the Peng-Robinson equation of state as a function of carbon dioxide pressure. The reaction experiments showed that the initial reaction rate of 4-t-butylphenol at 313 K under 2 MPa of hydrogen pressure was increased by the addition of carbon dioxide, especially above a total pressure of 11 MPa. Direct visual observation showed that the solubility of 4-t-butylphenol increased with higher carbon dioxide pressure. The calculations based on the Peng-Robinson equation of state also showed that the solubility of 4-t-butylphenol in the 4-t-butylphenol carbon dioxide hydrogen (2 MPa) system at 313 K significantly increased by addition of carbon dioxide above a total pressure of 11 MPa. We concluded that the increase in the hydrogenation rates was caused by the increased concentration of 4-t-butylphenol substrate in the carbon dioxide solvent.
Keywords: 4-t-Butylphenol hydrogenation; Carbon dioxide solvent; Peng-Robinson equation; Rhodium catalyst; Supercritical fluid

Effect of cation distribution on structural and magnetic properties of Dy substituted magnesium ferrite - Bamzai, K. K.; Kour, Gurbinder; Kaur, Balwinder; Kulkarni, S. D. (Journal of Magnetism and Magnetic Materials, 2013)
Magnesium ferrite and dysprosium (Dy3+) substituted with composition MgDyxFe2-xO4 (x = 0.00-0.07) was prepared by solid state reaction technique. Spinel phase formation was identified using x-ray diffraction technique, thus establishing the cubic spinel symmetry. The morphology was seen through scanning electron microscopic technique, from where the grain size was calculated using average intercept line method. The elemental composition of pure and dysprosium substituted magnesium ferrite was calculated from energy dispersive x-ray analysis spectrum which is then correlated with the experimentally obtained values. Magnetic hysteresis loop of the various compositions establishes it to be soft ferrimagnetic material. The magnetic parameters such as saturation magnetization, coercivity, and retentivity were also calculated. Temperature dependence of saturation magnetization was done to find the Curie temperature of different compositions. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cation distribution; Curie temperature; Electron microscopy; Magnetization; Spinel ferrite

Effect of clay and of electrospinning on the polymorphism, structure and morphology of poly(vinylidene fluoride) - Neppalli, Ramesh; Wanjale, Santosh; Birajdar, Mallinath S.; Causin, Valerio (European Polymer Journal, 2013)
Electrospun poly(vinylidene fluoride) (PVDF) fibers, containing different amounts of montmorillonite clay were produced, in order to study the effect of clay and of the electrospinning process on the polymorphism, structure and morphology of the PVDF matrix, Clay acted as a processing aid agent, avoiding the formation of beads and improving the quality of the fibers. Clay and the electrospinning process acted synergically on the chain mobility, favoring the formation of beta phase of PVDF, the most valuable for its piezoelectric properties, and shaping its semicrystalline morphology. Electrospinning did not significantly aid the dispersion of clay within the matrix. The interplay of formulation and processing in these composites allowed to obtain PVDF-based materials with varying polymorphism, structure and morphology, offering the possibility to ultimately control their functional properties. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Composite; electrospinning; Poly(vinylidene fluoride); Polymer; polymorphism; SAXS

Effect of different arginine methylations on the thermodynamics of tat peptide binding to HIV-1 TAR RNA - Kumar, Santosh; Maiti, Souvik (Biochimie, 2013)
RNA-binding proteins are an important class of mediators that regulate cell function and differentiation. Methylation of arginine, a post-translational modification (PTM) found in these proteins, can modulate their function. Arginine can be monomethylated or dimethylated, depending on the type of methyl transferases involved. This paper describes a comparative study of the thermodynamics of unmodified and modified Tat peptide interaction with TAR RNA, where the peptide is methylated at epsilon (epsilon) and eta (eta) nitrogen atoms of guanidinium group of arginine side chain at position 52 or 53. The results indicate that monomethylation of arginine at epsilon (epsilon) nitrogen atom enhances binding affinity, owing to a more favourable enthalpy component which overrides the less favourable entropy change. In contrast, monomethylation of arginine residue at eta nitrogen results in reduced binding affinity originating exclusively from a less favourable enthalpy change leaving entropic component unaffected. However, in case of simultaneous methylation at epsilon and eta positions, the binding parameters remain almost unaffected, when compared to the unmodified peptide. In case of symmetric dimethylation at eta position the observed enthalpy change of the binding was found to be smaller than the values obtained for the unmodified peptide. Asymmetric dimethylation at eta position showed the most reduced binding affinities owing to less favourable enthalpy changes. These results provide insights that enable elucidation of the biological outcome of arginine methylation as PTMs that regulate protein function, and will contribute to our understanding of how these PTMs are established in vitro and in vivo. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: HIV-1; Post-translational modification; Protein methylation; RNA-protein interaction; Thermodynamics

Effect of foulants on arsenic rejection via polyacrylonitrile ultrafiltration (UF) membrane - Agarwal, Gopal P.; Karan, Raj; Bharti, Sachin; Kumar, Hemant; Jhunjhunwala, Sumit; Sreekrishnan, T. R.; Kharul, Ulhas K. (Desalination, 2013)
Arsenic rejection via modified polyacrylonitrile ultrafiltration (UF) membrane was found to be very high, however, the presence of commonly found foulants in arsenic solution affected membrane performance. The effect of commonly found foulants, such as ovalbumin, humic acid and egg white on arsenic rejection were studied. Experiments indicated that the As(V) rejection was affected by the total quantity of proteins and not the variety of proteins present in a solution. As(V) rejection was found to decrease with increasing proteins while fouling was found to increase from 25% for 0.1 mg/ml to 33% for 0.5 mg/ml egg white. The As(V) rejection was found to decrease with increasing concentration of humic acid for PAN membranes. Fouling studies showed that humic acid was a lesser foulant in comparison to egg white. However a combination of the two foulants led to a decrease in the overall fouling. pH was also found to be a very important factor for egg white dissolution and As(V) rejection. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; Egg white; Humic acid; Ovalbumin; Polyacrylonitrile; Ultrafiltration

Effect of loops and G-quartets on the stability of RNA G-quadruplexes - Pandey, Satyaprakash; Agarwala, Prachi; Maiti, Souvik (Journal of Physical Chemistry B, 2013)
The loop length, loop composition, salt concentration, and number of G-quartets are major determinants of G-quadruplex stability. We examined the effect of each of these factors on the thermal stability and folding topology of a library of RNA quadruplexes. The thermal stability of G2 and G3 RNA quadruplexes was investigated upon varying the loop length (from 1-1-1 to 15-15-15) and salt concentration (from sequence 1 to 100 mM KCl), while the effect of loop composition was explored using 18 naturally occurring potential RNA quadruplexes predicted in untranslated regions (UTRs). We found loop length and quadruplex stability to be inversely related for G2 RNA quadruplexes and G3 RNA quadruplexes with shorter loops. However, melting temperature saturates for G3 RNA quadruplexes with longer loops. RNA G-quadruplexes with longer loops (G3 15-15-15) displayed T-m values significantly higher than the physiological temperature. This study thus highlights the need to modify the consensus motif presently used by quadruplex prediction tools. An increase in the loop size from 7 bases to IS bases in the consensus motif will add to its predictive value for the discovery of potential RNA quadruplexes across transcriptomes.

Effect of N-acetylation and N-methylation of lysine residue of tat peptide on its interaction with HIV-1 TAR RNA - Kumar, Santosh; Maiti, Souvik (Plos One, 2013)
Post-translational modification (PTM) of RNA binding proteins (RBPs) play a very important role in determining their binding to cognate RNAs and therefore regulate the downstream effects. Lysine can undergo various PTMs and thereby contribute to the regulation of different cellular processes. It can be reversibly acetylated and methylated using a pool of respective enzymes, to act as a switch for controlling the binding efficiency of RBPs. Here we have delineated the thermodynamic and kinetic effects of N-acetylation and N-monomethylation of lysine on interaction between HIV-1 TAR RNA and its cognate binder Tat peptide (a model system). Our results indicate that acetylation of lysine 50 (K50), leads to eight-fold reduction in binding affinity, originating exclusively from entropy changes whereas, lysine 51 (K51) acetylation resulted only in three fold decrease with large enthalpy-entropy compensation. The measurement of kinetic parameters indicated major change (4.5 fold) in dissociation rate in case of K50 acetylation however, K51 acetylation showed similar effect on both association and dissociation rates. In contrast, lysine methylation did not affect the binding affinity of Tat peptide to TAR RNA at K50, nonetheless three fold enhancement in binding affinity was observed at K51 position. In spite of large enthalpy-entropy compensation, lysine methylation seems to have more pronounced position specific effect on the kinetic parameters. In case of K50 methylation, simultaneous increase was observed in the rate of association and dissociation leaving binding affinity unaffected. The increased binding affinity for methylated Tat at K51 stems from faster association rate with slightly slower dissociation rate.

Effect of organic modification on the intercalation and the properties of poly(phenylene oxide)/polystyrene blend-clay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Thermoplastic Composite Materials, 2013)
Nanocomposites prepared by the dispersion of unmodified and organically modified montmorillonite (MMT) clay into poly(2,6-dimethyl phenylene oxide)/polystyrene miscible blend in the range of 2-10 wt% clay were investigated by wide-angle x-ray diffraction, transmission electron microscopy, differential scanning calorimetry, thermogravimetric analysis and tensile mechanical tests. The systems based on unmodified sodium MMT (Na+MMT) as well as Cloisite 20A, Cloisite 30B and Cloisite 10A organically modified clays showed polymer intercalation. The glass transition temperature (T-g) value was not affected by the volume fraction of clay and chemical nature of the organoclay. The thermal degradation stability of nanocomposites is found to be only slightly better than that of the blend matrix. A percolation threshold of around 4 wt% organoclay loading is observed. An improvement of 35% relative to unfilled polymer blend matrix is observed for the modulus, for Cloisite 20A nanocomposite containing 2 wt% organoclay. The observed modulus improvement with significant retention of elongational tensile strength and tensile ductility in case of unmodified Na-MMT and Cloisite 30B nanocomposites appears promising. The modulus prediction using Halpin-Tsai model is found to be closer to the experimental data when MMT volume fraction rather than the organoclay volume fraction is used.
Keywords: filler; interface; interphase; mechanical properties; Nanostructures; Polymer-matrix composites

Effect of phytase from aspergillus niger on plant growth and mineral assimilation in wheat (Triticum aestivum Linn.) and its potential for use as a soil amendment - Gujar, Pradnya D.; Bhavsar, Kavita P.; Khire, Jayant Malhar (Journal of the Science of Food and Agriculture, 2013)
Background Extensive use of non-replenishable phosphate reserves as phosphate supplements in agriculture and animal feed poses a threat for environmental pollution and necessitated a search for alternative phosphate sources. Unlocking the phytate phosphorus using microbial phytase can provide an ecofriendly solution in agriculture. The aim of the present work was to evaluate the effect of phytase from Aspergillus niger NCIM 563 in degradation of phytate phosphorus to benefit plant nutrition and soil amendment in comparison with chemical fertilizers. Results An enzyme dose of 12 IU was sufficient to hydrolyze phytate and increase assimilation of phosphorus by about 74%. Phytase supplementation leads to increase in shoot:total length ratio by about 200%, indicating its growth-promoting effect. Consistency in phytase-induced growth was reflected at pot and tray levels, wherein shoot:total length ratio was observed to be 2.01 and 2.12 respectively. Mineral assimilation due to phytase was more efficient as compared to chemical fertilizers, thus overcoming the constraints of practicability and economics in the agriculture industry. Phytase was efficient in reducing the phytic acid content of soil by about 30% while simultaneously increasing the phytate phosphate availability by 1.18-fold. Conclusion Phytase from A. niger showed improvement in phytate phosphorus and mineral availability. Besides a plant growth-promoting effect, reduction in use of chemical fertilizers and soil improvement could be achieved simultaneously for maintaining the sustainability of agriculture. (c) 2012 Society of Chemical Industry
Keywords: mineral assimilation; Phytase; phytate degradation; plant growth promotion; soil amendment

Effect of the viscosity of poly(benzimidazole) on the performance of a multifunctional electrocatalyst with an ideal interfacial structure - Balan, Beena K.; Unni, Bipinlal; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2013)
A novel electrocatalyst system with unique multifunctional characteristics, originated by the presence of a proton conducting polybenzimidazole (PBI-BuI) bound layer and electron conducting hollow carbon nanofibers (CNF) with catalytically active Pt nanoparticles, has been devised based on a simple strategy. This was achieved by decorating Pt nanoparticles along the inner cavity, as well as on the outer walls of the hollow CNF support (F-Pt). In a further extension, a low molecular weight PBI, synthesized by optimizing the experimental parameters, was incorporated into the inner cavity and along the outer surfaces of F-Pt. Excellent dispersion of the Pt nanoparticles was achieved by properly utilizing the available carbon surface results in improved electrocatalytic activity, while the CNF backbone ensures high electron conductivity as well. The polymer binder coverage formed along the inner and outer wall surfaces provides an efficient triple phase boundary (TPB) around the Pt nanoparticles to facilitate the electrode reactions. The amount and the viscosity of the PBI-BuI in the electrode material were systematically varied to study the influence on the electrochemical performance. Transmission electron microscopy analysis confirms PBI insertion into the tubular cavity of CNF. Pore size distribution analysis implies that both the viscosity and the amount of PBI-BuI have a pivotal role in defining the microstructure of the electrode. Electrochemical studies using cyclic voltammetry (CV) and rotating disc electrode (RDE) reveal the exceptionally high activity of this hybrid material with an improved electrochemically active area. The significant improvement for the oxygen reduction reaction is further confirmed by the single cell analysis also. The high power density displayed by the PBI-BuI based system, as compared to the Nafion based system, validates the conceptualization of the well controlled triple-phase boundary in the system. These results demonstrate that PBI-BuI has a constructive effect in tuning the electrochemical activity at an optimum amount and at a favourable viscosity of the proton conducting polymer.

Effective fragment potential method in Q-CHEM: a guide for users and developers - Ghosh, Debashree; Kosenkov, Dmytro; Vanovschi, Vitalii; Flick, Joanna; Kaliman, Ilya; Shao, Yihan; Gilbert, Andrew T. B.; Krylov, Anna I.; Slipchenko, Lyudmila V. (Journal of Computational Chemistry, 2013)
A detailed description of the implementation of the effective fragment potential (EFP) method in the Q-CHEM electronic structure package is presented. The Q-CHEM implementation interfaces EFP with standard quantum mechanical (QM) methods such as HartreeFock, density functional theory, perturbation theory, and coupled-cluster methods, as well as with methods for electronically excited and open-shell species, for example, configuration interaction, time-dependent density functional theory, and equation-of-motion coupled-cluster models. In addition to the QM/EFP functionality, a fragment-only feature is also available (when the system is described by effective fragments only). To aid further developments of the EFP methodology, a detailed description of the C++ classes and EFP module's workflow is presented. The EFP input structure and EFP job options are described. To assist setting up and performing EFP calculations, a collection of Perl service scripts is provided. The precomputed EFP parameters for standard fragments such as common solvents are stored in Q-CHEM's auxiliary library; they can be easily invoked, similar to specifying standard basis sets. The instructions for generating user-defined EFP parameters are given. Fragments positions can be specified by their center of mass coordinates and Euler angles. The interface with the IQMOL and WEBMO software is also described. (c) 2013 Wiley Periodicals, Inc.
Keywords: effective fragment potential; EFP library; hybrid QM; IQMOL; MM; modular code; nonempirical force field; Q-CHEM; WEBMO

Efficient and stereoselective nitration of mono- and disubstituted olefins with AgNO2 and TEMPO - Maity, Soham; Manna, Srimanta; Rana, Sujoy; Naveen, Togati; Mallick, Arijit; Maiti, Debabrata (Journal of the American Chemical Society, 2013)
Nitroolefin is a common and versatile reagent. Its synthesis from olefin is generally limited by the formation of mixture of cis and trans compounds. Here we report that silver nitrite (AgNO2) along with TEMPO can promote the regio- and stereoselective nitration of a broad range of olefins. This work discloses a new and efficient approach wherein starting from olefin, nitroalkane radical formation and subsequent transformations lead to the desired nitroolefin in a stereoselective manner.

Efficient bakers' yeast-catalyzed multicomponent synthesis of -aminophosphonates in one pot - Bhattacharya, Asish K.; Mujahid, Mohammad (Synthetic Communications, 2013)
Utilizing bakers' yeast (Saccharomyces cerevisiae) as a biocatalyst, synthesis of -aminophosphonates in one pot has been accomplished by the three-component reaction of an aldehyde, an amine, and diethyl phosphite in moderate to good yields under solvent-free reaction conditions. Supplemental materials are available for this article. Go to the publisher's online edition of Synthetic Communications (R) to view the free supplemental file.
Keywords: -aminophosphonates; aldehydes; amines; green chemistry; Saccharomyces cerevisiae; solvent-free conditions

Efficient, direct synthesis of dimethyl carbonate from CO2 using a solid, calcined zirconium phenylphosphonate phosphite catalyst - Unnikrishnan, Pulikkeel; Varhadi, Poonam; Srinivas, Darbha (RSC Advances, 2013)
Direct synthesis of dimethyl carbonate (DMC) from CO2 and methanol with 100 mol% selectivity using a solid, reusable, hydrophobic, calcined zirconium phenylphosphonate phosphite catalyst is reported for the first time. DMC yield as high as 26 mmol g(-1) catalyst correlated with the concentration of acid and base sites is obtained.

Efficient, stable, and reusable silicoaluminophosphate for the one-pot production of furfural from hemicellulose - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (ACS Catalysis, 2013)
Development of stable, reusable, and water tolerant solid acid catalysts in the conversion of polysaccharides to give value-added chemicals is vital because catalysts are prone to undergo morphological changes during the reactions With the anticipation that silicoaluminophosphate (SAPO) catalysts will have higher hydrothermal stability, those were synthesized, characterized, and employed in a one-pot conversion of hemicellulose. SAPO-44 catalyst at 170 degrees C within 8 h could give 63% furfural yield with 88% mass balance and showed similar activity up to at least 8 catalytic cycles. The morphological studies revealed that SAPO catalysts having hydrophilic characteristics are stable under reaction conditions.
Keywords: furfural; Hemicellulose; hydrophilicity; SAPO; water-tolerant catalyst; zeolite

Electrochemical resolution of multiple redox events for graphene quantum dots - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Angewandte Chemie-International Edition, 2013)
Keywords: charging energy; differential pulse voltammetry; graphene; quantum dots; single-electron transfer

Electron rich porous extended framework as a heterogeneous catalyst for Diels-Alder reactions - Gole, Bappaditya; Bar, Arun Kumar; Mallick, Arijit; Banerjee, Rahul; Mukherjee, Partha Sarathi (Chemical Communications, 2013)
An electron rich porous metal-organic framework (MOF) has been synthesized, which acts as an effective heterogeneous catalyst for Diels-Alder reactions through encapsulation of the reactants in confined nano-channels of the framework.

Electronic transition dipole moments and dipole oscillator strengths within fock-space multi-reference coupled cluster framework: an efficient and novel approach - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2013)
Within the Fock-space multi-reference coupled cluster framework, we have evaluated the electronic transition dipole moments, which determine absorption intensities. These depend on matrix elements between two different wave functions (e. g., ground state to the excited state). We present two different ways, to calculate these transition moments. In the first method, we construct the ground and excited state wave functions with the normal exponential ansatz of Fock-space coupled cluster method and then calculate the relevant off-diagonal matrix elements. In the second approach, we linearize the exponential form of the wave operator which will generate the left vector, by use of Lagrangian formulation. The right vector is obtained from the exponential ansatz. In order to relate the transition moments to oscillator strengths, excitation energies need to be evaluated. The excitation energies are obtained from the Fock-space multi-reference framework. The transition dipole moments of the ground to a few excited states, together with the oscillator strengths of a few molecules, are presented. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4793277]

Electrophile induced branching cascade: a powerful approach to access various molecular scaffolds and their exploration as novel anti-mycobacterial agents - Patil, Nitin T.; Konala, Ashok; Sravanti, Sudha; Singh, Ashita; Ummanni, Ramesh; Sridhar, Balasubramanian (Chemical Communications, 2013)
Herein we report on the Electrophile Induced Branching Cascade (EIBC), a new technique to produce a variety of biologically important molecular scaffolds. Some compounds exhibit excellent activities against Mycobacterium smegmatis.

Employing arynes in transition-metal-free monoarylation of aromatic tertiary amines - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Biju, Akkattu T. (Organic Letters, 2013)
The highly monoselective N-arylation of aromatic tertiary amines using a transition-metal-free approach using arynes has been developed. The reaction afforded functionalized diaryl amines in moderate to excellent yield. High levels of functional group compatibility especially with halogen containing substrates, dyes and donor-acceptor systems, and high yields of products are the notable features of the present reaction.

Enantiodivergent routes to (+) and (-)-novioses from (-)-pantolactone - Rajesh, B. M.; Shinde, Madhuri V.; Kannan, M.; Srinivas, Gujjary; Iqbal, Javed; Reddy, D. Srinivasa (RSC Advances, 2013)
Noviose, a rare sugar moiety present in many biologically interesting molecules such as novobiocin and tiacumicin was obtained through formal synthesis in (+)- and (-)-forms starting from commercially available (-)-pantolactone in an enantiodivergent manner.

Enantioselective total synthesis of desbromoarborescidines A-C and the formal synthesis of (S)-deplancheine - Mondal, Pravat; N. P. Argade (Journal of Organic Chemistry, 2013)
Starting from Boc-protected tryptamine and (S)-tetrahydro-5-oxo-2-furancarboxylic acid, facile enantioselective total synthesis of desbromoarborescidines A-C and the formal synthesis of (S)-deplancheine have been accomplished via a common intermediate (S)-indolo[2,3-a]quinolizine. Synthesis of enantiomerically pure (S)-acetoxyglutarimide, stereoselective reductive intramolecular cyclization, hydroxyl group assisted in situ N-Boc-deprotection, selective deoxygenation, of the xanthate ester, and lactam hydrolysis followed by an appropriate exchange of nitrogen regioselectivity in intramolecular cyclization were the decisive steps.

Engaging isatins in solvent-free, sterically congested passerini reaction - Kaicharla, Trinadh; Yetra, Santhivardhana Reddy; Roy, Tony; Biju, Akkattu T. (Green Chemistry, 2013)
A facile, atom-economic and environmentally-benign protocol for the synthesis of biologically important oxindole derivatives in high yields has been demonstrated by employing isatins as carbonyl compound surrogates in a Passerini reaction carried out under solvent-free conditions. Moreover, electron-deficient phenols can also be used as the acid component in this reaction. In addition, the synthetic utility of the present methodology was examined by the one-pot synthesis of oxindoles with a free -OH group at the benzylic position.

Enhanced dual-effect of adsorption and photodegradation of SiO2 embedded TiO2 hybrid catalyst for improved decolourization of methylene blue - Sonar, Shilpa K.; Wagh, Reshma V.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Awate, Shobhana V. (Water Air and Soil Pollution, 2013)
Dual-effects of adsorption and photodegradation over titania, silica embedded titania, silica and commercial Degussa P-25 samples were studied for the decolourization of methylene blue in aqueous medium. Silica embedded titania and silica were prepared using inexpensive polymeric version of ethyl silicate as a source of silica. Catalysts were characterized by X-ray diffraction, scanning electron microscopy, UV-Vis spectroscopy and low temperature (77 K) nitrogen adsorption measurements. Among all the catalysts, silica embedded titania has exhibited faster decolourization of methylene blue solution on account of the enhancement of adsorption followed by degradation. An amount of the catalyst and the initial dye concentration of MB solution were found to influence the decolourization activity. Compared to titania catalyst, silica embedded titania and Degussa P-25 have shown the red shift in their UV-Vis spectrum. The experimental data of the reaction fitted well to the pseudo first order kinetic model. In present studies, the adsorption mechanism for the decolourization of MB solution was found to be applicable for an intra particle diffusion model.
Keywords: Adsorption; kinetic model; Methylene blue; Photodegradation; Silica embedded titania

Enhanced electrochromic coloration in Ag nanoparticle decorated WO3 thin films - Kharade, Rohini R.; Mali, Sawanta S.; Patil, Satish P.; Patil, Kashinath R.; Gang, Myong G.; Patil, Pramod S.; Kim, Jin H.; Bhosale, Popatrao N. (Electrochimica Acta, 2013)
WO3/Ag composite thin films were prepared by microwave assisted sol-gel synthesis (MW-SGS) of WO3 followed by vacuum evaporation of Ag nanoparticles and their enhanced electrochromic coloration was investigated. The composition and morphology of WO3 thin films with different thickness of Ag layer obtained by vacuum evaporation were investigated. Distinct plasmon absorption bands of Ag nanoparticle thin films were obtained. The optical band gap energy of WO3/Ag films decreased with increasing the Ag layer thickness. The surface of these films has been examined using X-ray photoelectron spectroscopy (XPS) to gain information about the chemical states of species present at surfaces. Experimental results indicated that the conductivity of the films increased after surface modification by Ag layer. To investigate the origin of enhanced electrochromic absorption in optical properties, working electrode consisting of WO3/Ag thin film was used and observed the optical properties during electrochemical reaction. It was found that composite electrode shows enhancement in electrochromic properties in terms of optical modulation (Delta OD) and coloration efficiency (eta). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ag2WO4; CIE coordinates; Electrochromism; SPR; WO3/Ag composite thin films

Enhanced field-emission behavior of layered MoS2 sheets - Kashid, Ranjit V.; Late, Dattatray J.; Chou, Stanley S.; Huang, Yi-Kai; De, Mrinmoy; Joag, Dilip S.; More, Mahendra A.; Dravid, Vinayak P. (Small, 2013)
Field emission studies are reported for the first time on layered MoS2 sheets at the base pressure of approximate to 1 x 10(-8) mbar. The turn-on field required to draw a field emission current density of 10 A/cm(2) is found to be 3.5 V/m for MoS2 sheets. The turn-on values are found to be significantly lower than the reported MoS2 nanoflowers, graphene, and carbon nanotube-based field emitters due to the high field enhancement factor (approximate to 1138) associated with nanometric sharp edges of MoS2 sheet emitter surface. The emission current-time plots show good stability over a period of 3 h. Owing to the low turn-on field and planar (sheetlike) structure, the MoS2 could be utilized for future vacuum microelectronics/nanoelectronic and flat panel display applications.

Enhanced hole carrier transport due to increased intermolecular contacts in small molecule based field effect transistors - Dharmapurikar, Satej S.; Arulkashmir, Arulraj; Das, Chayanika; Muddellu, Pooja; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2013)
Small molecules and oligomers can be synthesized with very high purity and precise molecular weights, but they often do not form uniform thin films while processed from solution. Decreased intermolecular contacts between the small molecules are another disadvantage. To increase the intermolecular contacts in small molecules, we have chosen i-indigo, as one of the conjugated molecular units. The electron poor i-indigo has been connected with electron rich triphenylamine to synthesize a donor-acceptor-donor type small molecule. The propeller shaped triphenylamine helps to increase the solubility of the small molecule as well as isotropic charge transport. The intermolecular spacing between the molecules has been found to be low and did not vary as a function of thermal annealing. This implies that the intermolecular contacts between the small molecules are enhanced, and they do not vary as a function of thermal annealing. Organic field effect transistors (OFET) fabricated using a small molecule exhibited a hole carrier mobility (mu) of 0.3 cm(2)/(V s) before thermal annealing. A marginal increase in mu was observed upon thermal annealing at 150 degrees C, which has been attributed to changes in thin film morphology. The morphology of the thin films plays an important role in charge transport in addition to the intermolecular spacing that can be modulated with a judicious choice of the conjugated molecular unit.
Keywords: hole mobility; i-indigo; organic field effect transistor; quadrupole interaction; small molecules; triphenylamine

Enhancement of chemical stability and crystallinity in porphyrin-containing covalent organic frameworks by intramolecular hydrogen bonds - Kandambeth, Sharath; Shinde, Digambar Balaji; Panda, Manas K.; Lukose, Binit; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: covalent organic frameworks; hydrogen bonds; mesoporous materials; porphyrinoids; tautomerism

Environmentally benign enhanced H-2 production from abundant copious waste H2S using size tuneable cubic bismuth (Bi-0) quantum dots-GeO2 glass photocatalyst under solar light - Apte, Sanjay K.; Garaje, Sunil N.; Naik, Sonali D.; Waichal, Rupali P.; Kale, Bharat B. (Green Chemistry, 2013)
Hydrogen sulfide is a copious gas produced in refineries (15-20%) as well as billions of tons produced as a by-product in alkali industries. Selectively, only 5% has been utilised for the Claus process to produce liquid sulfur and it is also well known for its uneconomical and environmental problems. Here, we have demonstrated a significant green approach for conversion of poisonous H2S into H-2 by stable cubic bismuth (Bi-0) quantum dot-glass nanosystems using solar light as the energy source. Previously, metal oxides and sulfides have been demonstrated as solar light photocatalysts. However, a unique bismuth quantum dot-glass nanosystem has been designed where cubic phase bismuth quantum dots of size 1-2 nm are grown in the germanate glass matrix successfully. The presence of bismuth (Bi-0) was confirmed by XRD, Raman, TEM and X-ray photoelectron spectroscopy (XPS). The glass nanosystem shows quantum confinement with variation of the band gap from 2.95-1.51 eV. Considering the broad absorption from visible to near IR, we used this glass nanosystem as a solar light active photocatalyst and hydrogen production with respect to the quantum confinement of bismuth (Bi-0) quantum dots has been demonstrated for the first time. The photocatalytic activity for hydrogen production using glass nano-systems having bismuth quantum dot sizes of 1-2 nm and 3-6 nm was measured under solar light and prima fascia observations revealed that the glass nanosystems with very small quantum dots (1-2 nm) showed enhanced hydrogen evolution (11 541 mu mol h(-1) g(-1)) from H2S. The hydrogen evolution obtained is much higher than for previously reported visible light active nanostructured sulfide/oxide or embedded glass nanosystems. The glass nanosystems were also used for water splitting and show evolution of hydrogen without any co-catalyst. It is noteworthy that the quantum dot-glass photocatalyst is highly stable and catalyst regeneration is quite easy and fast. Hence, the QD-bismuth-glass nanocomposites have significant advantages over normal nanosized powder catalysts. Such unique glass nanosystems will also have great potential in photonics and optoelectronic applications.

Enzymatic degumming of silk with microbial proteases - More, Shivaji V.; Khandelwal, Harish B.; Joseph, M. A.; Laxman, Ryali Seeta (Journal of Natural Fibers, 2013)
Degumming of Chinese bivoltine silk with alkaline proteases from various microbial sources was investigated and compared with commercial enzymes. Among the proteases tested, two fungal and two actinomycete proteases were promising, which showed weight loss similar to conventional method (19.58% to 21.78%). Conidiobolus brefeldianus and BOA-2 proteases were best enzymes, which showed weight loss similar to conventional method with low enzyme concentrations and in shorter time. No significant differences were found in tensile strength or elongation at break by enzymatic degumming indicating that there was no damage to the fiber. Scanning electron micrographs showed the sericin deposits were removed and the fibers were separated.
Keywords: Alkaline Protease; bivoltine; degumming; microbial; Silk; weight loss

Epoxidation of styrene by t-butyl hydroperoxide over gold nanoparticles supported on Yb2O3: effect of gold deposition method, gold loading, and calcination temperature of the catalyst on its surface properties and catalytic performance - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, N. S.; Uphade, B. S.; Bhargava, Suresh Kumar (Journal of Catalysis, 2013)
Surface properties and epoxidation performance of Au/Yb2O3 catalyst are influenced by the method of gold deposition [viz. deposition-precipitation (DP), homogeneous deposition-precipitation (HDP) or impregnation], gold loading (0.9-6.6 wt%), and the catalyst calcination temperature (400-900 degrees C)]. The catalyst showed the best epoxidation performance when it was prepared by the HDP method and calcined at 500 degrees C. The Au/Yb2O3 catalyst even after calcination at 900 degrees C showed good activity and epoxide selectivity. Both Au-0 and Au3+ surface species were found in the catalyst calcined at 800 degrees C, but only Au-0 species were observed at the lower calcination temperatures (<600 degrees C). The selectivity for styrene oxide increased continuously with the reaction temperature (from 75 degrees C to 97 degrees C) and time (1-5 h), indicating that styrene oxide did not undergo secondary reactions under these conditions. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/Yb2O3 catalyst; Epoxidation of styrene; gold nanoparticles; Styrene oxide; tert-Butyl hydroperoxide

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.

Evaluation of ethanol production by a new isolate of yeast during fermentation in synthetic medium and sugarcane bagasse hemicellulosic hydrolysate - Hande, Aparna; Mahajan, Siddharth A.; Prabhune, Asmita (Annals of Microbiology, 2013)
A new xylose fermenting yeast was isolated from over-ripe banana by enrichment in xylose-containing medium. The phylogenetic analysis of ITS1-5.8S-ITS2 region sequences of ribosomal RNA of isolate BY2 revealed that it shows affiliation to genus Pichia and clades with Pichia caribbica. In batch fermentation, Pichia strain BY2 fermented xylose, producing 15 g l(-1) ethanol from 30 g l(-1) xylose under shaking conditions at 28A degrees C, with ethanol yield of 0.5 g g(-1) and volumetric productivity of 0.31 g l(-1) h(-1). The optimum pH range for ethanol production from xylose by Pichia strain BY2 was 5-7. Pichia strain BY2 also produced 6.08 g l(-1) ethanol from 30 g l(-1) arabinose. Pichia strain BY2 can utilize sugarcane bagasse hemicellulose acid hydrolysate for alcohol production, efficiency of fermentation was improved by neutralization, and sequential use of activated charcoal adsorption method. Percent total sugar utilized and ethanol yield for the untreated hydrolysate was 17.14% w/v and 0.33 g g(-1), respectively, compared with 66.79% w/v and 0.45 g g(-1), respectively, for treated hemicellulose acid hydrolysate. This new yeast isolate showed ethanol yield of 0.45 g g(-1) and volumetric productivity of 0.33 g l(-1) h(-1) from sugarcane bagasse hemicellulose hydrolysate detoxified by neutralization and activated charcoal treatment, and has potential application in practical process of ethanol production from lignocellulosic hydrolysate.
Keywords: D-xylose; Ethanol; Pichia; Sugarcane bagasse hemicellulose

Evaluation of viability of halogen•••O2N interactions: insight form crystal packing in a series of isomeric halo and nitro substituted triaryl compounds with modular positioning of halogen and NO2 groups - Ramana, Chepuri V.; Goriya, Yogesh; Durugkar, Kulbhushan A.; Chatterjee, Soumitra; Krishnaswamy, Shobhana; Gonnade, Rajesh G. (CrystEngComm, 2013)
A series of isomeric triaryl compounds with a modular positioning of the halogen and NO2 groups have been synthesized by the azide–alkyne “click reaction” and have been characterized by single crystal X-ray structure analysis. This isomeric series has provided an opportunity for understanding the efficiency of the bifurcated halogen⋯NO2 synthon in the organization of the molecules in the crystalline lattice. The changes in molecular conformation, crystal packing and supramolecular aggregation due to the change in the relative positioning of the complementary groups, halogen atom and the NO2 group on ring A and ring C respectively, have been discussed. All the isomers synthesized are crystalline and establish the triazole as a reliable linker for crystal engineering oriented molecular synthesis. The 2-NO2 derivatives display in general, a helical architecture and 3-NO2 derivatives exhibit a centrosymmetric dimeric assembly via the complementary C–H⋯O interactions leading to either a helical or a 2-dimensional sheet pattern. The molecular organization in 4-NO2 derivatives revealed in general a 2D sheet pattern.

Evidence and characterization of dynamic heterogeneity in binary mixtures of phosphoric acid and benzimidazole - Pahari, Swagata; Roy, Sudip (Journal of Chemical Physics, 2013)
We report here anomalous diffusions of components in mixtures of monomer of polybenzimidazole, i.e., 2-phenyl-1H, 1'H-5,5'-bibenzo[d] imidazole (BI) and phosphoric acid (PA) from molecular dynamics simulations. We have observed initial drop and further increase in self-diffusion constant for both monomer molecule (BI) and PA with gradual increase in PA concentration. The origin of such anomalous diffusion is identified in this work, which happens to be the presence of dynamic heterogeneity in each component of the binary mixture. We characterized microscopic picture of dynamical heterogeneity by finding correlation between dynamical heterogeneity and structural arrangement among the components of the binary system. Different types of H-bonding arrangements in the BI-PA systems at different concentration of PA are observed. The stability of the H-bonded network consisting of different types of H-bonds between BI and PA in the system has been studied by calculating the lifetime of various H-bonds. The results indicate that there are fast and slow moving PA molecules in the mixtures because of coexistence of different types of hydrogen bonds among the components of the mixture. (C) 2013 AIP Publishing LLC.

Evolution and magnetic characteristics of NiO-Ni(OH)(2) core-shell nanostructures - Mahajan, Mangesh B.; Joy, Pattayil Alias (Physical Chemistry Chemical Physics, 2013)
The evolution and magnetic behaviour of NiO-Ni(OH)(2) core-shell nanostructures with different thicknesses of the hydroxide shell have been studied. The nickel hydroxide shell is found to alter the magnetic characteristics of nickel oxide at low temperatures and explains the origin of the exchange bias effect due to the anti-ferromagnetic NiO core and a ferromagnetic nickel hydroxide shell.

Exclusion from hexagonal mesophase surfactant domains drives end-to-end enchainment of rod-like particles - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen, Debasis; Bhagavatula L. V. Prasad; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2013)
Anisotropic rod-like particles assemble end-to-end when the surfactant/water matrix in which they are dispersed is cooled from the isotropic to the lyotropic hexagonal phase. We demonstrate the formation of such end-to-end assemblies for gold nanorods, which are tens of nanometers in size, as well as for micrometer-sized ellipsoidal polystyrene particles. In both cases, the particles are well-dispersed in the low-viscosity surfactant/water phase above the isotropic-H-1 transition temperature. On cooling into the H-1 phase, mesophase domains form and the particles are expelled to the isotropic phase. As the H-1 domains grow and finally impinge, the particles are localized at the domain boundaries where they reorient and assemble end-to-end. Remarkably, we observe the formation of end-to-end assemblies of gold nanorods even for volume fractions as low as 2 x 10(-6) in the initially dispersed state. The extent of particle ``enchainment'' increases with the particle concentration and with the aspect ratio of the particles.

Expedient preparative isolation, quantification and characterization of limonoids from neem fruits - Haldar, Saikat; Phapale, Prasad B.; Kolet, Swati P.; Thulasiram, Hirekodathakallu V. (Analytical Methods, 2013)
Major basic limonoids from Neem fruits such as azadirone, epoxyazadiradione and azadiradione were isolated in preparative scale using an automated and rapid medium pressure liquid chromatography (MPLC)-based protocol. They were individually quantified using HPLC. An LC-ESI-MS/MS-based rapid identification technique was developed for the high-throughput screening of these limonoids in phytochemical extracts.

Exploring the effectiveness of different Lewis pair combinations in caged structures for the catalysis of ammonia borane dehydrogenation: a DFT study - Pal, Amrita; Vanka, Kumar (Physical Chemistry Chemical Physics, 2013)
Zero dimensional cage structures containing four phenyl rings separated by imine linkers have recently been synthesized. In the current work, through a computational investigation using density functional theory (DFT), we demonstrate that modifying such cages by replacing the 2, 4, 6 carbon atoms in the phenyl rings to yield new rings, as well as replacing the imine moiety in the linker by other electronegative atoms, can yield interesting new cages that can be reactive in catalysing reactions such as the dehydrogenation of ammonia borane-an important reaction in hydrogen storage research. Specifically, it is predicted that phosphorus-nitrogen pairs (phosphorus in the 2, 4, 6 positions in the ring, nitrogen in the linker position), germanium-nitrogen and germanium-phosphorus pair combinations would lead to effective Lewis pairs that can work in tandem to dehydrogenate ammonia borane efficiently under room temperature conditions.

Extended coupled cluster through nth perturbation order for molecular response properties: a comparative study - Gupta, Jitendra; Manohar, Prashant Uday; Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2013)
In this paper, we have presented and analyzed the extended coupled cluster (ECC) energy functional, truncated up to nth perturbation order in which expansion is limit to operators of the single and double excitations. The expression for the first order energy derivatives based on the above truncation schemes has been derived and numerically analyzed. We have done a comparative study for dipole moment in various perturbative ECC (n) methods (2 <= n <= 5) for three systems (HF, H2O and BH) at equilibrium geometry. We have particularly studied two variants of ECC (4) and ECC (5*) method for stretched geometry. We have analyzed the contribution of important terms present in ECC functional based on perturbative argument. We have compared our results with standard coupled cluster (CCSD) as well as cubic truncated ECC and also benchmarked with the full CI results wherever available. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Energy functional; Extended coupled cluster

Extra- and intracellular gold nanoparticles synthesis using live peanut callus cells - Raju, D.; Mehta, Urmil J.; Ahmad, Absar (Current Nanoscience, 2013)
An important challenge of considerable topical significance in nanotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials in large quantities with variable sizes, shapes and chemical compositions. Green synthesis routes for the production of inorganic metal nanoparticles using whole cell of microorganisms and plant extracts are gaining tremendous popularity as these are non-toxic, cheap and occur at ambient conditions. The present work emphasizes on gold nanoparticles synthesis protocol using live plant callus cells. Peanut callus cells when incubated with HAuCl4 solution in ambient conditions reduced the precursor and lead to formation of well dispersed, water soluble extracellular and intracellular gold nanoparticles within 24 hours. The biosynthesis of gold nanoparticles was monitored by UV-visible spectroscopy (UV-Vis) and further characterized by X-ray diffraction analysis (XRD), Energy Dispersive Spectroscopy (EDS) and Selected Area Electron Diffraction (SAED). The particle size distribution shows that the average particle size is 50 nm for extra-and 31 nm for intracellular gold nanoparticles. The nanoparticles may be stabilized by proteins secreted by callus cells. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, plant cell-based method for the synthesis of nanoparticles over a wide range of chemical compositions.
Keywords: Biosynthesis; callus; gold nanoparticles; live cells; Peanut; TEM

Extracellular biosynthesis of CdTe quantum dots by the fungus fusarium oxysporum and their anti-bacterial activity - Syed, Asad; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
The growing demand for semiconductor [quantum dots (Q-dots)] nanoparticles has fuelled significant research in developing strategies for their synthesis and characterization. They are extensively investigated by the chemical route; on the other hand, use of microbial sources for biosynthesis witnessed the highly stable, water dispersible nanoparticles formation. Here we report, for the first time, an efficient fungal-mediated synthesis of highly fluorescent CdTe quantum dots at ambient conditions by the fungus Fusarium oxysporum when reacted with a mixture of CdCl2 and TeCl4. Characterization of these biosynthesized nanoparticles was carried out by different techniques such as Ultraviolet-visible (UV-Vis) spectroscopy, Photoluminescence (PL), X-ray Diffraction (XRD), X-ray Photoelectron spectroscopy (XPS), Transmission Electron Microscopy (TEM) and Fourier Transformed Infrared Spectroscopy (FTIR) analysis. CdTe nanoparticles shows antibacterial activity against Gram positive and Gram negative bacteria. The fungal based fabrication provides an economical, green chemistry approach for production of highly fluorescent CdTe quantum dots. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Biosynthesis; CdTe; Fungus; Nanoparticles

Extracellular biosynthesis of water dispersible, protein capped Mn5O8 nanoparticles using the fungus fusarium oxysporum and study of their magnetic behavior - Uddin, Imran; Poddar, Pankaj (Journal of Nanoengineering and Nanomanufacturing, 2013)
Nanomaterials of different sizes, shapes and compositions are being synthesized by various chemical, physical and biological routes. The pressing need of the hour is to have a synthesis protocol which does not harm the environment in any way and is inexpensive so that the benefits can be reaped by all. In this regard, the biological synthesis routes weigh over the chemical and physical ones which are toxic and expensive respectively. The biological routes occur at ambient conditions of temperature, pressure and pH and help protect the ecosystem as these do not employ any hazardous chemicals. Moreover, the nanoparticles obtained via biological routes are naturally protein capped which prevents their agglomeration and helps them retain their shape, size and stability for several months. One such important material is manganese oxide (Mn5O8) which at the nanoscale, has found good use in catalysis and as ionic conductors in fuel cells or batteries. The compound Mn5O8 exists in mixed valences of Mn2+ and Mn4+ and has drawn attention due to its antiferromagnetic nature. Here we report extracellular biosynthesis of manganese oxide (Mn5O8 nanoparticles in the size range of 10–11 nm at room temperature by challenging the fungus Fusarium oxysporum with manganese (II) acetate tetrahydrate [(CH3CO2)2 Mn · 4H2O] as precursor. The Mn5O8 nanoparticles so formed were characterized by TEM, XRD, FTIR, XPS, and TGA. Two mixed manganese ion valencies (Mn2+ and Mn4+) of Mn5O8 have been confirmed by XPS studies and antiferromagnetic transitions by magnetic measurements.

Easy access to alpha-aryl substituted gamma-ketophosphonates: lewis acid mediated reactions of 1,3-diketones with alpha-hydroxyphosphonates and tandem regioselective C-C bond cleavage - Pallikonda, Gangaram; Chakravarty, Manab; Sahoo, Manoj Kumar (Organic & Biomolecular Chemistry, 2014)
A range of alpha-aryl substituted gamma-ketophosphonates is synthesised by Lewis acid mediated reactions of 1,3-diketones and easily accessible, inexpensive benzylic alpha-hydroxyphosphonates in an operationally simple method under solvent-free conditions without exclusion of air/moisture. A regioselective C-C bond cleavage for 1,3-diketones in a tandem fashion has also been demonstrated. Synthesis of a gamma-ketophosphonate with phenol functionality at the a-position (structural analogue of raspberry ketone, a natural product) has also been presented.

Effect of composition and pretreatment parameters on activity and stability of Cu-Al catalysts for water-gas shift reaction - Mane, Rasika B.; Jeong, Dae-Woon; Malawadkar, Atul V.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (ChemCatChem, 2014)
We investigated various Cu species responsible for highly efficient Cu-Al oxide catalyst for the water-gas shift reaction (WGSR). The formation of various Cu species was achieved by systematically varying the Cu-Al composition in the coprecipitated mixed Cu-Al oxides. The Cu-Al composition of 70:30 (Cu-Al-7) was the best for WGSR using the reformate gas composition. In addition, the Cu-Al-7 catalyst reduced under 100% H-2, was relatively stable with time on stream of 100 h, at higher gas hourly space velocity of 36201 h(-1). The structural investigation of our coprecipitated catalysts with varying Cu-Al compositions revealed the formation of nonzero oxidation state copper and metallic Cu to be essential for the observed WGSR activity. In addition, the highest activity and stability of Cu-Al-7 catalysts reduced under 100% H-2 at lower temperature was attributed to particle-size stabilization and a lower extent of Cu aggregation by Cu2O and boehmite phases, respectively, along with the formation of various Cu species during the activation protocol for 12 h. Complete CO2 selectivity without methanation was observed for all the Cu-Al compositions irrespective of their pretreatment conditions.
Keywords: aluminum; Copper; fuel cells; Hydrogen; reduction

Effect of gold nanoparticle on structure and fluidity of lipid membrane - Mhashal, Anil R.; Roy, Sudip (Plos One, 2014)
This paper deals with the effect of different size gold nanoparticles on the fluidity of lipid membrane at different regions of the bilayer. To investigate this, we have considered significantly large bilayer leaflets and incorporated only one nanoparticle each time, which was subjected to all atomistic molecular dynamics simulations. We have observed that, lipid molecules located near to the gold nanoparticle interact directly with it, which results in deformation of lipid structure and slower dynamics of lipid molecules. However, lipid molecules far away from the interaction site of the nanoparticle get perturbed, which gives rise to increase in local ordering of the lipid domains and decrease in fluidity. The bilayer thickness and area per head group in this region also get altered. Similar trend, but with different magnitude is also observed when different size nanoparticle interact with the bilayer.

Effect of method of preparation on hydrodesulphurization activity of Co- or Ni-promoted MoS2/SBA-15 catalysts - Garg, Shelu; Soni, Kapil; Prasad, V. V. D. N.; Kumar, Manoj; Bhaskar, Thallada; Gupta, J. K.; Dhar, G. Murali; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2014)
Ordered mesoporous material SBA-15 was synthesized and used as a support for the preparation of molybdenum sulphide catalysts through precipitation from homogeneous solution (PFHS) technique with the Mo content varying from 2-12 wt%. The prepared catalysts were evaluated for thiophene hydrodesulphurizadon catalytic activities at 400 degrees C. Catalysts prepared through PFHS method resulted in highly dispersed MoS2 catalysts, which were inferred from powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), low temperature oxygen chemisorptions (LTOC) and BET surface area analysis. The relationship between XPS intensity ratio, oxygen chemisorption and catalytic activities is discussed in terms of highly dispersed nano particles of MoS2 and its consequence in accommodating more promoted atoms at the edge sites.
Keywords: HDS; MoS2; PFHS method; promotional effects; SBA-15

Effect of pH on the hydrolytic kinetics of gamma-glutamyl transferase from bacillus subtilis - Balakrishna, Sharath; Prabhune, Asmita (Scientific World Journal, 2014)
The effect of pH on the steady state kinetics of gamma-glutamyl transferase (GGT) from Bacillus subtilis was examined using glutamyl-(3-carboxyl)-4-nitroanilide as the chromogenic reporter substrate. The enzyme was active in the pH range 7.0-11.0 with the optimum activity at pH 11.0. We noticed a pH dependent transformation in the nature of substrate consumption kinetics. The substrate saturation curves were hyperbolic in the pH range 7.0-9.0 but changed into sigmoid form at pH 10.0 and 11.0. Hill's coefficients were > 1. We also analysed the effect of pH on the structure of the enzyme. The circular dichroism spectra of the enzyme sample at pH 9.0 and 11.0 were coincidental in both far and near UV regions indicating conservation of the secondary and tertiary structures, respectively. Themolecular weight of the enzyme sample was the same in both pH 7.0 and 11.0 indicating conservation of the quaternary structure. These results show that the kinetic transformation does not involve significant conformational changes. Cooperative binding of multiple substrate molecules may not be the basis for the sigmoid kinetics as only one substrate binding site has been noticed in the reported crystal structures of B. subtilis GGT.

Effect of preparation parameters on characterization and activity of Co3O4 catalyst in liquid phase oxidation of lignin model substrates - Mate, Vivek R.; Jha, Ajay; Joshi, U. D.; Patil, K. R.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2014)
The nano structured spinel cobalt oxide (Co3O4) was prepared via simple co-precipitation method and its catalytic activity was evaluated for the liquid phase aerobic oxidation of lignin sub structure compounds such as veratryl alcohol. Catalyst preparation parameters influenced its morphology eventually affecting its oxidation activity. Thus, nano rod shaped CO3O4 catalyst showed 75% and 38% conversion of veratryl alcohol with complete selectivity to veratryl aldehyde in toluene and water, respectively, under base free condition. The influence of reaction conditions, such as temperature, oxygen pressure and catalyst loading was studied to obtain the optimum product yield and selectivity to the desired product. Furthermore, oxidation of various sub-structures of lignin model compounds was also studied over the same catalyst which was found to be in the following order: secondary alcohol >di-substituted > tri-substituted > monosubstituted > non-substitution. The stability of the catalyst was confirmed by its successful recycle for three times. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Coniferyl alcohol; Nano Co3O4; Sinapyl alcohol; TPR; Veratryl alcohol

Effect of pt incorporation in LaBO3 (B = Mn, Fe, Co) perovskites on water gas shift activity - Rajesh, Thattarathody; Upadhyay, Anuj; Sinha, Anil K.; Deb, Sudip K.; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2014)
Pt incorporated perovskites LaBO3 (B = Mn, Co, Fe) were synthesised and characterised to understand the charge state of Pt in these materials. At the temperature range used in this study, Pt could be stabilised in ionic form in Co and Fe perovskites but not in LaMnO3. Consequent to incorporation of Pt in +2 and +4 oxidation states, reduction in B site ion charge state occurred, enhancing oxygen vacancies. Pt doped Co and Fe perovskites showed high activity for CO conversion under water gas shift conditions but the activity characteristics were found to be different for the two catalysts; LaCo1-xPtxO3-delta showed methanation whereas the Fe counterpart was active in water gas shift reaction. It was also observed that methanation could be decreased and water gas shift enhanced in case of Pt doped Co perovskite when compared to Pt impregnated perovskite or mixed oxides. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Methanation; Perovskites; Pt doping; Water gas shift reaction; XANES

Effect of self-assembly on triiodide diffusion in water based polymer gel electrolytes: an application in dye solar cell - Soni, S. S.; Fadadu, K. B.; Vekariya, R. L.; Debgupta, Joyashish; Patel, K. D.; Gibaud, A.; Aswal, Vinod K. (Journal of Colloid and Interface Science, 2014)
The preparation of ordered polymer gels from the amphiphilic block copolymers, Pluronic (R) F77, P123 and polyethylene glycol in the presence of ionic liquid, iodine and organic additives is presented. At 35%(w/w) concentration these copolymers (F77 and P123) self-assembled into cubic liquid crystalline phase in aqueous solution and characterized by using SAXS and AFM measurements. The effects of micellar aggregation formed by polymers on the ionic transport and triiodide diffusion have been studied by electro-chemistry and SANS experiments. The ionic migration or triiodide diffusion through these polymer gels is found to be affected by the PEO/PPO content in the polymer backbone. These gels were successfully employed as an electrolyte in a dye sensitized solar cell. A remarkable solar to electricity conversion efficiency and good stability was obtained using Pluronic (R) F77 based gel, which is attributed to its thermoreversible sol to gel transition. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Amphiphilic block copolymer; Dye solar cell; Micellar nanochannels; SANS; SAXS; Self-assembly; Water based gel electrolytes

Effect of silicon doping on the reactivity and catalytic activity of gold clusters - Manzoor, Dar; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2014)
Doping is known to be an excellent and simple way of catalyst design. Although notable progress has been made in understanding the reactivity and catalytic activity of gas-phase and supported gold clusters, very few studies have been carried out on the doped gold clusters. In the present work, we have carried out density functional theory calculations to investigate the effect of silicon doping on the reactivity and catalytic activity of gold nanoclusters. The present work particularly focuses on the adsorption and activation of molecular oxygen on the pristine and silicon-doped gold clusters. The results confirm that the silicon-doped Au7Si cluster shows considerable binding and activation of the O-2 molecule in comparison to the pristine Au-8 cluster as reflected in the relevant geometrical parameters (O-O and Au-O bond lengths) and O-O stretching frequency. However, silicon doping has no contrasting effect on the reactivity and catalytic activity of the Au-7 cluster. In addition to the stronger binding and activation of the O-2 molecule, the doped Au7Si cluster leads to a significant reduction in the activation barrier (0.57 eV) for the environmentally important CO oxidation reaction in contrast to the catalytically inactive pristine Au-8 cluster (1.22 eV). Thus, our results highlight the critical role of doping foreign impurities for future endeavors in the field of gold nanocatalysis.

Effect of SnO2/Al2O3 ratio of Si-based MFI on its acidity and hydrophobicity: application in selective hydroxyalkylation of p-cresol - Garade, Ajit C.; Malwadkar, A. V.; Niphadkar, P. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Rode, C. V. (Catalysis Communications, 2014)
Silica based MR type molecular sieves with various SnO2/Al2O3 ratios were synthesized from gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23(TPA)(2)O:35H(2)O where 0 <= x <= 0.02 and 0 <= y <= 0.01. Recyclable, Al-free Sn-MFI catalyst showed 31% conversion of formaldehyde with 100% selectivity to 2,2'-methylenebis(4-methylphenol) in hydroxyalkylation of p-cresol with formaldehyde on account of moderate acidity and higher hydrophobicity. (C) 2013 Elsevier B.A. All rights reserved.
Keywords: Al-27 MAS NMR; Hydroxyalkylation; Molecular sieves; p-Cresol; Stannosilicate

Effect of the branching pattern of hydrophobic dendrons on the core structure of linear-dendritic copolymer micelles - Kalva, Nagendra; Aswal, Vinod K.; Ambade, Ashootosh V. (Macromolecular Chemistry and Physics, 2014)
Hydrophobic dendrons based on different branching patterns, viz. 3,5-di- and 3,4,5-trisubstituted phenyl rings, consist of the same backbone but exhibit different sizes, shapes, and hydrophobic densities. These dendrons are attached to poly(ethylene glycol) and the core properties of the copolymer micelles are investigated in tetrahydrofuran (THF)/water mixtures by neutron scattering. Two polymers with intermediate hydrophobicity are studied further with variations in the solvent composition and the temperature. The aggregation numbers for 3,4,5-based dendron copolymers are lower, with more THF molecules of solvation compared with the 3,5-based dendron copolymer, the difference being greater at higher generations due to different molecular shapes. The micellar core size increases in small steps with dendron size so that dye encapsulation is tuned.
Keywords: diblock copolymers; linear-dendritic copolymers; micelles; neutron scattering; structure-property relations

Effects of method of preparation on catalytic activity of Co-Zn double-metal cyanide catalysts for copolymerization of CO2 and epoxide - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2014)
Co-Zn double-metal cyanide (DMC) complexes are well-known catalysts for ring-opening polymerization of epoxides and co-polymerization of CO2 and epoxides. This work provides an insight on structure-activity relationship of DMC for poly(cyclohexene carbonate) synthesis. Seven samples of DMC were prepared by different methods and mode of reagent addition. Highly active catalyst could be synthesized even without using a co-complexing agent. CO2 adsorption studies revealed that higher the guest-host interaction higher would be the catalytic activity. High density and strength of Lewis acid sites, moderate crystallinity, low crystal symmetry (rhombohedral/monoclinic), Cl- ions and coordinated tert.-butanol (complexing agent) control the catalytic activity for polycarbonates. Chloride in the structure avoided induction period by increasing acidity of the catalyst and thereby, improving the guest-host interactions. Polycarbonates with CO2 incorporation as high as 86 mol%, average molecular weight of 20900 and polydispersity index of 1.8 were prepared at complete conversion of cyclohexene oxide. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; CO2 utilization; Copolymerization of CO2 and cyclohexene oxide; Double-metal cyanide; Polycarbonate; Structure-activity relationship

Efficient and mild method for preparation of allylic amines from aziridine-2-alcohols using PPh3/I-2/imidazole - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N. (Tetrahedron Letters, 2014)
Allylic amines are synthesized in good to excellent yields by treatment of aziridine-2-alcohols with PPh3/I-2/imidazole in THF as solvent under mild conditions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chiral allylic amine; Chiral aziridine-2-alcohols; PPh3/iodine/imidazole; Reductive elimination

Efficient conversion of cellulose to levulinic acid by hydrothermal treatment using zirconium dioxide as a recyclable solid acid catalyst - Joshi, Sunil S.; Zodge, Amit D.; Pandare, Kiran V.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2014)
Conversion of cellulose into platform chemicals is essential for sustainable development of the chemical industry. With this aim, single step hydrothermal conversion of cellulose to industrially important levulinic acid using zirconium dioxide as a catalyst has been investigated. A remarkably high yield (53.9 mol %) of levulinic acid with excellent accountability and total conversion of cellulose has been achieved at 180 degrees C reaction temperature and reaction time of 3 h with 2 wt % of catalyst and 2 g of cellulose. The major products identified were levulinic acid (LA), formic acid (FA), 5-hydroxymethylfurfural (5-HMF), furfural, and humins. Formation of humins during cellulose hydrolysis and dehydration was observed and is also confirmed by NMR and FTIR analysis. The effect of various reaction parameters such as temperature, time, substrate concentration, and catalyst loading on conversion and selectivity has been studied. The catalyst has been regenerated and recycled several times without any loss of activity and selectivity.

Efficient synthesis of 1,5-benzodiazepines catalyzed by bismuth nitrate - Bhattacharya, Asish K.; Dange, Santoshkumar S.; Polanki, Innaiah K.; Chand, Hemender R. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2014)
An efficient method has been developed for the synthesis of biologically active 1,5-benzodiazepines in one-pot by reacting o-phenylenediamine and ketones catalyzed by bismuth nitrate pentahydrate at room temperature or under microwave irradiation.
Keywords: 1; 5-benzodiazepines; bismuth nitrate pentahydrate; o-Phenylenediamine; synthetic methods

Efficient synthesis of 9-aryldihydrophenanthrenes by a cascade reaction involving arynes and styrenes - Bhojgude, Sachin Suresh; Bhunia, Anup; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
A mild, general, and transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes is reported. The aryne generated by the fluoride-induced,1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes an efficient cascade reaction initiated by the Diels-Alder reaction with the differently substituted styrenes leading to the formation of 9-aryl-9,10-dihydrophenanthrene derivatives in moderate to good yields.

Efficient synthesis of glycerol carbonate/glycidol using 1,8-diazabicyclo [5.4.0] undec-7-ene (DBU) based ionic liquids as catalyst - Munshi, Mudassir K.; Biradar, Pradeep S.; Gade, Swapna M.; Rane, Vilas H.; Kelkar, Ashutosh A. (RSC Advances, 2014)
Transesterification of dimethyl carbonate with glycerol to glycerol carbonate has been catalyzed efficiently using basic ionic liquids as catalysts. Activity of all the ILs tested is very high and the best result (96% conversion with 82% selectivity to glycerol carbonate and 18% selectivity to glycidol) was obtained using IL1 as catalyst. The effect of catalyst loading has significant influence on the selectivity pattern. The higher activity of the ionic liquid is explained with a plausible mechanism based on the co-operative effect of both cation and anion.

Efficient synthesis of O-aryloxime ethers by copper fiuorapatite catalyzed cross-coupling of aryloximes with arylboronic acids - Mulla, Shafeek Abdul Rashid; Chavan, Santosh S.; Inamdar, Suleman M.; Pathari, Mohsinkhan Y.; Shaikh, Taufeekaslam M. Y. (Tetrahedron Letters, 2014)
A novel, highly efficient, and mild protocol has been developed for the synthesis of O-aryloxime ethers in good to excellent yields at ambient reaction conditions. This is the first report in which =N-O-Ar linkage was achieved with ecofriendly, recyclable, heterogeneous copper fluorapatite (CuFAP) catalyst via C-O cross coupling of aryloxime with arylboronic acid in the presence of Cs2CO3 as base and methanol as solvent. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Arylboronic acid; Aryloxime; Copper fluorapatite; O-Aryloxime ethers

Efforts towards the synthesis of microsporin B: ready access to both the enantiomers of the key amino acid fragment - Swaroop, Pandrangi Siva; Tripathy, Sibanarayan; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (Tetrahedron Letters, 2014)
Both the isomers methyl-(2S,8R)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate and methyl-(2S,8S)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate of an unusual amino acid residue and the key fragment of microsporin B are prepared. The key steps include cross metathesis and enzymatic kinetic resolution. In addition, a linear tetrapeptide with desired components towards total synthesis is also reported. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cross metathesis; Enzymatic resolution; HDAC inhibitor; Microsporin; Tetrapeptide

Electrochemical preparation of vertically aligned, hollow CdSe nanotubes and their p-n junction hybrids with electrodeposited Cu2O - Debgupta, Joyashish; Devarapalli, Rami Reddy; Rahman, Shakeelur; Shelke, Manjusha V.; Pillai, Vijayamohanan K. (Nanoscale, 2014)
Vertically aligned, hollow nanotubes of CdSe are grown on fluorine doped tin oxide (FTO) coated glass substrates by ZnO nanowire template-assisted electrodeposition technique, followed by selective removal of the ZnO core using NH4OH. A detailed mechanism of nucleation and anisotropic growth kinetics of nanotubes have been studied by a combination of characterization tools such as chronoamperometry, SEM and TEM. Interestingly, ``as grown'' CdSe nanotubes (CdSe NTs) on FTO coated glass plates behave as n-type semiconductors exhibiting an excellent photo-response (with a generated photocurrent density value of similar to 470 mu A cm(-2)) white in contact with p-type Cu2O (p-type semiconductor, grown separately on FTO plates) because of the formation of a n-p heterojunction (type II). The observed photoresponse is 3 times higher than that of a similar device prepared with electrodeposited CdSe films (not nanotubes) and Cu2P on FTO. This has been attributed to the hollow 1-D nature of CdSe NTs, which provides enhanced inner and outer surface areas for better absorption of light and also assists faster transport of photogenerated charge carriers.

Electrochemically grown nanoporous MnO2 nanowalls on a porous carbon substrate with enhanced capacitance through faster ionic and electrical mobility - Anothumakkool, Bihag; Kurungot, Sreekumar (Chemical Communications, 2014)
We report the deposition of uniform porous MnO2 nanowalls on a conducting carbon fiber substrate using a simple electrochemical method, which produces ordered nano-channels demarcated by the MnO2 walls for easy ion transport and a continuous electron path created by the carbon backbone. The system achieves a specific capacitance of 1149 F g(-1) and retains 565 F g(-1) even at dragging conditions as high as 100 A g(-1).

Electrodeposited polyethylenedioxythiophene with infiltrated gel electrolyte interface: a close contest of an all-solid-state supercapacitor with its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Badiger, Manohar V.; Kurungot, Sreekumar (Nanoscale, 2014)
We report the design of an all-solid-state supercapacitor, which has charge storage characteristics closely matching that of its liquid-state counterpart even under extreme temperature and humidity conditions. The prototype is made by electro-depositing polyethylenedioxythiophene (PEDOT) onto the individual carbon fibers of a porous carbon substrate followed by intercalating the matrix with polyvinyl alcohol-sulphuric acid (PVA-H2SO4) gel electrolyte. The electrodeposited layer of PEDOT maintained a flower-like growth pattern along the threads of each carbon fiber. This morphology and the alignment of PEDOT led to an enhanced surface area and electrical conductivity, and the pores in the system enabled effective intercalation of the polymer-gel electrolyte. Thus, the established electrode-electrolyte interface nearly mimics that of its counterpart based on the liquid electrolyte. Consequently, the solid device attained very low internal resistance (1.1 Omega cm(-2)) and a high specific capacitance (181 F g(-1)) for PEDOT at a discharge current density of 0.5 A g(-1). Even with a high areal capacitance of 836 mF cm(-2) and volumetric capacitance of 28 F cm(-3), the solid device retained a mass-specific capacitance of 111 F g(-1) for PEDOT. This is in close agreement with the value displayed by the corresponding liquid-state system (112 F g(-1)), which was fabricated by replacing the gel electrolyte with 0.5 M H2SO4. The device also showed excellent charge-discharge stability for 12 000 cycles at 5 A g(-1). The performance of the device was consistent even under wide-ranging humidity (30-80%) and temperature (-10 to 80 degrees C) conditions. Finally, a device fabricated by increasing the electrode area four times was used to light an LED, which validated the scalability of the process.

Electrokinetic properties of PMAA functionalized NiFe2O4 nanoparticles synthesized by thermal plasma route - Bhosale, Shivaji V.; Mhaske, Pravin; Kanhe, N.; Navale, A. B.; Bhoraskar, S. V.; Mathe, V. L.; Bhatt, S. K. (Solid State Physics: Proceedings of the 58th Dae Solid State Physics Symposium 2013, PTS A & B, 2014)
The magnetic nickel ferrite (NiFe2O4) nanoparticles with an average size of 30nm were synthesised by Transferred arc DC Thermal Plasma route. The synthesized nickel ferrite nanoparticles were characterized by TEM and FTIR techniques. The synthesized nickel ferrite nanoparticles were further functionalized with PMAA (polymethacrylic acid) by self emulsion polymerization method and subsequently were characterized by FTIR and Zeta Analyzer. The variation of zeta potential with pH was systematically studied for both PMAA functionalized (PNFO) and uncoated nickel ferrite nanoparticles (NFO). The IEP (isoelectric points) for PNFO and NFO was determined from the graph of zeta potential vs pH. It was observed that the IEP for NFO was at 7.20 and for PNFO it was 2.52. The decrease in IEP of PNFO was attributed to the COOH functional group of PMAA.
Keywords: IEP; NiFe2O4; PMAA; Thermal plasma; Zeta potential

Electronic structure-sunlight driven water splitting activity correlation of (Zn1-yGay)(O1-zNz) - Rajaambal, Sivaraman; Yadav, A. K.; Jha, Shambhu Nath; Bhattacharyya, Dibyendu; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2014)
(Zn1-yGay)(O1-zNz) (y <= 0.10; z <= 0.15) solid solutions have been investigated for their electronic structure and visible light photocatalytic activity, and a correlation was found between them. (Zn1-yGay)(O1-zNz) with ZnO as the major component have been synthesized by a solution combustion method in 10 minutes using simple raw materials. The local structures of Zn K edge and Ga K edge, and changes in the chemical environment with the incorporation of Ga and N in ZnO were determined by EXAFS study. EXAFS and XRD results suggested the dissolution of GaN in the ZnO lattice. The homogeneity of the solid solution was demonstrated from HRTEM studies. Photoluminescence studies revealed the creation of a new band at the top of the ZnO valence band (VB), and thus the broadening of the VB of (Zn1-yGay)(O1-zNz) or a decrease in the band gap was attributed to the origin of visible light absorption. UV-Vis spectral studies showed light absorption up to 550 nm, which directly supports the VB broadening. Predominant oxygen vacancies and high photocorrosion observed for ZnO were fully suppressed for (Zn1-yGay)(O1-zNz) , indicating the minimization of defects, and thus more sustainability under irradiation conditions. The bare solid solution exhibited reasonable and promising activity for solar hydrogen evolution and photoelectrochemical current generation at 0 V. The present work explained factors such as the preparation method, single phase structure with the stabilization of integral parts, homogeneity in the structure, compensation of oxygen vacancies, and suppression of the density of recombination centres that play a pivotal role in realizing solar energy harvesting.

Electronic transition dipole moment: a semi-biorthogonal approach within valence universal coupled cluster framework - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2014)
Electronic dipole strengths (square of transition moments) and oscillator strengths are evaluated for various transitions, arising from the ground state to a few valence excited states. Parallel to two other methods of calculating the dipole strength within the Fock-space multireference coupled cluster framework, a new semi-biorthogonal approach is formulated and implemented in this article. This semi-biorthogonal approach can evaluate dipole strengths at a lower computational effort than the biorthogonal approach without compromising on the accuracy. This new method is compared and tested against the previously developed expectation value and biorthogonal approach for various molecular transitions. (C) 2014 Wiley Periodicals, Inc.
Keywords: electronic transition dipole; Fock-space; oscillator strength; semi-biorthogonal expectation value

Electronically and catalytically functional carbon cloth as a permeable and flexible counter electrode for dye sensitized solar cell - Tathavadekar, Mukta; Biswal, Mandakini; Agarkar, Shruti A.; Giribabu, Lingamallu; Ogale, Satishchandra (Electrochimica Acta, 2014)
In this work we demonstrate that a conducting carbon cloth obtained by one-step pyrolysis of easily available cellulose fabric competes favorably with the commonly employed expensive platinum/FTO system as a counter electrode for dye sensitized solar cell (DSSC). In view of the low carbonization temperature (1000 degrees C) which forbids full graphitization, the nature of carbon in this case is represented by topologically randomly assembled nanoscale graphene units (turbostratic carbon). This morphology has high density of edge states and oxygen containing surface groups rendering multitude of catalytic sites for the reduction of I-3(-). Moreover the cloth is permeable to the dye and/or liquid electrolyte and its absorption properties also help retain the electrolyte. A fairly high efficiency of 5.8% is achieved using such cloth as a counter electrode as against 7% with the conventional Pt/FTO system. Moreover, the permeable property of the cloth eliminates a complete step of drilling hard TCO substrates for final dispensing of electrolyte into the device and the sealing process is also facile. In fact even the dye can be dispensed through the cloth. Finally, the flexibility of the carbon cloth can adapt easily to flexible/wearable DSSC designs. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: conducting carbon cloth; counter electrode; DSSC; without drilling

Electrostatics determine vibrational frequency shifts in hydrogen bonded complexes - Dey, Arghya; Mondal, Sohidul Islam; Sen, Saumik; Ghosh, Debashree; Patwari, G. Naresh (Physical Chemistry Chemical Physics, 2014)
The red-shifts in the acetylenic C-H stretching vibration of C-H center dot center dot center dot X (X = O, N) hydrogen-bonded complexes increase with an increase in the basicity of the Lewis base. Analysis of various components of stabilization energy suggests that the observed red-shifts are correlated with the electrostatic component of the stabilization energy, while the dispersion modulates the stabilization energy.

Elements of managing transfer of technology from laboratory to industry: technology transfer management (TTM) - Saraf, C. U. (Journal of Scientific & Industrial Research, 2014)
This research paper throws light on problems faced by small, medium and large scale. chemical industries in managing the transfer of technology from laboratory to industry. There are several reasons that may increase cost and time overruns and thus causes inordinate delay in completing transfer of technology in both private and public sector projects. This paper also suggests solutions to eliminate the problems and underlines the importance of involving local and national R & D institutes in effectively ``Managing Transfer of Chemical Technology'' into commercial practice. This communication presents ``a13 steps model'' developed by the researcher for efficient, smooth and effective transfer of technology. The findings have been duly supported by data interpretations, with appropriate examples of technology transfer and literature published. The primary data collection technique used is structured questionnaire as well as in-depth interviews of entrepreneurs, heads of R and D units and staff involved in technology transfer in chemical industries in and around Pane. The facts are also supported by the secondary analysis of literature published in related area. The basic objective of this communication is to communicate Technology Transfer Process Model (TTP) for effective commercialization of technology.
Keywords: Industrial Technology Commercialization; Multi Disciplinary Man Power Team (MDMPT); Technology Management; Technology Transfer; Technology Transfer Offices (TTO); Technology Transfer Process Model (TTP)

Elucidation of ionic interactions in the protic ionic liquid solutions by isothermal titration calorimetry - Rai, Gitanjali; Kumar, Anil (Journal of Physical Chemistry B, 2014)
The strong hydrogen-bonded network noted in protic ionic liquids (PILs) may lead to stronger interactions of the ionic entities of PILs with solvents (water, methanol, ethylene glycol, climethylsulfoxide (DMSO), N,N'-dimethylformamide (DMF)) as compared with those of aprotic ionic liquids (APILs). The PILs used in this work are 1-methylimidazolium tetrafluoroborate, 2-methylpyridinium tetrafluoroborate, and N-methylpyrrolodinium tetrafluoroborate in comparison to 1-butyl-3-methylimidazolium tetrafluoroborate, which is classified as an APIL. In this work, the excess partial molar enthalpy, H-IL(E) obtained from isothermal calorimetric titrations at 298.15 K is used to probe the nature of interactions of the PIL cations with solvent molecules against those present in APIL solvent systems. This work also reports interesting flip-flopping in the thermal behavior of these PIL-solvent systems depending upon the structure of the cationic ring of a PIL. In some cases, these flip-flops are the specific fingerprints for specific PILs in a common solvent environment. The excess partial molar enthalpy at infinite dilution, H-IL(E,infinity), of these PILs bears a critical dependence on the solvent properties. An analysis of relative apparent molar enthalpies, phi(L), of the PIL solutions by the ion interaction model of Pitzer yields important information on ionic interactions of these systems.

Employing arynes in transition-metal-free, N-heterocycles initiated multicomponent reactions - Bhunia, Anup; Biju, Akkattu T. (Synlett, 2014)
Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and various carbonyl compounds have been reported. With (iso)quinoline as the nucleophile and carbonyl compounds, such as aldehydes, ketones, and N-substituted isatins as electrophiles, the reaction afforded oxazino (iso)quinoline derivatives and the reaction proceeded via 1,4-dipolar intermediates. Interestingly, when the nucleophilic trigger used is pyridine, the reaction furnished indolin-2-one derivatives, and it is probable that the reaction proceeds via a pyridylidene intermediate.
Keywords: arynes - multicomponent reaction - oxindoles - pyridines - quinolines

Emulsion ionic liquid membranes (EILMs) for removal of Pb(II) from aqueous solutions - Lende, Avinash B.; Dinker, Manish K.; Bhosale, Vikas K.; Kamble, Sanjay P.; Meshram, Pawan D.; Kulkarni, Prashant S. (RSC Advances, 2014)
Ionic liquids (ILs) are playing increasingly important roles in the membrane separation processes. The present manuscript discusses the removal of Pb(II) ions from aqueous solution using an emulsion ionic liquid membrane (EILM) process. Initially, the emulsion liquid membrane (ELM) was prepared by stirring strip phase (sulphuric acid) and organic phase (surfactant: span 80, extractant: D2EHPA, diluent: hexane) together under high speed agitation. Note that, the parameters of the ELM process such as emulsification speed, pH of the feed phase, treat ratio, extractant and surfactant concentrations were studied for the maximum removal of Pb(II) ions. The role of IL was explored by adding hydrophobic IL, octylmethylimidazole hexafluorophosphine ([OMIM][PF6]), in the organic phase. The performance of ELM with and without IL was compared on the basis of stability, enrichment factor and the removal efficiency for Pb(II). The results showed that the percentage of Pb(II) extraction was complete by the emulsion membrane with IL (EILM) in comparison to the 97% achieved by neat ELM. Further, the stability and the enrichment factor of the EILM were found to be 2-3 times greater than that of the ELM. The FT-IR spectroscopic analysis revealed that bond interactions between IL and membrane phase components avoided the coalescence of internal phase droplets and enhanced the emulsion stability. The results obtained in this work support the use of the IL [OMIM][PF6] as both a stabilizer and carrier for the overall improvement of the ELM process.

Enantioselective heterogeneous bronsted acid catalysis - Mutyala, Anil Kumar; Patil, Nitin T. (Organic Chemistry Frontiers, 2014)
This highlight describes the synthesis and catalytic activities of heterogeneous chiral Bronsted acid catalysts. The heterogeneous catalysts are stable, easily separable from the reaction mixture and can be used multiple times without any loss of activity. As a remarkable particularity, the use of heterogeneous catalyst systems has been exemplified for designing continuous flow reactors.

Engineering of the tat pathway and chaperons - Ghosh, Deepanjan; Ramasamy, Sureshkumar (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Protein transport; Signal sequence; Tat Pathway

Engineering reactors for catalytic reactions - Ranade, Vivek V. (Journal of Chemical Sciences, 2014)
Catalytic reactions are ubiquitous in chemical and allied industries. A homogeneous or heterogeneous catalyst which provides an alternative route of reaction with lower activation energy and better control on selectivity can make substantial impact on process viability and economics. Extensive studies have been conducted to establish sound basis for design and engineering of reactors for practising such catalytic reactions and for realizing improvements in reactor performance. In this article, application of recent (and not so recent) developments in engineering reactors for catalytic reactions is discussed. Some examples where performance enhancement was realized by catalyst design, appropriate choice of reactor, better injection and dispersion strategies and recent advances in process intensification/ multifunctional reactors are discussed to illustrate the approach.
Keywords: Catalyst; effectiveness; engineering; hydrodynamics; reactors

Enhanced capacitance retention in a supercapacitor made of carbon from sugarcane bagasse by hydrothermal pretreatment - Wahid, Malik; Puthusseri, Dhanya; Phase, Deodatta; Ogale, Satishchandra (Energy & Fuels, 2014)
A unique morphology-controlling protocol involving hydrothermal preprocessing before pyrolysis is presented to convert cellulosic waste in the form of sugarcane bagasse into three-dimensional (3D) interconnected, conducting, and high surface area carbon nanochannels. The large buffer spaces in such a porous carbon sample yield impressive electrochemical capacitance (C-sp) of 280 F/g at a current density of 1 A/g (and 275 F/g at 5 mV/s), with 72% retention even at a very high current density of 20 A/g. In contrast, the non-hydrothermally treated sample exhibits a C-sp value of 180 F/g at 1 A/g and only 52% retention at 20 A/g. The much better performance of the hydrothermally preprocessed bagasse-derived carbon (BHAC) can be ascribed to the solvent retention inside the buffer spaces created, negating the diffusional limitations of pore inaccessibility at higher scan rates. The BHAC has a high surface area of 1260 m(2)/g with a fairly good (11 wt %) concentration of oxygen functionality. The material renders a good energy density of Wh/kg at a power density of 3.5 kW/kg and shows good cyclability of 90% after 1000 charge/discharge cycles.

Enhanced catalytic activity of polyethylenedioxythiophene towards tri-iodide reduction in DSSCs via 1-dimensional alignment using hollow carbon nanofibers - Anothumakkool, Bihag; Game, Onkar S.; Bhange, Siddheshwar N.; Kumari, Tanya; Ogale, Satishchandra B.; Kurungot, Sreekumar (Nanoscale, 2014)
Here, we report a highly conducting 1-dimensionally (1-D) aligned polyethylenedioxythiophene (PEDOT) along the inner and outer surfaces of a hollow carbon nanofiber (CNF) and its application as a counter electrode in a dye sensitized solar cell (DSSC). The hybrid material (CP-25) displays a conversion efficiency of 7.16% compared to 7.30% for the standard Pt counter electrode, 4.48% for bulk PEDOT and 5.56% for CNF. The enhanced conversion efficiency of CP-25 is attributed to the accomplishment of high conductivity and surface area of PEDOT through the 1-D alignment compared to its bulk counterpart. Reduced charge transfer resistance and high conductivity of CP-25 could be proven by cyclic voltammetry, impedance analysis and Tafel experiments. Further, through a long-term stability test involving efficiency profiling for 20 days, it is observed that CP-25 possesses excellent durability compared to the bulk PEDOT.

Enhanced field emission properties of doped graphene nanosheets with layered SnS2 - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Applied Physics Letters, 2014)
We report here our experimental investigations on p-doped graphene using tin sulfide (SnS2), which shows enhanced field emission properties. The turn on field required to draw an emission current density of 1 mu A/cm(2) is significantly low (almost half the value) for the SnS2/reduced graphene oxide (RGO) nanocomposite (2.65 V/mu m) compared to pristine SnS2 (4.8 V/mu m) nanosheets. The field enhancement factor beta (similar to 3200 for the SnS2 and similar to 3700 for SnS2/RGO composite) was calculated from Fowler-Nordheim (F-N) plots, which indicates that the emission is from the nanometric geometry of the emitter. The field emission current versus time plot shows overall good emission stability for the SnS2/RGO emitter. The magnitude of work function of SnS2 and a SnS2/graphene composite has been calculated from first principles density functional theory (DFT) and is found to be 6.89 eV and 5.42 eV, respectively. The DFT calculations clearly reveal that the enhanced field emission properties of SnS2/RGO are due to a substantial lowering of the work function of SnS2 when supported by graphene, which is in response to p-type doping of graphene. (C) 2014 AIP Publishing LLC.

Enhanced interaction of molecular oxygen with amino acid complexes of silver and gold clusters - Manzoor, Dar; Pal, Sourav (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
Density functional theory calculations have been carried out to study the effect of amino acid adsorption on the reactivity of silver and gold clusters with molecular oxygen. It is found that the amino acids glycine and alanine form stable complexes with both Ag-4 and Au-4 clusters. However, the extent of interaction is more in the case of the Au-4 cluster, as reflected from the increase in binding energy in the amino acid Au-4 complexes. Our results confirm that the adsorption of amino acids glycine and alanine enhances the reactivity of Ag-4 and Au-4 clusters towards O-2 molecule. The enhanced reactivity of O-2 molecule towards the amino acid metal cluster complexes is manifested by an increase in the O-2 binding energy and a decrease in the M-O (M = Ag, Au) bond length. Moreover, it is found that the co-adsorption of amino acids and O-2 molecule on the Ag-4 and Au-4 clusters is cooperative.
Keywords: Amino acid complexes; Density functional calculations; Gold clusters; Metal clusters; Silver clusters; Theoretical chemistry

Enhanced kinetics for the clathrate process in a fixed bed reactor in the presence of liquid promoters for pre-combustion carbon dioxide capture - Babu, Ponnivalavan; Ho, Chie Yin; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
In this work, we present enhanced kinetics of hydrate formation for the clathrate process in the presence of two liquid promoters namely THF (tetrahydrofuran) and TBAB (tetra-n-butyl ammonium bromide) in a FBR (fixed bed reactor) for pre-combustion capture of CO2. Silica sand was used as a medium to capture CO2 from CO2/H-2 gas mixture by hydrate crystallisation. Experiments were performed at different temperatures (274.2 K and 279.2 K) and 6.0 MPa to determine the total gas uptake, induction time and rate of hydrate formation. The observed trends indicated that higher driving force resulted in higher gas consumption and significantly reduced induction time. For the same driving force, higher gas consumption and shorter induction time was achieved by THF as compared to TBAB. 5.53 mol% THF attained higher gas consumption than 1.0 mol% THF whereas 3.0 mol% TBAB attained lower gas consumption than 0.3 mol% TBAB. A highest gas uptake of 51.95 (+/- 5.183) mmol of gas/mol of water and a highest rate of 51.21(+/- 8.91) mol.min(-1).m(-3) were obtained for 5.53 mol% THF at 6.0 MPa and 279.2 K. Overall, this study indicated better hydrate formation kinetics with the use of THF in an FBR configuration for CO2 capture from a fuel gas mixture. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Fixed bed reactor; Gas hydrates; Pre-combustion capture; Promoters

Enhanced mineralization of gaseous organic pollutant by photo-oxidation using Au-Doped TiO2/MCM-41 - Tangale, Nilesh P.; Belhekar, Anuja A.; Kale, Kishor B.; Awate, Shobhana V. (Water Air and Soil Pollution, 2014)
The synthesis, characterization, and photocatalytic evaluation of titania-loaded MCM-41 with and without Au doping are reported in the present study. The samples were characterized by powder XRD, TEM, low temperature N-2 adsorption/desorption, UV-Vis, and FTIR. UV-induced vapor-phase photo-oxidation of acetone was used as a probe reaction to study the role of Au in mineralization of volatile organic compounds (VOCs), viz. acetone at different concentrations. The doping of Au in titania-loaded MCM-41 resulted in the decrease of BET surface area, total pore volume, and average pore size. UV-Vis diffuse reflectance spectra of Au-doped titania-loaded MCM-41 showed the red shift in their absorption bands compared to titania-loaded MCM-41. The activity of mineralization of acetone by photocatalysis for 2 % Au-doped titania-loaded MCM-41 was found to be similar to 1.6 times higher than titania-loaded MCM-41. The presence of cocatalytic nanosized gold might be responsible for their enhanced activity on account of the delayed recombination of electron/hole pair. Although, almost complete mineralization of acetone was observed irrespective of the initial concentration of acetone in air (up to 3.72 mol%) by all the catalysts, 2 wt.% Au-doped titania-loaded MCM-41 has shown the most enhanced activity.
Keywords: Acetone; Doping; Gold; Mineralization of VOCs; Photo-oxidation; TiO2/MCM-41

Enhanced photoluminescence and photoactivity of plasmon sensitized nSiNWs/TiO2 heterostructures - Yenchalwar, Sandeep G.; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V. (Physical Chemistry Chemical Physics, 2014)
A light sensitive wide band gap radial heterojunction between TiO2 and nSiNWs sensitized by gold nanoparticles is reported. The surface plasmon of AuNPs influences the optical and photocurrent properties of the heterojunction considerably. Improvement in the band gap emission of TiO2 has been found at the expense of defect radiation. Excitation of AuNPs deposited on nSiNWs/TiO2 by light irradiation shows a wavelength-dependent photocurrent due to the increased photoactivity of the heterojunction.

Enhancement in the field emission behavior of graphene in N-2/O-2 high vacuum ambience - Suryawanshi, S. R.; Kolhe, Pankaj S.; Gavhane, D. S.; Patil, S. S.; Chavan, P. G.; More, Mahendra A.; Late, Dattatray J. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Herein we report, pressure dependent field emission (FE) behaviour of a few-layer graphene emitter. Gas dependent FE properties have been investigated in ultra high vacuum (UHV), as well as in N-2 and O-2 ambience at base pressure similar to 1x10(-6) torr. Interestingly, the graphene emitter when operated in N-2/O-2 ambience exhibits lower turn-on field and higher emission current density, as compared to the UHV conditions. The emission current stability investigated at preset value of similar to 1 mu A over the period of more than 2 hrs is found better in the N2 ambience and is characterized by fewer fluctuations, in contrast to the behaviour in the O-2 ambience. The observed enhanced electron emission behavior in N-2/O-2 ambience is attributed to modulation of the work function of graphene emitter.
Keywords: graphene; Pressure Dependent Field Emission

Enhancement of CO2 uptake in iso-reticular Co based zeolitic imidazolate frameworks via metal replacement - Panda, Tamas; Gupta, Krishna M.; Jiang, Jianwen; Banerjee, Rahul (CrystEngComm, 2014)
Three Co based Zeolitic Imidazolate Frameworks (Co-ZIF-68, -69 and -81) which adopt a GME topology with high porosity have been synthesized. These Co-ZIFs show high CO2 (273 K/298 K) uptake compared to their isostructural Zn based analogues, which has been proved experimentally as well as by ab initio calculations.

Enhancing cubosome functionality by coating with a single layer of poly-epsilon-lysine - Deshpande, Sonal; Venugopal, Edakkal; Ramagiri, Shobha; Bellare, Jayesh R.; Kumaraswamy, Guruswamy; Singh, Neetu (ACS Applied Materials & Interfaces, 2014)
We report the preparation and characterization of monoolein cubosomes that can be easily surface modified through adsorption of a single layer of cationic poly-epsilon-lysine. Poly-epsilon-lysine coated cubosomes show remarkable stability in serum solution, are nontoxic and, are readily internalized by HeLa cells. The poly-epsilon-lysine coating provides chemical handles for further bioconjugation of the cubosome surface. We also demonstrate that the initial release rate of a hydrophilic drug, Naproxen sodium, from the cubosomes is retarded with just a single layer of polymer. Interestingly, cubosomes loaded with Naproxen sodium, recently shown to have anticancer properties, cause more apoptosis in HeLa cells when compared to free unencapsulated drug.
Keywords: bioconjugation; cubosomes; drug delivery vehicle; dual loading; theranostics

Enzyme mediated synthesis of water-dispersible, naturally protein capped, monodispersed gold nanoparticles; their characterization and mechanistic aspects - Khan, Shadab Ali; Ahmad, Absar (RSC Advances, 2014)
Inorganic nanomaterials are conventionally synthesized under harsh environments like extremes of temperature, pressure and pH. These methods are eco-unfriendly, expensive, toxic, cumbersome, yield bigger particles which agglomerate due to not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions viz. room temperature, atmospheric pressure, physiological pH and is reliable, eco-friendly and cheap. We have already reported the extracellular biosynthesis of monodispersed gold nanoparticles from the whole cells of novel extremophilic actinomycete Thermomonospora sp. In order to know the exact mechanism of synthesis, we decided to investigating it further. Here we describe the simple protocol for purification of the temperature and SDS resistant sulfite reductase enzyme and organic capping molecule, which are required for the synthesis and stabilization of gold nanoparticles respectively. This purified enzyme was then employed for the synthesis of gold nanoparticles along with the capping molecule, which render gold nanoparticles monodispersed in solution.

Esterification of levulinic acid to ethyl levulinate over bimodal micro-mesoporous H/BEA zeolite derivatives - Patil, C. R.; Niphadkar, P. S.; Bokade, Vijay V.; Joshi, P. N. (Catalysis Communications, 2014)
A series of bimodal micro-mesoporous H/BEA zeolite derivatives were prepared by the post-synthesis modification of H/BEA zeolite by NaOH (0.05 M-1.2 M) treatment Samples were characterized by powder XRD, low temperature nitrogen adsorption/desorption, temperature programmed desorption of ammonia and ICP. The mesopore formation was found to play a crucial role in liquid phase esterification of levulinic acid with ethanol. The enhanced catalytic activity of a bimodal micro-mesoporous H/BEA zeolite derivative (H/BEA(0.10)) prepared by treatment with 0.1M NaOH can be mainly attributed to the high mesoporosity coupled with better preserved crystallinity and acidic properties. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Esterification; ethyl levulinate; H/BEA zeolite; Mesoporosity; Post-synthesis modification

Esterification of renewable levulinic acid to ethyl levulinate biodiesel catalyzed by highly active and reusable desilicated H-ZSM-5 - Nandiwale, Kakasaheb Y.; Niphadkar, Prashant S.; Deshpande, Shilpa S.; Bokade, Vijay V. (Journal of Chemical Technology and Biotechnology, 2014)
BACKGROUNDIn the near future, fossil fuel will have limitations in terms of availability and also great concerns over its environmental impact. New routes and related technologies based on renewable feedstocks can overcome most of these problems associated with fossil fuel. Among current biodiesel sources, ethyl levulinate (EL) biodiesel obtained from catalytic esterification of renewable levulinic acid (LA) with ethanol has received a great deal of attention. The use of desilicated H-ZSM-5 (DH-ZSM-5) as heterogeneous acid catalyst for EL biodiesel production in a closed system (under autogeneous pressure) was studied. RESULTSThe effect of reaction parameters such as ethanol to LA molar ratio (4:1 to 10:1), catalyst to LA ratio (0.10-0.25), speed of agitation (100-400rpm), particle size (53-355 mu m), reaction temperature (363-403K) and reaction time (7h) was investigated to maximize LA conversion. CONCLUSIONLevulinic acid conversion reached 95% over DH-ZSM-5 and the catalyst was reusable for up to six cycles. This LA conversion and the catalyst reusability values are higher than others reported in the literature. A pseudo-homogeneous (P-H) kinetic model indicated that reaction rate constants increased with increasing molar ratio, catalyst to LA ratio and reaction temperature. The activation energy decreased from 73.14 to 21.08 kJ mol(-1) when increasing the catalyst to LA ratio from 0.10 to 0.25, which implies a kinetically controlled reaction. (c) 2013 Society of Chemical Industry
Keywords: desilicated H-ZSM-5; Esterification; ethyl levulinate; levulinic acid

Evaluation of genetic variability in Symplocos laurina Wall. from two biodiversity hotspots of India - Bhagwat, Rasika M.; Banu, Sofia; Dholakia, Bhushan B.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, Vidya S. (Plant Systematics and Evolution, 2014)
Symplocos laurina Wall., an important medicinal tree species, is one of the pioneering plants for establishment of shola forest ecosystem. We analyzed 208 accessions of S. laurina from 13 populations belonging to three ecoregions in India namely, Western Ghats, Eastern Ghats and Northeast India, to comment on the genetic diversity and population structure of the species. Of the 100 inter simple sequence repeat primers screened, eight were selected based on their clear and reproducible polymorphic patterns. These eight ISSR primers produced on an average 1,014 bands from 208 accessions, of which 6.58 % were rare bands, 55.96 % were shared bands and 37.46 % were similar bands. The primers, UBC835 and UBC880, amplified the highest number of polymorphic loci (16), while the primer UBC852 amplified the least number of amplicons (9). The values for total genetic diversity (H-T) and the average heterozygosity (H-S) were 0.3407 and 0.2263, respectively; while the coefficient of genetic differentiation (G(ST)) was 0.3358. Within-population variance was higher (68 %) than among-population variance (17 %), indicating high intra-population genetic diversity. These populations were grouped according to their geographical location in cluster analysis. Mantel test also showed significant positive correlation between genetic and geographical distances. The present study revealed the importance of the Palghat gap in South India in shaping the distribution of genetic diversity in S. laurina.
Keywords: Biodiversity hotspots; Genetic diversity; ISSR; Palghat gap; Symplocos laurina

Evaluation of multipoint dosing strategy in a miniaturized tubular reactor: nitration of salicylic acid - Debnath, Soujoy; Kienle, Achim; Kulkarni, Amol A. (Chemical Engineering & Technology, 2014)
A 2D non-isothermal reaction engineering model for a tubular reactor was developed for a complex reaction network of salicylic acid nitration. The influence of different operating and design parameters was studied to minimize the amount of secondary nitration products and limit the maximum temperature inside the reactor. Critical temperature effects were observed for larger reaction tubes, whereas close to isothermal conditions were perceived in smaller tubes. With single-point dosing of both reactants, complete conversion can be achieved but formation of secondary nitration products cannot be avoided. For a given number of dosing points, a suitable combination of the operating parameters allowed to achieve complete conversion and better yield of the desired product.
Keywords: Multipoint injection; nitration; Plug-flow reactor; Salicylic acid; Tubular reactor

Evaluation of n-type ternary metal oxide NiMn2O4 nanomaterial for humidity sensing - Gawli, Yogesh; Badadhe, Satish S.; Basu, Aniruddha; Guin, Debanjan; Shelke, Manjusha V.; Ogale, Satishchandra (Sensors and Actuators B-Chemical, 2014)
Synthesis of mono-dispersed oleic acid (OA) capped NiMn2O4 (NMO) nanoparticles and their use for humidity sensing is reported. Oleic acid capped NMO (NMO-cOA) nanoparticles are synthesized from nickel oleate and manganese oleate complex. NiMn2O4 is obtained by removing oleic acid capping at 500 degrees C in air. X-ray diffraction analysis shows formation of pure NiMn2O4 phase which is also confirmed by HRTEM-SAED analysis. The TEM analysis also shows that the nanoparticles are nearly mono-dispersed. Doctor bladed films of NMO nanoparticles are seen to exhibit excellent humidity sensing property. The resistivity is seen to change by two orders with humidity change from 11% RH to 92% RH with fairly good linearity over the entire range. The response and recovery times are also fast. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Humidity; Impedance; Nanoparticles; NiMn2O4; Oleic acid; Sensor

Evolution of an adenine-copper cluster to a highly porous cuboidal framework: solution-phase ripening and gas-adsorption properties - Venkatesh, V.; Pachfule, Pradip; Banerjee, Rahul; Verma, Sandeep (Chemistry-A European Journal, 2014)
The synthesis and directed evolution of a tetranu-clear copper cluster, supported by 8-mercapto-N9-propyladenine ligand, to a highly porous three-dimensional cubic framework in the solid state is reported. The structure of this porous framework was unambiguously characterized by Xray crystallography. The framework contains about 62% solvent-accessible void; the presence of a free exocyclic amino group in the porous framework facilitates reversible adsorption of gas and solvent molecules. Oriented growth of framework in solution was also tracked by force and scanning electron microscopy studies, leading to identification of an intriguing ripening process, over a period of 30 days, which also revealed formation of cuboidal aggregates in solution. The elemental composition of these cuboidal aggregates was ascertained by EDAX analysis.
Keywords: cuboidal frameworks; gas adsorption; metal-organic frameworks; Ostwald ripening; solution-phase ripening

Exceptionally high yields of furfural from assorted raw biomass over solid acids - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (RSC Advances, 2014)
Development of stable and recyclable solid acid catalysts in the efficient valorisation of hemicellulose to yield C-5 sugars and furfural is vital to boost the prospects of using lignocelluloses for chemicals synthesis. Using an silicoaluminophosphate, namely SAPO-44, as a catalyst, an environmentally benign process of furfural synthesis from diversified real substrates (without any treatment or the need for separation of its components) is shown. In an efficient one-pot methodology, at 443 K and in the presence of a biphasic solvent system, selective conversions of hemicelluloses from raw biomass (bagasse, rice husk and wheat straw) to extraordinarily high yields of furfural of about 93% were attainable. Under similar reaction conditions, an 82% yield of furfural is also achievable directly from isolated hemicellulose within 10 h. Hydrophilic SAPO-44, having higher hydrothermal stability, showed similar activity for all the substrates for a minimum of up to 8 times in recycling runs. Various physicochemical characterizations (X-ray diffraction, thermogravimetric analysis-derivative thermogravimetry, temperature programmed desorption-NH3, N-2 sorption, solid-state nuclear magnetic resonance spectroscopy) of fresh and spent catalysts were used to improve SAPO-44 stability.

Excited state geometry optimisation using fock-space multi-reference coupled cluster method - Dutta, Achintya Kumar; Bhattacharya, Sumantra (Molecular Physics, 2014)
The Fock-space multi-reference coupled cluster method is used for the geometry optimisation of the low-lying excited states of the molecules. Molecular geometries of the carbon monohydride cation (CH)(+), water (H2O), ozone (O-3) and formaldehyde (HCHO) in their low-lying excited states are optimised. Excited state gradients are calculated using finite field multi-reference coupled cluster method. We compare our results with other theoretical and/or experimental results, wherever available.
Keywords: adiabatic excitation energy; excited state; Fock-space multi-reference coupled cluster; geometry optimisation; numerical derivative

Expedient preparative isolation and tandem mass spectrometric characterization of C-seco triterpenoids from neem oil - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Dandekar, Devdutta S.; Thulasiram, Hirekodathakallu V. (Journal of Chromatography A, 2014)
C-seco triterpenoids are widely bioactive class of natural products with high structural complexity and diversity. The preparative isolation of these molecules with high purity is greatly desirable, although restricted due to the complexity of natural extracts. In this article we have demonstrated a Medium Pressure Liquid Chromatography (MPLC) based protocol for the isolation of eight major C-seco triterpenoids of salannin skeleton from Neem (Azadirachta indica) oil. Successive application of normal phase pre-packed silica-gel columns for the fractionation followed by reverse phase in automated MPLC system expedited the process and furnished highly pure metabolites. Furthermore, eight isolated triterpenoids along with five semi-synthesized derivatives were characterized using ultra performance liquid chromatography-electrospray ionization-quadrupole/orbitrap-MS/MS spectrometry as a rapid and sensitive identification technique. The structure-fragment relationships were established on the basis of plausible mechanistic pathway for the generation of daughter ions. The MS/MS spectral information of the triterpenoids was further utilized for the identification of studied molecules in the complex extract of stem and bark tissues from Neem. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ESI(+)-quadrupole/orbitrap-MS/MS; MPLC; Neem oil; Preparative isolation; Salannin; Triterpenoids

Experimental determination of the electrostatic nature of carbonyl hydrogen-bonding interactions using IR-NMR correlations - Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemical Letters, 2014)
Hydrogen-bonding plays a fundamental role in the structure, function, and dynamics of various chemical and biological systems. Understanding the physical nature of interactions and the role of electrostatics in hydrogen-bonding has been the focus of several theoretical and computational research. We present an experimental approach involving IR-C-13 NMR correlations to determine the electrostatic nature of carbonyl hydrogen-bonding interactions. This report provides a direct experimental evidence of the classical nature of hydrogen-bonding interaction in carbonyls, independent of any theoretical approximation. These results have important implications in chemistry and biology and can be applied to probe the reaction mechanisms involving carbonyl activation/stabilization by hydrogen bonds using spectroscopic techniques.

Extended coupled cluster method for potential energy surface: a decoupled approach - Joshi, Sayali P.; Vaval, Nayana (Chemical Physics Letters, 2014)
Extended coupled cluster (ECC) method has been implemented extensively for the calculation of molecular properties. In this Letter we report the potential energy surface (PES) study using coupled and a decoupled approximation of ECC. HF, N-2 and C-2 are studied as test systems. N-2 and C-2 being doubly and triply bonded, are considered to be interesting systems for PES study. We compare our results with full CI (FCI) results wherever available. Decoupled approach within ECC framework shows good convergence for all the molecules. (C) 2014 Elsevier B.V. All rights reserved.

Extracellular biosynthesis of gadolinium oxide (Gd2O3) nanoparticles, their biodistribution and bioconjugation with the chemically modified anticancer drug taxol - Khan, Shadab Ali; Gambhir, Sanjay; Ahmad, Absar (Beilstein Journal of Nanotechnology, 2014)
As a part of our programme to develop nanobioconjugates for the treatment of cancer, we first synthesized extracellular, protein-capped, highly stable and well-dispersed gadolinium oxide (Gd2O3) nanoparticles by using thermophilic fungus Humicola sp. The biodistribution of the nanoparticles in rats was checked by radiolabelling with Tc-99m. Finally, these nanoparticles were bioconjugated with the chemically modified anticancer drug taxol with the aim of characterizing the role of this bioconjugate in the treatment of cancer. The biosynthesized Gd2O3 nanoparticles were characterized by UV-vis spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoemission spectroscopy (XPS). The Gd2O3-taxol bioconjugate was confirmed by UV-vis spectroscopy and fluorescence microscopy and was purified by using high performance liquid chromatography (HPLC).
Keywords: bioconjugation; biodistribution; gadolinium oxide; humicola sp; transmission electron microscopy

Extracellular biosynthesis of metal sulfide nanoparticles using the fungus fusarium oxysporum - Senapati, Satyajyoti; Syed, Asad; Khan, Shadab; Pasricha, Renu; Khan, Mohammad Islam; Kumar, Rajiv; Ahmad, Absar (Current Nanoscience, 2014)
The development of reliable, eco-friendly processes for the synthesis of nanomaterials is an important aspect of nanotechnology. One approach that shows immense potential is based on the biosynthesis of nanoparticles using microorganisms such as bacteria. In this report, we demonstrate the extracellular biosynthesis and complete characterization of metal sulfide (PbS, ZnS, MnS and NiS) nanoparticles using fungus, Fusarium oxysporum. We observed that the exposure of aqueous solution of 1 mM metal sulfate to fungus Fusarium oxysporum resulted in the formation of highly stable technologically important metal sulfide semiconductor nanoparticles. Fusarium oxysporum synthesizes lead sulfide and zinc sulfide nanoparticles of fractal type structure whereas manganese sulfide and nickel sulfide nanoparticles are of variable polydispersed morphology. The variable morphology may be due to the dissimilar interaction of metal sulfide nanoparticles with capping proteins secreted by the fungus in solution. The nanoparticles solution is found to be extremely stable with little evidence of aggregation even after a month of storage. The long term stability of the nanoparticles is due to the proteins secreted by fungus in the nanoparticle solution which bind to the surface of the nanoparticles and thus prevent aggregation.
Keywords: Biosynthesis; enzymes; fungi; metal sulfide; Nanoparticles

Extracellular synthesis of silver nanoparticles using living peanut seedling - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Applied Nanoscience, 2014)
Synthesis of nanoparticles by environment friendly method is an important aspect of nanotechnology. In the present study, extracellular reduction of silver ions to silver nanoparticles was carried out using living peanut plant. The electron microscopic analysis shows that the formed nanoparticles were of different shapes and sizes. The formed nanoparticles were polydispersed. The shapes of the nanoparticles were spherical, square, triangle, hexagonal and rod. Most of the particles were spherical and 56 nm in size. EDS analysis confirmed the formed nanoparticles were of silver. The crystalline nature of nanoparticles was confirmed by diffraction. This method opens up an exciting possibility of plant-based synthesis of other inorganic nanomaterials. This study confirms the synthesis of extracellular silver nanoparticles by living plant.
Keywords: Nanoparticles; Shapes; Silver; synthesis; TEM

Easy `filter-and-separate' method for enantioselective separation and chiral sensing of substrates using a biomimetic homochiral polymer - Senthilkumar, T.; Asha, S. K. (Chemical Communications, 2015)
We present a polyfluorene appended with protected L-glutamic acid that exhibited a reversible alpha-helix/beta-sheet-like conformation and helical porous fibrous morphology mimicking the super-structure of proteins. The new homochiral polymer probe enabled efficient heterogeneous enantioselective separation and chiral sensing of a wide variety of substrates from their aqueous racemic mixture using an easy `Filter-and-Separate' method.

Eco-friendly enzymatic dehairing of skins and hides by C-brefeldianus protease - Khandelwal, Harish B.; More, Snehal V.; Kalal, K. M.; Laxman, Ryali Seeta (Clean Technologies and Environmental Policy, 2015)
Alkaline protease from Conidiobolus brefeldianus was efficient in unhairing various types of skins and hides. The crude protease preparation was active toward keratin-azure, elastin-orcin, azocasein, and azocoll, but did not show true collagenase activity. In addition, the crude enzyme exhibited other enzyme activities such as chondroitinase, laminarase, and chitinase. Complete hair removal of skin/hide by the protease achieved in 16-18 h. The dehaired pelt showed smooth and white appearance due to hair removal along with epidermal layer. In addition, the grain was clean and without damage in enzymatically dehaired pelts. The microscopic observation of the cross-section of dehaired goat skin and cow hide showed absence of epidermis, hair shaft with empty follicles. Enzymatic dehairing resulted in complete and uniform fiber opening in the dermis and corium region. Physical properties viz. tensile strength, elongation, and tear strength of dyed crust of enzymatically and conventionally dehaired pelts were comparable. Results were also validated on large scale with goat skins and cow hides.
Keywords: Alkaline Protease; Conidiobolus brefeldianus; Cow hides; Dehaired pelts; Enzymatic dehairing; Sheep skins

Ecological turmoil in evolutionary dynamics of plant-insect interactions: defense to offence - Mishra, Manasi; Lomate, Purushottam R.; Joshi, Rakesh S.; Punekar, Sachin A.; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
Available history manifests contemporary diversity that exists in plant-insect interactions. A radical thinking is necessary for developing strategies that can co-opt natural insect-plant mutualism, ecology and environmental safety for crop protection since current agricultural practices can reduce species richness and evenness. The global environmental changes, such as increased temperature, CO (2) and ozone levels, biological invasions, land-use change and habitat fragmentation together play a significant role in re-shaping the plant-insect multi-trophic interactions. Diverse natural products need to be studied and explored for their biological functions as insect pest control agents. In order to assure the success of an integrated pest management strategy, human activities need to be harmonized to minimize the global climate changes. Plant-insect interaction is one of the most primitive and co-evolved associations, often influenced by surrounding changes. In this review, we account the persistence and evolution of plant-insect interactions, with particular focus on the effect of climate change and human interference on these interactions. Plants and insects have been maintaining their existence through a mutual service-resource relationship while defending themselves. We provide a comprehensive catalog of various defense strategies employed by the plants and/or insects. Furthermore, several important factors such as accelerated diversification, imbalance in the mutualism, and chemical arms race between plants and insects as indirect consequences of human practices are highlighted. Inappropriate implementation of several modern agricultural practices has resulted in (i) endangered mutualisms, (ii) pest status and resistance in insects and (iii) ecological instability. Moreover, altered environmental conditions eventually triggered the resetting of plant-insect interactions. Hence, multitrophic approaches that can harmonize human activities and minimize their interference in native plant-insect interactions are needed to maintain natural balance between the existence of plants and insects.
Keywords: Climatic change; Co-evolution; Ecosystem; Human interference; Plant-insect interaction

Effect of alkali and alkaline earth metal ions on benzyl alcohol oxidation activity of titanate nanotube-supported Au catalysts - Nepak, Devadutta; Srinivas, Darbha (RSC Advances, 2015)
Sodium titanate nanotubes (NaTNTs) were prepared by alkali treatment of anatase titania. They were then ion-exchanged with alkali and alkaline earth metal ions to get ATNTs (A = Li+, K+, Cs+, Mg2+, Ca2+, Sr2+ and Ba2+). Gold (1-5 wt%) was supported on these nanotubes by a deposition-precipitation method and investigated as a catalyst for the selective oxidation of benzyl alcohol with air/molecular oxygen (1 atm) under solvent-and alkali-free conditions. Detailed characterization by X-ray powder diffraction, high resolution transmission electron microscopy, N-2-physisorption, diffuse reflectance UV-visible spectroscopy, X-ray photoelectron spectroscopy and CO2-temperature-programmed desorption techniques revealed that the basicity of the catalyst influences the uptake, mean particle size, electronic properties and oxidation activity of the supported gold. Benzaldehyde formed with a selectivity of about 99%. The catalytic activity (turnover frequency) was found to have a direct relationship with the basicity and an inverse relationship with the Au particle size. Among the catalysts investigated, Au/BaTNTs, having higher basicity, smaller Au particles and higher metal dispersion, showed enhanced catalytic activity than the other Au/ATNT catalysts. Pd addition to Au leading to Au-Pd/BaTNTs increased the activity (TOF) but lowered the selectivity for benzaldehyde (80 wt%). Titanate nanotubes donate electron density to Au particles, yielding electron rich Au ions, which are responsible for activating molecular oxygen and oxidizing benzyl alcohol. Au/BaTNTs, having higher basicity and lower size Au nanoparticles than the other Au/ATNT, activates molecular oxygen more easily and thereby enhances the catalytic activity.

Effect of b site coordination environment in the ORR activity in disordered brownmillerites Ba2In2-xCexO5+delta - Jijil, Chamundi P.; Bhange, Siddheshwar N.; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2015)
Ba2In2O5 brownmillerites in which the In site is progressively doped with Ce exhibit excellent oxygen reduction activity under alkaline conditions. Ce doping leads to structural changes advantageous for the reaction. Twenty-five percent doping retains the ordered structure of brownmillerite with alternate layers of tetrahedra and octahedra, whereas further increase in Ce concentration creates disorder. Structures with disordered oxygen atoms/vacancies are found to be better oxygen reduction reaction catalysts probably aided by isotropic ionic conduction, and Ba2In0.5Ce1.5O5+delta is the most active. This enhanced activity is correlated to the more symmetric Ce site coordination environment in this compound. Stoichiometric perovskite BaCeO3 with the highest concentration of Ce shows very poor activity emphasizing the importance of oxygen vacancies, which facilitate O-2 adsorption, in tandem with catalytic sites in oxygen reduction reactions.
Keywords: brownmillerite; fuel cell; oxygen disorder; oxygen reduction reaction; Rietveld refinement

Effect of interfacial mass transfer on the dispersion in segmented flow in straight capillaries - Deshpande, Jaydeep B.; Kulkarni, Amol A. (AICHE Journal, 2015)
The effect of interfacial mass transfer on the extent of dispersion in liquid-liquid segmented flow in straight capillaries is studied. In the absence of interfacial mass transfer, dispersion coefficient was seen to go through a minimum with increasing flow rates. In the presence of mass transfer, physicochemical properties of both the phases and slug lengths were seen to vary along the capillary length. The extent of dispersion was always higher in the presence of interfacial mass transfer. The predictions using axial dispersion model deviated noticeably for larger capillaries as the model does not account for varying buoyancy, dynamic contacting, and Marangoni convection. Simulations of a first-order interfacial reaction considering varying slug lengths showed a significant change in optimum operating parameters than the conventional approach. A special case of drop-on-demand type of controlled two-phase flow in capillaries was also studied. (c) 2015 American Institute of Chemical Engineers.
Keywords: capillary; dispersion; interfacial mass transfer; segmented flow; slugs

Effect of lipid bilayer composition on membrane protein association - Pawar, Aiswarya B.; Prasanna, Xavier; Sengupta, Durba (Advances in Planar Lipid Bilayers and Liposomes, 2015)
Diverse cellular functions are supported by membrane protein assemblies associated with the cell membrane. Although considered to be protein-mediated, membrane components are now being recognized as critical in modulating and sometime dictating function. This chapter discusses the effect of the lipid bilayer, in particular its composition on membrane protein organization. Computational methods have been successful in quantifying transmembrane protein association and general features of dimerization profiles are explored. Understanding the molecular basis of the interactions has lead to the recognition of the lipophobic effects. These nonspecific effects include those that arise from membrane perturbations and lipid chain packing and have been shown to modulate the energetics as well as the structural characteristics of membrane protein dimerization. In addition, specific interactions arising from direct protein–lipid interactions and protein–cholesterol interactions have been suggested to influence membrane protein association. We summarize here a few examples highlighting the role of the lipid bilayer on membrane protein organization.

Effect of nutritional factors on growth and L-asparaginase production by three thermophilic coprophilous fungi - Ajmeera, Shanthi Priya; Rao, Vankudoth Koteswara; Sreelatha, B.; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (Current Research in Microbiology Biotechnology, 2015)
The present study aimed to investigate the effect of nutritional factors on L-asparaginase production by three thermophilic caprophilous fungi (Thielavia terrestris, Malbranchea cinnamomea and Scytalidium thermophilum) was assessed in YES medium by substituting starch and L-asparagine so as to supply equal amount of carbon and nitrogen sources respectively. D-glucose, starch, maltose and mannitol were best source for growth and L-asparaginase production by all three thermophilic caprophilous fungi under investigation. Similarly L-asparagine, L-arginine, L-tyrosine and L-histidine were good nitrogen sources for both growth and L-asparaginase production. Production of the variance of the data showed the significant difference (P<0.05) among the three thermophilic caprophilous fungi with regards to carbon and nitrogen source.

Effect of Pd and Ce on the enhancement of ethanol vapor response of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Vaishampayan, M. V.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Sensors and Actuators B-Chemical, 2015)
The undoped SnO2 and 4 wt% Ce-doped SnO2 were successfully synthesized by a facile co-precipitation route. The ternary systems were prepared by Pd-loading (0.5, 1.5 and 3.0 wt%) on the 4 wt% Ce-doped SnO2 nanoparticles. The structure and morphology of the nanocrystalline powders were investigated by X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The nanocrystalline powders were screen printed on the alumina substrates to form thick films to investigate their gas response properties. The gas response studies reveal that 4 wt% Ce-doped SnO2 with the loading of 3.0 wt% Pd exhibits high response (88%) towards ethanol (100 ppm) at an operating temperature of 250 degrees C with quick response (6 s) and rapid recovery (20 s). The high ethanol vapor response at lower operating temperature of this sensor is attributed to the spill-over mechanism of Pd particles present on the SnO2 surface and enhancement in alkalescence of SnO2 due to Ce-doping. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ce-doped tin oxide; Gas sensor; Semiconductor; Thick film

Effects of careful designing of SAPO-44 catalysts on the efficient synthesis of furfural - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (Catalysis Today, 2015)
Considering the growing importance of furfural, it is necessary to develop a robust solid acid catalyst for the conversion of xylan (hemicelluloses) into furfural in a one-pot method. In this study, the effects of various components (Si, Al and P) and crystallization time on the preparation of acidic materials and their properties are extensively described. It is seen that with the increase in crystallization time (0, 48, 96, 176 h) during the synthesis of silicoaluminophosphate (SAPO-44), materials morphology changes from amorphous to AFI to CHA and the best activity for furfural synthesis (82%) from xylan was observed with SAPO-44 catalyst aged for 176 h. Since, acidity in the SAPO-44 is guided by the incorporation of Si in the ALPO framework, study on Si molar concentration (0.8, 1.0, 1.2, 1.4 and 1.6) in SAPO-44 was carried out and it was observed that SAPO-44 having 1.0 mole of Si content is the best catalyst for the xylan/xylose conversion to furfural. Catalyst structure-activity correlation is thoroughly defined with the help of several physico-chemical properties. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomass; furfural; Hemicellulose; SAPO-44; Xylose

Efficacy of food preservatives and volatile compounds in the control of ochratoxin a production by penicillium species - Vankudoth, Koteswara Rao; Rao, K. Narasimha; Sivadevuni, Girisham; Reddy, S. M. (Proceedings of the National Academy of Sciences, India - Section B: Biological Sciences, 2015)
In the present investigation different volatile compounds and food preservatives were tested for their efficiency in the control of growth and ochratoxin A (OTA) production by Penicillium verrucosum and Penicillium nordicum. Volatiles such as phenols and formic acid which have no residual effect were proved to be effective in checking the growth and OTA production by both the species of Penicillium under study. Vapours of phenols and formic acid significantly inhibited OTA produced by P. verrucosum, while aniline and toluene inhibited the OTA production by P. nordicum to a significant level. A positive correlation coefficient was observed between the growth and toxin production by P. verrucosum (0.55) and P. nordicum (0.66) against different volatile compounds tried. Among food preservatives, sodium acetate and sodium metabisulphate were responsible for total inhibition of OTA production by P. verrucosum at 150 lg/ml concentration. P. nordicum proved to be comparatively more resistant to these substances than P. verrucosum. In conclusion of present investigation, phenol, formic acid, amyl alcohol, propionic acid, sodium acetate and sodium metabisulphate were found to be effective in checking the growth and OTA production by both the species of Penicillium under investigation, and can be exploited in protecting the poultry feed from unwanted mould growth and mycotoxin production.

Efficacy study of potential anti-tubercular molecules: in-vitro and ex-vivo - Nawale, Laxman; Sarkar, Dhiman (National Science Day, 2015)
Tuberculosis: Infectious disease caused by the bacillus Mycobacterium tuberculosis Second leading infectious killer after HIV/AIDS In 2013, 8.6 million TB cases were reported out of which 1.3 million died Emergence of Multi-drug resistant TB (MDR-TB) and extremely drug resistant TB (XDR) for which no drugs are available. Latency being a cause of recurring TB infection is a major problem in eradication of TB

Efficient access to enantiopure 1,3-disubstituted isoindolines from selective catalytic fragmentation of an original desymmetrized rigid overbred template - Pandey, Ganesh; Varkhedkar, Rajesh; Tiwari, Divya (Organic & Biomolecular Chemistry, 2015)
An efficient and scalable synthesis of various enantiopure 1,3-disubstituted isoindolines is reported. The base catalyzed nucleophilic fragmentation of a rigid overbred template is established with various substrates to afford the corresponding 1,3-disubstituted isoindoline ester, amide, thioate, 1,3-amino alcohol and isoindolylcarboxylic acid. The crucial rigid overbred template is synthesized in an optically pure form in multigram scale by asymmetric desymmetrization of the corresponding meso compound.

Efficient Ag-nanoparticle embedded semi-IPN hydrogel for catalytic applications - Patwadkar, Manjusha V.; Gopinath, Chinnakonda S.; Badiger, Manohar V. (RSC Advances, 2015)
Silver nanoparticle embedded semi-IPN hydrogels based on a combination of poly(acrylamide) and poly(aspartic acid) were synthesized. These semi-IPN hydrogel networks can potentially serve as micro or nano reactors for entrapment of metal nanoparticles. Current methodology allows us to entrap metal nanoparticles throughout hydrogel networks via poly(aspartic acid) chains which are dispersed homogeneously in the gel matrix. The Ag-NPs were characterized by UV-vis absorption spectroscopy, transmission electronic microscopy (TEM), X-ray diffraction (XRD) and energy dispersive X-ray analysis (EDAX). The Ag embedded hydrogels catalyze the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 very efficiently at room temperature with good recyclability upto 3 cycles.

Efficient method for the conversion of agricultural waste into sugar alcohols over supported bimetallic catalysts - Tathod, Anup P.; Dhepe, Paresh Laxmikant (Bioresource Technology, 2015)
Promoter effect of Sn in the PtSn/gamma-Al2O3 (AL) and PtSn/C bimetallic catalysts is studied for the conversion of variety of substrates such as, C5 sugars (xylose, arabinose), C6 sugars (glucose, fructose, galactose), hemicelluloses (xylan, arabinogalactan), inulin and agricultural wastes (bagasse, rice husk, wheat straw) into sugar alcohols (sorbitol, mannitol, xylitol, arabitol, galactitol). In all the reactions, PtSn/AL showed enhanced yields of sugar alcohols by 1.5-3 times than Pt/AL. Compared to C, AL supported bimetallic catalysts showed prominent enhancement in the yields of sugar alcohols. Bimetallic catalysts characterized by X-ray diffraction study revealed the stability of catalyst and absence of alloy formation thereby indicating that Pt and Sn are present as individual particles in PtSn/AL. The TEM analysis also confirmed stability of the catalysts and XPS study disclosed formation of electron deficient Sn species which helps in polarizing carbonyl bond to achieve enhanced hydrogenation activity. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Agricultural waste; Bimetallic catalyst; Hydrogenation; Monosaccharides; Polysaccharides

Efficient one pot regioselective synthesis of a 3,3 `-spiro-phosphonylpyrazole-oxindole framework via base mediated [1,3]-dipolar cycloaddition reaction of the Bestmann-Ohira reagent with methyleneindolinones - Shelke, Anil M.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2015)
A one pot, highly regioselective synthesis of racemic 3,3'-spiro-phosphonylpyrazole-oxindole by 1,3-dipolar cycloaddition of an in situ generated anion of dialkyl 1-diazomethylphosphonate from the Bestmann-Ohira reagent (BOR) & methyleneindolinones has been developed. The synthesis affords the highly functionalized pyrazole scaffolds in good yields with excellent regioselectivity under mild reaction conditions within a short reaction time.

Efficient organocatalytic route for asymmetric total synthesis of stagonolide F - Shelke, Anil M.; Suryavanshi, Gurunath (Tetrahedron Letters, 2015)
A stereoselective total synthesis of Stagonolide F (98% ee) is described employing asymmetric alpha-aminooxylation, Jorgensen's asymmetric epoxidation, Brown asymmetric allylation, Steglich esterification and ring closing metathesis as key steps. The use of organocatalytic alpha-aminooxylation and Jorgensen's asymmetric epoxidation of aldehydes for the introduction of chirality makes this approach more attractive. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: alpha-Aminooxylation; Jorgensens's asymmetric epoxidation; Macrolide; Ring-closing metathesis; Total synthesis

Efficient robust fluorite CeZrO4-delta oxide catalyst for the eco-benign synthesis of styrene - Periyasamy, Kaliyappan; Aswathy, Venugopalan T.; Kumar, Venugopal Ashok; Manikandan, Marimuthu; Shukla, Rakesh; Tyagi, Avesh K.; Raja, Thirumalaiswamy (RSC Advances, 2015)
In this work, we have reported CeO2, ZrO2, physically mixed (PH)-CeO2/ZrO2 and fluorite CeZrO4-delta oxides and their catalytic activities for the oxidative dehydrogenation (ODH) of ethyl benzene (EB) to styrene (ST) using molecular oxygen, air and carbon dioxide as oxidants. The catalysts were prepared by a gel-combustion method followed by calcination at 600 degrees C for 6 h and subjected to catalytic activity measurements. All the catalysts were characterized and studied by various physicochemical methods. The reaction parameters were varied systematically such as different catalysts, oxidants, temperatures, EB flow and oxidant flow. CeZrO4-delta accounted for a 47% styrene yield for 72 h without any significant deactivation under optimized reaction conditions. A thorough analysis of the spent catalysts demonstrated the robustness of the catalyst for this reaction under different oxidants and reaction conditions. Pristine CeO2 deactivated easily and the activity decreased with time on stream of the reaction.

Efficient shoots regeneration and genetic transformation of bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Gupta, Neha; Ruby; Shirgurkar, M. V.; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2015)
Bacopa monniera is an important source of metabolites with pharmaceutical value. It has been regarded as a valuable medicinal plant and its entire commercial requirement is met from wild natural population. Recently, metabolic engineering has emerged as an important solution for sustained supply of assured and quality raw material for the production of active principles. Present report describes efficient in vitro multiplication and transformation method for geneticmanipulation of this species. MS medium supplemented with 2 mgl(-1) BA and 0.2 mgl(-1) IAA was found optimum for maximum shoot regeneration (98.33 %) from in vitro leaves with 2-3 longitudinal cuts. Agrobacterium tumefaciens-mediated transformation method was used for generating transgenic B. monniera plants. Putative transformants were confirmed by GUS assay and PCR based confirmation of hptII gene. DNA blot analysis showed single copy insertion of transgene cassette. An average of 87.5 % of the regenerated shoots were found PCR positive for hptII gene and GUS activity was detected in leaves of transgenic shoots at a frequency of 82.5 % The efficient multiple shoots regeneration system described herein may help in mass production of B. monniera plant. Also, the high frequency transformation protocol described here can be used for genetic engineering of B. monniera for enhancement of its pharmaceutically important metabolites.

Efficient sorption and photocatalytic degradation of malachite green dye onto NiS nanoparticles prepared using novel green approach - Prasad, Kumar Suranjit; Prajapati, Sheel; Selvaraj, Kaliaperumal (Korean Journal of Chemical Engineering, 2015)
The extract of the Asparagus racemosus leaf tissue works as a stabilizing and capping agent and assists the formation of stable colloidal nanoparticles. Nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX and XRD, respectively. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of near spherical, polydispersed, crystalline NiS of diameter ranging from 4-27 nm. X-ray diffraction studies showed the formation of 110, 101, 300, 021, 220, 221, 131, 410, 401, 321, 330 and 021 planes of hexagonal NiS. EDAX analysis confirmed the presence of Ni and S in nanosphere. The maximum sorption capacity (q (m) ) of NiS nanoparticles for MG dye was found to be 64.85 mg/g. Decolorization as well as disintegration of malachite green under white light illumination was confirmed by LC-MS studies. Results of the present study suggest that nanosized NiS can play an instrumental role in photocatalytic degradation of malachite green dye present in water bodies.
Keywords: Degradation; FTIR; Malachite Green; NiS Nanoparticles; TEM

Electrochemical preparation of nitrogen-doped graphene quantum dots and their size-dependent electrocatalytic activity for oxygen reduction - Shinde, Dhanraj B.; Dhavale, Vishal M.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Bulletin of Materials Science, 2015)
Here we report a remarkable transformation of nitrogen-doped multiwalled carbon nanotubes (MWCNTs) to size selective nitrogen-doped graphene quantum dots (N-GQDs) by a two-step electrochemical method. The sizes of the N-GQDs strongly depend on the applied anodic potential, moreover increasing potential resulted in a smaller size of N-GQDs. These N-GQDs display many unusual size-dependant optoelectronic (blue emission) and electrocatalytic (oxygen reduction) properties. The presence of N dopants in the carbon framework not only causes faster unzipping of MWCNTs but also provides more low activation energy site for enhancing the electrocatalytic activity for technologically daunting reactions like oxygen reduction. The smaller size of N-GQDs has shown better performance as compared to the large N-GQDs. Interestingly, N-GQDs-3 (size = 2.5 +/- 0.3 nm, onset potential = 0.75 V) show a 30-mV higher positive onset potential shift compared to that of N-GQDs-2 (size = 4.7 +/- 0.3 nm, onset potential = 0.72 V) and 70 mV than that of N-GQDs-1 (size = 7.2 +/- 0.3, onset potential = 0.68 V) for oxygen reduction reaction (ORR) in a liquid phase. These result in the size-dependent electrocatalytic activity of N-GQDs for ORR as illustrated by the smaller sized N-GQDs (2.5 +/- 0.3 nm) undoubtedly promising metal-free electrocatalysts for fuel cell applications.
Keywords: fuel cells; MWCNTs; N-GQDs; oxygen reduction reaction; unzipping

Electrochemically exfoliated black phosphorus nanosheets - prospective field emitters - Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
Herein we report field emission (FE) investigations on an electrochemically exfoliated few-layered black phosphorus nanosheet emitter at a base pressure of approximately 1x10(-8) mbar. The turn-on electric field required to draw an emission current density of approximately 10 A/cm(2) is found to be about 4.2 V/m. Furthermore, few-layered black phosphorus nanosheet emitters deliver an emission current density of about 170 A/cm(2) at an applied field of about 7.5 V/m. The emission current vs. time plot measured at preset current values of about 5 A shows emission current fluctuations within +/- 10% of the average value, indicating the highly stable nature of the black phosphorus field emitter. Thus, the 2D black phosphorus nanosheets synthesized using the simple electrochemical exfoliation method can be utilized for micro/nanoelectronics and flat panel FE display applications.
Keywords: field emission; Layered compounds; Nanostructures; Phosphorus

Electron attachment to DNA and RNA nucleobases: an EOMCC investigation - Dutta, Achintya Kumar; Sengupta, Turbasu; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2015)
We report a benchmark theoretical investigation of both vertical and adiabatic electron affinities of DNA and RNA nucleobases: adenine, guanine, cytosine, thymine, and uracil using equation of motion coupled cluster method. The vertical electron affinity (VEA) values of the first five states of the DNA and RNA nucleobases are computed. It is observed that the first electron attached state is energetically accessible in gas phase. Furthermore, an analysis of the natural orbitals exhibits that the first electron attached states of uracil and thymine are valence-bound in nature and undergo significant structural changes on attachment of an extra electron, which reflects in the deviation of the adiabatic electron affinity (AEA) than that of the vertical ones. Conversely, the first electron attached states of cytosine, adenine, and guanine are in the category of dipole-bound anions. Their structure, by and large, remain unaffected on attachment of an extra electron, which is evident from the observed small difference between the AEA and VEA values. VEA and AEA values of all the DNA and RNA nucleobases are found to be negative, which implies that the first electron attached states are not stable rather quasi bound. The results of all previous theoretical calculations are out of track and shows large deviation with respect to the experimentally measured values, whereas, our results are found to be in good agreement. Therefore, our computed values can be used as a reliable standard to calibrate new theoretical methods. (c) 2015 Wiley Periodicals, Inc.
Keywords: DNA-RNA bases; electron affinity; EOMCC

Embedded multiple shooting methodology in a genetic algorithm framework for parameter estimation and state identification of complex systems - Sarode, Ketan Dinkar; Kumar, V. Ravi; Kulkarni, B. D. (Chemical Engineering Science, 2015)
A novel parameter estimation and state identification algorithm for nonlinear dynamical systems from data by embedding a multiple shooting methodology in the framework of a genetic algorithm (EMSGA) is described. The advantages of EMSGA are brought out by studies with two highly nonlinear examples, viz., the chaotic dynamics of a non-isothermal CSTR and the glycolysis regulation in Lactococcus lactis for production of lactic acid. For the chaotic dynamics with extremely high sensitivity to parameter values and initial conditions, EMSGA accurately estimates all process parameters while at the same time recovering the true dynamics of monitored and unmonitored variables from limited extents of noisy dynamic data. The superiority in accuracy and computational time of EMSGA over standalone genetic or multiple shooting algorithms for parameter estimation is shown for comparison purposes. In fact, EMSGA adapts well to the use of generalized canonical models, e.g., the S-system, where use of the fundamental Taylor series method of any order for integration becomes possible. This makes EMSGA highly efficient and exemplified here by estimating all the parameters of the derived higher dimensional 5-system model for the CSTR. Comparative studies with a well-known global-local enhanced scatter search method corroborate the suitability and advantages of the EMSGA methodology. For the glycolysis regulation example the numerical robustness of EMSGA is brought out by estimating a large number of model parameters when a majority of them are raised to the power of the state variables. Interestingly, we show that from noisy in vivo dynamic data it becomes possible to completely recover the noise-free dynamical behavior of unmonitored species concentrations using EMSGA. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Canonical models; Chaotic dynamics; Genetic algorithm; Multiple shooting; Noise reduction; parameter estimation

Emerging energy applications of two-dimensional layered materials - Late, Dattatray J.; Rout, Chandra Sekhar; Chakravarty, Disha; Ratha, Satyajit (Canadian Chemical Transactions, 2015)
Atomically thin semiconducting transition metal dichalcogenides (TMDCs) layered materials have recently been emerged as an exciting area of research due to accessibility for easy synthesis using various chemical and physical methods. These two-dimensional (2D) layered materials with single layer have direct and wide band gap due to which, they are more suitable for nanoelectronics and optoelectronics device applications. Here, we present a review of the energy related aspects of atomically thin layered materials like MoS2, WS2, MoSe2, WSe2, InSe, GaSe, GaTe, MoTe2, WTe2 etc. for supercapacitor, solar cell, lithium ion battery and water splitting application. By significantly assessing various materials and comparing their performances with challenging technology, the advantages and disadvantages of this promising area of energy materials are recognized, which may provide guidelines for future progress.

Enantioselective cooperative catalysis - Inamdar, Suleman M.; Shinde, Valmik S.; Patil, Nitin T. (Organic & Biomolecular Chemistry, 2015)
In recent years, enantioselective cooperative catalytic reactions, wherein two catalysts work simultaneously to form products which cannot be obtained by the use of a single catalyst alone, have attracted considerable attention. This review focuses on this emerging field, with particular emphasis on mechanistic aspects, which will help readers to understand the role of each catalyst.

Enantioselective syntheses of (R)-pipecolic acid, (2R,3R)-3-hydroxypipecolic acid, beta-(+)-conhydrine and (-)-swainsonine using an aziridine derived common chiral synthon - Chavan, Subhash P.; Khairnar, Lalit B.; Pawar, Kailash P.; Chavan, Prakash N.; Kawale, Sanket A. (RSC Advances, 2015)
Concise total syntheses of (R)-pipecolic acid, (R)-ethyl-6-oxopipecolate, (2R, 3R)-3-hydroxypipecolic acid and formal syntheses of beta-(+)-conhydrine, (-)-lentiginosine, (-)-swainsonine and 1,2-di-epi-swainsonine have been accomplished starting from a common chiral synthon. The present strategy employs regioselective aziridine ring opening, Wittig olefination and RCM as the key chemical transformations.

Enantioselective synthesis of functionalized pyrazoles by NHC-catalyzed reaction of pyrazolones with alpha,beta-unsaturated aldehydes - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Suresh, Eringathodi; Biju, Akkattu T. (Organic Letters, 2015)
The N-heterocyclic carbene (NHC)-organocatalyzed enantioselective annulation reaction of pyrazolones with alpha,beta-unsaturated aldehydes proceeding via the chiral alpha,beta-unsaturated acyl azolium intermediates under oxidative conditions is presented. The reaction afforded dihydropyranone-fused pyrazoles in moderate to good yields and good er values under operationally simple and base-free conditions.

Enantioselective synthesis of guggultetrol and D-ribo-phytosphingosine tetraacetate via L-proline catalyzed sequential alpha-aminooxylation/Horner-Wardsworth-Emmons olefination-Sharpless asymmetric dihydroxylation strategy - Venkataramasubramanian, V.; Kumar, B. Senthil; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
An efficient enantioselective synthesis of two bioactive molecules, that is, guggultetrol and D-ribo-phytosphingosine, is described with high enantioselectivity (>98% ee) starting from commercially available 1-hexadecanol. The synthesis comprises organocatalyzed sequential alpha-aminooxylation of an aldehyde followed by Horner-Wardsworth-Emmons olefination and Sharp less asymmetric dihydroxylation as the key chiral inducing steps. For both syntheses, gamma-hydroxy-alpha,beta-unsaturated ester serves as the common intermediate obtained from proline catalysis. (C) 2015 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (+)-hygroline and (+)-pseudohygroline via Keck allylation and CBS reduction - Bhoite, Shubhangi P.; Kamble, Rohit B.; Suryavanshi, Gurunath M. (Tetrahedron Letters, 2015)
An enantioselective synthesis of (+)-hygroline and (+)-pseudohygroline has been achieved in high optical purity (98% ee) from readily available 1,4-butanediol. The synthesis strategy employs a Keck allylation, CBS reduction, and Wacker oxidation. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: CBS reduction; Keck allylation; Pyrrolidines; Wacker oxidation

Enantiospecific synthesis of both enantiomers of the longtailed mealybug pheromone and their evaluation in a new zealand vineyard - Ramesh, Remya; Bell, Vaughn; Twidle, Andrew M.; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2015)
The irregular monoterpenoid sex pheromone of Pseudococcus longispinus and its enantiomer were prepared from the corresponding bornyl acetates. The use of readily accessible chiral starting materials and lactone lactone rearrangement are the highlights of the present synthesis. The biological activities of the two enantiomers and racemic mixture were tested in a New Zealand vineyard. The (S)-(+)-enantiomer was significantly more attractive to P. longispinus males than the racemic mixture or the (R)-(-)-enantiomer.

Encapsulation of ultra small metal clusters in silica: evolution of the concept of nanoreactors and the case of Ag-Pd@SiO2 alloy catalyst - Mondal, Sourik; Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (Catalysis Today, 2015)
The concept of encapsulation of ultra small clusters within silica evolved as a means to address the sintering of active metal nanoparticles and subsequent deactivation observed in supported noble metal catalysts. It is hypothesised that sintering, which mainly occurs due to mobility of metal species on the support surfaces, can be minimised if the growth and movement of metal nanoparticles are constrained. First, nanoparticles are isolated inside 1D channels in 2D mesoporous compounds and the idea develops to complete encapsulation of thiol protected ultra small nanoclusters in silica spheres. Sintering is better controlled in the latter due to the confined space for growth of nanoparticles. Access of reactant molecules to the active metal surfaces also is ensured by porosity created in the silica matrix forming the basis of the concept of nanoreactors. In this paper, we elaborate on the evolution of this concept from our earlier work on highly sinter resistant silica encapsulated Au, Pd and Au-Pd alloys to the present system of Ag-Pd alloy encapsulated in silica. Silver, with the lowest Tammann temperature among noble metals, is highly prone to sintering which is adequately controlled by alloying with Pd as well as encapsulation in silica. Its enhanced activity in paranitrophenol reduction in comparison with pure metals indicates the advantageous effect of alloying. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ag-Pd alloy; Encapsulation; Sinter resistant; Sintering; Ultra small nanoclusters

Ene-nucleic acids: a different paradigm to DNA chemistry - Varada, Manojkumar; Erande, Namrata D.; Kumar, Vaijayanti A. (RSC Advances, 2015)
Acyclic prochiral nucleic acids such as FNA, UNA, GNA and cyclic chiral TNA are all considered as precursors of DNA and RNA in the chemical etiology of nucleic acids. The chemical reasoning would suggest that unsaturated precursors with constrained flexibility and selectivity based on cis/trans isomers could be the missing link between the prochiral-acyclic and chiral-cyclic structures mentioned above. We find that ene-nucleic acids derived from an isoprenoid skeleton possess requisite flexibility and rigidity while forming stable duplex structures with complementary DNA and RNA.

Engineering ligands on the Au center: discovering broadly applicable gold catalysis with high turnover numbers - Inamdar, Suleman M.; Patil, Nitin T. (Organic Chemistry Frontiers, 2015)
The research groups of Hammond/Xu and Zhang report the discovery of new ligands for gold catalysis. With these ligands, gold catalyzed reactions have been reported for a broader range of substrates with very high TONs at a level that can match the needs of large-scale applications.

Engineering proteins for thermostability with iRDP web server - Panigrahi, Priyabrata; Sule, Manas; Ghanate, Avinash; Ramasamy, Sureshkumar; Suresh, C. G. (Plos One, 2015)
Engineering protein molecules with desired structure and biological functions has been an elusive goal. Development of industrially viable proteins with improved properties such as stability, catalytic activity and altered specificity by modifying the structure of an existing protein has widely been targeted through rational protein engineering. Although a range of factors contributing to thermal stability have been identified and widely researched, the in silico implementation of these as strategies directed towards enhancement of protein stability has not yet been explored extensively. A wide range of structural analysis tools is currently available for in silico protein engineering. However these tools concentrate on only a limited number of factors or individual protein structures, resulting in cumbersome and time-consuming analysis. The iRDP web server presented here provides a unified platform comprising of iCAPS, iStability and iMutants modules. Each module addresses different facets of effective rational engineering of proteins aiming towards enhanced stability. While iCAPS aids in selection of target protein based on factors contributing to structural stability, iStability uniquely offers in silico implementation of known thermostabilization strategies in proteins for identification and stability prediction of potential stabilizing mutation sites. iMutants aims to assess mutants based on changes in local interaction network and degree of residue conservation at the mutation sites. Each module was validated using an extensively diverse dataset. The server is freely accessible at http://irdp.ncl.res.in and has no login requirements.

Enhanced carbon dioxide hydrate formation kinetics in a fixed bed reactor filled with metallic packing - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Chemical Engineering Science, 2015)

Enhanced electron field emission from NiCo2O4 nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Materials Research Express, 2015)
Electron emission properties of electrodeposited spinel NiCo2O4 nanosheet arrays grown on Ni foam have been studied. The work function of NiCo2O4 was calculated by density functional theory using the plane-wave basis set and used to estimate the field enhancement factor. The NiCo2O4 nanosheet arrays exhibited a low turn-on field of 1.86 V mu m(-1) at 1 mu A cm(-2) and current density of 686 mu A cm(-2) at 3.2 V mu m(-1), with field enhancement factor beta = 1460 and good field emission current stability. The field emission properties of the NiCo2O4 nanosheet arrays showed enhanced performance compared to chemically prepared NiCo2O4 nanosheets. Hence, the nanosheet arrays have great potential as robust high performance vertical structure electron emitters for future flat panel displays and vacuum electronic device applications.
Keywords: Density functional theory; field emission; nanosheets; NiCo2O4; spinel

Enhanced field emission of plasma treated multilayer graphene - Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2015)
Electron emission properties of multilayer graphene (MLG) prepared by a facile exfoliation technique have been studied. Effect of CO2 Ar, N-2, plasma treatment was studied using Raman spectroscopy and investigated for field emission based application. The CO2 plasma treated multilayer graphene shows an enhanced field emission behavior with a low turn on field of 0.18 V/mu m and high emission current density of 1.89 mA/cm(2) at an applied field of 0.35 V/mu m. Further the plasma treated MLG exhibits excellent current stability at a lower and higher emission current value. (C) 2015 AIP Publishing LLC.

Enhancing efficiency of perovskite solar cell via surface microstructuring: superior grain growth and light harvesting effect - Tathavadekar, Mukta C.; Agarkar, Shruti A.; Game, Onkar S.; Bansode, Umesh P.; Kulkarni, Sneha A.; Mhaisalkar, Subodh G.; Ogale, Satishchandra B. (Solar Energy, 2015)
We have introduced a novel approach to enhance the perovskite solar cell efficiency by controlling the grain growth and light harvesting properties of perovskite crystallites. Instead of using a mesoporous TiO2 layer, we have modified the surface microstructuring of the TiO2 film by dispensing nano assembled TiO2 submicron structures (nanobeads, NBs) on TiO2 compact layer. With this new approach solar cell efficiency was improved significantly through an increase in both J(sc) and V-oc. This high efficiency is attributed to crystallite size of the perovskite phase. These also act as light scattering centers giving higher current density and reduced recombination effects giving higher open circuit voltage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grain growth; Light harvesting; Perovskite solar cells; TiO2 nanobeads

Environmentally benign catalytic process for esterification of renewable levulinic acid to various alkyl levulinates biodiesel - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2015)
This study explores, the use of modified zeolite (Micro/Meso-HZ-5) obtained by desilication post-treatment as heterogeneous catalyst for esterification of biomass derived renewable levulinic acid (LA) with different alkyl alcohols such as methanol, ethanol, n-butanol, and n-octanol aiming to produce corresponding alkyl levulinate. This method of production of alkyl levulinates would be sustainable process, as it can be used as novel miscible diesel biofuels preventing global warming by decreasing atmospheric CO2. The LA conversion obtained over Micro/Meso-HZ-5 was higher than H-ZSM-5, which is due to the combined effect of increase in Bronsted acid sites, total acidity, and other properties such as BET surface area and the generation of mesoporosity. The maximum LA conversion of 91, 95, 96, and 98% with 100% selectivity toward alkyl levulinate was obtained, when LA was being esterified over Micro/Meso-HZ-5 with methanol, ethanol, n-butanol, and n-octanol, respectively, at optimal process parameters. Micro/Meso-HZ-5 catalyst was found to be reusable for six cycles. Furthermore, pseudo homogeneous (P-H) kinetic model of the esterification of LA with the studied four alcohols were established with R-2>0.99, using the experimental data. A P-H kinetic model implies that, the esterification reaction follows second order reversible kinetics. (c) 2014 American Institute of Chemical Engineers Environ Prog, 34: 795-801, 2015
Keywords: biofuels; Esterification; kinetic model; levulinic acid; meso-HZ-5; micro

Environmentally friendly route for grafting of molybdenum carbonyl onto a diaminosilane-modified SBA-15 molecular sieve and its catalytic behaviour in olefin epoxidation - Baskaran, Thangaraj; Kumaravel, Raju; Christopher, Jayaraj; Ajithkumar, Thalasseril G.; Sakthivel, Ayyamperumal (New Journal of Chemistry, 2015)
A simple route has been established for grafting molybdenum carbonyl onto the surface of a diaminosilane-modified SBA-15 molecular sieve. The successful grafting of the molybdenum carbonyl species onto diamine-functionalized SBA-15 was evident from FT-IR studies. The resultant molybdenum-carbonyl-complex-grafted SBA-15 (SBA-DA-Mo) materials show promising activity for the epoxidation of various olefins with good conversion (90-95%) and the formation of epoxide as the major product. The catalytic activity remains constant over several runs.

EOMIP-CCSD(2)*: an efficient method for the calculation of ionization potentials - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2015)
A new approximation within the domain of EOMIP-CC method is proposed. The proposed scheme is based on the perturbative truncation of the similarity transformed effective Hamiltonian matrix. We call it the EOMIP-CCSD(2)* method, which scales as noniterative N-6 and its storage requirement is very less, compared to the conventional EOMIP-CCSD method. The existing EOMIP-CCSD(2) method has a tendency to overestimate the ionization potential (IP) values. On the other hand, our new strategy corrects for the problem of such an overestimation, which is evident from the excellent agreement achieved with the experimental values. Furthermore, not only the ionization potential but also geometry and IR frequencies of problematic double radicals are estimated correctly, and the results are comparable to the CCSD(T) method, obviously at lesser computational cost. The EOMIP-CCSD(2)* method works even for the core ionization and satellite IP, where the earlier EOMIP-CCSD(2) approximation dramatically fails.

Esterification of renewable levulinic acid to n-butyl levulinate over modified H-ZSM-5 - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Chemical Engineering & Technology, 2015)
The synthesis of n-butyl levulinate, one of the most important biodiesel additives, by catalytic esterification of biomass-derived levulinic acid (LA) with n-butanol over modified H-ZSM-5 (micro/meso-HZ-5) in a closed-batch system is reported for the first time. The optimization of the reaction conditions such as the reactant molar ratio, the catalyst loading, the reaction time and the temperature was performed in view to maximize the yield of n-butyl levulinate. Micro/meso-HZ-5 was found to be the most efficient catalyst, with 98% yield of n-butyl levulinate and a reusability for six cycles, which is higher than reported in the literature. A possible catalytic mechanism for the esterification reaction is also proposed. A second-order pseudo-homogeneous model with R-2 > 0.97 confirmed that the esterification reaction is performed in the kinetic regime due to the high activation energy of 23.84 kJ mol(-1).
Keywords: Esterification; kinetic model; levulinic acid; Micro/meso-HZ-5; n-Butyl levulinate

Evaluation of imidazolium-based ionic liquids towards vermicidal activity: in vitro & in silico studies - Charan, K. T. Prabhu; Ranjan, Prabodh; Manojkumar, Kasina; Pothanagandhi, Nellepalli; Jha, Prakash C.; Khedkar, Vijay M.; Sivaramakrishna, Akella; Vijayakrishna, Kari (RSC Advances, 2015)
A series of six different ionic liquids (ILs) of the kind 1-alkyl-3-methylimidazolium bromide/hydroxide (IL-Br and IL-OH) tailored with different N-alkyl side chains (ethyl, butyl, octyl) were synthesized and evaluated for their vermicidal activity against the Indian earthworm, Pheretima posthuma. The percentage of paralysis and mortality of earthworms against ILs were recorded in a dose dependent (at different concentrations 2, 4, 8 and 16 mM) and time dependent manner. The ILs with hydroxide as the counter anion (IL-OH) showed higher vermicidal activity compared to their bromide counterparts (IL-Br). Moreover, the ILs with the longest alkyl chain (octyl) were observed to have significant vermicidal activity compared to the rest (ethyl and butyl) as well as the standard drug, Albendazole. Furthermore, theoretical modeling was carried out to visualize the preferential docking positions of these ILs into the active site of beta-tubulin. Fascinatingly, it was found that the ILs with longest alkyl side chain showed remarkable vermicidal activity compared to the rest, and the molecular docking studies not only validated the experimental results, but also showed per-residue interaction analysis between the ILs and the different components of beta-tubulin.

Exfoliation of bulk inorganic layered materials into nanosheets by the rapid quenching method and their electrochemical performance - Chakravarty, Disha; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report herein the results of our investigations on the synthesis of transition-metal dichalcogenide (TMDC) semiconductor layered materials of MoS2, WS2, MoSe2, and WSe2 by the rapid quenching method. The bulk powders were added to deionized water in a polypropylene tube and subsequently flushed with argon gas. Thirty rapid freezing (30 s in a liquid nitrogen bath) and heating (20 min in an oil bath at 60 degrees C) cycles were then carried out. The reaction product was obtained in a yield in excess of 60 wt.-%, which indicates that the method can be utilized on an industrial scale for the production of 2D nanosheets. The as-synthesized products were then characterized by TEM, which revealed nanosheet-like morphologies. Raman spectroscopy confirmed the high quality of the nanosheet samples. The exfoliated samples also showed good electrochemical performance. Of the TMDC samples investigated, the WSe2 nanosheets were found to give the best performance due to their uniform morphology, large surface area, and fewest number of defects.
Keywords: chalcogenides; Electrochemistry; Layered compounds; Molybdenum; Nanostructures; Tungsten

Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).

Experimental signature of microheterogeneity in ionic liquid-H2O systems and their perturbation by adding Li+ salts: a pulsed gradient spin-echo NMR approach - Nanda, Raju; Rajamohanan, P. R.; Kumar, Anil (Chemphyschem, 2015)
Distinct microheterogeneity has been observed in the [OMIM]Br-H2O system, which is interestingly perturbed by the addition of Li+ salts, indicating unusual diffusivity of [OMIM]Br and H2O molecules. However, the diffusional dynamics of water clusters show contrasting salting behavior at higher concentrations of Li+ salts, following the classical salting phenomenon in lower amounts. In contrast, the existing microheterogeneity in the [BMIM]Br-H2O system is weak enough to show any perturbation caused by the Li+ salts on the NMR time scale.
Keywords: ionic liquids; lithium; microheterogeneity; salt effect; viscosity

Exploiting powder x-ray diffraction to establish the solvent-assisted solid-state supramolecular assembly of pillar[5]quinone - Shivakumar, Kilingaru I.; Yan, Yuncheng; Hughes, Colan E.; Apperley, David C.; Harris, Kenneth D. M.; Sanjayan, Gangadhar J. (Crystal Growth & Design, 2015)
We report the solvent-mediated supramolecular assembly of pillar[5]quinone (P[5]Q), a symmetric cyclamer containing five benzoquinone moieties bridged by five alternating methylene units. The supramolecular assembly of P[5]Q is shown to be facilitated by 1,1,2,2-tetrachloroethane (TCE) as solvent, producing a microcrystalline solvate material P[5]Q(.)2TCE with a fluffy texture. Optical and electron microscopy reveal that this material has a rod-shaped morphology, extending to several micrometers in length. Due to the microcrystalline nature of the material, structure determination was carried out directly from powder X-ray diffraction data, augmented by high-resolution solid-state C-13 NMR. The two crystallographically distinct TCE molecules occupy different types of void in the structure and have different dynamic properties. Crystallization of P[5]Q was attempted from a large number of different solvents, but only TCE was found to facilitate the formation of a crystalline phase. Indeed, features of the crystal structure suggest that the TCE component plays an important role in promoting the columnar assembly of P[5]Q molecules.

Exploring microstructural changes in structural analogues of ibuprofen-hosted in situ gelling system and its influence on pharmaceutical performance - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (AAPS Pharmscitech, 2015)
The present work explores inner structuration of in situ gelling system consisting of glyceryl monooleate (GMO) and oleic acid (OA). The system under study involves investigation of microstructural changes which are believed to govern the pharmaceutical performance of final formulation. The changes which are often termed mesophasic transformation were analysed by small angle Xray scattering (SAXS), differential scanning calorimetry (DSC), rheology and plane polarised light (PPL) microscopy. The current work revealed transformation of blank system from W/O emulsion to reverse hexagonal structure upon addition of structural analogues of ibuprofen. Such transformations are believed to occur due to increased hydrophobic volume within system as probed by SAXS analysis. The findings of SAXS studies were well supported by DSC, rheology and PPL microscopy. The study established inverse relationship between log P value of structural analogues of ibuprofen and the degree of binding of water molecules to surfactant chains. Such relationship had pronounced effect on sol-gel transformation process. The prepared in situ gelling system showed sustained drug release which followed Higuchi model.
Keywords: flurbiprofen; hexagonal phase; ibuprofen; ketoprofen; liquid crystal; sustained drug release

Exploring the differences in metabolic behavior of astrocyte and glioblastoma: a flux balance analysis approach - Bhowmick, Rupa; Subramanian, Abhishek; Sarkar, Ram Rup (Systems and Synthetic Biology, 2015)

Expression of stable reference genes and SPINDLY gene in response to gibberellic acid application at different stages of grapevine development - Upadhyay, A.; Jogaiah, S.; Maske, S. R.; Kadoo, Narendra Y.; Gupta, V. S. (Biologia Plantarum, 2015)
Gibberellic acid (GA(3)) is widely used at different stages of berry development, and to understand the molecular mechanism of its action requires identification of stable reference genes. We sprayed grapevine (Vitis vinifera L.) cv. Thompson Seedless with GA(3) at rachis stage for rachis elongation, at flower cluster stage for flower thinning, and at 3 - 4 mm berry stage for berry elongation. Tissue samples were collected at different time points after GA(3) application. The expression of 10 candidate reference genes was analyzed using 4 different algorithms to assess their suitability for real time-PCR data normalization. Based on the overall ranking, PP2A, Sutra, and SAND were identified as the most stably expressed genes across all samples. With regard to different stages, tubulin, EF1 alpha, and UBC were the most stable genes during rachis elongation; PP2A, SAND, and Sutra were the most suitable at the flower cluster and berry stages. The expression of GA signaling gene SPINDLY (VvSpy) was analyzed to validate the stable reference genes. After the GA(3) application, the expression of VvSpy was reduced at the rachis stage but did not change at the flower cluster and berry stages. The expression profile of VvSpy was comparable when two or three reference genes were used for data normalization.
Keywords: developmental stages; Vitis vinifera

Extrusion film casting of long chain branched polypropylene - Chikhalikar, Kalyani; Banik, Sourya; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Doshi, Pankaj; Pol, Harshawardhan; Lele, Ashish K. (Polymer Engineering and Science, 2015)
Extrusion film casting (EFC) is an important melt processing operation which is extensively used to make polypropylene (PP) films. Linear PP shows significant amount of necking and draw resonance during EFC. One of the ways to reduce necking is to introduce long chain branches (LCB) on the polymer backbone. The long branches impart extensional strain hardening behavior thereby stabilizing the melt flow. In this work, we investigate the influence of long chain branching in polypropylene on the extent of necking in the EFC process. Laboratory scale EFC experiments were performed on homopolymer PP of linear and long chain branched architectures. Simulations of the EFC process were carried out using the one-dimensional flow model of Silagy et al., Polym. Eng. Sci.,36, 2614 (1996) into which we incorporate two different multi-mode molecular constitutive equations namely, the eXtended Pom-Pom' equation (XPP, for long chain branched PP) and the Rolie-Poly' equation (RP-S, for linear PP). Our experimental data confirm that presence of long chain branching in PP reduces the extent of necking and our numerical predictions show qualitative agreement with experimental data, thereby elucidating the role of chain architecture on the extent of necking. POLYM. ENG. SCI., 55:1977-1987, 2015. (c) 2014 Society of Plastics Engineers

Earth abundant iron-rich N-doped graphene based spacer and cavity materials for surface plasmon-coupled emission enhancements - Srinivasan, Venkatesh; Vernekar, Dnyanesh; Jaiswal, Garima; Jagadeesan, Dinesh; Ramamurthy, Sai Sathish (ACS Applied Materials & Interfaces, 2016)
We demonstrate for the first time the use of Fe based nanoparticles on N-doped graphene as spacer and cavity materials and study their plasmonic effect on the spontaneous emission of a radiating dipole. Fe-C-MF was produced by pyrolizing FeOOH and melamine formaldehyde precursor on graphene, while Fe-C-PH was produced by pyrolizing the Fe-phenanthroline complex on graphene. The use of the Fe-C-MF composite consisting of Fe-rich crystalline phases supported on N-doped graphene presented a spacer material with 116-fold fluorescence enhancements. On the other hand, the Fe-C-PH/Ag based cavity resulted in an 82-fold enhancement in Surface Plasmon-Coupled Emission (SPCE), with high directionality and polarization of Rhodamine 6G (Rh6G) emission owing to Casimir and Purcell effects. The use of a mobile phone as a cost-effective fluorescence detection device in the present work opens up a flexible perspective for the study of different nanomaterials as tunable substrates in cavity mode and spacer applications.
Keywords: Casimir effect; fluorescence enhancements; iron carbides; N-doped graphene; Purcell factor; surface plasmon-coupled emission

Editorial: actinobacteria in special and extreme habitats: diversity, function roles, and environmental adaptations - Qin, Sheng; Li, Wen-Jun; Dastager, Syed Gulam; Hozzein, Wael N. (Frontiers in Microbiology, 2016)
Keywords: actinobacteria; activities; diversity; environmental adaptation; omics technologies; special and extreme environments

Effect of additives on formation and decomposition kinetics of methane clathrate hydrates: application in energy storage and transportation - Kumar, Asheesh; Kushwaha, Omkar Singh; Rangsunvigit, Pramoch; Linga, Praveen; Kumar, Rajnish (Canadian Journal of Chemical Engineering, 2016)
Methane gas storage and transportation via clathrate hydrates is proposed to be a potential solution for large-scale energy storage. In this work, we study the formation and decomposition kinetics of methane hydrates (MH) in a laboratory-scale unstirred crystallizer. The present investigation demonstrates comparative studies of hydrate formation and dissociation kinetics in the presence of tetrahydrofuran (55.6 and 27.8mmol/mol, 5.56 and 2.78mol% THF) and sodium dodecyl sulphate (1mg/g, 0.1wt% SDS). Moreover, the storage capacity and hydrate formation kinetics in both the systems are discussed. In a recent work, enhanced methane hydrate growth in the presence of THF at close to atmospheric conditions was demonstrated. The emphasis of the current work is to study the stability of hydrates to understand dissociation kinetics by measuring the rate of hydrate decomposition at different temperatures. Hydrate stability measurements were performed at -8, -3, 2, 10, and 20 degrees C to study the decomposition rates of MH and self-preservation in presence of the two additives THF and SDS.

Effect of different fixed bed media on the performance of sodium dodecyl sulfate for hydrate based CO2 capture - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Kumar, Pushpendra; Balomajumder, Chandrajit (Materials & Design, 2016)
Sodium Dodecyl Sulfate (SDS) is used as a kinetic promoter in gas hydrate formation. In this work, the performance of SDS for carbon dioxide gas hydrate formation in two different fixed bed media: silica sand and zeolite (5A and 13X) has been evaluated. The concentration of SDS was fixed at 0.5 wt%. The experiments were carried out in batch mode with the initial pressure fixed at 3.0 MPa, and the temperature kept constant at 274.65 K. The results showed that hydrate of carbon dioxide with fixed bed of silica sand was significantly promoted by the addition of SDS as compared to the other fixed bed medium used in this study: zeolite 13X. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide; Fixed bed media; Hydrate formation; Kinetic promoter; Silica sand; Zeolite 5A and 13X

Effect of different temperature on structural, magnetic and dielectric properties of strontium hexaferrite powder synthesised using aloe vera plant extracts - Solanki, Neha; Jotania, R. B.; Khomane, Ramdas B.; Kulkarni, B. D. (Advanced Science Letters, 2016)
M-type SrFe12O19 hexaferrite particles synthesized using the aloe vera plant extract. Biological materials of microorganisms, plants, enzymes have been suggested as an ecological alternative for conventional reagents in physical and chemical methods. In present paper we report effect of temperature on structural, morphology, magnetic and dielectric properties of M-type SrFe12O19 particles synthesised by Green synthesis technique using Aloe vera plant extract. The metal nitrates (Sr and Fe) were dissolved in aloe vera extract solution and then mixture was kept in oil bath at 100 degrees C till it become dry. The obtain dried powder calcined in a wide temperature range, from 450 degrees C to 1150 degrees C for 4 hours in a static air atmosphere. The calcined powders were characterised using various instrumental techniques like Fourier transform infrared spectroscopy (FTIR) X-ray diffractometry (XRD), Scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), Vibrating Sample Magnetometry (VSM), and dielectric measurements. XRD, FTIR, SEM, Magnetic and dielectric measurements were carried out at room temperature. XRD analysis confirms the formation of mono phase of strontium hexaferrite at 1150 degrees C.
Keywords: Aloe Vera Extract; green synthesis; M-Type Hexaferrite; Strontium Hexaferrite

Effect of donors on the activation mechanism in ziegler-natta catalysis: a computational study - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (Chemcatchem, 2016)
Full quantum chemical calculations, using density functional theory (DFT), have been conducted to explain the effect of donors on the ``activation mechanism'' in the Ziegler-Natta (Z-N) catalyst system. In the activation mechanism, the inactive (TiCl4)-Cl-IV catalyst converts into the active (TiCl2Et)-Cl-III catalyst with the help of the AlEt3 present in the system. The donors that have been considered in this study are: ethyl benzoate (eb), two representative diether cases, a phthalate donor, and a silyl ester donor. The results indicate that eb and the diether donor cases donor have a negative effect on the barriers for the activation mechanism. However, the eb donor can be displaced from the MgCl2 surface by AlEt3, which matches experimental observations. For the phthalate, silyl ester and TiCl3-OC4H8Cl cases, the results indicate that a significant induction period would be present in Z-N systems employing such donors or having such a catalytic center, before catalysis could commence.
Keywords: Alkylation; aluminum; Density functional calculations; surface chemistry; titanium

Effect of heterocycles on field-effect transistor performances of donor-acceptor-donor type small molecules - Chini, Mrinmoy Kumar; Mahale, Rajashree Y.; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
Two D-A-D small molecules comprising triphenylamine and diketopyrrolopyrrole were synthesized having either furan or thiophene connected to the fused lactam ring. In this design, furan/thiophene diketopyrrolopyrrole acts as an acceptor and triphenylamine acts as a donor. Propeller shaped triphenylamine has its effect on packing, processability and plays a vital role in determining the pi-pi molecular orbital stacking in such compounds and thus the mobility of charge carriers. With TDPPT and FDPPT, maximum hole carrier mobility obtained is 2.88 x 10(-3) cm(2) V-1 s(-1) and 1.60 x 10(-3) cm(2) V-1 s(-1), respectively using bottom gate bottom contact field-effect transistor. (C) 2016 Elsevier B.V. All rights reserved.

Effect of mixed acid catalysis on pretreatment and enzymatic digestibility of sugar cane bagasse - Pal, Siddhartha; Joy, Shereena; Kumbhar, Pramod; Trimukhe, K. D.; Varma, Anjanikumar; Padmanabhan, Sasisanker (Energy & Fuels, 2016)
Aqueous pretreatment using homogeneous acid catalyst is considered as a low-cost technology in the production of lignocellulosic bioethanol. To establish the synergism of mixed acids, pilot-level aqueous pretreatments of bagasse covering a wide range of combined severity (CS) were carried out. To investigate the effect of application of mixture of acids on xylose hydrolysis as well as glucose hydrolysis via pretreatment and enzymatic hydrolysis, the following three combinations of acids were explored: (1) oxalic acid + sulfuric acid (organic + mineral acid), (2) phosphoric + sulfuric acid (mineral acids), and (3) ferric chloride + sulfuric acid (Lewis acid with a mineral acid). Of the pretreatments evaluated, the synergism was most pronounced for the combination of sulfuric and phosphoric acid, which resulted in more than 90% conversion of hemicellulose to xylose and 70% conversion of cellulose to glucose through enzymatic hydrolysis. Fourier transform infrared (FTIR) studies of pretreated samples showed higher syringyl/guaiacyl (S/G) ratio for sulfuric and phosphoric acid combination pretreatment, leading to higher enzymatic conversion. FTIR and dynamic light scattering (DLS) experiments conducted on pretreated sugar cane bagasse provided useful correlation with regard to the pretreatment type, particle size, and enzymatic hydrolysis.

Effect of number of branches on the performance of fractal impeller in a stirred tank: mixing and hydrodynamics - Mule, Gunwant M.; Lohia, Rajat; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2016)
Number of blades of an impeller, impeller design and its positioning in a stirred tank is known to affect the mixing in a stirred tank reactor. The extent of non-uniformity in mixing from conventional impellers can be reduced significantly using a space-filling impeller like a fractal impeller. In this work, we report the effect of number of branches (and hence the number of blades) of fractal impeller on power consumption, mixing and hydrodynamics. Velocity measurements were carried out using ultrasonic velocity profiler (UVP). Measurements showed that the performance of fractal impeller with different configuration is equivalent, however, better than standard impellers in terms of mixing achieved per unit power consumption. No significant difference was observed in radial and axial mean velocity profiles for three different configurations. However, the tangential velocity was found higher for four branches than two and three branches FL Two distinct circulation loops were observed in upper as well as lower half of the vessel in r-z plane. Strong tangential flow throughout the baffled vessel helps to achieve good mixing even at low rotational speeds. (C) 2016 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Fractal impeller; Number of branches; UVP; Tangential velocity; Mixing

Effect of orifice shape on water disinfection efficacy - Gaikwad, V.; Gaikwad, S.; Ranade, V. (Pollution Research, 2016)
Hydrodynamic cavitation offers distinct advantages for water disinfection and waste watei treatment particularly at large scales of operations. For applying hydrodynamic cavitation foi water disinfection/treatment, water stream to be treated is passed through a fluidic device ir which there exists a low pressure region. Cavities are generated in this region when the pressurt falls below vapour pressure (in absence of any dissolved gases). These cavities are then collapsec when they travel to regions of higher pressure and lead to very high shear, temperatures anc pressures in localized regions. These high pressure/temperature as well as high shear facilitati disinfection as well as reduction in chemical oxygen demand, colour and amonical nitrogen in the water. In this work, we have investigated hydrodynamic cavitation generated by five difieren orifices have been studied which have different shapes with same fractional open area and have tested their effectiveness for water disinfection. The efficacy of generated cavitation on wate disinfection was quantified based on measurements of non-pathogenic E. coli colony forminj units (CFU/mL). The presented results and analysis will be useful for designing hydrodynamii cavitation based systems for water disinfection

Effect of out-of-plane alkyl group's position in dye-sensitized solar cell efficiency: a structure-property relationship utilizing indoline-based unsymmetrical squaraine dyes - Alagumalai, Ananthan; Fairoos, Munavvar M. K.; Vellimalai, Punitharasu; Sil, Manik Chandra; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2016)
Squaraine dyes are promising chromophores to harvest visible and near-infrared (NIR) photons. A series of indoline-based unsymmetrical squaraine (SQ) dyes that contain alkyl chains at sp(3) C- and N- atoms of indoline moieties with a carboxylic acid anchoring group were synthesized. The optical and electrochemical properties of the SQ dyes in solution were nearly identical as there was no change in the D-A-D SQ framework; however, remarkable changes with respect to the power conversion efficiencies (PCE) were observed depending upon the position of alkyl groups in the dye. Introduction of alkyl groups to the indoline unit that was away from anchoring unit were helped in more dye loading with controlled organization of dyes on surface, increased charge transfer resistance, long electron lifetime, and hence higher PCE than that of the corresponding isomer in which the alkyl groups funtionalized indoline unit contains the carboxylic acid anchoring group. Careful analysis of incident photon-to current conversion efficiency (IPCE) profiles indicated the presence of aggregated structure on the TiO2 surface that contributes to the charge injection in the presence of a coadsorbent. A dye-sensitized solar cell (DSSC) device made out of SQ5 was achieved an efficiency of 9.0%, with an open-circuit potential (V-oc) of 660 mV and short-circuit current density (J(sc)) of 19.82 mA/cm 2, under simulated AM 1.5G illumination (100 mW/cm(2)). The IPCE profile of SQ5 shows an onset near to 750 nm with a good quantum efficiency (>80%) in the range of 550-700 nm, indicating the importance of self-organization of dyes on the TiO2 surface for an efficient charge injection. This present investigation revealed the importance of position of alkyl groups in the squaraine-based dyes for the better PCE.

Effect of plasma treatment on multilayer graphene: X-ray photoelectron spectroscopy, surface morphology investigations and work function measurements - Patil, Urmila V.; Pawbake, Amit S.; Machuno, Luis G. B.; Gelamo, Rogerio V.; Jadkar, Sandesh R.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report here the effect of plasma treatment on multilayer graphene samples as determined by X-ray photoelectron spectroscopy and surface morphology studies with atomic force microscopy, scanning electron microscopy and transmission electron microscopy. The plasma treatment was modified to introduce controlled levels of defects and functionalities to the graphene samples to give tunable properties. The elemental composition and structure were investigated by XPS and micro Raman spectroscopy. The XPS study showed that there was a slight variation in the sp(2)/sp(3) hybridization ratio between the plasma-treated samples and the pristine sample. Kelvin probe measurements were carried out on all the multilayer graphene samples and indicated a slight variation in the work function of the graphene samples after plasma treatment.

Effect of plug temperature on the strain and thickness distribution ofcomponents made by plug assist thermoforming - Marathe, D.; Rokade, D.; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Gupta, S.; Kulkarni, S.; Juvekar, Vinay A.; Lele, Ashish K. (International Polymer Processing, 2016)
Plug temperature is a key parameter affecting the thickness distribution of thermoplastic components made by plug assist thermoforming. For a specified pair of plug and plastic sheet, the variation in plug temperature can alter the coefficient of friction (COF) between the pair. We show here how the temperature dependence of COF influences the nature and extent of biaxial stretching of the sheet and consequently the thickness distribution of the thermoformed component. In the present study, high impact polystyrene (HIPS) sheets were thermoformed into axisymmetric cups using a plug-assist process in which the aluminum plug temperature (T-plug) was varied from ambient to above the glass transition temperature of HIPS (similar to 100 degrees C). Biaxial strain maps on the surfaces of the formed cups were measured and quantified using Grid Strain Analysis (GSA). Thickness distributions of the cups were also measured. Temperature dependent COF between HIPS and aluminum was determined independently using a rotational rheometer. The measured COF was low for T < 100 degrees C, whereas it increased appreciably at and above 100 degrees C. We conclude that when T-plug < 100 degrees C the HIPS sheet slips on the plug during forming, and this results in biaxial stretching of the base and walls of the formed cup. In contrast for T-plug > 100 degrees C, a significant reduction in the magnitude of slip is expected. Here the sheet is gripped at the clamp and by the plug during forming which causes reduced biaxial stretching of the base and increased uniaxial stretching of the walls of the cup. Simulations of plug-assist thermoforming using a temperature dependent COF showed qualitative agreement with the GSA data thereby supporting our inferences.

Effect of polyvinylpyrrolidone at methane hydrate-liquid water interface. application in flow assurance and natural gas hydrate exploitation - Choudhary, Nilesh; Das, Subhadip; Roy, Sudip; Kumar, Rajnish (Fuel, 2016)

Effect of process intensifying parameters on the hydrodynamic cavitation based degradation of commercial pesticide (methomyl) in the aqueous solution - Raut-Jadhav, Sunita; Saini, Daulat; Sonawane, Shirish; Pandit, Aniruddha (Ultrasonics Sonochemistry, 2016)
Methomyl, a carbamate pesticide, is classified as a pesticide of category-1 toxicity and hence shows harmful effects on both human and aquatic life. In the present work, the degradation of methomyl has been studied by using hydrodynamic cavitation reactor (HC) and its combination with intensifying agents such as H2O2, fenton reagent and ozone (hybrid processes). Initially, the optimization of operating parameters such pH and inlet pressure to the cavitating device (circular venturi) has been carried out for maximizing the efficacy of hydrodynamic cavitation. Further degradation study of methomyl by the application of hybrid processes was carried out at an optimal pH of 2.5 and the optimal inlet pressure of 5 bar. Significant synergetic effect has been observed in case of all the hybrid processes studied. Synergetic coefficient of 5.8, 13.41 and 47.6 has been obtained by combining hydrodynamic cavitation with H2O2, fenton process and ozone respectively. Efficacy of individual and hybrid processes has also been obtained in terms of energy efficiency and extent of mineralization. HC + Ozone process has proved to be the most effective process having highest synergetic coefficient, energy efficiency and the extent of mineralization. The study has also encompassed the identification of intermediate by-products generated during the degradation and has proposed the probable degradation pathway. It has been conclusively established that hydrodynamic cavitation in the presence of intensifying agents can effectively be used for complete degradation of methomyl. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Advanced Oxidation Processes (AOPs); Hydrodynamic cavitation; Methomyl; Synergetic coefficient; Venturi

Effect of sequence on the ionization of guanine in DNA - Chakraborty, Rahul; Ghosh, Debashree (Physical Chemistry Chemical Physics, 2016)
The accurate estimation of the ionization energies and understanding the nature of the ionized states of the nucleic acid bases (NABs) are crucial to the understanding of the DNA damage mechanism. The vertical ionization energy (VIE) of guanine is the lowest among the NABs and the ionization energies are strongly affected by the environment, such as solvation and characteristics of nearby NABs. Therefore, we investigate the sequence dependence of the VIEs of guanine in B-DNA. We use the equation of motion coupled cluster method for the estimation of ionization potential with single and double excitations (EOM-IP-CCSD) and density functional theory with dispersion corrected omega B97x-D for the estimation of VIEs. A significant amount of non-additivity or cooperativity, directly proportional to charge delocalization, is noticed in the change in VIE due to the interaction with the nearby NABs. While the change in VIE due to base pairing originates predominantly from charge-dipole interactions, stacking between base pairs is a more complicated balance of dispersion and charge-dipole interactions as well as stabilization due to the delocalization of the positive charge. The long range interactions are however dominated by 1/r(3) distance dependence which shows the major role played by charge-dipole interactions. The extent of localization of positive holes on guanine is also estimated for various sequences.

Effect of sintering temperature and vinca petals extract on structural and magnetic properties of delafossite CuFeO2 - Dhruv, Preksha N.; Solanki, Neha; Kulkarni, Shailja; Jotania, R. B. (International Conference On Condensed Matter and Applied Physics (ICC 2015), 2016)
Delathssite CuFeO2, multi ferroic powder was synthesized using Sol-Gel auto combustion method. Influence of vinea flower petals extract on structural and magnetic properly of CuFeO2 were investigated. X-ray analysis of normal samples (synthesized without presence of vinca petals extract) shows formation of hematite and ferrite phases while the sample synthesized in presence of vinca petals extract show only mono phase. The absorption bands in FTIR spectra present between 510-460 cm(-1)in both the samples are due to stretching of Fe-O vibrations. VSM analysis shows that the squareness ratio (Mr/Ms) of the sample prepared using vinca petals extract obtains value of squareness ratio <0.5, which attributes multi domain formation of samples.

Effect of solvation on electron detachment and excitation energies of a green fluorescent protein chromophore variant - Bose, Samik; Chakrabarty, Suman; Ghosh, Debashree (Journal of Physical Chemistry B, 2016)
Hybrid quantum mechanics/molecular mechanics (QM/MM) is applied to the fluorinated green fluorescent protein (GFP) chromophore (DFHBDI) in its deprotonated form to understand the solvatochromic shifts in its vertical detachment energy (VDE) and vertical excitation energy (VEE). This variant of the GFP chromophore becomes fluorescent in an RNA environment and has a wide range of applications in biomedical and biochemical fields. From microsolvation studies, we benchmark (with respect to full QM) the accuracy of our QM/MM calculations with effective fragment potential (EFP) as the MM method of choice. We show that while the solvatochromic shift in the VEE is minimal (0.1 eV blue shift) and its polarization component is only 0.03 eV, the effect of the solvent on the VDE is quite large (3.85 eV). We also show by accurate calculations on the solvatochromic shift of the VDE that polarization accounts for similar to 0.23 eV and therefore cannot be neglected. The effect of the counterions on the VDE of the deprotonated chromophore in solvation is studied in detail, and a charge-smearing scheme is suggested for charged chromophores.

Effect of the amino acid L-histidine on methane hydrate growth kinetics - Bhattacharjee, Gaurav; Choudhary, Nilesh; Kumar, Asheesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Natural Gas Science and Engineering, 2016)
In the present study, the effect of a polar amino acid, L-histidine on methane hydrate growth kinetics has been investigated. Methane hydrate formation experiments were carried out in a stirred tank reactor setup at pressure and temperature conditions of 274.15 K and 5.0 MPa respectively. Two different concentrations (0.1 and 1 wt %) of L-histidine were studied. Hydrate growth through molecular dynamic (MD) simulation was also studied; pressure and temperature conditions for the simulations were set at 10.0 MPa and 270.0 K, while the concentration of L-histidine was kept fixed at 0.94 wt %. Hydrate formation runs using MD simulation were carried out with optimal concentration of methane in water. The presence of L-histidine in the system was found to significantly enhance methane hydrate growth kinetics as compared to pure water for both experimental and MD simulation runs. Final gas consumption with 1 wt % L-histidine was found to be comparable to that with 1 wt % SDS, the most commonly used additive for hydrate promotion studies. L-histidine is a benign additive which offers considerable enhancement in methane hydrate formation kinetics and can be utilized for various hydrate based technologies such as methane storage and transport. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Amino acid; Crystal growth; Gas hydrate; kinetics; Molecular dynamic simulation

Effect of total and pair configurational entropy in determining dynamics of supercooled liquids over a range of densities - Banerjee, Atreyee; Nandi, Manoj Kumar; Sastry, Srikanth; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2016)
In this paper, we present a study of supercooled liquids interacting with the Lennard Jones potential and the corresponding purely repulsive (Weeks-Chandler-Andersen) potential, over a range of densities and temperatures, in order to understand the origin of their different dynamics in spite of their structures being similar. Using the configurational entropy as the thermodynamic marker via the Adam Gibbs relation, we show that the difference in the dynamics of these two systems at low temperatures can be explained from thermodynamics. At higher densities both the thermodynamical and dynamical difference between these model systems decrease, which is quantitatively demonstrated in this paper by calculating different parameters. The study also reveals the origin of the difference in pair entropy despite the similarity in the structure. Although the maximum difference in structure is obtained in the partial radial distribution function of the B type of particles, the rdf of AA pairs and AB pairs gives rise to the differences in the entropy and dynamics. This work supports the observation made in an earlier study [A. Banerjee et al., Phys. Rev. Lett. 113, 225701 (2014)] and shows that they are generic in nature, independent of density. Published by AIP Publishing.

Effective and selective oxidation of 2-butanol over Mn supported catalyst systems - Prabu, Kandasamy; Prabu, Marimuthu; Venugopal, Ashok Kumar; Venugopalan, Aswathy Thareparambil; Sandilya, W. V. Y. Sai; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (Applied Catalysis A-General, 2016)
Oxidation of alcohols to their corresponding aldehydes/ketones is an important reaction in industries as well as in academic perspective. Selective oxidation (Selox) of alcohols like methanol, ethanol and propanol are well studied in literature; however, alcohols like butanol, pentanol, octanol is a challenging task. Selective oxidation of 2-butanol to methyl ethyl ketone (MEK) is an important reaction due to its wide range of applications. Herein, we demonstrated the selective oxidation of 2-butanol to MEK over Mn supported on different oxide supports. A series of MnxOy-Al2O3 (MA), MnxOy-CeO2 (MC), MnxOy-ZrO2 (MZ) and MnxOy-SiO2 (MS) catalysts were prepared by co-precipitation followed by hydrothermal method. As synthesised catalysts were characterised by various physico-chemical characterisation techniques. It was found that the presence of Mn3O4 species in MA and MZ catalysts is responsible for maximum catalytic activity towards 2-butanol oxidation. MA catalyst conferred a maximum 2-butanol conversion of 51% and 88% selectivity towards MEK. XPS analysis revealed that Mn in MA catalyst exists in +2 and +3 oxidation states and responsible for 2-butanol oxidation. Moreover it was found that the acidity of the catalyst also plays an important role in catalytic activity. (C) 2016 Published by Elsevier B.V.

Effective noncovalent functionalization of poly(ethylene glycol) to reduced graphene oxidenanosheets through gamma-radiolysis for enhanced lubrication - Gupta, Bhavana; Kumar, Niranjan; Panda, Kalpataru; Melvin, Ambrose A.; Joshi, Shailesh; Dash, Sitaram; Tyagi, Ashok Kumar (Journal of Physical Chemistry C, 2016)
High-quality reduced graphene oxide (rGO) nanosheets (NSs) were synthesized by the oxidation of graphite followed by hydrazine treatment for the reduction of the oxygen functionalities. gamma-Radiolysis was then used for the functionalization of the rGO-NSs with poly(ethylene glycol) 200 (PEG200). The functionalization resulted in the intercalation of PEG200 molecules in rGO through hydrogen bonding between the hydroxyl groups of rGO and the oxygen atoms of PEG200 molecules. This resulted in an increase in the d spacing of the graphene sheets and a decrease in the defect density of the carbon network in the rGO. The friction coefficient and wear of sliding steel surfaces were reduced by 38% and 55%, respectively, when 0.03 mg mL(-1) PEG200-functionalized rGO dispersed in PEG200 was used. The lubrication properties can be described by bipolar interactions between PEG200 and rGO, leading to effective dispersion. Chemical analysis of wear particles showed decomposition of rGO into nanosized graphite domains, as exhibited by mechanical energy produced in tribo-contact. Moreover, these domains formed effective and stable tribofilms on the steel wear tracks that easily sheared under the action of contact stress. This significantly enhanced the antifriction and antiwear properties, resulting in improved oxidation resistance of PEG200 under the tribo-contact. It was found that, at high rGO concentrations, the lubrication efficiency decreased as a result of graphene-graphene intersheet collisions, producing mechanical energy and chemical defects at contact interfaces.

Effects of the benzoxazole group on green fluorescent protein chromophore crystal structure and solid state photophysics - Ghodbane, Abdelhamid; Fellows, W. Brett; Bright, John R.; Ghosh, Debashree; Saffon, Nathalie; Tolbert, Laren M.; Fery-Forgues, Suzanne; Solntsev, Kyril M. (Journal of Materials Chemistry C, 2016)
Four benzoxazole-substituted GFP chromophores that differ by the length of their alkyl chain (from C1 to C12) were synthesized. In solution, the four compounds showed identical spectroscopic behavior, emitting blue light with moderate quantum yield. In the solid state, the butyl, pentyl and dodecyl derivatives strongly emitted orange light, while the methyl derivative was only weakly emissive. Based on the X-ray data and DFT calculations, emission in the solid state was explained by the formation of excimers. A very unusual ``hot-dog''-type excimer was found for the dodecyl derivative, in which two overlapping chromophores are separated by an alkyl chain.

Effects of thermal treatment of ZnO-ZnCr2O4 catalyst on the particle size and product selectivity in dehydrocyclization of crude glycerol and ethylenediamine - Sarkari, Reema; Krishna, Vankudoth; Sudhakar, Medak; Rao, Tumula Venkateshwar; Padmasri, Aytam Hari; Srinivas, Darbha; Venugopal, Akula (Kinetics and Catalysis, 2016)
The ZnO-ZnCr2O4 (Zn-Cr-O) sample obtained by decomposition of Zn-Cr hydrotalcite precursor was subjected to the thermal treatment at different temperatures and the physico-chemical properties of the Zn-Cr-O system were compared with its catalytic behavior in dehydrocyclization of crude glycerol and ethylenediamine (EDA). Upon high temperature treatment of Zn-Cr-O the Cr6+ ions underwent autoreduction to form stable Cr3+ species and the particle size of both ZnO and ZnCr2O4 increased dramatically. Thermal effect did not influence the intermolecular cyclisation of EDA to form pyrazine. By contrast, an inversely proportional dependence was found between the rate of formation of 2-methylpyrazine and the particle size of Zn-Cr-O whereas the rate of 2-pyrazinylmethanol was directly proportional to the particle size.

Efficacy of zero-valent copper (Cu-0) nanoparticles and reducing agents for dechlorination of mono chloroaromatics - Raut, Sandesh S.; Kamble, Sanjay P.; Kulkarni, Prashant S. (Chemosphere, 2016)
The zero-valent copper (Cu-0) nanoparticles were prepared by chemical reduction method. The morphology of nanoparticles was investigated by using X ray diffraction, scanning electron microscopy-energy dispersive X ray, UV-visible spectrophotometer and Brunauer-Emmett-Teller surface area analyser. The Cu-0 nanoparticles along with reducing agents, NaBH4/5% acidified alcohol were used for the dechlorination of chloroaromatics at room temperature. Chlorobenzene (Cl-B), chlorotoluene (Cl-T), chloropyridine (Cl-Py) and chlorobiphenyl (Cl-BPh) were selected as the contaminants. The effect of various operating parameters such as pH, concentration of the catalyst and reducing agent (NaBH4), and recycling of the catalyst on dechlorination were studied. Nearly complete dechlorination of all the chloroaromatics were achieved in the presence of Cu-0 nanoparticles (2.5 g L-1) and NaBH4 (1.0 g L-1.) within 12 h. On the contrary, approximately 70% of dechlorination was observed in the presence of 5% acidified alcohol at similar experimental conditions. The dechlorination mechanism highlighted the importance of Cu-0 nanoparticles as a surface mediator. The kinetics of the dechlorination of chloroaromatics was investigated and compared with chloroaliphatics. The dechlorination rate differed from 0.23 h(-1) (Cl-B) to 0.15 h(-1) (Cl-BPh) in the presence of Cu-0 nanoparticles and NaBH4. The effectiveness of Cu nanoparticles with NaBH4 (1 g L-1) and 5% acidified alcohol as electron donors were studied by oxidation-reduction potential and observed to be -1016 mV and -670 mV, respectively. Final products of the dechlorination were benzene, toluene, pyridine and biphenyl, as identified by gas chromatograph mass spectrometer and nuclear magnetic resonance spectroscopy. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acidified alcohol; ChloroAromatics; Hydrodechlorination; NaBH4; Wastewater treatment; Zero-valent copper (Cu-0) nanoparticles

Efficient access to alkynylated quinalizinones via the gold(I)-catalyzed aminoalkynylation of alkynes - Shinde, Popat S.; Shaikh, Aslam C.; Patil, Nitin T. (Chemical Communications, 2016)
The gold-catalyzed aminoalkynylation of alkynes for the synthesis of quinalizinones is reported. For instance, the reaction of pyridinoalkynes with 1-[(triisopropylsilyl)-ethynyl]-1,2-benziodoxol-3(1H)-one (TIPS-EBX) in the presence of a catalytic amount of AuCl at 50 8C afforded alkynylated quinalizinones in 57-87% yields.

Efficient cellular entry of (r-x-r)-type carbamate-plasmid DNA complexes and its implication for noninvasive topical DNA delivery to skin - Vij, Manika; Natarajan, Poornemaa; Yadav, Amit K.; Patil, Kiran M.; Pandey, Tanuja; Gupta, Nidhi; Santhiya, Deenan; Kumar, Vaijayanti A.; Fernandes, Moneesha; Ganguli, Munia (Molecular Pharmaceutics, 2016)
Arginine-rich cell penetrating peptides are powerful tools for in vitro as well as in vivo delivery of a wide plethora of biomolecules. However, presence of consecutive arginine residues leads to enhanced amenability for proteolytic degradation as well as steric hindrances for membrane interactions which compromise its bioavailability. In order to overcome these limitations we previously reported a safe and stable octaarginine based oligomer, i.e., (r-x-r)4-carbamate, where the backbone amide linkages were replaced by carbamate linkages and 6-aminohexanoic acid based spacer moieties were incorporated for better flexibility, hydrophobicity, optimal spacing of guanidinium groups, and protection against proteolytic cleavage; resulting in improved transfection efficiency over its amide counterpart. In the present work we have investigated the mechanism behind this enhanced transfection efficiency and, based on our observations, demonstrate how the synergistic effect of rationalized oligomer designing, complex characteristics, and cell type contributes to overall effective intracellular delivery. Our results indicate that the (r-x-r)4-carbamate plasmid DNA complexes primarily utilize lipid raft dependent pathway of cellular entry more than other pathways, and this possibly facilitates their increased entry in the lipid raft rich milieu of skin cells. We also emphasize the utility of oligomer (r-x-r)4-carbamate as an efficient carrier for topical delivery of nucleic acids in skin tissue. This carrier can be utilized for safe, efficient, and noninvasive delivery of therapeutically relevant macromolecular hydrophilic cargo like nucleic acids to skin.
Keywords: Cell penetrating peptides; endocytosis; nucleic acid delivery; skin penetration; transfection

Efficient methods for preparing silicon compounds - Sen, Sakya S.; Roesky, H. W. (Academic Press, 2016)
Efficient Methods for Preparing Silicon Compounds is a unique and valuable handbook for chemists and students involved in advanced studies of preparative chemistry in academia and industry. Organized by the various coordination numbers (from two to six) of the central silicon atom of the reported compounds, this book provides researchers with a handy and immediate reference for any compound or properties needed in the area. Edited by a renowned expert in the field, each chapter explores a different type of compound, thoroughly illustrated with useful schemes and supplemented by additional references. Knowledgeable contributors report on a broad range of compounds on which they have published and which are already used on a broad scale or have the potential to be used in the very near future to develop a new field of research or application in silicon chemistry. Includes contributions and edits from leading experts in the field Includes detailed chemical schemes and useful references for each preparative method Organized by the coordination numbers of the central silicon atom for each compound for easy navigation Serves as a go-to primer for researchers in novel compositions of silicon matter.

Efficient strategy for the construction of both enantiomers of the octahydropyrroloquinolinone ring system: total synthesis of (+)-aspidospermidine - Pandey, Ganesh; Burugu, Shiva Kumar; Singh, Pushpendra (Organic Letters, 2016)
An efficient and highly stereoselective intramolecular [3 + 2] cycloaddition of nonstabilized azomethine ylide generated from a designed bicyclic aminal precursor is reported for the synthesis of both (-)- and (+)-octahy-dropyrroloquinolinone. One of the enantiomers is further advanced to accomplish the total synthesis of (+)-aspidospermidine.

Efficient synthesis of potent anti-tubercular drug candidate BM212 - More, N. A.; Patil, M. D.; Garud, D. R.; Gajbhiye, J. M. (Rasayan Journal of Chemistry, 2016)
A novel five step total synthesis route for an anti-tubercular drug BM212 starting from 4-chlorophenacyl bromide was developed with 48% overall yield. The synthesis is amiable for the synthesis of biologically active derivatives of BM 212.

Electrocatalytic water oxidation by a molecular cobalt complex through a high valent cobalt oxo intermediate - Das, Debasree; Pattanayak, Santanu; Singh, Kundan K.; Garai, Bikash; Sen Gupta, Sayam (Chemical Communications, 2016)
Biuret-modified tetraamidomacrocyclic cobalt complex [Co-III-bTAML]- is shown to catalyze electrochemical water oxidation at basic pH leading to the formation of O-2. Electrochemical and spectroscopic studies indicate a high valent cobalt oxo intermediate isoelectronic to Co-V(O) as the active oxidant. The kinetic isotope effect of 8.63 indicates an atom proton transfer mechanism.

Electron detachment and subsequent structural changes of water clusters - Das, Susanta; Sengupta, Turbasu; Dutta, Achintya Kumar; Pal, Sourav (Journal of Physical Chemistry A, 2016)
A cost-effective equation of motion coupled cluster method, EOMIP-CCSD(2), is used to investigate vertical and adiabatic ionization potential as well as ionization-induced structural changes of water clusters and compared with CCSD(T), CASPT2, and MP2 methods. The moderate N-5 scaling and low storage requirement yields EOMIP-CCSD (2) calculation feasible even for reasonably large molecules and clusters with accuracy comparable to CCSD(T) method at much cheaper computational cost. Our calculations shed light on the authenticity of EOMIP-CCSD(2) results and establish a reliable method to study of ionization energy of molecular clusters. We have further investigated the performance of several classes of DFT functionals for ionization energies of water clusters to benchmark the results and to get a reliable functionals for the same.

Electronic structure and properties of layered gallium telluride - Shenoy, U. Sandhya; Gupta, Uttam; Narang, Deepa S.; Late, Dattatray J.; Waghmare, Umesh V.; Rao, C. N. R. (Chemical Physics Letters, 2016)
Layer-dependent electronic structure and properties of gallium monochalcogenides, GaX where X=S, Se, Te, have been investigated using first-principles calculations based on various functionals, with a motivation to assess their use in photocatalytic water splitting. Since hydrogen evolution by water splitting using visible light provides a promising way for solar energy conversion, both theoretical and experimental studies have been carried out on the photochemical hydrogen evolution by GaTe. We also present the Raman spectra of GaTe examined by both theory and experiment. (C) 2016 Elsevier B.V. All rights reserved.

Electrostatic interactions are key to C=O n-pi* shifts: an experimental proof - Haldar, Tapas; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Carbonyl n-pi* transitions are known to undergo blue shift in polar and hydrogen-bonding solvents. Using semiempirical expressions, previous studies hypothesized several factors like change in dipole moment and hydrogen-bond strength upon excitation to cause the blue shift. Theoretically, ground-state electrostatics has been predicted to be the key to the observed shifts, however, an experimental proof has been lacking. Our experimental results demonstrate a consistent linear correlation between IR (ground-state phenomenon) and n-pi* frequency shifts (involves both ground and excited electronic-states) of carbonyls in hydrogen-bonded and non-hydrogen-bonded environments. The carbonyl hydrogen-bonding status is experimentally verified from deviation in n-pi*/fluorescence correlation. The IR/n-pi* correlation validates the key role of electrostatic stabilization of the ground state toward n-pi* shifts and demonstrates the electrostatic nature of carbonyl hydrogen bonds. n-pi* shifts show linear sensitivity to calculated electrostatic fields on carbonyls. Our results portray the potential for n-pi* absorption to estimate local polarity in biomolecules and to probe chemical reactions involving carbonyl activation/stabilization.

Employing arynes in diels–alder reactions and transition-metal-free multicomponent coupling and arylation reactions - Bhojgude, Sachin Suresh; Bhunia, Anup; Biju, Akkattu T. (Accounts of Chemical Research, 2016)
Conspectus <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Arynes are highly reactive intermediates having several applications in organic synthesis for the construction of various ortho-disubstituted arenes. Traditionally, arynes are generated in solution from haloarenes under strongly basic conditions. However, the scopes of many of the aryne reactions are limited because of the harsh conditions used for their generation. The renaissance of interest in aryne chemistry is mainly due to the mild conditions for their generation by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates. This Account is focused on the Diels–Alder reaction of arynes and their transition-metal-free application in multicomponent couplings as well as arylation reactions. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">The Diels–Alder reaction of arynes is a powerful tool for constructing benzo-fused carbocycles and heterocycles. In 2012, we developed an efficient, broad-scope, and scalable Diels–Alder reaction of pentafulvenes with arynes affording benzonorbornadiene derivatives. Subsequently, we accomplished the Diels–Alder reaction of arynes with dienes such as 1,2-benzoquinones and tropones. Moreover, we uncovered a transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes by the reaction of arynes with styrenes that proceeds via a Diels–Alder/ene-reaction cascade. In addition, we demonstrated the reaction of arynes with indene/benzofurans, which proceeds via a tandem [4 + 2]/[2 + 2] sequence. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Multicomponent coupling (MCC) involving arynes mainly comprises the initial addition of a nucleophile to the aryne followed by interception of the aryl anion intermediate with an electrophile (provided the nucleophilic and electrophilic moieties do not belong to the same molecule). We have disclosed aryne MCCs initiated by N-heterocycles such as (iso)quinoline, pyridine, and aziridines. When (iso)quinoline is used as the nucleophilic trigger and N-substituted isatin as the third component, the reaction affords spirooxazino(iso)quinolines via 1,4-dipolar intermediates. Unexpectedly, using pyridine affords indolin-2-ones, where the reaction proceeds via the pyridylidene intermediate. Additionally, we developed the phosphine-triggered aryne MCCs for the synthesis of functionalized benzooxaphospholes. In another phase of our work, we studied the synthetic utility of CO2 as a one-carbon synthon in aryne MCCs for the synthesis of phthalimides. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Engaging arynes as an aryl source is one of the transition-metal-free methods for arylation reactions. We have demonstrated the N-arylation of aromatic tertiary amines and O-arylation of aliphatic alcohols using arynes. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">It is anticipated that the chemistry of arynes will continue to prosper and will lead to surprising developments for the synthesis of various 1,2-disubstituted arenes of molecular complexity and structural diversity. Future challenges in this area include the utility of arynes in enantioselective transformations and the synthesis and reactions of exotic heterocyclic arynes.
Keywords: 2-Benzoquinones; Cycloaddition; Facile N-arylation; O-arylation; One-Pot; Aldehydes; Benzyne; Amines; Heterocycles; Acids; 1

Employing carboxylic acids in aryne multicomponent coupling triggered by aziridines/azetidines - Roy, Tony; Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Thangaraj, Manikandan; Garai, Bikash; Biju, Akkattu T. (Organic Chemistry Frontiers, 2016)
The transition-metal-free aryne multicomponent coupling (MCC) involving carboxylic acids initiated by aziridines/azetidines has been reported. The use of aziridines as nucleophiles afforded N-aryl beta-amino alcohol derivatives and the application of azetidines as nucleophilic triggers furnished N-aryl gamma-amino alcohol derivatives in moderate to good yields. These reactions proceed under mild conditions and result in the formation of a new carbon-nitrogen bond and a new carbon-oxygen bond. The utility of carboxylic acids in aryne MCCs has been demonstrated, and the synthetic potential of phenols as acid surrogates in the present aryne MCCs has been realized.

Enantioselective modular total synthesis of macrolides Sch725674 and C-4-epi-Sch725674 - Sharma, Brijesh M.; Gontala, Arjun; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
The convergent total synthesis of Sch725674 has been accomplished by starting from (R)-1,2-epoxyheptane and assembling five modules in a highly stereoselective manner to give the final product in 6.6% overall yield. The same strategy was extended to the synthesis of its C-4 epimer. Key reactions of the synthetic pathway include a Jacobsen hydrolytic kinetic resolution of an epoxide followed by its regioselective opening through a Yamaguchi-Hirao alkynylation, and ring-closing metathesis reaction to furnish the unique 14-membered ring macrolactone. In addition, the influence of protecting groups on the efficiency of the ring-closing metathesis (RCM) macrocyclization has been studied to maximize its yields.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; Macrocycles; Metathesis; Natural products

Enantioselective synthesis of spirocyclohexadienones by NHC-catalyzed formal [3+3] annulation reaction of enals - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
The enantioselective synthesis of pyrazolone-fused spirocyclohexadienones was demonstrated by the reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones under oxidative N-heterocyclic carbene (NHC) catalysis. This atom-economic and formal [3+3] annulation reaction proceeds through a vinylogous Michael addition/spiroannulation/dehydrogenation cascade to afford spirocyclic compounds with an all-carbon quaternary stereocenter in moderate to good yields and excellent ee values. Key to the success of the reaction is the cooperative NHC-catalyzed generation of chiral alpha,beta-unsaturated acyl azoliums from enals, and base-mediated tandem generation of dienolate/enolate intermediates from pyrazolinones.
Keywords: annulation reactions; asymmetric catalysis; N-heterocyclic carbenes; organocatalysis; spiro compounds

Enantiospecific formal synthesis of inthomycin C - Athawale, Paresh R.; Kashinath, K.; Reddy, D. Srinivasa (Chemistry Select, 2016)
An enantiospecific synthesis of Hatakeyama's intermediate enynol has been accomplished in both enantiomeric forms. As these intermediates can be converted to (3R)-inthomycin C and (3S)-inthomycin C through respective enynol intermediates using reported procedures, present effort may be regarded as formal synthesis of inthomycin C in both enantiomeric forms. Our synthesis highlights the use of pantolactone chiral pool and thus reconfirms the previously assigned absolute stereochemistry as 3R to the natural product inthomycin C.

Encapsulation of yeast (Saccharomyces cereviciae) by spray drying for extension of shelf life - Chandralekha, A.; Tavanandi, A. Hrishikesh; Amrutha, N.; Hebbar, H. Umesh; Raghavarao, K. S. M. S.; Gadre, Ramchandra V. (Drying Technology, 2016)
The objective of the present work was to encapsulate yeast using different carrier materials and examine their efficacy in retaining viability of cells after spray drying. Slurry containing yeast cells along with known amount of carrier material (maltodextrin, corn starch, gum arabic, acacia gum, polyethylene glycol 8000, -cyclodextrin, and skimmed milk powder, one at a time) was added and served as feed. Among these carrier materials attempted, corn starch and maltodextrin showed the best results with respect to powder yield (59%, w/w) and cell survival (80.5%), respectively. However, considering both survival and powder yield (67 and 59% w/w, respectively), corn starch was observed to be the most suitable carrier material.
Keywords: Cell viability; Encapsulation; freeze-drying; spray drying; Yeast

Endohedrally doped gold nanocages: efficient catalysts for O-2 activation and CO oxidation - Manzoor, Dar; Krishnamurty, Sailaja; Pal, Sourav (Physical Chemistry Chemical Physics, 2016)
Gold nanocages are the most attractive catalytic materials as all the atoms in the cage type clusters reside on the surface, making them available for chemisorption by reacting molecules. Due to a hollow space at the center, their chemical and catalytic properties can be tuned effectively and easily by endohedral doping. While a significant experimental and theoretical understanding is currently available on the structural and electronic properties of doped gold cages, very little information is available on their reactivity and catalytic behavior. In the present work, with the help of density functional theory calculations we demonstrate that endohedral doping leads to a notable increase in the binding energy of molecular oxygen on the gold nanocages. The enhancement in the O-2 binding energy on the doped gold cages is also confirmed by a significant decrease in the Au-O and an increase in the O-O bond lengths, corroborated by a red shift (similar to 250 cm(-1)) in the O-O stretching frequency as compared to the pristine cage. Furthermore, interestingly, the doped gold cages show very low activation barriers for the environmentally important CO oxidation reaction as compared to the pristine gold cage. Importantly, the decrease in the barrier height is comparatively greater for the rate limiting step of O-O-C-O intermediate formation and as a result the CO oxidation is expected to be more facile on the doped gold cages. Thus, the current study highlights the role of heteroatom doping in imparting new chemical and catalytic properties to gold cages and is expected to spur further research in the design of efficient gold nanocatalysts.

Engineering and in vitro evaluation of acid labile cholesterol tethered MG132 nanoparticle fortargeting ubiquitin-proteasome system in cancer - Ghosh, Chandramouli; Gupta, Neha; More, Piyush; Sengupta, Poulomi; Mallick, Abhik; Santra, Manas Kumar; Basu, Sudipta (Chemistryselect, 2016)
In recent years, proteasome has evolved as one of the important alternative targets in cancer chemotherapy. However, selective targeting of proteasome system in cancer cells still remains a major challenge. To address this, a potent peptide based proteasome inhibitor MG132 was chemically conjugated with biocompatible-biodegradable cholesterol by acid cleavable hydrazone linkage. Spherical nanoparticles (MG132-NPs) were engineered from cholesterol-MG132 conjugate. Increased amount of free MG132 was released from these nanoparticles in acidic environment compared to physiological milieu in a slow and controlled manner. These MG132-NPs were taken up by breast cancer MCF7 cells into lysosomes within 6 h. Proteasome system was inhibited by these MG132-NPs leading to stabilization of beta-catenin, cyclin A and cyclin B in HEK-293T cells. Interestingly, MG132-NPs induced much improved cell death in drug resistant MDA-MB-231 cells with insignificant toxicity in healthy cells (HEK293 and L929) even in higher concentration.

Engineering crystals that facilitate the acyl-transfer reaction: insight from a comparison of the crystal structures of myo-inositol-1,3,5-orthoformate-derived benzoates and carbonates - Tamboli, Majid I.; Krishanaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (ACTA Crystallographica Section C-Structural Chemistry, 2016)
Minor variations in the molecular structure of constituent molecules of reactive crystals often yield crystals with significantly different properties due to altered modes of molecular association in the solid state. Hence, these studies could provide a better understanding of the complex chemical processes occurring in the crystalline state. However, reactions that proceed efficiently in molecular crystals are only a small fraction of the reactions that are known to proceed (with comparable efficiency) in the solution state. Hence, for consistent progress in this area of research, investigation of newer reactive molecular crystals which support different kinds of reactions and their related systems is essential. The crystal structures and acyl-transfer reactivity of a myo-inositol-1,3,5-orthoformate-derived dibenzoate and its carbonate (4-O-benzoyl-2-O-phenoxycarbonyl-myo-inositol 1,3,5-orthoformate, C21H18O9) and thiocarbonate (4-O-benzoyl-2-O-phenoxythiocarbonyl-myo-inositol 1,3,5-orthoformate, C21H18O8S) analogs are compared with the aim of understanding the relationship between crystal structure and acyl-transfer reactivity. Insertion of an O atom in the acyl (or thioacyl) group of an ester gives the corresponding carbonate (or thiocarbonate). This seemingly minor change in molecular structure results in a considerable change in the packing of the molecules in the crystals of myoinositol-1,3,5-orthoformate-derived benzoates and the corresponding carbonates. These differences result in a lack of intermolecular acyl-transfer reactivity in crystals of myo-inositol-1,3,5-orthoformate-derived carbonates. Hence, this study illustrates the sensitivity of the relative orientation of molecules, their packing and ensuing changes in the reactivity of resulting crystals to minor changes in molecular structure.

Enhanced clathrate hydrate formation kinetics at near ambient temperatures and moderate pressures: Application to natural gas storage - Veluswamy, Hari Prakash; Kumar, Sharad; Kumar, Rajnish; Rangsunvigit, Pramoch; Linga, Praveen (Fuel, 2016)
SNG (solidified natural gas) technology via clathrate hydrates is a potential method for large scale stationary storage of natural gas. Clathrate hydrate formation kinetics in presence of methane and 5.6 mol% tetrahydrofuran (THF) was investigated in an unstirred reactor configuration at moderate pressure and temperature conditions. It is well known that the presence of THF generally improves the thermodynamic stability of the resulting hydrate. In order to study the scale-up potential of this approach, kinetics of hydrate growth at temperatures close to ambient conditions and moderate pressures is required. Hydrate formation experiments were performed at three different temperatures - 283.2 K, 288.2 K and 293.2 K and at experimental pressures of 7.2 MPa, 5.0 and 3.0 MPa. Further, we report a synergistic effect of kinetic promotion of mixed methane hydrate formation by coupling THF and sodium dodecyl sulfate (SDS) at 293.2 K. For the first time, we observe rapid mixed methane/THF hydrate formation kinetics at 293.2 K in presence of just 100 ppm sodium dodecyl sulfate surfactant with methane gas uptake of 3.45 (+/- 0.17) kmol/m(3) of water in 1 h. This is also the first study to demonstrate such rapid hydrate formation kinetics with significant methane storage capacity at temperature of 293.2 K (closer to the ambient temperature). Further, substantial methane gas uptake of 3.52 (+/- 0.13) kmol/m(3) of water is possible even at reduced experimental pressure of 3.0 MPa and 283.2 K in 2 h. Minimal energy requirement in an unstirred reactor for mixed methane/THF hydrate formation storage can propel the SNG technology for large scale commercial deployment. Further improvement in the process can be achieved by optimizing the cooling requirement through innovative reactor design and operating the process in a semi-batch or continuous mode. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Methane hydrates; Natural gas storage; Rapid kinetics; surfactant; Tetrahydrofuran; Unstirred reactor

Enhanced drug release by selective cleavage of cross-links in a double-cross-linked hydrogel - Tiwari, Neha; Badiger, Manohar V. (RSC Advances, 2016)
In the present paper, we report on the synthesis and characterization of redox sensitive double-cross-linked poly(acrylic acid) hydrogels using two different cross-linking agents, Jeffamine (R) and cystamine. The amount of two cross-linking agents was varied in order to synthesize hydrogels with different mechanical strengths. Jeffamine provides mechanical stability to the hydrogels while cystamine incorporates redox sensitivity. The stress values at the break point of the mono-and double-crosslinked hydrogels were determined from stress-strain plots. The disulphide bonds (S-S) in the cystamine were cleaved selectively in the presence of dithiothreitol, which increased the degree of hydrogel swelling. This phenomenon of in situ breaking of one cross-linking and increasing the swelling ratio could be used in swelling-controlled drug delivery systems. The implication of selective breaking of cross-links on the swelling-controlled release of the anticancer drug doxorubicin was demonstrated. We also successfully prepared Ag nanoparticles in the dual cross-linked hydrogels in order to incorporate antibacterial properties and studied their release by selective cleavage of cystamine bonds. These double-cross-linked hydrogels show great promise in drug delivery and tissue engineering applications.

Enhanced electrochemical performance of polypyrrole coated MoS2 nanocomposites as electrode material for supercapacitor application - Thakur, Anukul K.; Choudhary, Ram Bilash; Majumder, Mandira; Gupta, Govind; Shelke, Manjusha V. (Journal of Electroanalytical Chemistry, 2016)
Binary nanocomposites of polypyrrole (PPY) and Molybdenum disulfide (MoS2), with varying weight% of MoS2 viz. MP1, MP2, and MP3 corresponding to 12.5, 25, and 50% of MoS2 respectively, were prepared via. in-situ polymerization method. X-ray diffraction (XRD), field emission scanning microscopy (FESEM), and transmission electron microscopy (TEM) were employed to study the structure and morphology of the prepared nanocomposites. The electrochemical properties were studied by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS) techniques. The nanocomposite electrode material MP2 reached a specific capacitance of 400 F/g at the current density 1 A/g which was higher than that of pure PPY and the other two nanocomposites viz. MP1 and MP3 having different compositions of MoS2 and PPY than that of MP2. It was noteworthy that the maximum capacitance value was obtained only for an optimum dose of MoS2 (MP2 in this case with 25% of MoS2) and any deviation from which ultimately degraded the capacitive performance of the nanocomposite electrode material. This could be attributed to the occurrence of maximum interaction between MoS2 and PPY in the nanocomposite only at a particular concentration of its host materials. The results showed that the specific capacitance of MP2 nanocomposite declined by 7.2% after 5000 cycles. Further, MP2 nanocomposite electrode showed much higher energy density (8.88 Wh/kg) as well as power density (2286 W/kg) which were higher than that shown by PPY electrode. (C) 2016 Elsevier B.V. All rights reserved.

Enhanced field emission behavior of layered MoSe2 - Suryawanshi, Sachin R.; Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; More, Mahendra A.; Late, Dattatray J. (Materials Research Express, 2016)
Herein, we report one step facile chemical vapor deposition method for synthesis of single-layer MoSe2 nanosheets with average lateral dimension similar to 60 mu m on 300 nm SiO2/Si and n-type silicon substrates and field emission investigation of MoSe2/Si at the base pressure of similar to 1 x 10(-8) mbar. The morphological and structural analyses of the as-deposited single-layer MoSe2 nanosheets were carried out using an optical microscopy, Raman spectroscopy and atomic force microscopy. Furthermore, the values of turn-on and threshold fields required to extract an emission current densities of 1 and 10 mu A cm(-2), are found to be similar to 1.9 and similar to 2.3 V mu m(-1), respectively. Interestingly, the MoSe2 nanosheet emitter delivers maximum field emission current density of similar to 1.5 mA cm(-2) at a relatively lower applied electric field of similar to 3.9 V mu m(-1). The long term operational current stability recorded at the preset values of 35 mu A over 3 hr duration and is found to be very good. The observed results demonstrates that the layered MoSe2 nanosheet based field emitter can open up many opportunities for their potential application as an electron source in flat panel display, transmission electron microscope, and x-ray generation. Thus, the facile one step synthesis approach and robust nature of single-layer MoSe2 nanosheets emitter can provide prospects for the future development of practical electron sources.
Keywords: atomically thin nanosheets; chemical vapor deposition; field emission; layered MoSe2

Enhanced nucleation of polypropylene by metal-organic frameworks (MOFs) based on aluminium dicarboxylates: influence of structural features - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (RSC Advances, 2016)
Metal-organic frameworks (MOFs) based on aluminium dicarboxylates provide a new platform for the enhanced nucleation of isotactic polypropylene (iPP). For instance, aluminium dicarboxylates exhibit a unique butterfly-like structure similar to that of carboxylate-alumoxanes and correlates well with the nucleation characteristics of iPP. A subtle change in the structure of the ligand backbone (fumarate/succinate) does not alter the framework structure despite changing the hydrophilic/hydrophobic character and its subsequent nucleation characteristics. This suggests that the nucleating agent should facilitate favourable interaction with hydrophobic iPP for efficient nucleation. Further, a systematic variation of the alkyl chain length in the Al-dicarboxylate does not change the nucleation efficiency considerably, even though it increases the distance between the octahedral alumina chains in the metal-organic framework, suggesting that the butterfly-like structure present in the framework is a key aspect for nucleation. Finally, the significance of the orientational conformation of the dicarboxylate around the metal centre for the nucleation is confirmed by the poor nucleation efficiency of chromium and zirconium suberate MOFs where the orientation of suberate would be different from that of aluminium suberate due to the difference in the ligation of the carboxylate group. The present work thus provides valuable pathways for developing new nucleating agents based on MOFs with appropriate selection and orientation of the organic linkers around the metal centre.

Enhancement in rate of photocatalysis upon catalyst recycling - Sorathiya, Kalpesh; Mishra, Biswajit; Kalarikkal, Abhishek; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Khushalani, Deepa (Scientific Reports, 2016)
Recyclability is an important aspect for heterogeneous photo-catalysts. Ease of recovery and stability of the photo-catalyst in terms of efficiency over the number of cycles are highly desired and in fact it is ideal if the efficiency is constant and it should not decrease marginally with each cycle. Presented here is a seminal observation in which the photocatalytic activity is shown to improve with increasing number of catalytic cycles (it is 1.7 times better after the 1st cycle and 3.1 times better after the 2nd cycle). Specifically, nanorods of pure TiO2 and TiO2 doped with controlled amount of tungsten have been used to degrade two model pollutants: Phenol and Rhodamine B under exclusive visible light illumination. It was found that, in case of 1 mol.% W incorporation, rate of photocatalysis and also the range of visible light absorption of the photocatalyst increased after the photocatalysis as compared to before photocatalysis. This aspect is unique for doped TiO2 and hence provides an intriguing way to mitigate low photoactivity.

Enhancing the strain sensitivity of CoFe2O4 at low magnetic fields without affecting the magnetostriction coefficient by substitution of small amounts of Mg for Fe - Anantharamaiah, P. N.; Joy, Pattayil Alias (Physical Chemistry Chemical Physics, 2016)
Attaining high magnetostrictive strain sensitivity (d lambda/dH) with high magnetostriction strain (lambda) is desirable for sintered polycrystalline cobalt ferrite for various applications. It is shown that substitution of a small amount of Fe3+ by Mg2+ in CoMgxFe2-xO4 (x < 0.1) gives a comparable maximum magnetostriction coefficient to that of the unsubstituted counterpart, with large improvement in the strain sensitivity at relatively low magnetic fields. A large increase in the magnetostriction coefficient is obtained at low magnetic fields for the substituted compositions. The magnetostriction parameters are further enhanced by magnetic field annealing of the sintered products. The results are analyzed based on powder XRD, Raman spectroscopy, XPS and magnetic measurements and based on the results from these studies, the changes in the magnetostriction parameters are correlated with the changes in the cation distribution, magnetic anisotropy and microstructure.

Epilogue - Ranade, V. V.; Joshi, S. S. (Industrial catalytic processes for fine and specialty chemicals, 2016)
This chapter recaptures the key points and the lessons learned from our experience in applying the material discussed in this book to addressing industrially relevant issues. Some comments on future trends in catalysis and catalytic processes are included. We hope that this book will stimulate further work on this very important area from an industrial as well as a scientific point of view.

Epoxide ring-opening reaction by using sol-gel-synthesized palladium supported on a strontium hydroxyl fluoride catalyst - Acham, Vaibhav R.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B. (Comptes Rendus Chimie, 2016)
Palladium supported on a strontium hydroxyl fluoride catalyst was synthesized by a one-pot fluorolytic sol-gel method. The prepared catalyst was characterized by various physicochemical techniques. The sol-gel method has led to the formation of a high surface area (57 m(2)g(-1)), mesoporous (pore diameter = 13.0 nm) catalyst with uniform dispersion of Pd nanoparticles of size similar to 7 nm on the surface of strontium hydroxyl fluoride. The catalyst was used for epoxide alcoholysis, and 100% conversion was obtained with 96% selectivity for beta-alkoxy alcohols under mild conditions: The catalyst could be recycled for up to three catalytic cycles without any appreciable decrease in conversion and selectivity, indicating the stability of the catalyst under the reaction conditions. Further, the mechanism of alcoholysis was proposed on the basis of the physicochemical characteristics of the catalyst and on the basis of the products formed during the catalytic reaction. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.

ESP promoted "on water" click reaction: a highly economic and sustainable protocol for 1,4-disubstituted-1H-1,2,3-triazole synthesis at room temperature - Konwar, Manashjyoti; Ali, Abdul A.; Chetia, Mitali; Saikia, Prakash J.; Khupse, Nageshwar D.; Sarma, Diganta (Chemistryselect, 2016)
A highly economic and green protocol for azide-alkyne cyclo-addition reactions in water has been developed which offers a mild, practical and inexpensive basic alternative to the conventional protocols. The protocol uses readily available, considered as waste material, Egg Shell Powder (ESP) as an additive for CuAAC reaction. The reactions proceeded in water in presence of this basic waste material derived additive under 'external base/ligand/reducing agent/organic solvent' free conditions affording good to excellent yields of the desired products.

[Et3NH][HSO4] catalyzed efficient synthesis of 5-arylidene-rhodanine conjugates and their antitubercular activity - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Research on Chemical Intermediates, 2016)
We have described a highly efficient, safer protocol for the synthesis of 5-arylidene-rhodanine conjugates catalyzed by Bronsted acidic ionic liquid [Et3NH][HSO4] in excellent yields. The protocol offers cost-effective, environmentally benign, solvent-free conditions and recycle-reuse of the catalyst. The synthesized 5-arylidene-rhodanine conjugates were characterized on the basis of (1) H NMR, C-13 NMR and HRMS spectral data. A series of 5-arylidene-rhodanine derivatives 3a-h, 4a-h were synthesized and evaluated for their in vitro antitubercular activity against dormant Mycobacterium tuberculosis H37Ra and M. bovis BCG strains. Moreover, compounds 3a, 3b, 3e, 3f, 3g, 3h and 4f exhibited good antitubercular activity and were also evaluated for anti-proliferative activity against MCF-7, A549 and HCT116 cell lines using modified MTT assay and found to be noncytotoxic. Compounds 3a-h and 4f were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards M. tuberculosis. Furthermore, in silico ADME prediction of all the tested compounds followed the criteria for orally active drug and, therefore, these compounds may have a good potential for eventual development as oral agents.

Evaluating the anticancer activity and nanoparticulate nature of homeopathic preparations of Terminalia chebula - Wani, Kirtee; Shah, Nilesh; Prabhune, Asmita; Jadhav, Arun; Ranjekar, Prabhakar; Kaul-Ghanekar, Ruchika (Homeopathy, 2016)
Background: Breast cancer is the most common cancer diagnosed among women and is the second leading cause of cancer death. Homeopathic medicines are part of the alternative medicines that are given as a supportive therapy in breast cancer. The objective of this study was to investigate the anticancer activity of commercially available homeopathic preparations of Terminalia chebula (TC) and evaluate their nanoparticulate nature. Methods: Mother tincture (MT) and other homeopathic preparations (3X, 6C and 30C) of TC were tested for their effect on the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cell lines by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Cell growth assay was performed to analyze the effect of the different potencies on the growth kinetics of breast cancer cells. MT and 6C were evaluated for the presence of nanoparticles by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Results: MT decreased the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cells. However, the other potencies (3X, 6C and 30C) decreased the viability of only breast cancer cells without affecting the viability of the non-cancerous cells. All the potencies, MT, 3X, 6C and 30C, reduced growth kinetics of breast cancer cells, more specifically at 1:10 dilution at 24, 48 and 72 h. Under SEM, MT appeared as a mesh-like structure whereas under TEM, it showed presence of nanoclusters. On the other hand, 6C potency contained 20 nm sized nanoparticles. Conclusion: The current study reports the anticancer activity of homeopathic preparations of TC against breast cancer and reveals their nanoparticulate nature. These preliminary results warrant further mechanistic studies at both in vitro and in vivo levels to evaluate the potential of TC as nanomedicine in breast cancer.

Evaluation of uttroside B, a saponin from Solanum nigrum Linn, as a promising chemotherapeutic agent against hepatocellular carcinoma - Nath, Lekshmi R.; Gorantla, Jaggaiah N.; Thulasidasan, Arun Kumar T.; Vijayakurup, Vinod; Shah, Shabna; Anwer, Shabna; Joseph, Sophia M.; Antony, Jayesh; Veena, Kollery Suresh; Sundaram, Sankar; Marelli, Udaya K.; Lankalapalli, Ravi S.; et al. (Scientific Reports, 2016)
We report, for the first time, the remarkable efficacy of uttroside B, a potent saponin from Solanum nigrum Linn, against liver cancer. The compound has been isolated and characterized from the leaves of Solanum nigrum Linn, a plant widely used in traditional medicine and is a rich resource of several anticancer molecules. Uttroside B, that comprises of beta-D-glucopyranosyl unit at C-26 of the furostanol and beta-lycotetraosyl unit at C-3, is ten times more cytotoxic to the liver cancer cell line, HepG2 (IC50: 0.5 mu M) than sorafenib (IC50: 5.8 mu M), the only FDA-approved drug for liver cancer. Moreover, it induces cytotoxicity in all liver cancer cell lines, irrespective of their HBV status, while being non-toxic to normal immortalized hepatocytes. It induces apoptosis in HepG2 cells by down-regulating mainly the activation of MAPK and mTOR pathways. The drastic reduction in HepG2-xenograft tumor size achieved by uttroside B in NOD-SCID mice and substantiation of its biological safety through both acute and chronic toxicity studies in Swiss albino mice warrants clinical validation of the molecule against hepatic cancer, for which, the chemotherapeutic armamentarium currently has limited weapons.

Evidence for dry molten globule-like domains in the pH-induced equilibrium folding intermediate of a multidomain protein - Acharya, Nirbhik; Mishra, Prajna; Jha, Santosh Kumar (Journal of Physical Chemistry Letters, 2016)
The role of van der Waals (vdW) packing interactions compared to the hydrophobic effect in stabilizing the functional structure of proteins is poorly understood. Here we show, using fluorescence resonance energy transfer, dynamic fluorescence quenching, red-edge excitation shift, and near- and far-UV circular dichroism, that the pH-induced structural perturbation of a multidomain protein leads to the formation of a state in which two out of the three domains have characteristics of dry molten globules, that is, the domains are expanded compared to the native protein with disrupted packing interactions but have dry cores. We quantitatively estimate the energetic contribution of vdW interactions and show that they play an important role in the stability of the native state and cooperativity of its structural transition, in addition to the hydrophobic effect. Our results also indicate that during the pH-induced unfolding, side-chain unlocking and hydrophobic solvation occur in two distinct steps and not in concerted manner, as commonly believed

Evolution of specific 3 `-5 `-linkages in RNA in pre-biotic soup: a new hypothesis - Kumar, Vaijayanti A. (Organic & Biomolecular Chemistry, 2016)
This article reviews the different possibilities towards progression of the formation of DNA/RNA in the chemical world, before life, in enzyme-free conditions. The advent of deoxyribo- and ribopentose-sugars, nucleosides, nucleotides and oligonucleotides in the prebiotic soup is briefly discussed. Further, the formation of early single stranded oligomers, base-pairing possibilities and information transfer based on the stability parameters of the derived duplexes is reviewed. Each theory has its own merits and demerits which we have elaborated upon. Lastly, using clues from this literature, a possible explanation for the specific 3'-5'-linkages in RNA is proposed.

Exfoliated 2D black phosphorus nanosheets: field emission studies - Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2016)
A few layer black phosphorus (BP) nanosheets are obtained by micromechanical cleavage from a bulk BP crystal. In a typical exfoliation procedure, a layer of BP is peeled off from bulk crystal with the help of Scotch tape and transferred onto SiO2/Si and pristine Si substrates. The morphological and structural analyses of the samples were carried out using an optical microscopy, a transmission electron microscopy, and a Raman spectroscopy. Field emission investigations on a few layered BP nanosheets on Si substrate were carried out at the base pressure of 1 x 10(-8) mbar. The turn-on value, corresponding to emission current density of similar to 1 mu A/cm(2), is found to be similar to 5.1V/mu m for BP nanosheets/Si emitter and high field enhancement factor (beta) similar to 1164, attributed to atomically thin/sharp edges of the BP nanosheets. The emission current shows good stability at a preset value of similar to 5 mu A over a period of more than 8 h. The present results demonstrate the potential of the mechanically exfoliated BP nanosheets/Si field emitter for the development of practical electron sources. (C) 2016 American Vacuum Society.

Expedient cobalt-catalyzed C–H alkynylation of (enantiopure) benzylamines - Landge, Vinod Gokulkrishna; Midya, Siba Prasad; Rana, Jagannath; Shinde, Dinesh R.; Balaraman, Ekambaram (Organic Letters, 2016)
A unified strategy for cobalt-catalyzed ortho-C-H bond alkynylation of benzylamines is reported. Simple, commercially available CoBr2 was used as a cobalt source. The developed alkynylation strategy is robust and efficient and has a broad substrate scope including 1 degrees, 2 degrees, and 3 degrees benzylamines. The mechanistic study shows that C-H bond cleavage is reversible, and the kinetic study illustrates that the rate of reaction depends solely on the catalyst.
Keywords: Terminal Alkynes; Bond Activation; Directed Functionalization; Aminoquinoline Benzamides; Ortho-C(Sp(2))-H Bonds; Mechanistic Insights; Selective Access; Carbon-Hydrogen; Nickel; Annulation

Experimental and computational analysis of supramolecular motifs involving C-sp2(aromatic)-F and CF3 groups in organic solids - Panini, Piyush; Gonnade, Rajesh G.; Chopra, Deepak (New Journal of Chemistry, 2016)
A detailed experimental (SCXRD) and theoretical (PIXEL and QTAIM) investigation of the evolution of different supramolecular motifs formed via the presence of both C(sp(2))/(sp(3))-F groups in the crystal packing has been performed in a series of newly synthesized substituted benzanilides (containing ``both'' the fluorine and the trifluoromethyl group in the same molecule) along with previously reported similarly related crystal structures [CrystEngComm, 2008, 10, 54-67; CrystEngComm, 2012, 14, 1972-1989, CrystEngComm, 2013, 15, 3711-3733]. It was observed that the highest stabilized molecular motifs primarily consist of C(sp(2))-H center dot center dot center dot F-C(sp(2)) H-bonds in preference to C(sp(2))-H center dot center dot center dot F-C(sp(3)) H-bonds in the crystal. The motifs involving C(sp(2))-H center dot center dot center dot F-C(sp(2))/(sp(3)) H bonds were observed to be present over the entire distance range between 2.2 and 2.7 angstrom, albeit the difference in energies of stabilization involving fluorine atoms attached to sp(2) and sp(3) carbon is not significant in molecular crystals. From QTAIM analysis, the C(sp(2))/(sp(3))-F center dot center dot center dot F-C(sp(2))/(sp(3)) interactions were observed to be a closed shell in nature and provide local stabilization, indicating the formation of bonds, similar to weak hydrogen bonds observed in crystals.

Experimental investigation to elucidate why tetrahydrofuran rapidly promotes methane hydrate formation kinetics: applicable to energy storage - Kumar, Asheesh; Daraboina, Nagu; Kumar, Rajnish; Linga, Praveen (Journal of Physical Chemistry C, 2016)
Methane storage as SNG (solidified natural gas) in the form of clathrate hydrates is an emerging, economically feasible and environmentally benign technology for large scale storage. Mixed tetrahydrofuran (THF)-methane (CH4) hydrates offer a paradigm shift to milder storage conditions and faster hydrate formation kinetics, providing a promising scenario to scale up the SNG technology. In this work, we synthesize mixed THF-CH4 hydrates in a high pressure microdifferential scanning calorimeter (HP mu-DSC) to elucidate the two-step hydrate formation mechanism of mixed THF-CH4 hydrate identifying the synergism between THF and CH4. Heat flow change during hydrate formation and dissociation of mixed THF-CH4 hydrates formed in the presence of 5.56 mol % THF (stoichiometric composition) were monitored. The two step-mechanism of mixed THF-CH4 hydrate formation was further confirmed by the pressure-temperature profile and visual observations with a sample volume scale -up of about 350 times that of mu-DSC experiments.

Exploration of magnetically separable Ag@AgxNiy core/graded-alloy-shell nanostructures - Kumar, Mukesh; Soni, Kiran; Satpati, Biswarup; Gopinath, Chinnakonda S.; Deka, Sasanka (Chemical Communications, 2016)
We report novel bimetallic Ag@AgxNiy core@graded-alloy-shell nanoparticles (CGAS NPs), i.e. single Ag core NPs shelled by an AgxNiy graded alloy and stabilized by the CTAB surfactant employing a novel synthesis method. These Ag@AgxNiy CGAS NPs demonstrated superior catalytic performance in the synthesis of biologically active 3-amino alkylated indoles under green conditions.

Exploration of the diastereoselectivity in an unusual Grignard reaction and its application towards the synthesis of styryl lactones 7-epi-(+)-goniodiol and 8-epi-(-)-goniodiol - Chavan, Subhash P.; Khatod, Harshali S.; Das, Tamal; Vanka, Kumar (RSC Advances, 2016)
An unusual diastereoselective Grignard reaction is explored, where the Grignard reagents are derived from 1,n-dihaloalkanes. A steric bias due to the presence of a quaternary centre adjacent to the acetonide ester at the benzylic position is responsible for the formation of an intramolecularly reduced product in almost quantitative yield. This steric hindrance is responsible for the diastereoselectivity observed with a variety of aromatic as well as aliphatic esters. The unusual Grignard reaction furnishes long chain secondary alcohols possessing a terminal olefin, which are synthetically important intermediates. As an application of this method, the diastereoselective synthesis of styryl lactones viz. 7-epi-(+)-goniodiol (29) and 8-epi(-)-goniodiol (30) has been achieved.

Exploration of the presence of bulk-like water in AOT reverse micelles and water-in-oil nanodroplets: the role of charged interfaces, confinement size and properties of water - Hande, Vrushali R.; Chakrabarty, Suman (Physical Chemistry Chemical Physics, 2016)
The properties of water in a confined environment can be drastically different than the bulk water. In a confined system, e.g. the interior of a reverse micelle, there exist at least two distinct regions namely ``interfacial water'' characterized by markedly slower dynamics, and ``core water'', which may resemble bulk water for a larger size of the water pool. Using atomistic molecular dynamics simulations, we systematically investigate the presence of bulk-like water in AOT reverse micelles (RMs) with varying size given by w(0) = [H2O]/[AOT] = 10, 15 and 20. In order to understand the effect of the negatively charged interface of the RM, we have performed control studies for the model systems of water-in-oil (isooctane) nanodroplets with the same size of the water pool as the RM systems. In order to quantify the deviations from bulk-like behavior, we have used three kinds of structural order parameters, namely (i) number density to probe the local translational ordering, (ii) tetrahedral order and hydrogen bond distribution to probe the local orientational ordering, and (iii) dipolar orientation relative to the radial vector to capture the global orientational ordering of the water dipoles. We demonstrate that the size of the ``core water'' region that resembles bulk water decreases in the above order, i.e. orientational order parameters of water molecules are perturbed by the charged interface to a larger length scale as compared to the translational order. We have compared the translational and rotational dynamics of the water molecules for the interfacial and core regions to find that the slower dynamics persists even for the core water for the size range that we have studied although to a much lesser extent as compared to the interfacial water. Moreover, we demonstrate that the hydrophobic interface in the water-in-oil nanodroplets has a much weaker effect on the structure and dynamics of the confined water molecules as compared to the anionic RMs. Thus, the major contribution towards the structural ordering and slow dynamics of water in a charged RM system would originate from the strong electrostatic and hydrogen bonded interactions with the interface, and not due to the spatial confinement effect.

Exploring activity differences between the hydroformylation catalysts: Insights from theory - Dangat, Yuvraj B.; Rizvi, Masood Ahmad; Pandey, Pippalad; Vanka, Kumar (Journal of Organometallic Chemistry, 2016)
Hydroformylation catalysis is the most important homogeneous catalysis process of the current day. The current computational investigation aims to understand the nature of the hydroformylation process when monodentate ligands are employed. The complete catalytic cycle for different monodentate ligands bound to the rhodium center has been studied with full quantum chemical calculations, with density functional theory (DFT). To the best of our knowledge, this is the first systematic investigation of the relative free energy surfaces for mono-coordinate monodentate and bi-coordinated monodentate ligands in hydroformylation catalysis. The results indicate that the barriers are lower for the mono-coordinate monodentate species in comparison to the bi-coordinate monodentate, for all the ligand cases studied, indicating higher activity for the mono-coordinate monodentate active species. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Density functional theory (DFT) calculations; Hydroformylation; Monodentate; Rhodium

Exploring the reducing role of boron: added insights from theory - Dangat, Yuvraj B.; Vanka, Kumar (Dalton Transactions, 2016)
Carbon-carbon coupling in CO molecules is a challenging proposition, and very few main group complexes have been shown to effect this process. A recently reported triply bonded diboryne system (1) is notable for coupling four CO molecules to produce a (bis) boralactone species. The current full quantum chemical computational investigation with density functional theory (DFT) provides important insights into the nature of the CO coupling process by triply bonded diboryne systems. The complete reaction pathway leading to the formation of the (bis) boralactone has been determined. Factors that make this system so successful in coupling CO groups have been elucidated, and pertinent issues, such as why the coupling process stops after four CO additions, have been explored. Also, importantly, insights have been gained through the natural bond orbital (NBO) analysis into how the back-donation from diboryne activates CO.

Expression of proteins involved in digestion and detoxification are regulated in helicoverpa armigera to cope up with chlorpyrifos insecticide - Dawkar, Vishal V.; Chikate, Yojana R.; More, Tushar H.; Gupta, Vidya S.; Giri, Ashok P. (Insect Science, 2016)
Helicoverpa armigera is a key pest in many vital crops, which is mainly controlled by chemical strategies. To manage this pest is becoming challenging due to its ability and evolution of resistance against insecticides. Further, its subsequent spread on nonhost plant is remarkable in recent times. Hence, decoding resistance mechanism against phytochemicals and synthetic insecticides is a major challenge. The present work describes that the digestion, defense and immunity related enzymes are associated with chlorpyrifos resistance in H. armigera. Proteomic analysis of H. armigera gut tissue upon feeding on chlorpyrifos containing diet (CH) and artificial diet (AD) using nano-liquid chromatography-mass spectrometry identified upregulated 23-proteins in CH fed larvae. Database searches combined with gene ontology analysis revealed that the identified gut proteins engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification. Biochemical and quantitative real-time polymerase chain reaction analysis of candidate proteins indicated that insects were struggling to get nutrients and energy in presence of CH, while at the same time endeavoring to metabolize chlorpyrifos. Moreover, we proposed a potential processing pathway of chlorpyrifos in H. armigera gut by examining the metabolites using gas chromatography-mass spectrometry. H. armigera exhibit a range of intriguing behavioral, morphological adaptations and resistance to insecticides by regulating expression of proteins involved in digestion and detoxification mechanisms to cope up with chlorpyrifos. In these contexts, as gut is a rich repository of biological information; profound analysis of gut tissues can give clues of detoxification and resistance mechanism in insects.
Keywords: chlorpyrifos; Helicoverpa armigera; insecticide resistance; proteomics; real-time PCR

Extension of the effective fragment potential method to macromolecules - Gurunathan, Pradeep Kumar; Acharya, Atanu; Ghosh, Debashree; Kosenkov, Dmytro; Kaliman, Ilya; Shao, Yihan; Krylov, Anna I.; Slipchenko, Lyudmila V. (Journal of Physical Chemistry B, 2016)
The effective fragment potential (EFP) approach, which can be described as a nonempirical polarizable force field, affords an accurate first-principles treatment of noncovalent interactions in extended systems. EFP can also describe the effect of the environment on the electronic properties (e.g., electronic excitation energies and ionization and electron-attachment energies) of a subsystem via the QM/EFP (quantum mechanics/EFP) polarizable embedding scheme. The original formulation of the method assumes that the system can be separated, without breaking covalent bonds, into closed-shell fragments, such as solvent and solute molecules. Here, we present an extension of the EFP method to macromolecules (mEFP). Several schemes for breaking a large molecule into small fragments described by EFP are presented and benchmarked. We focus on the electronic properties of molecules embedded into a protein environment and consider ionization, electron-attachment, and excitation energies (single-point calculations only). The model systems include chromophores of green and red fluorescent proteins surrounded by several nearby amino acid residues and phenolate bound to the T4 lysozyme. All mEFP schemes show robust performance and accurately reproduce the reference full QM calculations. For further applications of mEFP, we recommend either the scheme in which the peptide is cut along the C-alpha-C bond, giving rise to one fragment per amino acid, or the scheme with two cuts per amino acid, along the C-alpha-C and C-alpha-N bonds. While using these fragmentation schemes, the errors in solvatochromic shifts in electronic energy differences (excitation, ionization, electron detachment, or electron-attachment) do not exceed 0.1 eV. The largest error of QM/mEFP against QM/EFP (no fragmentation of the EFP part) is 0.06 eV (in most cases, the errors are 0.01-0.02 eV). The errors in the QM/molecular mechanics calculations with standard point charges can be as large as 0.3 eV.

Effect of ligand attachment on the C-I bond dissociation process on aluminum nanoclusters: a DFT investigation - Sengupta, Turbasu; Samanta, Bipasa; Pal, Sourav (Journal of Physical Chemistry C, 2017)
The influence of the ligand attachment on the activation process of carbon halogen bond on small sized aluminum nanoclusters are investigated using density functional theory. Attaching suitable ligand to metal clusters is among the widely popular techniques often used by experimentalists in order to stabilize metastable clusters. In depth theoretical investigations have shown that based on the jellium configuration of the cluster, attaching an electron withdrawing ligand can either make a cluster more reactive toward the C-I dissociation or may convert the cluster relatively inert. The alteration of the activation barriers and other associated parameters due to ligand attachment are included in this paper along with additional calculations and explanations. The study also shows that even the reaction parameters of specific magic clusters can be significantly altered via ligand attachment. The activation process of small molecules on metal clusters are of crucial importance for the development of material science and cluster chemistry. The present investigation will therefore be useful for better understanding of the properties of the ligated clusters as well as may also aid the experimentalists toward controlling the reactivity of a specific cluster as required.

Effect of molecular weight of curing agents on properties of nanocomposites based on epoxy resin and organoclay with reactive modifier - Jagtap, Siddheshwar B.; Ratna, Debdatta (Journal of Applied Polymer Science, 2017)
Nanocomposites of epoxy resin and clay modified with half neutralized salt of Jeffamine D400 were prepared by curing separately with three polyetheramines curing agents of different molecular weights and reactivity. The molecular weight of curing agents and their structural similarity with modifier played an important role in deciding the curing behavior, thermomechanical, and morphological properties of epoxy/clay nanocomposites. Morphological analysis carried out by X-ray diffraction (XRD) and transmission electron microscope (TEM) clearly show that the dispersion of clay layers in epoxy matrix decreases with decreasing molecular weight of the curing agents. Curing study done by using temperature modulated differential scanning calorimetry (MDSC) demonstrates that extragallery reaction rate increases with decreasing molecular weight of curing agents. Dynamic mechanical analysis (DMA) of epoxy/3 wt % modified clay composite prepared by curing with curing agent of higher molecular weight shows around 270% improvement in storage modulus (glassy) as compared with its neat epoxy network.

Effect of phytase and FYM on soil enzyme activities, microbial population and nutrient availability of non-calcareous soil - Jadhav, A.B.; Suradkar, R.; Taggu, B.; Tamboli, B.D.; Priyanka, B. (Journal of the Indian Society of Soil Science, 2017)
A pot culture experiment was conducted to assess the effect of phytase and FYM levels on soil enzyme activities and nutrient availability of non-calcareous soil under soybean cultivation. The treatment consisted of four levels of phytase (0, 1200, 2400 and 3600 IU) and FYM (0, 2.5, 5.0 and 7.5 t ha-1). Enzyme activities and nutrient availability in soil was assessed at 50% flowering and harvest of soybean. It was observed that application of phytase @ 3600 IU recorded significantly higher acid and alkaline phosphatase and dehydrogenase activity at both the growth stages of soybean. Results revealed that significant interaction effect with combine application of phytase @ 3600IU and FYM @ 7.5 t ha-1 recorded higher bacterial, fungal and actinomycetes population. Combined application of phytase @ 3600 IU and FYM @ 7.5 t ha-1 recorded significantly higher available nitrogen (289.3 and 213.6 kg ha-1) and potassium (295.0 and 270.6 kg ha-1) at 50% flowering and at harvest of soybean, respectively. However, in case of phosphorus (P), at 50% flowering significantly higher available P was recorded with phytase @ 3600 IU + 7.5 t ha-1 (23.9 kg ha-1). Reduction trend obtained for calcium carbonate content from 4.24 to 3.68% at 50% flowering and from 4.20 to 3.60% at harvest stage was obtained with the application of phytase @ 3600 IU. This study suggest that application of phytase in combination with manure substantially improves soil biological activities as well as better nutrient supply to crop.

Effect of postharvest ethylene treatment on sugar content, glycosidase activity and its gene expression in mango fruit - Chidley, Hemangi G.; Deshpande, Ashish B.; Oak, Pranjali S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2017)
BACKGROUND: Ripening-associated softening is one of the important attributes that largely determines the shelf-life of mango (Mangifera indica Linn.) fruits. To reveal the effect of pre-climacteric ethylene treatment on ripening-related softening of Alphonso mango, ethylene treatment was given to mature, raw Alphonso fruits. Changes in the pool of reducing and non-reducing sugars, enzymatic activity of three glycosidases: ss-D-galactosidase, alpha-D-mannosidase and ss-D-glucosidase and their relative transcript abundance were analysed for control and ethylene treated fruits during ripening. RESULTS: Early activity of all the three glycosidases and accelerated accumulation of reducing and non-reducing sugars on ethylene treatment was evident. ss-D-Galactosidase showed the highest activity among three glycosidases in control fruits and marked increase in activity upon ethylene treatment. This was confirmed by the histochemical assay of its activity in control and ethylene treated ripe fruits. Relative transcript abundance revealed high transcript levels of ss-D-galactosidase in control fruits. Ethylene-treated fruits showed early and remarkable increase in the ss-D-galactosidase transcriptswhile alpha-D-mannosidase transcript variants displayed early accumulation. CONCLUSION: Thefindings suggest reduction in the shelf-life of Alphonso mango upon pre-climacteric ethylene treatment, a significant role of ss-D-galactosidase and alpha-D-mannosidase in the ripening related softening of Alphonso fruits and transcriptional regulation of their expression by ethylene. (C) 2016 Society of Chemical Industry

Effect of reduction protocol of Pd catalysts on product distribution in furfural hydrogenation - Date, N. S.; Biradar, N. S.; Chikate, R. C.; Rode, C. V. (ChemistrySelect, 2017)
Single step conversion of furfural to ring hydrogenation and decarbonylation products, 2-methyltetrahydrofuran (2-MeTHF) and tetrahydrofuran (THF) in high selectivity was achieved by controlling the particle size of Pd/C catalyst. The particle size variation of Pd/C catalysts in the range of 3.8 to 22 nm could be achieved by employing different reducing agents. Of particular interest was the NaBH4 reduced catalyst (Pd-B/C), which gave the lowest crystallite size of 4.8 nm due to incorporation of B into the inner lattices of Pd-Pd. This phase was evidenced by a characteristic XRD peak of Pd-B at 2q=38.85 degrees as well as a shift of (111) peak (40.07 degrees) of Pd towards the lower value (39.8 degrees). As compared to formaldehyde reduced catalyst (Pd-F/C), Pd-B/C catalyst completely suppressed the formation of furfuryl alcohol to give > 65% selectivity to 2-MeTHF and THF. At 180 degrees C, almost equal distribution of side chain hydrogenation and ring opening products, 2-MF (45%) and PeDO (37 %), respectively, was observed while, higher temperature clearly favoured ring hydrogenation and decarbonylation reactions to give 2-MeTHF and THF.

Effect of Ru precursors and reduction conditions on catalyst performance in glycerol hydrogenolysis - Mane, R.B.; Patil, S.T.; Gurav, H.; Rayalu, S.S.; Rode, C.V. (ChemistrySelect, 2017)
Catalyst precursors, their reduction protocols and reaction conditions integrally influenced the activity and selectivity pattern in glycerol hydrogenolysis. Ru prepared from chloride precursor (Ru(Cl)/C−B) showed the maximum selectivity to C−C cleavage products EG (56 %) and methanol (17 %) with 23 % selectivity to 1,2-PDO. While, that prepared from nitrosyl precursor (Ru(n)/C−B) showed higher selectivity to 1,2-PDO (44 %) and lower to EG (42 %). The catalysts prepared either with chloride or nitrosyl precursors but reduced by H2 showed lower glycerol conversion (10-11 %) than NaBH4 reduced catalysts. For these catalysts, 1,2-PDO selectivity increased to 40–43 % along with the major formation of 2-propanol (48-49 %) and very less selectivities to C−C cleavage products. The lower activity of the H2 reduced catalysts can be related to their lower acidity and the bigger Ru metal particle size (3-5 nm). For Ru(Cl)/C−B catalyst, glycerol conversion increased from 28–97 % with a rise in temperature from 180 to 250 oC also favoring 1,2-PDO selectivity; indicating that C−O bond cleavage was favoured in comparison to C−C scission, at higher temperature.

Effect of shape of protrusions and roughness on the hydrophilicity of a surface - Chowdhury, Sheelan Sengupta; Pandey, Prithvi Raj; Kumar, Rajnish; Roy, Sudip (Chemical Physics Letters, 2017)
We have investigated wetting of model rough surfaces made up of hydrophilic triangular and hexagonal pillars (protrusions). The surface roughnesses are altered by varying the area of the rough surface, the height of the pillars, and the surface interactions to the water. We have established a correlation between structure i.e., the shape of a pillar, which actually depends on the number of edges (due to shape), and the wetting phenomena. We have found that surface with higher number of edges repels water at lower roughness value. We explain the correlation by analyzing the variation of interactions energy components and density profiles of water on the structured surfaces. (C) 2017 Elsevier B.V. All rights reserved.

Effect of side-chain functionality on the organic field-effect transistor performance of oligo(p-phenylenevinylene) derivatives - Chini, Mrinmoy Kumar; Chatterjee, Shyambo (Journal of Applied Polymer Science, 2017)
In order to observe the effects of the substitution of electronegative flourine with aromatic groups in oligo(p-phenylenevinylene) compounds on their packing, morphology, and charge carrier mobility, we have synthesized napthol-substituted oligo(p-phenylenevinylene) compounds and examined their solubility, redox properties, thin film morphologies, and charge carrier properties. To date, very few examples of conjugated oligomers bearing napthol side groups have been reported in the literature. After annealing at 150 degrees C, the mobility of S1, S2, and S3 was 4.0x10(-2) cm(2) V-1 s(-1), 1.2x10(-2) cm(2) V-1 s(-1), and 2.6x10(-3) cm(2) V-1 s(-1), respectively. (c) 2017 Wiley Periodicals, Inc.

Effect of size and site preference of trivalent non-magnetic metal ions (Al3+, Ga3+, In3+) substituted for Fe3+ on the magnetostrictive properties of sintered CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Journal of Physics D-Applied Physics, 2017)
The influence of size and crystallographic site preference of three non-magnetic isovalent metal ions of larger (In3+), comparable (Ga3+) and smaller (Al3+) sizes, substituted for Fe3+ in the spinel lattice of CoFe2O4 on its magnetostrictive properties is compared. For the different compositions in CoFe2-xMxO4 (M = In3+, Ga3+, Al3+ and 0 <= x <= 0.3), significant changes in the structural and magnetic parameters are observed with the degree of substitution, due to the size and site preferences. Magnetic and Raman spectral studies revealed that Al3+ is substituted for Fe3+ at both octahedral and tetrahedral sites for all compositions, whereas In3+ and Ga3+ are substituted for Fe3+ at the tetrahedral site only for x <= 0.2 and partly at the octahedral site for x > 0.2. Regardless of the differences in the ionic size, site preference and the magnetic properties, compositions in all three series with x = 0.1 showed almost equal magnitude of maximum magnetostriction (lambda(max) = similar to 230 ppm), marginally higher than that of x = 0 (217 ppm). However, at higher substituted compositions, lambda(max) is decreased with x, but the decrease is much faster for the Al-substituted compositions. The maximum strain sensitivity, [d lambda/dH](max), is also found to be comparable for all three compositions. The comparable magnetostriction characteristics and high strain at low magnetic fields for different substituted compositions at low levels of substitution are attributed to the local structural distortions associated with the inhomogeneous distribution of the substituted ions in the spinel ferrite lattice. The studies suggest ways to optimise the magnetostriction properties of properly substituted sintered cobalt ferrite for applications in sensors and actuators.

Effect of viscoelastic relaxation modes on stability of extrusion film casting process modeled using multi-mode Phan-Thien-Tanner constitutive equation - Dhadwal, Renu; Banik, Sourya; Doshi, Pankaj; Pol, Harshawardhan (Applied Mathematical Modelling, 2017)
Extrusion film casting (EFC) is a commercially important process that is used to produce a significant quantity of polymer films, sheets and coatings for both industrial and household applications. Recently, we have demonstrated the influence of polymer chain architecture on the extent of necking under isothermal as well as non-isothermal film casting operation for commercially relevant polyolefin based materials [1-4]. In the present research, we focus on another instability that frequently occurs in high-speed EFC process called as draw resonance. Draw resonance manifests itself as an instability that causes periodic fluctuations in both the width as well as thickness of the extruded molten film above a critical draw ratio (DR). In this work, we have carried out a linear stability analysis of the isothermal EFC process using a multi-mode Phan-Thien-Tanner (PTT) constitutive equation to determine the onset of draw resonance. We show that as the number of relaxation modes is increased there is a dramatic change in the stability regions. In particular, there is a marked variation in the stability regions obtained by Simulating the multi-mode model and those obtained by taking averaged relaxation time of the modes. Additionally, as the number of faster-relaxing modes in a multi-mode spectrum is progressively increased, the process becomes increasingly stable as the level of elasticity in the melt decreases. Finally, the addition of a long relaxation mode in a multi-mode spectrum is akin to adding a long chain branch to a linear polymer that leads to a reduction in film necking and in many cases to enhanced process stability. (C) 2017 Elsevier Inc. All rights reserved.

Effective degradation of organic water pollutants by atmospheric non-thermal plasma torch and analysis of degradation process - Bansode, Avinash H.; More, Supriya Eknath; Siddiqui, Ejaz Ahmad; Satpute, Shruti; Ahmad, Absar; Bhoraskar, Sudha V.; Mathe, Vikas L. (Chemosphere, 2017)
The paper reports the use of atmospheric non-thermal plasma torch as a catalyst for degradation of various organic pollutants dissolved in water. A flow of He mixed with air was used to produce the dielectric barrier discharge (DBD), at the tip of the torch, using pulsed electric excitation at 12 kV. The torch, operated at a power of 750 mW/mm², was seen to completely degrade the aqueous solutions of the pollutants namely methylene blue (MB), methyl orange (MO) and rhodamine-B (RB), at around 10⁻⁴ M concentrations, the concentration of polluants is one order higher than of routinely used heterogeneous photocatalytic reactions, within 10 min of irradiation time at room temperature. UV Visible spectra of the organic dye molecules, monitored after different intervals of plasma-irradiation, ranging between 1 and 10 min, have been used as tools to quantify their sequential degradation. Further, instead of using He, only air was used to form plasma plume and used for degradation of organic dye which follow similar trend as that of He plasma. Further, Liquid Chromatography Mass Spectroscopy (LCMS) technique has been used to understand degradation pathway of methylene blue (MB) as a representative case. Total organic carbon (TOC) measurements indicates significant decrease in its content as a function of duration of plasma exposure onto methylene blue as a representative case. Toxicity studies were carried out onto Gram negative Escherichia coli. This indicated that methylene blue, without plasma treatment, shows growth inhibition, whereas with plasma treatment no inhibition was observed.

Effects of micellization on growth kinetics of methane hydrate - Bhattacharjee, Gaurav; Kushwaha, Omkar Singh; Kumar, Asheesh; Khan, Muzammil Yusuf; Patel, Jay Narayan; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2017)
Surfactants are Specific functional materials, that form various types of self-assemblies and affect local water ordering alongside solution properties. Such surface active agents are used extensively in gas hydrate based applications as kinetic hydrate promoters. To understand the effect of surfactant micelles on hydrate formation kinetics, a novel surfactant system capable of producing micelles at hydrate forming temperature was developed. The presence of surfactant micelles in this new system (a combination of anionic surfactant SDS and zwitterionic surfactant CAPB) was determined through DLS measurements. Pure methane and a coal bed methane mixture were individually used to assess the efficacy of the surfactant mixture for hydrate formation. This study conclusively proves for the first time that the presence of surfactant micelles enhances hydrate formation kinetics. The findings reported here can contribute significantly toward improving the utility of surfactants in gas hydrate based technological applications such as gas separation and methane storage.

Efficient and durable oxygen reduction electrocatalyst based on CoMn alloy oxide nanoparticles supported over N-doped porous graphene - Singh, Santosh K.; Kashyap, Varchaswal; Manna, Narugopal; Bhange, Siddheshwar N.; Soni, Roby; Boukherroub, Rabah; Szunerits, Sabine; Kurungot, Sreekurnar (ACS Catalysis, 2017)
Transition metal oxide derived materials are very important for various applications, such as electronics, magnetism, catalysis, electrochemical energy conversion, and storage. Development of efficient and durable catalysts for the oxygen reduction reaction (ORR), an important reaction in fuel cells and metal air batteries, is highly desirable. Moreover, the futuristic catalysts for these applications need to be costeffective in order to ensure a competitive edge for these devices in the energy market. This article describes the synthesis of a cost-effective and efficient electrocatalyst for ORR It is based on supporting CoMn alloy oxide nano particles on N-doped porous graphene through a simple and scalable microwave irradiation method. Microwave irradiation was found to be very crucial for the fast creation of pores in the graphene framework with a concomitant formation of the CoMn alloy oxide nanoparticles. A series of catalysts have been synthesized by varying the Co:Mn ratio, among which, the one with the Co:Mn ratio of 2:1 [designated as CoMn/pNGr(2:1)] displayed remarkably higher ORR activity in 0.1 M KOH solution. It showed a similar to 60 mV potential shift with a low Tafel slope of 74 mV/decade, which is comparable to that derived from the commercial Pt/C catalyst. This high activity of CoMn/pNGr(2:1) has been credited to the cooperative effect arising from the metal entities and the defects present in the N-doped porous graphene. Finally, real system-level validations of the use of CoMn/pNGr(2:1) as cathode catalyst could be performed by fabricating and testing single-cells of an anion-exchange membrane fuel cell (AEMFC) and a primary Zn-air battery, which successfully demonstrated the efficiency of the catalyst to facilitate ORR in real integrated systems of the single-cell assemblies.
Keywords: anion-exchange membrane fuel cell; cooperativity effect; microwave synthesis; oxygen reduction reaction; porous N-doped graphene; Zn-air battery

Efficient exciton to dopant energy transfer in Mn2+-Doped (C4H9NH3)2PbBr4 two-dimensional (2D) layered perovskites - Biswas, A. (Chemistry of Materials, 2017)
Three-dimensional ABX3 perovskite material has attracted immense interest and applications in optoelectronic devices, because of their enabling properties. Recently, Mn2+ doping directly into APbCl3-type three-dimensional (3D) nanocrystals, manifesting host-to-dopant energy transfer, have been reported for LED display applications. Strongly bound excitons in the doped system can enhance the dopant-carrier exchange interactions, leading to efficient energy transfer. Here, we report the simple and scalable synthesis of Mn2+-doped (C4H9NH3)2PbBr4 two-dimensional (2D) layered perovskites. The Mn2+-doped 2D perovskite shows enhanced energy transfer efficiency from the strongly bound excitons of the host material to the d electrons of Mn2+ ions, resulting in intense orange-yellow emission, which is due to spin-forbidden internal transition (4T1 → 6A1) with the highest quantum yield (Mn2+) of 37%. Because of this high quantum yield, stability in ambient atmosphere, and simplicity and scalability of the synthetic procedure, Mn2+-doped 2D perovskites could be beneficial as color-converting phosphor material and as energy down-shift coating for perovskite solar cells. The newly developed Mn2+-doped 2D perovskites can be a suitable material to tune dopant-exciton exchange interactions to further explore their magneto-optoelectronic properties.
Keywords: Doping (additives); Energy Efficiency; Energy Transfer; Exchange interactions; Excitons; Light Emitting Diodes

Efficient hydrogenation of concentrated aqueous furfural solutions in to furfuryl alcohol under ambient conditions in presence of PtCo bimetallic catalysts - Dohade, Manisha; Dhepe, Paresh Laxmikant (Green Chemistry, 2017)
Furfural (FAL), a major biomass-derived chemical, can be hydrogenated to yield the industrially importantplatform chemical, furfuryl alcohol (FOL). Although heterogeneous catalyst-based methods are known toyield FOL from dilute solutions of FAL, they mainly operate at high temperatures and/or high pressures ofhydrogen and in the presence of organic solvents. In this work, we employ bimetallic PtCo/C catalysts withvarying metal concentrations to achieve the maximum possible FOL yield (100%) at 35 °C under 0.1 MPa H2in water. With concentrated FAL (40 wt%) at 50 °C and under 1 MPa H2pressure, 86% yield of FOL wasobserved. Moreover, eﬃcient catalyst recycling was observed over at least four runs with marginal loss inactivity due to handling error and isolation of FOL in pure form conﬁrmed by NMR and HPLC.Characterization of catalysts with several physico-chemical techniques (XRD, TEM, XPS, ICP, TPR) revealsthe presence of electron-rich Pt and ionic Co species in proximity with each other and these worksynergistically to facilitate maximum possible yield of FOL under ambient conditions and in water medium

Efficient organic photovoltaics with improved charge extraction and high short-circuit current - Mohan, Minu; Nandal, Vikas; Paramadam, Sanish; Reddy, Kasala Prabhakar; Ramkumar, Sekar; Agarwal, Sumanshu; Gopinath, Chinnakonda S.; Nair, Pradeep R.; Namboothiry, Manoj A. G. (Journal of Physical Chemistry C, 2017)
Exciton generation, dissociation, free carrier transport, and charge extraction play an important role in the short-circuit current (J(sc)) and power conversion efficiency of an organic bulk heterojunction (BHJ) solar cell (SC). Here we study the impact of band offset at the interfacial layer and the morphology of active layer on the extraction of free carriers. The effects are evaluated on an inverted BHJ SC using zinc oxide (ZnO) as a buffer layer, prepared via two different methods: ZnO nanoparticle dispersed in mixed solvents (ZnO A) and sol-gel method (ZnO B). The device with ZnO A buffer layer improves the charge extraction and J(sc),. The improvement is due to the better band offset and morphology of the blend near the ZnO A/active layer interface. Further, the numerical analysis of current-voltage characteristics illustrates that the morphology at the ZnO A/active layer interface has a more dominant role in improving the performance of the organic photovoltaic than the band offset.

Efficient oxidation of ethyl benzene using in situ generated molybdenum acetylide oxo-peroxo complex as recyclable catalyst - Khomane, Sonali B.; Doke, Dhananjay S.; Dongare, M. K.; Halligudi, S. B.; Umbarkar, S. B. (Applied Catalysis A-General, 2017)
Selective oxidation of various alkanes/alkyl aromatics to corresponding carbonyl compounds has been carried out with very high conversion (similar to 98%) and selectivity (up to 100%) for carbonyl compounds using cyclopentadienyl molybdenum acetylide complex, CpMo(CO)(3)(C CPh) (1) as catalyst and tert-butyl hydrogen peroxide (TBHP) as an oxidant and turnover number (TON) of 88 was obtained with turnover frequency (TOF) of 2.45 h(-1). Mo acetylide oxo-peroxo species is formed in situ by reaction of 1 with TBHP during the course of reaction as catalytically active species. Interestingly even though the catalytically active species is homogeneous in nature it could be recycled very easily by recovering the catalytically active species as solid after addition of diethyl ether, and separating the products into organic phase. In the case of ethyl benzene oxidation, even after three recycles no appreciable loss in ethyl benzene conversion and acetophenone selectivity was observed. This complex showed high catalytic activity for the oxo functionalization of other alkyl aromatics and alkanes such as substituted ethyl benzenes, toluene as well as cyclohexane. TBHP was found to be more efficient oxidant than hydrogen peroxide for this oxidation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Alkyl aromatics; Carbonyl compounds; Homogeneous catalysis; Molybdenum acetylide complex; Oxo-peroxo species

Efficient palladium catalyzed Mizoroki-Heck cross-coupling in water - Jadhav, Sanjay N.; Rode, Chandrashekhar V. (Green Chemistry, 2017)
The homogeneous Pd-catalysed Mizoroki-Heck coupling reaction was successfully performed in water in the absence of any additives under aerobic conditions. The various key reaction parameters that affect the yield of the desired cross-coupling product were optimized. The Pd(PPh3)(4)/Et3N/H2O/98 degrees C catalyst system was found to be highly active (TOF = 12 to 14 h(-1)) towards achieving excellent yield of the Mizoroki-Heck coupling products for a wide range of electron-withdrawing as well as electron-donating aryl bromides and chlorides in the shortest reaction time. Pd(PPh3) 4 catalyst deactivation during the Mizoroki-Heck coupling reaction was investigated and to evolve a strategy for achieving ten times Pd-metal recyclability without appreciable loss of its activity. Thus, the proposed mechanism provides access to a variety of olefins in aqueous medium, making this protocol eco-friendly.

Efficient Sn(II)-catalyzed one-pot synthesis of a 3-substituted azetidine-2,4-dione framework - Chavan, Santosh S.; Supekar, Mrudul V.; Burate, Pralhad A.; Rupanwar, Bapurao D.; Shelke, Anil M.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2017)
A novel Sn(II)-catalyzed tandem cyclization reaction of aromatic aldehydes with ethyl cyanoacetate has been achieved to afford a series of 3-substituted azetidine-2,4-diones in good to excellent yields. This protocol provides straightforward access to construct the azetidine core through sequential Knoevenagel condensation, hydration and the C-N cyclization reaction.

Efficient synthesis of functionalized olefins by wittig reaction using amberlite resin as a mild base - Valkute, Tushar R.; Aratikatla, Eswar K.; Bhattacharya, Asish K. (Synthetic Communications, 2017)
A convenient procedure for the synthesis of olefins by the reaction of stabilized, semistabilized, and nonstabilized phosphorous ylides with various aldehydes or ketone using Amberlite resin as a mild base is described. Our developed method offers facile and racemization-free synthesis of ,-unsaturated amino esters and chiral allylic amine. The developed methodology offers mild reaction conditions, high efficiency, and facile isolation of the final products, a practical alternative to known procedures

Efficient synthesis of the opioid analgesic (R)-phenampromide via an aziridinium ion - Mujahid, Mohammad; Mujumdar, Prashant; Sasikumar, Murugesan; Deshmukh, Shirish P.; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2017)
A simple and efficient synthesis of the opioid analgesic agent (R)-phenampromide with high enantiopurity (> 99% ee) via the formation of an aziridinium ion as a key step using commercially available starting material is described. (C) 2017 Elsevier Ltd. All rights reserved.

Efficient trifluoromethylation of C(sp(2))-H functionalized alpha-oxoketene dithioacetals: a route to the regioselective synthesis of functionalized trifluoromethylated pyrazoles - Sharma, N.; Kumari, N.; Chundawat, T. S.; Kumar, S.; Bhagat, S. (RSC Advances, 2017)
An operationally simple approach for the regioselective construction of diversely substituted trifluoromethylated pyrazoles via nucleophilic trifluoromethylation of iodo-substituted alpha-oxoketene dithioacetals is described. X-ray crystallographic studies confirmed the trifluoromethylation as well as formation of a regioselective cyclized product. Furthermore, trifluoromethylated pyrazoles bearing thiomethyl groups may allow further functionalization and are of considerable interest in medicinal chemistry.

Efficient valorisation of palm shell powder to bio-sorbents for copper remediation from aqueous solutions - Kushwaha, Shilpi; Soni, Harnish; Bojja, Sreedhar; Padmaja, P. (Journal of Environmental Chemical Engineering, 2017)
Alternative bio-sorbents, prepared from cost effective pre-treatment of biomass have been used to remediate toxic heavy metals. Palm shell powder (PSP) and acid treated palm shell powder (APSP) provide an attractive approach for the removal of Cu(II) from aqueous solutions and further use of the copper loaded adsorbents as catalysts. PSP was charred with sulfuric acid (H2SO4) to oxidize ligno-cellulosic groups present in PSP, resulted in acid treated palm shell powder (APSP). Structure property relationship was explored with the help of sophisticated spectroscopic tools (¹³C nuclear magnetic resonance (¹³C NMR), X-Ray photoelectron spectroscopy (XPS), X-Ray diffraction (XRD) and Fourier-transform infrared (FTIR) spectroscopy). Pretreatment lead to conversion of ligno-cellulosic content to more valuable and easily process-able polysaccharide content.APSP and PSP displayed a maximum adsorption capacity of 125 and 36 mg/g respectively for copper. Copper adsorption was found to be more in APSP due to presence of COOH groups which rendered the surface more hydrophilic and amenable to enhanced Cu²⁺ sorption. Furthermore the adsorbents loaded with copper could be used as catalysts for oxidation of styrene. The developed adsorbents promise advantages such as low cost, high adsorption capacity, environmental friendliness as well as zero sludge.

Elastic compressible energy storage devices from ice templated polymer gels treated with polyphenols - Das, Chayanika; Chatterjee, Soumyajyoti; Kumaraswamy, Guruswamy; Krishnarnoorthy, Kothandam (Journal of Physical Chemistry C, 2017)
Design and fabrication of rechargeable energy storage devices that are robust to mechanical deformation is essential for wearable electronics. We report the preparation of compressible supercapacitors that retain their specific capacitance after large compression and that recover elastically after at least a hundred compression expansion cycles. Compressible supercapacitors are prepared using a facile, scalable method that readily yields centimeter-scale macroporous objects. We ice template a solution of polyethylenimine in green tea extract to prepare a macroporous cross-linked polymer gel (PG) whose walls are impregnated with green tea derived polyphenols. As the PG is insulating, we impart conductivity by deposition of gold on it. Gold deposition is done in two steps: first, silver nanoparticles are formed on the PG walls by in situ reduction by polyphenols and then gold films are deposited on these walls. Gold coated PGs (GPGs) were used as electrodes to deposit poly(3,4-ethylenedioxythiophene) as a pseudocapacitive material. The specific capacitance of PEDOT coated GPGs (PGPG) was found to be 253 F/g at 1 A/g. PGPG could be compressed and expanded over a hundred cycles without any suffering mechanical failure or loss of capacitative performance. The capacitance was found to be 243 F/g upon compressing the device to 25% of its original size (viz. compressive strain = 75%). Thus, even large compression does not affect the device performance. This device shows power and energy densities of 2715 W/kg and 22 Wh/kg, respectively, in the uncompressed state. The macroporous nature of PGPG makes it possible to fill the PGPG pores with gel electrolyte. We report that the gel electrolyte filled supercapacitor exhibited a specific capacitance of 200 F/g, which increased by 4% upon 75% compression.

Electrical resistance tomography for gas holdup in a gas-liquid stirred tank reactor - Sardeshpande, Madhavi V.; Gupta, Suraj; Ranade, Vivek V. (Chemical Engineering Science, 2017)
Gas-Liquid flows in stirred tank reactors (STR) are used in many significant industrial operations such as hydrogenation, absorption, stripping, oxidation, hydrogenation, ozonation, chlorination, fermentation, etc. Gas-Liquid STRs are expected to perform several functions such as mixing, dispersing gas into liquid, mass and heat transfer and reactions. Gas hold up distribution and various flow regimes are the key parameters affecting performance of gas-liquid STRs. Various techniques such as visual analysis, photography, light attenuation, optical probe method are used to understand gas hold-up distribution within stirred tanks. Most of these techniques have some limitations with respect to measurement of gas hold up distribution. Electrical Resistance Tomography (ERT) is an upcoming technique for obtaining both qualitative and quantitative data on multiphase process units non-invasively and non-intrusively. In this work, an attempt was made to establish and validate the ERT technique for characterizing gas-liquid flows in a laboratory scale STR using the Rushton turbine impeller. ERT was used to study gas holdup and to identify flow regimes. The results were compared with the visual measurements as well as previously published correlations. The effect of gas flow rate, impeller speed on the mean gas holdup is discussed. The methodology and results presented in this work will be useful to effectively apply ERT for characterizing gas-liquid flows in stirred tanks. (C) 2017 Elsevier Ltd. All rights reserved.

Electrochemical formation of Fe-V (O) and mechanism of its reaction with water during O-O bond formation - Pattanayak, Santanu; Chowdhury, Debarati Roy; Garai, Bikash; Singh, Kundan K.; Paul, Amit; Dhar, Basab B.; Sen Gupta, Sayam (Chemistry-A European Journal, 2017)
A detailed electrochemical investigation of a series of iron complexes (biuret-modified tetraamido iron macrocycles FeIII-bTAML), including the first electrochemical generation of Fe-V(O), and demonstration of their efficacy as homogeneous catalysts for electrochemical water oxidation (WO) in aqueous medium are reported. Spectroelectrochemical and mass spectral studies indicated FeV(O) as the active oxidant, formed due to two redox transitions, which were assigned as Fe-IV(O)/Fe-III(OH2)and Fe-V(O)/Fe-IV(O). The spectral properties of both of these high-valent iron oxo species perfectly match those of their chemically synthesised versions, which were thoroughly characterised by several spectroscopic techniques. The O-O bond-formation step occurs by nucleophilic attack of H2O on FeV(O). A kinetic isotope effect of 3.2 indicates an atom-proton transfer (APT) mechanism. The reaction of chemically synthesised Fe-V(O) in CH3CN and water was directly probed by electrochemistry and was found to be first-order in water. The pK(a) value of the buffer base plays a critical role in the rate-determining step by increasing the reaction rate several-fold. The electronic effect on redox potential, WO rates, and onset overpotential was studied by employing a series of iron complexes. The catalytic activity was enhanced by the presence of electron-withdrawing groups on the bTAML framework. Changing the substituents from OMe to NO2 resulted in an eightfold increase in reaction rate, while the overpotential increased threefold.

Electrochemical synthesis of a ternary transition metal sulfide nanosheets on nickel foam and energy storage application - Sahoo, Surjit; Naik, Kusha Kumar; Late, Dattatray J.; Rout, Chandra Sekhar (Journal of Alloys and Compounds, 2017)
We report growth of nickel cobalt sulfide (NCS) ultrathin nanosheets directly on Ni foam substrate by a facile and novel electrodeposition method. The as-prepared NCS sample is used as an electrode material for supercapacitor application due to their large electrochemically active surface area and interconnected nanosheet channels for the facilitation of ion transportation. The NCS nanosheets possess enhanced electrochemical performance in terms of fast and high reversible faradaic reactions characterized by prominent oxidation and reduction peaks. NCS nanosheets showed an ultrahigh specific capacitance of 1712 Fg(-1) at a current density of 1 Ag-1 with excellent cyclic stability. The excellent supercapacitor performance of NCS nanosheets can be attributed to its rich redox reactions as well as high transport rate for both electrolyte ions and electrons. (C) 2016 Elsevier B.V. All rights reserved.

Electrochemical water oxidation catalyzed by an in situ generated alpha-Co(OH)(2) film on zeolite-Y surface - Bose, Suranjana; Debgupta, Joyashish; Ramsundar, Rani M.; Das, Samar K. (Chemistry-A European Journal, 2017)
The design and synthesis of an efficient and robust water-oxidation catalyst with inexpensive materials remains an important challenge in the context of artificial photosynthesis. Herein, a simple but unique technique is reported to in situ generate a thin-film of alpha-Co(OH)(2) on the surface of zeolite-Y [hereafter referred to as Y-alpha-Co(OH)(2)] that acts as an efficient and stable catalyst for electrochemical water oxidation in alkaline medium. Catalyst Y-alpha-Co(OH)(2) is so stable that it retains its catalytic activity even after 2000 cyclic voltammetric cycles of water oxidation. Expectedly, the chemical composition of alpha-Co(OH)(2) on the surface of zeolite-Y remains same as that of parent Y-alpha-Co(OH)(2) after 2000 electrocatalytic cycles. A Tafel slope as low as 59 mV decade(-1) in 0.1m KOH (pH 13) suggests faster oxygen evolution kinetics (overpotential = 329 mV; turnover frequency = 0.35 mol O-2 (mol Co)(-1)s(-1) at 1 mA cm(-2)) than the existing alpha-Co(OH)(2)-based electrocatalysts operating in alkaline medium.

Electrodeposited nickel cobalt manganese based mixed sulfide nanosheets for high performance supercapacitor application - Sahoo, S.; Mondal, R.; Late, D. J.; Rout, C. S. (Microporous and Mesoporous Materials, 2017)
Porous multi component Nickel Cobalt Manganese Sulfide (NCMS) nanosheets have been grown on Ni foam by cathodic electrodeposition method. The as-prepared NCMS nanosheets sample is used as an electrode material for supercapacitor application due to its large electrochemically active surface and high porosity structure. Moreover, NCMS nanosheets have good electrical and mechanical connections to the conductive Ni foam to achieve enhanced reaction kinetics with improved electrode integrity. The NCMS nanosheets exhibit an ultrahigh specific capacitance of 2717 Fig at a current density of 1 Aug with excellent cyclic stability and energy density of 94.07 Wh/kg. The electrodeposited NCMS nanosheets with extraordinary electrochemical performance enable the novel electrodes to hold great potential for high efficient energy storage systems.

Electronic control on linear versus branched alkylation of 2-/3-aroylbenzofurans with acrylates: combined DFT and synthetic studies - Srinivas, Kolluru; Dangat, Yuvraj; Kommagalla, Yadagiri; Vanka, Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2017)
Investigations on the factors that govern unusual branched alkylation of 2-aroylbenzofurans with acrylates by Ru-catalyzed carbonyl-directed C-H activation has been carried out by calculating the kinetics associated with the two key steps-the coordination of the acrylate with the intermediate ruthenacycle and the subsequent migratory insertion reaction-studied with the help of DFT calculations. Eight possible orientations for each mode of alkylation have been considered for the calculations. From these calculations, it has been understood that there is a synergistic operation of the steric and electronic effects favoring the branched alkylation. Further DFT investigations on the alkylation of the isomeric 3-aroylbenzofurans indicated a preference for the linear alkylation and this has been verified experimentally. Overall, the observed/calculated complementary selectivity in the alkylation of 2-/3-aroylbenzofurans with acrylates reveals that the substrate-dependent charge distribution of the Ru-C bond in the intermediate ruthenacycle is an important determining factor and thus the current work opens up a new domain of substrate design for controlling regioselectivity.
Keywords: acrylates; Alkylation; aroylbenzofuran; C-H activation; Density functional calculations

Electron–nucleus scalar–pseudoscalar interaction in PbF: Z-vector study in the relativistic coupled-cluster framework - Sasmal, S.; Talukdar, K.; Nayak, M.K.; Vaval, N.; Pal, S. (Molecular Physics, 2017)
The scalar–pseudoscalar interaction constant of PbF in its ground state electronic configuration is calculated using the Z-vector method in the relativistic coupled-cluster framework. The precise calculated value is very important to set upper bound limit on (Formula presented.)-odd scalar–pseudoscalar interaction constant, ks, from the experimentally observed (Formula presented.)-odd frequency shift. Further, the ratio of the effective electric field to the scalar–pseudoscalar interaction constant is also calculated which is required to get an independent upper bound limit of electric dipole moment of electron, de, and ks and how these (de and ks) are interrelated is also presented here. © 2017 Informa UK Limited, trading as Taylor & Francis Group

Electrostatic origin of the red solvatochromic shift of DFHBDI in RNA spinach - Bose, Samik; Chakrabarty, Suman; Ghosh, Debashree (Journal of Physical Chemistry B, 2017)
Interactions with the environment tune the spectral properties of biological chromophores, e.g., fluorescent proteins. Understanding the relative contribution of the various types of noncovalent interactions in the spectral shifts can provide rational design principles toward developing new fluorescent probes. In this work, we investigate the origin of the red shift in the absorption spectra of the difluoro hydroxybenzylidene dimethyl imidazolinone (DFHBDI) chromophore in RNA spinach as compared to the aqueous solution. We systematically decompose the effects of various components of interactions, namely, stacking, hydrogen bonding, and long-range electrostatics, in order to elucidate the relative role of these interactions in the observed spectral behavior. We find that the absorption peak of DFHBDI is red-shifted by similar to 0.35 eV in RNA relative to the aqueous solution. Earlier proposals from Huang and co-workers have implicated the stacking interactions between DFHBDI and nucleic acid bases to be the driving force behind the observed red shift. In contrast, our findings reveal that the long-range electrostatic interactions between DFHBDI and negatively charged RNA. make the most significant contribution. Moreover, we notice that the opposing electrostatic fields due to the RNA backbone and the polarized water molecules around the RNA give rise to the resultant red shift. Our results emphasize the effect of strong heterogeneity in the various environmental factors that might be competing with each other.

Elucidating the photoprotection mechanism of eumelanin monomers - Ghosh, Paulami; Ghosha, Debashree (Journal of Physical Chemistry B, 2017)
Eumelanin, the functional polymer in human skin, forms a heterogeneous layered structure intrinsic to its broadband monotonic spectra. The inherent structural heterogeneity of eumelanin makes the photoprocesses very complex and diverse in nature. Due to this diversity, a complete mechanistic picture of these photoprocesses, essential to understanding the photoprotective properties, has been missing to date. In this study, we recreate the potential energy surfaces of the low-lying excited states of the multiple monomeric forms of eumelanin constituents that play a prominent role in either photoprotection or photodamage pathways. Our results indicate a diverse set of pathways for the photoexcited species to relax back to the ground state, that depends on the specific monomeric form. Furthermore, the excited state reaction channels show the scope of extensive interconversion between the different monomers and therefore, we propose that the heterogeneity of eumelanin is key to its photoprotection capability.

Elucidation of molecular mechanism of stability of the heme-regulated eIF2α kinase upon binding of its ligand, hemin in its catalytic kinase domain - Bhavnani, V. (Journal of Biomolecular Structure and Dynamics, 2017)
The eIF2α kinase activity of the heme-regulated inhibitor (HRI) is regulated by heme which makes it a unique member of the family of eIF2α kinases. Since heme concentrations create an equilibrium for the kinase to be active/inactive, it becomes important to study the heme binding effects upon the kinase and understanding its mechanism of functionality. In the present study, we report the thermostability achieved by the catalytic kinase domain of HRI (HRI.CKD) upon ligand (heme) binding. Our CD data demonstrates that the HRI.CKD retains its secondary structure at higher temperatures when it is in ligand bound state. HRI.CKD when incubated with hemin loses its monomeric state and attains a higher order oligomeric form resulting in its stability. The HRI.CKD fails to refold into its native conformation upon mutation of H377A/H381A, thereby confirming the necessity of these His residues for correct folding, stability, and activity of the kinase. Though our in silico study demonstrated these His being the ligand binding sites in the kinase insert region, the spectra-based study did not show significant difference in heme affinity for the wild type and His mutant HRI.CKD.
Keywords: Heme Regulated Inhibitor (HRI); HRI-eIF2α Complex; Protein–Ligand Modeling; Thermostability

Enantioselective synthesis of functionalized β-lactones by NHC-catalyzed aldol lactonization of ketoacids - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
N-Heterocyclic carbene (NHC)-catalyzed intramolecular aldol lactonization of readily available ketoacids leading to the enantioselective synthesis of cyclopentane-fused β-lactones is presented. The reaction proceeds via the generation of NHC-bound enolate intermediates formed from the ketoacids in the presence of the peptide coupling reagent HATU and NHC generated from the chiral triazolium salt. The functionalized β-lactones are formed under mild conditions in high yields and enantioselectivities.

Enantioselective synthesis of spiro γ-butyrolactones by N-heterocyclic carbene (NHC)-catalyzed formal [3+2] annulation of enals with 3-hydroxy oxindoles - Mukherjee, Subrata; Joseph, Sumi; Bhunia, Anup; Gonnade, Rajesh Ghanshyam; Reddy, Santhi Vardhan; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2017)
The N-heterocyclic carbene (NHC)-catalyzed enantioselective formal [3 + 2] annulation of α,β-unsaturated aldehydes with 3-hydroxy oxindoles is presented. Under oxidative conditions using the bisquinone oxidant, the reaction resulted in the synthesis of spiro γ-butyrolactones in moderate to good yields, enantioselectivity and diastereoselectivity. The reaction likely proceeds via the generation of the NHC-bound α,β-unsaturated acylazolium intermediate from enals, which was intercepted by the dioxindoles in a formal [3 + 2] pathway to form the spirocyclic compounds. However, a deeper mechanistic investigation revealed that the reaction can also proceed via the homoenolate intermediate. In this case, the dioxindole was oxidized to the corresponding isatin derivative using traces of air under basic conditions, and was intercepted with the NHC-bound homoenolate intermediate in a formal [3 + 2] pathway to afford the spiro compound.

Engineering cell surface glycans with carbohydrate enantiomers to alter bacterial binding and adhesion - Gade, Madhuri; Chaudhary, Preeti Madhukar; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemistryselect, 2017)
Chirality of carbohydrate has critical functions in many biological processes. Changes in the configuration of even one sugar molecules may cause abnormal behavior or even inhibit specific processes. Herein, we have shown bioorthogonal conjugation of mannose enantiomers on HeLa cell surfaces induced a different rate of bacterial binding and cell adhesion.
Keywords: Bioorthogonal reaction; Carbohydrate; E. coli; Enantiomer; Surfaces functionalization

Engineering molecular topology: A pseudopeptidic macrocyclic figure-eight motif - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P.; Butcher, Ray; Haridas, V. (European Journal of Organic Chemistry, 2017)
We herein present a rational-design strategy for the synthesis of molecules with figure-eight topology. The design concept is based on the incorporation of turn units in the back-bone of the macrocycle. The molecular structures and the folding are studied by X-ray crystallography and NMR, FT-IR, and CD spectroscopy.
Keywords: Macrocycles; noncovalent interactions; Pi interactions; topology; X-ray diffraction

Enhanced field emission characteristics of a 3D hierarchical Hfo2-Zno heteroarchitecture - Shisode, Raju T.; Suryawanshi, Sachin R.; Mistari, Chetan D.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Three dimensional (3D) HfO2-ZnO heteroarchitecture comprised of thin coating of HfO2 on self assembled 3D ZnO urchins with pointed apex has been synthesized using hydrothermal route followed by Pulsed Laser Deposition (PLD). The as-synthesized HfO2-ZnO heteroarchitecture was characterized using XRD, SEM, EDS, and (HR) TEM, in order to reveal its structural, morphological, and chemical properties. The HfO2-ZnO heteroarchitecture emitter exhibits superior field emission (FE) behaviour in contrast to the pristine ZnO urchins, demonstrated by delivery of high emission current density of similar to 885 mA/cm2 at an applied field of similar to 3.35 V/mm, against similar to 383 mA/cm(2) at an applied field of similar to 4.32 V/mu m for the pristine ZnO urchins emitter. Interestingly, the HfO2-ZnO heteroarchitecture emitter exhibits excellent emission current stability characterized with fewer fluctuations, owing to very good ion-bombardment resistance offered by the HfO2 coating. Furthermore, the heteroarchitecture thus obtained facilitates tailoring of the morphology with high aspect ratio and modulation of electronic properties as well, thereby enhancing the FE behaviour. Despite HfO2 being wide band gap and high-k material, the HfO2-ZnO heteroarchitecture exhibits potential as promising candidate for fabrication of high current density cold cathode
Keywords: 3D heteroarchitecture; Field Emission (FE); hydrothermal; PLD; TEM

Enhanced field emission performance of MoO3 nanorods and MoO3-rGO nanocomposite - Bankar, Prashant K.; Khandare, Lina N.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
The graphene and semiconducting hybrid based nanostructures have emerged as a new class of multifunctional materials with improved performance in comparison to the pristine semiconductors. Here, as-synthesized MoO3-reduced graphene oxide (rGO) nanocomposite emitter exhibits enhanced field emission (FE) behavior as compared to the pristine 1D MoO3 nanorods. The hydrothermally synthesized 1D MoO3 nanorods (1D) are grafted on the rGO sheet (2D) using a simple room temperature sonochemical method. The morphological and structural analysis confirms the attachment of MoO3 nanorods with rGO and the improved conductivity of the sample indicates a strong electronic interaction between them. Furthermore, the FE studies of as-synthesized MoO3 nanorods and MoO3-rGO nanocomposite emitters, carried out at a base pressure -1 x 10(-8) mbar, reveals the values of turn on field (required to draw an emission current density of 1 mu A/cm(2)) as 1.6 and 1.4 V/mu m, respectively. Interestingly, the maximum emission current density of 2810 mA/cm(2) is achieved at a lower applied field of 2.7 V/mu m from the MoO3-rGO nanocomposite emitter. The enhancement in FE performance of MoO3-rGO nanocomposite is attributed to the improved electrical conductivity, mechanical properties and higher concentration of protruding edges (emission sites). This observation can be extended to other graphene-based 1D inorganic hybrid semiconductor nanocomposites, which can provide a valuable opportunity to explore novel hybrid materials for vacuum nano-electronic devices.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, Prashant K.; Ratha, Satyajit; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of a and beta-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of beta-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of alpha and beta-NiMoO4 at a base pressure of similar to 1 x 10(-8) mbar. The obtained turn-on field at emission current density of 1 mu A/cm(2) for beta-NiMoO4 nanosheets and alpha-NiMoO4 is 1.3V/mu m and 2.2V/mu m respectively were observed. The maximum field emission current density of 1.006 mA/cm(2) at an applied electric field of 2.7V/mu m was achieved for beta-NiMoO4 nanosheets. Furthermore, we found that the beta-NiMoO4 nanosheets possess good field emission performance compared to alpha-NiMoO4. The results indicate that NiMoO4 can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase. (C) 2017 Elsevier B.V. All rights reserved.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, P. K. (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of α and β-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of β-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of α and β-NiMoO4 at a base pressure of ∼1 × 10−8 mbar. The obtained turn-on field at emission current density of 1 μA/cm2 for β-NiMoO4 nanosheets and α −NiMoO4 is 1.3 V/μm and 2.2 V/μm respectively were observed. The maximum field emission current density of 1.006 mA/cm2at an applied electric field of 2.7 V/μm was achieved for β-NiMoO4 nanosheets. Furthermore, we found that the β-NiMoO4 nanosheets possess good field emission performance compared to α-NiMoO4. The results indicate that NiMoO4can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase.
Keywords: Current stability; field emission; nanosheets; NiMoO4

Enhanced proton conduction by post-synthetic covalent modification in a porous covalent framework - Samanta, Partha; Desai, Aamod V.; Anothumakkool, Bihag; Shirolkar, Mandar M.; Karmakar, Avishek; Kurungot, Sreekumar; Ghosh, Sujit K. (Journal of Materials Chemistry A, 2017)
A highly chemically stable porous covalent framework (PCF-1) based on ether linkages has been synthesized, which exhibits no loss up to similar to 500 degrees C along with retention of integrity under acidic, basic and oxidative reagent conditions. Owing to its thermal and chemical stability, post-synthetic covalent modification was executed for the introduction of pendant sulphonic acid (-SO3H) groups. The covalently modified compound (PCF-1-SO3H) presents a remarkably high conductivity (ca. 0.026 S cm(-1)), with an similar to 130 fold enhancement in proton conductivity over the parent compound. This value is comparable with those of commercially used Nafion-based proton conducting materials and stands as the highest known value in the regime of post-synthetically modified porous organic frameworks. It is noteworthy to mention that PCF-1 is stable in both acidic and alkaline media, which is not commonly observed for most of the porous materials trialed as proton conducting materials, including metal organic frameworks.

Environmentally benign bioderived carbon microspheres-supported molybdena nanoparticles as catalyst for the epoxidation reaction - Doke, Dhananjay S.; Umbarkar, Shubhangi B.; Gawande, Manoj B.; Zbori, Radek; Biradar, Ankush V. (ACS Sustainable Chemistry & Engineering, 2017)
A one pot synthesis of molybdenum oxide nanoparticles (NPs supported on bioderived carbon microspheres is reported. The catalyst was synthesized by the low temperature hydrothermal (LTH) method using D-glucose and bagasse as the carbon source. The carbonization of bagasse resulted in the formation of nonuniform carbon microspheres while glucose resulted in uniform carbon spheres. SEM and STEM elemental mapping show the uniform distribution of molybdenum oxide NPs over the carbon microspheres. XPS spectroscopy confirmed that molybdenum was in the Mo6+ oxidation state. The 1% MoO3 supported on carbon microspheres derived from D-glucose showed excellent catalytic activity up to 100% olefin conversion with 100% epoxide selectivity using organic tent-butyl hydroperoxide as an oxidant. The catalyst was successfully used for up to five cycles without losing substantial activity and selectivity.
Keywords: Carbon microspheres; epoxidation; heterogeneous catalysis; Hydrothermal synthesis; TBHP

Epalrestat-cytosine cocrystal and salt structures: attempt to control E,Z -> Z,Z isomerization - Nangia, Ashwini Kumar; Battini, Swapna (Crystal Growth & Design, 2017)
Cocrystallization of the anti-diabetic drug Eparlestat (EPR) with cytosine (CYT) gave EPR‒‒CYT-H+ form I, a salt-cocrystal hybrid structure, salt hydrate (EPR‒‒CYT-H+‒H2O, 1:2:1), and non-stoichiometric solvates of EPR‒‒CYT-H+ with EtOH/n-PrOH included in the rhombohedral symmetry voids, referred to as form II. Desolvation of EPR‒‒CYT-H+ form II solvates resulted in an unsolvated form II of EPR‒‒CYT-H+ which was characterized by DSC, TGA and NMR. The carboxylate•••cytosinium synthon was observed in the salts structure along with the uncommon CYT-H+•••H+-CYT base pairing in the structures of salt-cocrystal hybrid and salt hydrate. The crystalline forms were characterized by spectroscopic (IR, NMR), thermal (DSC, HSM, TGA), powder X-ray diffraction (PXRD) and single crystal X-ray diffraction (SC-XRD) techniques. The intent of using the salt/ salt-cocrystal forms as a means to stop the E,Z  Z,Z isomerization of EPR was not successful in photo-irradiation experiments.

Estimating the lipophobic contributions in model membranes - Dubey, Vikas; Prasanna, Xavier; Sengupta, Durba (Journal of Physical Chemistry B, 2017)
The insertion and association of membrane proteins is critical in several cellular processes. These processes were thought to be protein-driven, but increasing evidence points toward an important role of the lipid bilayer. The lipid-mediated contribution has been shown to be important in the association of membrane peptides, but the corresponding ``lipophobic'' component has not been directly estimated. Here, we calculate the free energy of insertion for transmembrane peptides and estimate the lipophobic component from the cost of cavity formation. The free-energy calculations were performed using the coarse-grain Martini force field, which has been successful in predicting membrane protein interactions. As expected, the charged moieties have the least favorable free energy of insertion and the highest cost of cavity formation. A length dependence was observed in polyalanine peptides with the lipid-mediated component increasing nonlinearly with peptide length. Membrane fluidity was tested by varying the temperature, and opposing effects were observed for short and long peptides. The dependence of the lipid-mediated effects on peptide length and temperature was not uniform and gives valuable insight into the anisotropic nature of the membrane. The results are an important step in estimating membrane effects in protein insertion and association.

Estimation of gas induction in jet loop reactors: influence of nozzle designs - Sharma, D.V. (Chemical Engineering Research and Design, 2017)
Jet loop reactors are used widely for conducting gas liquid reactions because of the high mass transfer achieved in the gas–liquid ejector. Studies have shown that the mass transfer has a very strong correlation to the amount of gas induced in the ejector, and hence it is important to understand gas induction to enhance the performance of any gas–liquid nozzle. In this work, we used a single phase CFD model of the ejector with one adjustable parameter for estimating gas induction rates. After establishing that the model adequately describes the experimental data, the model was used for a quick evaluation of ejector geometries. Influence of key geometric parameters of gas–liquid ejectors like nozzle diameter, mixing tube length, distance between the nozzle outlet and mixing tube, suction chamber geometry and diffuser angle was investigated. It was found that dependence of gas induction on geometric parameters like distance between nozzle—mixing tube, suction chamber geometry, diffuser angle was either weak or had a clear maxima at or beyond a certain value of the geometric parameter. Other parameters like mixing tube length and nozzle diameter have a more complex impact on gas induction. The presented approach and results will be useful for quantifying influence of nozzle designs on gas induction rate in jet loop reactors.
Keywords: CFD; Gas Induction; Jet Loop Reactors; Nozzle Geometry

Evaluating a new high-throughput twin-arginine translocase assay in bacteria for therapeutic applications - Ghosh, D. (Current Microbiology, 2017)
The twin-arginine translocase (Tat) pathway is involved in the transport of folded proteins in bacteria, and has been implicated in virulence and pathogenesis. A simple but efficient assay based on the quantification of the exopolysaccharide colanic acid was developed as a new means to study Tat function. Colanic acid contains a methylpentose (l-fucose) component, and its production is directly linked to the Tat pathway through the transport of enzymes involved in polysaccharide biosynthesis. Monitoring of l-fucose levels can be applied for identification of new Tat substrates and high-throughput screening of Tat inhibitors for therapeutic applications.

Examination into the taxonomic position of Bacillus thermotolerans Yang et al., 2013, proposal for its reclassification into a new genus and species Quasibacillus thermotolerans gen. nov., comb. nov. and reclassification of B. encimensis Dastager et al., - Verma, Ashish; Pal, Yash; Khatri, Indu; Ojha, Anup Kumar; Gruber-Vodicka, Harald; Schumann, Peter; Dastager, Syed Gulam; Subramanian, Srikrishna; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2017)
Two novel Gram-staining positive, rod-shaped, moderately halotolerant, endospore forming bacterial strains 5.5LF 38TD and 5.5LF 48TD were isolated and taxonomically characterized from a landfill in Chandigarh, India. The analysis of 16S rRNA gene sequences of the strains confirmed their closest identity to Bacillus thermotolerans SgZ-8T with 99.9% sequence similarity. A comparative phylogenetic analysis of strains 5.5LF 38TD, 5.5LF 48TD and B. thermotolerans SgZ-8(T) confirmed their separation into a novel genus with B. badius and genus Domibacillus as the closest phylogenetic relatives. The major fatty acids of the strains are iso-C15:0 and iso-C16:0 and MK-7 is the only quinone. The major polar lipids are diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. The digital DNA-DNA hybridization (DDH) and ortho average nucleotide identity (ANI) values calculated through whole genome sequences indicated that the three strains showed low relatedness with their phylogenetic neighbours. Based on evidences from phylogenomic analyses and polyphasic taxonomic characterization we propose reclassification of the species B. thermotolerans into a novel genus named Quasibacillus thermotolerans gen. nov., comb. nov with the type strain SgZ-8(T) (=CCTCC AB2012108(T)=KACC 16706(T)). Further our analyses also revealed that B. encimensis SGD-V-25(T) is a later heterotypic synonym of Bacillus badius DSM 23(T).

Expeditious and solvent-free nickel-catalyzed C−H arylation of arenes and indoles - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2017)
An efficient solvent-free nickel-catalyzed method for C−H bond arylation of arenes and indoles has been developed, which proceeds expeditiously through chelation assistance. The reaction is highly selective for mono-arylation and tolerates sensitive and structurally diverse functionalities, such as halides, ethers, amines, indole, pyrrole and carbazole. This reaction represents the first example of a nickel-catalyzed C−H arylation by monochelate assistance and symbolizes a rare precedent in solvent-free C−H arylation. Mechanistic investigations by various controlled reactions, kinetic studies, and deuterium labeling experiments suggest that the arylation follows a single electron transfer (SET) pathway involving the turnover-limiting C−H nickelation process.

Experimental study and Ab-initio calculations on the molecular structure, infrared and Raman spectral properties of dinitroimidazoles - Ravi, P. (Chemical Data Collections, 2017)
The structural and vibrational properties of 1,4-dinitroimidazole, 2,4-dinitroimidazole and 1-methyl-2,4-dinitroimidazole have been explored both experimentally and theoretically. The N1-N6, C2-NO2, C4-NO2, N1-CH3 lengths were found to be varied with the levels of theory and the calculated values were over estimated compared with those of experimental values. The experimental vibrational frequencies were compared with those values calculated at the HF/6–311 ++G(d,p), B3P86/6–311 ++G(d,p), B3LYP/6–311 ++G(d,p) and B3LYP/aug-cc-pVDZ levels. The calculated frequencies were in good agreement with the experimental values and the relative mean deviations between the measured and calculated vibrational frequencies were smaller than 1% for all molecules. The discrepancies in the bond lengths bond angles and harmonic frequencies are confined to the relative positions of NO2 groups that present a great deviation from the planarity of the molecule. Nevertheless the structural parameters and harmonic vibrational frequencies of nitroimidazoles calculated at the B3LYP/aug-cc-pVDZ level are superior compared with those values computed from other levels of calculation.

Exploiting directional long range secondary forces for regulating electrostatics dominated noncovalent interactions - Tiwari, Mrityunjay; Vanka, Kumar (Chemical Science, 2017)
It has been well established that long range secondary electrostatic interactions (SEIs) have a significant effect on the stability of supramolecular complexes. However, general rules for exploiting SEIs in the rational design of diverse supramolecular complexes have been difficult to obtain. In this work, we outline a quantum chemical approach for understanding the strength of electrostatic interactions. This approach is seen to provide excellent correlation between the electrostatic force and the binding energy between two partners in hydrogen-bonded complexes, as well as that between two ions in ion-pair complexes. Furthermore, we illustrate how the understanding of the binding allows for the rational design of new complexes where the association constant between the two partners can be increased or decreased, as desired, by several orders of magnitude. Hence, the current work showcases a general, simple and powerful method of understanding and exploiting long range secondary electrostatic interactions.

Exploiting phosphate-starved cells of scenedesmus SP for the treatment of raw sewage - Yewalkar-Kulkarni, Swati; Gera, Gayatri; Nene, Sanjay; Pandare, Kiran; Kulkarni, Bhaskar; Kamble, Sanjay (Indian Journal of Microbiology, 2017)
Phosphate depletion is one of the favorable ways to enhance the sewage water treatment with the algae, however, detailed information is essential with respect to internal phosphate concentration and physiology of the algae. The growth rate of the phosphate-starved Scenedesmus cells was reduced drastically after 48 h. Indicating cells entered in the stationary phase of the growth cycle. Fourier Transform Infrared analysis of phosphate-starved Scenedesmus cells showed the reduction in internal phosphate concentration and an increase in carbohydrate/phosphate and carbohydrate/lipid ratio. The phosphate-starved Scenedesmus cells, with an initial cell density of, 1 x 10(6) cells mL(-1) shows 87% phosphate and 100 % nitrogen removal in 24 h. The normal Scenedesmus cells need approximately 48 h to trim down the nutrients from wastewater up to this extent. Other microalgae, Ankistrodesmus, growth pattern was not affected due to phosphate starvation. The cells of Ankistrodesmus was able to reduce 71% phosphate and 73% nitrogen within 24 h, with an initial cell density of, 1 x 10(6) cells mL(-1).
Keywords: Ankistrodesmus; Fourier Transform Infrared; Phosphate starvation; Scenedesmus; Sewage treatment

Exploiting the dual role of ethynylbenziodoxolones in gold-catalyzed C(sp)-C(sp) cross-coupling reactions - Banerjee, Somsuvra; Patil, Nitin T. (Chemical Communications, 2017)
Reported herein is the gold-catalyzed alkynylation of terminal alkynes using ethynylbenziodoxolones (EBXs), where EBXs serve a dual role as oxidants as well as alkyne transfer agents to access unsymmetrical 1,3-diynes. Hence, the catalytic system requires no external oxidants and is compatible with a broad range of substrates, including those with polar functional groups such as NH, OHand B(OH)(2).

Exploration of amination reactions on highly extendable active sites of Pd(II)-3-allylsalicylaldiminophenol (ASIP) complex over thiofunctionalized SBA-15 - Lazar, Anish; Vinod, C. P.; Singh, A. P. (Microporous and Mesoporous Materials, 2017)
An effective and impressive heterogeneous catalyst, Pd(II)-3-allylsalicylaldiminophenol-SBA-15, dubbed as Pd(II)ASIP@SBA-15, for amination reactions of aryl halides to synthesize secondary amines (2), has been synthesized and characterized. Pd(II)ASIP@SBA-15 has been synthesized by the covalent anchoring of 3-allylsalicylaldehyde over thiofunctionalized SBA-15, then further reaction with 2-aminophenol, followed by metallation process by using Pd(11)(OAc)(2). A specifically designed cheap and easily available organic ligand, 3-allylsalicylaldiminophenol (ASIP), was synthesized from 3-allylsalicylaldehyde and 2-aminophenol. Using this, the synthesis of Pd(II)ASIP@SBA-15 was carried out whereby the ligand providing an active co-ordination or chelating sites for palladium metal. This strategy helped in exposing the Pd(11)ASIP active sites from surface to channels of SBA-15 support during the reactions. The synthesized catalyst were characterized by CHN analysis, PXRD, Nitrogen sorption analyses, TG & DTA, FTIR, C-13 and Si-29 CPMASS NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. Pd(II)ASIP@SBA-15 catalyst was screened in heterogeneous amination reactions of aryl halides to produce N-aryl derivatives or secondary amines with high catalytic activity as revealed by turn over frequency (TOF) calculations. To explore the heterogeneous nature of catalysts, amination reactions were carried with neat Pd(II)ASIP complex and Pd(11)(OAc)(2) catalysts. The catalyst was recycled several times without much loss of activity and Sheldon hot filtration test has been performed. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Amination Reactions; heterogeneous catalysis; Reusable; Supported catalysis

Exploring the effect of hydroxylic and non-hydroxylic solvents on the reaction of [(VO)-O-IV(beta-diketonate)2] with 2-aminobenzoyl-hydrazide in aerobic and anaerobic conditions - Biswas, Nirmalendu; Patra, Debashis; Mondal, Bipul; Bera, Sachinath; Acharyya, Swarnali; Biswas, Anup Kumar; Mukhopadhyay, Titas Kumar; Pal, Amrita; Drew, Michael G. B.; Ghosh, Tapas (Dalton Transactions, 2017)
Refluxing [(VO)-O-IV(beta-diketonate)(2)], namely [(VO)-O-IV(acetylacetonate)(2)] and [(VO)-O-IV(benzoylacetonate)(2)], separately with an equivalent or excess amount of 2-aminobenzoylhydrazide (ah) in laboratory grade (LG) CH3OH in aerobic conditions afforded non-oxidovanadium(IV) and oxidovanadium(V) complexes of the type [V-IV(L-1)(2)] (1), [(VO)-O-V(L-1)(OCH3)](2) (3) and [V-IV(L-2)(2)] (2), and [(VO)-O-V(L-2)(OCH3)] (4), respectively. (L-1)(2-) and (L-2)(2-) represent the dianionic forms of 2-aminobenzoylhydrazone of acetylacetone (H2L1) and benzoylacetone (H2L2), respectively, (general abbreviation, H2L), which was formed by the in situ condensation of ah with the respective coordinated [beta-diketonate] in medium-to-good yield. The yield of different resulting products was dependent upon the ratio of ah to [(VO)-O-IV(beta-diketonate)(2)]. For example, the yield of 1 and 2 complexes increased significantly associated with a decrease in the amount of 3 and 4 with an increase in the molar ratio of ah. Upon replacing CH3OH by a non-hydroxylic solvent, LG CHCl3, the above reaction yielded only oxidovanadium(V) complexes of the type [(VO)-O-V(L-1)(OH)](2) (5), [(VO)-O-V(L-2)(OH)] (6) and [(V2O3)-O-V(L)(2)] (7, 8) whereas, upon replacing CHCl3 by another non-hydroxylic solvent, namely LG CH3CN, only the respective [(V2O3)-O-V(L)(2)] (7, 8) complex was isolated in 72-78% yield. However, upon performing the above reactions in the absence of air using dry CH3OH or dry CHCl3, only the respective [V-IV(L)(2)] complex was obtained, suggesting that aerial oxygen was the oxidising agent and the type of pentavalent product formed was dependent upon the nature of solvent used. Complexes 3 and 4 were converted, respectively, to 7 and 8 on refluxing in LG CHCl3 via the respective unstable complex 5 and 6. The DFT calculated change in internal energy (Delta E) for the reactions 2[(VO)-O-V(L-2)(OCH3)] + 2H(2)O -> 2[(VO)-O-V(L-2)(OH)] + 2CH(3)OH and 2[(VO)-O-V (L-2)(OH)] -> [(V2O3)-O-V(L-2)(2)] + H2O was, respectively, +3.61 and -7.42 kcal mol(-1), suggesting that the [(VO)-O-V(L-2) (OH)] species was unstable and readily transformed to the stable [(V2O3)-O-V(L-2)(2)] complex. Upon one-electron reduction at an appropriate potential, each of 7 and 8 generated mixed-valence [(L) (VO)-O-V-(mu-O)-OVIV(L)]species, which showed valence-delocalisation at room temperature and localisation at 77 K. Some of the complexes showed a wide range of toxicity in a dose-dependent manner against lung cancer cells comparable with that observed with cis-platin.
Keywords: Effective Core Potentials; Lung-cancer cells; Molecular-Orbital Methods; Non-oxido vanadium(iv); Non-Oxo; Oxovanadium(iv) Complexes; Tridentate ono ligand; Ray crystal-structure; Trigonal-prismatic Co-ordination; V-IV complex

Exploring the gem-dimethyl effect in the formation of imine-based macrocycles and cages - Madhu, Suresh; Rashmi, E. V.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2017)
Using the gem-dimethyl effect as a platform, a variety of organic [2+2] macrocycles and [2+3] cofacial cages was obtained in high yields. Imine-based macrocyclization could be performed even at high concentrations (0.5 to 1.0 M), via instant mixing of aldehydes and amines.

Exploring the influence of shapes and heterogeneity of glyco-gold nanoparticles on bacterial binding for preventing infections - Toraskar, Suraj; Gade, Madhuri; Sangabathuni, Sivakoti; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemmedchem, 2017)
To investigate the effects of the heterogeneity and shape of glyco-nanoprobes on carbohydrate-protein interactions (CPIs), alpha-d-mannose-and beta-d-galactose-linked homo-and heterogeneous glycodendrons were synthesized and immobilized on spherical and rod-shaped gold nanoparticles (AuNPs). Lectin and bacterial binding studies of these glyco-AuNPs clearly illustrate that multivalency and shape of AuNPs contribute significantly to CPIs than the heterogeneity of glycodendrons. Finally, bacterial infection of HeLa cells was effectively inhibited by the homogeneous glycodendron-conjugated rod-shaped AuNPs relative to their heterogeneous counterparts. Overall, these results provide insight into the role of AuNP shape and multivalency as potential factors to regulate CPIs.

Exploring the role of GS-GOGAT cycle in microcystin synthesis and regulation - a model based analysis - Banerjee, Swarnendu; Subramanian, Abhishek; Chattopadhyay, Joydev; Sarkar, Ram Rup (Molecular Biosystems, 2017)
Toxic cyanobacteria blooms populate water bodies by consuming external nutrients and releasing cyanotoxins that are detrimental for other aquatic species, producing a significant impact on the plankton ecosystem and food web. To exercise population-level control of toxin production, understanding the biochemical mechanisms that explain cyanotoxin regulation within a bacterial cell is of utmost importance. In this study, we explore the mechanistic events to investigate the dependence of toxin microcystin on external nitrogen, a known regulator of the toxin, and for the first time, propose a kinetic model that analyzes the intracellular conditions required to ensure nitrogen dependence on microcystin. We hypothesize that the GS-GOGAT cycle is manipulated by variable influx of different intracellular metabolites that can either disturb or promote the balance between the enzyme microcystin synthetase and substrate glutamate to produce variable microcystin levels. As opposed to the popular notion that nitrogen starvation increases microcystin synthesis, our analyses suggest that under certain intracellular metabolite regimes, this relationship can either be completely lost or reversed. External nitrogen can only complement the conditions fixed by intracellular glutamate, glutamine and 2-oxoglutarate. This mechanistic understanding can provide an experimentally testable hypothesis for exploring the less-known biology of microcystin synthesis and designing specific interventions.

Extraction of the very high tunneling current and extremely stable emission current from GdB6/W-tip source synthesized using arc plasma - Suryawanshi, Sachin R.; Kanhe, Nilesh; Mathe, Vikas L.; Phase, Deodatta M.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Herein, we report the one step arc plasma synthesis of the GdB6 (Gadolinium hexaboride) nanoparticles and its field emission (FE) characteristics on tungsten point substrate (GdB6/ W). The SEM /TEM analysis revealed the GdB6 nanoparticles on W point substrate exhibit irregular shaped, grainy, dense, course morphology, i.e. uniformly covering the entire tip substrate surface. For GdB6/W point source, the values of the turn-on and threshold fields, defined as field required to draw an emission current density similar to 1 mA/cm(2) and similar to 100 mA/cm(2), respectively are found to be similar to 2.2 and similar to 2.7 V/mm, for anodecathode separation of similar to 1 mm. Interestingly, a very high emission current density of similar to 3.5 A/cm(2) has been drawn from the GdB6/W point emitter at relatively lower applied field of similar to 6.4 V/mm. The field enhancement factor found to be similar to 10,250. The GdB6/W point electron source exhibits a good emission current stability at similar to 10 mA for a period of 6 hr. The emission current stability is enumerated in terms of standard deviation and its magnitude has been measured to be only 1.72% with respect to the average value. The superlative field emission characteristics signify the GdB6/W point electron source as potential candidates for vacuum micro/nanoelectronics device applications.
Keywords: Arc Plasma; field emission; Thin films

Easily accessible lithium compound catalyzed mild and facile hydroboration and cyanosilylation of aldehydes and ketones - Bisai, Milan; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2018)
Simple and readily accessible lithium compounds such as 2,6-ditertbutyl phenolate lithium (1a), 1,1' dilithioferrocene (1b) and nacnac lithium (1c) are found to be efficient single site catalysts for hydroboration of...

Education with a purpose - Nangia, Ashwini K. (Current Science, 2018)

Effect of alkali and alkaline earth metal on Co/CeO2 catalyst for the water gas shift reaction of waste derived synthesis gas - Lee, Yeol-Lim; Jha, Ajay; Jang, Won-Jun; Shim, Jae-Oh; Rode, Chandrashekhar V.; Jeon, Byong-Hun; Bae, Jong Wook; Roh, Hyun-Seog (Applied Catalysis A-General, 2018)
We prepared a series of alkali (Na and K) and alkaline earth metal (Ca and Ba) promoted Co/CeO2 catalysts to investigate the effect of the promoter on the catalytic performance of the catalyst in the high-temperature water gas shift (WGS) reaction of waste derived synthesis gas. Interestingly, alkali metal promoted catalysts deactivated rapidly compared to alkaline earth metal promoted catalysts. Alkaline earth metal promoted catalysts showed relatively higher stability (>50 h) even at a very high gas hourly space velocity of 143,000 h(-1). X-ray diffraction (XRD) and transmission electron microscopy (TEM) results reveal that the higher stability of the alkaline earth metal promoted catalysts was due to the strong resistance to sintering, showing a relatively small crystallite size of metallic cobalt compared to the alkali metal promoted catalysts after WGS reaction.
Keywords: Alkaline earth metal; Co/CeO2; High temperature water-gas shift; Sintering resistance; stability; Waste derived synthesis gas

Effect of crystal packing on the thermosalient effect of the pincer-type diester naphthalene-2,3-diyl-bis(4-fluorobenzoate): a new class II thermosalient solid - Tamboli, Majid I.; Karothu, Durga Prasad; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Naumov, Pance (Chemistry-A European Journal, 2018)
The pincer-like double ester naphthalene-2,3-diyl-bis(4-fluorobenzoate) (2) is pentamorphic. Upon heating crystals of form I to below their melting point (441-443 K), they undergo a phase transition accompanied by a thermosalient effect, that is, rare and visually striking motility whereby the crystals jump or disintegrate. The phase transition and the thermosalient effect are reversible. Analysis of the crystal structure revealed that form I is a class II thermosalient solid. Crystals of form III also underwent a reversible phase transition in the temperature range of 160 to 170 K; however, they were not thermosalient. Comparison of the structures and the mechanical responses of the two polymorphs revealed that the thermosalient effect of form I was due to reversible closing and opening of the arms of the diester molecules in a tweezer-like action.

Effect of hyperglycemic conditions on the early self-assembly of the alzheimer's amyloid beta peptide: implications for neurotoxicity - Menon, Sneha; Sengupta, Neelanjana (Biophysical Journal, 2018)

Effect of membrane composition on receptor association: implications of cancer lipidomics on ErbB receptors - Pawar, Aiswarya; Sengupta, Durba (Journal of Membrane Biology, 2018)
The association of single transmembrane receptors, such as the ErbB receptors is a key event in initiating cell signaling networks. The interactions between these receptors have been well characterized for both ligand-driven and pre-formed dimers. However, the role of the membrane in modulating association is less well understood and assumes greater importance in light of altered membrane composition in diseased states. Here, we discuss how membrane composition has been observed to induce both structural and dynamic differences in receptor association. Computational studies, especially those using coarse-grain simulations have been successful in predicting the role of the membrane and calculating the related free energy landscapes. Membrane perturbations and differences in lipid chain order, related to the lipophobic effect, have been shown to play a large role in driving membrane protein association. Further, we review lipid compositions reported in diseased conditions and its effect on transmembrane receptor association, focusing on the ErbB growth factor receptor dimers in cancer. Understanding the role of the membrane in receptor association will provide general design principles driving receptor organization, as well as help to identify novel therapeutic strategies.

Effect of sodium dodecyl sulfate surfactant on methane hydrate formation: a molecular dynamics study - Choudhary, Nilesh; Hande, Vrushali R.; Roy, Sudip; Chakrabarty, Suman; Kumar, Rajnish (Journal of Physical Chemistry B, 2018)
In experimental studies, it has been observed that the presence of sodium dodecyl sulfate (SDS) significantly increases the kinetics of hydrate formation and the final water-to-hydrate conversion ratio. In this study, we intend to understand the molecular mechanism behind the effect of SDS on the formation of methane hydrate through molecular dynamics simulation. Hydrate formation conditions similar to that of laboratory experiments were chosen to study hydrate growth kinetics in 1 wt % SDS solution. We also investigate the effect of interactions with isolated SDS molecules on methane hydrate growth. It was observed that the hydrophobic tail part of the SDS molecule favorably interacts with the growing hydrate surface and may occupy the partial hydrate cages while the head groups remain exposed to water.

Effect of structural properties of organosolv lignins isolated from different rice husks on their liquefaction using acidic ionic liquids - Singh, Sandip K.; Dhepe, Paresh L. (Clean Technologies and Environmental Policy, 2018)
Lignin is the only naturally available sustainable resource of aromatic compound on the Earth. Depending on the properties of lignin and the reaction conditions employed for the liquefaction, it is observed that the product distribution alters. Since ionic liquids (ILs) are considered as green and have tuneable properties, in the current work, imidazolium-based acidic ILs were employed to liquefy organosolv lignins derived from different varieties of rice husks. When liquefaction was carried out at 120 A degrees C for 1 h 36% yield for EtOAc- and DEE-soluble products with high mass balance (97 +/- 3%) was observed. The detailed characterisations of lignins and organic solvent-soluble products were done by variety of techniques [GC-MS, FT-IR, UV-Vis, 2D (HSQC) NMR], and based on this, the correlation between activity and properties of catalyst and lignin was established. Depolymerisation of organosolv lignin (derived from three rice husks) into aromatic product was done, and experimental correlation studies were performed in both.

Effect of support on the catalytic activity of WOx promoted Pt in green diesel production - Janampelli, Sagar; Darbha, Srinivas (Molecular Catalysis, 2018)
Platinum and WOx-promoted platinum supported on SiO2-Al2O3, Al2O3, AlPO4-5 and ZrO2 catalysts were prepared by wet impregnation method and investigated for deoxygenation of oleic acid (OA, a representative fatty acid) producing diesel-range hydrocarbons. Support and WOx influenced the textural, electronic and catalytic properties of Pt. WOx promoted the deoxygenation activity through hydrodeoxygenation pathway. Structure-activity correlations revealed that metallicity of Pt and acidity of the catalyst are crucial in determining the catalytic performance and product selectivity. Among the catalysts tested, 4Pt-8WO(x)/ZrO2, having adequate metal dispersion and electron rich Pt (desired for hydrogen splitting), reduced WOx species (W5+;-desired for OA activation) and less amount of strong acid sites (desired to avoid hydrocracking) showed highest catalytic deoxygenation performance (OA conversion = 100 mol% and C18 hydrocarbon selectivity = 89.4% at 260 degrees C and 20 bar H-2 pressure). The study reveals that support plays a crucial role in determining the catalytic performance of platinum. (C) 2017 Elsevier B.V. All rights reserved.

Effect of titration time on the catalytic performance of Cu/CeO2 catalysts for water-gas shift reaction - Na, Hyun-Suk; Shim, Jae-Oh; Jang, Won-Jun; Jeon, Kyung-Won; Kim, Hak-Min; Lee, Yeol-Lim; Lee, Da-We; Yoo, Seong-Yeun; Bae, Jong Wook; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Today, 2018)
We herein report the preparation of ceria (CeO2) via a simple precipitation method for use as a catalyst support in the water-gas shift (WGS) reaction. More specifically, we optimized the titration time required to obtain highly active CeO2-supported catalysts for the WGS reaction. As such, Cu was employed as the active metal coupled with the CeO2 support. Notably, the CeO2-0 supported Cu catalyst (where the precipitant was immediately injected into a cerium nitrate solution) exhibited the highest CO conversion at a gas hourly space velocity of 36,050 h(-1). This high catalytic activity of the Cu/CeO2-0 catalyst was mainly due to its high Brunauer-Emmett-Teller (BET) surface area, enhanced Cu dispersion, high number of oxygen vacancies, and enhanced reducibility.

Effect of turbulent dispersion on hydrodynamic characteristics in a liquid jet ejector - Sharma, Deepankar; Patwardhan, Ashwin; Ranade, Vivek (Energy, 2018)
Gas induction using a liquid jet is an extensively studied phenomenon. Many studies have been published detailing various hydrodynamic and mass transport aspects of gas induction in ejectors. Conversely, multiple studies have been published detailing jet dynamics, jet break up, nozzle geometry, effects of turbulence etc. In the modelling of the jet ejector systems CFD framework is used as the flow of gas is coupled with the liquid flow and the flow parameters like volume fraction, pressure drop/profile and velocity profiles both local and average are highly interdependent. Hence, it becomes important to capture all the flow physics in the simulations in order to understand the hydrodynamics. In the previous models the effect of turbulent dispersion was not included which led to incorrect calculation of phase profile, and other related parametric values. In the present work, the turbulence effects and its impact on the jet dynamics and gas induction rate in an ejector have been studied. Capturing the correct phase as well as velocity profile is imperative for the extension of the model to mass transfer and reactions. Lastly, other hydrodynamic properties like pressure drop, phase hold up and pressure profile help better the design correlations for jet ejectors.

Effects of constant kinetic energy of different impacting particles on slurry erosion wear of AA 6063 - Nandre, Bhushan D.; Desale, Girish R. (Journal of Tribology-Transactions of the ASME, 2018)
The present experimental study investigates the effect of constant kinetic energy on erosion wear of aluminum alloy 6063. Three different natural erodents (quartz, silicon carbide, and alumina) with different particle sizes are used to impact at 45 deg and 90 deg impact angles. For calculating the number of particles in the slurry pot, it is assumed that the solid particles are of spherical shape. The total numbers of impacting solid particles were kept constant by adjusting the solid concentration, velocity, and test duration. The scanning electron microscope (SEM) images of the three erodents show that the alumina particles have sharp edges with more angularity, and silicon carbide particles have subangular nature while quartz particles are blocky in shape. The mass loss per particle at 45 deg impact angle is observed higher than at normal impact angle. It may be due to the change in material removal mechanism with changing the impact angle. It is also found that the mass loss per particle from the target material having different particle size with constant kinetic energy remains constant for respective erodents. This indicates that the velocity exponent of impacting particles is around 2. The SEM images of eroded surfaces reveal the different mechanisms of material removal at 45 deg impact angle and at normal impact angle.

Efficient method for cyclopentanone synthesis from furfural: understanding the role of solvents and solubility in a bimetallic catalytic system - Dohade, Manisha; Dhepe, Paresh L. (Catalysis Science & Technology, 2018)
The platform chemical, furfural (FAL), is obtained from C5 stream of biomass, and effective conversion into various chemicals including cyclopentanone (CPO) would find many industrial applications. It is desirable to convert FAL to CPO under low H-2 pressure with high selectivity. In the current work, bimetallic catalysts with Pt as the base metal supported on carbon are evaluated in the synthesis of CPO using a biphasic solvent system. By tuning the solvent ratio, with toluene/water (3:4 v/v), 75% yield of CPO is achieved under 1 MPa H-2 at 180 degrees C. The difference in solubility of the substrate, intermediates and products, along with the optimum ratio of Pt and Co metals plays a crucial role in achieving better yields.

Efficient method for synthesis of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural and fructose using Pd/CC catalyst under aqueous conditions - Rathod, Pramod V.; Jadhav, Vrushali H. (ACS Sustainable Chemistry & Engineering, 2018)
Pd/CC catalyst was synthesized from readily available biomass-derived D-glucose. The catalyst was characterized using various techniques such as Fourier transform infrared spectroscopy, powder X-ray diffraction, energy dispersive X-ray analysis, scanning electron microscopy, C-13 cross polarization NMR, transmission electron microscopy, X-ray photoelectron spectroscopy, and Brunauer-Emmett-Teller (BET) surface area analysis. This catalyst showed excellent catalytic activity toward the synthesis of industrially important 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethylfurfural (HMF) and fructose. The process is simple, efficient, green, and industrially feasible. Oxidation of HMF proceeded in 85% yield, and dehydration of fructose followed by oxidation gave 64% yield of FDCA with 100% purity using Pd/CC catalyst and molecular O-2 as an oxidizing agent under aqueous reaction conditions. The one pot two step procedure is highly efficient for synthesis of FDCA from fructose as it avoids isolation of HMF and requires a single catalyst for two different steps. FDCA finds utility in next-generation bioplastic poly(ethylene 2,5-furandicarboxylate) (PEF), which is a replacement for fossil-fuel-based poly(ethylene terephthalate) (PET).

Efficient solar light-driven H-2 production: post-synthetic encapsulation of a Cu2O co-catalyst in a metal-organic framework (MOF) for boosting the effective charge carrier separation - Karthik, Peramaiah; Balaraman, Ekambaram; Neppolian, Bernaurdshaw (Catalysis Science & Technology, 2018)
The development of new and efficient catalytic systems for solar light-driven hydrogen generation is one of the prime focuses of contemporary chemical sciences. Indeed, the charge carrier separation efficiency of a photocatalyst plays a vital role in photocatalysis. Herein, we have successfully designed a Cu2O-encapsulating NH2-MIL-125(Ti) MOF by a post-synthetic encapsulation strategy. The Cu2O-encapsulating MOF material showed a remarkable enhancement in photocatalytic H-2 production activity under solar light illumination. Gratifyingly, the H-2 production activity under solar light was around approximate to 28-fold higher than that of the pristine MOF. The enhancement in photocatalytic activity may be attributed to efficient charge carrier separation through Ti3+ sites and the broad light absorption of the Cu2O-encapsulating MOF photocatalyst. The possible electron transport mechanism, potential energy diagram (V vs. NHE), and the existence of Ti3+ ions have been demonstrated by various spectroscopic studies.

Efforts to access the potent antitrypanosomal marine natural product janadolide: synthesis of des- tert -butyl janadolide and its biological evaluation - Athawale, Paresh R.; Jachak, Gorakh; Shukla, Anurag; Shanmugam, Dhanasekaran; Reddy, Srinivasa (ACS Omega, 2018)
To identify novel antitrypanosomal agents based on Janadolide, a potent macrocyclic polyketide–peptide hybrid, a macrolactonization strategy was explored. We prepared des-tert-butyl Janadolide and evaluated its antitrypanosomal activity. Our findings suggest that the tert-butyl group is necessary for the desired bioactivity.

Electrochemical capacitive energy storage in PolyHIPE derived nitrogen enriched hierarchical porous carbon nanosheets - Deshmukh, Ashvini B.; Nalawade, Archana C.; Karbhal, Indrapal; Qureshi, Mohammed Shadbar; Shelke, Manjusha V. (Carbon, 2018)
Porous and interconnected electrodes based on carbon nanoarchitectures offer comprehensive advantages of large specific surface area and high porosity consequently increasing the specific capacitance of ultracapacitor energy storage systems. Emulsion-templated polymers, PolyHIPEs (Polymerized High Internal Phase Emulsions) are highly porous polymers with a structure of cages interconnected by windows thus provide suitable framework to create such porous carbon nanostructures. Herein, nitrogen enriched porous carbon nanosheets are synthesized by pyrolysis of polymer-silica hybrid PolyHIPE and subsequent silica removal. This nitrogen enriched porous carbon nanosheets when tested as an electrode for ultracapacitor, showed specific capacitance as high as 209 F/g at a current density of 1 A/g in 1 M H2SO4 with excellent capacity retention over long cycling. (c) 2017 Elsevier Ltd. All rights reserved.
Keywords: Energy storage; Nitrogen enriched porous carbon nanosheets; PolyHIPE template; Ultracapacitor

Electrochemically synthesized faceted CuInTe2 nanorods as an electron source for field emission applications - Lakhe, Manorama G.; Joshi, Padmshree; Choudhary, Ram J.; Ganesan, V.; Joag, Dilip S.; Chaure, Nandu B. (New Journal of Chemistry, 2018)
Herein, CuInTe2 (CIT) thin films with faceted nanorod-like morphology have been synthesized on a flexible molybdenum foil using a water-based low-cost electrodeposition technique. The co-deposition potential for CIT was optimized using cyclic voltammetry with respect to that of the Ag/AgCl reference electrode, and films were deposited from -0.6 V to -0.9 V at the working temperature of 75 degrees C. The as-prepared CIT films exhibited an amorphous nature, whereas the RTP-annealed films exhibited a highly crystalline chalcopyrite nature as a function of the growth potential. A red shift was observed in the Raman spectra of the as-deposited films that shifted towards the original position upon annealing. The Cu/In ratio obtained by the EDS analysis was found to decrease systematically upon increasing the growth potential. X-ray photoelectron spectroscopy (XPS) studies revealed the presence of Cu+, Cu2+ satellites, In3+, Te2-, and Te4+ states of Cu, In, and Te. The field emission study showed a maximum current density of 1.74 mA cm(-2), which was attainable at an applied electric field of 1.5 V mu m(-1). The turn-on field was found to be 0.92 V mu m(-1), comparable to that of the carbon nanofibres. The emitter exhibited stable electron emission over a period of 3 hours. The faceted CIT nanorods with columnar growth are a potential candidate for application as an electron source, and herein, the field emission of CIT nanorods is reported for the first time.

Electron transfer rate analysis of a site-specifically wired copper oxidase - Schlesinger, Orr; Pasi, Mor; Dandela, Rambabu; Meijler, Michael M.; Alfonta, Lital (Physical Chemistry Chemical Physics, 2018)
Electron transfer kinetic parameters of site-specifically wired copper oxidase were investigated. The enzyme's orientation towards the electrode was controlled by incorporation of propargyl-L-lysine as a site-specific anchoring point. Herein, we demonstrate the importance of immobilization orientation and how it affects electron transfer efficiency and kinetics to each of the enzyme's two active sites.

Electronic structure of Gd based transition metal antimonides GdTSb (T = Ni, Pt) - Sahariya, Jagrati; Kumar, Pancham; Bhamu, K. C.; Soni, Amit (2nd International Conference on Condensed Matter and Applied Physics (ICC-2017), 2018)
We report the electronic and magnetic properties of ternary GdNiSb and GdPtSb compounds with cubic MgAgAs type structure. The energy bands, density of states and atom specific magnetic moments of compounds have been computed using GGA+U approach. The calculations predict that GdNiSb is a small band gap semiconductor whereas GdPtSb is metallic in nature.

Electrospinning of non-ionic cellulose ethers/polyvinyl alcohol nanofibers: characterization and applications - Wali, Ashwini; Zhang, Yucheng; Sengupta, Poulomi; Higaki, Yuji; Takahara, Atsushi; Badiger, Manohar V. (Carbohydrate Polymers, 2018)
The morphology of spin-coated films and electrospun fibers of ethyl hydroxy ethyl cellulose (EHEC), hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) and their blends with Poly(vinyl alcohol) (PVA) was examined by AFM, SEM and contact angle measurements. These polysaccharides upon blending with PVA exhibited smooth surface which was evidenced by Atomic Force Microscopy (AFM) observation. The electrospinnability of above polysaccharides with PVA was demonstrated for the first time. The oriented fibers could be obtained using a rotating disc collector. Contact angles of spin-coated films and electrospun fibers were discussed in terms of hydrophobicity and wetting characteristics. Further, The nanofibers of EHEC/PVA were in-situ crosslinked using citric acid and were used for controlled release of an antibacterial drug, Chlorhexidine Digluconate (ChD). In-vitro studies of cytotoxicity, cell growth and cell proliferation were performed using L929 mouse fibroblast cells. These nanofiber mats show potential in drug delivery and as scaffolds in tissue engineering applications.
Keywords: cellulose; drug delivery; electrospinning; Ethyl hydroxy ethyl cellulose; Hydrophobically modified ethyl hydroxy ethyl; scaffold; Spin coating

Elucidating efficacy of biomass derived nanocomposites in water and wastewater treatment - Kirti, Saumaya; Bhandari, Vinay M.; Jena, Jyotsnarani; Bhattacharyya, Arnab S (Journal of environmental management, 2018)
In the present study, two synthesis methods of nanocomposites-one involving a mixture of biomass and the other using chemical modification were investigated to evaluate practical application of green approach in pollution control, specifically for water and wastewater treatment. Newer multifunctional superparamagnetic nanocomposites using biomaterials such as unripened fruit of Cassia fistula (Golden shower) and Aloe vera were developed as an example of green approach while chemical modification was illustrated using n-octanol. Two specific model applications were studied for the developed materials-dye removal (Methyl Blue and Congo Red) and disinfection-demonstrating antimicrobial property. To elucidate the multifunctional character, the texture, morphology and composition of the prepared bionanocomposites were studied. The surface area values were 6.2 and 9.8 m(2)/g for Aloe vera and octanol based nanocomposites while the average pore diameters were 1.79 nm and 5.7 nm respectively, indicating presence of highly developed micropores in the first material having a honeycomb shape and the later showing excellent staircase type formation with larger pores. A very high dye removal to the extent of 100% was obtained that can be attributed largely to the functionalities imparted from Cassia fistula compared to ingredients from Aloe vera and octanol. The nanomaterials could be completely separated with absolute ease by applying simple magnetic field. Also, successful application of the developed materials in disinfection, removal of E. coif, was demonstrated with a very high efficiency of over 95%. The biomass derived nanocomposites exhibit excellent pollutant removal and disinfection properties, even at very low nanoparticle content; octanol based material indicating similar to 5 times lowered cost, while the Aloe vera based bionanocomposites have potential for cost reduction to the extent of 10 times as compared to only magnetite nanoparticles, thereby highlighting techno-economical alternative in water and wastewater treatment.

Employing arynes for the generation of aryl anion equivalents and subsequent reaction with aldehydes - Gaykar, Rahul N.; Bhunia, Anup; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
Arynes are highly reactive intermediates, which are utilized for the electrophilic arylation of various X-H bonds (X = O, N, S etc.). Herein, a new synthetic strategy is demonstrated, where arynes are converted into aryl anion equivalents by treatment with phosphines and a base. The addition of phosphines to arynes form the phosphonium salts, which in the presence of a carbonate base generates the aryl anion equivalent. Subsequent addition of the aryl anions with aldehydes afforded the secondary alcohols.

Enantioselective N-heterocyclic carbene-catalyzed cascade reaction for the synthesis of pyrroloquinolines via N-H functionalization of indoles - Mukherjee, Subrata; Shee, Sayan; Poisson, Thomas; Besset, Tatiana; Biju, Akkattu T. (Organic letters, 2018)
Functionalization of the indole N-H bond for enantioselective synthesis of biologically important pyrroloquinoline derivatives has been reported under oxidative N-heterocyclic carbene catalysis conditions. The interception of catalytically generated chiral alpha,beta-unsaturated acylazoliums with the indole derivatives proceeds in an aza-Michael/Michael/lactonization sequence to deliver the pyrroloquinoline derivatives in good yields, diastereoselectivities, and enantioselectivities. The simultaneous enhancement of reactivity and selectivity observed in polar aprotic solvents is noteworthy.

Enhanced activity of Withania somnifera family-1 glycosyltransferase (UGT73A16) via mutagenesis - Singh, Somesh; Patel, Krunal A.; Sonawane, Prashant D.; Vishwakarma, Rishi K.; Khan, Bashir M. (World Journal Of Microbiology & Biotechnology, 2018)
This work used an approach of enzyme engineering towards the improved production of baicalin as well as alteration of acceptor and donor substrate preferences in UGT73A16. The 3D model of Withania somnifera family-1 glycosyltransferase (UGT73A16) was constructed based on the known crystal structures of plant UGTs. Structural and functional properties of UGT73A16 were investigated using docking and mutagenesis. The docking studies were performed to understand the key residues involved in substrate recognition. In the molecular model of UGT73A16, substrates binding pockets are located between N- and C-terminal domains. Modeled UGT73A16 was docked with UDP-glucose, UDP-glucuronic acid (UDPGA), kaempferol, isorhamnetin, 3-hydroxy flavones, naringenin, genistein and baicalein. The protein-ligand interactions showed that His 16, Asp 246, Lys 255, Ala 337, Gln 339, Val 340, Asn 358 and Glu 362 amino acid residues may be important for catalytic activity. The kinetic parameters indicated that mutants A337C and Q339A exhibited 2-3 fold and 6-7 fold more catalytic efficiency, respectively than wild type, and shifted the sugar donor specificity from UDP-glucose to UDPGA. The mutant Q379H displayed large loss of activity with UDP-glucose and UDPGA strongly suggested that last amino acid residue of PSPG box is important for glucuronosylation and glucosylation and highly specific to sugar binding sites. The information obtained from docking and mutational studies could be beneficial in future to engineer this biocatalyst for development of better ones.

Enhanced and synergistic downregulation of oncogenic miRNAs by self-assembled branched DNA - Nahar, S.; Nayak, A. K.; Ghosh, A.; Subudhi, U.; Maiti, S. (Nanoscale, 2018)
miRNAs, a group of small non-coding RNA molecules, regulate the expression of many genes involved in various cellular processes. Acute evidence suggests that one miRNA can regulate many genes as its targets, while one gene can be targeted by many miRNAs that co-operatively regulate the gene. Thus, targeting a single miRNA is not sufficient enough to rescue the disease phenotype but it is also essential to target multiple miRNAs simultaneously. This inspired us to design a novel DNA nanostructure that can concurrently downregulate multiple oncomiRNAs. Here we designed a programmable antimiR branched DNA (antimiR-bDNA) nanostructure having antimiRNAs for selective binding to oncomiRNAs miRNA-27a, 96 and 182 which collectively downregulate FOXO1a expression. The antimiR-bDNAs show enhanced stability compared to naked antimiRNAs in serum and are able to knockdown these miRNAs with up to similar to 50% greater repression as compared to antimiRNAs. This synergistic miRNA repression leads to the restoration of FOXO1a protein levels which in turn inhibit G1-S traversion in cancer cells. To the best of our knowledge, this is the first study harnessing the ability of bDNA structures to silence multiple miRNAs simultaneously.

Enhanced microwave absorption property of reduced graphene oxide (RGO)-strontium hexaferrite (SF)/poly (vinylidene) fluoride (PVDF) - Acharya, Sanghamitra; Gopinath, Chinnakonda S.; Alegaonkar, Prashant; Datar, Suwarna (Dimond and Related Materials, 2018)
Enormous growth in the use of electronic gadgets presents a challenge to develop efficient electromagnetic interference (EMI) shielding materials specifically using composites with properties such as light weight and high shielding due to absorption. In the present work we have synthesized a composite material with three components; Reduced Graphene Oxide (RGO) and Strontium Hexaferrite (SrFe12O19) (SF) bound together by polymer Poly (Vinylidene) Fluoride (PVDF). Composite RGO/SF (RGOSF) was prepared by facile one port chemical reduction method. Surface anchoring of similar to 500 nm of magnetic particles over the graphene sheet was confirmed by Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Crystal structure of SF particles was analyzed before and after composite formation with RGO. Effective crystallite size was estimated from both XRD and Raman Spectroscopy which showed similar trend moving from SF to RGOSF to RGOSFPVDF. Polymer composite films of RGOSFPVDF were prepared by hot pressing. Both real and imaginary part of magnetic and dielectric parameters were studied. It was observed that enhancement of interfacial polarization and anisotropic heat loss in PVDF matrix was generated by RGOSF which ultimately created more scattering center and helped in absorption of electromagnetic radiation. Critical film thickness of 3 mm was capable to shield up to 33 dB EM energy of which > 99.9% was due to absorption.

Enhanced selectivity of 3-D ordered macroporous Pt/Al2O3 catalysts in nitrites removal from water - Sekhar, A. C. Sunil; Zaki, A.; Troncea, S.; Casale, S.; Vinod, C. P.; Dacquin, J. P.; Granger, P. (Applied Catalysis A-General, 2018)
Tailored macroporous mesoporous alumina supports have been successfully prepared using a single hard templating approach. Pt nanoparticles, showing similar physico-chemical properties, were homogeneously dispersed throughout the different alumina frameworks as catalytic active phase for drinking water treatment. We demonstrated that careful modification of pore properties of the catalyst (size and connectivity) by pseudomorphic transformation can strongly modulate the reaction rate and selectivity through the limited access to Pt active sites within the alumina porous particles. Specifically, 3-D Ordered Macroporous Pt-Al2O3 catalysts with a high degree of interconnectivity yield to superior catalytic properties (enhanced activity and selectivity) over pure mesoporous counterparts in the hydrogenation of nitrites in water. We found that large pores (240 nm) interconnected with windows (110 nm) alleviate mass transfer limitations and clearly improve NZ selectivity. The findings of this study further suggest the possibility of engineering the pore architecture of the support to fine tune the selectivity for a particular reaction rather than investigating more on tuning the properties of the costly active metallic phase.

Enhanced strain sensitivity in magnetostrictive spinel ferrite Co1-xZnxFe2O - Bhame, Shekhar D.; Joy, P. A. (Journal of Magnetism and Magnetic Materials, 2018)
We report the magnetic and magnetoelastic properties of spinel oxide system Co1-xZnxFe2O4 (CZF series) where x = 0.0, 0.1, 0.2, 0.3, 0.4, and 0.5. All the composition were prepared by conventional solid state synthesis method and exhibited pure spinel phase formation. The lattice parameters showed gradual increase indicating uniform distribution Zn ions in cobalt ferrite lattice. The magnetic properties such as saturation magnetization and coercive field were drastically affected with Zn substitution showing enhanced saturation magnetization and a sharp decrease in the coercivity. The room temperature magnetostrictive properties showed a promising 30% enhancement in the slope of magnetostriction curve for x = 0.2 composition and a reasonable magnetostrictive strain of 110 ppm indicating its suitability as a promising magnetostrictive material. (c) 2017 Elsevier B.V. All rights reserved.

Enhancement of field electron emission in topological insulator Bi2Se3 by Ni doping - Mazumder, K.; Sharma, A.; Kumar, Y.; Bankar, P.; More, M. A.; Devan, R.; Shirage, P. M. (Physical Chemistry Chemical Physics, 2018)
Nanostructures of bismuth selenide (Bi2Se3), a 3D topological insulator material, and nickel (Ni) doped Bi2Se3 samples were prepared by a hydrothermal method to explore the field emission properties. An enrichment in the field electron emission (FE) properties in terms of the threshold and turn-on field values of Bi2Se3 and Ni doped Bi2Se3 nanostructures was measured at a base pressure of ∼1 × 10−8 mbar. Using the background of the Fowler–Nordheim (FN) theory a field enhancement factor (β) of 5.7 × 103 and a threshold field value of 2.5 V μm−1 for 7.5% Ni doped Bi2Se3 were determined by investigating the J–E plot of the FE data. The value of β is three times higher than that of pure Bi2Se3 confirming the superior FE properties. The emission current was found to be very stable with the property of long standing durability as a negligible amount of variation was observed when measured at a constant value of 5 mA for 3 hours. The experimental results signify many opportunities for potential applications of Ni doped Bi2Se3 as a source of electrons in scanning as well as transmission electron microscopy, flat panel displays and as an X-ray generator, etc.

Entacapone: improving aqueous solubility, diffusion permeability, and cocrystal stability with theophylline - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Suresh, Kuthuru; Gunnam, Anilkumar; Nangia, Ashwini (Crystal Growth & Design, 2018)
Cocrystallization is a well-established technique to improve the solubility, bioavailability, and stability of active pharmaceutical ingredients (APIs) but permeability and diffusion rate control via cocrystals is relatively less well studied, and the exact role of coformers in influencing the diffusion rate of drug cocrystals is still not fully understood. The aqueous solubility and permeability diffusion of Entacapone, ETP, a Biopharmaceutical Classification System (BCS) Class IV drug of low solubility and low permeability, with Generally Regarded as Safe (GRAS) coformers has been studied. Fixed stoichiometry cocrystals of ETP with acetamide (ACT, 1:1), nicotinamide (NAM, 1:1), isonicotinamide (INAM, 1:1), pyrazinamide (PYZ, 1:1), and isoniazid (INZ), 1:1) were prepared by solvent-assisted grinding. Theophylline (THP) resulted in a cocrystal hydrate (ETP-THP-FIYD 1:1:1). The cocrystals were structurally characterized by single crystal and powder X-ray diffraction, DSC and TGA thermal measurements, and IR and NMR spectroscopy. Solubility and dissolution rate showed that there is a correlation between cocrystal stability and solubility governed by the heteromeric N-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O hydrogen bonds and conformational changes of ETP in cocrystal structures. ETP-THP-HYD and ETP-PYZ exhibit faster dissolution rate and high solubility and they are stable in phosphate buffer medium compared to the other cocrystals which dissociate partially during solubility experiments. Diffusion rates in a Franz cell showed that the stable and high solubility ETP-THP-HYD cocrystal has good permeability. Given that stability, solubility, and permeability are in general inversely correlated, the entacapone-theophylline hydrate cocrystal is a unique example of the thermodynamically stable cocrystal exhibiting high solubility and high permeability.

Enthalpic interactions in aqueous strong electrolytes upon addition of ionic liquids - Jain, Preeti; Kumar, Anil (Physical Chemistry Chemical Physics, 2018)
The present study deals with the inter-ionic interactions between strong electrolytes and ionic liquids based on the thermodynamic properties such as excess partial molar enthalpy, H-IL(E), relative apparent molar enthalpy, phi(L), and the enthalpic interaction parameters. The thermodynamic properties of the systems are the key indicators to understand the interionic interactions. We have conducted a systematic investigation of the enthalpic behavior of aqueous solution of salts and ionic liquids and their mixtures. The present study also emphasizes how the H-IL(E) values for the mixture of aqueous solution of ionic liquids and salts deviate from linearity as compared to those of the constituent aqueous ionic liquid or salt. This deviation from linearity for the H-IL(E) values has been discussed here.

Environmental impact study of bagasse valorization routes - Mandavgane, Sachin Arvind; Joglekar, Saurabh; Tandulje, Akshay P.; Kulkarni, Bhaskar D. (Waste and Biomass Valorization, 2018)
India is the world’s second largest sugarcane producer and a major manufacturer of molasses-derived ethanol. The sugarcane produced is widely used in the production of sugar and 1G ethanol. Though sugar and 1G ethanol are the major concerns, there is still a huge amount of bagasse waste generated in the sugar factories. This bagasse has also some end use value, as it can be utilized for production of methanol, 2G ethanol and electricity. Even though the technology for production of these value added products is well established, it is important to analyze the social, economical and environmental impacts associated with these production processes. This work compares the environmental impacts of various sugarcane conversion processes on life cycle basis. The functional unit used is one tonne of sugarcane cultivated in field. Four routes identified for bagasse conversion- conversion of bagasse to methanol (Route 1), conversion of bagasse to ethanol via 2 stage dilute acid process (Route 2), conversion of bagasse to ethanol via enzymatic process (Route 3) and electricity production from bagasse (Route 4). On comparison of these routes on midpoint indicators such as global warming potential (GWP), acidification potential (AP), eutrophication potential (EP) and ozone depletion potential (ODP) and photochemical ozone creation potential (POCP), it is observed that the methanol production is having the highest environmental indicator values. Even though ethanol production processes and cogeneration process are having nearly similar results, it can be said that cogeneration process is the more eco-friendly one.
Keywords: Bagasse valorization; Environmental impact; LCA; Midpoint indicators

Enzymatic formation of a skipped methyl‐substituted octaprenyl side chain of longestin (KS‐505a): involvement of homo‐IPP as a common extender unit - Taro Ozaki; Shinde, Sandip S.; Gao, Lei; Okuizumi, Ryo; Liu, Chengwei; Ogasawara, Yasushi; Lei, Xiaoguang; Dairi, Tohru; Minami, Atsushi; Oikawa, Hideaki (Angewandte Chemie, 2018)
Longestin (KS‐505a), a specific inhibitor of phosphodiesterase, is a meroterpenoid that consists of a unique octacyclic terpene skeleton with branched methyl groups at unusual positions (C1 and C12). The biochemical analysis of Lon23, a methyltransferase involved in the biosynthesis of longestin, demonstrated that methylation of IPP afforded 3Z‐3‐methyl IPP. This compound as well as IPP was selectively accepted as extender units by Lon22, a geranylgeranyl diphosphate (GGPP) synthase homolog, to yield dimethylated GGPP (dmGGPP). Absolute configuration of dmGGPP was determined to be (4R, 12R) by degradation and chiral GC analysis. These findings led us to propose key steps of the biosynthetic pathway of the unusual homoterpenoid longestin.

Eosin Y photoredox catalyzed net redox neutral reaction for regiospecific annulation to 3-sulfonylindoles via anion oxidation of sodium sulfinate salts - Rohokale, Rajendra S.; Tambe, Shrikant D.; Kshirsagar, Umesh A. (Organic & Biomolecular Chemistry, 2018)
An eosin Y photoredox catalyzed net redox neutral process for 3-sulfonylindoles via the anionic oxidation of sodium sulfinate salts and its radical cascade cyclization with 2-alkynyl-azidoarenes was developed with visible light as a mediator. The reaction offers metal and oxidant/reductant free, visible light mediated vicinal sulfonamination of alkynes to 2-aryl/alkyl-3-sulfonylindoles and proceeds via the generation of a sulfur-centered radical through direct oxidation of the sulfinate anion by an excited photocatalyst with a reductive quenching cycle. The mild conditions, use of an organic dye as photo-catalyst, bench stability and easily accessible starting materials make the present approach green and attractive.

Epoxyazadiradione suppresses breast tumor growth through mitochondrial depolarization and caspase-dependent apoptosis by targeting PI3K/Akt pathway - Kumar, Dhiraj; Haldar, Saikat; Gorain, Mahadeo; Kumar, Santosh; Mulani, Fayaj A.; Yadav, Amit S.; Miele, Lucio; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (BMC Cancer, 2018)
Background: Breast cancer is one of the most commonly diagnosed invasive cancers among women around the world. Among several subtypes, triple negative breast cancer (TNBC) is highly aggressive and chemoresistant. Treatment of TNBC patients has been challenging due to heterogeneity and devoid of well-defined molecular targets. Thus, identification of novel effective and selective agents against TNBC is essential. Methods: We used epoxyazadiradione to assess the cell viability, mitochondrial potential, ROS level, cell migration, apoptosis and protein expression in cell culture models of TNBC MDA-MB-231 and ER+MCF-7 breast cancer cells. The molecular mechanism was examined in two different type of breast cancer cells in response to epoxyazadiradione. We have also analyzed the effect of epoxyazadiradione on breast tumor growth using in vivo mice model. Results: In this study, we for the first time investigated that out of 10 major limonoids isolated from Azadirachta indica, epoxyazadiradione exhibits most potent anti-cancer activity in both TNBC and ER+breast cancer cells. Epoxyazadiradione induces apoptosis and inhibits PI3K/Akt-mediated mitochondrial potential, cell viability, migration and angiogenesis. It also inhibits the expression of pro-angiogenic and pro-metastatic genes such as Cox2, OPN, VEGF and MMP-9 in these cells. Furthermore, epoxyazadiradione attenuates PI3K/Akt- mediated AP-1 activation. Our in vivo data revealed that epoxyazadiradione suppresses breast tumor growth and angiogenesis in orthotopic NOD/SCID mice model. Conclusion: Our findings demonstrate that epoxyazadiradione inhibits PI3K/Akt-dependent mitochondrial depolarisation, induces apoptosis and attenuates cell migration, angiogenesis and breast tumor growth suggesting that this compound may act as a potent therapeutic agent for the management of breast cancer.
Keywords: Angiogenesis; Apoptosis; Breast cancer; Limonoids; Metastasis; PI3K

Erratum to: catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V. (Research on Chemical Intermediates, 2018)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone®–KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone–KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine–Oxone as an unprecedented catalyst–oxidant combination.
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

Ethoxy-ester functionalized imidazolium based ionic liquids for lithium ion batteries - Nirmale, Trupti; Khupse, Nageshwar; Gore, Rohitkumar; Ambekar, Jalindar; Kulkarni, Milind; Varma, Anjanikumar; Kale, Bharat (ChemistrySelect, 2018)
Ethoxy ester functionalized imidazolium and bis(tri fluoromethanesulfonyl)imide based ionic liquids (ILs) are synthesized and considered as electrolyte for lithium ion batteries. The series of ethoxy ester functionalized ionic liquids were chosen with increase in ethoxy unit from one to three, followed by polymeric units. These ionic liquids provide both ester and ethoxy groups as interaction sites for Li+ ions enhancing the Li+ ion transportation, resulting in ionic conductivity of 10(-3) Scm(-1) at 25 degrees C, which is of 10(3) factor higher than ethoxy containing polyethylene oxide solid polymer electrolyte. It's noteworthy that the conductivity increases as ethoxy units are increased from one to three units, followed by a decrease for the polymeric ethoxy unit. Electrochemical stability window of these ionic liquids improves as the ethoxy groups are added to imidazolium cation. The Li/LiFePO4 cell fabricated with [ME(3)AMIm][TFSI] electrolyte shows good initial discharge capacity of 98.5 mAhg(-1) at 0.05 C-rate at room temperature, which gradually decreases with cycling. Systematic investigation of electrode surfaces by using SEM and EDX shows deposition of passivation layers on their surfaces. Ionic liquids fabricated by this facile method provide a promising model system for understanding the molecular interactions in promoting the lithium-ion conduction mechanism. The advantages and the limits associated to series of ionic liquid electrolytes are critically investigated.

Evaluating antimalarial efficacy by tracking glycolysis in Plasmodium falciparum using NMR spectroscopy - Shivapurkar, Rupali; Hingamire, Tejashri; Kulkarni, Akshay S.; Rajamohanan, P. R.; Reddy, D. Srinivasa; Shanmugam, Dhanasekaran (Scientific Reports, 2018)
Glucose is an essential nutrient for Plasmodium falciparum and robust glycolytic activity is indicative of viable parasites. Using NMR spectroscopy, we show that P. falciparum infected erythrocytes consume similar to 20 times more glucose, and trophozoites metabolize similar to 6 times more glucose than ring stage parasites. The glycolytic activity, and hence parasite viability, can be measured within a period of 2 h to 5 h, using this method. This facilitates antimalarial bioactivity screening on ring and trophozoite stage parasites, exclusively. We demonstrate this using potent and mechanistically distinct antimalarial compounds such as chloroquine, atovaquone, cladosporin, DDD107498 and artemisinin. Our findings indicate that ring stage parasites are inherently more tolerant to antimalarial inhibitors, a feature which may facilitate emergence of drug resistance. Thus, there is a need to discover novel antimalarial compounds, which are potent and fast acting against ring stage parasites. The NMR method reported here can facilitate the identification of such molecules.

Evaluation of Candida tropicalis (NCIM 3321) extracellular phytase having plant growth promoting potential and process development - Puppala, Kumar Raja; Naik, Tejali; Shaik, Alfina; Dastager, Syed; Kumar, V. Ravi; Khire, Jayant; Dharne, Mahesh (Biocatalysis and Agricultural Biotechnology, 2018)
Phytase is known to provide a solution for depletion of phosphorus (P). It helps it by hydrolyzing the insoluble P source in soil which is phytate. In this study, provides insight on yeast Candida tropicalis (NCIM 3321) which produces cell bound and extracellular thermostable phytase. The media components were optimized to enhance the enzyme production and checked for plant growth promoting activity. On optimization the isolate exhibited enhanced cell bound and extracellular phytase activity by four folds (from 236 to 1024 IU DCG⁻¹) and by five folds (from 0.46 to 1.95 IU ml⁻¹) respectively in 36 h. The production time decreased to 24 h compare to shake flask on Up-scaling the production process upto 10 L scale, thus increasing the productivity of cell bound (1810 IU DCG⁻¹day⁻¹) and extracellular phytase (6.08 IU ml⁻¹ day⁻¹). The crude phytase (12 IU) from NCIM 3321 strain was studied for plant growth promotion activity in lab scale and field level experiments with maize crop. Findings of the study revealed that the extracellular phytase derived from non pathogenic C. tropicalis (NCIM 3321) was found to be plant growth stimulating by increasing the available P in soil. Our findings of phytase isolated from non-pathogenic yeast C. tropicalis NCIM 3321 exhibited dephytinization potential. Therefore, current study may have profound application in sustainable agriculture.

Evaluation of humidity sensor based on PVP-RGO nanocomposites - Bhangare, Bhagyashri; Jagtap, Shweta; Ramgir, Niranjan; Waichal, Rupali; Muthe, K. P.; Gupta, S. K.; Gadkari, Sanjay C.; Aswal, D. K.; Gosavi, Suresh (IEEE sensors journal, 2018)
his paper describes the humidity sensing properties of one step in situ synthesized poly (N-vinyl pyrrolidone)- reduced graphene oxide (PVP-RGO) nanocomposites. Different PVP-RGO nanocomposites were obtained by varying PVP/GO weight %ratio as x/50 mg, wherein x = 25, 50, and 75 mg, respectively. The real-time adsorption kinetics of the water molecules during the humidity sensing were also discussed using Elovich model, pseudo first and second order equations. The increase in humidity response of 1.5 PVP-RGO nanocomposite is attributed to the presence of large amount of oxygen functionalities. The above observation was corroborated using spectroscopic analysis. The optimized PVP-RGO nanocomposite showed faster response kinetics with response and recovery times of 10 and 20 s, respectively. The present humidity sensor shows remarkable linearity over the range of 20-90%RH. More specifically, sensitivity was correlated with oxygen functionalities created due to variation of PVP during the functionalization of RGO nanosheets.

Evolutionary perspectives of genotype-phenotype factors in leishmania metabolism - Subramanian, Abhishek; Sarkar, Ram Rup (Journal of Molecular Evolution, 2018)
The sandfly midgut and the human macrophage phagolysosome provide antagonistic metabolic niches for the endoparasite Leishmania to survive and populate. Although these environments fluctuate across developmental stages, the relative changes in both these environments across parasite generations might remain gradual. Such environmental restrictions might endow parasite metabolism with a choice of specific genotypic and phenotypic factors that can constrain enzyme evolution for successful adaptation to the host. With respect to the available cellular information for Leishmania species, for the first time, we measure the relative contribution of eight inter-correlated predictors related to codon usage, GC content, gene expression, gene length, multi-functionality, and flux-coupling potential of an enzyme on the evolutionary rates of singleton metabolic genes and further compare their effects across three Leishmania species. Our analysis reveals that codon adaptation, multi-functionality, and flux-coupling potential of an enzyme are independent contributors of enzyme evolutionary rates, which can together explain a large variation in enzyme evolutionary rates across species. We also hypothesize that a species-specific occurrence of duplicated genes in novel subcellular locations can create new flux routes through certain singleton flux-coupled enzymes, thereby constraining their evolution. A cross-species comparison revealed both common and species-specific genes whose evolutionary divergence was constrained by multiple independent factors. Out of these, previously known pharmacological targets and virulence factors in Leishmania were identified, suggesting their evolutionary reasons for being important survival factors to the parasite. All these results provide a fundamental understanding of the factors underlying adaptive strategies of the parasite, which can be further targeted.
Keywords: Codon usage; Evolutionary rate variation; Leishmania metabolism; Multi-functionality; Physiological fluxcoupling; Principal component regression (PCR)

Excited state intramolecular proton transfer in 1,8-Dihydroxy-9,10-anthraquinone dye: Revealing microstructures in [C(n)mIm][NTf2] and [C(n)mIm][BF4] series of ionic liquid solvents - Beniwal, Vijay; Kumar, Anil; Pal, Haridas (Journal of Photochemistry and Photobiology A-Chemistry, 2018)
Excited state intramolecular proton transfer (ESIPT) in 18-dihydroxy-9,10-anthraquinone (18DHAQ) dye has been investigated in two series of 1-alkyl-3-methylimidazolium ([C(n)mIm](+)) based ionic liquid (IL) solvents, [C(n)mlm][NTf2] and [C(n)mlm][BF4], with n = 2, 4, 6, 8 and 10, using steady-state (SS) and time resolved (TR) fluorescence studies. In both the IL series, fluorescence intensity for tautomer (T*) form gradually decreases relative to normal (N*) form with increasing n value for [C(n)mlm](+) cations. Observed results suggest microstructure formation and its consequent effect on the ESIPT process of the dye in these IL solvents. Since more extensive microstructures are likely with larger n values of [C(n)mIm](+) cations, the dye is expectedly solubilized more in the polar microdomains of the solvent microstructures, resulting better stabilization for the more dipolar N* state and hence a higher emission intensity from this state. This proposition is clearly supported by ultrafast (sub-picosecond) fluorescence kinetics for both N* and T* states, though sub-nanosecond TR results indicate very similar fluoresce decays for both N* and T*, suggesting an eventual kinetic equilibrium between two states subsequent to the initial ultrafast and fast forward and backward ESIPT processes. Small differences between the results in the [C(n)mIm][NTf2] and [C(n)mIm][BE4] series of ILs are attributed to dissimilar size, shape and basicity of [NTf2]- and [BF4]- anions, responsible for some characteristic changes in the microstructures formed in the respective solvent series. To the best of our knowledge, present study is the only report demonstrating modulations in the ESIPT process through microstructure formations in neat [C(n)mIm](+) based IL solvents. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 1; 1-Alkyl-3-methylimidazolium ionic liquids; 8-Dihydroxyanthraquinone; Emission modulations of tautomeric forms; ESIPT process; Microstructure formation

Excited-state prototropism of 7-hydroxy-4-methylcoumarin in [C(n)mim][BF4] series of ionic liquid-water mixtures: insights on reverse micelle-like water nanocluster formation - Beniwal, Vijay; Kumar, Anil; Pal, Haridas; Choudhury, Sharmistha Dutta (Photochemical & Photobiological Sciences, 2018)
This study explores the excited state prototropic behavior of the fluorophore, 7-hydroxy-4-methylcoumarin (7H4MC), in the [C(n)mim][BF4] (n = 2, 4, 6, 8, 10) series of ionic liquid (IL)-water mixtures at low water contents. In pure IL media, 7H4MC exists in the neutral form in both ground and excited states. However, on addition of water to the ILs, the excited neutral form of the dye is gradually converted to the anionic and the tautomeric species, leading to characteristic changes in the emission spectra. The similarity in the spectral features of 7H4MC in the IL-water system with that in a conventional reverse micelle system rather than with organic solvent-water mixtures, suggests that in the presence of water, the ILs are organized into reverse micelle-like structures with the consequent formation of confined water pockets. The results further suggest that formation of water nanoclusters and the ensuing changes in excited state prototropic behavior of the dye, is facilitated by increase in the alkyl chain length of the IL cation. These propositions are supported by time-resolved fluorescence studies. To the best of our knowledge this is the first report on proton transfer reaction in IL-water mixtures at low water contents. Considering that ILs are useful as solvents and surfactants, and IL-water mixtures in particular have applications in chemical extractions and biocatalysis, an understanding of the structural organization and water pool formation in these systems is quite important. The insights obtained from the prototropic transformations of 7H4MC are significant not only for fundamental self-assembly studies, but also for the development of ILs as chemical reaction media.

Experimental and theoretical investigations of different diketopyrrolopyrrole-based polymers - Murugan, Pachaiyappan; Raghavendra, Venkatraman.; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Mandal, Asit Baran; Subramanian, Venkatesan; Samanta, Debasis (ACS Omega, 2018)
Diketopyrrolopyrrole (DPP)-based polymers are often considered las the most promising donor moiety in traditional bulk heterojunction solar cell devices. In this paper, we report the synthesis, characterization of various DPP-based copolymers with different molecular weights, l and polydisper sity where other aromatic repeating units (phenyl or thiophene based) are connected by alternate double bonds or triple bonds. Some of the copolymers were used for device fabrication and the crucial parameters such as fill factor (FF) and open circuit voltage (V-oc) were calculated. The density functional theory was used to optimize the geometries and deduce highest occupied molecular orbital lowest unoccupied molecular orbital gaps of all the polymers and'theoretically predict their optical and electronic properties. Optical properties of all the polymers, electrochemical properties and band gaps were also obtained experimentally and compared with the theoretically predicted values.

Experimental evidences for existence of varying moieties and functional groups in assorted crop waste derived organosolv lignins - Singh, Sandip K.; Dhepe, Paresh L. (Industrial Crops and Products, 2018)
Isolation of organosolv lignins (ORGLs, water:ethanol, 180 degrees C, 1 h, 93 +/- 5% mass balance) from various lignocellulosic materials like rice husk (RH), wheat straw (WS), bagasse (BG) & wood chips (WC) was done and experimental evidences are provided to perceive the differences in the structures of isolated lignins. To achieve this on bulk level, lignins were characterized by XRD, GPC, TGA & elemental analysis and on molecular level using UV-vis, ATR, 1D/2D HSQC NMR techniques. Besides isolated lignins, crop wastes and pulps were also characterized to divulge details on their properties. It was revealed that lignins have varying concentrations of sinapyl (S), coniferyl (G) and p-coumaryl alcohols (H) and tricin (T) moieties. While, Tricin (T) type lignin moieties are observed only in RH and WS derived lignins, RH derived lignin has higher concentration of side chains than other isolated lignins. Additionally, it is discovered that most lignins have G as main moiety.

Exploiting functionalities of biomass in nanocomposite development: application in dye removal and disinfection along with process intensification - Kirti, Saumaya; Bhandari, Vinay M.; Jena, Jyotsnarani; Sorokhaibam, Laxmi Gayatri; Bhattacharyya, Arnab S. (Clean Technologies and Environmental Policy, 2018)
A green synthesis of multifunctional superparamagnetic nanocomposites using the whole unripened fruit of Cassia fistula (Golden shower) with potential for removal of both cationic and anionic dyes and antimicrobial property is reported for the first time in the present work. A natural medium in the form of clarified butter was used to enhance the multifunctional character. The surface morphology, textural characteristics and composition of the prepared nanoparticles and composites were studied to understand the multifunctional nature. The dye removal was investigated for four different dyes, namely methyl blue, Congo red, rhodamine-B and auramine. Iron nanoparticles were largely effective in the removal of acidic dyes, while the magnetic nanocomposites were effective for the removal of both acidic and basic dyes which can be attributed to the functionalities imparted from Cassia fistula and clarified butter. The dye removal behavior can be significantly enhanced (similar to 50%) using process intensification-adsorption coupled with acoustic cavitation, which also indicated a reduced adsorbent loading as compared to the conventional adsorptive dye removal. The nanomaterials were completely separated from dye solution with absolute ease of separation by applying simple magnetic field. Also, the developed materials were useful in disinfection of E. coli with a high efficiency of 90% confirming significant antimicrobial property at lower concentrations.

Exploring GPCR lipid interactions by molecular dynamics simulations: excitements, challenges, and the way forward - Sengupta, Durba; Prasanna, Xavier; Mohole, Madhura; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2018)
Gprotein-coupled receptors (GPCRs) are seven transmembrane receptors that mediate a large number of cellular responses and are important drug targets. One of the current challenges in GPCR biology is to analyze the molecular signatures of receptor-lipid interactions and their subsequent effects on GPCR structure, organization, and function. Molecular dynamics simulation studies have been successful in predicting molecular determinants of receptor-lipid interactions. In particular, predicted cholesterol interaction sites appear to correspond well with experimentally determined binding sites and estimated time scales of association. In spite of several success stories, the methodologies in molecular dynamics simulations are still emerging. In this Feature Article, we provide a comprehensive overview of coarse-grain and atomistic molecular dynamics simulations of GPCR-lipid interaction in the context of experimental observations. In addition, we discuss the effect of secondary and tertiary structural constraints in coarse-grain simulations in the context of functional dynamics and structural plasticity of GPCRs. We envision that this comprehensive overview will help resolve differences in computational studies and provide a way forward.

Exploring immuno-regulatory mechanisms in the tumor microenvironment: model and design of protocols for cancer remission - Ganguli, Piyali; Sarkar, Ram Rup (Plos One, 2018)
The tumor microenvironment comprising of the immune cells and cytokines acts as the 'soil' that nourishes a developing tumor. Lack of a comprehensive study of the interactions of this tumor microenvironment with the heterogeneous sub-population of tumor cells that arise from the differentiation of Cancer Stem Cells (CSC), i.e. the 'seed', has limited our understanding of the development of drug resistance and treatment failures in Cancer. Based on this seed and soil hypothesis, for the very first time, we have captured the concept of CSC differentiation and tumor-immune interaction into a generic model that has been validated with known experimental data. Using this model we report that as the CSC differentiation shifts from symmetric to asymmetric pattern, resistant cancer cells start accumulating in the tumor that makes it refractory to therapeutic interventions. Model analyses unveiled the presence of feedback loops that establish the dual role of M2 macrophages in regulating tumor proliferation. The study further revealed oscillations in the tumor sub-populations in the presence of T-H1 derived IFN-gamma that eliminates CSC; and the role of IL10 feedback in the regulation of T-H1/T-H2 ratio. These analyses expose important observations that are indicative of Cancer prognosis. Further, the model has been used for testing known treatment pro-tocols to explore the reasons of failure of conventional treatment strategies and propose an improvised protocol that shows promising results in suppressing the proliferation of all the cellular sub-populations of the tumor and restoring a healthy T-H1/T-H2 ratio that assures better Cancer remission.

Exploring the biological roles of Dothideomycetes ABC proteins: leads from their phylogenetic relationships with functionally-characterized Ascomycetes homologs - Dube, Gaurav; Kadoo, Narendra; Prashant, Ramya (PLoS One, 2018)
Background The ATP-binding cassette (ABC) superfamily is one of the largest, ubiquitous and diverse protein families in nature. Categorized into nine subfamilies, its members are important to most organisms including fungi, where they play varied roles in fundamental cellular processes, plant pathogenesis or fungicide tolerance. However, these proteins are not yet well-understood in the class Dothideomycetes, which includes several phytopathogens that infect a wide range of food crops including wheat, barley and maize and cause major economic losses. Results We analyzed the genomes of 14 Dothideomycetes fungi (Test set) and seven well-known Ascomycetes fungi (Model set-that possessed gene expression/functional analysis data about the ABC genes) and predicted 578 and 338 ABC proteins from each set respectively. These proteins were classified into subfamilies A to I, which revealed the distribution of the subfamily members across the Dothideomycetes and Ascomycetes genomes. Phylogenetic analysis of Dothideomycetes ABC proteins indicated evolutionary relationships among the subfamilies within this class. Further, phylogenetic relationships among the ABC proteins from the Model and the Test fungi within each subfamily were analyzed, which aided in classifying these proteins into subgroups. We compiled and curated functional and gene expression information from the previous literature for 118 ABC genes and mapped them on the phylogenetic trees, which suggested possible roles in pathogenesis and/or fungicide tolerance for the newly identified Dothideomycetes ABC proteins. Conclusions The present analysis is one of the firsts to extensively analyze ABC proteins from Dothideomycetes fungi. Their phylogenetic analysis and annotating the clades with functional information indicated a subset of Dothideomycetes ABC genes that could be considered for experimental validation for their roles in plant pathogenesis and/or fungicide tolerance.

Effect and position of spiro-bipropylenedioxythiophene pi-spacer in donor-pi-spacer-acceptor dyes for dye-sensitized solar cell - Sil, Manik Chandra; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Dyes and Pigments, 2019)
Improper orientation and self-assembly of dyes on TiO2 surface are the main disadvantages at the dye-TiO2 interface that governs both charge injection and dye regeneration processes. In this report, a series of homo spiro-dimeric donor-pi-spacer-acceptor (D-pi-A) dyes based on bithiophene and terthiophene spacers with two-anchoring group containing dyes, TT1, T1T, TT1T were designed and synthesized by Pd-catalyzed successive Suzuki coupling followed by direct arylation reactions. The position of branching centre in TT1 and T1T was systematically varied, where the spiro unit was placed near and away from the anchoring carboxylic acid unit, respectively. The dimeric spiro-dye T1T showed device performance, which is 1.6 fold higher than its structural isomeric analogue TT1, of 3.9% with a V-oc and J(sc) of 0.593 V and 9.09 mA/cm2, respectively, whereas for the isomeric analogue TT1 a device performance of 2.45% (V-oc of 0.568 V and J(sc) of 6.25 mA/cm2) under simulated 1 Sun (100 mW/cm2) condition. The improved Voc for the dye T1T compared to TT1 dye was ascribed to the dipole moment exerted by the dyes on TiO2 surface. Further the PCE of 4.16% (V-oc 0.589 V, J(sc) 9.79 mA/cm2 respectively) maximum was observed, when an extra thiophene unit was inserted in between the donor and pi-spacer in dye TT1T. The shifting the position of branching spiroBiProDOT pi-spacer makes an impact on the device performance by synergistically enhancing both Voc and Jsc.
Keywords: CDCA; D-pi-A Spiro dye; Dye aggregation; dye-sensitized solar cell; spiroBiProDOT spacer

Effect of copper contamination on zooplankton epidemics - Banerjee, Swarnendu; Sarkar, Ram Rup; Chattopadhyay, Joydev (Journal of Theoretical Biology, 2019)
Infectious disease and chemical contamination are increasingly becoming vital issues in many ecosystems. However, studies integrating the two are surprisingly rare. Contamination not only affects the inherent host-resource interaction which influences the epidemic process but may also directly affect epidemiological traits via changes in host's behaviour. The fact that heavy metal such as copper is also an essential trace element for organisms, further increase complexity which make predicting the resultant effect of contamination and disease spread difficult. Motivated by this, we model the effect of copper enrichment on a phytoplankton-zooplankton-fungus system. We show that extremely deficient or toxic copper may have a destabilizing effect on the underlying host-resource dynamics due to increased relative energy fluxes as a result of low host mortality due to fish predation. Further, on incorporating disease into the system, we find that the system can become disease-free for an intermediate range of copper concentration whereas it may persist for very less copper enrichment. Also, we predict that there may exist vulnerable regions of copper concentration near the toxic and deficient levels, where the parasite can invade the system for a comparatively lower spore yield. Overall, our results demonstrate that, the effect of contamination may be fundamental to understanding disease progression in community ecology. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Bistability; Chemical contamination; Daphnia-parasite; Hormesis; Host-resource

Effect of co-substitution of Co2+ and V5+ for Fe3+ on the magnetic properties of CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Physica B: Condensed Matter, 2019)
Different chemical compositions in Co1+2xVxFe2-3xO4 (0 ≤ x ≤ 0.1) have been synthesized by the conventional solid-state reaction method and processed under identical conditions. The materials are investigated to assess the impact of change in the oxidation states of metal ions on structural and magnetic properties of cobalt ferrite. Rietveld refinement of the X-ray diffraction patterns revealed a single phase nature of all compositions with cubic spinel structure. The cubic lattice parameter was found to decrease non-linearly from 8.393 Å for x = 0 to 8.377 Å for x = 0.1, due to the effect of ionic size and valency of the substituted metal ions. Sintered co-substituted compositions exhibited smaller grains against unsubstituted counterpart, due to low melting point of raw material V2O5. Strong experimental evidence of V substitution for Fe at the tetrahedral sites of the spinel ferrite has been extracted from the Raman spectral analysis. Saturation magnetization (Ms) was observed to decrease from 452 kA/m for x = 0–411 kA/m for x = 0.1. Coercivity (Hc) and magnetocrystalline anisotropy (K1) were also found to follow the same trend. Variation of the structural and magnetic parameters is attributed to the changes in the oxidation state of Co from 2 + to 3 + as it is confirmed from the results of XPS analysis.

Effect of electrostatic interactions on structure and mechanical properties of ice templated colloid-polymer composites - Suresh, Karthika; Kumaraswamy, Guruswamy (Journal of Physics D-Applied Physics, 2019)
When an aqueous dispersion of negatively charged colloids, cationic polymer and crosslinker is frozen and the polymer is allowed to crosslink in the frozen state, we obtain a self-standing macroporous composite foam. This material is soft, despite the high concentration of colloids and yet is remarkably elastic to large compressive strains. In these macroporous composites, the pore walls comprise colloidal particles held within a crosslinked polymer network. Here, we investigate the effect of varying colloid- polymer interactions in pre-fabricated macroporous composites on their microstructure and mechanical properties. During preparation of the composite, cationic polymer adsorbs on the negatively charged colloids. We tune the surface charge of particles embedded in a macroscopic monolith by immersing the composites in water maintained at different pH. In this way, we tune polymer-particle interactions in the composite. We observe a sudden increase in interparticle distance and swelling of composite when pH is decreased below the particle's isoelectric point. Correspondingly, we observe reduction in Young's and shear moduli, compression strength and macroscopic energy dissipation. We did not observe any pH dependent changes in pure polymer sponges (prepared by ice templating and crosslinking a polymer solution that does not contain colloidal particles). Therefore, the pH dependent structural and mechanical property changes arise from the composite structure rather than purely from the crosslinked polymer. We believe that the reduction in mechanical stiffness when the polymer-particle interaction becomes repulsive is because of the reduction in interfacial contacts between particle and polymer. Therefore, the mechanical stiffness of ice templated composite is strongly influenced by interactions between the polymer and particle surface.
Keywords: colloid; electrostatic interaction; ice templating; mechanical properties; Polymer

Effect of media components and growth conditions for improved linoleic acid production by beauveria species - Sanghi, Smrati; Chirmade, Tejas; More, Snehal; Prabhune, Asmita; Gupta, Vidya; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2019)
Beauveria species are well-known insect pathogenic fungi, and Beauveria bassiana is used as a biopesticide against various pests in agriculture. However, the Beauveria species has not been reported as producers of microbial oils. In this study, Beauveria spp. MTCC 5184 was used to produce microbial oil with high linoleic acid (LA) content. Ten experiments were performed to evaluate the effects of several media parameters, such as carbon and nitrogen sources, pH, various concentrations of carbon and nitrogen, growth duration, and oleic acid (OLA) supplementation for maximum LA and dry biomass production by the fungus. Several of these parameters had a significant impact on the production of LA, as well as dry biomass. The glucose yeast extract (GYE) medium supplemented with 1.5% (w/v) peptone yielded maximum LA (0.32 +/- 0.01 g L-1) and biomass (5.51 +/- 0.26 g L-1). However, through the addition of 1.0% (w/v) OLA, the precursor of LA, LA production was enhanced 12-fold (1.24 +/- 0.03 g L-1), and the biomass production increased by 5-fold (11.05 +/- 0.46 g L-1) in comparison to those in the basal (GYE) medium. Using lactose as the sole carbon source produced the lowest LA (0.05 +/- 0.00 g L-1) and biomass (1.04 +/- 0.10 g L-1). The results of this study will be useful for the commercial exploitation of this fungus for the production of LA-rich microbial oil for use in the production of lubricants, greases, paints, cosmetics, etc.

Effect of processing conditions on the rheological properties of blends of ultra high molecular weight polyethylene with high‐density polyethylene - Chaudhuri, K.; Poddar, S.; Pol, H.; Lele, A.; Mathur, A.; Srinivasa Rao, G.S.; Jasra, R. (Polymer Engineering and Science, 2019)
Blends of high‐density polyethylene (HDPE) with small amounts of ultra‐high molecular weight polyethylene (UHMWPE) were prepared by melt mixing in a twin‐screw microcompounder. Two types of UHMWPE differing in their states of chain entanglement were used. The blend composition, time of mixing, and rotation speed of the screws were varied. Rheological properties of the blends were studied in oscillatory shear and uniaxial elongational tests. Reduction in phase angle measured in dynamic shear rheology and increase in extensional strain hardening were found to be useful indicators for quantifying the extent of mixing of the two components. Although the disentangled UHMWPE showed reasonable mixing with HDPE during typical residence times of melt compounding operations, the entangled UHMWPE remained essentially undissolved. The extent of mixing increased with mixing time and screw speed. POLYM. ENG. SCI., 2018. © 2018 Society of Plastics Engineers

Effect of substitution on the excited state photophysical and spectral properties of boron difluoride curcumin complex dye and their derivatives: a time dependent-DFT study - Selvam, Karthick; Gandhi, Sivaraman; Krishnarnurty, Sailaja; Gopalakrishnan, Gopu (Journal of Photochemistry and Photobiology B-Biology, 2019)
The optical, charge transport and electronic properties of boron difluoride curcumin (BFC) complex have been explored using the DFT (Density Functional Theory) method and B3LYP functional with the combination of 6-31 + G(d,p) as a basis set. The influence of substitution with various electron releasing and withdrawing groups on the above properties is analyzed and discussed in this work. The results reveal that the BFC complex on additional electron releasing substitution experiences redshifts in the optical transitions, and this is correlated with the dipole moment, NBO charges, HOMO-LUMO energy gap. Further, the absorption (lambda(abs)) and emission (lambda(ems)) spectra of substituted and unsubstituted BFCs are calculated using Time-Dependent Density Functional Theory (TD-DFT). The results show that the electron releasing groups strongly influence the absorption and emission spectra of BFC. Electron releasing groups in BFC derivatives generate the wavelength shift (Bathochromic), but the electron-withdrawing groups in BFC don't affect the lambda(abs) and lambda(ems) when compare to its original (parent) compound. The output of the research work strongly recommends that the amino, phenyl and N, N'-dimethylamino derivatives are potential candidates to act as fluorescent materials due to enhance the emission behavior of BFC and also can be used as an electron/charge transport material for organic light-emitting diodes (OLEDs).
Keywords: Absorption; Boron difluoride curcumin; Emission; Molecular orbitals; Time-dependent density functional theory

Effective polysulfide trapping polar interlayer for high rate Li-S batteries - Karuppiah, Saravanan; Kalimuthu, Balakumar; Nazrulla, Mohammed Azeezulla; Krishnamurty, Sailaja; Nallathamby, Kalaiselvi (Journal of Materials Chemistry A, 2019)
A microporous and polymeric C3N4 framework (CNF), when exploited as an interlayer and as a cathode host in Li-S batteries, demonstrates significantly improved electrochemical behavior with a special relevance to high rate applications up to 5C. A CNF obtained through a template free synthesis approach and activated with KOH is endowed with a high specific surface area of 1000 m(2) g(-1), a desirable nitrogen content (13%) to ensure polarity and a microporous architecture, required to increase the accommodation capability of discharge products. The difference in electronegativity between C and N in CNFs combats in a major way the shuttling of lithium polysulfides (LIPSs) and ensures the realization of increased LIPS binding sites due to the presence of pyridinic nitrogen. Furthermore, a CNF driven change in the molecular configuration of adsorbed LIPSs leads to the uniform distribution and sequestration of discharge products. Similarly, micropores and the polymeric nature of CNFs facilitate the effective confinement of LIPSs and ably accommodate the volume changes (through the formation of Li2S upon discharge) respectively, especially when a microporous CNF interlayer is involved in the Li-S assembly. In particular, a CNF with 60 wt% sulfur loading, otherwise represented as CNFS-60, when exploited as a cathode in combination with the deployment of a CNF interlayer exhibits appreciable capacity values of 500 and 400 mA h g(-1) at 3 and 5C respectively. Furthermore, the combination of the CNF interlayer and cathode demonstrates a steady state discharge capacity of 437 mA h g(-1) at 1C rate up to 300 cycles, without any significant capacity loss. The involvement of chemical interaction of the CNF with lithium polysulfides is demonstrated using density functional theory calculations. Hence, the effective trapping and the subsequent localization of migrating LIPSs arising from the strong chemical interaction of the CNF with soluble LIPSs and the advantages of high concentration of accessible pyridinic nitrogen sites to the LIPS adsorption in improving the electrochemical behavior of the Li-S system could be understood. This new CNF based interlayer provides a promising approach and ample scope for its implementation in futuristic Li-S batteries.

Efficient and convenient route for the synthesis of thiophene-2-carboxamidines as potential inhibitors of nitric oxide synthase (NOS) - Rashid, P. P.; Singh, Dharmendra; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2019)
A mild and efficient synthesis of substituted thiophene-2-carboxamidines which are potent inhibitors of nitric oxide synthase (NOS) is reported herein. The key step involves reaction of a BOC-protected imidazolyl thiophene-2-carboxamidine reactive intermediate with various primary amines to form BOC-thio-phene-2-carboxamidines which could be readily deprotected using TFA to furnish free carboxamidines. The method is very mild and tolerates diverse substituents including sensitive peptide and amino acid fragments. This new methodology represents a substantial improvement to the literature method owing to its simplicity and hassle-free purification procedures. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Amidines; Nitric oxide synthase (NOS); Nitric oxide synthase inhibitors; Thiophene-2-carboxamidines

Efficient and cost effective synthesis of acetamides catalyzed by calcium chloride - Sangole, M. T.; Thorat, S. M.; Shirsath, S.; Deshmukh, S. P.; Muthukrishnan, M.; Mujahid, M. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
CaCl2 has been found to be an efficient and cost effective catalyst for the rapid synthesis of acetamides in high yields. The use of stoichiometric quantities of acetic anhydride under solvent free conditions without any additional chromatographic purifications makes this protocol a safe alternative to the existing methods.
Keywords: Acetamide; acetylation; Acylation; Amine; CaCl2

Efficient bifunctional reactivity of K-doped CrO(OH) nanosheets: exploiting the combined role of Cr(iii) and surface -OH groups in tandem catalysis - Vernekar, Dnyanesh; Ratha, Satyajit; Rode, Chandrashekhar; Jagadeesan, Dinesh (Catalysis Science & Technology, 2019)
This work reports the bifunctional catalytic activity of layered K-doped alpha-CrO(OH). The combined action of the redox active Cr(III) and the surface hydroxyl groups was efficiently used to carry out 2-3 oxidation reactions in tandem followed by condensation/coupling reactions in one pot. Oxidation of benzyl alcohol followed by Knoevenagel condensation or coupling reactions forming C-C and C-N linkages in one pot is demonstrated. The catalyst has been characterized using XRD, IR, TGA, CO2-TPD, cyclic voltammetry, XPS and microscopic techniques to gain insight into the nature of active sites. The role of O- and O2- on the CrO(OH) catalyst in the bifunctional activity was studied using analytical techniques. Recyclability and leaching tests confirmed that K-alpha-CrO(OH) is a stable and environmentally safe catalyst.

Efficient broad-band emission from contorted purely corner-shared one dimensional (1D) organic lead halide perovskite - Biswas, Anupam; Bakthavatsalam, Rangarajan; Shaikh, Samir R.; Shinde, Aparna; Lohar, Amruta; Jena, Satyam; Gonnade, Rajesh G.; Kundu, Janardan (Chemistry of Materials, 2019)

Efficient heterogeneous copper fluorapatite (CuFAP)-catalysed oxidative synthesis of diaryl sulfone under mild ligand- and base-free conditions - Kamble, R. B.; Chavan, S. S.; Suryavanshi, G. (New Journal of Chemistry, 2019)
A simple, eco-friendly and efficient method for the synthesis of unsymmetrical diaryl sulfones using heterogeneous copper fluorapatite (CuFAP)-catalysed coupling of aryl sulfonic acid and phenyl boronic acid has been developed with good to excellent yields without use of any ligand, base or co-catalyst. Broad substrate scope and gram scale operations are the important features of this method.

Efficient removal of Arsenic (III) by novel micro and nano dialdehyde cellulose-cysteine complex extracted from wood pulp cellulose - Chen, Hui; Sharma, Sunil; Sharma, Priyanka; Yeh, Heidi; Hsiao, Benjamin (Abstracts of Papers of the American Chemical Society, 2019)

Efficient synergetic combination of H-USY and SnO2 for direct conversion of glucose into ethyl levulinate (Biofuel Additive) - Heda, Jidnyasa; Niphadkar, Prashant; Bokade, Vijay (Energy & Fuels, 2019)
Ethyl levulinate (EL), a biofuel additive for petroleum and biodiesel can also be used as a 100% fuel to replace petroleum diesel with the existing diesel engine. The major problem to make the EL process economical is the lack of a proper conversion technology to convert C-6 sugars such as glucose with higher yield of EL as well as process which can tolerate higher glucose concentration to increase productivity. The present study highlighted the catalytic synthesis of EL from glucose over synergetic combination of zeolite H-USY and Lewis acidic catalysts such as Sn-beta, TiO2, ZrO2, and SnO2. Because of the strong Lewis acidic nature and the subsequent enhancement in the isomerization rate from glucosides to fructosides, the synergetic combination of H-USY with SnO2 showed higher EL yield than the combination with other Lewis acidic catalysts. So far, the highest EL yield of 81% from glucose (50 g/L) at 180 degrees C in 3 h was achieved over the optimal combination of 95% H-USY and 5% SnO2 having strong/weak acidity and B/L ratios of 1.30 and 0.75, respectively. The study was further extended for establishing the proposed reaction mechanism without the formation of 5-hydroxymethyl furfural, levulinic acid, and formic acid which makes the overall process clean and green.

Efficient synthesis of optically active neolignans ligraminol D and E - Ghotekar, Ganesh S.; Mujahid, M.; Muthukrishnan, M. (Synthesis-Stuttgart, 2019)
Efficient syntheses of optically active neolignans ligraminol D and E were achieved in four simple steps starting from easily available chiral benzyl glycidyl ethers. The products were obtained in good overall yields and high enantioselectivities. The protocol might also be useful in the synthesis of other ligraminols or related neolignans.
Keywords: benzyl glycidyl ether; Epoxide; lignan; ligraminol; Mitsunobu

Electrocatalysis of oxygen reduction reaction on shape-controlled pt and pd nanoparticles-importance of surface cleanliness and reconstruction - Devivaraprasad, Ruttala; Nalajala, Naresh; Bera, Bapi; Neergat, Manoj (Frontiers in Chemistry, 2019)
Shape-controlled precious metal nanoparticles have attracted significant research interest in the recent past due to their fundamental and scientific importance. Because of their crystallographic-orientation-dependent properties, these metal nanoparticles have tremendous implications in electrocatalysis. This review aims to discuss the strategies for synthesis of shape-controlled platinum (Pt) and palladium (Pd) nanoparticles and procedures for the surfactant removal, without compromising their surface structural integrity. In particular, the electrocatalysis of oxygen reduction reaction (ORR) on shape-controlled nanoparticles (Pt and Pd) is discussed and the results are analyzed in the context of that reported with single crystal electrodes. Accepted theories on the stability of precious metal nanoparticle surfaces under electrochemical conditions are revisited. Dissolution, reconstruction, and comprehensive views on the factors that contribute to the loss of electrochemically active surface area (ESA) of nanoparticles leading to an inevitable decrease in ORR activity are presented. The contribution of adsorbed electrolyte anions, in-situ generated adsorbates and contaminants toward the ESA reduction are also discussed. Methods for the revival of activity of surfaces contaminated with adsorbed impurities without perturbing the surface structure and its implications to electrocatalysis are reviewed.
Keywords: Adsorption; Dissolution; oxygen reduction reaction; Palladium; platinum; reconstruction; shape-control; surface cleaning

Electron crystallography - Blake, Alexander J.; de Boissieu, Marc; Nangia, Ashwini (IUCRJ, 2019)

Electronic integration and thin film aspects of Au-Pd/rGO/TiO2 for improved solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala P.; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2019)
In the present work, we have synthesized noble bimetallic nanoparticles (Au-Pd NPs) on a carbon-based support and integrated with titania to obtain Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2 nanocomposites using an ecofriendly hydrothermal method. Here, a 1:1 (w/w) Au-Pd bimetallic composition was dispersed on (a) high-surface-area (3000 m(2) g(-1)) activated carbon (Au-Pd/C), prepared from a locally available plant source (in Assam, India), and (b) reduced graphene oxide (rGO) (Au-Pd/rGO); subsequently, they were integrated with TiO2. The shift observed in Raman spectroscopy demonstrates the electronic integration of the bimetal with titania. The photocatalytic activity of the above materials for the hydrogen evolution reaction was studied under 1 sun conditions using methanol as a sacrificial agent in a powder form. The photocatalysts were also employed to prepare a thin film by the drop-casting method. Au-Pd/rGO/TiO2 exhibits 43 times higher hydrogen (H-2) yield in the thin film form (21.50 mmol h(-1) g(-1)) compared to the powder form (0.50 mmol h(-1) g(-1)). On the other hand, Au-Pd/C/TiO2 shows 13 times higher hydrogen (H-2) yield in the thin film form (6.42 mmol h(-1) g(-1)) compared to the powder form (0.48 mmol h(-1) g(-1)). While powder forms of both catalysts show comparable activity, the Au-Pd/rGO/TiO2 thin film shows 3.4 times higher activity than that of Au-Pd/C/TiO2. This can be ascribed to (a) an effective separation of photogenerated electron-hole pairs at the interface of Au-Pd/rGO/TiO2 and (b) the better field effect due to plasmon resonance of the bimetal in the thin film form. The catalytic influence of the carbon-based support is highly pronounced due to synergistic binding interaction of bimetallic nanoparticles. Further, a large amount of hydrogen evolution in the film form with both catalysts (Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2) reiterates that charge utilization should be better compared to that in powder catalysts.
Keywords: bimetal; Photocatalysis; surface plasmon resonance; TiO2; water splitting

Electrospun polycaprolactone/hydroxyapatite/ZnO nanofibers as potential biomaterials for bone tissue regeneration - Shitole, Ajinkya A.; Raut, Piyush W.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand P.; Garnaik, Baijayantimala (Journal of Materials Science-Materials In Medicine, 2019)
Fabricating a bioartificial bone graft possessing structural, mechanical and biological properties mimicking the real bone matrix is a major challenge in bone tissue engineering. Moreover, the developed materials are prone to microbial invasion leading to biomaterial centered infections which might limit their clinical translation. In the present study, biomimetic nanofibrous scaffolds of Poly -caprolactone (PCL)/nano-hydroxyapatite (nHA) were electrospun with 1wt%, 5wt%, 10wt%, 15wt% and 30wt% of zinc oxide (ZnO) nanoparticles in order to understand the optimal concentration range of (ZnO) nanoparticles balancing both biocompatibility and osteoregeneration. The developed nanofibrous scaffolds were successfully characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), contact angle, fourier transform infrared spectroscopy (FTIR), wide-angle X-Ray diffraction (WAXD), brunaueremmett Teller (BET) surface area and tensile testing. Biocompatibility of the developed scaffolds at in vitro level was evaluated by culturing MG-63 cells and investigating the impact on cell viability, proliferation, protein adsorption, alkaline phosphatase (ALP) activity and biomineralization. The PCL/nHA scaffolds exhibited a 1.2-fold increase in cell viability and proliferation, while incorporation of ZnO nanoparticles to PCL/nHA imparted antimicrobial activity to the scaffolds with a progressive increase in the antimicrobial efficacy with increasing ZnO concentration. The results of cell viability were supported by ALP activity and mineralization assay, wherein, PCL/nHA/ZnO scaffolds showed higher ALP activity and better mineralization capacity as compared to pristine PCL. Although, the PCL/nHA/ZnO scaffolds with 10, 15 and 30wt% of ZnO particles exhibited superior antimicrobial efficacy against both gram-negative (E. coli) and gram-positive (S. aureus) bacteria, a significant decrease in the cell viability and mechanical properties was observed at higher concentrations of ZnO namely 15 and 30%. Amongst the various ZnO concentrations studied optimal cell viability, antimicrobial effect and mechanical strength were observed at 10wt.% ZnO concentration. Thus, the present study revealed that the biomimetic tri-component PCL/nHA/ZnO scaffolds with ZnO concentration range of10% could be ideal for achieving optimal biocompatibility (cell proliferation, biomineralization, and antimicrobial capacity) and mechanical stability thus making it a promising biomaterial substrate for bone tissue regeneration. [GRAPHICS] .

Embedding S=1/2 Kagome-like lattice in reduced graphene oxide - Gupta, Kriti; Jha, Plawan Kumar; Dadwal, Arun; Debnath, Anil K.; Jaiswal, Ishan; Rana, Shammi; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry Letters, 2019)
An elegant platform to explore frustrated magnetism is the kagome spin lattice. In this work, clinoatacamite, a naturally occurring S = 1/2 kagome-like antiferromagnetic insulator, is synthesized in water at ambient pressure for the first time from a cuprous chloride (CuCl) precursor whereby Cu(I) was spontaneously oxidized to Cu(II) in the form of clinoatacamite [Cu-2(OH)(3)Cl] with a simultaneous reduction of graphene oxide (GO) to reduced graphene oxide (rGO) in one pot. A stable nanocomposite of phase-pure clinoatacamite nanocrystals embedded in the rGO matrix was isolated. The clinoatacamite-rGO nanocomposite was determined to be magnetically active with a markedly enhanced coercive field of similar to 2500 Oe at S K as well as electronically active with a conductivity value of similar to 200 S.m(-1) at 300 K. Our results illustrate an avenue of combining exotic magnetic and electronic lattices without impeding their individual characteristics and synergistically generating a new class of magnetic semiconductors.

Enantioselective formal total synthesis of (-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Gonnade, Rajesh G. (Organic Letters, 2019)
The enantioselective formal total synthesis of (-)-quinagolide has been accomplished in a linear sequence of 8 purification steps from pyridine. The key steps are (a) organocatalyzed Diets-Alder reaction for fixing all three stereocenters on piperidine ring; (b) protecting group enabled deoxygenation of isoquinuclidine skeleton under Birch reduction condition; (c) Lewis acid (TiCl4) catalyzed intramolecular Friedel-Crafts cyclization of dicarboxylic acid; and (d) one-pot diastereoselective ketone reduction-intramolecular cyclization to form oxazolidinone which enables trans-geometry installation. During the course of the synthesis, an interesting reductive cleavage of the C-N bond in the electron-deficient isoquinuclidine skeleton under the Birch reduction conditions has been observed. This is the first synthetic effort to access the core skeleton of (-)-quinagolide.

Enhanced energy density and stability of self-assembled cauliflower of Pd doped monoclinic WO3 nanostructure supercapacitor - Gupta, S. P.; Patil, V. B.; Tarwal, N. L.; Bhame, S. D.; Gosavi, S. W.; Mulla, I. S.; Late, D. J.; Suryavanshi, S. S.; Walke, P. S. (Materials Chemistry and Physics, 2019)
Enhanced electrochemical performance of WO3 nanostructures by engineering their morphology, structural and surface defect at nanoscale is feasible. Herein we report the effect of Pd doping on the morphological and electrochemical properties of WO3 at nanoscale prepared by a simple hydrothermal method. The synthesized pristine WO3 (cabbage like morphology) and Pd doped WO3 (cauliflower like morphology) are examined by using XRD, XPS, Raman spectra, BET, FE-SEM, TEM. The morphological investigation shows the effective rebuilding of nanosheets assembled cabbage shaped pristine WO3 into nanobricks assembled cauliflower shaped Pd doped WO3 with improvement in crystallinity, surface area and conductivity. As a result, the enhancement in the electrochemical performance of cauliflower shaped Pd-WO3 is recorded four times higher specific capacitance than pristine WO3. Additionally, the excellent cyclic stability (almost ten times higher than pristine WO3) up to 1100 cycles with nearly 86.95% capacity retention is observed in Pd-WO3 attributed to Pd content and highly modified structural arrangement.

Enhanced light harvesting and charge separation over wormhole mesoporous TiO2-X nanocrystallites towards efficient hydrogen generation - Negi, Sanjay Singh (Sustainable Energy & Fuels, 2019)
Here meso-TiO2-X materials with combined visible light absorption, high surface area, an anatase-rutile heterojunction, and electrically interconnected nanocrystallites in a wormhole mesoporous framework are achieved. Meso-TiO2-X materials were prepared by solution combustion synthesis (SCS), followed by hydrogenation at higher temperatures. The materials are thoroughly characterised by various physicochemical techniques. A small band gap (2.8 eV), type IV-H-2 mesoporosity with a biphasic heterojunction, and small pore depths (10 nm) in a wormhole mesoporous framework are observed with 35AP. Photocatalytic water splitting for hydrogen production and photocurrent generation were carried out with meso-TiO2-X materials under simulated sunlight. A six-fold increase in activity under AM 1.5G irradiation was observed, which is attributed to the generated mid-gap states which lead to band gap reduction, improved optical absorption in the visible and infrared light region resulting in higher charge carrier density. The presence of a biphasic heterojunction between the (1 0 1) anatase and (1 1 0) rutile facets assists in effective charge separation. A low charge diffusional constraint associated with wormhole mesoporosity helps in facile charge transport to the surface for improved charge utilisation in redox reactions.

Enhancing epi-cedrol production in escherichia coli by fusion expression of farnesyl pyrophosphate synthase and epi-cedrol synthase - Navale, Govinda R; Sharma, Poojadevi; Said, Madhukar S; Ramkumar, Sudha; Dharne, Mahesh S; Thulasiram, H., V; Shinde, Sandip S (Engineering in Life Science, 2019)
Terpene synthase catalyses acyclic diphosphate farnesyl diphosphate into desired sesquiterpenes. In this study, a fusion enzyme was constructed by linking Santalum album farnesyl pyrophosphate synthase (SaFPPS) individually with terpene synthase and Artemisia annua Epi-cedrol synthase (AaECS). The stop codon at the N-terminus of SaFPPS was removed and replaced by a short peptide (GSGGS) to introduce a linker between the two open reading frames. This fusion clone was expressed in Escherichia coli Rosseta DE3 cells. The fusion enzyme FPPS-ECS produced sesquiterpene 8-epi-cedrol from substrates isopentenyl pyrophosphate and dimethylallyl pyrophosphate through sequential reactions. The K-m values for FPPS-ECS for isopentyl diphosphate was 4.71 mu M. The fusion enzyme carried out the efficient conversion of IPP to epi-cedrol, in comparison to single enzymes SaFPPS and AaECS when combined together in enzyme assay over time. Further, the recombinant E. coli BL21 strain harbouring fusion plasmid successfully produced epi-cedrol in fermentation medium. The strain having fusion plasmid (pET32a-FPPS-ECS) produced 1.084 +/- 0.09 mg/L epi-cedrol, while the strain harbouring mixed plasmid (pRSETB-FPPS and pET28a-ECS) showed 1.002 +/- 0.07 mg/L titre in fermentation medium by overexpression and MEP pathway utilization. Structural analysis was done by I-TASSER server and docking was done by AutoDock Vina software, which suggested that secondary structure of the N- C terminal domain and their relative positions to functional domains of the fusion enzyme was greatly significant to the catalytic properties of the fusion enzymatic complex than individual enzymes.

Enhancing the device efficiency by filling the traps in photoanodes - Sudhakar, Vediappan; Krishnamoorthy, Kothandam (Journal of Materials Chemistry C, 2019)
Traps are ubiquitous in semiconductors and act as recombination sites. These recombination sites have a deleterious effect on the device efficiency. Thus, trap filling is used to increase the efficiency of devices. The traps are filled by dopants that either inject or extract electrons to/from the semiconductor. The trap-filled devices exhibit superior performance as compared to their unfilled counterparts. However, to date, this approach has not been explored in dye-sensitized solar cells despite the well-established presence of traps in them. The traps in the TiO2 photoanode are due to the presence of oxygen vacancies. Therefore, herein, we treated the photo anodes with hydrazine and filled the traps that increased all device metrics. Moreover, further sintering of the trap-filled photoanodes in the presence of hydrazine led to the formation of a nitrogen-doped photoanode. The device comprising a nitrogen-doped photoanode exhibited the efficiency increase of 23%. The detailed analysis of the device performance led to the conclusion that trap filling suppressed back electron transfer and increased the photo conversion efficiency.

Epoxidation of karanja (Millettia pinnata) oil methyl esters in the presence of hydrogen peroxide over a simple niobium-containing catalyst - Scotti, Nicola; Ravasio, Nicoletta; Evangelisti, Claudio; Psaro, Rinaldo; Penso, Michele; Niphadkar, Prashant S.; Bokade, Vijay V.; Guidotti, Matteo (Catalysts, 2019)
The synthesis, characterization and catalytic performance of a conceptually simple, novel NbOx-SiO2 catalyst are here described. The niobium(V)-silica catalyst was prepared starting from cheap and viable reactants, by alkaline deposition of NH4Nb(C2O4)(2)H2O in the presence of fructose as a stabilizer and subsequent calcination. The NbOx-SiO2 solid (0.95 Nb wt.%) was tested in the liquid-phase epoxidation with aqueous hydrogen peroxide of methyl oleate, as a model substrate. It was then tested in the epoxidation of a mixture of methyl esters (FAMEs) obtained by transesterification with methanol and purification of karanja oil, extracted from the autochthonous Indian variety of Millettia pinnata tree. The catalyst showed a promising performance in terms of methyl oleate conversion (up to 75%) and selectivity to epoxide (up to 82%). It was then tested on the FAME mixture from karanja oil, where interesting conversion values were attained (up to 70%), although with lower selectivities and yields to the mixture of desired epoxidized FAMEs. The solid withstood four catalytic cycles overall, during which a non-negligible surface reorganization of the Nb(V) sites was observed. However, this restructuring did not negatively affect the performance of the catalysts in terms of conversion or selectivity.
Keywords: epoxidation; fatty acid methyl esters; heterogeneous catalysis; Hydrogen peroxide; karanja oil; mesoporous silica catalyst; Millettia pinnata; niobium catalysts

Estrogen receptor activation in response to Azadirachtin A stimulates osteoblast differentiation and bone formation in mice - Kushwaha, Priyanka; Ahmad, Naseer; Dhar, V. Yogeshwar; Verma, Ashwni; Haldar, Saikat; Mulani, Fayaj A.; Trivedi, Prabodh K.; Mishra, Prabhat R.; Thulasiram, V. Hirekodathakallu; Trivedi, Ritu (Journal of Cellular Physiology, 2019)
The positive effectsof the sex hormone in sustaining bone homeostasis areexercised by maintaining the equilibrium betweencell activity and apoptosis. In this regard, the importance of estrogen receptors in maintaining the bone is that it is anattractive drug target,if devoid of known side effects. In this study, we show that a natural pure compound Azadirachtin A (Aza A) isolated from Azadirachta indica binds selectively to a site in the estrogen receptor, identifying itself to bea selective tissue modifier. Using computational and medicinal chemistry, we show that Aza A binds potentially and selectively to estrogen receptor-alpha (ER alpha) as compared with ER beta. This preferential binding of Aza A to ER alpha with good pharmacokinetic distribution in the body forms metabolites, showing that it is well absorbed. In in vivo estrogen deficiency models for osteoporosis, Aza A at a much lower dose enhances new bone formation at both sites of the trabecular and cortical bone with increased bone strength and presentswith no hyperplastic effect in the uterus.
Keywords: ALP; Gene expression; micro-CT; mineralization; osteoblast cells

Evidence of nitrite acting as a stable and robust inducer of non-cultivability in Mycobacterium tuberculosis with physiological relevance - Gample, Suwarna P.; Agrawal, Sonia; Sarkar, Dhiman (Scientific Reports, 2019)
Tuberculosis (TB) is the ninth leading cause of death worldwide, ranking above human immunodeficiency virus. Latency is the major obstacle in the eradication of this disease. How the physiology of the pathogen changes in transition to the latent stage needs to be understood. The latent bacteria extracted from animal hosts exist in a nonculturable (NC) phase, whereas bacteria extracted from most in vitro models are culture-positive. In the present study, we observed that nitrite, up to a concentration of 5 mM, shows the growth of Mycobacterium tuberculosis (MTB) in liquid media, but this effect starts reversing at higher concentrations. At a concentration of 10 mM, nitrite induces rapid nonculturability of MTB at the aerobic stage. This noncultivable dormancy was confirmed by analyzing the characteristics of NC bacteria. Further differential gene expression analyses clearly supported the formation of a dormancy phenotype. This study will be helpful for the use of this bacillus as a dormancy model in future studies on TB latency.

"EviMass": A literature evidence-based miner for human microbial associations - Srivastava, Divyanshu; Baksi, Krishanu D.; Kuntal, Bhusan K.; Mande, Sharmila S. (Frontiers in Genetics, 2019)
The importance of understanding microbe-microbe as well as microbe-disease associations is one of the key thrust areas in human microbiome research. High-throughput metagenomic and transcriptomic projects have fueled discovery of a number of new microbial associations. Consequently, a plethora of information is being added routinely to biomedical literature, thereby contributing toward enhancing our knowledge on microbial associations. In this communication, we present a tool called "EviMass" (Evidence based mining of human Microbial Associations), which can assist biologists to validate their predicted hypotheses from new microbiome studies. Users can interactively query the processed back-end database for microbe-microbe and disease-microbe associations. The EviMass tool can also be used to upload microbial association networks generated from a human "disease-control" microbiome study and validate the associations from biomedical literature. Additionally, a list of differentially abundant microbes for the corresponding disease can be queried in the tool for reported evidences. The results are presented as graphical plots, tabulated summary, and other evidence statistics. EviMass is a comprehensive platform and is expected to enable microbiome researchers not only in mining microbial associations, but also enriching a new research hypothesis. The tool is available free for academic use at https://web.rniapps.net/evimass.

Evolution of ZnO nanostructures as hexagonal disk: Implementation as photoanode material and efficiency enhancement in Al: ZnO based dye sensitized solar cells - Parra, Mohammad Ramzan; Pandey, Padmini; Siddiqui, Hafsa; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Haque, Fozia Z. (Applied Surface Science, 2019)
Hexagon shaped pristine and Al doped ZnO nanodisks (NDs) with exposed +/- [0001] polar facets were successfully synthesized using modified sol-gel method without the involvement of any structural directing or capping agents. It was investigated that OH- ions in mixed solvent system is responsible for pore formation and inhibit the growth of ZnO along the direction of c-axis leading to a high percentage exposure of active +/- [0001] polar facets and encourage the formation of ZnO NDs. Crystallographic analysis revealed that crystallite size and lattice constants are decreased, with the addition of Al3+ ions. The results obtained from Raman, and XPS analysis further corroborated with the XRD results, revealed the successful incorporation of Al3+ ions into ZnO lattice. Optical study revealed the band gap tunability with the incorporation of Al ion as dopant. Enhanced power conversion efficiency (PCE) of 1.96% (J(sc) similar to 7.69 +/- 0.23 mA/cm(2)) was observed for Al: ZnO hexagonal NDs based DSSC. The increased PCE in Al: ZnO based DSSC can be attributed to the higher inner surface area for dye anchoring by the interconnected network of the disk-like structure. The obtained results were satisfactory and most importantly the synthesis procedure proposed in present work is excellent for the synthesis of perfectly hexagonal shaped disks under precised synthesis parameters. The device interface study was further conducted using electrochemical impedance spectroscopy which revealed better charge transport process and charge storage ability with the incorporation of Al3+ ions into ZnO lattice.
Keywords: dye sensitized solar cells; Hexagonal disks; Sol-gel method; ZnO

Experimental and density functional theory investigations of catechol sensing properties of ZnO/RGO nanocomposites - Ponnusamy, Rajeswari; Venkatesan, Rajiu; Gangan, Abhijeet; Samal, Rutuparna; Chakraborty, Brahmananda; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2019)
Catechol, an essential industrial feedstock is one of the major environmental pollutant which causes several health issues including skin irritation, eye damage and genetic defects. In this work, we have investigated the catechol sensing performance of ZnO/RGO composites for its quantitative detection. ZnO/RGO composite showed superior electron transfer kinetics, sensitivity (162.04 mu A mM cm(-2)) and lower detection limit (47 nM) than that of bare ZnO nanoparticles. Further, the change in the zeta potential towards the lower negative demonstrated the strong electrostatic interaction between ZnO-RGO and catechol where it is converted as 1, 2 Benzoquinone through redox reactions. By using state of the art of Density Functional Theory simulations, we have demonstrated the interaction of catechol molecule on various ZnO clusters and RGO supported ZnO clusters. The strong bonding between p orbital of O atom of catechol and d orbital of Zn atom and its charge transfer facilitate the oxidation of catechol molecule. In the presence of RGO, the binding energy of catechol and charge transfer increases which qualitatively infer that RGO/ZnO exhibits higher sensitivity compared to bare ZnO and in consistency with the experimental observations.

Experimental and theoretical charge density, intermolecular interactions and electrostatic properties of metronidazole - Kalaiarasi, Chinnasamy; George, Christy; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Poomani, Kumaradhas (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2019)
Metronidazole is a radiosensitizer; it crystallizes in the monoclinic system with space group P2(1)/c. The crystal structure of metronidazole has been determined from high-resolution X-ray diffraction measurements at 90 K with a resolution of (sin 0/lambda) max = 1.12 angstrom(-1). To understand the charge-density distribution and the electrostatic properties of metronidazole, a multipole model refinement was carried out using the Hansen-Coppens multipole formalism. The topological analysis of the electron density of metronidazole was performed using Bader's quantum theory of atoms in molecules to determine the electron density and the Laplacian of the electron density at the bond critical point of the molecule. The experimental results have been compared with the corresponding periodic theoretical calculation performed at the B3LYP/6-31G** level using CRYSTAL09. The topological analysis reveals that the N-O and C-NO2 exhibit less electron density as well as negative Laplacian of electron density. The molecular packing of crystal is stabilized by weak and strong inter- and intramolecular hydrogen bonding and H center dot center dot center dot H interactions. The topological analysis of O-H center dot center dot center dot N, C-H center dot center dot center dot O and H center dot center dot center dot H intra- and intermolecular interactions was also carried out. The electrostatic potential of metronidazole, calculated from the experiment, predicts the possible electrophilic and nucleophilic sites of the molecule; notably, the hydroxyl and the nitro groups exhibit large electronegative regions. The results have been compared with the corresponding theoretical results.
Keywords: atomic valence index; Electron density; Electrostatic potential; intermolecular interactions; metronidazole; radiosensitizer

Experimental investigation of isothermal vapor-liquid equilibrium and estimation of excess thermodynamic properties (h(E)) of CHO2K-H2O from 278.15 to 423.15 K - Takalkar, Gorakshnath D.; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (Journal of Chemical and Engineering Data, 2019)
In this paper, vapor liquid equilibrium (VLE) of a binary mixture, potassium formate-water (CHO2K-H2O), was measured experimentally using a dynamic moving type VLE setup in the temperature range of 313.15 to 393.15 K. Overall, large vapor pressure data points generated for the mole fraction of CHO2K from 0.023 to 0.461 and the solution temperature up to 423.15 K were used to correlate the local composition-based activity coefficient model (NRTL model). The data obtained via the thermodynamic model fitting shows good agreement with the experimental VLE data with overall average relative deviation of 2.15% and root-mean-square deviation of 0.25%. The obtained results further indicate that the binary mixture exhibits a negative deviation from the Raoult's law, which is an important characteristic of the working fluid used for a heat-activated vapor absorption system (VAS). Therefore, the CHO2K-H2O mixture can be considered as an alternative working pair that will overcome the limitations allied to the crystallization and corrosion of the commercial working fluids mainly lithium bromide-water (LiBr-H2O). The fitted nonrandom two-liquid model was further utilized to determine the excess thermodynamic properties, solution enthalpy, solution entropy, and equilibrium P-T-x (Duhring) plot.

Experimental investigation on performance of helical spring lock washer under different operating conditions - Wagh, Hemant Krishnarao; Desale, Girish R. (Journal of Failure Analysis and Prevention, 2019)
In mechanical systems, emphasis has been given to the selection and health monitoring of both bolt and nut in the bolted joint assembly; less attention has been given to the performance of spring washers due to tightening torque, usage duration and reuse. In the present experimental investigation, the load–deflection characteristics of helical spring lock (HSL) washer during compressive loading and unloading are determined using newly designed and developed test rig. Also, the load–deflection characteristics of the HSL washers are examined for reuse cycles. Additionally, the effect of compressive loading and unloading on the reaction load within elastic limit is determined. Further, the loss of helix height due to compressive loading and its effect on strain energy is examined. The tests have evidenced of loss of helix height and strain energy of HSL washer due to compressive loading which deteriorates its functionality in further usage.

Exploring battery-type ZnO/ZnFe2O4 spheres-3D graphene electrodes for supercapacitor applications: advantage of yolk-shell over solid structures - Jhajharia, Suman Kumari; Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemElectroChem, 2019)
Recently, a ZnO/ZnFe2O4 composite has been reported to be a promising material for energy storage, owing to its large specific capacity and good redox activity. However, due to the inability to accommodate its strong volumetric variations during operation, it fails to retain its capacitance, which remains as a significant hitch. Herein, we present our attempt towards solving this through a binder-free electrode design comprising a porous yolk-shell ZnO/ZnFe2O4 composite matrixed inside a 3D network of graphene, which, in turn, is grown on Ni foam. The design exhibits a four-fold increase in its specific capacitance, yielding 1334 F g(-1) (specific capacity of 370.5 mAh g(-1)) at a current density of 0.5 A g(-1) in comparison to that of the ZnO/ZnFe2O4 electrodes (309 F g(-1) (85.8 mAh g(-1)) at 0.5 A g(-1)) comprising solid metal oxide spheres. The major advantage of the design is the well-defined yolk-shell architecture that provides free space for volume expansion during long cycling processes and channels for ionic transportation; whereas, the conductive 3D graphene network and porous Ni foam facilitate electronic conduction. The availability of free space in yolk-shell sphere electrodes facilitates the capacitance retention of up to 80 % beyond 5000 cycles at a current density of 1 A g(-1), which is in contrast to the capacitance retained by the solid spheres of only approximately 60 %. These results directly demonstrate the significant consequence of the yolk-shell architecture-based binder-free design and its promising potential in high-performing supercapacitors and batteries.
Keywords: binder-free electrodes; graphene hydrogels; Supercapacitors; volume expansion; yolk-shell spheres

Exploring energy profiles of protein-protein interactions (PPIs) Using DFT method - Bapat, Sanket; Vyas, Renu; Karthikeyan, Muthukumarasamy (Letters in Drug Design & Discovery, 2019)
Background: Large-scale energy landscape characterization of protein-protein interactions (PPIs) is important to understand the interaction mechanism and protein-protein docking methods. The experimental methods for detecting energy landscapes are tedious and the existing computational methods require longer simulation time. Objective: The objective of the present work is to ascertain the energy profiles at the interface regions in a rapid manner to analyze the energy landscape of protein-protein interactions Methods: The atomic coordinates obtained from the X-ray and NMR spectroscopy data are considered as inputs to compute cumulative energy profiles for experimentally validated protein-protein complexes. The energies computed by the program were comparable to the standard molecular dynamics simulations. Results: The PPI Profiler not only enables rapid generation of energy profiles but also facilitates the detection of hot spot residue atoms involved therein. Conclusion: The hotspot residues and their computed energies matched with the experimentally determined hot spot residues and their energies which correlated well by employing the MM/GBSA method. The proposed method can be employed to scan entire proteomes across species at an atomic level to study the key PPI interactions.

Exploring notch pathway to elucidate phenotypic plasticity and intra-tumor heterogeneity in gliomas - Chowdhury, Saikat; Sarkar, Ram Rup (Scientific Reports, 2019)
The phenotypic plasticity and self-renewal of adult neural (aNSCs) and glioblastoma stem cells (GSCs) are both known to be governed by active Notch pathway. During development, GSCs can establish differential hierarchy to produce heterogeneous groups of tumor cells belong to different grades, which makes the tumor ecosystem more complex. However, the molecular events regulating these entire processes are unknown hitherto. In this work, based on the mechanistic regulations of Notch pathway activities, a novel computational framework is introduced to inspect the intra-cellular reactions behind the development of normal and tumorigenic cells from aNSCs and GSCs, respectively. The developmental dynamics of aNSCs/GSCs are successfully simulated and molecular activities regulating the phenotypic plasticity and self-renewal processes in normal and tumor cells are identified. A novel scoring parameter ``Activity Ratio'' score is introduced to find out driver molecules responsible for the phenotypic plasticity and development of different grades of tumor. A new quantitative method is also developed to predict the future risk of Glioblastoma tumor of an individual with appropriate grade by using the transcriptomics profile of that individual as input. Also, a novel technique is introduced to screen and rank the potential drug-targets for suppressing the growth and differentiation of tumor cells.

Exploring the potential of Desmodium gangeticum (L.) DC. extract against spatial memory deficit in rats - Changdar, Nilanjan; Ganjhu, Rajesh Kumar; Rijal, Samita; Kumar, Ayush; Mallik, Shanchari Basu; Nampoothiri, Madhavan; Shenoy, Rekha R.; Sonawane, Kiran B.; Rao, Mallikarjuna C.; Mudgal, Jayesh (Pharmacognosy Magazine, 2019)
Background: A few published reports demonstrated the neuroprotective effect of Desmodium gangeticum (L.) DC. in an acute model of dementia. Objective: The purpose of the present study was to evaluate the preclinical efficacy of D. gangeticum against chronic dementia when administered prophylactically. Materials and Methods: Chronic spatial memory deficit was induced in rats by aluminum chloride (AlCl3, 10 mg/kg, i.p.). Treatment with hydroalcoholic whole plant extract of D. gangeticum (DG extract) was initiated 2 week before AlCl3 challenge and continued till the 51(st) day after the challenge, orally at the dose of 400 mg/kg/day. The spatial memory was assessed by Morris water maze test. Hippocampal and frontal cortex acetyl cholinesterase (AChE) and oxidative stress were assessed in diseased rat brains. Results: Chronic administration of AlCl3 produced spatial memory deficit in rats. Memory impairment was manifested in rats as an increase in escape latency and D-quadrant latency whereas a decrease in total time spent in D-quadrant. These behavioral alterations were reversed significantly by the treatment with DG extract. In addition, DG extract significantly increased the island time, indicating memory improvement. DG extract corrected the declined AChE in frontal cortex and altered frontal cortex/hippocampus catalase activity. Phytochemical investigation of the DG extract revealed large content of saponins among the other phytochemicals such as tannins, alkaloids, and flavonoids. Conclusion: These results indicate the possible prophylactic potential of saponin-rich DG extract against chronic memory deficit in rats.
Keywords: Acetyl cholinesterase; Aluminum chloride; dementia; Desmodium gangeticum (L) DC; Oxidative stress

Exploring the steady operation of a continuous pilot plant for the di-nitration reaction - Sharma, Mrityunjay; Acharya, Roopashree B.; Kulkarni, Amol A (Chemical Engineering & Technology, 2019)
Continuous-flow synthesis of the selective herbicide pendimethalin was demonstrated in both a laboratory-scale and a pilot-scale reactor using only concentrated nitric acid as nitrating agent. The di-nitration reaction follows second-order kinetics where the reaction is first order with respect to both reactant and nitric acid. The pinched-tube reactor was chosen for pilot-scale reactor fabrication due to its excellent mixing and mass transfer characteristics compared to a straight-tube reactor. The estimated mass transfer coefficient showed similar nature in the laboratory-scale and the pilot-scale pinched-tube reactor, ensuring similar performance at the pilot scale. Di-nitration in continuous flow, inline quenching, extraction, and phase separation are some of the salient features of the developed pilot plant. The importance of the start-up time for achieving steady state in the flow system at the large scale is highlighted.

External oxidant-dependent reactivity switch in copper-mediated intramolecular carboamination of alkynes: access to a different class of fluorescent ionic nitrogen-doped polycyclic aromatic hydrocarbons - Shaikh, Aslam C.; Banerjee, Somsuvra; Mule, Ravindra D.; Bera, Saibal; Patil, Nitin T. (Journal of Organic Chemistry, 2019)
An interesting case of external oxidant-controlled reactivity switch leading to a divergent set of ionic nitrogen-doped polycyclic aromatic hydrocarbons (N-doped PAHs), is presented here, which is quite unrecognized in copper-mediated reactions. In the current scenario, from the same pyridino-alkyne substrates, the use of the external oxidant Ph1(0Ac)2, in combination with Cu(OTf)(2), gave N-doped spiro-PAHs via a dearomative 1,2-carboamination process; whereas, without the use of oxidant, an alkyne/azadiene [4 + 2]-cycloaddition cascade occurred to exclusively afford ionic N-doped PAHs. These newly synthesized N-doped PAHs further exhibit tunable emissions, as well as excellent quantum efficiencies.

Early metastable assembly during the stress-induced formation of worm-like amyloid fibrils of nucleic acid binding domains of TDP-43 - Pillai, Meenakshi; Jha, Santosh Kumar (Biochemistry, 2020)
TDP-43 protein travels between the cytosol and the nucleus to perform its nucleic acid binding functions through its two tandem RNA recognition motif domains (TDP-43(tRRM)). When exposed to various environmental stresses, it forms abnormal aggregates in the cytosol of neurons, which are the hallmarks of amyotrophic lateral sclerosis and other TDP-43 proteinopathies. However, the nature of early structural changes upon stress sensing and the consequent steps during the course of aggregation are not well understood. In this study, we show that under low-pH conditions, mimicking starvation stress, TDP-43(tRRm) undergoes a conformational opening reaction linked to the protonation of buried ionizable residues and grows into a metastable oligomeric assembly (called the ``low-pH form'' or the ``L form''). In the L form, the protein molecules have disrupted tertiary structure, solvent-exposed hydrophobic patches, and mobile side chains but the native-like secondary structure remains intact. The L form structure is held by weak interactions and has a steep dependence on ionic strength. In the presence of as little as 15 mM KCl, it fully misfolds and further oligomerizes to form a beta-sheet rich ``beta form'' in at least two distinct steps. The beta form has an ordered, stable structure that resembles worm-like amyloid fibrils. The unstructured regions of the protein gain structure during L (sic) beta conversion. Our results suggest that TDP-43(tRRm) could function as a stress sensor and support a recent model in which stress sensing during neurodegeneration occurs by assembly of proteins into metastable assemblies that are precursors to the solid aggregates.

Effect of aromatic rings and substituent on the performance of lithium batteries with rylene imide cathodes - Aher, Jagdish; Graefenstein, Alexander; Deshmukh, Gunvant; Subramani, Kumar; Krueger, Bastian; Haensch, Mareike; Schwenzel, Julian; Krishnamoorthy, Kothandam; Wittstock, Gunther (ChemElectroChem, 2020)
Rylene imides (RIs) are attractive organic battery materials because of the inherent modularity of the molecules. While strong aggregation of RIs is disadvantageous for fast lithium-ion transport in the organic active material, decreasing the solubility of the RIs in battery electrolytes is essential to avoid performance fading. Therefore, the design and synthesis of RIs for lithium batteries is a non-trivial task that must, among other considerations, balance lithium-ion transport in the solid material vs. low solubility by controlling aggregation and packing. We have chosen triphenylamine (TPA) as a substituent which disrupts the aggregation but maintains a low solubility due to increased aromaticity of TPA. We have synthesized three RIs with one, two, and four aromatic units in the core. All of them showed stable specific capacity over 300 charge-discharge cycles. The batteries also showed specific capacities close to their theoretical capacities with 97-99 % coulombic efficiency. The maximum specific energy and specific power were 197 mWh g(-1) and 37 mW g(-1), respectively.
Keywords: lithium-ion batteries; organic cathode material; rylene imides; solubility; triphenylamine

Effect of bio-filler on hybrid sisal-banana-kenaf-flax based epoxy composites: a statistical correlation on flexural strength - Vivek, Somasundaram; Kanthavel, Karuppusamy; Torris, Arun; Kavimani, Vijayananth (Journal of Bionic Engineering, 2020)
This work deals with the investigation of the synergistic effect of bagasse ash with sisal-banana-kenaf-flax fibers reinforced epoxy composite for their flexural behavior. The composites with three combinations of hybrid fibers viz. sisal/kenaf (HSK), banana/kenaf (HBK), and banana/flax (HBF) with bagasse ash (BGA) as filler material are fabricated using vacuum bag assisted resin transfer molding. Experiments were conducted based on L27 orthogonal array to understand the influence of control factor viz. fiber volume, alkali concentration & BGA over output response.X-ray micro computed tomography analysis was conducted over the developed sample to infer the uniform dispersion of fiber and filler material. The experimental results reveal that the addition of fiber up to 30 vol% depicts better strength and further addition results in a negative impact. Increasing in order of BGA decreases the flexural strength of the developed composites.
Keywords: bagasse ash; flexural strength; natural fiber; vacuum bag assisted resin transfer molding; X-ray micro computed tomography

Effect of melatonin on tau aggregation and tau-mediated cell surface morphology - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Aggregation of Microtubule-associated protein Tau and its deposition in the form of neurofibrillary tangles (NFTs) is one of the pathological hallmarks of Alzheimer's disease (AD). Tau aggregation inhibition has been targeted in various studies including natural compounds and synthetic small molecules. Here, we have studied neurohormone- Melatonin against in vitro Tau aggregation and observed its effect on membrane topology, tubulin network and Tau phosphorylation in Neuro2A and N9 cell lines. The aggregation and conformation of Tau was determined by ThT fluorescence and CD spectroscopy respectively. The morphology of Tau aggregates in presence and absence of Melatonin was studied by transmission electron microscopy. Melatonin was found to reduce the formation of higher order oligomeric structures without affecting the overall aggregation kinetics of Tau. Melatonin also modulates and helps to maintain membrane morphology, independent on tubulin network as evidenced by FE-SEM and immunofluorescence analysis. Overall, Melatonin administration shows mild anti-aggregation and cytoprotective effects. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cell surface morphology; melatonin; Paired helical filaments; tau protein; Tauopathies

Effect of physical properties of dispersed phase on the residence time distribution in straight capillaries - Raval, Joy; Suryawanshi, Nalinee B.; Kulkarni, Amol A. (Chemical Engineering Science, 2020)

Effect of solvent-substrate noncovalent interactions on the diastereoselectivity in the intramolecular carbonyl-ene and the staudinger [2+2] cycloaddition reactions - Jain, Shailja; Vanka, Kumar (Journal of Physical Chemistry A, 2020)
Noncovalent interactions (NCIs) have been identified as important contributing factors for determining selectivity in organic transformations. However, cases where NCIs between solvents and substrates are responsible for a major extent for determining selectivity are rare. The current computational study with density functional theory identifies two important transformations where this is the case: the intramolecular carbonyl-ene reaction and the Staudinger [2 + 2] cycloaddition reaction. In both cases, the role of explicit solvent molecules interacting non-covalently with the substrate has been taken into account. Calculations indicate that the diastereomeric ratio would be 95.0:5.0 for the formation of tricyclic tetrahydrofuran diastereomers via the intramolecular carbonyl-ene reaction and 94.0:6.0 for the formation of the triflone diastereomers via the Staudinger [2 + 2] cycloaddition reaction, which corroborates with the experiment. Interestingly, in both the cases, the calculations indicate that noninclusion of explicit solvent molecules would lead to only a small difference between the competing transition states, which leads to the conclusion that solvent-substrate NCIs are the major cause for diastereoselectivity in both the cases considered.

Effect of substituent of roof shape amines on the molecular recognition of optically active acids by NMR spectroscopy - Gupta, Riddhi; Gonnade, Rajesh G.; Bedekar, Ashutosh V. (ChemistrySelect, 2020)
Optically active roof shape derivatives of benzyl amines were synthesized and screened as chiral solvating agents for the study of molecular recognition of chiral compounds by NMR and UV spectroscopy. The effect of substituents on the aromatic ring of benzyl unit is investigated to assess the binding ability with the analyte and an experimental correlation is observed. Altering the substituents on the ring of benzyl amine and the acidic substrates, significantly influence the CSA interactions. The supramolecular interactions between acid and amine in the single crystal X-ray analysis of the diastereomeric salts provide further insight of the mode of molecular recognition.
Keywords: Chiral Solvating Agents; molecular recognition; NMR spectroscopy; Roof Shape Amine; UV spectroscopy

Effect of tert-alcohol functional imidazolium salts on oligomerization and fibrillization of amyloid beta (1-42) peptide - Said, Madhukar S.; Navale, Govinda R.; Yadav, Ashok; Khonde, Nilesh; Shinde, Sandip S.; Jha, Anjali (Biophysical Chemistry, 2020)
Imidazolium based IL's has gained vast interest in developing biological applications. Oligomerization and fibrillization of amyloid beta (1-42) peptide are mainly responsible for the extra-neuronal deposition of amyloid fibrils in neurodegenerative disorders like Alzheimer's disease (AD). Here, we report an effect of tert-BuOH-functional imidazolium ILs on oligomerization and fibrillization of amyloid beta (1-42) Peptide in vitro. In this study, a series of these [alkyl-(t)OHim][OMs] ILs with methyl sulphonate counter anion by varying alkyl chains were used. Among the seven protic ILs, four showed strong binding and inhibition activity for the formation of amyloid beta (1-42) aggregation by using Thioflavin T fluorescence binding assay. The secondary structural analysis of the peptide, pre-incubated with active ILs shows the loss of ordered beta-sheet amyloid structure. The longer alkyl chain ILs showed that an increased in amyloid binding and hence an inhibition effect on amyloid aggregation was enhanced. Thus, we propose that ILs could be presented as potential candidates for therapeutic intervention against Alzheimer's disease (AD).
Keywords: Aggregation; Amyloid beta (1-42) peptide; Biofilm inhibitor; Imidazolium ionic liquid

Efficacy of clay catalysts for the dehydration of fructose to 5-hydroxymethyl furfural in biphasic medium - Lucas, Nishita; Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana (Journal of Porous Materials, 2020)
5-Hydroxymethyl furfural (HMF) is one of the important platform chemical obtained from C6 sugars derived from biomass. The efficiency of montmorillonite clay catalysts (K-10, K-20, K-30, and Al pillared clay) has been systematically explored for the synthesis of HMF through dehydration of fructose in a biphasic solvent system. The catalysts were characterized by XRD, N(2)sorption,Al-27 MAS NMR,Si-29 NMR and FT-IR of chemisorbed pyridine. Acid treated K-10 catalyst was found to be the best among the clay catalysts tested. Various reaction parameters such as reaction temperature, catalyst content, solvent were optimized for achieving better yield of HMF. Under optimized reaction conditions, K-10 catalyst affords 80 mol% fructose conversion with HMF yield of 61 mol%. Insight into the type of acid sites essential for such cascade reactions has been furnished. Utilization of clay catalysts for HMF production will be beneficial to improve overall economics for the production of platform chemicals like HMF from biomass-derived raw materials.
Keywords: 5-hydroxymethyl furfural; Acidity; Clays; fructose; Insights

Efficacy of octahedral molecular sieves for green and sustainable catalytic reactions - Lucas, Nishita; Gurrala, Lakshmiprasad; Halligudi, S. B. (Molecular Catalysis, 2020)
Sustainability and Green Chemistry has emerged as catchphrase in modern era and researchers worldwide have embraced it as new paradigm of development. In this context identifying potential materials able to curb multiple grave issues thus contributing towards sustainability is vital. Catalytic materials are quite potent for addressing current social, economic and environmental problems like harnessing alternative energy source, pollution prevention/remediation and manufacturing of commodity chemicals. Thus, the present review accentuates the efficacy of porous octahedral molecular sieves (OMS) as catalyst for such environmentally important reactions. It discusses about structural importance of OMS and their applications for green and sustainable catalytic reactions. Finally, the limitations are highlighted and future perspectives are presented which will ameliorate its catalytic utilization in energy and environmental domains.
Keywords: catalytic transformations; Lignocellulosic biomass; octahedral molecular sieves; platform chemicals; renewable feedstock

Efficient method for the synthesis of quinoxaline derivatives catalyzed by titanium silicate-1 - Chandrachood, Pranav S.; Jadhav, Amol R.; Garud, Dinesh R.; Deshpande, Nirmala R.; Puranik, Vedavati G.; Kashalkar, Rajashree V. (Research on Chemical Intermediates, 2020)
A series of quinoxaline derivatives were efficiently synthesized by convenient and simple procedure in excellent yields using 1 wt.% of titanium silicate (TS-1) catalyzed reaction of 1,2-diamines and 1,2-diketones in methanol at room temperature. This reaction is scalable to multigram scale and the catalyst is recyclable. [GRAPHICS] .
Keywords: 2-Diketones; Aromatic 1; o-Phenylenediamine; Quinoxaline; Room temperature; Titanium silicate-1

Efficient processing of reactions involving diazonium salts: meerwein arylation in an impinging-jet reactor - Shukla, Chinmay A.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Organic Process Research & Development, 2020)
This work reports a novel approach for performing high-throughput synthesis of Meerwein arylation in an impingingjet reactor. The multistep reaction was performed in a single reactor via in situ diazonium salt generation followed by Meerwein arylation. The work involves many iterations between experiments and simulations (where we integrate simulating the flow, heat transfer, and reaction simultaneously) for optimization of conditions in an inverted impinging-jet reactor. The effect of design variables viz. catalyst concentration, inlet temperature, and monomer mole ratio on the yield of the desired product was studied in detail, and the simulation results were used to plan the continuous experiments. An infrared camera was used to monitor the transient reactor temperature for steady-state analysis. The lab-scale inverted impinging-jet reactor with over 93% isolated yield can offer a space-time yield of 277.78 tons/m(3)/day. The numbering-up of an inverted impinging-jet reactor can be an effective way for cleaner production of products through typical Meerwein arylation.
Keywords: computational fluid dynamics; high throughput synthesis; impinging-jet reactor; IR camera; Meerwein arylation; Numbering-up

Efficient synthesis of gamma-valerolactone-a potential fuel from biomass derived levulinic acid using catalytic transfer hydrogenation over Hf@CCSO3H catalyst - Jori, Popat K.; Jadhav, Vrushali H. (Catalysis Letters, 2020)
A new hafnium based carbonaceous catalyst (Hf@CCSO3H) was prepared by simultaneous carbonization and sulfonation of readily available glucose, followed by incorporation of hafnium metal on the surface of catalyst. The catalyst was well characterized using FT-IR, PXRD, EDX, SEM, C-13 CPNMR, XPS and BET analysis. The catalytic activity of Hf@CCSO3H was evaluated for synthesis of gamma-valerolactone-a potential fuel and green solvent. gamma-valerolactone was synthesized from biomass derived levulinic acid by catalytic transfer hydrogenation using 150 wt% of catalyst at 200 celcius for 24 h in isopropanol solvent as a hydrogen donor. 100% conversion of levulinic acid was achieved with an excellent yield of 96% with more than 99% selectivity of gamma-valerolactone as evident from GC analysis. The method developed is simple, efficient and economical. [GRAPHICS] .
Keywords: gamma-Valerolactone; Hydrogenation; levulinic acid; Transfer

EGCG impedes human Tau aggregation and interacts with Tau - Sonawane, Shweta Kishor; Chidambaram, Hariharakrishnan; Boral, Debjyoti; Gorantla, Nalini Vijay; Balmik, Abhishek Ankur; Dangi, Abha; Ramasamy, Sureshkumar; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Tau has not been fully explored. By various biophysical and biochemical analyses like ThS fluorescence assay, MALDI-TOF analysis and Isothermal Titration Calorimetry, we demonstrate dual effect of EGCG on aggregation inhibition and disassembly of full-length Tau and their binding affinity. The IC50 for Tau aggregation by EGCG was found to be 64.2 mu M.

Electrochemical evaluation of the stability and capacity of r-GO-wrapped copper antimony chalcogenide anode for Li-ion battery - Yadav, Poonam; Sharma, Neha; Patrike, Apurva; Sabri, Ylias M.; Jones, Lathe A.; Shelke, V. Manjusha (ChemElectroChem, 2020)
Poor cycling stability and capacity fade are primary concerns for next-generation anode materials for Li-ion batteries. In non-carbonaceous anode materials, alloying with Li leads to volume increase that affects practical applications, and increase in particle size, amorphization and reduced conductivity can all lead to a loss of performance. In this work, binary antimony sulfide (Sb2S3) and ternary copper antimony sulfide (CuSbS2) are synthesized by a convenient solvothermal process. These materials are used to study the Li-active/inactive concept, by incorporating Cu into Sb(2)S(3)forming CuSbS(2)wherein Cu is Li inactive whereas Sb is Li active. By direct comparison, we have shown that incorporating Cu into binary antimony sulfide (Sb2S3) resulting into ternary copper antimony sulfide (CuSbS2) addresses the problem of poor conductivity and capacity loss, as Cu provides conductivity leading to enhanced charge transfer and prevents Sb particle aggregation while charge-discharge by exhibiting spectator or diluent ion effect. The better performance of CuSbS(2)is associated with the better Li(+)ion diffusion in the CuSbS2(D=8.97x10(-15) cm(2) s(-1)) compared to Sb2S3(D=2.76x10(-15) cm(2) s(-1)) and lower series resistance of CuSbS2(R=4.70x10(5) omega) compared to Sb2S3(R=5.81x10(8) omega). We have also investigated the composite with the addition of rGO. The CuSbS2-rGO delivered a reversible capacity of 672 mAh g(-1)after 1000 cycles at 200 mA g(-1)which has shown best performance.
Keywords: Batteries; chalcogenides; Diffusion coefficient; lithium; Ternary sulfides

Electrochemical performance of pre-lithiated ZnMoO4 and r-GO@ZnMoO4 composite anode for lithium-ion battery application - Bin Masood, Khalid; Parte, Golu; Jain, Neha; Dwivedi, Pravin K.; Kumar, Pushpendra; Shelke, V, Manjusha; Patel, Rp; Singh, Jai (Journal of the Taiwan Institute of Chemical Engineers, 2020)
Exploring a safer replacement of Li metal anode is crucial for technological, and fundamental importance. Li-metal is a preferred choice as anode material for lithium-ion battery (LIB) applications. However, parasitic dendritic growth on the Li metal surface during cycling causes instability and safety dreads. In the present study, we have investigated that the pre-lithiated ZnMoO4 is superior to its carbon-based counterparts (r-GO@ZnMoO4), moreover safer and sustainable than Li metal anode. The pre-lithiated ZnMoO4 delivers a better reversible capacity (similar to 1000 mAhg(-1) at 0.1 Ag-1), superior rate capability (similar to 400 mAh g(-1) at 2 Ag-1), and excellent cycling stability over 300 cycles at 0.1 Ag-1, as compared to bare ZnMoO4 and r-GO@ZnMoO4 composite. The present investigation is an attempt to provide a substitute for commonly used Li-metal/carbon anodes with better performance. (C) 2020 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Cycling stability; Electrochemistry; Li-ion battery; Nyquist plot; Rate performance; ZnMoO4 nanocomposites

Electronic structure evolution of Pd@Co nanocatalysts under oxidation and reduction conditions and preferential CO oxidation - Jain, Ruchi; Gopinath, Chinnakonda S. (ChemCatChem, 2020)
Herein, we present the surface electronic structure and morphological evolution under reduction and oxidation conditions for Pd@Co (PC) core-shell nanoparticles with different Pd : Co ratio (PC=2 : 1, 1 : 1 and 1 : 2). Extensive measurements have been made with NAPXPS (near ambient pressure x-ray photoelectron spectroscopy) under oxidising and reducing conditions, and ex-situ HRTEM. It has been demonstrated that PC catalysts are thermally stable towards morphological changes, at least up to 575 K. Nonetheless, it shows a significant surface electronic structure changes under reaction environments, which are highly relevant to heterogeneous catalysis. As expected, high (low) population of metallic (oxidised) Co was observed, while retaining core shell structure under reduction (H(2)and vacuum annealing) environment. Interestingly, the Pd-Co metallic interface helps to overcome the pyrophoric nature of cobalt and stabilised a significant amount of metallic Co at Pd-Co interface even in the presence of 0.1 mbar O(2)up to 575 K. The presence of Pd-Co and Pd-Co@Co(3)O(4)interfaces in reaction environment makes the catalyst dual functional. The proof of concept has been explored in terms of oxidation of CO in the presence of H(2)or O-2.
Keywords: Core-Shell morphology; Electronic Structure; heterogeneous catalysis; interface; XPS

Electronic structure parameter of nuclear magnetic quadrupole moment interaction in metal monofluorides - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2020)
The electronic structure parameter (W-M) of the nuclear magnetic quadrupole moment (MQM) interaction in numerous open-shell metal monofluorides (viz., MgF, CaF, SrF, BaF, RaF, and PbF) is computed in the fully relativistic coupled-cluster framework. The electron-correlation effects are found to be very important for the precise calculation of W-M in the studied molecular systems. The molecular MQM interaction parameter scales nearly as Z(2) in the alkaline earth metal monofluorides, where Z is the nuclear charge of metal. Our study identifies (RaF)-Ra-223 as a good candidate for the experimental search of the nuclear MQM, which can help unravel the physics beyond the standard model in the hadron sector of matter.

Electrospun fibers and sorbents as a possible basis for effective composite wound dressings - Saul Alvarez-Suarez, Alan; Dastager, Syed G.; Bogdanchikova, Nina; Grande, Daniel; Pestryakov, Alexey; Carlos Garcia-Ramos, Juan; Lizeth Perez-Gonzalez, Graciela; Juarez-Moreno, Karla; Toledano-Magana, Yanis; Smolentseva, Elena; Antonio Paz-Gonzalez, Juan; Popova, Tatiana; et al. (Micromachines, 2020)
Skin burns and ulcers are considered hard-to-heal wounds due to their high infection risk. For this reason, designing new options for wound dressings is a growing need. The objective of this work is to investigate the properties of poly (epsilon-caprolactone)/poly (vinyl-pyrrolidone) (PCL/PVP) microfibers produced via electrospinning along with sorbents loaded with Argovit (TM) silver nanoparticles (Ag-Si/Al2O3) as constituent components for composite wound dressings. The physicochemical properties of the fibers and sorbents were characterized using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and inductively coupled plasma optical emission spectroscopy (ICP-OES). The mechanical properties of the fibers were also evaluated. The results of this work showed that the tested fibrous scaffolds have melting temperatures suitable for wound dressings design (58-60 degrees C). In addition, they demonstrated to be stable even after seven days in physiological solution, showing no macroscopic damage due to PVP release at the microscopic scale. Pelletized sorbents with the higher particle size demonstrated to have the best water uptake capabilities. Both, fibers and sorbents showed antimicrobial activity against Gram-negative bacteria Pseudomona aeruginosa and Escherichia coli, Gram-positive Staphylococcus aureus and the fungus Candida albicans. The best physicochemical properties were obtained with a scaffold produced with a PCL/PVP ratio of 85:15, this polymeric scaffold demonstrated the most antimicrobial activity without affecting the cell viability of human fibroblast. Pelletized Ag/Si-Al2O3-3 sorbent possessed the best water uptake capability and the higher antimicrobial activity, over time between all the sorbents tested. The combination of PCL/PVP 85:15 microfibers with the chosen Ag/Si-Al2O3-3 sorbent will be used in the following work for creation of wound dressings possessing exudate retention, biocompatibility and antimicrobial activity.
Keywords: electrospinning; poly (epsilon-caprolactone); poly (vinyl pyrrolidone); silver sorbents; wound dressings

Electrospun nanofibers of Tin phosphide (SnP0.94) nanoparticles encapsulated in a carbon matrix: a tunable conversion-cum-alloying lithium storage anode - Yadav, Poonam; Malik, Wahid; Dwivedi, Pravin Kumari; Jones, Lathe A.; Shelke, Manjusha V. (Energy & Fuels, 2020)
Anodes with improved Li storage capability are required for next-generation lithium batteries. In this work we report a convenient synthesis strategy, based on electrospinning followed by reduction and phosphorization, to prepare a tin phosphide (SnP0.94) phase in a carbon nanofiber matrix. The layered structure offered by the SnP0.94 phase, along with its small size (5-20 nm) encapsulated in the conducting carbon matrix, leads to promising electrochemical Li storage characteristics. This composite has a capacity of 750 mAh g(-1) at 100 mA g(-1) with good cycling and rate stability. Electrochemical studies revealed a faster diffusion coefficient (1.86 x 10(-11) cm(2) s(-1)) for Li in the composite compared to the bare SnP0.94 (8.57 x 10(-14) cm(2) s(-1)), confirming the promise of this class of materials for cation storage in battery anodes.

Electrospun poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/polyethylene oxide (PEO) microfibers reinforced with ZnO nanocrystals for antibacterial and antibiofilm wound dressing applications - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Patel, Pratikshkumar R.; Dhanavade, Maruti J.; Badiger, V. Manohar; Marathe, Yogesh N.; Bohara, Raghvendra A. (New Journal of Chemistry, 2020)
Biocompatible and biodegradable polymers are extensively used in designing wound dressing materials. The present investigation deals with the preparation of a unique blend of zinc oxide (ZnO) nanoparticles incorporated in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)/polyethylene oxide (PEO) microfibersviaan electrospinning technique for antibacterial, antibiofilm and wound dressing applications. This composite was prepared by incorporating previously synthesized ZnO NPs with better antibacterial and antibiofilm activity in PHBV-PEO (4 : 1) polymers in chloroform solution. Scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy confirmed that ZnO NPs were incorporated in the PHBV-PEO microfibers. The synthesized microfibers exhibited enhanced mechanical properties after the incorporation of ZnO NPs. The results of antibacterial and antibiofilm activity of the prepared microfibers revealed that the incorporated ZnO NPs in different concentrations (1%, 3%, and 5%) showed different degrees of antibacterial activity against pathogenic Gram-positiveStaphylococcus aureus(NCIM 2654) and Gram-negativePseudomonas aeruginosa(NCIM 5032), which are the main bacteria found in wound infections. The PHBV-PEO-ZnO microfibers exhibited excellent hemocompatibility with improved swelling behavior after the incorporation of ZnO NPs.In vitrocytotoxicity assays revealed the non-toxic nature of the prepared PHBV-PEO-ZnO microfibers. The current work confirms that utilizing a unique blend of the biodegradable, biocompatible, thermoplastic and hydrophobic natural polymer PHBV with hydrophobic, biodegradable, non-toxic and synthetic polymer PEO with ZnO NPs holds great potential for use as an antibacterial and antibiofilm material for wound dressing applications.

Electrostatic manifestation of micro-heterogeneous solvation structures in deep-eutectic solvents: a spectroscopic approach - Chatterjee, Srijan; Haldar, Tapas; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
Deep eutectic solvents have emerged as inexpensive green alternatives to conventional solvents for diverse applications in chemistry and biology. Despite their importance as useful media in various applications, little is known about the microscopic solvation structures of deep eutectic solvents around solutes. Herein, we show that the electrostatic field, which can be estimated both from infrared experiments and theory, can act as a unified concept to report on the microscopic heterogeneous solvation of deep eutectic solvents. Using a fluorophore containing the carbonyl moiety as the solute and the electrostatic field as a descriptor of the solvation structure of the deep eutectic solvents, we report the residue-specific distribution, orientation, and hydrogen bonding in deep eutectic solvents constituting of choline chloride and alcohols of varying chain-lengths. We observe that an increase in alcohol chain-length not only affects the alcohol's propensity to form hydrogen bond to the solute but also alters the spatial arrangement of choline cations around the solute, thereby leading to a microheterogeneity in the solvation structure. Moreover, to extend our electrostatic field based strategy to other deep eutectic solvents, we report an emission spectroscopy based method. We show that this method can be applied, in general, to all deep eutectic solvents, irrespective of their constituents. Overall, this work integrates experiments with molecular dynamics simulations to provide insights into the heterogeneous DES solvation.

Elucidating the effect of CaF 2 on structure, biocompatibility and antibacterial properties of S53P4 glass - Prasad, Sakthi; Ganisetti, Sudheer; Jana, Anuradha; Kant, Shashi; Sinha, P. K.; Tripathy, Sucheta; Illath, Kavya; Ajithkumar, T. G.; Annapurna, K.; Allu, Amarnath R.; Biswas, Kaushik (Journal of Alloys and Compounds, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The present work focuses on the synthesis and structural elucidation of fluoride containing bioactive glasses in the system (in mol%) given by (53.86) SiO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> – (22.65) Na<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O – (21.77-x) CaO – (1.72) P<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> – x CaF<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, where, x = 0, 5.44, 10.885 and 16.33. The role of the incorporated fluoride and its distribution within the glass were interpreted and analyzed using Molecular dynamics (MD) simulations and the results were compared with the modified random network (MRN) model. The interpretations from the model have been verified using the MAS-NMR spectroscopy technique. According to this model, fluoride containing bioactive glasses have been proposed to consist of silicate rich network regions and modifier cation – fluoride rich inter-network regions. The interface region was found to consist of non-bridging oxygen species (NBO) and phosphate cations which are either isolated orthophosphates (<em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Q<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">0<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">P<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) or bridged with silicates in the form of pyrophosphate (<em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Q<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">1<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">P<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) units forming Si–O–P bonds. The gradual substitution of CaF<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> for CaO in the base glass resulted in an increase in the silicate network connectivity with a reduction in the NBOs and lead to an increase in the association of modifier cations with fluoride ions. However, fluoride ions were found to show a marginal preference to associate with Na<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">+<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> cations leading to a decrease in the association of Na<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">+<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> ions with orthophosphate and silicate units. These overall structural findings were correlated with the <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">in vitro<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> ion dissolution behaviour of the bioactive glasses as well as with the thermal properties. The glasses were tested for their <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">in vitro<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> cell viability towards mouse osteoblast type (MC3T3) cells in which fluoride containing bioactive glasses did not show any toxicity and exhibited better cell proliferation. The antibacterial efficacy of the fluoride containing glasses was tested at various concentrations (5, 10 and 20 mg/ml) in <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">E.coli<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> bacterial inoculum in which bactericidal action was evidenced.
Keywords: Fluoride bioactive glasses; In vitro apatite formation and bactericidal action; MAS-NMR spectroscopy; MD simulations

Enantio- and diastereocontrolled conversion of chiral epoxides to trans-cyclopropane carboxylates: application to the synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II (vol 10, pg 6987, 2012) - Kumar, Pradeep; Dubey, Abhishek; Harbindu, Anand (Organic & Biomolecular Chemistry, 2020)

Enantioselective separation using chiral amino acid functionalized polyfluorene coated on mesoporous anodic aluminum oxide membranes - Nikam, Shrikant B.; Asha, S. K. (Analytical Chemistry, 2020)
Homochiral mesoporous anodic aluminum oxide membranes (AAO) were prepared by coating protected chiral D/L aspartic acid appended polyfluorene in the pores. These chiral AAO membranes successfully demonstrated enantioselective recognition and separation of a range of amino acids from their aqueous racemic mixture by simple filtration. Enantioselective separation was achieved by selective adsorption of one enantiomer from the aqueous racemic mixture into the chiral pores of the AAO membrane leaving the filtrate enriched with the other enantiomer. Extraction and quantification of the adsorbed amino acid (glutamic acid) demonstrated that 1 mg of homochiral polyfluorene could effectively extract about 3.5 mg of glutamic acid with 95% enantiomeric excess in 24 h. This is one of the highest enantiomeric excesses (ee %) and yields reported so far in the literature for a racemic mixture of glutamic acid. The pore size of the AAO membrane influenced the efficiency of separation with a reduction in pore size from 200 to 20 nm leading to reduced ee % (similar to 95% to similar to 28%). These results raise the possibility for a facile method to carry out enantioselective separation.

Enantioselective synthesis of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones and their application to the synthesis of novel highly potent antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (ACS Omega, 2020)
Racemic and enantioselective syntheses of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones have been achieved using Horner-Wadsworth-Emmons olefination of trityl protected alpha-phenyl-alpha-amino aldehydes with tetraethyl methylenediphosphonate and diethyl ((phenylsulfonyl)methyl)phosphonate, respectively, without any racemization. The present strategy has also been successfully applied to the synthesis of peptidyl vinyl phosphonate and peptidyl vinyl sulfone derivatives as potential cysteine protease inhibitors of Chagas disease, K11002, with 100% de. The developed synthetic protocol was further utilized to synthesize hybrid molecules consisting of artemisinin as an inhibitor of major cysteine protease falcipain-2 present in the food vacuole of the malarial parasite. The synthesized artemisinin-dipeptidyl vinyl sulfone hybrid compounds showed effective in vitro inhibition of falcipain-2 and potent parasiticidal efficacies against Plasmodium falciparum in nanomolar ranges. Overall, the developed synthetic protocol could be effectively utilized to design cysteine protease inhibitors not only as novel antimalarial compounds but also to be involved in other life-threatening diseases.

Enantioselective synthesis of tricyclic beta-lactones by NHC-catalyzed desymmetrization of cyclic 1,3-diketones - Shee, Sayan; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2020)
The NHC-catalyzed desymmetrization of cyclic-1,3-diketones allowing the enantioselective construction of tricyclic beta-lactones with five contiguous stereocenters, including two quaternary stereocenters, has been developed. The mild and operationally simple addition of a-bromoenals to cyclopentane-1,3-diketone derivatives proceeds via the initial formation of chiral alpha,beta-unsaturated acylazolium intermediates and culminates in a cascade reaction, following the Michael-aldol-Iactonization pathway to deliver the beta-lactone derivatives in moderate to good yields and excellent selectivity.

Energetic and exergetic performance of NH3-H2O-based absorption refrigeration cycle: effect of operating factor - Takalkar, Gorakshnath Dadabhau; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (International Journal of Exergy, 2020)
One of the major objectives while designing the vapour absorption refrigeration system (VARS) is to acquire better performance within the accessible heat source and sink temperature limit. In this paper, attempts are made to identify the temperature limit for the optimisation of a single stage ammonia refrigeration system (AAR) by performing a thermodynamic analysis. To estimate the potential of utilisation of low-grade heat energy, operating factor (R) is considered towards optimising the energetic (COP) and exergetic COP (ECOP). The simulated COP and ECOP results are expended to predict the feasibility and optimum operating region for an AAR cycle in terms of theRand various operating temperatures such asT(gen),T-abs,T-cond,T-e. The operating factorRcovers a wide range of applications i.e., from deep-freezing (253.15 K) to air conditioning (283.15 K) and from water-cooling (303.15 K) to air cooling (318.15 K).
Keywords: AAR; ammonia absorption refrigeration; cold storage; exergy; operating factor; solar energy

Engineering pore morphology using silica template route over mesoporous cobalt oxide and its implications in atmospheric pressure carbon dioxide hydrogenation to olefins - Gupta, Sharad; Ciotonea, Carmen; Royer, Sebastien; Dacquin, Jean-Philippe; Vinod, C. P. (2020)
Highly ordered mesoporous cobalt oxides (denoted as m-Co-KIT-6 and m-Co-SBA-15) with three dimensional and two dimensional pore morphology respectively have been synthesized using 3D KIT-6, and 2D SBA-15 as silica template via nanocasting route. CO2 hydrogenation activity was evaluated for these mesoporous materials under atmospheric pressure conditions. In comparison to nanoparticles of cobalt oxide (Co3O4-nano), mesoporous catalysts showed excellent activity for CO2 hydrogenation due to their higher number of exposed active sites and lower mass diffusion limitations. The ordered mesoporous structure of Co3O4 catalysts favored the chain growth of carbon atoms for the production of C2+ hydrocarbons while Co3O4 nanoparticles showed strong selectivity toward CH4. High selectivity for C2+ (similar to 25%) was obtained for both m-Co-KIT-6 and m-Co-SBA-15 catalysts at 320 degrees C. In addition, the 3D pore structure of m-Co-KIT-6 catalyst exclusively formed more olefins (54.9%) fraction. (C) 2020 Published by Elsevier Ltd.
Keywords: CO2 hydrogenation; Mesoporous CO3O4; Olefin fraction; Pore morphology; Silica hard template

Engineering staphylococcal protein A for high-throughput affinity purification of monoclonal antibodies - Amritkar, Vinod; Adat, Satish; Tejwani, Vijay; Rathore, Anurag; Bhambure, Rahul (Biotechnology Advances, 2020)
Protein A chromatography is one of the most widely used purification steps in the manufacturing of the various classes of recombinant and non-recombinant antibodies. Due to the higher cost, lower binding capacity, and limited life cycle of Protein A ligand, this affinity-based purification step is often one of the most significant contributors to the cost of manufacturing of monoclonal antibody (mAb) products. In the last decade, there has been significant progress in improving the Protein A chromatography throughput by designing new engineered Staphylococcal Protein A (SPA) variants with higher dynamic binding capacity, considerable alkaline tolerance, and mild acidic elution pH. This review aims at summarizing the various protein engineering approaches used for improving the throughput of the Protein A-based affinity purification of various immunoglobulins. With biopharmaceutical producers operating under ever-increasing pressure towards reducing the cost of manufacturing, these advances in engineered protein A variants will help in processing larger cell culture volumes with high throughput and thereby significantly lower the cost of raw materials.
Keywords: Alkaline tolerance; Dynamic binding capacity; Elution pH; Monoclonal antibodies; Protein A

Enhanced anti-ageing and wound healing properties of Ficus religiosa L. bark, leaf and aerial root extract in human keratinocytes cell line (HaCaT) - Pandey, Prem; Seo, Hyo Hyun; Kim, Hye-In; Ryu, Seung Hwan; Dingre, Medini; Moh, Sang Hyun; Kulkarni, Atul; Parasharami, Varsha A. (Vegetos, 2020)
<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">Plants have played a vital role in curative and preventive healthcare. <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">Ficus religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> L., a medicinally important tree has been used as a traditional medicine to treat various ailments and skin diseases. However, its skin anti-ageing properties are not yet scientifically evaluated. Here we report the comparison of <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">F. religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> bark (FRAqB), leaf (FRAqL) and aerial-roots (FRAqAR) extracts for skin anti-ageing and wound healing properties. FRAqB, FRAqL and FRAqAR extracts preparation, cell culture, RNA isolation, real time PCR, astringent activity and wound healing assay were carried out using standard methods. Axio Observer FL-microscope and ImageJ software were used for wound healing assay analysis. The real time PCR study reveals that matrix metalloproteinase-1 (MMP) RNA was downregulated to 75% and 95% for FRAqB and FRAqAR, respectively. For procollagen C-endopeptidase enhancer 1 (PCOLCE), FRAqB and FRAqL enhanced RNA levels by 500% and 300%, respectively. FRAqB and FRAqL increased wound healing area to about 60% and FRAqAR by 50%. All three extracts demonstrated astringent activity which is significant for skin tightening. The study proves that extracts of <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">F. religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> are prominent candidates for pharmaceutical and cosmetic applications such as skin anti-ageing and wound healing.

Enhancing the mechanical properties of 3D printed polylactic acid using nanocellulose - Ambone, Tushar; Torris, Arun; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2020)
We report here a systematic investigation of the mechanical properties of polylactic acid (PLA) processed by fused filament fabrication (FFF) 3D printing vs PLA processed by compression molding. Our results show that the tensile strength and modulus of FFF-PLA is 49% and 41% lower, respectively, than compression molded samples of PLA. We also demonstrate here an approach to augment the mechanical properties of 3D printed PLA using nanocellulose. Incorporation of a small quantity (1 wt%) of cellulose nanofibers (CNF) was found to enhance the tensile strength and modulus of 3D printed PLA by 84% and 63%, respectively. X-ray microtomography was used to probe the morphology of 3D printed PLA and PLA/CNF composites. 3D printed PLA/CNF composites had significantly lesser voids as compared to neat 3D printed PLA. Differential scanning calorimetry study revealed that CNF can accelerate the nucleation and crystallization of 3D printed PLA leading to enhanced crystallinity. The thermal stability of 3D printed PLA/CNF composites was not compromised by the addition of CNF. The enhanced mechanical properties of 3D printed PLA/CNF composites can be ascribed to higher crystallinity and lesser defects.
Keywords: 3D printing; Biocomposites; composites; fused filament fabrication (FFF); Nanocellulose; polylactic acid (PLA)

Enhancing thermomechanical and chemical stability of polymer electrolyte membranes using polydopamine coated nanocellulose - Ram, Farsa; Velayutham, Parthiban; Sahu, Akhila Kumar; Lele, Ashish K.; Shanmuganathan, Kadhiravan (ACS Applied Energy Materials, 2020)
We report here an approach to enhance the chemical and thermomechanical stability of polymer electrolyte membranes without compromising proton conductivity. Multifunctional polydopamine coated nanocellulose (PNC) was prepared by oxidative polymerization of dopamine on nano cellulose fibers and subsequently incorporated in Nafion by solution blending. PNC had a very significant effect on the thermomechanical properties of Nafion showing up to 200% improvement in the storage modulus at 90 degrees C. The PNC network also enhanced the dimensional stability of Nafion under constant stress. The 3 wt % PNC composite membrane showed a drastic reduction in creep compliance of about 39.9% and 46.5% in J(max) at 30 degrees and 60 degrees C, respectively. Free radical scavenging properties of polydopamine also helped to significantly enhance the chemical stability of Nafion, which was ascertained by accelerated degradation tests conducted in Fenton's reagent at 70 degrees C over 40 days. F-19 CP MAS solid state NMR, FTIR, and tensile tests on the membranes show higher chemical stability of the 3 wt % PNC composite membrane. The proton conductivity of the 3 wt % PNC composite membrane at 90 degrees C and 100% RH (similar to 125 mS/cm) was slightly higher than the Nafion membrane (similar to 94 mS/cm) at similar conditions. The retention of proton conductivity even with lower water uptake could be ascribed to proton hopping through polydopamine coated nanocellulose. Performance of the composite membrane was also evaluated in a single stack fuel cell and found to be better than recast Nafion. The benefits derived by this approach are not restricted to Nafion alone and shall broadly apply to many other polymer membranes.
Keywords: cellulose nanofibers; chemical stability; dimensional stability; fuel cell; polydopamine; polymer electrolyte membrane

Enhancing titers and productivity of rCHO clones with a combination of an optimized fed-batch process and ER-stress adaptation - Chandrawanshi, Vikas; Kulkarni, Rohan; Prabhu, Anuja; Mehra, Sarika (Journal of Biotechnology, 2020)
To increase the productivity of rCHO cells, many cell engineering approaches have been demonstrated that over-express or knockout a specific gene to achieve increased titers. In this work, we present an alternate approach, based on the concept of evolutionary adaptation, to achieve cells with higher titers. rCHO cells, producing a monoclonal antibody, are adapted to ER-stress, by continuous culturing under increasing concentration of tunicamycin. A sustained higher productivity of at-least 2-fold was achieved in all the clones, in a concentration-dependent manner. Similarly, a 1.5-2 fold increase in final titers was also achieved in the batch culture. Based on metabolic analysis of the adapted cells, a fed-batch process was designed where significantly higher titersare achieved as compared to control. Metabolic flux analysis is employed in addition with gene expression analysis of key genes to understand the basis of increased performance of the adapted cells. Overall, this work illustrates how process modifications and cellular adaptation can be used in synergy to drive up product titers.
Keywords: Adaptive laboratory evolution; CHO cells; ER-stress; Fed-batch; Increased productivity and titers; Recombinant protein production; UPR pathway

Enolate-mediated regioselective synthesis of 1,2,3-triazoles via azide-aldehydes or ketones [3+2]-cycloaddition reactions in aqueous phase - Tripathi, Anupam; Rode, V, Chandrashekhar; Llop, Jordi; Chavan, Subhash P.; Joshi, Sameer M. (Tetrahedron Letters, 2020)
A synthetic route for the direct conversion of arylazides into the corresponding trizoles via phase transfer catalyst-assisted [3+2] cycloaddition reaction under basic conditions in aqueous medium is reported. This synthetic methodology, which offers high yields and excellent regioselectivity for varieties of triazoles at 100 degrees C for 24 h-48 h and this `greener' synthesis constitutes an alternative to the previously reported well established click reactions. Published by Elsevier Ltd.
Keywords: Azides plus aldehydes or ketones; Click chemistry; triazoles; Water

Enteric pH responsive cargo release from PDA and PEG coated mesoporous silica nanoparticles: a comparative study in Drosophila melanogaster - Sapre, Nidhi; Chakraborty, Rusha; Purohit, Poorvi; Bhat, Suresh; Das, Gaurav; Bajpe, Sneha R. (RSC Advances, 2020)
Physiological stimulus-specific cargo release from nanoparticle carriers is a holy grail of drug delivery research. While the majority of such work is carried out in vitro with cell lines, widespread use of common mammalian model systems - mice and rats - is difficult due to the associated cost and regulatory restrictions. Here we use the inexpensive, easily reared, excellent genetic model system Drosophila melanogaster to test pH responsive cargo release from widely used mesoporous silica nanoparticles (MSNs) coated with pH sensitive polydopamine (PDA) and polyethylene glycol (PEG) polymers. We synthesized 650 +/- 75 nm diameter PDA or PEG coated mesoporous silica nanoparticles loaded with a fluorescent dye and fed to individual adult flies. Subsequently, the passage of the particles were monitored through the fly gut. As in mammals, the fly intestine has multiple pH specific zones that are easily accessible for imaging and also genetic, biochemical or physiological manipulations. We observed that both the species of MSNs ruptured around the acidic (pH < 4.0) middle midgut of the flies. PEG coated particles showed sharper specificity of release in the acidic middle midgut of flies than the PDA coated ones and had less tendency to clump together. Our results clearly show that the Drosophila gut can be used as a model to test pH responsive biocompatible materials in vivo. Our work paves the way for greater use of Drosophila as an in vivo complete systemic model in drug delivery and smart materials research. It also suggests that such specific delivery of chemical/biological cargo can be exploited to study basic biology of the gut cells and their communication with other organs.

Enzymatic and non-enzymatic detoxification of reactive carbonyl compounds improves the oxidative stress tolerance in cucumber, tobacco and rice seedlings - Nareshkumar, Ambekar; Subbarao, Sindhu; Vennapusa, Amarnatha Reddy; Ashwin, Vargheese; Banarjee, Reema; Kulkarni, Mahesh J.; Ramu, Vemanna S.; Udayakumar, Makarla (Journal of Plant Growth Regulation, 2020)
Detoxification of reactive carbonyl compounds (RCC) is crucial to sustain cellular activity to improve plant growth and development. Seedling growth is highly affected by accumulation of RCC under stress. We report non-enzymatic, enzymatic mechanisms of detoxification of RCC in the cucumber, tobacco and rice seedling systems exposed to glucose, NaCl, methyl viologen (MV) induced oxidative stress. The cucumber seedlings exposed to carbonyl stress had higher levels of malondialdehyde (MDA), protein carbonyls (PCs) and advanced glycation end-product N-carboxymethyl-lysine (AGE-CML) that negatively affected the seedling growth. The overexpression of enzyme encoding aldo-keto reductase-1 (AKR1) in tobacco and rice showed detoxification of RCC, MDA and methylglyoxal (MG) with improved seedling growth under glucose, NaCl and MV-induced oxidative stress. Further, small molecules like acetylsalicylic acid (ASA), aminoguanidine (AG), carnosine (Car), curcumin (Cur) and pyridoxamine (PM) showed detoxification of RCC non-enzymatically and rescued the cucumber seedling growth from glucose, NaCl and MV-stress. In autotrophically grown rice seedlings these molecules substantially improved seedling growth under MV-induced oxidative stress. Seedlings treated with the small molecules sustained higher guaiacol peroxidase (GPX) enzyme activity signifying the role of small molecules in reducing carbonyl stress-induced protein inactivation and AGE-CML protein modifications. The results showed that besides enzymatic detoxification of RCC, the small molecules also could reduce cytotoxic effect of RCC under stress. The study demonstrates that small molecules are attractive compounds to improve the seedling growth under stress conditions.
Keywords: Oxidative stress; plant growth; Reactive carbonyl scavengers; Seed germination; small molecules

Epoxy functionalized polymer grafted magnetic nanoparticles by facile surface initiated polymerization for immobilization studies of Candida Antarctica lipase B - Afzal, Haq Asif; Ghorpade, Ravindra V.; Thorve, Asmita K.; Nagaraja, Sreeharsha; Al-Dhubiab, Bandar E.; Meravanige, Girish; Rasool, Sahibzada Tasleem; Roopashree, Teeka S. (Reactive & Functional Polymers, 2020)
Immobilization of Candida Antarctica lipase B (Cal-B) was done on the epoxy functionalized polymer (EFP) grafted magnetic nanoparticles (MNPs) via covalent attachment with the active epoxy groups. The EFP brushes were grafted on iron-oxide based MNPs by a facile surface-initiated atom transfer radical polymerization (ATRP) using activators generated by electron transfer (AGET) of glycidyl methacrylate (GMA). Each step of the surface modification, polymer grafting, and enzyme immobilization process on the polymer grafted MNPs was studied using Fourier transform infrared spectroscopy (FTIR). A thermogravimetric analysis (TGA) calculated the amount of engineered organic components, a transmission electron microscopy (TEM) visualized the core-shell formation of the MNPs, and a vibrating sample magnetometer (VSM) validated their magnetic properties at various modification stages. The lipase immobilization efficiency was described as a function of immobilization time, as well as, enzyme amount. The activity was characterized within a range of pH, temperature, kinetic parameters, resusability and storage stability, for both the free and immoblized Cal-B enzyme. The results of this study suggested that poly(GMA) grafted MNPs can be successfully used for the immobilization of Cal-B with improved efficiencies compared to those obtained with free soluble lipase. The reported enzyme immobilization method appears to be reproducible and scalable for industrial production.
Keywords: Cal-B enzymes; enzymes; Immoblization; Magnetic nanoparticles

Essential gene prediction using limited gene essentiality information-an integrative semi-supervised machine learning strategy - Nandi, Sutanu; Ganguli, Piyali; Sarkar, Ram Rup (PloS One, 2020)
Essential gene prediction helps to find minimal genes indispensable for the survival of any organism. Machine learning (ML) algorithms have been useful for the prediction of gene essentiality. However, currently available ML pipelines perform poorly for organisms with limited experimental data. The objective is the development of a new ML pipeline to help in the annotation of essential genes of less explored disease-causing organisms for which minimal experimental data is available. The proposed strategy combines unsupervised feature selection technique, dimension reduction using the Kamada-Kawai algorithm, and semi-supervised ML algorithm employing Laplacian Support Vector Machine (LapSVM) for prediction of essential and non-essential genes from genome-scale metabolic networks using very limited labeled dataset. A novel scoring technique, Semi-Supervised Model Selection Score, equivalent to area under the ROC curve (auROC), has been proposed for the selection of the best model when supervised performance metrics calculation is difficult due to lack of data. The unsupervised feature selection followed by dimension reduction helped to observe a distinct circular pattern in the clustering of essential and non-essential genes. LapSVM then created a curve that dissected this circle for the classification and prediction of essential genes with high accuracy (auROC > 0.85) even with 1% labeled data for model training. After successful validation of this ML pipeline on both Eukaryotes and Prokaryotes that show high accuracy even when the labeled dataset is very limited, this strategy is used for the prediction of essential genes of organisms with inadequate experimentally known data, such as Leishmania sp. Using a graph-based semi-supervised machine learning scheme, a novel integrative approach has been proposed for essential gene prediction that shows universality in application to both Prokaryotes and Eukaryotes with limited labeled data. The essential genes predicted using the pipeline provide an important lead for the prediction of gene essentiality and identification of novel therapeutic targets for antibiotic and vaccine development against disease-causing parasites.

Evaluation of biomolecular interactions and cytotoxic activity of organometallic binuclear Ru(II) complexes of ferrocenyl thiosemicarbazones - Khanvilkar, Priyanka; Dash, Soumya R.; Vohra, Alisagar; Devkar, Ranjitsinh; Chakraborty, Debjani (Journal of Biomolecular Structure & Dynamics, 2020)
{Four new ferrocenyl substituted thiosemicarbazone ligands (L1-L4) and their corresponding binuclear ruthenium(II) arene complexes of the general type [(eta(6)-pcym)(L)Ru(mu-im)Ru(L)(eta(6)-p-cym)]Cl (C1-C4) and [(eta(6)-pcym)(L)Ru(mu-azpy)Ru(L)(eta(6)-p-cym)]Cl-2(C5-C8) (cym = cymene
Keywords: binuclear ruthenium(II) complexes; BSA binding interactions; DNA; Ferrocenyl thiosemicarbazone; HeLa human cervical carcinoma

Evaluation of uttroside B, a saponin from Solanum nigrum Linn, as a promising chemotherapeutic agent against hepatocellular carcinoma (vol 6, 36318, 2016) - Nath, Lekshmi R.; Gorantla, Jaggaiah N.; Thulasidasan, Arun Kumar T.; Vijayakurup, Vinod; Shah, Shabna; Anwer, Shabna; Joseph, Sophia M.; Antony, Jayesh; Veena, Kollery Suresh; Sundaram, Sankar; Marelli, Udaya K.; Lankalapalli, Ravi S.; et al. (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

EviMass: a literature evidence-based miner for human microbial associations (vol 10, 849, 2019) - Srivastava, Divyanshu; Baksi, Krishanu D.; Kuntal, Bhusan K.; Mande, Sharmila S. (Frontiers in Genetics, 2020)
Keywords: Human Disease; literature mining; microbial association; Microbiome; Web server

Examining the compatibility of energetic plasticizer DNDA-5 with energetic binders - Vijayalakshmi, R.; Agawane, N. T.; Talawar, M. B.; Khan, Md Abdul Shafeeuulla (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
The requirement of developing energetic binders with suitable energetic plasticizers is to enhance the mechanical properties and to reduce glass transition temperature of propellant and explosive formulations. Compatibility of energetic plasticizer 2,4-dinitro-2,4-diazapentane (DNDA-5) with four different energetic binders viz. poly glycidyl nitrate (PGN), poly(3-nitratomethyl-3-methyloxetane) (PLN), glycidyl azide polymer (GAP) and tetra functional glycidyl azide polymer (t-GAP) was studied by using differential scanning calorimeter (DSC) and density functional theory (DFT) methods. Results obtained for the pure binder was compared with the results obtained for binder/plasticizer blend in the parameters of decomposition temperature and the format of the peak which indicated the compatibility or incompatibility of DNDA-5 with the studied binders. Glass transition temperatures of all these blends were determined by low temperature DSC and showed desirable lowering of glass transition temperature with single peak in the case of PLN. The proposed energetic plasticizer DNDA-5 has displayed its compatibility with three binders PGN, PLN and GAP employing thermal techniques. DNDA-5 has been found as incompatible when it is mixed with t-GAP. The predicted relative trend of interaction energies between plasticizer and binder has provided concurrence to results drawn from thermal studies.
Keywords: Computational study; DNDA-5; Glass transition temperature; plasticizing effect; thermal

Expeditious and solvent-free nickel-catalyzed c-h arylation of arenes and indoles (vol 10, pg 2242, 2017) - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2020)
Keywords: Arylation; C-H activation; heterocycles; Homogeneous catalysis; Nickel

Experimental analysis of vapour-liquid phase equilibria for binary systems of diethyl carbonate with methyl, ethyl, isopropyl, n-butyl and isoamyl acetates at 95 kPa - Bhoi, Bharat R.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical Thermodynamics, 2020)
Experimental analysis of vapour-liquid phase equilibrium (VLE) for five binary pairs of diethyl carbonate (DEC) with methyl acetate, ethyl acetate, isopropyl acetate, n-butyl acetate and isoamyl acetate was carried out in this study. VLE data were generated experimentally at local atmospheric pressure of 95 kPa in a glass dynamic recirculation still. Reliability of data was checked with the thermodynamic consistency tests by Van Ness, infinite dilution, pure component and mean absolute deviation test. Experimental data was found to be thermodynamically consistent with all tests and data was regressed with Wilson, NRTL and UNIQUAC activity coefficient models to determine binary interaction parameters. Binary pair of DEC with n-butyl acetate has shown azeotropic behaviour with minimum boiling azeotrope and a close boiling behaviour through-out the composition range. No azeotropic behaviour was observed for the rest of the binary pairs. (c) 2020 Elsevier Ltd.
Keywords: Diethyl carbonate; ethyl acetate; Isobaric; Isopropyl acetate; methyl acetate; VLE

Experimental and theoretical investigations of the effect of heteroatom-doped carbon microsphere supports on the stability and storage capacity of nano-Co3O4 conversion anodes for application in lithium-ion batteries - Dwivedi, Pravin K.; Nair, Aathira; Mehare, Rupali S.; Chaturvedi, Vikash; Joshi, Kavita; Shelke, V, Manjusha (Nanoscale Advances, 2020)
Conversion-type anode materials have been intensely studied for application in Li-ion batteries (LIBs) due to their potentially higher capacities than current graphite-based anodes. This work reports the development of a high-capacity and stable anode from a nanocomposite of N and S co-doped carbon spheres (NSCSs) with Co3O4 (NSCS-Co3O4). A hydrothermal reaction of saccharose withl-cysteine was carried out, followed by its carbonization. CSs when used as supports for conversion-type materials provide efficient electron/ion transfer channels, enhancing the overall electrochemical performance of the electrodes. Additionally, the heteroatoms doped in a carbon matrix alter the electronic properties, often increasing the reactivity of the carbon surface, and they are reported to be effective for anchoring metal oxide nanoparticles. Consequently, the NSCS-Co3O4 nanocomposites developed in this work exhibit enhanced and stable reversible specific capacity over several cycles. Stable cycling behavior was observed at 1 A g(-1)with 1285 mA h g(-1) of specific capacity retained after 350 cycles along with more than 99% of coulombic efficiency. This material shows excellent rate capability with a specific capacity of 745 mA h g(-1) retained even at a high current density of 5 A g(-1). Detailed DFT-based calculations revealed the role of doped supports in controlling the volume expansion upon lithiation.

Experimental vapor-liquid phase equilibrium analysis of the binary systems of aniline with xylene isomers at 93.13 kPa - Yadav, Satyajeet S.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2020)
In the present work, vapor-liquid phase equilibrium (VLE) analyses of binary systems of aniline with four isomers of xylene, comprising p-xylene, m-xylene, o-xylene, and ethylbenzene, are reported at 93.13 kPa. The experimental VLE data was generated in a dynamic circulating vapor-liquid, and the data was found thermodynamically consistent using the Van Ness point-to-point consistency test. The experimental VLE data was regressed with the Wilson, NRTL, and UNIQUAC activity coefficient models to obtain the binary interaction parameters. No azeotropic or close-boiling behavior was observed in any of the binary pair, and these pairs were found suitable for separation through a conventional distillation method.

Exploring magnetic XY behavior in a quasi-2D anisotropic triangular lattice of Cu(II) by functionalized graphene - Gupta, Kriti; Dadwal, Arun; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2020)
Study on magnetism in two-dimensional (2D) spin-lattices is advancing rapidly. In this work, phase-pure botallackite (Bo) (Cu-2(OH)(3)Br), a quasi-2D S = 1/2 anisotropic triangular spin-lattice is stabilized over 2D reduced graphene oxide (rGO) nanosheets via simple oxidation-reduction reaction chemistry. In comparison to polycrystalline Bo, such an anchoring resulted in the oriented growth of Bo crystallites in the Bo-rGO system. The Bo-rGO nanocomposite was found to be magnetically active with a Neel transition at 8.9 K, crossing over to possible XY anisotropy at similar to 5 K-as revealed by complementary dc and ac susceptibility measurements-an unprecedented observation in the field assigned to an interfacial effect. This work demonstrates the potential usage of nonmagnetic 2D functionalized graphene to significantly modulate the magnetic properties of 2D spin-lattices.

Exploring the pharmacological potentials of biosurfactant derived from planococcus maritimus SAMP MCC 3013 - Waghmode, Samadhan; Swami, Sagar; Sarkar, Dhiman; Suryavanshi, Mangesh; Roachlani, Sneha; Choudhari, Prafulla; Satpute, Surekha (Current Microbiology, 2020)
Therapeutic potential of biosurfactant (BS) has been improved in recent years. Our present study deals with production of BS from Planococcus maritimus SAMP MCC 3013 in a mineral salt medium (MSM) supplemented with glucose (1.5% w/v). Further, BS has been purified and partially characterized as glycolipid type through our previous publication. Current research article aimed to evaluate biological potential of BS against Mycobacterium tuberculosis, Plasmodium falciparum and cancerous cell lines. Planococcus derived glycolipid BS was found to be a promising inhibitor of M. tuberculosis (MTB) H37Ra at IC50 64.11 +/- 1.64 mu g/mL and MIC at 160.8 +/- 1.64 mu g/mL. BS also showed growth inhibition of P. falciparum at EC50 34.56 +/- 0.26 mu M. Additionally, BS also displayed the cytotoxicity against HeLa (IC50 41.41 +/- 4.21 mu g/mL), MCF-7 (IC50 42.79 +/- 6.07 mu g/mL) and HCT (IC50 31.233 +/- 5.08 mu g/mL) cell lines. Molecular docking analysis was carried for the most popular glycolipid type BS namely Rhamnolipid (RHL) aiming to interpret the possible binding interaction for anti-tubercular and anti-cancer activity. This analysis revealed the involvement of RHL binding with enoyl reductase (InhA) of M. tuberculosis. Docking studies of RHL with tubulin directed several hydrophobic and Vander Waal interactions to exhibit anti-cancer potential. The present study will be helpful for further development of marine bioactive molecules for therapeutic applications. Their anti-tubercular, anti-plasmodial and cytotoxic activities make BS molecules as a noteworthy candidate to combat several diseases. To the best of our knowledge, this is the first report on projecting the pharmacological potential of Planococcus derived BS. Graphic

Extractive distillation configuration for nitric acid dehydration using sulfuric acid as a solvent - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Industrial & Engineering Chemistry Research, 2020)
In this work, an extractive distillation configuration for dehydration of nitric acid is proposed with sulfuric acid as a solvent. Thermodynamic modeling of the vapor-liquid equilibrium of binary and ternary systems of nitric acid/water/sulfuric acid is carried out using the electrolyte non-random two-liquid (eNRTL-RK) thermodynamic property method in the Aspen plus process simulator. The model performance is validated by comparing the experimental data with the estimated data by the eNRTL-RK model and is found to be in good agreement. The thermodynamic model is then used for developing a triple-column extractive distillation sequence, comprising a preconcentration column, an extractive distillation column, and a solvent recovery column. The configuration is designed, simulated, and optimized to concentrate dilute nitric acid using sulfuric acid as a solvent to break the nitric acid-water azeotrope. The operating and structural parameters of the distillation configuration are optimized simultaneously with an objective of minimizing the energy consumption and the total annual cost (TAC) of the overall configuration.

Easy and practical approach to access multifunctional cylcopentadiene- and cyclopentene-spirooxindoles via [3+2] annulation - Warghude, Prakash K.; Sabale, Abhijeet S.; Dixit, Ruchi; Vanka, Kumar; Bhat, Ramakrishna G. (Organic & Biomolecular Chemistry, 2021)
A highly regioselective [3 + 2] annulation of Morita-Baylis-Hillman (MBH) carbonates of isatin with aurone/thioaurone is developed. Spiroheterocycles such as spirooxindole cyclopentadiene and spirooxindole fused hydroxy cyclopentene derivatives are constructed in one pot by exploring the reactivity of Lewis bases. Combined experimental and density functional theory (DFT) calculations offered an insight into the reaction mechanism.

Editorial special issue in the journal of flow chemistry: engineering aspects of flow chemistry - Kockmann, Norbert; Hartman, Ryan; Kulkarni, Amol (Journal of Flow Chemistry, 2021)

Effect of CaCl2 and ZnCl2 salts on isobaric vapor-liquid equilibrium in separation of the azeotropic mixture of ethanol plus water - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Fluid Phase Equilibria, 2021)
Present work analyzes potential of calcium chloride (CaCl2) and zinc chloride (ZaCl(2)) salts as entrainer for breaking the minimum boiling azeotrope of ethanol and water. Isobaric vapor-liquid equilibrium (VLE) data for the binary systems of water + ethanol and ternary system of water + ethanol + calcium chloride, and water + ethanol + zinc chloride were measured at a constant pressure of 94.5 kPa. The effect of salts on the relative volatility of ethanol to water as well as on the vapor phase mole fractions of ethanol were also studied experimentally. From the experimental results, it is observed that with addition of salts, the azeotropic point of the ethanol and water system can be eliminated. Salting out effects in case of calcium chloride was more than that zinc chloride salt. The results obtained in this work showed that calcium chloride could be a better choice for separation of the water + ethanol azeotrope. Electrolyte nonrandom two-liquid (eNRTL) model was used to correlate the experimental VLE data. The model prediction with the regressed parameters was found in well agreement with the experimental data. The experimental data obtained in this work was found thermodynamically consistent using van Ness test. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Azeotrope; eNRTL; Ethanol; salts; Vapor-liquid equilibrium; Water

Effect of Mn2+ substitution into the hst lattice of ZnO via sol-gel route for boosting the dye-sensitized solar cells performance (Apr, 10.1007/s11696-021-01615-w, 2021) - Kumbhar, Deepak; Delekar, Sagar; Kumbhar, Sarita; Dhodamani, Ananta; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Chemical Papers, 2021)

Effect of Mn2+ substitution into the hst lattice of ZnO via sol-gel route for boosting the dye-sensitized solar cells performance - Kumbhar, Deepak; Delekar, Sagar; Kumbhar, Sarita; Dhodamani, Ananta; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Chemical Papers, 2021)
In this study, Mn2+ ion is doped in ZnO lattice framework at 1, 3 and 5 wt % by a simple and low-cost sol-gel route to attain improved optoelectronic response. The structural investigation by XRD and Raman analysis explores the formation of hexagonal wurtzite framework with variations in lattice parameters comprising peak intensities favors the Mn doping. The extent of doping was supported by EDS analysis, while XPS confirms doping in + 2 chemical state. The optical investigation by UV-visible and PL provides prominent peaks that also specify peak shifting in order of doping level, while the significant hexagon-shaped nanoparticle (NP) formation was deduced in SEM and TEM micrographs. These proficient ZnO NPs have been deposited on fluorine-doped tin oxide (FTO) conducting glass plate by doctor-blade technique to get photoanodes. The electrical performance of these photoanodes especially photocurrent generation was investigated under standard AM 1.5 one sun illuminations. The highest photoconversion efficiency was attained for 3% Mn-doped ZnO photoanode after xanthene-based organic dye sensitization with output efficiency (eta%) of 0.25% higher than 0.03% of bare ZnO. The comparable ionic radii with exactly half-filled 3d orbital simply overlap with the ZnO valence bond responsible for enhanced overall structural and optical properties that beneficial for DSSCs performance.
Keywords: gel; Mixed dye; Mn-doped ZnO; Photoelectrochemical cell; Sol&#8211

Effect of object shape on the flow past microstructures in small channel - Mule, Gunwant M.; Kulkarni, Amol A. (Fluid Dynamics Research, 2021)
Flow past objects in microfluidics and microscale devices are used to perturb the flow and thereby achieve effective mixing and heat transfer. This paper presents the observations on the flow past bluff (elliptical, rectangular and triangular) cylindrical micropillars (objects) having different cross-sectional area in a micro-channel through 2D simulations. The pertinent range of Re based on object dimension (0.1 Re 150) was chosen to understand the wake dynamics that would remain relevant for comparison with literature data. Drag coefficient, recirculation region, critical Reynolds number for flow oscillations and vortex strength in a channel were studied. The drag coefficient was found to increase with aspect ratio of the object. The critical Re for flow oscillations was found to increase with the cross-sectional area of the object. The vortex strength in a channel was seen highest for triangular cylinder compared to elliptical and rectangular cylinder.
Keywords: 2D simulations; flow past objects; micro and mini-channels; micropillars; wake dynamics

Effect of rice husk particle size on ZSM-5 physico-chemical properties for selective formation of 1,3,5-trimethyl-2-benzylbenzene (Pharmaceutical Intermediate) - Ghuge, Gorakh; Niphadkar, Prashant; Rathod, Simmy; Bokade, Vijay V. (ChemistrySelect, 2021)
Rice husk, rich in silica and abundantly available as waste, is presently destroyed by burning, which creates environmental issues. Thus, it will be advantageous if this rice husk waste can be used for preparation of valuable products. One of the application is its use as silica source in the synthesis of zeolites like ZSM-5, which are silico-aluminates. Rice husk waste is available in wide range of particle sizes in agricultural farms. There is no study available in open literature on use of these wide particle ranges for its direct application. This paper is an attempt to use wide particle size rice husk, its effect on ZSM-5 synthesis and its physico-chemical properties. Further these prepared ZSM-5 catalyst was evaluated for benzylation of mesitylene reaction. The study found that, rice husk of 600 mu m particle size is optimum as far as ZSM-5 synthesis, its physicochemical properties and further its application in mesitylene benzylation reaction.
Keywords: Mesitylene; Particle size; rice husk; Silica Source; ZSM-5

Effect of wettability on hydrodynamics and mass transfer in small capillaries - Sampat, Chaitanya; Pal, Sayan; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2021)
The wettability of the reactor wall has a significant effect on the interfacial liquid?liquid mass transfer rates in segmented flow. This work quantitatively demonstrates the importance of choosing the right material of construction of flow reactors to achieve the desired mass transfer performance. Glass and PTFE capillaries of identical diameter were used to study the effect of hydrophilic and hydrophobic surfaces on the hydrodynamics and mass transfer of the system. It was observed that for the overall mass transfer coefficient (kLa) changed by two orders of magnitude depending on the wettability of the continuous phase. The observations indicated that it is essential to achieve complete wetting of the capillary walls by the continuous phase for significant mass transfer enhancement. The observations are discussed on the basis of film thickness and slip velocity at the wall as well as the slip velocity at liquid?liquid interface. Predictions of the mass transfer coefficient using a model based on the interfacial and fluid properties showed excellent match with the experiments thereby allowing us to explore the effects of wettability on the overall mass transfer coefficient in greater detail. ? 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Liquid?liquid slug flow; Mass transfer; Slip velocity; Wettability

Effective structure of a system with continuous polydispersity - Patel, Palak; Nandi, Manoj Kumar; Nandi, Ujjwal Kumar; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2021)
In a system of N particles, with continuous size polydispersity, there exists an N(N - 1) number of partial structure factors, making it analytically less tractable. A common practice is to treat the system as an effective one component system, which is known to exhibit an artificial softening of the structure. The aim of this study is to describe the system in terms of M pseudospecies such that we can avoid this artificial softening but, at the same time, have a value of M << N. We use potential energy and pair excess entropy to estimate an optimum number of species, M-0. We then define the maximum width of polydispersity, Delta sigma (0), that can be treated as a monodisperse system. We show that M-0 depends on the degree and type of polydispersity and also on the nature of the interaction potential, whereas Delta sigma (0) weakly depends on the type of polydispersity but shows a stronger dependence on the type of interaction potential. Systems with a softer interaction potential have a higher tolerance with respect to polydispersity. Interestingly, M-0 is independent of system size, making this study more relevant for bigger systems. Our study reveals that even 1% polydispersity cannot be treated as an effective monodisperse system. Thus, while studying the role of polydispersity by using the structure of an effective one component system, care must be taken in decoupling the role of polydispersity from that of the artificial softening of the structure.

Effectors of root-knot nematodes: an arsenal for successful parasitism - Jagdale, Shounak; Rao, Uma; Giri, Ashok P. (Frontiers in Plant Science, 2021)
Root-knot nematodes (RKNs) are notorious plant-parasitic nematodes first recorded in 1855 in cucumber plants. They are microscopic, obligate endoparasites that cause severe losses in agriculture and horticulture. They evade plant immunity, hijack the plant cell cycle, and metabolism to modify healthy cells into giant cells (GCs) – RKN feeding sites. RKNs secrete various effector molecules which suppress the plant defence and tamper with plant cellular and molecular biology. These effectors originate mainly from sub-ventral and dorsal oesophageal glands. Recently, a few non-oesophageal gland secreted effectors have been discovered. Effectors are essential for the entry of RKNs in plants, subsequently formation and maintenance of the GCs during the parasitism. In the past two decades, advanced genomic and post-genomic techniques identified many effectors, out of which only a few are well characterized. In this review, we provide molecular and functional details of RKN effectors secreted during parasitism. We list the known effectors and pinpoint their molecular functions. Moreover, we attempt to provide a comprehensive insight into RKN effectors concerning their implications on overall plant and nematode biology. Since effectors are the primary and prime molecular weapons of RKNs to invade the plant, it is imperative to understand their intriguing and complex functions to design counter-strategies against RKN infection.

Efficient catalytic transfer hydrogenation-hydrodeoxygenation of lignin derived monomers: investigating catalyst properties-activity correlation - Singh, Dheerendra; Dhepe, Paresh L. (Catalysis Communications, 2021)
Reduction of O/C ratio of lignin derived monomers via hydrodeoxygenation (HDO) pathway is conventionally furnished using molecular hydrogen under severe conditions. Nonetheless, due to a prerequisite to accomplish HDO through commercially attractive methodology we report, HDO reactions of various phenolic compounds via catalytic transfer hydrogenation (CTH) pathway using very low loading of Ru (0.5 wt%) on neutral and acidic Al2O3 under nitrogen atmosphere. With guaiacol as a substrate, 74% cyclohexanol yield at 225 degrees C in the presence of IPA is realized. Bi-functionality of metal state, acidity of support and nature of alcohol are perceived to be responsible for the variation in activity.
Keywords: Catalytic transfer hydrogenation (CTH); Cyclohexanol; Hydrodeoxygenation; lignin; Supported metal catalysts

Efficient electrochemical oxygen reduction to hydrogen peroxide by transition metal-doped silicate Sr0.7Na0.3SiO3-delta - Thundiyil, Shibin; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2021)
Electrochemical oxygen reduction in a selective two-electron pathway is an efficient method for onsite production of H2O2. State of the art noble metal-based catalysts will be prohibitive for widespread applications, and hence earth-abundant oxide-based systems are most desired. Here we report transition metal (Mn, Fe, Ni, Cu)-doped silicates, Sr0.7Na0.3SiO3-delta, as potential electrocatalysts for oxygen reduction to H2O2 in alkaline conditions. These novel compounds are isostructural with the parent Sr0.7Na0.3SiO3-delta and crystallize in monoclinic structure with corner-shared SiO4 groups forming cyclic trimers. The presence of Na stabilizes O vacancies created on doping, and the transition metal ions provide catalytically active sites. Electrochemical parameters estimated from Tafel and Koutechy-Levich plots suggest a two-electron transfer mechanism, indicating peroxide formation. This is confirmed by the rotating ring disc electrode method, and peroxide selectivity and Faradaic efficiency are calculated to be in the range of 65-82% and 50-68%, respectively, in a potential window 0.3 to 0.6 V (vs RHE). Of all the dopants, Ni imparts the maximum selectivity and efficiency as well as highest rate of formation of H2O2 at 1.65 mu mol s(-1).
Keywords: H2O2; mixed metal oxide; ORR; silicate

Efficient metal-free organic room temperature phosphors - Nidhankar, Aakash D.; Goudappagouda; Wakchaure, Vivek C.; Babu, Sukumaran Santhosh (Chemical Science, 2021)
An innovative transformation of organic luminescent materials in recent years has realised the exciting research area of ultralong room-temperature phosphorescence. Here the credit for the advancements goes to the rational design of new organic phosphors. The continuous effort in the area has yielded wide varieties of metal-free organic systems capable of extending the lifetime to several seconds under ambient conditions with high quantum yield and attractive afterglow properties. The various strategies adopted in the past decade to manipulate the fate of triplet excitons suggest a bright future for this class of materials. To analyze the underlying processes in detail, we have chosen high performing organic triplet emitters that utilized the best possible ways to achieve a lifetime above one second along with impressive quantum yield and afterglow properties. Such a case study describing different classes of metal-free organic phosphors and strategies adopted for the efficient management of triplet excitons will stimulate the development of better candidates for futuristic applications. This Perspective discusses the phosphorescence features of single- and multi-component crystalline assemblies, host-guest assemblies, polymers, and polymer-based systems under various classes of molecules. The various applications of the organic phosphors, along with future perspectives, are also highlighted.

Eichhornia crassipes mediated bioinspired synthesis of crystalline nano silver as an integrated medicinal material: a waste to value approach - Moudgil, Aliesha; Deval, Animesh S.; Dharne, Mahesh S.; Sarkar, Dhiman M.; Choudhari, Amit S.; Chaudhari, Bhushan P. (Journal of Cluster Science, 2021)
The present study deals with the synthesis of silver nanoparticles from Eichhornia crassipes. Dynamic light scattering (DLS), Transmission electron microscopy (TEM), UV-Vis spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and X-ray diffraction (XRD) were performed for nanoparticle characterization. The aqueous plant extract of Eichhornia crassipes was phytochemically analyzed for phenol, flavonoid, reducing sugar content, alkaloids, saponins and carotenoids. The synthesized particles after optimization of important parameters have an average diameter of 12.48 +/- 3.43 nm with a spherical morphology and zeta potential of - 31.53 mV. At 100 mu g/ml of nanoparticle concentration, the antioxidant activity of 93.6% was observed. MIC (Minimum inhibitory concentration) values exhibiting the antimicrobial attributes reported an estimated value of 7.8 mu g/ml for gram-negative and higher values of 31.25 and 250 mu g/ml for gram-positive bacteria. The antibiofilm assay showed 86.89% and 74.7% of the reduction in violacein synthesis and biofilm inhibition respectively at 15 mu g/ml nanoparticle concentration. The anticancer assay reported the IC50 (Inhibitory concentration) values of 13.32, 14.71 and 19.91 mu g/ml for HeLa, HCT 116 and L6 cell lines respectively. Thus the study establishes a significant integrative treatment to combat secondary infections in cancer patients. Graphic
Keywords: antibacterial activity; Antibiofilm activity; Anticancer activity; Antioxidant activity; Eichhornia crassipes; silver nanoparticles

Elastic piezoelectric aerogels from isotropic and directionally ice-templated cellulose nanocrystals: comparison of structure and energy harvesting - Ram, Farsa; Biswas, Bipul; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Cellulose, 2021)
We report the preparation of highly compressible and elastic piezoelectric aerogels of carboxylated cellulose nanocrystals (CNCs). Aqueous CNC dispersions containing polyethyleneimine and crosslinker were frozen isotropically to yield isotropic aerogels, while oriented aerogels were prepared by directional freezing. These aerogels were highly flexible and porous (similar to 85% void fraction), exhibiting greater than 90% recovery at 50% compressive strain even after 100 compression-decompression cycles. Since such aerogels with low bulk modulus and high anisotropy would be an ideal platform for leveraging the piezoelectric properties of CNCs, we used them to prepare piezoelectric nanogenerator devices and determined their energy transduction behavior. Anisotropic aerogels led to an enhanced open-circuit voltage of 840 mV (at similar to 8 N applied force), which is over 2.6 times higher than isotropic aerogels (320 mV). The energy density of anisotropic aerogels was around 52 nW/cm(2), representing outstanding piezoelectric performance for cellulose-based aerogels. Such aerogels with high compressibility, elastic recovery and exceptional piezoelectric performance could have potential applications in sensors, wearable electronics, etc.
Keywords: Aerogel; Anisotropic; Cellulose nanocrystals; energy harvesting; Piezoelectricity

Electrocatalytic nitrogen reduction directed through the p-band center of boron on BSAC@Mo2C - Maibam, Ashakiran; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Materials Advances, 2021)
Greener modes of ammonia synthesis via the electrocatalytic route have been investigated on pristine and defective Mo2C based monolayers anchored with metal-free boron atom catalysts. Boron single atom catalysts (SACs) on the defective Mo2C monolayer has been found to activate N2 strongly with an adsorption energy of −1.92 eV and reduce it to NH3 efficiently with a significantly low overpotential of 0.41 eV. The exothermic adsorption of N2 and low overpotential for the nitrogen reduction reduction (NRR) appertain to the p-band center of the boron atom catalyst and charge transfer between the adsorbed N2 and the catalyst, respectively. This work brings forth the correlation between electron occupancy on the boron center and NRR catalytic efficiency on a metal-free SACs@Mo2C monolayer couple, thereby serving as a lead in designing metal free electrocatalysts for the NRR.

Electronic and optical properties of vacancy ordered double perovskites A(2)BX(6) (A=Rb, Cs; B=Sn, Pd, Pt; and X=Cl, Br, I): a first principles study - Faizan, Muhammad; Bhamu, K. C.; Murtaza, Ghulam; He, Xin; Kulhari, Neeraj; AL-Anazy, Murefah Mana; Khan, Shah Haidar (Scientific Reports, 2021)
The highly successful PBE functional and the modified Becke-Johnson exchange potential were used to calculate the structural, electronic, and optical properties of the vacancy-ordered double perovskites A(2)BX(6) (A=Rb, Cs; B=Sn, Pd, Pt; X=Cl, Br, and I) using the density functional theory, a first principles approach. The convex hull approach was used to check the thermodynamic stability of the compounds. The calculated parameters (lattice constants, band gap, and bond lengths) are in tune with the available experimental and theoretical results. The compounds, Rb2PdBr6 and Cs2PtI6, exhibit band gaps within the optimal range of 0.9-1.6 eV, required for the single-junction photovoltaic applications. The photovoltaic efficiency of the studied materials was assessed using the spectroscopic-limited-maximum-efficiency (SLME) metric as well as the optical properties. The ideal band gap, high dielectric constants, and optimum light absorption of these perovskites make them suitable for high performance single and multi-junction perovskite solar cells.

Electronically integrated mesoporous Ag-TiO2 nanocomposite thin films for efficient solar hydrogen production in direct sunlight - Mani, Sunesh S.; Rajendran, Sivaraj; Nalajala, Naresh; Mathew, Thomas; Gopinath, Chinnakonda S. (Energy Technology, 2021)
The synthesis of mesoporous TiO2 by a solution-based assembly process and Ag/TiO2 nanocomposites is provided. The efficacy of Ag/TiO2 nanocomposite as photocatalyst in thin-film form is demonstrated for solar hydrogen generation in sunlight. Integration of Ag with TiO2 dramatically enhanced the H-2 production: with 1 wt% Ag on TiO2 (TiAg-1), the H-2 yield was observed to be 4.59 mmol h(-1) g(-1), which is 2.3 (30) times larger than 0.5 wt% Ag on TiO2. TiAg-1 shows 4.3 times higher activity in film form compared with its powder counterpart. High photocatalytic efficiency is attributed to the surface plasmon resonance effect of Ag, electronic integration of Ag with TiO2, and subsequent valence band broadening, large distribution of Ag nanoparticles and abundant Ag-TiO2 Schottky junctions, and the later minimizes electron-hole recombination. Interparticle mesoporous network increases necking and the high surface area offers easy accessibility of the reactants to a large number of active sites.
Keywords: heterogeneous catalysis; heterojunctions; plasmon effect; Silver; solar energy conversion; Solar hydrogen

Elucidating the effect of CaF2 on structure, biocompatibility and antibacterial properties of S53P4 glass (vol 831, 154704, 2020) - Prasad, Sakthi; Ganisetti, Sudheer; Jana, Anuradha; Kant, Shashi; Sinha, P. K.; Tripathy, Sucheta; Illath, Kavya; Ajithkumar, T. G.; Annapurna, K.; Allu, Amarnath R.; Biswas, Kaushik (Journal of Alloys and Compounds, 2021)

Elucidating the effect of solid base on the hydrogenation of C5 and C6 sugars over Pt–Sn bimetallic catalyst at room temperature - Tathod, Anup P.; Dhepe, Paresh L. (Carbohydrate Research, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Conversion of sugars into <a class="topic-link" href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/sugar-alcohols" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about sugar alcohols from ScienceDirect's AI-generated Topic Pages">sugar alcohols at room temperature with exceedingly high yields are achieved over Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst in the presence of calcined <a class="topic-link" href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/hydrotalcite" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about hydrotalcite from ScienceDirect's AI-generated Topic Pages">hydrotalcite. pH of the reaction mixture significantly affects the conversion and selectivity for sugar alcohols. Selection of a suitable base is the key to achieve optimum yields. Various solid bases in combination with Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalysts were evaluated for hydrogenation of sugars. Amongst all combinations, the mixture (1:1 <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">wt/wt<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) of Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and calcined hydrotalcite showed the best results. Hydrotalcite helps to make the pH of reaction mixture alkaline at which sugar molecules undergo ring opening. The sugar molecule in open chain form has <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/carbonyl-group" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about carbonyl group from ScienceDirect's AI-generated Topic Pages">carbonyl group which can be polarized by Sn in Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and Pt facilitates the hydrogenation. In the current work, effect of both; solid base and Sn as a promoter has been studied to improve the yields of sugar alcohols from various C5 and C6 sugars at very mild reaction conditions.
Keywords: Bimetallic catalyst; Hydrogenation; Hydrotalcites; Sugar; Sugar alcohols

Emergence of cooperatively reorganizing cluster and super-Arrhenius dynamics of fragile supercooled liquids - Singh, Ankit; Bhattacharyya, Sarika Maitra; Singh, Yashwant (Physical Review E, 2021)
In this paper, we develop a theory to calculate the structural relaxation time tau(alpha) of fragile supercooled liquids. Using the information of the configurational entropy and structure, we calculate the number of dynamically free, metastable, and stable neighbors around a central particle. In supercooled liquids, the cooperatively reorganizing clusters (CRCs) in which the stable neighbors form ``stable'' nonchemical bonds with the central particle emerge. For an event of relaxation to take place, these bonds have to reorganize irreversibly; the energy involved in the processes is the effective activation energy of relaxation. The theory brings forth a temperature T-a and a temperature-dependent parameter psi(T) which characterize slowing down of dynamics on cooling. It is shown that the value of psi(T) is equal to 1 for T > T-a, indicating that the underlying microscopic mechanism of relaxation is dominated by the entropy-driven processes, while for T < T-a, psi(T ) decreases on cooling, indicating the emergence of the energy-driven processes. This crossover of psi(T) from high to low temperatures explains the crossover seen in tau(alpha). The dynamics of systems that may have similar static structure but very different dynamics can be understood in terms of psi(T). We present results for the Kob-Anderson model for three densities and show that the calculated values of tau(alpha) are in excellent agreement with simulation values for all densities. We also show that when psi(T), tau(alpha), and other quantities are plotted as a function of T/T-a, (or Ta/T), the data collapse on master curves.

Enantioselective reduction of ketones and synthesis of 2-methyl-2,3-dihydro-1-benzofuran catalyzed by chiral spiroborate ester - Patil, H. S.; Nikalje, M. D.; Chopade, A. U.; Chopade, M. U. (Russian Journal of Organic Chemistry, 2021)
Asymmetric reduction of homobenzylic ketones was achieved through the use of chiral spiroborate ester catalyst. The catalyst is applicable for both analytical and industrial purposes since it is not sensitive to air and moisture. A rapid synthetic route has been developed for the preparation of (S)-2-methyl-2,3-dihydro-1-benzofuran via enantioselective reduction of homobenzylic ketone in the presence of a chiral spiroborate catalyst as the key step.
Keywords: 2-methyl-2; 3-dihydro-1-benzofuran; asymmetric reduction; spiroborate ester

Enantioselective separation using chiral amino acid functionalized polyfluorene coated on mesoporous anodic aluminum oxide membranes (vol 92, pg 6850, 2020) - Nikam, Shrikant B.; Asha, S. K. (Analytical Chemistry, 2021)

Enantioselective synthesis of 5,6-dihydroindolizines by N-heterocyclic carbene (NHC)-catalyzed core-structure-inspired strategy of azolium-enolate cascade - Ghosh, Arghya; Shee, Sayan; Barik, Shilpa; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2021)
The core-structure motivated design has allowed the enantioselective synthesis of 5,6-dihydroindolizines via N-heterocyclic carbene (NHC) catalysis. The NHC-catalyzed reaction of alpha,beta-unsaturated aldehydes with the suitably substituted pyrrole derivatives proceed via the initial generation of alpha,beta-unsaturated acylazoliums from enals, and enolates from pyrroles and the reaction culminated in an efficient cascade process involving the Michael-aldol-lactonization-decarboxylation sequence to afford the products in reasonable yields and high selectivities. The method is further extended to the construction of spirocyclic 5,6-dihydroindolizines.

Energy and life cycle impact assessment for xylitol production from corncob - Dasgupta, Diptarka; Sidana, Arushdeep; Ghosh, Prasenjit; Sharma, Tripti; Singh, Jasvinder; Prabhune, Asmita; More, Snehal; Bhaskar, Thallada; Ghosh, Debashish (Journal of Cleaner Production, 2021)
The conversion of biobased feedstocks into energy and value-added chemicals is one main approach to address the current global challenge for waste mitigation through the biorefinery mode. Corncob biomass which is one of the most abundant agricultural residue in India with a high hemicellulose content, can serve as a potential low-cost raw material for food-grade xylitol production. The present study demonstrates a process for xylitol production from corncob biomass with detailed energy and life cycle analysis for viability assessment. The major highlight of the process is the use of microbial fermentation, where biomass-derived D-xylose is converted to xylitol with high selectivity. Overall, 0.502 kg of xylitol crystals could be produced from 3.5 kg of corncob biomass. Simulation analysis revealed that the evaporators are the primary consumers of energy, and the process of heat integration can significantly reduce the energy requirements of the overall process. Environmental impacts of the system evaluated showed emission results of 8.68 kg CO2 equivalent and revealed that marine aquatic and freshwater eco-toxicity are the only possible contributors to the environment. The results suggest that the process would have favourable energy balances, which can be used in pilot plant and heat exchanger network design and operation for xylitol production scale up to 500 L. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: biomass valorization; Life cycle impact assessment; simulation; xylitol

Engineering microstructure of LiFe(MoO4)(2) as an advanced anode material for rechargeable lithium-ion battery - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Dwivedi, Pravin Kumari; Praveen, C. S.; Karbhal, Indrapal; Shelke, V, Manjusha; Kim, Bomyung; Park, Chinho; Kale, Bharat B. (Journal of Materials Science-Materials In Electronics, 2021)
Graphite is considered as an ideal anode material for lithium-ion battery (LIB) due to its high stability, good conductivity and wide source of availability. However, the low energy density and theoretical capacity of graphite cannot meet the needs of high performance anode materials. To circumvent this issue, alternative materials have been sought for many years now. Herein, we report the synthesis of highly crystalline lithium iron molybdate LiFe(MoO4)(2) by combustion method and evaluated its performance as an anode material for lithium-ion batteries. Triclinic LiFe(MoO4)(2) crystals having particle size 2-5 mu m with good crystallinity were obtained. The material shows long cycle life and high rate performance than commercial graphite and exhibits first reversible discharge capacity of 931.6 mAh/g at a current density of 100 mA/g which is three times higher than commercial graphite. The high specific capacity together with the outstanding rate and cycle performance makes LiFe(MoO4)(2) a promising anode material for LIB. A detailed analysis on the crystal structure and electronic properties of LiFe(MoO4)(2) is presented based on DFT studies to complement the experimental observations.

Enhanced electrocatalytic activity of PtRu/nitrogen and sulphur co-doped crumbled graphene in acid and alkaline media - Pang, Liuqing; Miao, Yuanyuan; Bhange, Siddheshwar N.; Barras, Alexandre; Addad, Ahmed; Roussel, Pascal; Amin, Mohammed A.; Kurungot, Sreekumar; Szunerits, Sabine; Boukherroub, Rabah (Journal of Colloid and Interface Science, 2021)
The low mass activity and high price of pure platinum (Pt)-based catalysts predominantly limit their large-scale utilization in electrocatalysis. Therefore, the reduction of Pt amount while preserving the electrocatalytic efficiency represents a viable alternative. In this work, we prepared new PtRu2 nanoparticles supported on sulphur and nitrogen co-doped crumbled graphene with trace amounts of iron (PtRu2/PF) electrocatalysts. The PtRu2/PF catalysts exhibited enhanced electrocatalytic performance and stability for the hydrogen evolution reaction (HER) at pH = 0. Moreover, the prepared PtRu2/PF electrocatalyst displayed higher HER activity than commercial 20% Pt/C. The PtRu2/PF catalyst achieved a current density of 10 mA cm(-2) at an overpotential value of only 22 mV for HER, performing better activity than many other Pt-based electrocatalysts. Besides, the PtRu2/PF revealed a good performance for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline media. The PtRu2/PF catalyst recorded a current density of 10 mA cm(-2) at an overpotential of only 270 mV for OER in KOH (1.0 M) solution and an onset potential of 0.96 V vs. RHE (at 1 mA cm(-2)) for ORR in KOH (0.1 M) solution. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: HER; OER; ORR; PtRu2; Sulphur and nitrogen co-doped crumbled graphene

Enhanced one-pot selective conversion of cellulose to ethylene glycol over NaZSM-5 supported metal catalysts - Sreekantan, Sreejith; Kirali, Arun Arunima; Marimuthu, Banu (New Journal of Chemistry, 2021)
The mesopores interconnected with microporous NaZSM-5 was synthesised by sol-gel method. Reactions involving cellulose using different bimetallic and trimetallic combinations of nickel, aluminium, and tungsten metals supported on NaZSM-5 have been carried out. Different weight percentages (wt%) of Al, Ni, and W were loaded onto the NaZSM-5 support via a wet impregnation method. The prepared catalysts were characterized using PXRD, FE-SEM, HR-TEM, BET, and XPS studies to investigate the presence of mesopores, the textural properties, the metal loading, and the active oxidation states. The catalytic activities of the xAl-yNi-zW/NaZSM-5 (where x, y, and z are the wt% values of Al, Ni, and W, respectively) supported catalysts were studied during the one-pot conversion of cellulose into ethylene glycol at 220 degrees C and with a pressure of 70 bar H-2 (at the reaction temperature) in water (as a solvent). The 5%Al-8%Ni-25%W/NaZSM-5 catalyst exhibited the highest cellulose conversion of 100%, with an ethylene glycol yield as high as 89% (C mol%) under moderate reaction conditions being reported for the first time. Al3+ in the catalyst hydrolyzed cellulose, and W5+ species acted as acid centres that facilitated the retro-aldol condensation reaction and eventually led to an increased EG yield in the presence of Ni. The catalyst was moderately stable after four consecutive runs for 6 h at 220 degrees C and at a H-2 reaction pressure of 70 bar, though a 12 h reaction resulted in the highest EG yield. The high yields under moderate reaction conditions promise an energy-efficient and economically feasible process.

Enhanced photocatalytic properties of a chemically modified blue phosphorene - Maibam, Ashakiran; Das, Sawan Kumar; Samal, Pragnya Paramita; Krishnamurty, Sailaja (RSC Advances, 2021)
It is high time to placate the peak demand for an efficient, economic and green fuel in the form of H-2 through photocatalytic water splitting. Several low dimensional materials have been explored for their photocatalytic properties on account of their surface to volume ratio. The present study illustrates the excellent photocatalytic potential of a two-dimensional material, viz. a chemically tempered blue-phosphorene sheet, with single atom thickness and high carrier mobility. Metal-free element, sulphur, is explored as a dopant in a 32-atom blue-phosphorene sheet. The dopant is inserted at three locations viz. central, edge and central edge positions with varying concentrations from 3.125% to 18.75% (corresponding to n = 1 to 6 sulphur atoms within a 32-atom blue-phosphorene sheet, P32-nSn). The cohesive energy studies predict the higher stability of even number S doped sheets as compared to their odd counterparts. Photocatalytic activity is studied in terms of band gap and band alignment for different concentrations of the former. Studies reveal that edge doping demonstrates better water molecule activation independent of S atom concentration. The edge doped systems not only provide the chemical activity to activate water, but also show feasible HER overpotentials of 1.24-1.29 eV at neutral medium. Finally, this work opens up a driving lead of non-corrosive catalysts for water molecule splitting.

Enhanced photoelectrochemical cell performance of Co doped ZnO nanoparticles sensitized by affordable mixed dyes as sensitizer - Kumbhar, Deepak; Kumbhar, Sarita; Dhodamani, Anant; Delekar, Sagar; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Inorganic and Nano-Metal Chemistry, 2021)
In the present investigation, a simple sol-gel approach has been employed for the synthesis of hexagonal wurtzite ZnO nanoparticles (NPs). X-ray diffraction (XRD) rietveld study and Raman analysis reveal the mislaid of the mixed phases of ZnO NPs after doping. The scanning electron micrographs and transmission electron microscopy confirm the formation of hexagonal disk-shaped NPs. FTIR, PL, EDX, XPS validate optical and stoichiometric concentration of Co in ZnO lattice. UV-visible DRS study shows absorption edge with humps to the red region of the spectrum with increasing the absorption strength and shortening of band gap as the content of Co (II) increases. Finally, the prepared samples were coated on the surface of cleaned FTO substrate through a simple doctor blade technique and sensitized with prepared dye. The ZnO photoanode shows 0.036% of efficiency (eta%) while the photoanodes of Co doped samples expose the enhanced efficiencies of 0.29%, 0.389%, 0.089%.
Keywords: Co doped ZnO; mixed dyes as sensitizer; Photoelectrochemical cell; sol-gel

Enhanced solubility, permeability, and tabletability of nicorandil by salt and cocrystal formation - Mannava, M. K. Chaitanya; Gunnam, Anilkumar; Lodagekar, Anurag; Shastri, Nalini R.; Nangia, Ashwini K.; Solomon, K. Anand (Crystengcomm, 2021)
Cocrystallization is a rational selection crystal engineering approach for the development of novel solid forms with enhanced physicochemical and mechanical properties. Nicorandil (NCR) is a niacinamide vitamin derivative used to treat angina pectoris. A binary solid form screen of NCR with homologous dicarboxylic acids afforded NCR-oxalic acid (NCR-OA, 1:1), NCR-fumaric acid (NCR-FA, 1:1), NCR-succinic acid (NCR-SA, 1:1), and NCR-suberic acid (NCR-SBA, 1:0.5). The binary solids were characterized by powder X-ray diffraction, IR and NMR spectroscopy, and DSC. NCR-FA and NCR-SBA were crystallized by slow evaporation from chloroform and toluene solvents, respectively. Single crystal X-ray diffraction confirmed that NCR-FA is a molecular salt, while NCR-SBA is a neutral cocrystal. NCR and the FA anion are connected via the robust carbovlate-pyridinium synthon, whereas in the NCR-SBA cocrystal, the components associate via the carboxylic acid- -pyridine synthon. The phase stability, solubility, dissolution rate, diffusion rate and tabletability studies have demonstrated that the binary solids exhibit improved physical and mechanical properties compared to the NCR drug. Specifically, the NCR-FA salt and NCR-SBA cocrystal have higher solubility, dissolution rate, and hardness at lower pressures, making the formulation suitable for tablet compression.

Entacapone polymorphs: crystal structures, dissolution, permeability, and stability - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Rai, Sunil K.; Suresh, Kuthuru; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
Entacapone (ETP) is a catechol-O-methyltransferase (COMT) drug used to treat Parkinson's disease. ETP is available in the marketplace under the brand name Comtan since 2010, and ETP form-I was first reported in a patent published in 2001. However, analysis of its Xray crystal structures and stability relationship of ETP polymorphs and their dissolution and permeability profile have not yet been reported. We crystallized two new conformational polymorphs of ETP from a water and acetone mixture and studied the structural origin of polymorphism and their phase transformations, stability, equilibrium solubility, dissolution, and permeability properties. The ETP molecule adopts different conformations in the polymorphic structures with slight changes in carbonyl and nitrile group orientations. Thermal analysis suggests that form-III and form-IV are enantiotropically related to form-I, which is the thermodynamically stable form at ambient conditions. In contrast, form-II is monotropically related to form-I. Equilibrium solubility, dissolution, and permeability studies show that form-II persists in the slurry medium and dissolves faster with a high flux rate compared to the stable form-I in phosphate buffer solution at 37 +/- 0.5 degrees C.

Epigallocatechin-3-gallate modulates tau post-translational modifications and cytoskeletal network - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Oncotarget, 2021)
BACKGROUND: Alzheimer's disease is a type of dementia denoted by progressive neuronal death due to the accumulation of proteinaceous aggregates of Tau. Post-translational modifications like hyperphosphorylation, truncation, glycation, etc. play a pivotal role in Tau pathogenesis. Glycation of Tau aids in paired helical filament formation and abates its microtubule-binding function. The chemical modulators of Tau PTMs, such as kinase inhibitors and antibody-based therapeutics, have been developed, but natural compounds, as modulators of Tau PTMs are not much explored. MATERIALS AND METHODS: We applied biophysical and biochemical techniques like fluorescence kinetics, oligomerization analysis and transmission electron microscopy to investigate the impact of EGCG on Tau glycation in vitro. The effect of glycation on cytoskeleton instability and its EGCG-mediated rescue were studied by immunofluorescence microscopy in neuroblastoma cells. RESULTS: EGCG inhibited methyl glyoxal (MG)-induced Tau glycation in vitro. EGCG potently inhibited MG-induced advanced glycation endproducts formation in neuroblastoma cells as well modulated the localization of AT100 phosphorylated Tau in the cells. In addition to preventing the glycation, EGCG enhanced actin-rich neuritic extensions and rescued actin and tubulin cytoskeleton severely disrupted by MG. EGCG maintained the integrity of the Microtubule Organizing Center (MTOC) stabilized microtubules by Microtubule-associated protein RP/EB family member 1 (EB1). CONCLUSIONS: We report EGCG, a green tea polyphenol, as a modulator of in vitro methylglyoxal-induced Tau glycation and its impact on reducing advanced glycation end products in neuroblastoma cells. We unravel unprecedented function of EGCG in remodeling neuronal cytoskeletal integrity.
Keywords: Alzheimer’s disease; tau glycation; Tau glycation inhibition; tau protein; Tau PTMs

Estimation of reaction kinetics for aromatic and heterocycles nitration in mixed acids through computational chemistry approach - Jadhav, Pandurang M.; Pandey, Raj K.; Kulkarni, Amol A. (International Journal of Chemical Kinetics, 2021)
Nitration of aromatic compounds and heterocycles in mixed acid environment is one of the regularly performed large-scale reactions in the chemical industry. Although the reaction mechanism of nitration of aromatics in mixed acid is well established, the development of a methodology for the evaluation of kinetics of exothermic aromatic nitrations in a simplified and accurate way is necessary. Here we evaluate the applicability of a kinetic evaluation methodology based on Hammett's acidity function, acidity function, and empirical activity coefficient for the nitration reaction. The contributions from the functional groups on the aromatic ring and quantitative structure-activity relationships technique are considered for these evaluations. Natural bond orbital and magnetic index nucleus independent chemical shift analyses were carried out to obtain the substitution constants. The rate constant and activation energy values were evaluated at various temperatures and sulfuric acid strengths. The results were validated by comparing with the experimental data from the literature for several molecules. The effect of various functional groups (viz carbonyl, carboxyl, methyl, and amine) substituted on the benzene ring was also evaluated. For a few identified substrates, the data were used for estimation of residence time needed for complete conversion in continuous stirred tank reactor and in a plug flow reactor to quantify the effect of substitution constant and strength of sulfuric acid. The approach will help select a suitable reactor.
Keywords: Aromatic nitration; computational chemistry; Hammett analogy; mixed acids; Reaction kinetics; reactor selection

Evaluation of biocompatibility of synthesized low molecular weight PLGA copolymers using zinc L-proline through green route for biomedical application - Giram, Prabhanjan S.; Garnaik, Baijayantimala (Polymers for Advanced Technologies, 2021)
Poly(lactide-co-glycolide) (PLGA) copolymers were synthesized by ring opening polymerization in presence of zinc proline and stannous octoate in bulk through green route and were designated as PLGA-1 and PLGA-2 respectively. These copolymers were characterized using NMR, SEC, DSC, X-ray and MALDI-TOF analysis. For the first time, the low molecular weight of PLGA (similar to 11,000 Da) was mainly targeted to explore acute oral toxicity in the presence of zinc L-proline and stannous octoate. The haemolysis and cell viability assay were carried out for in-vitro cytotoxicity assessment. Haemolysis assay of PLGA-2 was confirmed and haemolytic potential exceeded limit of American society of testing of material standard. The cell viability study using fibroblast cell lines (NIH3T3), exhibited statistically significant difference in results between PLGA-1 and PLGA-2. The acute toxicity study was performed in Balb/c mice for biomarker, hematological and histopathological analysis. No mortality was observed during the entire observation period, and no macroscopic change of the organs was observed in PLGA-1 treated group where PLGA-2 treated group showed sign of toxicity. The results obtained from in-vitro and in-vivo studies suggested that PLGA-2 was toxic whereas PLGA-1 was nontoxic in nature. Therefore, PLGA-1 can be regarded as biocompatible biomaterials for potential for drug delivery and biomedical application.
Keywords: OECD-420; poly (lactide-co-glycolide); ring opening polymerization; Stannous octoate; zinc L-Proline

Evidence of an nN(amide) → π*Ar interaction in N-Alkyl-N,N′-diacylhydrazines - Deka, Jugal Kishore Rai; Sahariah, Biswajit; Sakpal, Sushil S.; Bar, Arun Kumar; Bagchi, Sayan; Sarma, Bani Kanta (Organic letters, 2021)
1,2-Dibenzoyl-1-tert-butylhydrazine (RH-5849) and related N-alkyl-N,N′-diacylhydrazines are environmentally benign insect growth regulators. Herein, we show that an unusual n<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">N(amide) → π*<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">Ar interaction mediated by a hydrazide amide nitrogen atom plays a crucial role in stabilizing their biologically active trans–cis (t–c) rotameric conformations. We provide NMR and IR spectroscopic evidence for the presence of these interactions, which is also supported by X-ray crystallographic and computational studies.

Exceptional capacitance enhancement of a non-conducting COF through potential-driven chemical modulation by redox electrolyte - Kushwaha, Rinku; Haldar, Sattwick; Shekhar, Pragalbh; Krishnan, Akshara; Saha, Jayeeta; Hui, Pramiti; Vinod, Chathakudath Prabhakaran; Subramaniam, Chandramouli; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2021)
Capacitors are the most practical high-storage and rapid charge-release devices. The number of ions stored per unit area and their interaction strength with the electrode dictates capacitor-performance. Microporous materials provide a high storage surface and optimal interactions. Adsorbing electron-rich and easily polarizable molecules into microporous electrodes is expected to boost Faradaic pseudo-activity. If such electrode-electrolyte interactions can be made as a potential-driven reversible process, the resulting capacitors would be adaptable and device-friendly. A composite covalent organic framework (COF)-carbon electrode with redox-active KI is combined in an H2SO4 electrolyte for the first time. This composite electrode benefits from the redox-functionality of COF and electronic conductivity of carbon, leading to superior capacitative activity. Operando spectro-electrochemical measurements reveal the existence of multiple polyiodide species, although the I-3(-) is the predominantly electroactive species adsorbing on the microporous triazine-phenol COF electrode. A systematic fabrication of the flexible solid-state devices using the COF-redox-electrolyte reveals a high areal capacitance of 270 +/- 11 mF cm(-2) and gravimetric capacitance of 57 +/- 8 F g(-1). The inclusion of KI in H2SO4 (electrolyte) yields an approximately eight-fold enhancement in solid-state gravimetric specific capacitance. The imine-COF retains 89% of its capacity even after 10 000 cycles.
Keywords: covalent organic frameworks; polyiodide; redox electrolytes; solid‐ state capacitors; Supercapacitors

Excimer to exciplex transition through realization of donor-acceptor interactions in luminescent solvent-free liquids - Wakchaure, Vivek Chandrakant; Goudappagouda; Das, Tamal; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Nanoscale, 2021)
Luminescent solvent-free organic liquids are known for their enhanced quantum yield, color tunability, and availability of a matrix for other dopants to generate hybrid luminescent materials with improved features for newer applications. Herein, we report a donor-acceptor based luminescent ``exciplex liquid'' by utilizing the slightly different electron affinity of the acceptor molecules. A red-shifted broad exciplex emission exhibited by the donor-acceptor pair even at a lower concentration of the acceptor (0.001 equiv.) indicates high efficiency in the solvent-free state. A detailed NMR study revealed weak intermolecular interactions between the donor and acceptor in the solvent-free matrix that stabilizes the exciplex liquid. The failure of structurally similar solid counterparts to form an exciplex confirms the advantage of the available supportive liquid matrix. Besides, the luminescent exciplex liquid is found efficient in sensing application, which is unachievable by either the individual liquids or their solid counterparts. Here, a transition of a donor-acceptor pair from a solid to solvent-free liquid results in a new hybrid liquid that can be an alternative for solid sensor materials.

Exploring edge functionalised blue phosphorene nanoribbons as novel photocatalysts for water splitting - Maibam, Ashakiran; Chakraborty, Debalina; Joshi, Krati; Krishnamurty, Sailaja (New Journal of Chemistry, 2021)
Hydrogen gas, a highly combustible and eco-friendly fuel is stealing the limelight and its production is one of the major areas of research. An efficient and green method for producing clean hydrogen gas with no harmful by-product is water splitting. With the introduction of low dimensional materials, water splitting has become an easier and cost-effective process. The present work demonstrates the application of one such low dimensional material viz., edge functionalised Blue Phosphorene Nano-Ribbons (BPNRs) as potential photocatalysts. With a carrier mobility of 10(3) cm(2) V-1 s(-1) and a band gap of 1.5-3.0 eV, BPNRs are an attractive candidate for photocatalysis. BPNRs with different edge oreintations, viz. zigzag and armchair are functionalised with CH3O, COOCH3, CHO, COOH, OH, NH2, CONH2, SH, C6H5, and NO2 groups. Their performance towards activating water molecules at different sites on the nanoribbon is studied. The functionalised edges of the BPNRs are the active sites showing similar to 1.2% to 3.2% efficiency in activating the O-H bond of the water molecule. Among the different groups explored, CONH2 functionalised zigzag BPNR clearly exhibits a higher potential towards the adsorption of water molecules (-0.98 eV) and activation of O-H bonds with an elongation of 3.2% and a red shift of 500.6 cm(-1). This is attributed to the lone pair of electrons on the nitrogen atom contributing to the electron donating nature of the CONH2 functional group.

Expression, purification and crystallization of Asrij, A novel scaffold transmembrane protein - Motiwala, Zenia; Darne, Priti; Prabhune, Asmita; Inamdar, Maneesha S.; Kulkarni, Kiran (Journal of Membrane Biology, 2021)
Asrij/OCIAD1 is a scaffold transmembrane protein belonging to the Ovarian Carcinoma Immunoreactive Antigen Domain containing protein family. In Drosophila and mouse models, Asrij localizes at the endosomal and mitochondrial membrane and is shown to regulate the stemness of hematopoietic stem cells. Interaction of Asrij with ADP Ribosylation Factor 1 (Arf1) is shown to be crucial for hematopoietic niche function and prohemocyte maintenance. Here, we report the heterologous expression, standardization of detergents and purification methodologies for crystallization of Asrij/OCIAD1. To probe the activity of bacterially expressed Asrij, we developed a protein complementation assay and conclusively show that Asrij and Arf1 physically interact. Further, we find that sophorolipids improve the solubility and monodispersibility of Asrij. Hence, we propose that sophorolipids could be novel additives for stabilization of membrane proteins. To our knowledge, this is the first study detailing methodology for the production and crystallization of a heterologously expressed scaffold membrane protein and will be widely applicable to understand membrane protein structure and function. Graphic
Keywords: Asrij/OCIAD1; Membrane protein crystallography; sophorolipids

Extracellular HDAC6 ZnF UBP domain modulates the actin network and post-translational modifications of Tau - Balmik, Abhishek Ankur; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Background: Microtubule-associated protein Tau undergoes aggregation in Alzheimer`s disease (AD) and a group of other related diseases collectively known as Tauopathies. In AD, Tau forms aggregates, which are deposited intracellularly as neurofibrillary tangles. Histone deacetylase-6 (HDAC6) plays an important role in aggresome formation, where it recruits polyubiquitinated aggregates to the motor protein dynein. Methods: Here, we have studied the effects of HDAC6 ZnF UBP on Tau phosphorylation, ApoE localization, GSK-3 beta regulation and cytoskeletal organization in neuronal cells by immunocytochemical analysis. This analysis reveals that the cell exposure to the UBP-type zinc finger domain of HDAC6 (HDAC6 ZnF UBP) can modulate Tau phosphorylation and actin cytoskeleton organization. Results: HDAC6 ZnF UBP treatment to cells did not affect their viability and resulted in enhanced neurite extension and formation of structures similar to podosomes, lamellipodia and podonuts suggesting the role of this domain in actin re-organization. Also, HDAC6 ZnF UBP treatment caused increase in nuclear localization of ApoE and tubulin localization in microtubule organizing centre (MTOC). Therefore, our studies suggest the regulatory role of this domain in different aspects of neurodegenerative diseases. Upon HDAC6 ZnF UBP treatment, inactive phosphorylated form of GSK-3 beta increases without any change in total GSK-3 beta level. Conclusions: HDAC6 ZnF UBP was found to be involved in cytoskeletal re-organization by modulating actin dynamics and tubulin localization. Overall, our study suggests that ZnF domain of HDAC6 performs various regulatory functions apart from its classical function in aggresome formation in protein misfolding diseases.
Keywords: Actin; Cytoskeleton; HDAC6; Microtubule; neurodegeneration; Phosphorylation; Podonut; Podosomes; Tau; Tauopathies

Effect of B site substitution in Gd2B2-xNiyO7-delta (B= Ti, Zr) ternary metal oxide catalysts in dry reforming of methane - Ghodke, Seema R.; Thundiyil, Shibin; Dongapure, Pavan; Devi, R. Nandini (Molecular Catalysis, 2022)
Structured catalysts are emerging as active and durable catalysts in dry reforming of methane due to their inherent characteristics like lattice insertion of active metals and consequent stability imparted. Here we report Ti and Zr substituted Gd2B2-xNiyO7-delta (B = Ti, Zr) catalysts synthesized by citrate gel method, which are characterized and tested for dry reforming of methane. Structure and Ni substitution has been confirmed by Rietveld refinement of powder XRD patterns and Raman analysis. TPR and CO2-TPD were performed to analyze the reducibility and effect of basic sites of catalysts in DRM activity. Ni doped Ti analogue shows stable and superior activity towards dry reforming of methane for 100 h. The in situ IR studies and XPS analysis confirmed the presence of surface hydroxyl species in this catalyst, which triggers the activation of CO2 and provides higher and durable activity in dry reforming reaction. Absence of any C formation in this catalyst after durability test indicates the mechanism of C gasification by the surface hydroxyl species enhancing stable activity for long durations.
Keywords: A(2)B(2)O(7); Citrate gel method; Dry reforming of methane; Ternary metal oxide

Effect of ionic interactions on crystallization of star telechelic poly (L-lactide) ionomers - Kulkarni, Amruta (Polymer, 2022)
Effect of ionic interactions on crystallization properties of star telechelic poly(L-lactide) ionomers was studied by performing isothermal crystallization experiments. We report a comparison between star PLLA and star telechelic PLLA ionomer. It was evident that the ionic interactions in the ionomer affected the crystallization rate as well as modified the spherulitic morphology. Employing Avrami analysis on the isothermal crystallization data we show that star PLLA shows faster crystallization at higher temperatures (closer to melting point) than the star PLLA ionomer. However, a reversal of this trend in crystallization is observed at lower temperatures (closer to glass transition temperature). The origin of high temperatures behaviour comparison is explained in terms of the higher secondary nucleation barrier for ionomers using the famous Lauritzen- Hoffman secondary nucleation theory. However, we point out that the assumption of equal diffusion barrier in this theory limits its range of applicability. In order to explain the low temperature behaviour, we invoke the activation energy comparison in PLLA and ionomer using rheological studies. We show that although the presence of ions in the polymer impede the secondary nucleation process, its effect is only observed at higher temperatures.
Keywords: Crystallization; Ionomer; Poly( L -lactide); Star polymer; Telechelic

Effect of oxalic acid and sulphuric acid hydrolysis on the preparation and properties of pineapple pomace derived cellulose nanofibers and nanopapers - Neenu, K. V.; Dominic, C. D. Midhun; Begum, P. M. Sabura; Parameswaranpillai, Jyotishkumar; Kanoth, Bipinbal Parambath; David, Deepthi Anna; Sajadi, S. Mohammad; Dhanyasree, P.; Ajithkumar, T. G.; Badawi, Michael (International Journal of Biological Macromolecules, 2022)
Nanocellulose is the ``green magnet'' which attracts a wide spectrum of industries towards it due to its availability, biodegradability, and possible smart applications. For the first time, pineapple pomace was being explored as an economic precursor for cellulose nanofibers. Nanofiber isolation was accomplished using a chemo-mechanical method and solution casting was adopted for the development of nanopapers. Moreover, the study examines the structural, optical, crystalline, dimensional, and thermal features of nanofibers isolated using different acid hydrolysis (oxalic acid and sulphuric acid) methods. Fourier-transform infra-red spectroscopy, 13C solid-state nuclear magnetic resonance spectroscopy, and X-ray diffraction analysis indicated the presence of type I cellulose. The transmittance, crystallinity index, and thermal stability of PPNFS (sulphuric acid treated fiber) were greater than PPNFO (oxalic acid treated fiber). The transmission electron microscopy and dynamic light scattering analysis confirmed the nanodimension of PPNFO and PPNFS. While comparing the optical and mechanical properties of nanopapers, PPNFS outperforms PPNFO. The tensile strength of the prepared nanopapers (64 MPa (PPNFO) and 68 MPa (PPNFS)) was found to be high compared to similar works reported in the literature. The prepared nanopaper is proposed to be used for food packaging applications.
Keywords: cellulose nanofibers; Cellulosic nanopapers; Pineapple pomace

The effects of cis and trans butenedioic acid on the physicochemical behavior of lumefantrine - Tomar, Devendrasingh; Lodagekar, Anurag; Gunnam, Anilkumar; Allu, Suryanarayana; Chavan, Rahul B.; Tharkar, Minakshi; Ajithkumar, T. G.; Nangia, Ashwini K.; Shastri, Nalini R. (Crystengcomm, 2022)
The present work investigates the effects of cis and trans butenedioic acid isomers (maleic acid and fumaric acid) on the crystallinity and pharmaceutical behavior of lumefantrine. Differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), attenuated total reflectance infrared spectroscopy (ATR-IR), solid-state nuclear magnetic resonance spectroscopy (ss-NMR), and single-crystal X-ray diffraction (SC-XRD) studies were employed. Lumefantrine-fumaric acid crystallized as a salt in the monoclinic space group P2(1)/c. In comparison, DSC and PXRD showed the formation of a co-amorphous solid with maleic acid. Complete proton transfer with a strong ionic interaction led to crystalline salt formation with the trans isomer, whereas weaker/fewer hydrogen bonds with the cis isomer of butenedioic acid led to a co-amorphous salt. The in vitro dissolution of both salts resulted in a similar 2.6-2.7-fold improvement in dissolution rate when compared to that of the crystalline lumefantrine. The crystalline and co-amorphous salts were stable under accelerated stability conditions (40 +/- 2 degrees C and 75 +/- 5% RH) for one month.

Efficient cascade C-N coupling reactions catalyzed by a recyclable MoOx/ Nb2O5 nanomaterial for valuable N-heterocycles synthesis - Singh, Nittan; Kalbande, Pavan Narayan; Umbarkar, Shubhangi; Sudarsanam, Putla (Molecular Catalysis, 2022)
The efficient cascade synthesis of pharmaceutically valuable N-heterocycles at solvent-free conditions was achieved using a robust, recyclable MoOx/Nb2O5 nanocatalyst. The results of catalyst screening revealed that the MoOx/Nb2O5 nanorods, calcined at 500 degrees C (MoNb5), exhibit excellent catalytic activity in the oxidative coupling of benzylamine with 96.5% conversion and >99.6% selectivity to the desirable imine product. The uniform dispersion of Mo-oxide nanoparticles (average particle size: 5.2 +/- 0.5 nm) on shape-controlled Nb2O5 nanorods (width: 5.3 +/- 0.5 nm and length: 23-38 nm) in MoNb5 catalyst led to improved structural and acid properties, beneficial for the cascade C-N bond construction. The shape-controlled MoNb5 catalyst showed versatile activity in various cascade C-N coupling reactions to obtain 2-phenylbenzimidazole, 2-phenyl-quinaxoline, and 2-phenyl-2,3-dihydroquinazolin-4(1H)-one with good to excellent yields at solvent-free con-ditions. The optimum ratio of Lewis/Bronsted acid sites, the unique structure of Nb2O5 nanorods, and the strong MoO3-Nb2O5 interaction are the key reasons for the higher activity of MoNb5 catalyst. The efficient reusability of MoNb5 catalyst, its remarkable activity in diverse N-heterocycles synthesis, and efficient gram-scale synthesis emphasize its practical application for the cascade C-N coupling reactions under benign conditions.
Keywords: Acid sites optimization; Cascade C-N bond formation; Diverse nitrogenous chemicals; Heterogeneous nanosized catalyst; MoO3-Nb2O5 interaction; Nb2O5 nanorods

Efficient route to 3,3 `-biindolinylidene-diones by iron-catalyzed dimerization of isatins - Jagtap, Rahul A.; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Iron-catalyzed dimerization of various isatin derivatives is described for the efficient synthesis of 3,3 `-biindolinylidene-diones (isoindigos). The reaction provides easy access to self-coupled and cross-coupled 3,3 `-indolinylidene-diones that have high relevance to biology and materials. This Fe(0)- or Fe(II)-catalyzed dimerization reaction tolerates a wide range of functionalities, such as fluoro, chloro, bromo, alkenyl, nitrile, ether, ester, pyrrolyl, indolyl and carbazolyl groups, including cyclic and acyclic alkyls as well as an alkyl-bearing fatty-alcohol moiety. Especially, the coupling between two distinct isatins provided excellent selectivity for the cross-dimerization with trace of self-couplings. The single-crystal X-ray diffraction study established the molecular structure of eight dimerized products. A preliminary mechanistic study of the Fe-catalyzed dimerization supported the radical pathway for the reaction.
Keywords: Cross-coupling; dimerization; iron; Isatin; Isoindigo; Mechanism

Efficient synthesis of 5-(hydroxymethyl)furfural esters from polymeric carbohydrates using 5-(chloromethyl)furfural as a reactive intermediate - Bhat, Navya Subray; Hegde, Shobhita L.; Dutta, Saikat; Sudarsanam, Putla (ACS Sustainable Chemistry & Engineering, 2022)
This work reports an efficient, gram-scale synthesis of 5-(hydroxymethyl)furfural (HMF) esters using biomass-derived 5-(chloromethyl)furfural (CMF) as a reactive intermediate. The HMF-esters have potential applications as chemicalintermediates, fuel additives, and bioactive compounds. Initially, CMF was prepared in good yields directly from polymericcarbohydrates (starch, inulin, and cellulose) and cellulosic materials (cotton andfilter paper) using a biphasic batch reaction system,consisting of aqueous hydrochloric acid and 1,2-dichloroethane. The use of ZnCl2as an additive allowed the reaction to proceedunder milder conditions while significantly improving the isolated yield of CMF. The effects of reaction temperature, reaction time,extracting solvent, and ZnCl2loading on CMF yield were investigated. Microcrystalline cellulose was converted into CMF with a72% isolated yield under optimized reaction conditions (80 degrees C, 2 h). After that, CMF was transformed into various novel esters ofHMF in excellent isolated yields (>85%) by reacting with a slight excess amount of the triethylammonium salt of various alkyl/arylcarboxylic acids under solvent-free conditions
Keywords: catalysis; cellulose; furanics; HMF-esters; renewable synthesis

Electrocatalytic alcohol oxidation by a molecular iron complex - Kuiry, Himangshu; Das, Debasree; Das, Soumadip; Chakraborty, Soham; Chandra, Bittu; Sen Gupta, Sayam (Faraday Discussions, 2022)
An efficient electrochemical method for the selective oxidation of alcohols to their corresponding aldehydes/ketones using a biomimetic iron complex, [(bTAML)Fe-III-OH2](-), as the redox mediator in an undivided electrochemical cell with inexpensive carbon and nickel electrodes using water as an oxygen source is reported. The substrate scope also includes alcohols that contain O and N heteroatoms in the scaffold, which are well tolerated under these reaction conditions. Mechanistic studies show the involvement of a high-valent Fe-V(O) species, [(bTAML)Fe-V(O)](-), formed via PCET (overall 2H(+)/2e(-)) from [(bTAML)Fe-III-OH2](-) at 0.77 V (vs. Fc(+)/Fc). Moreover, electrokinetic studies of the oxidation of C-H bonds indicate a second-order reaction, with the C-H abstraction by Fe-V(O) being the rate-determining step. The overall mechanism, studied using linear free energy relationships and radical clocks, indicates a ``net hydride'' transfer, leading to the oxidation of the alcohol to the corresponding aldehyde or ketone. When the reaction was carried out at pH > 11, the reaction could be carried out at a similar to 500 mV lower potential than that at pH 8, albeit with reduced reaction rates. The reactive intermediate involved at pH > 11 is the corresponding one-electron oxidized [(bTAML)Fe-IV(O)](2-) species.

Electrochemically tuned synergistic nano-interface of a tertiary Ni(OH)(2)-NiO(OH)/NixP heterojunction material for enhanced and durable alkaline water splitting - Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemistrySelect, 2022)
Making water splitting cheaper is the need of the hour.The present work reports a nickel-based, non-precious catalytic system, synthesized by a two-step electrodeposition (ED) process followed by a short-term heat treatment. The Ni(OH)(2)-NiO(OH)/NixP heterojunction has been synthesized and optimized through an unprecedented, energy-conserving method to achieve its best OER performance. Further, it has been carefully tuned for the first time by thoroughly optimizing the ED parameters to exhibit Hydrogen Evolution Reaction (HER). At high current regimes, the performance surpassed that of the Ru/C and Pt/C (>= 500 mA and >= 600 mA) respectively. The full cell electrolyzer configuring NOPO||NOPH further establishes the supremacy of the present electrocatalysts over the benchmark Ru/C||Pt/C. Moreover, the present electrocatalyst displayed 60 and 70 hours of HER and OER performances at -100 mA and 100 mA currents respectively. In short, this work is an example that illustrates how a single chemical system gets to exhibit two complementary catalytic behaviors that is, water oxidation and reduction when certain synthetic parameters are meticulously optimized.
Keywords: Electrodeposition; heterojunction; Ni(OH)(2)-NiO(OH); NixP; non-precious metal; water splitting

Electrodeposited layered sodium vanadyl phosphate (NaxVOPO4 center dot nH(2)O) as cathode material for aqueous rechargeable zinc metal batteries - Dilwale, Swati; Ghosh, Meena; Vijayakumar, Vidyanand; Kurungot, Sreekumar (Energy & Fuels, 2022)
Aqueous rechargeable zinc metal batteries (ARZMBs) present a safer and cost-effective solution for energy storage in stationary applications. However, a major challenge is the lack of suitable cathode materials simultaneously exhibiting high operating voltage and long cycling stability. Herein, we report the polyanionic sodium-intercalated layered vanadyl phosphate [NaxVOPO4 center dot nH(2)O (NVP)] as a suitable high-voltage and stable cathode for ARZMBs. This work employs a simpler electrochemical route (electrodeposition) for the synthesis of NVP over functionalized carbon fiber substrates and its application as a binder-free cathode in ARZMBs. The electrodeposited NVP possesses a morphology of vertically aligned well-separated nanosheet bundles resembling a flower. When used as the ARZMB cathode, the NVP electrode delivers a specific discharge capacity of 100 mA h g(-1) at 0.033 A g(-1) and high cycling stability (98% retention of the initial capacity over 1100 cycles at 0.333 A g(-1)) in a mild aqueous electrolyte with moderate zinc salt concentration. The observed electrochemical performance of NVP is credited to the synergistic effect of unique nanoflower morphology, the pillaring effect offered by the intercalated Na, and the intimate contact of the active material with the carbon fiber network. These factors are favorable for enhancing the transport of the electrolyte ions and electrons and maintaining the structural stability of the electrode during long-term cycling. The NVP electrode could also deliver appreciable performance (a discharge capacity of 73 mA h g(-) 1 and a current density of 0.033 A g(-1)) in quasi-solidstate ARZMB cells employing PVA/Zn(CF3SO3)(2) gel electrolyte.

Electronic structure evolution from metallic vanadium to metallic VxOy: a nappes study for o2+v gas-solid interaction - Ranjan, Ravi; Mhamane, Nitin B.; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2022)
Gas-solid interactions between molecular oxygen and metallic vanadium surfaces and the systematic evolution in the electronic structure of vanadium oxide (VOx) surfaces have been explored in the present work by near-ambient pressure photo-electron spectroscopy (NAPPES). The current article studies the evolution of various oxides of vanadium as a function of partial pressure of O2 (ultrahigh vacuum to 1 mbar), temperature (298- 875 K), and the exposure time to oxygen (up to 18 h). Valence -band (VB) and core-level spectral measurements recorded with UV (He-I = 21.2 eV) and Al K alpha (1486.6 eV) photons, respectively, show interesting changes. (1) Oxidation is limited to the top layers of vanadium at 298 K and up to a partial pressure of 1 mbar O2. About 50% of vanadium gets oxidized, and the remaining amount exists as metal within the top 10 nm. (2) Metallic vanadium disappears above 625 K, and it is predominantly oxidized to a mixture of V4+ and V5+ oxidation states at a 0.1 mbar partial pressure of O2. Points 1 and 2 suggest the predominantly thermodynamically controlled nature of vanadium oxidation through oxygen diffusion into the subsurface and bulk layers. (3) The Fermi-level (EF) feature observed first at >= 725 K at a 0.1 mbar O2 pressure demonstrates the formation of metallic VO2; however, its metallic nature is preserved even at ambient temperature due to interweaving nanodomains of VOx with VO2. (4) Only partial conversion of surface layers to V5+ (V2O5) along with VO2 and V2O3 (within the probing depth of 8-10 nm by near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS)) was observed even after prolonged heating (18 h) in 1 mbar O2 pressure. (5) The nature of the surface changes between metal and semiconducting/ insulator oxides is substantiated by the observation of changes in work function (phi) and EF features. Typical VB features and Fermi intensity of V-metal and vanadium oxides were observed, and the results were corroborated with core-level and VB spectra. The present results extend the capabilities of NAPPES to explore the electronic structure evolution as a function of reaction conditions and underscore its relevance to areas such as heterogeneous catalysis and sensing.

Electrospun zinc-manganese bimetallic oxide carbon nanofibers as freestanding supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Kim, Yongil; Kim, Taegun; El-Newehy, Mohamed; Aldalbahi, Ali; Yoon, Sam S. (International Journal of Energy Research, 2022)
Flexible, lightweight, and freestanding zinc-manganese oxide carbon nanofibers are promising materials for the fabrication of portable electronic devices. Composite nanofibers were synthesized using terephthalic acid and sodium dodecyl sulfate. Terephthalic acid improves the flexibility of the composite fibers and facilitates the diffusion of electrolytic ions. Meanwhile, sodium dodecyl sulfate aids to elevate the metal (zinc) oxide particles to the surface of the nanofibers during annealing. The texturing of the carbon nanofiber surface with ZnO enhances the electrochemical activity of the composite fibers. Parametric studies were conducted by varying the weight ratio of zinc and manganese acetates from zero to unity. The optimal case with a ratio of 0.75 produces specific capacitances of 1080 and 817 F center dot g(-1) at current densities of 1 and 10 A center dot g(-1), respectively, with a wide potential window of 1.6 V, indicating outstanding energy storage capabilities. The capacitance retention was 92% after 10 000 galvanostatic charge-discharge cycles. The bending angle test confirmed the mechanical durability of the freestanding carbon nanofiber electrodes, and the corresponding change in the cyclic voltammetry curve was negligible.
Keywords: electrospinning; freestanding electrode; high-energy-density; supercapacitor; ZnMn2O4

Elliptically birefringent chemically tuned liquid crystalline nanocellulose composites for photonic applications - Singh, Shiva; Bhardwaj, Shakshi; Verma, Chhavi; Chhajed, Monika; Balayan, Kajal; Ghosh, Kaushik; Maji, Pradip K. (Journal of Molecular Liquids, 2022)
Cellulose nanocrystals (CNCs) based photonic materials are one of the promising materials in the recent trends. The liquid crystalline behavior of the CNCs can be tailored to different advanced applications. The proposed research investigates the potential of CNCs as an optically active material. CNCs were tuned to hydroxypropyl nano cellulose (HPNC) with the degree of substitution 1.39. The prepared liquid crystalline HPNC were dispersed in various concentrations of monomethyl ether of polyethylene glycol to get waterborne materials with specific optical anisotropy. The extraction, modification, and morphology of the CNCs were investigated using NMR (Nuclear Magnetic Resonance), TEM (Transmission Electron Microscopy), XRD (X-ray Powder Diffraction), and FESEM (Field Emission Scanning Electron Microscopy) analysis. The prepared HPNC was analyzed using a hot stage POM (Polarized Optical Microscope) for optical anisotropy. The thermal stability of prepared CNCs and HPNC was also investigated. Upon optimization using rheology and POM, it was found that at the ratio of 1:1, HPNC (5 wt%) and mPEG (40 wt%) had the most distinct optical properties. The potential of the prepared materials can be further explored in sensing, smart coating, and security materials. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: bagasse; Cellulose nanocrystals; Elliptical birefringence; liquid crystals; optical anisotropy

Elucidating the influence of structure and Ag+ -Na+ ion-exchange on crack-resistance and ionic conductivity of Na3Al1.8Si1.65 P-1.8 O-12 glass electrolyte - Keshri, Shweta R.; Mandal, Indrajeet; Ganisetti, Sudheer; Kasimuthumaniyan, S.; Kumar, Rajesh; Gaddam, Anuraag; Shelke, Ankita; Ajithkumar, Thalasseril G.; Gosvami, Nitya Nand; Krishnan, N. M. Anoop; Allu, Amarnath R. (Acta Materialia, 2022)
Glasses are emerging as promising and efficient solid electrolytes for all-solid-state sodium-ion batteries. However, they still suffer from poor ionic conductivity and crack-resistance, which need to be improved for better battery performance, reliability, and service life. The current study shows a significant enhancement in crack resistance (from 11.3 N to 32.9 N) for Na3Al (1.8) Si-1.65 P1.8O12 glass (Ag-0 glass) upon Na+ -Ag+ ion-exchange (IE) due to compressive stresses generated in the glass surface while the ionic conductivity values (similar to 10(-5) S/cm at 473 K) were retained. In this study, magic angle spinning-nuclear magnetic resonance (MAS-NMR), molecular dynamics (MD) simulations, Vickers micro hardness, and impedance spectroscopic techniques were used to evaluate the intermediate-range structure, atomic structure, crack resistance and conductivity of the glass. MAS-NMR and MD simulations confirm the presence of Si-OAl-O-P groups in the glass, thus enabling formation of Na percolated channel regions. AC-conductivity analysis for Ag-0 and ion-exchanged Ag-0 glass suggests that the mobility of Na+ ion increases with increasing temperature. It is observed that the measured mean square displacement (root < R-2(t(p))>) for sodium cations using AC-conductivity isotherms is nearly constant up to 448 K and then increases with increasing temperature up to 523 K. From the impedance spectra for ion-exchanged Ag-0 glass, it is identified that the increase in root < R-2 (t(nu))> and thereby, the mobility of sodium-ions for Ag-0 glass is due to the structural variations in the Ag-0 glass with increasing the temperature. Overall, the mechanisms presented in this article helps in formulating better glass based electrolyte materials for room temperature or high temperature sodium-ion batteries. (C) 2022 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: amorphous; Ion-exchange; Ionic-conductivity; MD simulations; Mechanical property

Emerging landscape of molecular interaction networks: opportunities, challenges and prospects - Panditrao, Gauri; Bhowmick, Rupa; Meena, Chandrakala; Sarkar, Ram Rup (Journal of Biosciences, 2022)
Network biology finds application in interpreting molecular interaction networks and providing insightful inferences using graph theoretical analysis of biological systems. The integration of computational bio-modelling approaches with different hybrid network-based techniques provides additional information about the behaviour of complex systems. With increasing advances in high-throughput technologies in biological research, attempts have been made to incorporate this information into network structures, which has led to a continuous update of network biology approaches over time. The newly minted centrality measures accommodate the details of omics data and regulatory network structure information. The unification of graph network properties with classical mathematical and computational modelling approaches and technologically advanced approaches like machine-learning- and artificial intelligence-based algorithms leverages the potential application of these techniques. These computational advances prove beneficial and serve various applications such as essential gene prediction, identification of drug-disease interaction and gene prioritization. Hence, in this review, we have provided a comprehensive overview of the emerging landscape of molecular interaction networks using graph theoretical approaches. With the aim to provide information on the wide range of applications of network biology approaches in understanding the interaction and regulation of genes, proteins, enzymes and metabolites at different molecular levels, we have reviewed the methods that utilize network topological properties, emerging hybrid network-based approaches and applications that integrate machine learning techniques to analyse molecular interaction networks. Further, we have discussed the applications of these approaches in biomedical research with a note on future prospects.
Keywords: Centrality; disease mechanisms; hybrid network-based models; machine learning; molecular interaction networks; network topology; systems biology

Enantioselective Au(I)/Au(III) redox catalysis enabled by chiral (P,N)-ligands - Chintawar, Chetan C.; Bhoyare, Vivek W.; Mane, Manoj V.; Patil, Nitin T. (Journal of the American Chemical Society, 2022)
Presented herein is the first report of enantioselective Au(I)/Au(III) redox catalysis, enabled by a newly designed hemilabile chiral (P,N)-ligand (ChetPhos). The potential of this concept has been demonstrated by the development of enantioselective 1,2-oxyarylation and 1,2-aminoarylation of alkenes which provided direct access to the medicinally relevant 3-oxy- and 3-aminochromans (up to 88% yield and 99% ee). DFT studies were carried out to unravel the enantiodetermining step, which revealed that the stronger trans influence of phosphorus allows selective positioning of the substrate in the C-2-symmetric chiral environment present around nitrogen, imparting a high level of enantioselectivity.

Enantioselective Cu(I)-catalyzed borylative cyclization of enone-tethered cyclohexadienones and mechanistic insights - Jadhav, Sandip B.; Dash, Soumya Ranjan; Maurya, Sundaram; Nanubolu, Jagadeesh Babu; Vanka, Kumar; Chegondi, Rambabu (Nature Communications, 2022)
Rapidly building molecular structures with both elements of complexity and flexibility is a key goal of organic synthesis. Here the authors show a tandem copper-catalyzed beta-borylation/Michael addition on prochiral enone-tethered 2,5-cyclohexadienones, to generate bicyclic borylated products in high yield and enantioselectivity. The catalytic asymmetric borylation of conjugated carbonyls followed by stereoselective intramolecular cascade cyclizations with in situ generated chiral enolates are extremely rare. Herein, we report the enantioselective Cu(I)-catalyzed beta-borylation/Michael addition on prochiral enone-tethered 2,5-cyclohexadienones. This asymmetric desymmetrization strategy has a broad range of substrate scope to generate densely functionalized bicyclic enones bearing four contiguous stereocenters with excellent yield, enantioselectivity, and diastereoselectivity. One-pot borylation/cyclization/oxidation via the sequential addition of sodium perborate reagent affords the corresponding alcohols without affecting yield and enantioselectivity. The synthetic potential of this reaction is explored through gram-scale reactions and further chemoselective transformations on products. DFT calculations explain the requirement of the base in an equimolar ratio in the reaction, as it leads to the formation of a lithium-enolate complex to undergo C-C bond formation via a chair-like transition state, with a barrier that is 22.5 kcal/mol more favourable than that of the copper-enolate complex.

Enantioselective separation of amino acids using chiral polystyrene microspheres synthesized by a post-polymer modification approach - Nikam, Shrikant B.; Asha S. K (ACS Polymers Au, 2022)
The enantioselective separation of a racemic mixture of amino acids was achieved by chiral amino acid-modified polystyrene (PS) that was developed by a post-polymer modification approach. Styrene was polymerized using the reversible addition–fragmentation chain-transfer (RAFT) polymerization technique and further post-polymer modification was applied by Friedel–Crafts acylation reaction with chiral N-phthaloyl-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-leucine acid chloride to obtain the protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu. The chiral PS (protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu) was assembled into microspheres using a surfactant and was used for carrying out the enantioselective separation of amino acid racemic mixtures by enantioselective adsorption followed by a simple filtration process. Compared to as-precipitated chiral PS (protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu) powder, the protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu microspheres exhibited a better enantioselective separation efficiency (ee %). Furthermore, the protected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu was deprotected to obtain the amine-functionalized deprotected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu chiral PS, which was also assembled into microspheres and used for carrying out enantioselective separation. Deprotected PS-<span class="smallcaps smallerCapital" style="box-sizing: border-box; outline: none; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-caps: small-caps; font-variant-alternates: normal; color: rgb(0, 0, 0); font-family: georgia, serif; font-size: 17.008px; background-color: rgb(244, 244, 244);">l-Leu-functionalized chiral PS microspheres could achieve up to 81.6 ee % for the enantioselective separation of a racemic mixture of leucine. This is one of the first reports of the synthesis of amino acid-modified chiral PS microspheres and their application to the simple filtration-based enantioselective separation of native amino acids from their racemic mixtures.

Enantioselective synthesis of dihydrothiopyranones via NHC- catalyzed [3+3] annulation of 2-bromoenals with beta-oxodithioesters - Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2022)
The N-heterocyclic carbene (NHC)-organocata-lyzed [3 + 3] annulation of 2-bromoenals with fi-oxodithioesters resulting in the enantioselective synthesis of dihydrothiopyranones is presented. The chiral a,fi-unsaturated acylazoliums generated from 2-bromoenals and carbenes underwent smooth interception with the sulfur nucleophiles to furnish the sulfur heterocycles in satisfactory yields/selectivity. The regioselective formation of dihydrothiopyranones over the competing dihydropyranones is noteworthy.

Enceleamycins A-C, furo-naphthoquinones from amycolatopsis sp. MCC0218: isolation, structure elucidation, and antimicrobial activity - Khan, Abujunaid; Said, Madhukar S.; Borade, Balasaheb R.; Gonnade, Rajesh; Barvkar, Vitthal; Kontham, Ravindar; Dastager, Syed G. (Journal of Natural Products, 2022)
Three novel furo-naphthoquinones, enceleamycins A-C (1-3), and a new N-hydroxypyrazinone acid (4) were identified from the strain Amycolatopsis sp. MCC 0218, isolated from a soil sample collected from the Western Ghats of India. Their chemical structure and absolute and relative configurations were established by 1D and 2D NMR spectroscopy, single-crystal X-ray crystallography, and high-resolution mass spectrometry. Compounds 1 and 3 were active against methicillin-susceptible and -resistant Staphylococcus aureus with MIC values of 2-16 mu g/mL.

Engineering nucleotide sugar synthesis pathways for independent and simultaneous modulation of N-glycan galactosylation and fucosylation in CHO cells - Prabhu, Anuja; Shanmugam, Dhanasekaran; Gadgil, Mugdha (Metabolic Engineering, 2022)
Glycosylation of recombinant therapeutics like monoclonal antibodies (mAbs) is a critical quality attribute. N-glycans in mAbs are known to affect various effector functions, and thereby therapeutic use of such glycoproteins can depend on a particular glycoform profile to achieve desired efficacy. However, there are currently limited options for modulating the glycoform profile, which depend mainly on over-expression or knock-out of glyco-syltransferase enzymes that can introduce or eliminate specific glycans but do not allow predictable glycoform modulation over a range of values. In this study, we demonstrate the ability to predictably modulate the gly-coform profile of recombinant IgG. Using CRISPR/Cas9, we have engineered nucleotide sugar synthesis pathways in CHO cells expressing recombinant IgG for combinatorial modulation of galactosylation and fucosylation. Knocking out the enzymes UDP-galactose 4 `-epimerase (Gale) and GDP-L-fucose synthase (Fx) resulted in ablation of de novo synthesis of UDP-Gal and GDP-Fuc. With Gale knock-out, the array of N-glycans on recom-binantly expressed IgG is narrowed to agalactosylated glycans, mainly A2F glycan (89%). In the Gale and Fx double knock-out cell line, agalactosylated and afucosylated A2 glycan is predominant (88%). In the double knock-out cell line, galactosylation and fucosylation was entirely dependent on the salvage pathway, which allowed for modulation of UDP-Gal and GDP-Fuc synthesis and intracellular nucleotide sugar availability by controlling the availability of extracellular galactose and fucose. We demonstrate that the glycoform profile of recombinant IgG can be modulated from containing predominantly agalactosylated and afucosylated glycans to up to 42% and 96% galactosylation and fucosylation, respectively, by extracellular feeding of sugars in a dose-dependent manner. By simply varying the availability of extracellular galactose and/or fucose, galactosylation and fucosylation levels can be simultaneously and independently modulated. In addition to achieving the pro-duction of tailored glycoforms, this engineered CHO host platform can cater to the rapid synthesis of variably glycoengineered proteins for evaluation of biological activity.
Keywords: Antibody; Cell engineering; Fucosylation; Fx; Galactosylation; Gale; glycosylation; Nucleotide sugar synthesis; Recombinant therapeutics

Enhanced anisole hydroxylation over a hierarchical micro/mesoporous TS-1 catalyst - Patil, Chetana R.; Niphadkar, Prashant; Kamble, Sanjay P.; Rode, V. Chandrashekhar (New Journal of Chemistry, 2022)
Hierarchical TS-1 materials were synthesized using hydrothermal synthesis and a post modification technique through desilication. They were evaluated for hydroxylation of anisole to produce industrially important chemicals, o-methoxyphenol (OMP) and p-methoxyphenol (PMP). The detailed characterization of the prepared catalysts, such as morphology, structure, nature of Ti and surface area were obtained by SEM, HR-TEM, XRD, UV-VIS spectroscopy and the BET technique. The effects of various operational parameters such as substrate/H2O2 molar ratio, reaction temperature, catalyst concentration and solvent effect on the hydroxylation of anisole have been studied in detail. The microporous TS-1 catalyst showed 32% anisole conversion with 34% selectivity to PMP, while the micro/mesoporous DTS-1 catalyst showed enhanced activity for anisole hydroxylation, i.e. 54% conversion with 55% selectivity towards PMP. The increased framework Ti and improved accessibility of the active sites located in the channels of DTS-1, which permit the mass transfer of reactants, transition states and products from the mesopores of DTS-1, were responsible for the enhanced catalytic activity and selectivity towards p-methoxyphenol.

Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C

Enhanced hydrogen fuel production using synergistic combination of solar radiation and TiO2 photocatalyst coupled with Burkholderia cepacia lipase - de Souza Brandao, Luma Mirely; Barbosa, Milson dos Santos; de Jesus, Roberta Anjos; Bharad, Pradnya Arunrao; Lima, Alvaro Silva; Faria Soares, Cleide Mara; Navarro Yerga, Rufino Manuel; Bilal, Muhammad; Romanholo Ferreira, Luiz Fernando; Iqbal, Hafiz M. N.; Gopinath, Chinnakonda S.; Figueiredo, Renan Tavares (International Journal of Hydrogen Energy, 2022)
Promising and sustainable alternatives for hydrogen production have been investigated. Among these, the use of enzymes may represent an efficient alternative. In this work, an increase in hydrogen production under simulated sunlight by combining TiO2 and TiO2/MgCl2 with Burkholderia cepacia lipase (BCL) was reported. The samples (TiO2, TiO2/MgCl2, and TiO2 /MgCl2/BCL) were characterized by X-ray diffraction (XRD), thermo-gravimetric (TGA), N-2 adsorption-desorption isotherms (BET), scanning electron microscopy (SEM), and UV-Visible absorption spectra. Hydrogen production tests were performed in aqueous methanol solutions under simulated sunlight. The results demonstrated that 130-times greater increase in hydrogen production rate was observed by the addition of BCL than individual TiO2. This better hydrogen production rate can be attributed to the increase in the amount of reduction equivalent of the system due to the oxidation of protein peptides caused by TiO2. In conclusion, the results indicate that hydrogen production efficiency can be significantly improved when integrating TiO2/MgCl2 with BCL. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen production; Lipase; Nano-conjugated enzymes; Photocatalyst; Solar radiation; Titanium dioxide

Enhanced proton conductivity in amino acid based self-assembled non-porous hydrogen-bonded organic frameworks - Pramanik, Titas; Anand, Ashish; Pandikassala, Ajmal; Illathvalappil, Rajith; Kurungot, Sreekumar; Row, T. N. Guru (Chemical Communications, 2022)
beta-Alaninium oxalate hemihydrate, glycinium oxalate, and L-leucinium oxalate salt-cocrystals as non-porous self-assembled hydrogen-bonded organic frameworks afforded proton conductivity of 2.43 x 10(-2) S cm(-1) (60 degrees C, 95% RH), 3.03 x 10(-2) S cm(-1) (60 degrees C, 95% RH), and 1.19 x 10(-2) S cm(-1) (80 degrees C, 95% RH), respectively. These materials possess an extensive 3-dimensional network of hydrogen bonds in their crystal structures, making them efficient proton conducting membranes. The reduction in conductivity values over 10(-1) S cm(-1) order upon exposure of the samples to a D2O atmosphere in extreme conditions ratified the role of humidity for the conduction of protons. This work explores the relationship between structural features and proton conductivity for the design of proton conducting membranes that are easy to synthesize, eco-friendly, and cheap with potential for futuristic applications.

Evaluating suitability of confined impinging jet reactor for exothermic reactions: hydrodynamics, residence time distribution, and heat transfer - Khan, Muzammilanwar S.; Mane, Mayur; Kulkarni, Amol A. (AICHE Journal, 2022)
Effect of confinement (wall proximity) of a confined impinging jet reactor (CIJR) on the flow field, residence time distribution and heat transfer are explored, through experiments and CFD simulations. Hydrodynamic characteristics are evaluated for different parameters namely confinement, impinging jet velocity, temperature gradient, and so on. For 2 mm confinement, highest values of dispersion number and overall heat transfer coefficient are observed due to interaction of turbulent eddies followed by the effect of reactor wall proximity. For the CIJR having confinements above 10 mm, jet velocity need to be greater than 3 m/s to achieve both, excellent mixing efficiency and high heat removal rate. Empirical correlations for Dispersion and Nusselt numbers as a function of Re-j and L/D are obtained, over a range of 500 <= Rej <= 3000\$\$ 500\textbackslashle {\textbackslashmathit{\textbackslashoperatornameRe}}_j\text backslashle 3000 \$\$ and 5 <= L/D <= 35\$\$ 5\textbackslashle L/D\textbackslashle 35 \$\$, which correspond to jet velocity of 0.5-3 m/s. The present study gives a basis for designing CIJR suitable for rapid, homogeneous, exothermic reactions.
Keywords: confinement; exothermic reactions; heat transfer; impinging jets; residence time distribution

Exploring the core microbiota in scented rice (Oryza sativa L.) rhizosphere through metagenomics approach - Dhondge, V. Harshal; Barvkar, Vitthal T.; Paul, Dhiraj; Dastager, Syed G.; Pable, Anupama A.; Nadaf, Altafhusain B. (Microbiological Research, 2022)
Rice is a major food crop cultivated around the globe. Specially scented rice varieties are of commercial importance but they are low-yielding. The rhizospheric microflora plays a significant role in improving yield and aroma. However, the core microbiome of the scented rice rhizosphere is comparatively less explored. Here, we analyzed the core microbiome associated with the rhizosphere of the scented (Ambemohar-157 and Dehradun basmati) in comparison with non-scented rice (Kolam and Arize 6444 Gold) cultivated at two different geoclimatic zones of India (Maharashtra and Uttarakhand) using the metagenomics approach. The alpha and beta diversity analysis showed that the microbial communities associated with scented and non-scented varieties significantly changes with respect to richness, diversity, and evenness. The taxonomic profiling revealed the variation in composition, diversity, and abundance of the microbiome in terms of phyla and genera associated with scented rice varieties over non-scented. The cluster analysis distinguishes the microbial communities based on their geographical positions. The core microbiome analysis revealed that scented rice rhizosphere shelters distinct and unique microbiota. 28.6 % of genera were exclusively present only in the scented rice rhizosphere. The putative functional gene annotation revealed the high abundance of genes related to the biosynthesis of 2-acetyl-1-pyrroline (2AP) precursors in scented rice. The precursor feeding analysis revealed proline as a preferred substrate by 2AP synthesizing bacteria. The 2AP precursor proline and proline metabolism genes showed a positive correlation. The scented rice-specific rhizobacteria pointed out in this study can be used as bioinoculants for enhancing aroma, yield, and sustainable rice cultivation.
Keywords: Metagenome; Microbial community; Microbiome; Oryza sativa; Rhizosphere; rice

Exploring the structure and electronic properties of germanium doped boron clusters using density functional theory based global optimization method - Anis, Insha; Dar, Mohd Saleem; Rather, Ghulam Mohammad; Dar, Manzoor Ahmad (New Journal of Chemistry, 2022)
Density functional theory calculations in the framework of B3LYP, TPSS and M06-L were carried out to investigate the effect of single and double germanium atom doping on the geometric structure and electronic properties of boron clusters with 10 to 20 atoms. Global minima of GeBn and Ge2Bn (n = 10-20) were first obtained through Crystal Structure Analysis by the Particle Swarm Optimization method and then subsequently optimized using meta-generalized gradient approximation, hybrid and local functionals. It is found that the lowest energy structures of GeBn and Ge2Bn clusters exhibit planar, quasi-planar, semi-cage, bowl, and double ring topologies. Like BnSi clusters, the results reveal that the germanium atom prefers the peripheral regions of the B-n framework contrary to transition metal doped boron clusters. Furthermore, the calculated electronic properties such as the average binding energy and second order difference in binding energy indicate GeB20 and Ge2B16 to be the most stable clusters. Molecular orbital and adaptive natural density partitioning analyses were carried out to understand the extra stability of GeB20 and Ge2B16 clusters.

Early cellular events and potential regulators of cellulase induction in Penicillium janthinellum NCIM 1366 - Christopher, Meera; Sreeja-Raju, Athiraraj; Abraham, Amith; Gokhale, Digambar Vitthal; Pandey, Ashok; Sukumaran, Rajeev K. (Scientific Reports, 2023)
Cellulase production by fungi is tightly regulated in response to environmental cues, and understanding this mechanism is a key pre-requisite in the efforts to improve cellulase secretion. Based on UniProt descriptions of secreted Carbohydrate Active enZymes (CAZymes), 13 proteins of the cellulase hyper-producer Penicillium janthinellum NCIM 1366 (PJ-1366) were annotated as cellulases- 4 cellobiohydrolases (CBH), 7 endoglucanases (EG) and 2 beta glucosidases (BGL). Cellulase, xylanase, BGL and peroxidase activities were higher for cultures grown on a combination of cellulose and wheat bran, while EG was stimulated by disaccharides. Docking studies indicated that the most abundant BGL- Bgl2- has different binding sites for the substrate cellobiose and the product glucose, which helps to alleviate feedback inhibition, probably accounting for the low level of glucose tolerance exhibited. Out of the 758 transcription factors (TFs) differentially expressed on cellulose induction, 13 TFs were identified whose binding site frequencies on the promoter regions of the cellulases positively correlated with their abundance in the secretome. Further, correlation analysis of the transcriptional response of these regulators and TF-binding sites on their promoters indicated that cellulase expression is possibly preceded by up-regulation of 12 TFs and down-regulation of 16 TFs, which cumulatively regulate transcription, translation, nutrient metabolism and stress response.

Effect of acidity and mesoporosity in H-USY on conversion of wheat straw to ethyl levulinate (Biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Nandanwar, Sachin; Bokade, Vijay (Journal of the Indian Chemical Society, 2023)
Cold flow properties of biodiesel can be improved by addition of additives especially ethyl levulinate (EL up to 20%). There are very limited information on synthesis of EL from actual raw biomass like wheat straw over heterogeneous catalyst. The present article elaborated on optimization of Acidity to Mesoporosity ratio in H-USY, which is crucial for its application in conversion of raw wheat straw to selective formation of EL in one-step. The acidity and mesoporosity is monitor by systematic post treatment of desilication and dealumination. Optimum acidity/mesoporosity ratio of 3.6 in HUSY resulted in to maximum EL yield of 24.5%, which is probably the highest so far.
Keywords: Acidity; Biofuel additive; Dealumination; Desilication; ethyl levulinate; H-USY; Mesoporosity; Wheat straw

Effect of charge and solvation shell on non-radiative decay processes in s-block cationic metal ion water clusters - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2023)
Intermolecular Coulombic decay or electron transfer-mediated decay are the autoionization processes through which a molecule can relax. This relaxation is only possible if the inner valence's ionization potential (IP) exceeds the system's double ionization potential (DIP). To study the effects of charge and solvation shell, we have calculated the IP, DIP values, and lifetime of Na-2s and Mg-2s temporary bound states in various optimized structures of Na+-(H2O)(n) and Mg2+-(H2O)(n) (n = 1-5) micro-solvated clusters, where n water molecules are distributed in a way that some are directly bound to the metal ion and the rest to the water molecules. The first and second solvation shells are the names for the former and the latter water-binding positions, respectively. For a given n, the lifetime of decaying states is longer when water molecules are in the second solvation shell. We found that the Mg-2p state can decay for all n values in Mg2+-(H2O)(n) clusters, whereas the Na-2p state's decay is possible for n >= 2 in Na+-(H2O)(n) clusters. Our findings highlight the influence of metal ions' charge, different solvation shell structures, and the number of water molecules on the decay rate. These systems are relevant to the human body, which makes this study significant.

Effect of microwave heating on the residence time distribution in a tubular reactor - Sonawane, Jayesh R.; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2023)
Microwave(MW) heating has been revolutionary in various applications,including chemical synthesis. A nonconventional heating approach reducesthe reaction time significantly. For a continuous flow tubular reactorunder microwaves, the temperature would change from the inlet to theoutlet depending on the dielectric constant of the reaction mass,which would further change the physical properties, viz., the densityand viscosity of the material. Such changes in the physical propertieswould lead to nonideal flows and would affect the conversion as wellas selectivity for reactions. In order to understand the extent ofsuch a nonideality, here for the first time we have done systematicstudies of the residence time distribution in a helical coil reactor.The axial dispersion model has been modified to take into accountthe temperature-dependent physical properties of the fluid. The empiricalcorrelation for the dispersion number is obtained over the range of450 & LE; P (W) & LE; 1200 and 60 & LE; T (& DEG;C) & LE; 150. This study will help model thereaction kinetics as well as reactor design under microwave specificallyfor heat sensitive reactions where variations in the overall residencetime would affect the yield and selectivity of the end product.

Effect of protonation and deprotonation on electron transfer mediated decay and interatomic coulombic decay - Kumar, R.; Vaval, N. (ChemPhysChem, 2023)
Electronically excited atoms or molecules in an environment are often subject to interatomic/intermolecular Coulombic decay (ICD) and/or electron transfer mediated decay (ETMD) mechanisms. A few of the numerous variables that can impact these non-radiative decay mechanisms include bond distance, the number of nearby atoms or molecules, and the polarisation effect. In this paper, we have studied the effect of protonation and deprotonation on the ionization potential (IP), double ionization potential (DIP), and lifetime (or decay width) of the temporary bound state in these non-radiative decay processes. We have chosen LiH-NH3 and LiH-H2O as test systems. The equation of motion coupled cluster singles and doubles method augmented by complex absorbing potential (CAP-EOM-CCSD) has been used in calculating the energetic position of the decaying state and the system's decay rate. Deprotonation of LiH-NH3/LiH-H2O either from the metal center (LiH) or from ammonia/water lowers the IP and DIP compared to the neutral systems. In contrast, protonation increases these quantities compared to neutral systems. The protonation closes the inner valence state relaxation channels for ICD/ETMD. For example, the decay of the O-2s/N-2s state stops in protonated systems (LiH2+-H2O, LiH2+-NH3, and LiH-NH4+). Our study also shows that the efficiency, i. e., the rate of ICD/ETMD, can be altered by protonation and deprotonation. It is expected to have implications for chemical and biological systems.

The effect of substituents on the aggregation-induced emission of 9,10-phenanthraquinone-hydrazones - Kumar, M. Naveen; Lyngkhoi, Deikrisha Lyngdoh; Gaikwad, Sudhakar; Samanta, Debabrata; Khatua, Snehadrinarayan; Pramanik, Susnata (New Journal of Chemistry, 2023)
Organic luminophores, particularly & pi;-conjugated systems, have become crucial in modern optoelectronic devices that utilise luminescence as an output signal, requiring aggregate or solid-states, such as nanoparticles, thin films, or crystals. Herein, we report the one-step synthesis of six hydrazone derivatives using condensation reactions between 9,10-phenanthrenedione and different aromatic hydrazines, comprising electron-donating/electron-withdrawing groups and a quinoline moiety. The introduction of a conjugated & pi;-system leads to complete co-planarization of molecules resulting in large bathochromic shifts in their absorption profile, the maximum red-shifts ever observed for the hydrazones. These hydrazones are weakly fluorescent in dilute acetonitrile solutions. However, they exhibit enhanced emissions of up to 300-fold in aggregated states. Dynamic light scattering (DLS) and scanning electron microscopy (SEM) studies support nanoaggregate formation. All the compounds exhibit red to NIR emissions in their crystalline state with as high as 75% quantum efficiency.

Effective distribution of gold nanorods in ordered thick mesoporous silica: a choice of noninvasive theranostics - Prasad, Rajendra; Selvaraj, Kaliaperumal (ACS Applied Materials & Interfaces, 2023)
Porous silica coated gold nanorod core-shell structures demonstrate a multifunctional role in bioimaging, drug delivery, and cancer therapeutics applications. Here, we address a new approach for effective distribution of gold nanorods (GNRs) in a mesoporous silica (MS) shell, viz., one nanorod in one silica particle (GMS). We have studied that silica coating presents major advantages for the better biocompatibility and stability of GNRs. In this study, two different thicknesses of silica shell over GNRs have been discussed as per the application's need; GNRs in thin silica (11 nm) are fit for phototherapy and bioimaging, whereas thick and porous silica (51 nm) coated gold nanorods are suitable for triggered drug delivery and theranostics. However, effective distribution of GNRs in ordered architecture of thick mesoporous silica (MS, more than 50 nm thickness) with high surface area (more than 1000 m(2)/g) is not well understood so far. Here, we present methodical investigations for uniform and highly ordered mesoporous silica coating over GNRs with tunable thickness (6 to 51 nm). Judicious identification and optimization of different reaction parameters like concentrations of silica precursor (TEOS, 1.85-43.9 mM), template (CTAB, 0.9-5.7 mM), effect of temperature, pH (8.6-10.8), stirring speed (100-400 rpm), and, most importantly, the mode of addition of TEOS with GNRs have been discussed. Studies with thick, porous silica coated GNRs simplify the highest ever reported surface area (1100 m(2)/g) and cargo capacity (57%) with better product yield (g/batch). First and foremost, we report a highly scalable (more than 500 mL) and rapid direct deposition of an ordered MS shell around GNRs. These engineered core-shell nanoparticles demonstrate X-ray contrast property, synergistic photothermal-chemotherapeutics, and imaging of tumor cell (96% cell death) due to released fluorescent anticancer drug molecules and photothermal effect (52 degree celsius) of embedded GNRs. A deeper insight into their influence on the architectural features and superior theranostics performances has been illustrated in detail. Hence, these findings indicate the potential impact of individual GMS for image guided combination therapeutics of cancer.
Keywords: CombinationTherapy; Contrast Agent; Core-ShellStructure; GoldNanorods; Imaging; Mesoporous silica; Nanoparticles; TheranosticsIntervention

Effective valorization of blackstrap molasses to poly gamma glutamic acid (γ-PGA) using L-glutamic acid independent feeding approach and its significance as drought mitigator in wheat plant - Nair, Pranav G.; Dharne, Mahesh S. (Industrial Crops and Products, 2023)
One of the finest approaches towards sustainable waste management is its effective valorization to value-added products (VAPs). Waste valorization is garnering considerable attention since it delivers substantial advantages, including environmental stability and a sustainable and viable platform for producing different VAPs. One such VAP is the poly gamma glutamic acid (& gamma;- PGA), an extortionate biopolymer known to date. Its exorbitant cost is the main barrier preventing & gamma;- PGA from becoming commercially viable. Hence, the key to the successful commercialization of & gamma;- PGA is its sustainable and cost-effective production. In the present study, the ability of Bacillus paralicheniformis NCIM 5769 to utilize molasses for & gamma;-PGA production with minimal nutrients was investigated. Results showed that 30% molasses combined with 2% ammonium nitrate was the optimal medium for & gamma;-PGA production. Additionally, the anti-drought activity of the synthesized & gamma;-PGA was evaluated on wheat plants showing significantly higher shoot length, biomass content, and germination rate compared to the control group. These findings suggest that & gamma;-PGA produced from molasses has the potential to be used as a drought mitigator in wheat plant, thereby achieving the mission of circular economy and sustainable development goal (SGD) 12, i.e. pursuing sustainability patterns for consumption & production.
Keywords: Anti-drought; circular economy; Poly gamma glutamic acid; Sustainable; Waste valorization

Efficient and convenient heterogeneous Cu/MCM-41 catalyst for the synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives - Dhengale, Shankar D.; Bhosale, Tanaji R.; Shinde, Sachin B.; Rode, Chandrashekhar V.; Kolekar, Govind B.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2023)
An efficient and convenient method for synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives using Cu/MCM-41 (20 mg) as heterogeneous catalyst. The advantages have an excellent product yield within a short time and easy work-up procedure, and the products have directly recrystallized from hot methanol with cost-effective catalyst. One-pot three-component reaction from aromatic aldehydes, cyclic 1,3-dicarbonyl compounds, and 1-naphthyl amine has been carried under ethanol as a solvent with reflux condition. Moreover, the catalyst can be recovered conveniently and reused efficiently, and recyclable. [GRAPHICS] .
Keywords: Benzo[c]acridine; dimedone; Heterogeneous Cu/MCM-41 catalyst; Multicomponent one-pot reaction

Efficient olefin epoxidation with high turnover rates over ordered mesoporous silica nanoparticles with uniform manganese sites - Negi, Sanjay Singh; Khatri, Prateek; Singh, Anand Pal (Microporous and Mesoporous Materials, 2023)
Olefin epoxidation has been studied over a series of mesoporous manganese silicate nanoparticles and tBuOOH. Partial substitution of Si by Mn in silica framework leads to highly dispersed, distorted Mn(III) sites, confirmed by various physicochemical analyses. High conversion and stable styrene oxide, stilbene oxide and epoxy cyclohexane yield have been achieved with MS75 with 1:1.5 ratio of olefin: oxidant. However, at faster reaction rates lower styrene oxide yield is observed at lower Mn-containing catalyst (MS100). High TON, TOF over manganese sites shows accessible monomeric Mn sites. Attributed to high reactant density at redox-active Mn silicate sites due to facile diffusion across shallow pore depth channels of nanoparticulate om-MSx and surface hydrophobic characteristics. The catalysts were found to be stable under recycling and filtration experiments. The excellent stability against leaching of active manganese species indicates stable sites and good textural properties in om-MSx, essential for extended activity.
Keywords: epoxidation; Manganese silicates; Mesoporous silica nanoparticles; Ordered mesoporous silica; pH adjustment

Efficient synthesis of optically active herbicide (S)-metolachlor via reductive ring opening of 2-methoxymethylaziridine - Nalla, Viswanadh; Mujahid, Mohammad; Sasikumar, Murugesan; Mujumdar, Prashant; Muthukrishnan, Murugan (Arkivoc, 2023)
An efficient synthesis of a well known chiral herbicide, (S)-metolachlor has been described using 2methoxymethylaziridine ring formation and reductive ring opening as key steps using commercially available (R)-epichlorohydrin. The present protocol delivers the required enantiomer of metolachlor in overall yield of 50.8% and high enantiopurity (>99%).
Keywords: Aziridine; Epoxide; Epoxide ring opening; herbicide synthesis; Metolachlor

Electrocatalytic hydrogen evolution mediated by an organotelluroxane macrocycle stabilized through secondary interactions - Narsimhulu, Gujju; Samuel, Calvin; Palani, Sathishkumar; Dasari, Sai Hemant Kumar; Krishnamoorthy, Kothandam; Baskar, Viswanathan (Dalton Transaction, 2023)
A discrete liphophilic organotelluroxane macrocycle has been found to catalyse the hydrogen evolution reaction (HER) by proton reduction efficiently. The macrocycle is synthesized via chloride abstraction from bis(p-methoxyphenyl) tellurium dichloride (p-MeOC6H5)2TeCl2 (1) by silver salts AgMX4 (MX4 = BF4-, and ClO4-) resulting in in situ generated di-cationic tetraorganoditelluroxane units; two such units are held together by two weak anions mu 2-MX4, bridging to form 12-membered di-cationic macrocycles [((p-MeO-C6H4)2Te)2(mu-O)(mu 2-F2BF2)2]2+ (2) and [((p-MeO-C6H4)2Te)2(mu-O)(mu 2-O2ClO2)2]2+ (3) stabilized via Te-(mu 2-BF4/ClO4), with secondary interactions. The charge is balanced by the presence of two more anions, one above and another below the plane of the macrocycle. Similar reaction at higher temperatures leads to the formation of telluronium salts R3TeX [X = BF4- (4), ClO4- (5)] as a major product. The BF4- anion containing macrocycle and telluronium salt were monitored using 19F NMR. HRMS confirmed the structural stability of all the compounds in the solution state. The organotelluroxane macrocycle 2 has been found to act as an efficient electrocatalyst for proton reduction in an organic medium in the presence of p-toluene sulfonic acid as a protic source. A discrete liphophilic organotelluroxane macrocycle has been found to catalyse hydrogen evolution reaction (HER) by proton reduction efficiently.
Keywords: Anion Transport; Proton-Reduction

Electrocatalytic nitrogen reduction on defective graphene modulated from single atom catalyst to aluminium clusters - Maibam, Ashakiran; Krishnamurty, Sailaja; BabaRao, Ravichandar (Applied Surface Science, 2023)
Density Functional Theory (DFT) investigation on the most earth-abundant Al-based catalysts, has been conducted detailing its electronic properties and catalytic efficacy for nitrogen reduction at ambient condition. The Al-based catalysts have been modulated to perform as par a highly performing, but rare, Ru-single atom catalytic center by varying number of Al atoms, shape, and size. The coalesce of band-center, work function and electronic properties in metal atom catalysts along with N-N bond activation has been demonstrated to be responsible for an efficient nitrogen reduction reaction (NRR) with Delta Gmax of 0.78 eV in Al5 supported on N-doped double vacancy graphene (Al5@N4-DVG) catalyst. Electron localization function analysis has shown a weak physisorption of N2 in the Al-based catalysts. Projected Density of States (PDOS) illustrates the enhancement of aluminium electron density in Al5@N4-DVG led to enhanced orbital densities overlap of Alp and Np electrons. The Bader charge analysis and electronic analysis of the intermediates show efficient electron gain on the N atoms, leading to formation of NH3 from the NxHy intermediates in Al5@N4-DVG catalyst.

Electrode|electrolyte interface enhancement in quasi-solid-state zinc-air batteries through an anion conducting polymer electrolyte interlayer by in situ polymerization - Kurian, Maria; Vijayakumar, Vidyanand; Manna, Narugopal; Kanheerampockil, Fayis; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2023)
This work introduces a novel concept of electrode|electrolyte interface enhancement using an ultraviolet (UV) light-assisted in situ polymerization strategy to improve the performance of quasi-solid-state zinc-air batteries (ZABs). The suitability of the UV polymerization strategy to process a mechanically stable OH- conducting anion exchange polymer electrolyte membrane (AEPEM) reinforced by a glass fiber (GF) separator is also reported. The in situ polymerized ionomer-skin/interlayer (a thin anion-conducting polymer coating over the air-cathode of ZAB) acts as a buffer layer to narrow down the performance gap generally observed between ZABs possessing quasi-solid-state electrolytes and standard liquid electrolytes, respectively. For instance, when combined with the in situ polymerization strategy, a rechargeable ZAB (rZAB) based on an AEPEM-GF composite membrane delivered a high power density of 140 mW cm(-2), higher than that of the one without an in situ polymerized ionomer interlayer (120 mW cm(-2)). Notably, in a flexible rZAB configuration, this new strategy resulted in enhanced rate capability and cycling stability for 14 h at an operating current density of 2 mA cm(-2).

Electronic fingerprints for diverse interactions of methanol with various Zn-based systems - Mehta, Shweta; Joshi, Kavita (Surface Science, 2023)
We have investigated various Zn-based catalysts for their interaction with methanol (MeOH). MeOH is one of the most critical molecules being studied extensively, and Zn-based catalysts are widely used in many industrially relevant reactions involving MeOH. We note that the same element (Zn and O, in the present study) exhibits different catalytic activity in different environments. The changing environment is captured in the underlying electronic structure of the catalysts. In the present work, we compared the electronic structure of Zn-based systems, i.e., ZnAl2O4 and ZnO along with oxygen preadsorbed Zn (O-Zn) and metallic Zn. We demonstrate the one-to-one correlation between the pDOS of the bare facet and the outcome of that facet's interaction (i.e. either adsorption or dissociation of MeOH) with MeOH. These findings would pave the way towards the in-silico design of catalysts.
Keywords: DFT; Electronic properties; Methanol; Zn-based systems; ZnO

Electrostatic modulation of intramolecular and intermolecular interactions during the formation of an amyloid-like assembly - Pillai, Meenakshi; Das, Atanu; Jha, Santosh Kumar (Biochemistry, 2023)
The mechanism of protein aggregation can be broadly viewedas ashift from the native-state stabilizing intramolecular to the aggregated-phasesustaining intermolecular interactions. Understanding the role ofelectrostatic forces on the extent of modulation of this switch hasrecently evolved as a topic of monumental significance as proteinaggregation has lately been connected to charge modifications of anaging proteome. To decipher the distinctive role of electrostaticforces on the extremely complicated phase separation landscape, weopted for a combined in vitro-in silico approach to ascertainthe structure-dynamics-stability-aggregabilityrelationship of the functional tandem RRM domains of the ALS-relatedprotein TDP-43 (TDP-43(tRRM)), under a bivariate solutioncondition in terms of pH and salt concentration. Under acidic pH conditions,the native TDP-43(tRRM) protein creates an aggregation-proneentropically favorable partially unfolded conformational landscapedue to enthalpic destabilization caused by the protonation of theburied ionizable residues and consequent overwhelming fluctuationsof selective segments of the sequence leading to anti-correlated movementsof the two domains of the protein. The evolved fluffy ensemble witha comparatively exposed backbone then easily interacts with incomingprotein molecules in the presence of salt via typical amyloid-aggregate-likeintermolecular backbone hydrogen bonds with a considerable contributionoriginating from the dispersion forces. Subsequent exposure to excesssalt at low pH conditions expedites the aggregation process via anelectrostatic screening mechanism where salt shows preferential bindingto the positively charged side chain. The applied target observable-specificapproach complementarity unveils the hidden information landscapeof an otherwise complex process with unquestionable conviction.

Elevated level of glycated KQTALVELVK peptide of albumin is associated with the risk of diabetic nephropathy - Chaurasiya, Arvindkumar H.; Jaiswal, Meera R.; Bayatigeri, Santhakumari; Kahar, Shweta; Tiwari, Shalbha; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2023)
Diabetic nephropathyis a leading cause of end-stagerenal disease.Hence, early detection of diabetic nephropathy is essential to mitigatethe disease burden. Microalbuminuria, the currently used diagnosticmarker of diabetic nephropathy, is not efficient in detecting it atan early stage. Therefore, we explored the utility of glycated humanserum albumin (HSA) peptides for risk prediction of diabetic nephropathy.Three glycation-sensitive HSA peptides, namely, FKDLG-EENFK,KQTAL-VELVK, and KVPQVST-PTLVEVSR, with deoxyfructosyllysine(DFL) modification were quantified by targeted mass spectrometry (MS)in a study population comprising healthy and type II diabetes subjectswith and without nephropathy. Mass spectrometry, receiver operatingcharacteristic (ROC) curve, and correlation analysis revealed thatthe DFL-modified KQTALVELVK peptide was better than other glycatedHSA peptides and HbA(1c) for identifying diabetic nephropathy.DFL-modified KQTALVELVK could be a potential marker for risk predictionof diabetic nephropathy.

Emergent stability in complex network dynamics - Meena, Chandrakala; Hens, Chittaranjan; Acharyya, Suman; Haber, Simcha; Boccaletti, Stefano; Barzel, Baruch (Nature Physics, 2023)
The stable functionality of networked systems is a hallmark of their natural ability to coordinate between their multiple interacting components. Yet, real-world networks often appear random and highly irregular, raising the question of what are the naturally emerging organizing principles of complex system stability. The answer is encoded within the system's stability matrix-the Jacobian-but is hard to retrieve, due to the scale and diversity of the relevant systems, their broad parameter space and their nonlinear interaction dynamics. Here we introduce the dynamic Jacobian ensemble, which allows us to systematically investigate the fixed-point dynamics of a range of relevant network-based models. Within this ensemble, we find that complex systems exhibit discrete stability classes. These range from asymptotically unstable (where stability is unattainable) to sensitive (where stability abides within a bounded range of system parameters). Alongside these two classes, we uncover a third asymptotically stable class in which a sufficiently large and heterogeneous network acquires a guaranteed stability, independent of its microscopic parameters and robust against external perturbation. Hence, in this ensemble, two of the most ubiquitous characteristics of real-world networks-scale and heterogeneity-emerge as natural organizing principles to ensure fixed-point stability in the face of changing environmental conditions. Despite looking highly irregular, most real-world networks exhibit natural stability to external perturbations. A study of the properties of the stability matrix of networks now sheds light on the principles underlying this emerging stability.

Emerging trends in olefin polymerization: a perspective - Birajdar, Rajkumar S.; Bodkhe, Dnyaneshwar; Gupta, Poonam; Shaikh, Maulali H.; Ramekar, Rohan; Chikkali, Samir H. (Journal of macromolecular science part A- pure and applied chemistry, 2023)
The seemingly matured field of olefin polymerization still poses several challenges and holds enormous potential to meet contemporary material requirements. In this feature article, we examine the progress of olefin polymerization in the last two decades. Among the several emerging trends, we identify four most impactful discoveries, namely, (i) disentangled ultra-high molecular weight polyethylene (dUHMWPE), (ii) disubstituted functional olefin copolymerization, (iii) incorporation of bioderived comonomers in polyolefins, and (iv) application of above (ii, iii) functional polyolefins as compatibilizers. The dUHMWPE has attracted significant attention and heterogeneous Ziegler-type catalysts, homogenous metallocene, and post-metallocene catalysts have been reported to produce disentangled ultrahigh molecular weight polyethylene. Insertion copolymerization of difunctional disubstituted olefins has been reported only recently and ortho-phosphinobenzene sulfonate palladium catalyst outperforms the other catalysts. Interestingly, insertion copolymerization of bioderived olefins has witnessed a surge in the number of reports. Sugar and plant oil-derived olefins have been copolymerized with ethylene to obtain relatively hydrophilic polyethylene. The functional polyethylene is finding a new application as compatibilizer or displays better adhesion to surfaces. Thus, the feature article offers a succinct account of emerging trends in polyolefins, identifies the most impactful contributions, and debates the application potential of these new materials.
Keywords: compatibilizer; Functional polyethylene; Insertion (co)polymerization; renewable monomers; uHMWPE

Enantioselective intramolecular decarboxylative C-H bond func-tionalization of quinazolinones with amino acids by visible light photoredox catalysis - Sonavane, Sameer R.; Mhaske, Santosh B. (Chemistry-An Asian Journal, 2023)
The direct visible light-mediated intramolecular decarboxylative C-H functionalization of Csp(2)-H bond adjacent to the nitrogen of a heteroarene has been achieved by iridium-catalyzed photodecarboxylative radical cyclization. This method offers rapid entry to the synthesis of quinazolinone scaffolds from easily accessible starting materials. The newly developed protocol is mild, operationally simple, oxidant free and general. The utility of this unique Csp(3)-Csp(2) bond forming reaction has been demonstrated in the syntheses of Circumdatin, Sclerotigenine and Benzomalvin A class of quinazolinone natural products and their congeners. The present work represents an interesting example of use of memory of chirality in decarboxylative C-C bond forming enantioselective photoredox reaction.
Keywords: C-H functionalization; memory of chirality; Minisci reaction; photodecarboxylative cyclization; photoredox catalysis; quinazolinone alkaloid; Radical

Enantioselective synthesis of (+)-Sedridine, (-)-Allosedridine and their N-Methyl analogs via Maruoka-Keck allylation and CBS reduction - Bhoite, Shubhangi P.; Suryavanshi, Gurunath (Natural Product Research, 2023)
A simple synthetic approach has been developed for the enantioselective total synthesis of (+)-Sedridine, (-)-Allosedridine and their analogs such as (+)-N- Methyl Sedridine and (-)-N-Methylallosedridine. The synthesis was achieved by using commercially available starting materials via Maruoka-Keck allylation, Wacker oxidation, and CBS reduction. The synthetic root provides a good diastereomeric ratio and high yields.
Keywords: CBS reduction; Maruoka-Keck allylation; Piperidine; Wacker oxidation

Enhanced degradation of metformin using surface-coated vortex diodes - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical engineering and processing-process intensification, 2023)
The present work successfully demonstrates, for the first time, complete degradation of metformin using newer surface-coated vortex diode (SCVD) with copper and nickel coating to provide catalytic activity in the conventional hydrodynamic cavitation (HC) for significantly enhanced degradation efficiency. The SCVDs have dual functionality and the efficacy of catalytic cavitation reactors get enhanced using process intensifications of the type H2O2 addition, pH modification, and combined approach of HC+ pH+ H2O2 apart from the advantage of low pressure drop for the vortex flow based cavitation in vortex diode (Delta P of 1 bar). Complete, 100%, degradation of metformin (MTF) was achieved within 5 min with integration of optimized H2O2 dose and exceptionally high synergistic index value over 300, indicating extraordinary synergy for both Cu and Ni-SCVD. Acidic condition promote degradation and a complete degradation with a high 43-48% mineralization was observed using HC+ pH 4+ (1:200) H2O2 with less intermediates formation. The SCVDs reveal remarkable enhancement of similar to 9800% in per-pass degradation and 1400-3400% in cavitational yield as compared to conventional cavitation process under similar conditions. The newer SCVDs with catalytic activity can provide more cost-effective solutions for industrial and real-life applications.
Keywords: Cavitation; Oxidation; pollution; Technology; Wastewater treatment

Enhancing diradical character of chichibabin's hydrocarbon through fluoride substitution - Kundu, Gargi; Dash, Soumya Ranjan; Kumar, Ravi; Vanka, Kumar; Ghosh, Aryya; Sen, Sakya S. (ChemPlusChem, 2023)
In this work, 5-SIDipp [SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] (1) derived Chichibabin's hydrocarbon with an octafluorobiphenylene spacer (3) has been reported. The addition of two equivalents of 5-SIDipp with decafluorobiphenyl in presence of BF3 gives the double C-F bond activated imidazolium salt with two tetrafluoroborate anions, 2. Further reduction of 2 gives the fluorine substituted 5-SIDipp based Chichibabin's hydrocarbon, 3. Quantum chemical calculations suggested a singlet state of 3 with a singlet-triplet energy gap (?ES-T) of 3.7 kcal mol(-1), which is substantially lower with respect to the hydrogen substituted NHC-based Chichibabin's hydrocarbons (10.7 kcal mol(-1), B3LYP). As a result, the diradical character (y) of 3 (y=0.62) is also noticeably higher than the hydrogen substituted CHs (y=0.41-0.43). The ?ES-T was found to be higher in CASSCF (22.24 kcal mol(-1)) and CASPT2 (11.17 kcal mol(-1)) for 3 and the diradical character (d) is 44.6 %.
Keywords: C-F Bond Activation; Chichibabin & PRIME; DFT; N-Heterocyclic carbene; s Hydrocarbon

Equilibrium adsorption of nitrogen, oxygen, and argon on silver-exchanged hierarchical ETS-10 - Shrotri, Aadesh R.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Chemical and Engineering Data, 2023)
Silver-exchanged hierarchical ETS-10(Ag-H-ETS-10) was synthesizedusing Ag+ exchange with hierarchical Engelhard titanosilicate(H-ETS-10) using silver nitrate solution. The physical propertiesof the adsorbent were analyzed using X-ray diffraction (XRD), BETsurface area, nitrogen adsorption-desorption, pore volume,energy dispersive spectroscopy (EDS), and high resolution-transmissionelectron microscopy (HR-TEM). N-2 physisorption data confirmedthat a micro-mesoporous (bimodal) structure was created in the Ag-H-ETS-10.The equilibrium adsorbent data of pure gases N-2, O-2, and Ar were investigated in the temperature range from 288to 318 K up to 10 bar. The equilibrium adsorption capacity of Ag-H-ETS-10was found to be 1.12 mmol g(-1) for N-2,0.87 mmol g(-1) for O-2, and 1.09 mmol g(-1) for Ar at 298 K and & SIM;10 bar. & SIM;20% higheradsorption capacity was found for N-2 and Ar in Ag-H-ETS-10compared to Ag-ETS-10. The higher sorption capacity was attributedto the formation of a bimodal structure and & pi;-complexation interactionby the Ag cation, which allows a multilayer of N-2 and Armolecules. The Sips isotherm model was well fitted for the Ag-H-ETS-10experimental data among Langmuir, Freundlich, Toth, and Temkin models.The measured equilibrium adsorption data for Ag-H-ETS-10 can be usefulfor the O-2 purification process.

Etherification of biomass-derived glycerol to oxygenated fuel additives using dodecatungstophosphoric-silica-supported catalyst: characterization and kinetic studies - Magar, Subhash B.; Kapoor, Ashish; Jana, Sumit Kumar; Pal, Dan Bahadur; Rode, Chandrashekhar V. (Biomass Conversion and Biorefinery, 2023)
Commercial biodiesel production is becoming popular due to its sustainability and reduced greenhouse gas emissions in comparison to fossil fuels. Biodiesel production involves the co-generation of crude glycerol that is not directly viable. Valorization of glycerol is essential from techno-economic perspective to achieve goals of circular economy. In this study, the glycerol etherification was carried out using tert-butyl alcohol in presence of dodecatungstophosphoric/silica (DTP/SiO2) catalyst for production of tert-butyl glycerol ethers that can be used as fuel additives. A series of DTP/SiO2 catalysts were prepared with various compositions by impregnating heteropoly acids (HPA, H3PW12O40). The product analysis was performed to monitor mono-, di-, and tri-tert-butyl glycerol ethers. The kinetic studies were conducted based on Langmuir-Hinshelwood model. The rate constants were determined from experimental data by regression analysis. The catalysts were characterized by X-ray diffraction, SEM/EDX, and thermogravimetric analysis. Varying DTP loadings resulted in different catalytic activities. Activation energy (38.23 kJ/mol), activation enthalpy (25.94 kJ/mol), activation entropy (-163.8 J/mol/K), and Gibbs free energy of activation (88.67 kJ/mol) were attained for DTP/SiO2 (20%) catalyst that exhibited the best selectivity for di-tert-butyl glycerol ethers.
Keywords: Catalytic; etherification; fuel additives; Hinselwood; Impregnation; kinetics; Langmuir

Evaluation of Fe3O4 incorporated functionalized carbon nanotube self-standing buckypaper as electrodes for solid-state symmetric supercapacitor - Bhaviripudi, Vijayabhaskara Rao; Dwivedi, Pravin K.; Pabba, Durga Prasad; Aepuru, Radhamanohar; Nakate, Umesh T.; Espinoza-Gonzalez, Rodrigo; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Iron (II, III) oxide and carbonaceous materials drawn considerable attention in energy storage owing to their special features. In this study, simple reverse co-precipitation, acid functionalization and vacuum filtration methods adopted to synthesis Fe3O4 nanoparticles of size 11 nm and -COOH acid functionalized multi-wall carbon nanotubes (FMWCNT). And further used them to prepare and optimize Fe3O4 in FMWCNT as 15 wt% and 25 wt% self-standing buckypapers of around 30-mu m thickness as electrodes for solid-state symmetric capacitor in the form of coin cell. The results show that 15 wt% and 25 wt% of Fe3O4-FMWCNT buckypapers hybrid nanostructures have Fe3O4 nanoparticles successfully incorporated in FMWCNT. The 25 wt% Fe3O4-FMWCNT electrodes with charge transfer resistance of 140 Ohm showed high areal specific capacitance (Cs) 78.5 mF/cm2 and retained 80 % of its Cs until 800 cycles even at high current density of 1 mA/cm2, scan rate of 100 mV/s whereas 15 wt% Fe3O4-FMWCNT showed low Cs of 47 mF/cm2 and retained 80 % of its Cs over 5000 cycles whereas only FMWCNT show Cs is 36 mF/cm2 with 54 Ohm. Finally, a solid-state symmetric supercapacitor coin cell with self-standing 25 wt% Fe3O4-FMWCNT buckypaper showed an excellent power density of 129.5 mW cm-3 and energy density of 3.6 mWh cm-3 is the innovation of the current work. This is mainly attributed to the combined effect of pseudocapacitive behavior from Fe3O4 by faradaic reaction with additional charge transfer resistance and electric double layer (EDLC) behavior from FMWCNTs by non-faradaic of electronic, ionic transport during charging-discharging. As-made solid-state symmetric supercapacitor appears as a high-performance storage device without extra support of current collectors for practical applications and for fabri-cation of planar capacitors.
Keywords: Buckypaper; Power density; specific capacitance; Symmetric supercapacitor

Evaluation of the adhesive properties of vanillin-derived polyhydroxy urethanes - Ghuge, Gorakh Hiraman; Kambikanam, Karthika Vayalachery; Nair, Kiran Sukumaran (Journal of Applied Polymer Science, 2023)
Poly(hydroxy urethanes) (PHUs) have been considered attractive and safer variants of conventional polyurethanes (PUs). To improve the prerequisites of green and sustainable chemistry herein, we propose the synthesis and utilization of cyclic carbonate monomers majorly derived from vanillin, a lignin derivative, and CO2 for the development of PHUs. Kinetic evaluation on the polymerization temperature ascertained 80 degrees C as the optimum condition for PHU synthesis. The structural evaluation of PHUs was carried out by various spectroscopic techniques, such as FTIR, (HNMR)-H-1, and C-13-NMR, molar masses were determined by gel permeation chromatography (Mn varied between 2500 and 11,100 g/mol), and thermal properties evaluated by differential scanning calorimeter (Tg in the ranges of 28-42 degrees C), and thermogravimetric analysis (stable above 180 degrees C). Since the PHUs are enriched with pendant hydroxyl groups on their backbone which can promote adhesion, lap shear studies on the aluminum substrate exhibited a maximum shear strength of 1.65 +/- 0.37 MPa. This study demonstrates an attractive and environment-friendly pathway for developing novel PHUs network using renewable biobased resources and further explores its applicability as adhesives.
Keywords: adhesive; biobased cyclic dicarbonate; diamines; poly(hydroxyurethane)s; Vanillin

Evolutionary conservation of protein dynamics: insights from all-atom molecular dynamics simulations of `peptidase' domain of Spt16 - Gaur, Neeraj K.; Ghosh, Biplab; Goyal, Venuka Durani; Kulkarni, Kiran; Makde, Ravindra D. (Journal of Biomolecular Structure and Dynamics, 2023)
Protein function is encoded in its sequence, manifested in its three-dimensional structure, and facilitated by its dynamics. Studies have suggested that protein structures with higher sequence similarity could have more similar patterns of dynamics. However, such studies of protein dynamics within and across protein families typically rely on coarse-grained models, or approximate metrics like crystallographic B-factors. This study uses mu s scale molecular dynamics (MD) simulations to explore the conservation of dynamics among homologs of similar to 50 kDa N-terminal module of Spt16 (Spt16N). Spt16N from Saccharomyces cerevisiae (Sc-Spt16N) and three of its homologs with 30-40% sequence identities were available in the PDB. To make our data-set more comprehensive, the crystal structure of an additional homolog (62% sequence identity with Sc-Spt16N) was solved at 1.7 angstrom resolution. Cumulative MD simulations of 6 mu s were carried out on these Spt16N structures and on two additional protein structures with varying degrees of similarity to it. The simulations revealed that correlation in patterns of backbone fluctuations vary linearly with sequence identity. This trend could not be inferred using crystallographic B-factors. Further, normal mode analysis suggested a similar pattern of inter-domain (inter-lobe) motions not only among Spt16N homologs, but also in the M24 peptidase structure. On the other hand, MD simulation results highlighted conserved motions that were found unique for Spt16N protein, this along with electrostatics trends shed light on functional aspects of Spt16N. Communicated by Ramaswamy H. Sarma.
Keywords: Backbone fluctuations; FACT complex; histone binding; interdomain motion; M24 peptidase

Exceptional cyclability of thermally stable PVdF-co-HFP/SiO2 nanocomposite polymer electrolytes for sodium ion batteries - Das, Akhila; Melepurakkal, Amrutha; Sreeram, Pranav; Gireesh, K. T.; Balakrishnan, Neethu T. M.; Fatima, M. J. Jabeen; Pullanchiyodan, Abhilash; Ahn, Jou-Hyeon; V. Shelke, Manjusha; Raghavan, Prasanth (Journal of Energy Storage, 2023)
Thermally stable composite polymer electrolyte (CPE) devising PVdF-co-HFP polymer with in-situ generated silica (SiO2) as filler is synthesised via non-solvent- induced phase inversion technique. The filler loading of in-situ synthesised silica in PVdF-co-HFP is varied from 0 to 9 wt% and its morphological, thermal and electrochemical characterization is carried out. Among the different composite electrolytes, the PVdF-co-HFP containing 6 wt% SiO2 shows the uniform microporous structure with a highest porosity (84 %), surface area (784.14 m(2) g(-1)), electrolyte uptake (262 %) and electrolyte retention value (0.48). The incorporation of in-situ SiO2 on CPE shows not only the enhancement in thermal stability but also reduced thermal shrinkage with an increase in the filler content. The electrochemical studies of PVdF-co-HFP containing 6 wt% SiO2 shows a higher ionic conductivity (0.71 mS cm(-1)) and potential stability >4.5 V verses Na/Na+. The Na-ion half-cells assembled with PVdF-co-HFP/SiO2 composite electrolyte show a specific capacity of similar to 120 mAh g(-1) at 0.3C rate in room temperature and a stable cycle performance with a Coulombic efficiency of around 100 % for 200 cycles.
Keywords: Composite electrolytes; Coulombic efficiency; polymer electrolytes; Sodium ion batteries; specific capacity; thermal stability

Excitation wavelength-dependent multi-coloured and white-light emissive pyrene-based hydrazones: suppression of Kasha's rule - Kumar, M. Naveen; Lyngkhoi, Deikrisha Lyngdoh; Gaikwad, Sudhakar; Samanta, Jayanta; Ahamed, Rafiq; Khatua, Snehadrinarayan; Pramanik, Susnata (Chemical Communications, 2023)
Multi-coloured and white-light emissions from pyrene-based hydrazones are described. They exhibit excitation wavelength-dependent emissions in solution due to the suppression of Kasha's rule. Interestingly, in dimethylformamide, 1-3 emit light that covers all the regions of primary colours as a function of excitation wavelength, and 1 and 2 emit white light (lambda ex = 420 nm) in isopropanol. Multi-coloured and white-light emissions from pyrene-based hydrazones are described.

Exploration of different solid variants of the anticancer medication Panobinostat (PNB) with improved physicochemical attributes - Kenguva, Gowtham; Giri, Lopamudra; Rout, Smruti Rekha; Acharya, Achyuta Nanda; Dandela, Rambabu (Journal of Molecular Structure, 2023)
Panobinostat (PNB), is a medication used for the treatment of multiple myeloma. It is a BCS Class II drug with strong permeability and poor solubility. Therefore, it is highly desirable to investigate novel PNB variants with improved physiochemical properties. In this regard, several solid forms of PNB have been produced employing mechanochemistry and solution crystallisation techniques using a variety of GRAS (Generally Recognized as Safe) salt formers, notably oxalic acid (OA), fumaric acid (FA), maleic acid (MA), and succinic acid (SA). Powder X-Ray Diffraction (PXRD), Single Crystal X-Ray Diffraction (SCXRD), and thermal analysis such as Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) were used to characterize all the synthesised molecular adducts. Hirshfeld surfaces and fingerprint plots demonstrate that the molecular entities are stabilized by O & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;C and H & BULL;& BULL;& BULL;H intermolecular interactions. Moreover, the solubility of parent PNB and its molecular adducts in pH 1.2/pH 6.8 was evaluated at room temperature. In every instance, an increase in the solubility of molecular salts relative to the parent medication is seen, notably PNB.MA exhibits enhanced solubility of 0.294 mg/ml, a 73fold increase over the parent PNB. Furthermore, it is observed that this upsurge in solubility of all the forms is static at pH 1.2. A thorough analysis of the recovered residue after solubility showed that most of the molecular adducts were stable at pH 6.8 and did not display any phase change or dissociation (with the exception of PNB.MA), but at pH 1.2 they transferred into a new stable form and extensive analysis confirmed that it converted into PNB.Cl salt. To the best of our knowledge, this is the first report on novel solid forms of PNB with enhanced physicochemical properties which implies that the obtained PNB molecular adduct may help in the development of improved PNB formulations.
Keywords: Hydrogen bond; Molecular adducts; solubility; Solvates

Exploring SiliaCat Pd-DPP as a recyclable heterogeneous catalyst for the multi-batch direct heteroarylation polymerization for P(NDI2OD-T2) - Kakde, Navnath R.; Asha, S. K. (Polymer Chemistry, 2023)
Donor-acceptor (D-A) conjugated polymers like P(NDI2OD-T2) are important constituents of the active layer of energy conversion devices like all-polymer solar cells. A cost-effective and environmentally amiable pathway for the synthesis of this and similar D-A polymers is highly desirable for the large-scale production of these materials. In this report we have combined two cost-effective approaches, namely, direct heteroarylation polymerization (DHAP) and a recyclable heterogeneous catalyst (SiliaCat Pd-DPP), for the multi-batch synthesis of P(NDI2OD-T2). The general applicability of the approach was first established with a series of conjugated small molecules based on naphthalene diimide and bithiophene derivatives (N1 to N6). The Meitlis hot filtration test and inductively coupled plasma-optical emission spectroscopy (ICP-OES) were conducted to estimate the quantity of leached palladium in the final reaction product. Catalyst recyclability up to five cycles was demonstrated for N1 with <2 ppm leached palladium impurity. A comparison was made with the homogeneous catalyst Pd(2)dba(3) which indicated the presence of much higher levels of palladium impurity in the final product. The polymerization of P(NDI2OD-T2) was demonstrated using the regular monomers (NDIOD-Br-2 and bithiophene) and also using a modified monomer with activated bithiophene (naphthalene diimide substituted bithiophene) under DHAP conditions employing SiliaCat Pd-DPP as the recyclable heterogeneous catalyst. The modified monomer proved to be amenable to DHAP polymerization using SiliaCat Pd-DPP as the heterogeneous catalyst, which could be consecutively reused four times with reproducible molecular weights in the range of M-n/M-w: 27.1/49.0 to 33.5/61.3.

Expounding lemonal terpenoids as corrosion inhibitors for copper using DFT based calculations - Samal, Pragnya Paramita; Singh, Chandrodai Pratap; Krishnamurty, Sailaja (Applied Surface Science, 2023)
The most important bottleneck in identifying an innovative and yet viable corrosion inhibitor for copper surfaces is discerning the chemical interactions at the interface of adsorbate and adsorbent. The present work, primarily, discerns the interface chemistry of green corrosion inhibitors, viz., lemonal terpenoids, with the copper surfaces for the first time. The interface chemistry is evaluated for distinct facets of copper, modelled by periodic surfaces to finite sized aggregates, with two stereoisomers viz., citral and neral through density functional calculations. The adsorption/ interaction properties between the surface and the corrosion inhibiting molecule are analysed through the electronic properties such as density of states, charge density difference plots and Bader charges where in distinct bonding mechanisms are identified as a function of varying facets. Apart from the adsorption properties, molecular packing properties are of paramount importance towards the design of an efficient corrosion inhibitor for a surface. Hence, we also analyse the intermolecular stacking energies between the inhibitors when packed among themselves in vacuum and when adhered on to metal surfaces. The studies bring forth an understanding that lemon terpenoids are highly potential corrosion inhibitors for copper surfaces, particularly, for Cu (110) surfaces both in neutral and protonated form.
Keywords: Copper surface; Density Functional Theory (DFT); Green corrosion inhibitors; Interface chemistry; Lemonal terpenoids; Molecular stacking

Early detection of KP.2 SARS-CoV-2 variant using wastewater-based genomic surveillance in Pune, Maharashtra, India - Rajput, Vinay; Das, Rashmita; Pramanik, Rinka; Nannaware, Kiran; Sushma, Y.; Taji, Nyabom; Rajput, Vishal; Rajkhowa, Riyakshi; Pacharne, Poonam; Shah, Priyanki; Gogate, Niharika; Sangwar, Poornima; et al. (Journal of Travel Medicine, 2024)

Editorial: microbial biodiversity and bioprospecting in polar ecosystems in the genomics era - Rizzo, Carmen; Dastager, Syed Gulam; Ay, Hilal (FRONTIERS IN MICROBIOLOGY, 2024)
Keywords: diversity; FJORD

Effect of citral partitioning on structural and mechanical properties of lipid membranes - Saraf, Deepashri; Porte, Sudha; Sengupta, Durba (European Physical Journal-Special Topics, 2024)
Delineating the interactions of cellular metabolites with lipid membranes and their effects on membrane physical and mechanical properties constitutes a key step for comprehensively understanding their biological function. The plant metabolite-citral is widely used in biotechnological and cosmeceutical processes, but significant gaps remain in our understanding of how it affects cellular membranes that it interacts with. In this study, we unravel the molecular mechanisms underlying the interactions of citral with compositionally distinct model membranes using atomistic molecular dynamics simulations. Specifically, we investigate two distinct membrane compositions: the neutral phosphatidylcholine-phosphatidylethanolamine (DOPC:DOPE) bilayer, representing mammalian cell membranes and the anionic phosphatidylcholine-phosphatidylglycerol (DOPC:DOPG) bilayer, mimicking bacterial cell membranes. Our simulations reveal that citral molecules readily partition into both membranes without distinct composition-dependent effects. Monomeric citral molecules localize mainly at the interface of the acyl chain region of the lipids, and a few translocation events are sampled in the simulations. Interestingly, we observe small differences in lipid fluidity although the citral molecules significantly influence the rigidity of lipid bilayers, and a higher bending modulus was observed in DOPC:DOPE lipid bilayers compared to DOPC:DOPG bilayers. Further, citral partitioning induces an increased tendency for lipid demixing in DOPC:DOPE membranes, as evidenced by the decreased values of the Shannon entropy. Our work is an important step to elucidate the molecular processes that underlie the differential impact of cell metabolites on compositionally distinct lipid membranes.

Effect of covalently functionalized Indian bentonite clay on thermal, mechanical strength and morphology structure of extrusion/injection-molded nylon 6 composites - Shanmugam, Kumaresan; Rokade, Dhammaraj S.; Ingole, Pravin G.; Pol, Harshawardhan V.; Arunachalam, Saravanakumar; Bajaj, Hari C. (Polymers for Advanced Technologies, 2024)
The research and development of functional polymer composites and their production have posed significant challenges, particularly in creating high mechanical strength and thermal stability composites. In this study, we utilized a micro corotation extruder and injection molding to produce covalently functionalized Indian bentonite clay-nylon 6 high-strength nanocomposites. For comparison, two different amines, 3-aminopropyl trimethoxysilane and N-[3-(trimethoxysilyl) propyl] ethylene di-amine, were used to functionalize bentonite clay. Additionally, 3% and 5% less amino clay filler was added in the nanocomposite to manufacture the polymer composite. Analytical techniques such as Powder X-Ray Diffraction, Fourier transform infrared, thermal gravimetric analysis, and Brunauer-Emmett-Teller surface area were used to characterize the molecular orientation of amine functionalization on clay minerals. Wide-angle X-ray diffraction, atomic force microscopy, and transmission electron microscope were used to characterize the nylon 6 intercalated in amino clay nanocomposite and the polymer structure morphology. Thermogravimetric analysis and differential scanning calorimetry were used to investigate the crystalline thermal behavior of clay-nylon 6 composites. From the results, it was observed that the composition containing 5 wt.% amino clay demonstrated a significant improvement in tensile strength when compared with the composition containing 3 wt.% amino clay. The mechanical strength and the thermal behavior showed a significant improvement of similar to 200% for 5% amino clay-nylon 6 nanocomposite.
Keywords: amine-functionalized clay; bentonite clay; melt intercalation; Nanocomposite; nylon 6; thermal and mechanical properties

Effect of CTMABr/SiO2 molar ratio in synthesis of micro-mesoporous ZSM-5 composite and its application in 5-EMF (biofuel additive) formation - Manal, Prajakta N.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Bokade, Vijay V. (Environmental Progress and Sustainable Energy, 2024)
Synthesis of micro-mesoporous zeolite composite with optimum micro and mesoporosity is an emerging research area due to its wide applications, especially in bulk chemical or biomass transformations. It offers advantages in preserving zeolite crystallinity, creating mesoporosity and converting bulky molecules into valuable products. This work presents the process of preparing bimodal micro-mesoporous ZSM-5 using dual templates (CTMABr and TPABr). XRD, N2 adsorption-desorption, SEM, TEM, Si-29, and Al-27 NMR were used to analyze the two-dimensional micro-mesoporous ZSM-5. One-step synthesis of bimodal micro-mesoporous ZSM-5 features dual micro/mesoporosity by a marginal decrease in the crystallinity (71%). Micro-mesoporous ZSM-5 composite was found to be dependent on the optimum CTMABr/SiO2 molar ratio of 0.04 to 0.06. The micro-mesoporous ZSM-5 zeolite composite was evaluated for cascade synthesis of 5-EMF (methoxymethyl furfural- biofuel additive) from fructose and exhibited a five fold increase in 5-EMF yield to 24.2% as compared with parent ZSM-5 (4.6%).
Keywords: fructose; methoxymethyl furfural-biofuel additive; micro-meso composite; ZSM-5

Effect of furfural, acetic acid and 5-hydroxymethylfurfural on yeast growth and xylitol fermentation using Pichia stipitis NCIM 3497 - Bhavana, B. K.; Mudliar, Sandeep N.; Bokade, V. V.; Debnath, S. (Biomass Conversion and Biorefinery, 2024)
The valorization of C5 sugars (xylose) from hemicellulose of agro-industrial residues to xylitol, as one of the multi-products biorefinery approach, mandates the pretreatment of biomass which releases fermentable sugars along with the generation of biological inhibitors affecting xylitol fermentation. This study was therefore evaluated to understand the inhibitory kinetics of furfural, 5-hydroxymethylfurfural and acetic acid on xylitol fermentation. Xylitol fermentation was established using Pichia stipitis NCIM 3497 with xylose as a pure substrate optimized for xylitol yield and productivity of 0.48 g/g of xylose and 0.13 g/L/h, respectively. The functional relationship of yeast specific growth rate and limiting substrate (xylose) was expressed by Monod-type kinetics. The inhibition kinetics results indicated that the effect of inhibitors on xylitol fermentation was furfural > acetic acid > HMF. Furfural (500 mg/L) and acetic acid (1000 mg/L) reduced xylitol yield by 59% and 44%, respectively, with least reduction of 9.89% exhibited by HMF. The synergistic effect of 500 mg/L furfural, 500 mg/L HMF and 1000 mg/L acetic acid showed the highest reduction in xylitol yield of 67.6% as compared to the control. Kinetic studies predicted that the maximum concentration of furfural, HMF and acetic acid which inhibited P. stipitis growth was 884 mg/L, 3258 mg/L and 2922 mg/L, respectively, whereas xylitol production was completely inhibited at 1069 mg/L furfural, 3498 mg/L HMF and 3714 mg/L acetic acid. Furfural and acetic acid were found to be a competitive inhibitor, while uncompetitive inhibition was observed with HMF indicating negligible effect on xylitol fermentation.
Keywords: Acetic acid; furfural; HMF; Inhibition kinetics; Pichia stipitis; Xylitol fermentation

Effect of position of donor units and alkyl groups on dye-sensitized solar cell device performance: indoline-aniline donor-based visible light active unsymmetrical squaraine dyes - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Om., 2024)
Indoline (In) and aniline (An) donor-based visible light active unsymmetrical squaraine (SQ) dyes were synthesized for dye-sensitized solar cells (DSSCs), where the position of An and In units was changed with respect to the anchoring group (carboxylic acid) to have In-SQ-An-CO2H and An-SQ-In-CO2H sensitizers, AS1-AS5. Linear or branched alkyl groups were functionalized with the N atom of either In or An units to control the aggregation of the dyes on TiO2. AS1-AS5 exhibit an isomeric pi-framework where the squaric acid unit is placed in the middle, where AS2 and AS5 dyes possess the anchoring group connected with the An donor, and AS1, AS3, and AS4 dyes having the anchoring group connected with the In donor. Hence, the conjugation between the middle squaric acid acceptor unit and the anchoring -CO2H group is short for AS2, AS5, and AK2 and longer for AS1, AS3, and AS4 dyes. AS dyes showed absorption between 501 and 535 nm with extinction coefficients of 1.46-1.61 x 10(5) M-1 cm(-1). Further, the isomeric pi-framework of An-SQ-In-CO2H and In-SQ-An-CO2H exhibited by means of changing the position of In and An units a bathochromic shift in the absorption properties of AS2 and AS5 compared to the AS1, AS3, and AS4 dyes. The DSSC device fabricated with the dyes contains short acceptor-anchoring group distance (AS2 and AS5) showed high photovoltaic performances compared to the dyes having longer distance (AS1, AS3, and AS4) with the iodolyte (I-/I-3(-)) electrolyte. DSSC device efficiencies of 5.49, 6.34, 6.16, and 5.57% have been achieved for AS1, AS2, AS3, and AS4 dyes, respectively; without chenodeoxycholic acid (CDCA), small changes have been observed in the device performance of the AS dyes with CDCA. Significant changes have been noted in the DSSC parameters (open-circuit voltage V-OC, short-circuit current J(SC), fill factor ff, and efficiency eta) for the AS5 dye while sensitized with CDCA and showed highest DSSC efficiency of 8.01% in the AS dye series. This study revealed the potential of shorter SQ acceptor-anchoring group distance over the longer one and the importance of alkyl groups on the overall DSSC device performance for the unsymmetrical squaraine dyes.

Effect of the presence of pinned particles on the structural parameters of a liquid and correlation between structure and dynamics at the local level - Patel, Palak; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2024)
Pinning particles at the equilibrium configuration of the liquid is expected not to affect the structure and any property that depends on the structure while slowing down the dynamics. This leads to a breakdown of the structure dynamics correlation. Here, we calculate two structural quantities: the pair excess entropy, S-2, and the mean field caging potential, the inverse of which is our structural order parameter (SOP). We show that when the pinned particles are treated the same way as the mobile particles, both S-2 and SOP of the mobile particles remain the same as those of the unpinned system, and the structure dynamics correlation decreases with an increase in pinning density, ``c.'' However, when we treat the pinned particles as a different species, even if we consider that the structure does not change, the expression of S-2 and SOP changes. The microscopic expressions show that the interaction between a pinned particle and a mobile particle affects S-2 and SOP more than the interaction between two mobile particles. We show that a similar effect is also present in the calculation of the excess entropy and is the primary reason for the well-known vanishing of the configurational entropy at high temperatures. We further show that, contrary to the common belief, the pinning process does change the structure. When these two effects are considered, both S-2 and SOP decrease with an increase in ``c,'' and the correlation between the structural parameters and the dynamics continues even for higher values of ``c.''

Effect of transition metals (Mn, Co, Ni, and Zn) in size-controlled metal ferrite nanocrystals on the electrocatalytic oxygen evolution reaction - Jeyavani, Vijayakrishnan; Manoj, Shanmugasundaram; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2024)
Metal ferrite (MFO) M2+Fe2O4 (M2+ = Mn, Co, Ni, and Zn) nanocrystals (NCs) with a controlled size of similar to 4 nm were synthesized using stearic acid as the capping agent via a facile solvothermal method. The as-synthesized MnFe2O4 (MnFO), CoFe2O4 (CoFO), NiFe2O4 (NiFO), and ZnFe2O4 (ZnFO) NCs were characterized by XRD, FT-IR, Raman, XPS, TGA, TEM, and HRTEM analyses. The electrocatalytic oxygen evolution reaction (OER) is significant for future renewable energy to produce pure hydrogen (H-2) fuels through H2O splitting. However, because of the complex proton-coupled multielectron transfer process, it is kinetically quite challenging. Fe-containing transition metal-based electrocatalysts are well studied since it has been observed that Fe has a significant role in enhancing OER activity. It is well-known that the size and shape of the Fe/ferrite-based nanoelectrocatalyst play a vital role in electrocatalysis reactions. However, it is also critical to understand the effect of other earth-abundant and cost-effective transition metal ions (e.g., Mn, Co, Ni, and Zn) combined with Fe/ferrite NC-based OER electrocatalytic reactions while keeping the size of NCs constant and compare their electrocatalytic properties toward the development of advanced nanoelectrocatalysts, which is rarely studied to the best of the authors knowledge. Therefore, herein, the electrocatalytic properties for OER were examined by using the as-synthesized MnFO, CoFO, NiFO, and ZnFO NCs to understand the effect of metal ions (Mn, Co, Ni, and Zn) on the Fe-based nanoelectrocatalysts by keeping the size of the nanoelectrocatalysts constant at similar to 4 nm. Additionally, the influence of different substrates, e.g., carbon paper (CP) and nickel foam (NF), on the electrocatalytic activity of MFO (MnFO, CoFO, NiFO, and ZnFO) NCs was also compared. Interestingly, as an OER nanoelectrocatalyst, the CoFO NCs on the CP substrate show better electrochemical OER activity than other MFO NCs, with a Tafel slope value of 49.4 mV dec(-1), an ECSA of 112 cm(2), and a long-term stability of 24 h, which is comparatively higher than the other as-synthesized MFO NCs. On the other hand, MnFO NCs on the NF substrate show better electrochemical OER activity than the other as-synthesized MFO NCs. Therefore, this work highlights the effect of the substrate and the influence of transition metals, e.g., Mn, Co, Ni, and Zn, on size-controlled Fe-based nanoelectrocatalysts toward developing advanced OER electrocatalysts.
Keywords: Carbonpaper; electrocatalysis; Ferrites; Nickel foam; Oxygen Evolution Reaction; Size-controlled nanocrystals

An effective, facile, and rapid synthesis of nanosized Mn3O4 using a microwave route - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Kamble, Aditi; Vaishnav, Vishal; Bogalera, Shivamurthy P.; Manikandan, Marimuthu; Nayaka, Girish Praveen; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Nanoparticle Research, 2024)
Microwave-assisted one-pot, one-step, calcination-free synthesis of nanosized Mn3O4 is reported using only benzylamine and manganese acetate. Benzylamine in this protocol plays a vital role for efficient microwave synthesis. This microwave method enables the synthesis of nanosized Mn3O4 in just few hours only in a single step eliminating the need of calcinations of any intermediate. The synthesized nanosized Mn3O4 was analyzed by XRD, HRTEM, EDAX, and Raman spectroscopy. The catalytic and electrochemical properties of as-synthesized Mn3O4 were investigated. In galvanostatic charge-discharge experiments, after 800 cycles, more than 89% capacitance was retained for electrodes made by as synthesized Mn3O4 nanomaterials indicating its very good stability. In the catalytic conversion of cinnamyl alcohol to cinnamaldehyde via oxidation, using as prepared nanosized Mn3O4 as a catalyst, it displays effective catalytic properties. A probable mechanical study of its formation was also envisaged. This synthesis protocol is additive-free, occurs in a short time, is facile, is energy efficient, and eliminates the use of many chemicals. These silent features make these reported protocols economically viable and environmentally benign which adhere to the principles of Green Chemistry.
Keywords: Calcination free; Electrochemical and catalytic properties; Nanosized Mn3O4; Single-step synthesis

Effects of gamma irradiation on non-polar GaN films deposited on sapphire using pulsed laser deposition - Rajgoli, Tahir; Sant, Tushar; Jejurikar, Suhas M.; Hinge, Sandip; Banpurkar, Arun; Dahiwale, S. S.; Late, Datta (Applied Surface Science, 2024)
The GaN films/layers exposed to gamma-radiations is known to harvest defects and vacancies in the crystals producing donor, acceptor and recombination centers within the bandgap. Therefore it is important to investigate and study the gamma- ray irradiation effects on various physical and chemical properties of a material before any optoelectronic and/or electronic devices are being fabricated. To avoid Stark effect which is observed in most of the optoelectronic devices fabricated using GaN films grew along polar face, use of non-polar GaN films is suggested by researchers. To address such issues the article reports the investigations of physical and chemical properties of non-polar GaN films grown on polar substrate using pulsed laser deposition, which were exposed to the 60Co gamma rays varying dose values. Resistive nature against the impairment of the films caused by gamma-rays observed herewith is highly encouraging, suggesting the use of non-polar GaN films as radiations harden material suitable for fabricating new generation gamma-ray detectors. To our knowledge very limited information is available that report such investigations.
Keywords: Gallium nitride; Gamma rays; PL emission; pulsed laser deposition

Efficient electrochemical synthesis of Cu 3 Si/Si hybrids as negative electrode material for lithium-ion battery - Jiang, Siwei; Cheng, Jiaxu; Nayaka, G. P.; Dong, Peng; Zhang, Yingjie; Xing, Yubo; Zhang, Xiaolei; Du, Ning; Zhou, Zhongren (Journal of Alloys and Compounds, 2024)
Nanoscaling and alloying techniques for silicon -based materials are widely recognized as vital technological approaches to effectively address the challenges associated with volume expansion and poor conductivity in silicon anodes. Developing short process, cost-effective preparation methods and shape controllable silicon -based materials is expected to improve their cyclability. Herein, utilizing the superior electrical conductivity of copper metal and its stable alloy interaction with silicon, the present study introduced a simple synthetic process by incorporating nanoscale Cu 2 O into a SiO 2 dioxide matrix under a combination of hydrothermal reaction with Cu (NO 3 ) 2 as the copper source and further sintering treatment. Under the conditions of a Cu:Si molar ratio to 3:8 under 850 degrees C by 2.6 V of constant electrolsyis for 3 h, straight silicon nanowires with a cross-sectional distribution were obtained. The Cu 3 Si alloy particles were enriched around silicon nanowires. Experimental testing was conducted to evaluate the electrochemical storage capabilities of Cu 3 Si/Si nanowires, resulting in an initial specific capacity of 2630.7 mAh g -1 and an initial coulombic efficiency of 88.94%. After 100 charge -discharge cycles, the discharge specific capacity reached 1675.4 mAh g -1 , with a capacity retention rate of 66.20%. This work demonstrates the effectiveness of constructing a Cu 3 Si conductive network for solving the volume expansion and conductivity problems of Si and the distinctive Cu 3 Si/Si architecture offers an exemplary model for the design of silicon -based composite anodes for advanced lithium -ion batteries.
Keywords: Cu3Si/Si alloy; Electrochemical storage capacity; Molten salt electrochemistry; Si nanowires

Efficient glycolysis of used PET bottles into a high-quality valuable monomer using a shape-engineered MnO nanocatalyst - Swapna, Bhattu; Singh, Nittan; Patowary, Suranjana; Bharali, Pankaj; Madras, Giridhar; Sudarsanam, Putla (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: Catalyst; kinetics; Nanorods; Oxidation; Oxides; POLY(ETHYLENE-TEREPHTHALATE); WASTE

Efficient one-pot process for synthesis of antiviral drug Ganciclovir - Sudrik, Vilas; Karpe, Dnyaneshwar; Jadhav, Vrushali; Lawande, Shamrao (Journal of Chemical Sciences, 2024)
A regioselective novel one-pot synthesis of heterocyclic purine derivative antiviral agent Ganciclovir in which initially guanine is treated with acetic anhydride in the presence of iodine (5%) to get diacetyl guanine intermediate, which undergoes in situ N-alkylation with AMDP in presence of catalytic acidic Amberlite IR-120 to get N-alkylated intermediate and finally deacetylation to get pure regioselective Ganciclovir, which is commercially viable and eco-friendly.Graphical abstractWe developed one-pot synthesis of antiviral drug Ganciclovir. Initially, Guanine is treated with acetic anhydride and iodine to yield diacetyl guanine 3. This intermediate then reacted with AMDP in the presence of acidic Amberlite IR-120 to obtain compound 5. Finally, deacetylation yields Ganciclovir 1, a commercially viable and eco-friendly process.
Keywords: Acidic Amberlite IR-120; acyclic nucleoside; anti-herpes; commercially viable; iodine; one-pot process; regiospecific

Efficient synthesis of a monomer for bioplastic-FDCA using glucose-HTC catalyst and pinnick oxidation from HMF & fructose - Kirdant, Swapnali P. P.; Bankar, Shubham R. R.; Jadhav, Vrushali H. H. (Catalysis Letters, 2024)
An efficient solvent mediated & use of metal-free catalyst strategy was developed for synthesis of FDCA over two steps. A simple & economical glucose-hydrothermally carbonized (Glu-HTC) catalyst was prepared and evaluated for synthesis of 2,5-Diformyl furan (DFF) from fructose & 5-hydroxymethylfurfural (HMF) in the 1(st) step. DFF was then converted to FDCA using Pinnick oxidation in the 2(nd) step. DFF was obtained in 82% & 86% yields from fructose & HMF respectively whereas FDCA was obtained in 94-95% yield from DFF. FDCA was thus formed in an overall yield of 78% and 81% from fructose & HMF respectively. This strategy eliminated use of expensive noble metals for FDCA synthesis and also intermediates such as HMFCA & FFCA were not observed after the reaction as DFF was completely oxidized to FDCA.
Keywords: 2; 5-Diformyl furan (DFF); 5-Furandicarboxylic acid; Biomass; D-fructose

Electrocatalytic and selective oxidation of glycerol to formate on 2D 3d-metal phosphate nanosheets and carbon-negative hydrogen generation - Chauhan, Inderjeet; Vijay, Pothoppurathu M.; Ranjan, Ravi; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Materials Au, 2024)
In the landscape of green hydrogen production, alkaline water electrolysis is a well-established, yet not-so-cost-effective, technique due to the high overpotential requirement for the oxygen evolution reaction (OER). A low-voltage approach is proposed to overcome not only the OER challenge by favorably oxidizing abundant feedstock molecules with an earth-abundant catalyst but also to reduce the energy input required for hydrogen production. This alternative process not only generates carbon-negative green H2 but also yields concurrent value-added products (VAPs), thereby maximizing economic advantages and transforming waste into valuable resources. The essence of this study lies in a novel electrocatalyst material. In the present study, unique and two-dimensional (2D) ultrathin nanosheet phosphates featuring first-row transition metals are synthesized by a one-step solvothermal method, and evaluated for the electrocatalytic glycerol oxidation reaction (GLYOR) in an alkaline medium and simultaneous H2 production. Co3(PO4)2 (CoP), Cu3(PO4)2 (CuP), and Ni3(PO4)2 (NiP) exhibit 2D sheet morphologies, while FePO4 (FeP) displays an entirely different snowflake-like morphology. The 2D nanosheet morphology provides a large surface area and a high density of active sites. As a GLYOR catalyst, CoP ultrathin (∼5 nm) nanosheets exhibit remarkably low onset potential at 1.12 V (vs RHE), outperforming that of NiP, FeP, and CuP around 1.25 V (vs RHE). CoP displays 82% selective formate production, indicating a superior capacity for C–C cleavage and concurrent oxidation; this property could be utilized to valorize larger molecules. CoP also exhibits highly sustainable electrochemical stability for a continuous 200 h GLYOR operation, yielding 6.5 L of H2 production with a 4 cm2 electrode and 98 ± 0.5% Faradaic efficiency. The present study advances our understanding of efficient GLYOR catalysts and underscores the potential of sustainable and economically viable green hydrogen production methodologies.

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG

Electrochemical energy storage in an organic supercapacitor via a non-electrochemical proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Devendrachari, Mruthyunjayachari Chattanahalli; Mendhe, Rahul Mahadeo; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Chemical Science, 2024)
Contrary to conventional beliefs, we show how a functional ligand that does not exhibit any redox activity elevates the charge storage capability of an electric double layer via a proton charge assembly. Compared to an unsubstituted ligand, a non-redox active carboxy ligand demonstrated nearly a 4-fold increase in charge storage, impressive capacitive retention even at a rate of 900C, and approximately a 2-fold decrease in leakage currents with an enhancement in energy density up to approximately 70% via a non-electrochemical route of proton charge assembly. Generalizability of these findings is presented with various non-redox active functional units that can undergo proton charge assembly in the ligand. This demonstration of non-redox active functional units enriching supercapacitive charge storage via proton charge assembly contributes to the rational design of ligands for energy storage applications.

Electrochemical property of nanosphere-like MgO electrode synthesized via SILAR in asymmetric supercapacitor - Gaikwad, D. S.; Bobade, R. G.; Suryawanshi, V. B.; Nakate, U. T.; Shaikh, S. F.; Al-Enizi, Abdullah M.; Dabke, N. B.; Lokhande, B. J.; Ambare, Revanappa C. (Journal of Materials Science-Materials in Electronics, 2024)
In this research article, we synthesized nanospheres of MgO thin-film substrate using the successive ionic layer adsorption and reaction (SILAR) technique on stainless steel substrates. The final optimized sample was used for physical characterization. XRD revealed the cubic structure of the MgO electrode. Additionally, it was utilized for electrochemical supercapacitive characterization, including cyclic voltammetry (CV), chronopotentiometry, and electrochemical impedance spectroscopy (EIS). Results showed that MgO nanospheres exhibited a higher specific capacitance (SC) of 536.06 F/g. The maximum values of specific energy and specific power were 30.79 Wh/kg and 1420 W/kg, respectively, at 2 mA/cm2 in 1-M KOH. The EIS plot confirmed an internal resistance (Ri) of 0.86 omega, indicating good power performance and outstanding rate capability of MgO nanospheres. This material demonstrated excellent cycling capability, retaining 91.38% capacitance after 5000 CV cycles. The MgO//AC device displayed an SC of 210.21 F/g at 5 mV/s in a PVA-KOH solid-state electrolyte. With an energy density of 23.90 Wh/kg and a power density of 1.84 kW/kg, the asymmetric supercapacitor performance showed that the MgO-based electrode is suitable for use in actual device manufacturing. After 5000 CV cycles, the supercapacitor device exhibited exceptional capacitance retention of 92.93%. Thus, this research successfully demonstrated the usefulness of the simple and affordable SILAR method for synthesizing pure MgO nanostructures for application in supercapacitors.

Electrochemically enabled (3+2) cycloaddition of unbiased alkenes and β-dicarbonyls - Suryawanshi, Sharad M.; Sahoo, Suman; Shaligram, Parth S.; Manna, Narugopal; Samanta, Ramesh C. (Chemical Communications, 2024)
A (3+2) cycloaddition between unbiased alkenes and 1,3-dicarbonyls is accomplished by judicious choice of electrode material and electrocatalyst to access dihydrofuran derivatives. A fluorinated porous carbon electrode with appropriate thickness governs unprecedented reactivity. This methodology eliminates the necessity for any stabilizing group within the alkene substrate. This is a rare example of the annulation of unbiased internal and terminal alkenes with cyclic and acyclic beta-dicarbonyls.
Keywords: 1; 3-DICARBONYL COMPOUNDS; DIHYDROFURANS; FACILE SYNTHESIS

Electrodeposited Co-Mn-Sn multicomponent alloy as an efficient electrocatalyst for hydrogen evolution reaction - Chandran, M. Athira; Karumuthil, Subash Cherumannil; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (International Journal of Hydrogen Energy, 2024)
Despite having exciting material characteristics, the potential of multi-component alloys (MCAs) as electrocatalysts has not been fully realized. In this work, efficient binary and ternary MCA electrocatalysts containing inexpensive metals like Co, Mn and Sn have been prepared via the electrodeposition process. When tested for hydrogen evolution reaction (HER) in an alkaline medium, ternary Co-Mn-Sn alloy displayed enhanced activity with the lowest overpotential of 136 mV, a Tafel slope of 111 mV dec 1 and a very low charge transfer resistance, making it superior to the binary alloys (Co-Mn and Co-Sn), or the single metal catalysts (Co, Mn and Sn). The ternary alloy also displayed high electro-chemical and structural stability, making it a viable electrocatalyst for the hydrogen economy.(c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Clean energy; electrocatalysis; Electrodeposition; hydrogen evolution reaction; Multi-component alloy; Non-platinum group metals

Electrostatics choreographs the aggregation dynamics of full-length TDP-43 via a monomeric amyloid precursor - Doke, Abhilasha A.; Jha, Santosh Kumar (Biochemistry, 2024)
TDP-43 is a ubiquitously expressed, multidomain functional protein that is distinctively known to form aggregates in many fatal neurodegenerative disorders. However, the information for arresting TDP-43 aggregation is missing due to a lack of understanding of the molecular mechanism of the aggregation and structural properties of TDP-43. TDP-43 is inherently prone to aggregation and has minimal protein solubility. Multiple studies have been performed on the smaller parts of TDP-43 or the full-length protein attached to a large solubilization tag. However, the presence of co-solutes or solubilization tags is observed to interfere with the molecular properties and aggregation mechanism of full-length TDP-43. Notably, this study populated and characterized the native, dimeric state of TDP-43 without the interference of co-solutes or protein modifications. We observed that the electrostatics of the local environment is capable of the partial unfolding and monomerization of the native dimeric state of TDP-43 into an amyloidogenic molten globule. By employing the tools of thermodynamics and kinetics, we reveal the structural characteristics and temporal order of the early intermediates and transition states during the transition of the molten globule to beta-rich, amyloid-like aggregates of TDP-43, which is governed by the electrostatics of the environment. The current advanced understanding of the nature of native and early aggregation-prone intermediates, early steps, and the influence of electrostatics in TDP-43 aggregation is essential for drug design.

Engineered PLGA core-lipid shell hybrid nanocarriers improve the efficacy and safety of irinotecan to combat colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS BIOMATERIALS SCIENCE & ENGINEERING, 2024)
Keywords: BULK-POLYMERIZATION; Drug-delivery; LIPOSOMAL DOXORUBICIN

Engineering inhibitory repeat domains of Pin-II type proteinase inhibitors indicate their high structural-functional tolerance to mutagenesis - Barbole, Ranjit S.; Joshi, Rakesh S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2024)
Plant proteinase inhibitors (PIs) are critical in defending against biotic stress. Most PIs contain an inhibitory repeat domain (IRD), which serves as the functional component, displaying a high degree of sequence and structural conservation. In this study, we examined the structural and functional resilience of IRDs using a combination of computational modeling and experimental validation. We have taken an evolution-based approach to enhance the PIs effectiveness of two previously identified Capsicum annuum IRDs, IRD4 and IRD10. Through in silico site-saturation mutagenesis of IRD4 and IRD10, we identified key sites associated with enhanced PI activity for targeted mutagenesis. Binding energy predictions for a mutant IRD library, tested against target proteases, suggested that positions R11 and N32 in IRD4 and N32 and H33 in IRD10 were promising candidates for further modification to improve inhibitory potential. Subsequent experimental validation revealed that the mutant proteins IRD4_R11K and IRD4_N32S exhibited stronger chymotrypsin inhibition than the wild-type (WT) IRD4. Similarly, the mutants IRD10_N32S and IRD10_H33 N demonstrated improved trypsin inhibition relative to the WT IRD10. These findings indicate that engineered IRD variants can tolerate structural changes while maintaining or enhancing their inhibitory activity against target proteases. Overall, this study demonstrates the potential of engineering PIs to increase their structural and functional resilience, offering new opportunities for biotechnological applications.
Keywords: Capsicum annum; Inhibitory repeat domain; molecular modeling; plant proteinase inhibitors; Proteases; Saturation mutagenesis

Enhanced catalytic conversion of disaccharides to propylene glycol using metal-supported graphitic carbon nitride - Kirali, Arun Arunima Balachandran; Narayanan, Hariprasad; Viswanathan, Balasubramanian; Yadav, Parmeshwar; Marimuthu, Banu (Energy and Fuels, 2024)
Propylene glycol (or) 1,2-propanediol (1,2-PD) is an important polyol widely used for pharmaceuticals, polyester resins, paints, cosmetics, antifreeze, etc. Sucrose has emerged as a promising feedstock to produce 1,2-PD, as indicated by recent research findings. Graphitic carbon nitride (g-C3N4/gCN) was synthesized by using different crucibles. Ni-Mo was loaded on different g-C3N4 supports via the wetness impregnation method for sucrose hydrogenolysis. Effects of different g-C3N4 supports were studied. Catalysts with varying Ni (x = 0-8 wt %) and Mo (y = 0-15 wt %) contents were characterized using XRD, BET, XPS, FE-SEM, Py-FTIR, HR-TEM, TPD (CO2)and Raman spectroscopy. An attempt was made on sucrose conversion into 1,2-PD using a Ni-Mo/g-C3N4 catalyst. The catalyst containing 8% Ni and 10% Mo on Gr-gCN exhibited the best performance, achieving complete sucrose conversion with a 76% yield of 1,2-PD under mild reaction conditions. The presence of highly dispersed nanoparticles and the nature of graphitic carbon nitride help improve the reactions' yield by allowing reactions at lower temperatures, reducing the occurrence of side reactions, and increasing recycling rates. A straightforward approach to material preparation, coupled with the exceptional dispersion of metal nanoparticles, paves the way for a novel platform for biomass conversion.

Enhanced degradation of ciprofloxacin hydrochloride using hybrid advanced oxidation process of hydrodynamic cavitation and ozonation - Bodawar, Narendra; Shetty, Rohit; Kamble, Sanjay; Kulkarni, Prashant (Chemical Engineering & Technology, 2024)
The degradation of ciprofloxacin hydrochloride (CFX), an extensively utilized antibiotic for bacterial infections, has been studied through the application of advanced oxidation processes (AOPs) including hydrodynamic cavitation (HC), ozonation (O3), the Fenton reaction, chemical oxidation, and hybrid AOPs such as HC/O3 and Fenton/O3. Among these, the hybrid combination of HC/O3 demonstrated the highest CFX degradation of 99.82 % within 180 min having an initial concentration of 1000 ppm. The optimization of the HC/O3 process was conducted by varying parameters including initial concentration, pH, ozone (O3) gas flowrate, and temperature. Throughout the degradation process, CFX underwent intermediate formation, which gradually degraded over time. The hydrodynamic cavitation (HC) in combination with ozone, referred to as the HC/ozonation process, was used for the degradation of ciprofloxacin hydrochloride present in wastewater. This process underwent optimization with respect to various reaction parameters, including the initial concentration, ozone flow rate, pH level, temperature, the influence of ions, and the specific water matrix. At these optimized conditions a degradation efficiency of 99.82 % was achieved after 180 min. image
Keywords: active pharmaceutical ingredients; Advance Oxidation Processes; Ciprofloxacin hydrochloride; Hybrid AOPs; Hydrodynamic cavitation

Enhanced disinfection efficiency using Cu vortex diode for providing safe drinking water: devising newer methodologies - Dixit, Divya; Balapure, Kshama; Bhandari, Vinay M. (Environmental Quality Management, 2024)
The present research aims to refine the hydrodynamic cavitation technique with traditional knowledgebase of Ayurveda for more efficient water disinfection and that has huge potential for implementation in real life, especially for substituting the existing chlorination method for drinking water treatment. The study incorporates use of newer copper reactor configuration, employing vortex flow for generating cavitation for the disinfection of water. Elimination of model contaminant, Escherichia coli, with initial concentration of ∼105 CFU/mL of bacteria was used for the disinfection study. Copper vortex diode with a capacity of 1 m3/h was employed as a cavitating device. The cavitation using copper vortex diode gave significantly higher disinfection, over 30%, compared that with conventional vortex diode, with aluminum as material of construction, under similar conditions. Remarkably, the addition of 0.1% betel leaf oil led to an extraordinary 260-fold increase in the rate of disinfection, requiring only a single pass to achieve complete bacteria elimination. Furthermore, a notably high synergistic index of 246.96 was achieved for the process intensification approach using the Cu vortex diode. The cost was substantially reduced by approximately three times to 0.011 $/m3 using the Cu vortex diode compared to the conventional vortex diode. The developed strategy offers significantly enhanced performance, as well as a techno-economical and sustainable solution for drinking water treatment to ensure the provision of safe drinking water. Moreover, the newer methodology can have the advantage of producing no harmful carcinogenic disinfection by-products compared to chemical disinfection processes apart from sustainable alternative to chlorination.

Enhancing the Catalytic Activity of Pd Nanocrystals towards Suzuki Cross-Coupling by g-C3N4 Photosensitization - Mondal, Sanjit; Sahoo, Lipipuspa; Banoo, Maqsuma; Vaishnav, Yuvraj; Prabhakaran Vinod, Chathakudath; Gautam, Ujjal (Chemnanomat, 2024)
Developing renewable means of activating molecules over traditional catalysts for C-C bond formation is desirable for industrial applications. Herein, we report a strategy to improve the efficiency of Pd nanoparticles (NPs) for the Suzuki cross-coupling reactions by visible-light irradiation using g-C3N4 nanosheets (NSs) as photosensitizer. Pd NPs mounted on g-C3N4 become electron-rich under visible-light due to generation of excited electrons in g-C3N4 and thereby accelerate the rate-determining step. Remarkable photocatalytic activity was accomplished utilizing Pd/g-C3N4 for the Suzuki cross-coupling reaction in environmentally benign aqueous settings under room temperature conditions. The activity remarkably improves (similar to 2.5 times) upon light irradiation, yielding one of the highest known turnover frequencies (TOF) of 1858 h(-1) and confirming the photosensitizer role of g-C3N4. The TOF for coupling of aryl bromides is also significantly high (similar to 356 h(-1)). We establish that the low-energy/long-lived excitons preferencially transfer to Pd, paving a way for rational designing photocatalysts for various C-C coupling reactions.
Keywords: 2D graphitic carbon nitride; C-C cross-coupling; exciton transfer; heterogeneous photocatalyst; Photosensitization

Enhancing the crystallization kinetics and mechanical properties of poly(lactic acid) blends for 3D printing application - Kothavade, Premkumar; Yadav, Prashant; Gopal, Animesh; Pol, Harshawardhan; Kafi, Abdullah; Bateman, Stuart; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2024)
3D printing of poly(lactic acid) (PLA) blends has been attempted to resolve issues such as inherent brittleness and slow crystallization rate of PLA. However, a persistent challenge remains in the form of phase separation or gradual migration of the blended soft polymer or plasticizers. To simultaneously enhance the miscibility of the blends and toughness of 3D-printed parts, a triblock copolymer PLA-PEG-PLA was synthesized and blended with PLA in varying proportions (5, 10, 15, and 20 wt %). Blending only 10-20 wt % low molecular weight PLA-PEG-PLA into PLA yielded a miscible blend that showed a 45-fold increase in elongation at break and a 23-fold enhancement in toughness over neat PLA. Scanning electron microscopy (SEM) images of fractured cross sections revealed a brittle to ductile transition in 3D-printed PLA/PLA-PEG-PLA samples. Isothermal crystallization studies and data analysis using the Avrami equation showed an enhancement in the crystal growth rate and overall rate of crystallization. The blends achieved half of their crystallinity in approximately 3 min, a significant improvement over the 9 min required by PLA alone. This underscores the efficiency of our approach. This was also evident in the spherulite growth of 3D-printed PLA and mPLA blends when examined using polarized optical microscopy (POM). To the best of our knowledge, this is the first report exploring the use of blends that include PLA and low molecular weight PLA-PEG-PLA triblock copolymers for 3D printing applications.
Keywords: Crystallization; FFF 3D printing; PLA-PEG-PLA triblock copolymer; poly(lacticacid); toughness

Entropy-driven reversible melting and recrystallization of layered hybrid perovskites - Rajput, Parikshit Kumar; Salunkhe, Parashurama; Sarma, Manmayuri; Basu, Meghasree; Gopal, Animesh; Joshi, Aprajita; Shingote, Ajinkya Sundarnath; Saha, Surajit; Rahman, Atikur; Nag, Angshuman (SMALL, 2024)
Keywords: hybrid perovskites; photodetector; reversible melting

Environment friendly synthesis of reduced graphene oxide from spent lithium-ion battery graphite and its nanocomposite with MoO3 nanorods for photocatalytic hydrogen evolution - Kangutkar, Raju S.; Walko, Priyanka; Athira, K.; Manjanna, J.; Devi, R. Nandini (Energy & Fuels, 2024)
Photocatalytic water splitting from solar H2 generation systems is of great interest as a sustainable fuel and an environmentally benign approach. A photocatalyst should be cost-efficient and highly productive to obtain a green H2 fuel. Thus, photocatalytic water splitting is significant for real-world applications. In the present work, we have successfully synthesized MoO3@rGO nanocomposite material with heterojunction as a stable and high-performance photocatalyst for the H2 evolution reaction in deionized (DI) water and natural seawater. First, MoO3 was prepared through a low-temperature hydrothermal method and composites with graphene oxide (GO) and reduced graphene oxide (rGO) precursors, followed by ultrasonication. rGO was obtained from GO, which is obtained from the spent graphite (anode material) by the modified Hummer's method. The rGO powder was reduced by an ascorbic acid-reducing agent under microwave irradiation using GO. The nanocomposite materials were characterized using XRD, Raman spectra, XPS, photoluminescence, FE-SEM, HR-TEM, and BET. The photocatalytic water splitting ability of MoO3@rGO was measured under visible light (lambda >= 420 nm) irradiation with the TEOA sacrificial reagent. The H2 generation rate in DI water and natural seawater was found to be 2183.41 and 2294.26 mu mol g-1 h-1, with an apparent quantum efficiency (AQE) of 5.72 and 5.98%, respectively. Such a high rate of H2 generated is ascribed to the novel surface contact between MoO3 and the rGO sheet as evident from HR-TEM images, wherein the rGO sheet is seen wrapped around MoO3. Consequently, the synergistic effect between MoO3 and rGO sheets is expected without the use of any other cocatalysts. Thus, electron-hole recombination is significantly minimized during the water reduction reaction. We believe that the MoO3@rGO nanocomposite is a potential photocatalyst for energy production.

Establishing a new efficiency descriptor for methanol oxidation reaction and its validation with commercially available Pt-based catalysts - Deshpande, Pooja S.; Radhakrishnan, Thulasi; Prasad, Bhagavatula L. V. (Fuel Cells, 2024)
Direct methanol fuel cells (DMFCs) have received a lot of attention in recent years as promising technology for generating clean and efficient energy. In DMFC, the anode catalyst is a vital component because it is involved in the oxidation of methanol, which produces electrons that can be used as an energy source. Cyclic voltammetry (CV) is commonly used to test the characteristics of the electrode materials before they are employed in the actual fuel cell. Interestingly in the case of DMFCs CV also is a useful technique to obtain vital information about the performance and expected efficiency of the electrodes. In general, the CV of methanol electrooxidation for Pt-based catalysts has two peaks, If in the forward scan (anodic scan) and Ib in the backward scan (cathodic scan). The ratio of these two peaks (If/Ib) is the most commonly used criterion for investigating CO poisoning in catalysts. However, there is a great deal of ambiguity surrounding this criterion, owing to the genesis of Ib. Addressing this we present here a new criterion to evaluate the efficiency of the catalyst using the same CV technique. We validate this newly proposed criterion with commercial Pt/C (comm. Pt/C) and other commercially available alloy catalysts.
Keywords: catalyst poisoning; CO tolerance; direct methanol fuel cells; electrocatalysis; Methanol oxidation reaction

The ex situ exsolved exsolved Ni-Ru alloy from nickel-ruthenium co-doped SrFeO perovskite as a potential catalyst for C=C and C=O hydrogenation - Bhavisha, Meloth; Balamurugan, Sarkarainadar; Gopinath, Chinnakonda S.; Sakthivel, Ayyamperumal (SUSTAINABLE ENERGY & FUELS, 2024)
Keywords: LIQUID-PHASE HYDROGENATION; OXIDE FUEL-CELLS

Experimental and kinetic modelling studies for the design of fixed bed methanol reactor over CuZA catalyst - Bagwan, Farahanaz M.; Dongapure, Pavan; Kulkarni, Amol A.; Vasireddy, Satyam Naidu (Chemical Engineering Research Design, 2024)
Direct conversion of CO 2 via hydrogenation to value-added chemicals is a vital approach for utilising CO 2 emitted into the atmosphere. In this paper, a critical analysis of reaction kinetic modelling studies is explored in a fixed bed reactor to improve methanol yield for different H 2 to CO 2 ratios by simulating a lab-scale reactor for adiabatic and isothermal conditions. The feed inlet temperature and pressure variations are applied to study the effect of both configurations on methanol production. The results show that the isothermal configuration yields 2.76% more methanol yield compared to the adiabatic reactor. The effect of H 2 to CO 2 molar ratios of 3, 6 and 9 on the performance of the catalyst and the influence of CO and CO 2 hydrogenation is investigated with model simulations. The overall methanol yield is increased from 19.03% to 36.41% with increase in H 2 to CO 2 molar ratio from 3 to 9. Experiments are performed using commercial copper-based catalyst for different temperatures of 210, 230 and 250 degrees C at a pressure of 40 bar for H 2 /CO 2 of 3 and GHSV of 720 h -1 as well as at optimal temperature of 250 degrees C and 50 bar with varying H 2 /CO 2 of 3, 6, 9 for 3 g and 6 g catalyst. The maximum methanol yield of 2.53% and space time yield of 13.59 mg/g cat .h is obtained at H 2 /CO 2 ratio of 9.
Keywords: CO2 conversion; CuZA catalyst; H2 toCO2 molar ratio; Kinetic modelling; Methanol

An explainable AI-assisted web application in cancer drug value prediction - Kothari, Sonali; Sharma, Shivanandana; Shejwal, Sanskruti; Kazi, Aqsa; D'Silva, Michela; Karthikeyan, M. (MethodsX, 2024)
<div class="u-margin-s-bottom" id="spara003" style="box-sizing: border-box; margin-top: 0px; margin-right: 0px; margin-left: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px; margin-bottom: 16px !important;"> In recent years, there has been an increase in the interest in adopting Explainable Artificial Intelligence (XAI) for healthcare. The proposed system includes <ul class="list" style="box-sizing: border-box; margin: 16px 0px; padding-right: 0px; padding-left: 0px; list-style: none; display: grid; grid-template-columns: fit-content(15%) fit-content(85%); gap: 0px 16px;"> • An XAI model for cancer drug value prediction. The model provides data that is easy to understand and explain, which is critical for medical decision-making. It also produces accurate projections. • A model outperformed existing models due to extensive training and evaluation on a large cancer medication chemical compounds dataset. • Insights into the causation and correlation between the dependent and independent actors in the chemical composition of the cancer cell. <div class="u-margin-s-bottom" id="spara007" style="box-sizing: border-box; margin-top: 0px; margin-right: 0px; margin-left: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px; margin-bottom: 16px !important;"> While the model is evaluated on Lung Cancer data, the architecture offered in the proposed solution is cancer agnostic. It may be scaled out to other cancer cell data if the properties are similar. The work presents a viable route for customizing treatments and improving patient outcomes in oncology by combining XAI with a large dataset. This research attempts to create a framework where a user can upload a test case and receive forecasts with explanations, all in a portable PDF report.

Explainable AI-assisted web application in cancer drug value prediction - Kothari, Sonali; Sharma, Shivanandana; Shejwal, Sanskruti; Kazi, Aqsa; D'Silva, Michela; Karthikeyan, M. (MethodsX, 2024)
<div class="u-margin-s-bottom" id="spara003" style="box-sizing: border-box; margin-top: 0px; margin-right: 0px; margin-left: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px; margin-bottom: 16px !important;"> In recent years, there has been an increase in the interest in adopting Explainable Artificial Intelligence (XAI) for healthcare. The proposed system includes <ul class="list" style="box-sizing: border-box; margin: 16px 0px; padding-right: 0px; padding-left: 0px; list-style: none; display: grid; grid-template-columns: fit-content(15%) fit-content(85%); gap: 0px 16px;"> • An XAI model for cancer drug value prediction. The model provides data that is easy to understand and explain, which is critical for medical decision-making. It also produces accurate projections. • A model outperformed existing models due to extensive training and evaluation on a large cancer medication chemical compounds dataset. • Insights into the causation and correlation between the dependent and independent actors in the chemical composition of the cancer cell. <div class="u-margin-s-bottom" id="spara007" style="box-sizing: border-box; margin-top: 0px; margin-right: 0px; margin-left: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px; margin-bottom: 16px !important;"> While the model is evaluated on Lung Cancer data, the architecture offered in the proposed solution is cancer agnostic. It may be scaled out to other cancer cell data if the properties are similar. The work presents a viable route for customizing treatments and improving patient outcomes in oncology by combining XAI with a large dataset. This research attempts to create a framework where a user can upload a test case and receive forecasts with explanations, all in a portable PDF report.

Exploring defect-engineered metal-organic frameworks with 1,2,4-triazolyl isophthalate and benzoate linkers - Chetry, Sibo; Lukman, Muhammad Fernadi; Bon, Volodymyr; Warias, Rico; Fuhrmann, Daniel; Moellmer, Jens; Belder, Detlev; Gopinath, Chinnakonda S.; Kaskel, Stefan; Poeppl, Andreas; Krautscheid, Harald (INORGANIC CHEMISTRY, 2024)
Keywords: Separation; spectroscopy; TRIAZOLYL

Exploring novel cocrystals of milrinone: a cardioprotective drug combined with nutraceuticals and an NSAID - Kenguva, Gowtham; Rekha Rout, Smruti; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CrystEngComm, 2024)
Milrinone is a bipyridine phosphodiesterase (PDE) inhibitor of the second generation. It's a PDE-III antagonist that raises cAMP levels to support heart function and acts as a systemic vasodilator in chronic decongested cardiovascular illness. It is categorised as class II in the Biopharmaceutics Classification System (BCS), indicating that it exhibits poor aqueous solubility and high permeability. Three new cocrystals of the cardioprotective drug milrinone (MR) with two nutraceuticals, e.g. sesamol (SES) and resveratrol (RES), and an anti-inflammatory drug, e.g. niflumic acid (NIF), were successfully synthesised using mechanochemical and solution crystallisation techniques. Thermal analysis (DSC and TGA) and diffraction tools (PXRD and SCXRD) were used to obtain structural insights into all the cocrystals. Their crystal structures indicate that the dimeric interactions in MR are preserved in the crystal structures in addition to carboxylic acid/phenol & ctdot;pyridine heterosynthons. Among the three synthesized molecular solids, MR.SES was more soluble than the native drug. The solubility of the cocrystals was correlated with polar surface contacts, the solubility of the coformer and melting points (inversely). We believe that the new MR.SES cocrystal offers a novel approach to enhance the drug's solubility, which may have a positive impact on its synergistic cardioprotective effects.

Exploring the catalytic potential of Mg-Cu alloys for enhanced activity toward CO2 hydrogenation - Thakkar, Kavita; Joshi, Kavita (Molecular Catalysis, 2024)
CO2, a well-known greenhouse gas, is a potential raw material that can produce various chemicals. Dissociation of CO2 to CO or hydrogenation to formate (HCOO*) or carboxyl (COOH*) intermediate is crucial in determining the reaction pathway for CO2 conversion. In this work, we demonstrate that alloys of Mg-Cu exhibit greater activity toward activation and hydrogenation of CO2 than transition metal alloys reported so far. Two different compositions of Mg-Cu, namely Mg2Cu and MgCu2, have been studied using periodic Density Functional Theory (DFT). Our investigations reveal that CO2 chemisorbs on both intermetallic alloys. Coadsorption of CO2 with H2O leads to the spontaneous formation of COOH* over Mg2Cu(224), whereas a negligible barrier (0.04 eV) is observed for MgCu2(311). HCOO* formation has a barrier of 0.34 eV and 0.42 eV on Mg2Cu(224) and MgCu2(311), respectively. Dissociation of CO2 to CO is kinetically unfavourable on both compositions of Mg-Cu. We provide a rationale for the observed activity by analyzing the electronic structure. Notably, the spontaneous hydrogenation of CO2 makes earth -abundant metals suitable candidates for alloying that await experimental verification.
Keywords: CO2 hydrogenation; DFT; Mg2Cu; MgCu2

Exploring the CeO2 support morphology for the carbon dioxide hydrogenation reaction using nickel catalysts - Gupta, Sharad; Jagtap, Anuradha; Vinod, C. P. (Journal of Physical Chemistry C, 2024)
The catalytic activity and stability are examined for the hydrogenation of carbon dioxide under atmospheric pressure over 2 wt % Ni/CeO2 nanorods (2Ni-CeNRs), nanocubes (2Ni-CeNCs), and nanopolyhedra (2Ni-CeNPs). The 2Ni-CeNR catalysts display excellent catalytic activity and higher stability compared with 2Ni-CeNC and 2Ni-CeNP catalysts. A comprehensive understanding of the surface atomic and electronic structure versus activity has been derived using high-resolution electron microscopy and spectroscopy techniques. High metal dispersion, strong metal-support interaction (SMSI) effect and abundant oxygen vacancies are deduced to play a crucial role in determining the catalytic activity and selectivity of the CO2 hydrogenation reaction.

Exploring the soft pinning effect in the dynamics and the structure-dynamics correlation in multicomponent supercooled liquids - Anwar, Ehtesham; Patel, Palak; Sharma, Mohit; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2024)
We study multicomponent liquids by increasing the mass of 15% of the particles in a binary Kob-Andersen model. We find that the heavy particles have dual effects on the lighter particles. At higher temperatures, there is a significant decoupling of the dynamics between heavier and lighter particles, with the former resembling a pinned particle to the latter. The dynamics of the lighter particles slow down due to the excluded volume around the nearly immobile heavier particles. Conversely, at lower temperatures, there is a coupling between the dynamics of the heavier and lighter particles. The heavier particles' mass slows down the dynamics of both types of particles. This makes the soft pinning effect of the heavy particles questionable in this regime. We demonstrate that as the mass of the heavy particles increases, the coupling of the dynamics between the lighter and heavier particles weakens. Consequently, the heavier the mass of the heavy particles, the more effectively they act as soft pinning centers in both high and low-temperature regimes. A key finding is that akin to the pinned system, the self-dynamics and collective dynamics of the lighter particles decouple from each other as the mass of the heavy particles has a more pronounced impact on the latter. We analyze the structure-dynamics correlation by considering the system under the binary and modified quaternary framework, the latter describing the pinned system. Our findings indicate that whenever the heavy mass particles function as soft pinning centers, the modified quaternary framework predicts a higher correlation.

Exploring the synthesis, characterization, electrical, and magnetic behavior of crystalline Ni1-xZnxFe2O4 nanoparticles - Adsure, Kiran T.; Jagtap, Sumant B.; Newaskar, Shivkumar R.; Kore, Kiran B.; Funde, Adinath M.; Patange, Sunil M.; Late, Dattatray J. (JOURNAL OF MATERIALS SCIENCE-MATERIALS IN ELECTRONICS, 2024)
Keywords: CO; DC RESISTIVITY; DIELECTRIC-PROPERTIES; FERRITE NANOPARTICLES; Ni; Substitution; ZN

Exploring thermocatalytic pyrolysis to derive sustainable chemical intermediates from plastic waste; role of temperature, catalyst, and reactor conditions - Venkataraghavan, R.; Bhure, Arvind; Khan, Tufeil Sartaj; Shikare, Dipak; Devi, R. Nandini; Dhepe, Paresh Laxmikant (Journal of the Indian Institute of Science, 2024)
Plastic waste is a growing concern globally on account of the increasing use of plastic worldwide, compounded by single-use applications, poor waste collection and management practices, and its consequent leakage into the environment. In addition, plastics are derived from non-renewable fossil resources, and their growing demand is also partly responsible for greenhouse gas emissions and climate change. The aim of this paper is to explore the potential of plastic waste as a material resource, and thermocatalytic pyrolysis as a recycling process, to produce aliphatic and aromatic hydrocarbons, which are important chemical intermediates for various industries. We show that plastic pyrolysis can achieve a high yield of liquid hydrocarbons (similar to 80%) with a suitable distribution of aliphatic and aromatic compounds, by using different pyrolysis conditions and a catalyst. Specifically, this paper demonstrates the possibility of deriving two key classes of hydrocarbons, i.e., aliphatic (C10-C20 hydrocarbons) and aromatic hydrocarbons (xylene, toluene and benzene derivatives) with a yield of similar to 80% liquid hydrocarbons via catalytic pyrolysis. We also briefly discuss the challenges and opportunities, and the environmental and economic implications.

Exploring unconventional σ-hole interactions: computational insights into the interaction of XeO3 with non-aromatic coordinating solvents - Dash, Soumya Ranjan; Vanka, Kumar (Chemphyschem, 2024)
In order to control the explosiveness and shock sensitivity of XeO3, we have investigated its plausible interaction with various non-aromatic coordinating solvents, serving as potential Lewis base donors, through density functional theory (DFT) calculations. Out of twenty six such solvents, the top ten were thus identified and then thoroughly examined by employing various computational tools such as the mapping of the electrostatic potential surface (MESP), Wiberg bond indices (WBIs), non-covalent interaction (NCI) plots, Bader's theory of atoms-in-molecules (AIM), natural bond orbital (NBO) analysis, and the energy decomposition analysis (EDA). The amphoteric nature of XeO3 was also explored by investigating the extent of back donation from the lone pair of Xe to the antibonding orbital of the donating atom/group of the solvent molecules. The C-H & mldr;O interactions were also found to be a contributing factor in the stabilization of these adducts. Although these aerogen-bonding interactions were found to be predominantly electrostatic, significant contributions from the orbital contributions, as well as dispersion interactions, were observed. The top three non-aromatic solvents (among the twenty six studied) which form the strongest adducts with XeO3 are proposed to be hexamethylphosphoramide (HMPA), N,N `-dimethylpropyleneurea (DMPU) and tetramethylethylenediamine (TMEDA).
Keywords: Aerogen bonding; Non-Aromatic Solvents; non-covalent interactions; Sigma-hole; XeO3

Extraction, characterization, and life cycle assessment of nanosilica from millet husk: sustainable alternative with low environmental impact - Dominic, C. D. Midhun; Rosa, Derval dos Santos; Barbosa, Rennan Felix da Silva; Anagha, O. V.; Neenu, K. V.; Begum, P. M. Sabura; Kumar, V. Aswathy; Parameswaranpillai, Jyotishkumar; Siriwong, Chomsri; Ajithkumar, T. G.; Shelke, Ankita; Pasc, Andreea (Journal of Cleaner Production, 2024)
Eco-friendly approaches for silica production are highly researched to respond increasing industrial demand for bio-nanofillers. Herein, nanosilica of 10-20 nm with mesoporosity was obtained through a mild oxalic acid pre-treatment of millet husk, followed by calcination at 700 degrees C for 2 h. Compared with commercial precipitated silica (CS) and millet husk ash (MHA) directly obtained by calcination of the husk, the pre-treated silica (MHS) had higher purity, revealed using EDX spectroscopy. Moreover, FTIR and Si-29 NMR showed a higher condensation degree in MHS with 73% of Q4 siloxane bonds vs 4% in MHA. The release of the metal and organic impurities from the husk also allows to reduce the crystallinity of MHS, and to increase the specific surface area from 82 m(2)/g in MHA to 238 m(2)/g in MHS. The type II N-2 adsorption-desorption isotherms of MHA and MHS indicate aggregates of non-porous silica particles. MHS also demonstrated remarkable thermal resilience. According to the LCA analysis, MHS has a 40% lower impact on global warming, a 38% lower impact on human carcinogenic toxicity, and a 38% lower impact on terrestrial acidification compared to rice husk nanosilica. This research thus addresses sustainability challenges by repurposing millet husks, which are readily available due to continuous millet cultivation, particularly in India. By reducing the ecological impact of husk disposal through burning, this study offers an economically viable technology for high-purity silica production, aligning with global efforts to combat climate change and promote sustainable practices.
Keywords: Life cycle assessment; Millet husk; Nanosilica; Oxalic acid

Extrusion 3D printing of intrinsically fluorescent thermoplastic polyimide: revealing an undisclosed potential - Kothavade, Premkumar; Kafi, Abdullah; Dekiwadia, Chaitali; Kumar, Viksit; Sukumaran, Santhosh Babu; Shanmuganathan, Kadhiravan; Bateman, Stuart (POLYMERS, 2024)
Keywords: Additive manufacturing; functional extrusion; high-performance polymers; thermoplastic polyimide

Early and advanced glycation end product analysis from women with PCOS on metformin - Ambekar, Aditi S.; Naredi, Nikita; Malakar, Dipankar; Vashum, Y.; Misra, Pratibha; Kulkarni, Mahesh (Reproductive Biology, 2025)
In this cross-sectional study, we have analyzed advanced glycation end products (AGEs) in the plasma and follicular fluid of women with polycystic ovary syndrome (PCOS) taking metformin during in vitro fertilization (IVF) and control women undergoing IVF. Glucose, fructose, fructosamine, carboxymethyl lysine/ arginine (CML/R) proteins, and pentosidine were measured in the plasma and paired follicular fluid. Glycated proteins were characterized by mass spectrometry. Fasting serum glucose and fructosamine were comparable; however, follicular fluid glucose and fructosamine were higher in the PCOS group, and other AGEs remained unaltered. Fructose was lower in both serum and follicular fluid from the PCOS group. A positive correlation between some of these AGEs and sugars estimated was observed. Glucose and fructosamine in the follicular fluid correlated with the antral follicle count. The number of glycated peptides identified in the PCOS group by mass spectrometry was more. Glycated K75, K402 amino acid residues of albumin were detected in the PCOS group only. Additionally, some proteins involved in steroidogenesis and oocyte maturation as well as transporters, and extracellular matrix proteins, were found to be glycated in the PCOS group, which may affect their function. Elevated glucose and fructosamine in the follicular fluid of the PCOS group may contribute to abnormal folliculogenesis. The glycation of albumin should be validated in more samples to be considered as a marker for PCOS diagnosis.
Keywords: Carboxymethyl lysine; Fructosamine; fructose; glucose; Pentosidine; Polycystic ovary syndrome

Effect of cyclization and alkyl group wrapping in visible-light-active unsymmetrical squaraine dyes for dye-sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Shivankar, Bhavana R.; Siby, Jesna; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
A series of alkyl group-appended indoline- and carboxylic acid-functionalized indolenine-based visible-light-active unsymmetrical squaraine dyes, SQA7-10, were designed, synthesized, and utilized for the dye-sensitized solar cells device fabrication. The number of alkyl group has been increased systematically on the indoline moiety to control the self-assembly of dyes on TiO2 and to passivate the photoanode that helps in improving the open-circuit voltage (V-OC) by avoiding the charge recombination process. SQA7-10 dyes showed an absorption between lambda(max) 536-540 nm, with molar extinction coefficients of 1.62-2.13 x 10(5) M-1 cm(-1) in CH3CN. Further, ultraviolet-visible (UV-vis) studies on TiO2 indicated the formation of H-aggregated dyes (505-510 nm), which can be controlled by appending the alkyl groups. The energy levels of the highest occupied molecular orbital (HOMO) of these dyes are well aligned with the Nernst potentials of I-/I(3)(-)electrolyte and [Cu(tmby)(2)](+/2+) electrolytes with sufficient overpotentials required for the dye regeneration process. DSSC devices made with these dyes showed systematic enhancements of open-circuit voltage (V-OC) and device efficiency with respect to alkyl group incorporation for SQA7-10 with I-/I-3(-) electrolytes. All of the SQA dyes exhibited the device V-OC of more than 805 mV, where the introduction of alkyl groups systematically enhanced the V-OC in the order of SQA7 (805 mV) < SQA8 (829 mV) < SQA9 (843 mV) < SQA10 (862 mV) without any addition of CDCA. Within the SQA dye series, SQA10 dye has achieved the highest DSSC device efficiency of 7.52% (J(sc) of 11.16 mA/cm(2), V-oc of 862 mV, and ff of 78%) with I-/I-3(-) electrolyte, whereas use of [Cu(tmby)(2)](+/2+) redox shuttle with SQA10 showed enhanced V-oc (1080 mV) and device efficiency (8.35%). The IPCE profile for the device fabricated with SQA dyes showed good response at 480 and 560 nm, which indicates the photocurrent generation from the aggregated structures.
Keywords: aggregation of dyes; charge recombination; Dye-sensitized solar cells; indoline and indolenine donors; visible-light-activeunsymmetrical squaraine dye

Effect of doping on electrocatalytic dehydrogenation and hydrogenation of methyl decalin-methyl naphthalene system - Verma, Tushar Singh; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2025)
The hydrogen economy can benefit from the use of liquid organic hydrogen carriers (LOHCs) for cross-continent hydrogen transportation in the future. However, dehydrogenation and hydrogenation of hydrogen require catalytic systems. Current research emphasizes selective Pt/Rh doping of Fe, Co, and Ni surfaces as catalysts for the dehydrogenation and hydrogenation of the methyl naphthalene-methyl decalin LOHC system, which has more than 7% hydrogen weight capacity and meets the practical requirements established by the European Union and the United States Department of Energy. Density functional theory-based computational techniques demonstrate how the chemical modification of these surfaces with a Pt and Rh single-atom catalyst (SAC) can improve the efficiency of dehydrogenation and hydrogenation. With a sustainable method, electrochemical dehydrogenation and hydrogenation on these robust surfaces produce effective hydrogen storage for extended periods without losing hydrogen. Furthermore, optimal results for the hydrogenation of 2-methyl naphthalene on Fe-Rh SAC with path-determining step (PDS) = 0.98 eV and dehydrogenation of 1-methyl decalin on Fe-Pt SAC with PDS = 1.49 eV were obtained for the most effective active sites for the enhanced electrochemical process. This study offers new possibilities for the catalytic dehydrogenation and hydrogenation of LOHC systems by highlighting the impact of doping on transition-metal-based catalysts.

An effective alliance for successful coupling: electrochemical alcohol oxidation mediated conversion of indoles to bis(indolyl)methanes - Baravkar, Mayur D.; Prasad, Bhagavatula L. V. (Journal of Applied Electrochemistry, 2025)
Electro-organic transformation of indoles to bis(indolyl)methanes (BIMs) has been successfully achieved by combining the electrochemical alcohol oxidation reaction (AOR) with indole coupling. The fact that it is the readily available alcohols and not the traditionally used aldehydes or ketones that provide the bridging -CH2- (methylene) for this transformation makes this path extremely attractive and valuable. The formation of aldehydes as reactive intermediates during the AOR has been dexterously utilized to achieve this transformation. Most gratifyingly, the transformation also can be carried out in water-alcohol mixtures and the yields and conversions are better than the most of the previously reported chemical catalytic transformations using specially designed metal complexes. Various substituted indoles were selectively converted to their corresponding BIMs in decent yields. This strategy could further be exploited for the synthesis of different natural products, including the much sought after deuterium substituted ones (as CD3OD is readily accessible), and other important biologically active alkaloids and drug molecules, etc.
Keywords: Alcohol oxidation reaction; Bis(indolyl)methanes; Direct alcohol fuel cell; Electroorganic transformations; Vibrindole A

Effectiveness of 3-amino-2-thiocyanato-α, β-unsaturated carbonyl compounds against chikungunya virus - Alagarasu, Kalichamy; Dhote, Radhika; Bagad, Pooja K.; Kharikar, Dwidhesh; Patil, Poonam; Roy, Diya; Shukla, Shridhar; Cherian, Sarah; Senthilkumar, Beeran; Parashar, Deepti (Future Medicinal Chemistry, 2025)
Aim Chikungunya fever (CHIKF) caused by the chikungunya virus (CHIKV) is characterized by the presence of long-term polyarthralgia in a minor proportion of the infected patients. Currently, there are no FDA-approved antivirals available. This study evaluated the anti-CHIKV potential of 16 synthetic 3-amino-2-thiocyanato-alpha, beta-unsaturated carbonyl compounds and elucidated their probable mechanisms of action. Methods Anti-CHIKV activity of 16 compounds were investigated in Vero CCL-81 cells using focus forming unit assay (FFU). Dose-dependent and time-dependent antiviral assays were performed for the effective compounds. Molecular docking was performed to find out their interactions with viral proteins. Results Five compounds showed promising anti-CHIKV activity by reducing viral titer with >1 log10 FFU/ml. Dose-dependent studies revealed that the compound 3 g was more effective in reducing the virus titer with a half-maximal inhibitory concentration (IC50) of 0.4315 mu M and a selectivity index of 35.99. Docking analyses revealed that all the compounds mainly interact with the non-structural proteins of CHIKV. Conclusions These findings demonstrate the in vitro anti-CHIKV activity of these compounds, and their possible mode of action via interference with early stages of infection and replication processes. This study warrants further preclinical and clinical evaluation to establish their safety and efficacy as novel anti-CHIKV therapeutics.
Keywords: 3-amino-2-thiocyanato-alpha; antivirals; beta-unsaturated carbonyl compounds; Chikungunya virus (CHIKV); nsP2 helicase; therapeutics

Efficient continuous catalytic process for production of bisphenol A - Dhotre, Kapil; Patil, Chetana Rupak; Tarade, Komal P.; Markandeya, Nishant; Pathak, Abhishek; Bhongale, Sunil S.; Kamble, Sanjay P. (Organic Process Research & Development, 2025)
Bisphenol A (BPA) is a versatile chemical compound that is essential for producing durable polycarbonate plastics and strong epoxy resins, which are integral to numerous everyday products. In the present study, BPA was prepared using phenol and acetone using a highly active and reusable ion-exchange resin (IER) Lewatit K1131S as the catalyst. Under optimized conditions, an acetone conversion of 84% and a BPA selectivity of 94% were achieved. The produced BPA was further purified, resulting in a 96% isolated yield with 99.5% purity. The reusability of Lewatit K1131S has been studied, and it was found that it can be reused multiple times without affecting the selectivity for BPA. The kinetics of the reaction was studied using the Langmuir-Hinshelwood model; it was found that the reaction follows pseudo-first-order kinetics, and the apparent activation energy was determined to be 12.7 kJ/mol. A continuous pilot scale process for the production of BPA using a fixed-bed reactor (packed with ion-exchange resin) has been developed. Pilot plant trials were conducted at different flow rates such as 200, 300, and 500 g/h, and a downstream processing methodology using an agitated thin film evaporator (ATFE) was employed for the BPA purification. This resulted in high throughput, producing 99.2% isolated BPA yield with 99.5% HPLC purity. Additionally, the robustness and viability of the catalyst were assessed at a flow rate of 200 g/h, producing 22.5 kg of BPA per kg of catalyst, highlighting its cost-effectiveness, stability, and resistance to deactivation, which shows its suitability for industrial-scale applications. The environmental viability of the process was further evaluated by using the E-factor and Process Mass Intensity (PMI) metrics. The estimated E-factor was 0.3118, while the corresponding PMI was 1.3935. These lower values indicate reduced waste generation, improved material efficiency, and enhanced sustainability of the process.
Keywords: bisphenolA; BPA purification; Continuous process; E-factor; ion-exchange resins (IER); PMI; process optimization; reactionkinetics

Efficient Copper-Catalyzed, One-Pot Synthesis of N2-Aryl Phosphoryl 1,2,3-Triazole 1-Oxides - Mujahid, M.; Bhavar, Akshay A.; Vara, Vijay; Gonnade, Rajesh; Muthukrishnan, M. (Asian Journal of Organic Chemistry, 2025)
A simple and facile one-pot process has been developed for the synthesis of N 2-aryl phosphoryl 1,2,3-triazole 1-oxide derivatives. This new approach utilizes simple and commercially available starting materials, operating under mild conditions. The method employs copper-catalyzed multicomponent reaction, involving the combination of arylhydrazines, beta-ketophosphonates, and tert-butyl nitrite. The developed protocol shows excellent functional group tolerance permitting an extensive range of substrate scope up to 92% isolated yield.
Keywords: Copper-catalyzed; Phosphoryl triazoles N-oxides; Phosphorylated compound; Triazole N-oxides

Efficient hydrogen liberation from autocatalytic wastewater treatment by green synthesized Ag2SeO3 nanocatalyst - Islam, Sk Najrul; Ansari, Ifra Ilyas; Gopinath, Chinnakonda S.; Ahmad, Absar (Inorganic Chemistry Communications, 2025)
Concerns about wastewater management, secure hydrogen storage, and interest in an affordable, effective, and user-friendly technique for releasing hydrogen have grown globally. Developing sustainable synthetic processes that result in industrially significant nanocatalyst to synergistically accelerate the evolution of hydrogen from wastewater treatment is extremely desirable. This work, for the first time, demonstrates the design and green fabrication of bactericidal silver selenite nanoparticles (Ag2SeO3 NPs) using the fungus Aspergillus niger for autocatalytic hydrogen production and methylene blue dye reduction by hydrolytic dehydrogenation of NaBH4. The morphology of Ag2SeO3 nanocatalysts with an average particle size of 60 nm was assessed by FETEM, while their surface chemistry, crystal structure, and optical properties were examined using XPS, XRD, and FTIR/ UV-Visible spectrophotometers, respectively. The sigmoidal trajectory of NaBH4 dehydrogenation with turnover frequencies (TOF) of 4750 mL g- 1 min- 1 suggested good autocatalytic activity of Ag2SeO3 NPs. The mechanistic study unveiled that autocatalysis was made possible by the creation of novel, active Ag co-catalyst which works synergistically with Ag2SeO3 NPs. For in-situ, real time assessment of Ag concentration during catalysis, hydrolysis of NaBH4 was carried out in the presence of methylene blue dye. The results showed that the active cocatalyst centers have a significant influence on autocatalytic hydrogen production at room temperature, reducing 98.8 % methylene blue (MB) dye in 6 min with a lesser hydrogen generation rate of 4174 mL g- 1 min- 1. The catalyst exhibited excellent stability and durability after fourth consecutive cycle, demonstrating its promise for long-term and recurring application in hydrogen liberation from autocatalytic MB dye reduction.
Keywords: Ag2SeO3 nanoparticles; Antibacterial; autocatalysis; Hydrogen generation; Wastewater treatment

Efficient synthesis of 3,3′-Spirooxindole γ-Butyrolactone via Rongalite-mediated domino reductive aldol and spiro-lactonization reactions - Chaudhari, Suryakant S.; Nichinde, Chandrakant B.; Patil, Baliram R.; Girase, Amardipsing S.; Kinage, Anil K. (ChemistrySelect, 2025)
In this study, we develop a novel methodology involving rongalite-mediated domino reductive/aldol reaction, followed by spiro-lactonization of 2-oxoindolin-3-ylidene acetates/malonates in presence of base to synthesis of 3,3 `-spirooxindole gamma-butyrolactone. The detail study, such as effect of solvent, effect of different base and substrate has been carried out. Scale up of this methodology is also done. Sodium hydroxymethanesulfinate dihydrate (rongalite) concurrently has a dual role in this context; it acts as a reducing agent as well as C1 synthon. This approach offers several advantages, such as being metal- and catalyst-free, involving a simple reaction protocol, having a wide substrate scope, using water as a green solvent, and providing good to excellent yields of the products under mild reaction conditions.
Keywords: (+/-) Coixspirolactam A & [3; 3 `-spirooxindole gamma-butyrolactone]; Domino reductive/aldol/spiro-lactonization; Good step economy; Rongalite as reductant & C1 synthon; Water as a green solvent

Efficient synthesis of functionalized alkylidenephthalides, butenolides, pyranones, and isocoumarins via I2-PPh3: synthesis of Thunberginols A and F - Abhang, Rohitkumar V.; Bhagwat, Prathamesh N.; Handore, Kishor L. (Organic & Biomolecular Chemistry, 2025)
A simple and efficient synthesis of functionalized alkylidenephthalides, butenolides, pyranones, and isocoumarins was achieved using I2-PPh3-Et3N reagent combination. The products obtained through this method act as versatile components in organic synthesis, enabling further modifications of functional groups. This method exhibits a wide substrate scope, employs straightforward and cost-effective reagents, eliminates the need for acidic, carbodiimide or other coupling agents, and operates at ambient temperature. Moreover, this methodology has been successfully applied to the synthesis of two natural products, Thunberginols A and F.

Electrochemical deconstruction of waste polyvinylidene chloride (PVDC) to value-added products in batch and flow - Mishra, Subhadip; Kar, Sourav; Rangappa, Raghavendrakumar; Patil, Prashant; Kadam, Vijay; Chikkali, Samir H.; Samanta, Ramesh C. (Chemistry-A European Journal, 2025)
Chlorinated polymers have made enormous contributions to materials science and are commercially produced on a large scale. These chlorinated polymers could be recycled as chlorine sources to efficiently produce valuable chlorinated compounds owing to their facile release of HCl. Although the thermal stability of PVDC is low compared to PVC, this can be advantageous in terms of easy and fast dehydrochlorination. Herein, we report an efficient electrochemical chlorination using poly(vinylidene chloride) (PVDC) as a chlorine source that works in an undivided cell and applies to a good number of examples. This method works on commodity polymers such as waste PVDC-PVC pharma blister film, PVDC-PO multilayer food packaging, and compression molded sheets of Ixan PVDC (with heat stabilizer) with similar efficiency. Furthermore, this method also provides the dechlorination of PVDC up to 98 %, leading to unsaturated dechlorinated material. Converting PVDC into more stable unsaturated compounds, the release of harmful chlorine-containing gases during incineration can be minimized. Additionally, this method is not only restricted to batch processes but an electroflow process for PVDC dechlorination and electrosynthesis has also been demonstrated.
Keywords: chlorination; Electrochemical recycling; Electroflow-synthesis; Graphitic material; Polyvinylidene chloride

Electronic, magnetic, and mechanical properties of co-doped GaSb: A promising diluted magnetic semiconductor - Samant, Ramnath; Saraf, Deepashri; Adhikari, Rajendra P.; Shilkar, Omkar; Raikar, Sakshit; Silveira, Allan; Sawant, Manthan; Sappati, Subrahmanyam; Joshi, Niharika; Desai, Ashish M. (Journal of Magnetism and Magnetic Materials, 2025)
{Understanding the interplay between magnetism and the electronic structure is crucial for the development of novel spintronic materials. This study employs density functional theory (DFT) calculations to investigate these properties in cubic Gallium Antimonide (GaSb) doped with Cobalt (Co) (Ga1-xCoxSb
Keywords: Density functional theory; Dilute magnetic semiconductors; Electronic properties; GaSb; mechanical properties; Spintronic materials

Energy-saving H2 production through H2S electrolysis accompanying solid sulfur recovery using a Ni3S2/Ni3N heterostructure as the electrocatalyst - Sinha, Nibedita; Das, Chandni; Pal, Santanu; Roy, Poulomi (ACS Applied Energy Materials, 2025)
The thermodynamically feasible electrochemical sulfion oxidation reaction (SOR) is advantageous for degrading the toxic H2S pollutant into the value-added chemical sulfur but often suffers from catalyst passivation due to blockage of electroactive sites by accumulation of solid sulfur. The strategic design of electrocatalysts with enhanced electrochemical activity and improved sulfur tolerance is thereby crucial to fully harness the benefits of the SOR. In this work, we developed nickel sulfide nanorods decorated with nickel nitride nanoparticles directly grown on conductive nickel foam as an efficient trifunctional electrocatalyst for the SOR, oxygen evolution reaction (OER), and hydrogen evolution reaction (HER). Optimized Ni3S2/Ni3N showed lower electrode potentials of 0.25, 1.487, and 0.89 V to achieve a benchmark current density of 10 mA cm(-2) for the SOR, OER, and HER, respectively. The hybrid H2S electrolysis setup employing a Ni3S2/Ni3N electrocatalyst drastically reduced the cell potential by 1.24 V compared to that of conventional water electrolysis at a current density of 200 mA cm(-2). Having said that, heterostructure formation not only enhances the activity for the SOR but also helps to avoid sulfur poisoning, enabling the electrocatalyst to sustain for 100 long hours at a high current density of 100 mA cm(-2). Consequently, the approach with the developed electrocatalyst has the ability to reduce the energy consumption by 59.22%, which can make rigorous, economically viable H-2 production driven by solar energy.
Keywords: energy-economic; H-2 production; H2S electrolysis; heterostructure; solidsulfur

Engineered silk matrix as a substitute for acellular dermal matrix in breast reconstruction surgery - Deshpande, Rucha; Shukla, Swati; Kale, Amod; Sayyad, Raeesa; Kewale, Bhawana; Deshmukh, Narendra; Nisal, Anuya; Venugopalan, Premnath (International Journal of Biological Macromolecules, 2025)
Implant-based breast reconstruction is a common standard of care for breast cancer patients following mastectomy. To support implant weight and placement, surgeons utilize autologous tissues, acellular dermal matrices (ADMs), or synthetic meshes. While ADMs provide structural support, they present significant risks, including infection transmission and seroma. Conversely, synthetic meshes exhibit poor cellular adhesion, leading to inadequate tissue integration. To address these challenges, there is a need for a matrix that enhances tissue integration while minimizing infection risks and other complications. Silk fibroin (SF), a natural biopolymer, possesses excellent biocompatibility and mechanical properties. This study introduces a novel engineered silk matrix (ESM) as an advanced solution for soft tissue regeneration, specifically in breast reconstruction surgery. The present study establishes the safety of ESM and evaluates its potential a tissue regeneration matrix through extensive in-vitro and in-vivo analyses. In-vitro assays demonstrated superior cellular adhesion, proliferation of human mammary fibroblast cells (HMFCs), collagen deposition and angiogenesis in ESM compared to collagen matrices and ADMs. Safety assessments, conducted in accordance with ISO 10993 guidelines, confirmed noncytotoxic nature of ESM. Furthermore, subcutaneous implantation revealed no systemic toxicity or adverse tissue reactions. In-vivo studies utilizing a Yorkshire pig model of simulated breast reconstruction surgery, demonstrated superior performance of ESM over collagen matrices in tissue regeneration. The findings showed enhanced fibroblast density, increased collagen deposition, and improved vascularization. These results suggest that ESM is a safer and more effective alternative to ADMs in breast reconstruction, with the potential to revolutionize post-mastectomy care for breast cancer patients.
Keywords: Biocompatibility; Breast reconstruction; ISO 10993; Polymer; Safety; Silk protein; tissue regeneration

Engineered silk-dressing for acceleratedwound healing: biocompatibility and efficacy studies - Deshpande, Rucha; Pillai, Lakshmi R.; Sayyad, Raeesa; Shukla, Swati; Nisal, Anuya; Venugopalan, Premnath (Macromolecular Bioscience, 2025)
Advanced wound care dressings are essential for improving clinical outcomes. The present study investigates the wound management potential of a unique dressing fabricated from silk proteins. The dressing was characterized for its physical and structural properties, including surface texture, porosity, fluid absorption capacity, and moisture vapor transmission rate. These parameters have been found to be critical for optimal wound healing. In vivo full thickness wound healing studies in a rat model validated the efficacy of the Silk-dressing compared to conventional cotton gauze and commercial polyurethane foam dressings. Histopathological analysis confirmed improved re-epithelialization, collagen deposition, angiogenesis, and formation of secondary follicles. Key advantages of Silk-dressing included non-adherence, absorption of exudate, maintenance of optimal moisture at wound site and acceleratedwound closure. Biocompatibility studies were also conducted in accordance with ISO 10993 guidelines, demonstrating no cytotoxicity, irritation, sensitization, or pyrogenicity. These findings highlight the potential of this uniquely designed Silk-dressing as a superior alternative for wound management, with a potential to improve clinical outcomes.
Keywords: Biocompatibility; biopolymer; ISO 10993; Silk protein; wound Healing

Engineering luminescent carbon dot emission through surface state functional group via heteroatom doping and unveiling the effect of solvents - Devi, Suman; Luwang, Meitram Niraj (Langmuir, 2025)
This work comprehends the synthesis of carbon dots from papaya leaves (PCD) using water, ethanolamine (EA), and dimethylformamide (DMF). Ethylenediamine (EDA) was used to introduce nitrogen doping. Water-based PCDs emit blue light, while those in EA and DMF emit red light due to increased oxidation. In EA or DMF with EDA, red emission quenches, and enhanced blue emission is observed, which infers reduced oxidation. This indicates that EDA shifted the emission back to the blue. These findings were confirmed by hypothetical mechanistic studies, Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The Raman spectrum revealed defect-activated D and G bands; defects increase in pure solvents compared to water but decreases in mixed solvents such as EA + EDA and DMF + EDA. In XPS, C-O bonds were detected at a higher level in EA and DMF, whereas C-N bonds were observed at a higher level in EDA. TEM images showed that the synthesized PCDs ranged from 1 to 5 nm, with interplanar spacing values consistent with X-ray diffraction (XRD) analysis. PCDs synthesized from a sustainable carbon source exhibit tunable fluorescence from blue to red and vice versa based on solvents used during the engineering of surface state functional group. This makes them promising candidates for fluorescent security inks.

Enhanced electrocatalytic performances of NiCr layered double hydroxides by oxalate intercalation in anion exchange membrane water electrolysis - Pal, Santanu; Sinha, Nibedita; Das, Chandni; Chauhan, Inderjeet; Ahmed, Tanbir; Roy, Poulomi (ACS Applied Materials & Interfaces, 2025)
Layered double hydroxides (LDHs) have attracted much attention these days in the field of water electrolysis due to easy modulation in their layered structure and properties. Herein, NiCr-LDH has been developed, and its interlayer spacing has been considerably increased by oxalate intercalation. Such increased interlayer spacing allows easy access of hydroxides to a large number of electroactive sites and thereby boosts the electrocatalytic performances both for oxygen and hydrogen evolution reactions. Being very active toward both the electrocatalytic reactions, the oxalate-intercalated NiCr-LDH was further explored in an alkaline anion exchange membrane water electrolyzer (AEMWE), achieving 800 mA cm-2 at 1.88 V cell voltage at an operating temperature of 60 degrees C. In fact, the electrolyzer efficiency has been determined to be as high as 69.66%, and the calculated H2 production cost was found to be \$0.97 per gasoline-gallon equivalent, which is well below the targeted cost by the Department of Energy, USA. The electrocatalyst was also examined in harsh alkaline media, like highly saline or seawater, which also indicated its ability to carry out sustainable seawater electrolysis, restricting chlorides to a great extent. Interestingly, post-electrolysis characterization reveals the fact that oxalate decomposition aided carbonate formation within interlayers of NiCr-LDH, and high affinity toward hydroxides is responsible for restricting chlorides during the electrolysis process, apart from the great electrocatalytic activity.
Keywords: Anion exchange; hydrogen production; interlayerspacing; Layered double hydroxide; Sustainable; water electrolyzer

Enhanced light-matter interaction in gas nitridation-derived TiNx thin films for potential plasmonic applications - Tony, Liya; Selvam, I. Packia; Vinod, C. P.; Potty, S. N. (Journal of Materials Science, 2025)
Titanium nitride is a substitute material exhibiting improved opto-electrical characteristics suitable for plasmonic purposes with adjustable attributes. In this study, we have embraced an innovative methodology for the fabrication of titanium nitride thin coatings via the nitridation of RF magnetron-sputtered titanium metallic films for surface plasmon resonance utilisation. The augmented electrical and optical features of TiN thin coatings prepared through the nitridation procedure are reported for the first time. The metallic coatings underwent gas nitridation at diverse temperatures within the range of 450-600 degrees C. The titanium nitride phase evolution in the coatings was corroborated by x-ray diffraction and x-ray photoelectron spectroscopy examinations. The dielectric function is deduced from reflection spectra through Drude-Lorentz model fitting, and the manifestation of surface plasmon excitation in the visible region was confirmed by correlating with carrier concentration assessments and by ensuring the required negative permittivity in the region. The red shift of screened plasma wavelength was observed with the nitridation temperature, and the same is varied in the wavelength range 400-700 nm. Ultimately, surface plasmons were excited in coatings with optimised thickness using Kretschmann configuration in wavelength interrogation mode.

Enhanced mid-visible light absorption and long-lived charge carriers in an electronically and structurally integrated BiVO4-TiO2 photoanode for efficient artificial photosynthesis applications - Jha, Vikas Kumar; Salgaonkar, Kranti N.; Saha, Avishek; Gopinath, Chinnakonda S.; Iyer, E. Siva Subramaniam (Nanoscale, 2025)
The ever-increasing demand for sustainable solutions for eliminating environmental pollutants, solar energy harvesting, water splitting, etc. have led to the design and development of novel materials to achieve the desired result. In this regard, structurally and electronically integrated (SEI) BiVO4-TiO2 (SEI-BVT) with abundant heterojunctions has emerged as a promising entity for efficient charge separation, which in turn enhances artificial photosynthesis (APS) activity. The present work adopted a unique synthetic strategy using SILAR to fabricate SEI-BVT from ionic precursors (Bi3+ and VO43-) into the pores of TiO2, exhibiting benchmark APS efficiency compared to the individual components. This preparation results in approximately 180 trillion uniformly distributed heterojunctions in 1 mg cm-2 of the SEI-BVT photoanode material. Charge carriers in SEI-BVT and BiVO4 are similar; however, the recombination is highly hindered when SEI-BVT heterojunctions are formed in the former. Our earlier work demonstrated 31-38% solar-to-fuel efficiency (STFE) with BiVO4-TiO2 for APS in the presence of the Pd-nanocube co-catalyst. The emphasis of the current work is to explore the dynamics of the light-induced processes in these heterojunctions to understand the interfacial charge transfer process. Femtosecond transient absorption (TA) spectroscopy has been employed to monitor the excited state dynamics. Our results show that new trap states have evolved under light illumination, which are significantly long-lived and hinder charge recombination, and consequently enhance STFE. A significantly large number of charge carriers exhibit a lifetime of >> 6 ns with visible light photons, at least up to 720 nm, which is higher than the band-gap absorption onset at 490 nm for SEI-BVT compared to bulk BiVO4. The rate of formation of charge carriers is significantly affected in the heterojunctions.

Enhanced oxygen electrocatalysis in zinc-air batteries via a bifunctional bimetallic organic framework - Shivade, Rajkiran D.; Pandey, Priyanshi; Shelke, Manjusha V. (Journal of Power Sources, 2025)
An efficient bifunctional oxygen electrocatalyst, a nickel-iron metal organic framework (NF-MOF) grown within three-dimensional (3D) nitrogen doped porous carbon (NPC) collectively referred as NF-MOF@NPC, is developed as high performance electrocatalyst for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The synergistic effect of bimetallic active sites coupled with conductive nitrogen doped porous carbon matrix, provides chemical stability, abundant active sites, enhanced electron transfer, and improve catalytic activity. NFMOF@NPC exhibits OER onset potential of 1.60 V at current density of 10 mA cm- 2 with Tafel slope of 126 mV dec- 1 and ORR half wave potential of 0.81 V with electron transfer number of 3.91. A zinc-air battery fabricated using NF-MOF@NPC shows peak power density of 102 mW cm-2 and specific capacity of 741 mAh g-Z 1n. It also exhibits remarkable cycling stability for 120 h at current density of 10 mA cm- 2 highlighting its promise as alternative for conventional platinum on carbon (Pt/C) and ruthenium dioxide (RuO2) electrocatalysts demonstrating its potential for next generation energy storage devices.
Keywords: Bifunctional Electrocatalyst; Rotating disk electrode; zinc-air battery

Enhanced Production and Techno-Economic Analysis of Sustainable Biofuel Production via Continuous Hydrogenation of Furfural Using the Cu-ZnO-Al2O3 Catalyst - Saha, Biswajit; Racha, Arundhathi; Chaudhary, Puneet Kumar; Singh, Brijesh Kumar; Samanta, Chanchal; Newalkar, Bharat L. (ACS Sustainable Chemistry & Engineering, 2025)
2-Methylfuran is a perfect green solution on the pathway of finding alternative fuels. We report here for the first time the continuous production of 2-methylfuran (2-MF), a sustainable biofuel from biomass-derived furfural (FFA), over an industrial Cu-ZnO-Al2O3 (CZA) catalyst. The modified coprecipitation method provides a uniformly dispersed crystalline structure to the synthesized catalysts, along with intended copper (Cu) loading achievement. Different Cu loadings affect the catalytic behavior and activity. Hence, CZA catalysts with two Cu loadings of 9.8 and 4.7% were studied in detail, denoted as C1 and C2, respectively. The catalysts were characterized via XRD, N-2 adsorption, H-2-TPR, NH3-TPD, XPS, ICP-MS, and TEM. Remarkably, the prepared catalysts demonstrate balanced acid sites with mesopores, a high surface area and pore volume, and better controlled nanoparticle size promoting catalytic activity. TEM and H-2-TPR studies reveal a better Cu dispersion. Existence of Cu2+ and Cu (+) even after reduction by XPS study proves the efficiency of the synthesized catalysts. Furthermore, TGA indicates the stability of CZA catalysts. To understand catalytic activity and selectivity, the investigation was carried out in a packed-bed fixed-bed stainless steel reactor. Better physiochemical properties result in high FFA conversion of 33.8% and selectivity of 99.6% for 2-MF. No side products were formed during reaction otherwise improbable via the continuous method. Compared with available literature, the CZA catalyst was found to exhibit superior catalytic performance. The reaction kinetics of furfural hydrogenation to 2-methylfuran was investigated, and it was found that the reaction order is high, and the activation energy was 61.2 kJ/mol. The rate constant k clearly obeyed the Arrhenius law from 180 to 220 degrees C. In addition, evaluation of reaction kinetics also indicated the absence of ring hydrogenation and decarbonylation products, which is difficult to achieve. Finally, the process shows significant economic viability, which resulted in the minimum levelized production cost for 2-methylfuran of 173,068.16 \$/ton with 78.32% overall energy efficiency.
Keywords: 2-methylfuran (2-MF); continuous production; Cu-ZnO-Al2O3; economic viability; furfural; green synthesis

Enhanced stability of sodium metal anodes in covalent triazine frameworks via progressive nucleation with optimized conducting composite matrix - Wasnik, Kundan; Bhatt, Rajesh C.; Shelke, Manjusha V. (Small, 2025)
Organic materials offer exciting possibilities to improve rechargeable battery performance in multiple ways. This study explores the Covalent Triazine Framework (CTF) as an interlayer to modulate progressive sodium nucleation and subsequent recurrent deposition/extraction in an anode-less sodium battery. The optimized composite, C60R40, which combines CTF with reduced graphene oxide (rGO), has demonstrated its effectiveness as a host. In half cell Na electrodeposition, the C60R40 host exhibits 99.9% coulombic efficiency at an applied current density and areal capacity of 6 mA cm-2 and 2 mAh cm-2, respectively, for 500 cycles. The stable performance is also observed in both full-cell and anode-less battery configurations. When paired with Na3V2(PO4)2F3, the sodium-plated C60R40 demonstrated a stable discharge capacity of 110 mAh g-1. Furthermore, the anode-less sodium battery configuration, with Na3V2(PO4)3 cathode, achieved a promising discharge capacity exceeding 50 mAh g-1 without any additional modifications. These findings highlight the significant role of organic materials in improving the performance of rechargeable sodium metal batteries.
Keywords: anode-less batteries; CTF; instantaneous and progressive nucleation; Nucleation and growth; SEI

Enhancement of mechanical and rheological properties of PA-12 through silane modification - Jadhav, V. Pravin; Mahajan, Digvijay; Patil, Prashant; Umbarkar, Shubhangi B.; Pol, Harshawardhan (Bulletin of Materials Science, 2025)
This research examines the effects of silane modifications on polyamide 12 (PA-12) to improve its mechanical and thermal properties. The study employs a reactive extrusion technique to integrate various silanes-Dynasylan (R) AMEO, Dynasylan (R) 1189, Dynasylan (R) DAMO and Dynasylan (R) VPS 4721-at different concentrations (0.25, 0.5 and 0.75%). Key findings reveal that silane modifications significantly enhance the tensile strength, impact resistance and viscoelastic behaviour of PA-12, with the Dynasylan (R) DAMO formulation achieving the highest tensile strength of 38.25 MPa vis-& agrave;-vis 8.02 MPa for PA-12. The modifications also resulted in a reduction of crystallinity by over 35%, contributing to improved toughness and impact strength. Rheological assessments indicate that the flow properties of PA-12 are positively altered, enhancing its complex viscosity and storage modulus, which are crucial for applications in automotive and aerospace industries. Thermal analysis through differential scanning calorimetry and thermogravimetric analysis confirms improved thermal stability, particularly in the 0.5% Dynasylan (R) AMEO-modified sample, exhibiting an onset temperature of 421.87 degrees C. The study emphasizes the importance of the silane type and dosage in tailoring PA-12's performance for advanced applications, suggesting future research directions to further refine silane-modification techniques for enhanced polymer performance. This research provides valuable insights into polymer-modification strategies, highlighting the potential for silane treatments to optimize the mechanical, thermal and rheological properties of PA-12 for diverse industrial applications.
Keywords: mechanical properties; Polyamide 12 (PA-12); reactive extrusion; rheological behaviour; silane modification; thermal stability

Enhancing asphalt pavement longevity through microcapsule-encapsulated rejuvenators: mechanical performance and self-healing evaluation - Gowda, Sachin; Behl, Ambika; Shanmuganathan, Kadhiravan; Gupta, Aakash (International Journal of Pavement Research and Technology, 2025)
Self-healing asphalt incorporating encapsulated rejuvenators presents a promising solution to extend pavement life by autonomously restoring binder functionality in aged or cracked regions. Calcium-alginate microcapsules encapsulating a commercially available bio-based rejuvenator available in the Indian market were synthesized (2–3 mm in diameter) and incorporated into Bituminous Concrete Grade-II asphalt mixtures at 0%, 0.5% and 1% (by aggregates weight). Capsules showed rupture strength > 18 N and thermal stability up to 200 °C. Microstructural (4D-XRM (X-ray Microscopy), Scanning Electron Microscopy (SEM), Brunauer-Emmett-Teller (BET)), chemical (Fourier Transform Infrared (FTIR), Energy-Dispersive X-ray Spectroscopy (EDAX), SARA) and mechanical (Indirect Tensile Strength (ITS), resilient modulus, dynamic creep, Semi-Circular Bending (SCB) healing) tests under unaged, short-term aged (STA) and long-term aged (LTA) conditions were performed. At 1% dosage, the Healing Index (HI) increased substantially (up to 58.03% for LTA), while volumetric, rutting and moisture resistance were not significantly affected. EDAX and SARA confirm targeted rejuvenator release under aging. These findings show that low dosages of Calcium alginate microcapsules can improve fracture recovery in aged asphalt mixtures without compromising initial performance, supporting their potential for self-healing pavements.

Enzymatic biodegradation of used engine oil using a novel lipase derived from renewable feedstocks - Tracy, Preetanshika; Dasgupta, Diptarka; Ashok, Patel Pratima; More, Snehal; Sarkar, Bipul; Porwal, Jyoti; Tripathi, Deependra (World Journal of Microbiology & Biotechnology, 2025)
This study introduces an eco-friendly enzymatic approach for biodegrading used engine oil, utilizing a novel lipase from the mesophilic yeast strain Pichia Caribbica. The yeast was cultured in detoxified corncob hydrolysate with used cooking oil as an inducer. OVAT study confirmed that the optimal pH and temperature for lipase production by the strain was 7.0 and 25 degrees Celsius, respectively, with lipase activity of 70 IU/mL. The enzyme effectively degraded similar to 46% of used engine oil over a period of 15 days. Gas Chromatography-Mass Spectrometry (GC-MS) and FT-IR analysis confirmed a significant reduction in hydrocarbon concentrations and the emergence of new functional groups, confirming the enzyme's ability to degrade complex hydrocarbons into less toxic derivatives. These findings highlight the lipase's potential as an effective biocatalyst for eco-friendly bioremediation of oil-contaminated environments, such as soils and aquatic systems, while also emphasizing its role in environmental management through the reuse of waste by-products in enzyme production, thus reducing the environmental impact of improper waste disposal.
Keywords: Biodegradation; Lipase; PC5703; Used cooking oil; Used engine oil

Enzymatic pathway for kupyaphore degradation in mycobacterium tuberculosis: mechanism of metal homeostasis and turnover - Bhosale, Rashmi S.; Chakraborty, Arnab; Wong, Tsung-Yun; Masal, Dattatraya P.; Choudhury, Rahul; Srivastava, Sonali; Reddy, D. Srinivasa; Aldrich, Courtney C.; Kamat, Siddhesh S.; Mohanty, Debasisa; Gokhale, Rajesh S. (ACS Chemical Biology, 2025)
Metallophores are essential for metal homeostasis, regulating availability, and mediating host-pathogen interactions. Kupyaphores are specialized metallophores produced by Mycobacterium tuberculosis (Mtb) that primarily chelate zinc to support bacterial survival. Elevated kupyaphore levels early in infection highlight their importance, while their rapid decline, despite increasing bacterial loads, indicates tightly regulated mechanisms of production, consumption, and degradation. However, the processes driving kupyaphore catabolism and their role in preventing zinc toxicity in Mtb remain unclear. Here, we show that covalent modification of the isonitrile moiety in kupyaphores releases zinc, triggering degradation through a sequential three-step enzymatic pathway encoded by Mtb. Isonitrile hydratase converts isonitrile groups into formamides, which are subsequently processed into amines by N-substituted formamide deformylase and ultimately oxidized to beta-ketoesters by amine oxidases. The biological significance of this pathway is underscored by the upregulation of these genes under metal-depleted and biofilm-forming conditions. Mutant Mtb strains lacking these genes exhibit impaired growth in metal-limiting environments and reduced levels of biofilm formation. Catalytic intermediates detected in Mtb cultures and infected mouse lung tissues confirm the pathway's in vivo activity. Further, genome mining reveals that similar enzymes are conserved across organisms producing isonitrile-containing metabolites, emphasizing the broader importance of this pathway. Understanding these processes could pave the way for novel therapeutic strategies targeting kupyaphore catabolism.

Essentials of Mo+6/Mo+4 and Ce+4/Ce+3 redox couples in auto-regenerated catalyst for dry methane reforming - Panda, Satyajit; Singh, Gaje; Kaishyop, Jyotishman; Gazi, Md Jahiruddin; Mule, Harshada Mahadev; Khan, Tuhin Suvra; Sharma, Ojasvi; Bordoloi, Ankur (Chemical Engineering Journal, 2025)
Biogas is a potential renewable carbon resource, and dry reforming is one of the promising routes to mitigate via generating syngas, used as a building block for the synthesis of chemicals and fuels. Coke deposition and metal sintering of the reported catalyst systems are the major challenges to developing an economically feasible dry reforming process. Molybdenum oxide is a versatile material with properties like oxygen storage, oxygen mobility, and sulphur tolerance. Here, an oxygen storage capacity enhanced catalyst has been designed by applying a mono layer molybdenum oxide on ceria-magnesia-modified alumina support using a unique chemical vapor deposition method. The Ru and Ni used as active components, and Gd as a promoter were dispersed over the modified support via a precipitation-deposition approach. The most efficient composition is found to be 4 % Ni, 0.5 % Gd, and 0.5 % Ru with Mo-promoted modified alumina with excellent stability up to 500 h for dry reforming reaction studies. Two redox cycles (Mo+6 to Mo+4 & Ce+4 to Ce+3) facilitated a significant number of oxygen vacancies, to limit surface carbon accumulation and support high catalytic stability and activity. The possible reaction pathways and stable surface intermediates were identified by using in-situ DRIFT studies, which included metal carbonyls, carboxylate species, and surface hydroxyl groups. Moreover, the DRIFT studies were supported with CH4-TPSR analysis and DFT studies evidence the formation of CHx species and subsequent oxidation. The additional advantage of the usage of molybdenum is the excellent S-tolerance capacity, which is fully scrutinized experimentally as well as theoretically.
Keywords: and Methane reforming; Coke resistant; Oxygen storage; Redox couple cycles; Sulphur tolerance

Ethyl cellulose-based controlled-release atrazine nanoformulation for effective and long-term weed management in agriculture - Gautam, Tripurari Rao; Vasmatkar, Pashupat; Gundloori, Rathna V. N.; Kadoo, Narendra (Industrial Crops and Products, 2025)
Atrazine (ATZ) is the second most widely used herbicide. However, its widespread use is hazardous to the environment. We developed ethyl cellulose-based nanoformulated atrazine (nfATZ) to achieve slow and sustained release of ATZ for long-term weed control in crops such as maize. Maize or corn is used in several industrial applications, including the production of ethanol, corn syrup, adhesives, textiles, biodegradable plastics, etc. As broadleaf weeds significantly impact maize yields, we evaluated the effects of nfATZ and conventional ATZ on tomato as a representative of broadleaf weeds. Various concentrations of ATZ and nfATZ (1-10 mg per kg of soil) were evaluated in pre-emergence, post-emergence, and re-emergence studies. Several morphological, physiological, and biochemical parameters of weeds were assessed, and the efficacy of the herbicide formulations was evaluated. nfATZ outperformed conventional ATZ even at lower concentrations with prolonged herbicidal effectiveness beyond 30 days, while the main crop remained unaffected. The weed mortality in nfATZ treatment was > 80 %, while it was 35 % - 45 % in ATZ treatment. The chlorophyll and carotenoid contents decreased by similar to 65 % in nfATZ-treated weeds, impacting their photosynthesis and overall health. ATZ and nfATZ also significantly impacted the activities of antioxidant enzymes, such as ascorbate peroxidase (similar to 57 %), superoxide dismutase (similar to 67 %), and peroxidase (similar to 77 %) in weeds. Thus, we conclude that nfATZ performed significantly better than ATZ in controlling weeds over the long term and reducing its environmental impact. Therefore, we propose nfATZ for highly effective and long-term weed control in large-scale production of industrial crops like maize.
Keywords: Controlled-release; Herbicide; Nanoformulation; Oxidative stress; Weed management; Weed mortality

Europium oxide on carbon nitride for electrocatalytic glycerol oxidation coupled with hydrogen evolution reaction - Jana, Jayasmita; Sharma, Tata Sanjay Kanna; Ghanem, Mohamed A.; Choi, Won Mook; Gopinath, Chinnakonda S.; Hur, Seung Hyun (Separation and Purification Technology, 2025)
{The integration of the electrochemical glycerol oxidation reaction (GOR) with the hydrogen evolution reaction (HER) has emerged as a promising alternative to the sluggish oxygen evolution reaction (OER) in water splitting toward the development of renewable and clean energy sources. However, suitable electrodes that facilitate redox kinetics while increasing the selectivity of the desired product(s) are still required. Herein, a series of europium oxide (Eu2O3) anchored on graphitic carbon nitride (g-CN) nanoaggregates (g-CNEux
Keywords: carbon support; electrocatalysis; Glycerol; HER; Rare earth metal

Evaluating sodium-ion pouch cell battery for renewable energy storage under extreme conditions - Shelke, Mehul; Boyer, Jamee M.; Mirzapure, Vinay; Pol, Vilas G. (Communications Chemistry, 2025)
A sodium-ion battery (SIB) is a sustainable energy storage technology based on abundantly available raw materials. It is a commercially viable option because of the processing similarity with Li-ion battery. Most of the energy storage studies focus on the near room temperature performance of different battery chemistries. Herein, we report the ultralow temperature performance of the SIB pouch cell. The cells fabricated using low-temperature compatible components showed significant specific energy values around 96, 74, and 46 Wh kg-1 at room temperature, -25 degrees C, and -50 degrees C, respectively. We demonstrated the battery performance under laboratory conditions as well as under actual windy and snowy environments. Such an exhibition highlights the use case of the SIB pouch cell as an emergency energy storage device in extreme weather conditions. Moreover, charging of SIB cell at -100 degrees C using polycrystalline Si solar cell is also reported, indicating the possibility of deployment for space expeditions.

Evaluating the catalytic potential of Lithium-decorated graphene quantum dots for small molecule activation - Samudre, Nikhil S.; Tiwari, Rukminesh (Chemical Physics, 2025)
The search for effective catalysts in small molecule activation has intensified as industries seek efficient and costeffective solutions. Lithium (Li), known for its unique electronic properties, is of significant interest as a catalyst. However, its specific catalytic potential when anchored on graphene quantum dots (GQDs) has not been fully explored. This study investigates the catalytic potential of lithium (Li) adatoms on GQDs with various edge conformations (zigzag and armchair) and sizes (24 and 42 atoms). Using density functional theory (DFT), we examine the interactions of Li-decorated GQDs with small molecules such as H2, N2, CO, O2, and CO2. Our findings reveal that Li-GQD complexes exhibit optimal catalytic activity for all these molecules, based on binding energy, charge distribution, and bond length changes. The smallest GQD, coronene (24 carbon atoms), shows the most promising catalytic activity, providing experimental leads for synthesizing and testing efficient Li-anchored catalysts.
Keywords: Catalytic activity; Density functional theory; graphene quantum dots; Lithium adatom; small molecule activation

Evaluating the preferential adsorption of N2 from a binary mixture of N2/O2 on extra-framework cations of zeolites: a computational and experimental study - Devasia, George; Nandanwar, Sachin U.; Krishnamurty, Sailaja (Physical Chemistry Chemical Physics, 2025)
Separation of N2 from a N2/O2 gas mixture is critical for various industrial/medical applications. Temperature/pressure swing adsorption is the top-notch industrial technology used for this separation, where zeolites are the materials used for adsorption. Zeolite X/Y with Li+ as an extra-framework cation is the best-known sorbent for N2 gas molecules. However, the present net zero emission scenario has made lithium a critical element, making it imperative to implement its alternative in various other technologies. In this context, the present work is a computational evaluation to identify a cation that can replace Li+ for preferential adsorption of N2 over O2. The DFT study, based on parameters such as selective adsorption energies of N2 over O2 and IR stretching frequencies of the adsorbed N2 and O2 molecules, identifies Mg2+, Ca2+, Sr2+, Co2+ and Zn2+ as potential cations. These cations have preferential adsorption for N2 over O2 by 10 kJ mol-1 or more. However, BOMD simulations reveal that only Mg2+, Ca2+, Co2+ and Zn2+ keep the N2 molecule bound at 300 K and the O2 molecule gets desorbed from these frameworks. The desorption temperature of N2 on Ca2+ and Zn2+ is 350 K and on Mg2+ is 400 K. These observations are corroborated by electronic charges on cations and molecular orbitals. Significantly, Ca2+ is identified to adsorb up to 2 N2 molecules, making it an ideal candidate for N2/O2 separation in place of Li+. To validate this, we have carried out an experimental study that showed a good N2 adsorption capacity of 2.1 mmol g-1 for Ca2+.

Evaluation of reaction kinetics for chemoselective hydrogenation of citral for intensification of citral intermediates using copper-based catalysts - Debtirtha, Banik; Kinage, Anil K.; Vasireddy, Satyam Naidu (Indian Chemical Engineer, 2025)
Citral intermediates’ formation kinetics is studied using non-noble metal catalyst (Cu/SiO2) to evaluate catalyst performance characteristics via chemoselective hydrogenation of citral. The catalyst is synthesised by the precipitation method and characterised using XRD, FESEM and BET surface area analyser. Hydrogenation experiments are carried out using an Autoclave reactor in the temperature range of 80–120°C, pressure range of 10–50 bar and for catalyst loadings of 0.5, 1 and 1.5 g. The intermediates product distribution comprises aldehyde and alcohol formation such as citronellal, nerol and citronellol formation. The performance of the Cu/SiO2 catalyst is evaluated using the parameters such as citral conversion, citronellol selectivity and yield as 96.96%, 95.30% and 92.30%, respectively under optimal conditions of 50 bar, 120°C and 1 g catalyst for the reaction time of 100 min. The absence of internal and external mass transfer limitations is verified using the Carberry number and Weisz-Prater modulus criterion. The intrinsic kinetics of the gas–liquid phase hydrogenation of citral is determined using the Langmuir–Hinshelwood-Hougen-Watson (LHHW) model for citral intermediates formation. The reaction kinetic parameters show that citronellol formation favours by the nerol route compared to citronellal conversion.

Expanding the Egbenema horizon: Novel species discovery in India and first complete genome assembly of the genus - Bhagat, Jayesh M.; Khilari, Ajinkya A.; Shanmugam, Dhanasekaran; Patankar, Meena (Algal Research-Biomass Biofuels and Bioproducts, 2025)
The recognition of Egbenema bharatensis, a novel species of cyanobacteria from the Northern Western Ghats, extends the ecological and phylogenetic understanding of the genus Egbenema and highlights terrestrial microbial diversity of the region. Morphological characterization revealed resemblance with other Egbenema species but was inconclusive for definitive taxonomic classification. Preliminary phylogenetic analysis based on 16S rRNA gene sequences indicated affiliation with the genus but showed less than 98 % similarity to known species, pointing toward taxonomic distinctiveness. Analysis of the 16S-ITS region further supported this differentiation, revealing unique secondary structural features. Based on these findings, we propose the isolate as a novel species within Egbenema. Whole-genome sequencing provided full resolution and functional genome annotation revealed nitrogen fixation, cobalamin biosynthesis, and stress tolerance pathways, suggesting its metabolic versatility and potential biotechnological applications. The presence of multiple toxin-antitoxin systems also reflects its adaptability to environmental fluctuation. This study also presents the first complete genome of the genus Egbenema, filling a significant gap in cyanobacterial genomic resources. These findings encourage integrative taxonomic practices and affirm the significance of exploring biodiversity hotspots for uncovering cryptic microbial diversity with ecological and industrial potential.
Keywords: 16S rRNA; Biodiversity hotspots; Cyanobacteria; Egbenema bharatensis; ITS secondary structure; Northern Western Ghats; whole-genome sequencing

Experimental investigation and lumped kinetic modeling studies for upcycling of polyolefins - Kavade, Omkar G.; Dhepe, Paresh L.; Devi, Nandini R.; Vasireddy, Satyam Naidu (Journal of the Indian Chemical Society, 2025)
The present work discusses on comparative kinetic analysis of the pyrolysis of polypropylene (PP), high-density polyethylene (HDPE), and low-density polyethylene (LDPE) using sophisticated lumped models. Unlike many previous studies that focused on single-polymer kinetic models or employed simplified reaction schemes, this study develops an enhanced multistep reaction network that explicitly considers both primary decomposition and secondary cracking pathways, thereby improving the accuracy of product distribution predictions. By integrating this detailed reaction framework with a robust nonlinear regression approach using LSQNONLIN and ODE45 solvers in MATLAB, the study achieved greater accuracy in estimating kinetic parameters than traditional curve-fitting methods. The findings reveal that HDPE exhibits the highest activation energy (222.97 kJ mol(-1)), indicating it is more thermally stable than LDPE (193.44 kJ mol(-1)) and PP (62.16 kJ mol(-1)). One of the highlights of the present work is that lower pyrolysis temperature (400 degrees C) is found to be optimum for liquid yield by reducing secondary cracking, which aligns with the sustainable fuel production principles. The study also emphasizes on the limitations of previous lumped models that overlooked wax decomposition pathways, which are crucial for optimizing the hydrocarbon distribution. Future research should investigate catalytic interventions and reactor design modifications to enhance the product selectivity and scalability. This study offers a more comprehensive kinetic framework for advancing the valorization of plastic waste through pyrolysis, aiding the development of efficient waste-to-fuel conversion strategies.
Keywords: Lumped kinetic modeling; Plastic pyrolysis; Rate constants; Reaction pathways; Secondary cracking reactions; Temperature-dependent product distributions

Exploring FeSe2 and porous carbon composite as a cost-effective host for Al3+ in aqueous Aluminum ion batteries - Mirzapure, Vinay; Patrike, Apurva; Shelke, V, Manjusha (Electrochimica Acta, 2025)
Aluminum is a high-energy-density material with low cost, making rechargeable aluminum ion batteries (AIBs) a attractive alternative to alkali metal ion batteries. However, the practical development of aqueous AIBs is hindered by limited electrode. Herein, we report FeSe2-decorated porous nitrogen and sulfur-doped carbon spheres (FSPNSCS) as a cathode material for aqueous AIBs, with an emphasis on the reaction kinetics and electrochemical performance. FSPNSCS is synthesized through a hydrothermal approach, confirmed by comprehensive characterizations using X-ray Diffraction for crystalline structure validation and Scanning Electron Microscopy for analyzing composite morphology. Electrochemical properties and kinetics are probed using cyclic voltammetry and galvanostatic charge-discharge tests. Ex-situ XRD reveals a notable peak shift towards higher 2 theta values during discharge, indicating lattice contraction due to Al3+ insertion. Sulfur and nitrogen doping impart elasticity to the lattice structure, enhancing stability during cycling. Ex-situ XPS confirms Al3+ storage and minimal oxide formation, as further supported by microscopic elemental mapping with HRTEM. The FSPNSCS cathode achieves a reversible capacity of 60 mAh g- 1 at a current density of 200 mA g- 1. The system exhibits outstanding cycling stability, retaining over 90 % of its capacity at 500 mA g- 1 over 1000 cycles, highlighting its potential to advance aqueous AIBs for sustainable energy storage.
Keywords: Aqueous aluminum ion battery; cathode material; Electrochemistry; Transition metal selenide

Exploring the electronic modulation in controlling the activity and selectivity of Ni-Au-In based catalyst in atmospheric pressure CO2 hydrogenation - Bajpai, Jyotsna P.; Gupta, Sharad; Goud, Devender; Deka, Diku Raj; V. Jagtap, Anuradha; Kumar, Pawan; Ahamed, Momin; Peter, Sebastian C.; Vinod, C. P. (Chemical Engineering Journal, 2025)
Nickel-based catalysts are widely used for the hydrogenation of CO2 but encounter stability challenges during prolonged reactions and at elevated temperatures. At atmospheric pressure, nickel primarily promotes methane formation in CO2 hydrogenation reactions. In this work, we demonstrate that the stability and activity of nickel can be significantly enhanced through gold (Au) modification. Furthermore, we achieve a near-complete selectivity switch from methane to CO by incorporating indium (In), mediated through the formation of Au-In alloy. This catalyst exhibits excellent CO2 conversion and CO selectivity at relatively lower temperatures (400 degrees C), addressing a major bottleneck in the Reverse Water-Gas Shifts (RWGS) reaction. XPS studies demonstrate an interesting electron transfer mechanism facilitated by gold, which involves the formation of electronrich Au species (Au delta-) and the development of Au-In alloys. This process improves the reducibility of nickel oxide while allowing a fraction of nickel to remain in its metallic form, managing a facile hydrogenation process and regulating the shift in selectivity from CH4 to CO.
Keywords: Alloy formation; Bimetallic catalyst; CO2 hydrogenation; RWGS; Selectivity switch; synergy; Trimetallic catalyst; XPS (X-ray photoelectron spectroscopy)

Exploring the structural and photophysical properties of tri-cation mixed halide double perovskites (Cs2AgIn0.85-XCeXBi0.15Cl6) for high-performance phosphor-based WLEDs - Ravi, Nalini; Kanapathi, Prakash; Mohan, Subramaniam; Appadurai, Tamilselvan (Dalton Transactions, 2025)
Owing to their superior optoelectronic properties, lead-free halide double perovskites (HDPs) have been extensively studied for a wide range of optoelectronic applications, especially for fabricating white light-emitting diodes (WLEDs). Considering white light emission, the HDP structure's dual octahedral configuration facilitates greater lattice distortion, thereby fostering strong electron-phonon coupling-derived self-trapped exciton (STE) emission upon photoexcitation. Herein, we propose facile fabrication of a highly feasible phosphor-converted white light LED and an intensive analysis of the structural, compositional and photophysical properties of a tri-cation mixed halide double perovskite. We chose Cs2AgIn0.85Bi0.15Cl6 as a potential candidate for electroluminescent-based white light LED devices as its composition exhibits high stability, direct-allowed transition, and a notable photoluminescence quantum yield. However, we incorporated a lanthanide ion (Ce3+) into this cubic HDP structure via tri-cation mixing at the B `' site (Cs2AgIn0.85-XCeXBi0.15Cl6) to internally disturb structural periodicity and further enhance STE emission. Initially, powder XRD revealed the lattice expansion induced by Ce3+ incorporation, while XPS and TEM verified the substitution of Ce3+ at the In3+ site. Meanwhile, compositional and optical studies established the role of Ce3+ in retaining the direct allowed transition by effectively replacing the In3+ site. Urbach energy (EU), a measure of energetic disorderness at band edges, was found to be significantly reduced, showing a value of 135 meV for the Ce-5% sample. Most significantly, PL emission studies revealed an appreciable enhancement in the PL intensity with a prolonged STE lifetime of 670 ns for Cs2AgIn0.80Ce0.05Bi0.15Cl6, indicating improved radiative recombination. Besides, excitation-dependent Pl and PLE studies revealed that the emission solely came from the STE states. Elaboratively, vibrational studies elucidated that the Ce-5% sample exhibited a restabilized elpasolite structure and enhanced lattice phonons, which ultimately helped in boosting STE emission, as proven by the Huang-Rhys factor (S = 13). Finally, an efficient and durable phosphor-converted WLED was fabricated, and its performance was assessed, revealing CIE coordinates of (0.35,0.32), a CCT of 4368 K, and an extremely high CRI (Ra) of 92. Thus, our work provides an exclusive strategy to enhance the STE emission for potential application in electroluminescent-based WLED devices.

Extraction of highly crystalline and thermally stable cellulose nanofiber from Heliconia psittacorum L.f. leaves - Paul, Sharon; Joseph, Anto; Hridhya, P. D.; Badawi, Michael; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Asrofi, Mochamad; Dominic, C. D. Midhun (International Journal of Biological Macromolecules, 2025)
Extracting cellulose nanofibers (CNF) from agro-waste is one of the promising and practical ways to develop sustainable nanocomposites. In this study, cellulose nanofibers were extracted from the leaves of Heliconia psittacorum for the first time. The combination of oxalic acid hydrolysis (5 wt%) and steam explosion was used for the isolation of CNF from the leaves of Heliconia psittacorum. The structural and chemical features of the prepared CNF were analyzed using various techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Solid state 13C Nuclear Magnetic Resonance Spectroscopy (13C NMR), Scanning Electron Microscopy (SEM), Energy Dispersive X ray analysis (EDX), Transmission electron Microscopy (TEM), X-Ray Diffraction (XRD) and Thermogravimetric analysis (TGA). TEM micrographs reported 15 to 40 nm diameter for the nanofibers synthesized. XRD analysis reported 91 % crystallinity index for CNF, whereas that of the untreated sample was 76 %. The maximum degradation of the CNF is reported at 355 degrees C, exceeds the untreated sample (316 degrees C). The tensile strength of the CNF derived paper was found to be 23 MPa. The recovered nanocellulose can be further utilized for various applications such as the automobile industry for developing lightweight parts, biosensors, super capacitors, absorption of greenhouse gases, wastewater treatment, and packaging applications.
Keywords: biomass valorization; Nanocellulose; Waste to resource

Effect of shape on cellular uptake of visible-light- and redox-responsive biodegradable linear-dendritic block copolymer micelles - Avhad, Shankarrao V.; Ambade, Ashootosh V. (Biomacromolecules, 2026)
Linear-dendritic block copolymers comprising poly(epsilon-caprolactone) attached to hydrophilic 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) ester dendron via a disulfide and containing a defined number of pendent visible-light-responsive donor-acceptor Stenhouse adduct (DASA) groups are synthesized using click chemistry and postpolymerization modification. Self-assembly in aqueous solution selectively affords rice grain-like ellipsoidal, rod-like, and spherical micelles, governed by the number of DASA groups. Progressive disassembly of the micelles is observed during photoswitching cycles. Release of camptothecin depends on the DASA content under light irradiation and is enhanced by the synergistic effect of two stimuli. Cellular uptake quantified by FACS analysis is demonstrated to be influenced by the shape of the micelles, with ellipsoidal micelles exhibiting higher efficiency than spherical micelles by following clathrin- and caveolae-mediated endocytosis as major pathways for internalization. Both types of micelles were found to maintain the particle size in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum at 37 degrees C. Doxorubicin (DOX)-loaded ellipsoidal micelles under photoirradiation show significantly higher apoptosis than free DOX.

Effect of sulfonation density on acid strength in ion exchange resins: Insights from solid-state NMR and density functional theory - Tumulu, Goutam Narayan; Datar, Sarvesh; Shelke, Ankita; Swain, Gitanjali; Ajithkumar, T. G.; Thirumalaiswamy, Raja; Mohan, Ojus; Mahajani, Sanjay M. (Molecular Catalysis, 2026)
Ion-exchange (IE) resins are widely used as solid acid catalysts; however, their surface acidity remains poorly characterized because their limited thermal stability precludes conventional NH3-based acidity measurements. Moreover, acid-site accessibility in IE resins is strongly governed by solvent- or reactant-induced swelling. Here, we investigate the surface acidity of commercial Amberlyst and Indion IE resins using & sup3;& sup1;P MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance), employing TMPO as a molecular probe dispersed on the resin with moderately swelling dichloromethane, thereby capturing the swollen-state acidity relevant for predicting catalytic activity. The deconvolution of the P-31 MAS NMR spectra reveals three distinct acid-strength zones arising from inhomogeneous sulfonation of the polymer matrix. The overall acidity, quantified by the area-weighted average P-31 chemical shift (delta), increases monotonically with sulfonation density. Notably, only resins containing acid sites stronger than similar to 80 ppm exhibited measurable catalytic activity in alpha-pinene isomerization, establishing a direct correlation between acidity and activity. Density functional theory (DFT) calculations on representative resin models, supported by electron-density analyses, attribute the enhancement of acid strength at higher sulfonation densities to cooperative hydrogen-bonding networks among neighboring sulfonic acid groups. Together, these findings establish P-31 MAS NMR-derived surface acidity as a catalytically relevant descriptor for the rational selection of IE resins in liquid phase acid-catalyzed chemistries.
Keywords: Acid strength; Density functional theory; heterogeneous catalysis; Ion-exchange resins; Solid acids; Solid-state NMR

Elucidating the potential of novel class biphenyl-phenyl acetate, IDD-AN-A1, an inhibitor targeting Isocitrate Lyase in Mycobacterium tuberculosis: a target to lead approach - Negi, Anjali; Perveen, Summaya; Kour, Harpreet; Sawant, Sanghapal D.; Sharma, Rashmi (Bioorganic Chemistry, 2026)
Isocitrate lyase (ICL), a pivotal enzyme of the glyoxylate shunt pathway in Mycobacterium tuberculosis (Mtb), represents an attractive target for the development of new anti-tuberculosis (TB) therapeutics. In this study, we identified 2-methoxy-4-((nitrosooxy)methyl)phenyl 2-(2-fluoro-[1,1 `-biphenyl]-4-yl)propanoate (IDDAN-A1) as a potent inhibitor of Mtb ICL. The compound exhibited strong activity against Mtb, with a minimum inhibitory concentration of 6.25 mu g/mL, and demonstrated potent inhibition in enzyme-based assays targeting ICL. Molecular docking studies further supported Mtb ICL as the potential molecular target of this compound. Cytotoxicity and hemolytic assays revealed a favorable safety profile for the compound with selectivity index >10. In combination studies, it exhibited additive and synergistic activity with the frontline drug Rifampicin and Delamanid respectively. Additionally, ex vivo assays simulating the intracellular environment of the pathogen demonstrated strong inhibitory potency. In vitro inhibition studies further confirmed the bacteriostatic nature of the compound across different concentrations. Collectively, these findings demonstrate that this molecule possesses promising anti-tuberculosis activity by targeting the ICL enzyme in Mtb.
Keywords: Anti-tuberculosis activity; Ex vivo; Isocitrate lyase; tuberculosis

Enhanced electrochemical performance of flexible polymer supercapacitors through optimization of organic acid-doping, carbon nanomaterials, and fabrication techniques - Parul; Lakshmi, Racherla Bhagya; Utturkar, Vivek; Natu, Varun; Aramanda, Shanmukha Kiran; Ramamurthy, Praveen C.; Kaka, Fiyanshu (Journal of Power Sources, 2026)
The proliferation of portable and wearable electronics necessitates flexible, high-performance energy storage devices. Flexible supercapacitors are poised to meet these demands due to their high power density, flexibility, and durability but scalable fabrication remains challenging due to costly and complex manufacturing methods. This study addresses this issue by implementing scalable, cost-effective spray coating and screen printing techniques to fabricate flexible micro-interdigitated supercapacitors (FMIS) based on Polyaniline (PANI) composites with carbon nanomaterials, using organic acids as crosslinking agents synthesized via hydrogel strategy. The formation of PANI emeraldine salt was verified through X-ray photoelectron spectroscopy, indicating key amine and imine functionalities, while scanning electron microscopy revealed surface morphologies with enhanced active surface areas beneficial for charge storage. Advanced 3D tomography maps porosity distribution and surface area per unit volume, correlating with electroactive areas calculated from the Randles-Sevcik equation. Electrochemical testing via cyclic voltammetry demonstrates an impressive areal capacitance of 173.2 +/- 9.6 mF cm-2 at 10 mV s-1 with Dunn's method distinguishing capacitive from diffusive contributions. Furthermore, EIS measurements highlight lower solution resistance in screen-printed devices, emphasizing the advantages of optimized electrode morphology for efficient charge transport. This study establishes a scalable approach for high-performance flexible supercapacitors, paving the way for next-generation energy storage solutions.
Keywords: Carbon nanomaterials; Coating techniques; Flexible Supercapacitors; PANI composites; X-ray micro-tomography

Enhanced photocatalytic hydrogen evolution in deionized/natural seawater and removal of organic pollutants using the heterostructure of CuO/Cu2O nanoparticles under visible light - Kangutkar, Raju S.; Walko, Priyanka; Nayaka, Girish Praveen; Nigam, Sandeep; Majumder, Chiranjib; Manjanna, Jayappa (Langmuir, 2026)
Water splitting for hydrogen production and reducing water pollution using solar light are part of the Sustainable Development Goals, which require highly active photocatalytic materials. The heterostructures have demonstrated remarkable photocatalytic advantages in visible light. Herein, we report microwave-assisted green synthesis of CuO/Cu2O nanoparticles using Tridax plant leaf extract. The synthesized nanoparticles were characterized by using PXRD, UV-DRS, Raman spectroscopy, XPS, PL, TRPL, FE-SEM, HR-TEM, BET, and photocurrent. The photocatalytic water splitting performance of CuO/Cu2O and CuO was measured under visible light (lambda >= 420 nm) irradiation using methanol as a sacrificial reagent in DI water and natural seawater. The H2 evolution rates in DI water for CuO/Cu2O and CuO are 2043.21 and 970.09 mu mol g-1 h-1 with apparent quantum efficiency (AQE) values of 5.60 and 2.66 %, respectively. In natural seawater, the H2 evolution rates are 2599.29 and 1370.54 mu mol g-1 h-1 with AQE values of 7.12 and 3.75 %, respectively. The rate of H2 evolution slightly increased in natural seawater. Also, the degradation of the methylene blue dye was examined here, and the efficiency of CuO/Cu2O was determined to be 97 % under natural sunlight. Electrocatalytic H2 evolution was also studied here by using linear sweep voltammetry. Tafel slope values for CuO/Cu2O and CuO are 153 and 250 mV dec-1, respectively. The lowest Tafel value of CuO/Cu2O indicates a faster rate of reaction, thereby producing easier charge separation and lowering the electron-hole recombination due to the presence of surface defects, smaller particle size, enhanced crystallinity, and the synergistic effect between Cu2O and CuO.

Exploring the mechanisms of yoga-based cardiac rehabilitation in heart failure via assessment of endothelial function, genomics and arterial health (Yoga-EndOmics): a study protocol - Shetty, Vindya Vasu; Patil, Laxmi Ramchandra; Patil, Satish G.; Aithal, Kiran; Oli, Ajay Kumar; Yenagi, Vijay Aravind; Kaulgud, Ram S.; Dharne, Mahesh; Chandra Sekaran, Ambalam M.; Prabhakaran, Dorairaj (BMJ Open, 2026)
Introduction Heart failure (HF) remains a major global health challenge, particularly in low-resource settings where access to comprehensive cardiac rehabilitation (CR) is limited. Yoga, a culturally contextualised mind-body intervention, holds promise as an adjunctive therapy in CR. The Yoga-EndOmics study aims to evaluate the effects of Yoga-based cardiac rehabilitation (Yoga-CaRe) on gene expression, endothelial function, vascular biomarkers and clinical outcomes in systolic HF, providing mechanistic insights into its potential integration into conventional cardiac rehabilitation.Methods and analysis This is a prospective, randomised, open-label, blinded-endpoint (PROBE) mechanistic trial enrolling 78 patients with HF with reduced ejection fraction (HFrEF). Participants will be randomised in a 1:1 ratio to receive either a structured Yoga-CaRe intervention or enhanced standard care for 3 months. The Yoga-CaRe group will attend 20 supervised sessions with guided home practice involving tailored asanas, pranayama and meditation. Primary outcomes are changes in endothelial-dependent flow-mediated dilation (FMD) and functional exercise capacity at 3 months. Secondary outcomes include changes in arterial compliance and stiffness, circulating biomarkers of endothelial dysfunction, oxidative stress and inflammation, and immediate changes in global gene expression profiles in peripheral blood mononuclear cells following the Yoga-CaRe intervention. Data will be analysed using analysis of covariance (ANCOVA) for between-group comparisons and significant analysis of microarray (SAM) for global gene expression profiles.Ethics and dissemination The study has received ethical clearance from the Institutional Ethics Committee of the SDM College of Medical Sciences and Hospital, India (SDMIEC/2025/1072) and is registered with the Clinical Trials Registry of India. Findings will be disseminated through peer-reviewed journals, scientific conferences and stakeholder engagement platforms to inform future integrative strategies in HF management.Trial registration number CTRI/2023/12/060758
Keywords: DNA Methylation; Genetics; Heart failure; Molecular Biology; Randomized Controlled Trial

Exploring the role of large synthons in the design of bicomponent salts of cimetidine - Khatun, Saheba; Sar, Bandana; Hosmani, Girish Siddanagouda; Mishra, Manish Kumar; Ravi, Punna Rao; Mukherjee, Arijit (Crystal Growth & Design, 2026)
Cimetidine, a popular histamine H2-receptor antagonist, represents a complex structural landscape exhibiting multiple forms. Attempts to synthesize a bicomponent salt with fumaric acid suffered from crystallization challenges in the past, especially toward the growth of anhydrous single crystals. In this work, we address these crystallization challenges by adopting an alternative crystallization approach involving ionic liquids and analyzing the structural landscape with a large synthon-based approach. Two novel forms of cimetidine fumarate were isolated. The structural differences in the forms of cimetidine fumarate were further explored by using different coformers as structural probes.